Absent B cells, agammaglobulinemia, and hypertrophic cardiomyopathy in folliculin-interacting protein 1 deficiency. - Saettini, Francesco; Poli, Cecilia; Vengoechea, Jaime; Bonanomi, Sonia; Orellana, Julio C; Fazio, Grazia; Rodriguez, Fred H; Noguera, Loreani P; Booth, Claire; Jarur-Chamy, Valentina; Shams, Marissa; Iascone, Maria; et al. (Blood, 2021)
Agammaglobulinemia is the most profound primary antibody deficiency that can occur due to an early termination of B-cell development. We here investigated 3 novel patients, including the first known adult, from unrelated families with agammaglobulinemia, recurrent infections, and hypertrophic cardiomyopathy (HCM). Two of them also presented with intermittent or severe chronic neutropenia. We identified homozygous or compound-heterozygous variants in the gene for folliculin interacting protein 1 (FNIP1), leading to loss of the FNIP1 protein. B-cell metabolism, including mitochondrial numbers and activity and phosphatidylinositol 3-kinase/AKT pathway, was impaired. These defects recapitulated the Fnip1-/- animal model. Moreover, we identified either uniparental disomy or copy-number variants (CNVs) in 2 patients, expanding the variant spectrum of this novel inborn error of immunity. The results indicate that FNIP1 deficiency can be caused by complex genetic mechanisms and support the clinical utility of exome sequencing and CNV analysis in patients with broad phenotypes, including agammaglobulinemia and HCM. FNIP1 deficiency is a novel inborn error of immunity characterized by early and severe B-cell development defect, agammaglobulinemia, variable neutropenia, and HCM. Our findings elucidate a functional and relevant role of FNIP1 in B-cell development and metabolism and potentially neutrophil activity.
Keywords: Adult; Agammaglobulinemia; Animals; B-Lymphocytes; Cardiomyopathy, Hypertrophic; Carrier Proteins; Child; Child, Preschool; Chromosomes, Human, Pair 5; Codon, Nonsense; Consanguinity; Crohn Disease; Developmental Disabilities; Disease Models, Animal; Disease Susceptibility; DNA Copy Number Variations; Female; Heart Defects, Congenital; Humans; Immunologic Deficiency Syndromes; Infections; Loss of Function Mutation; Lymphopenia; Male; Mice; Neutropenia; Pedigree; Uniparental Disomy; Whole Exome Sequencing

Association of De Novo Variants With Childhood Onset Moyamoya Disease and Diffuse Occlusive Vasculopathy. - Pinard, Amelie; Fiander, Maximillian D J; Cecchi, Alana C; Rideout, Andrea L; Azouz, Mohamed; Fraser, Stuart M; McNeely, P Daniel; Walling, Simon; Novara, Sarah C; Hurst, Anna C E; Guo, Dongchuan; Parkash, Sandhya; et al. (Neurology, 2021)
OBJECTIVE: To test the hypothesis that de novo genetic variants are responsible for moyamoya disease (MMD) in children with unaffected relatives, we performed exome sequencing of 28 affected children and their unaffected parents. METHODS: Exome sequencing was performed on 28 trios of affected patients with MMD and unaffected parents. RESULTS: We identified 3 novel rare de novo variants, 1 in the RING domain and 2 in a highly conserved region distal to the RING domain (4,114-4,120). These de novo cases of MMD present at a young age with aggressive MMD and uniquely have additional occlusive vascular lesions, including renal artery stenosis. Two previously reported cases had de novo variants in the same limited region and presented young with aggressive MMD, and 1 case had narrowing of the inferior abdominal aorta. CONCLUSIONS: These results indicate a novel syndrome associated with rare variants defined by de novo mutations disrupting highly conserved amino acids in the RING domain and a discrete region distal to the RING domain delimited by amino acids 4,114 to 4,120 leading to onset of severe MMD before 3 years of age and occlusion of other arteries, including the abdominal aorta, renal, iliac, and femoral arteries.
Keywords: Adenosine Triphosphatases; Adult; Age of Onset; Aortic Diseases; Arterial Occlusive Diseases; Child, Preschool; Female; Femoral Artery; Humans; Iliac Artery; Male; Moyamoya Disease; Mutation; Renal Artery Obstruction; Ubiquitin-Protein Ligases

Association of structural variation with cardiometabolic traits in Finns. - Chen, Lei; Abel, Haley J; Das, Indraniel; Larson, David E; Ganel, Liron; Kanchi, Krishna L; Regier, Allison A; Young, Erica P; Kang, Chul Joo; Scott, Alexandra J; Chiang, Colby; Wang, Xinxin; et al. (Am J Hum Genet, 2021)
The contribution of genome structural variation (SV) to quantitative traits associated with cardiometabolic diseases remains largely unknown. Here, we present the results of a study examining genetic association between SVs and cardiometabolic traits in the Finnish population. We used sensitive methods to identify and genotype 129,166 high-confidence SVs from deep whole-genome sequencing (WGS) data of 4,848 individuals. We tested the 64,572 common and low-frequency SVs for association with 116 quantitative traits and tested candidate associations using exome sequencing and array genotype data from an additional 15,205 individuals. We discovered 31 genome-wide significant associations at 15 loci, including 2 loci at which SVs have strong phenotypic effects: (1) a deletion of the ALB promoter that is greatly enriched in the Finnish population and causes decreased serum albumin level in carriers (p = 1.47 × 10) and is also associated with increased levels of total cholesterol (p = 1.22 × 10) and 14 additional cholesterol-related traits, and (2) a multi-allelic copy number variant (CNV) at PDPR that is strongly associated with pyruvate (p = 4.81 × 10) and alanine (p = 6.14 × 10) levels and resides within a structurally complex genomic region that has accumulated many rearrangements over evolutionary time. We also confirmed six previously reported associations, including five led by stronger signals in single nucleotide variants (SNVs) and one linking recurrent HP gene deletion and cholesterol levels (p = 6.24 × 10), which was also found to be strongly associated with increased glycoprotein level (p = 3.53 × 10). Our study confirms that integrating SVs in trait-mapping studies will expand our knowledge of genetic factors underlying disease risk.
Keywords: Alleles; Cardiovascular Diseases; Cholesterol; DNA Copy Number Variations; Female; Finland; Genome, Human; Genomic Structural Variation; Genotype; High-Throughput Nucleotide Sequencing; Humans; Male; Mitochondrial Proteins; Promoter Regions, Genetic; Pyruvate Dehydrogenase (Lipoamide)-Phosphatase; Pyruvic Acid; Serum Albumin, Human

Auto-antibodies to type I IFNs can underlie adverse reactions to yellow fever live attenuated vaccine. - Bastard, Paul; Michailidis, Eleftherios; Hoffmann, Hans-Heinrich; Chbihi, Marwa; Le Voyer, Tom; Rosain, Jérémie; Philippot, Quentin; Seeleuthner, Yoann; Gervais, Adrian; Materna, Marie; de Oliveira, Patricia Mouta Nunes; Maia, Maria de Lourdes S; et al. (J Exp Med, 2021)
Yellow fever virus (YFV) live attenuated vaccine can, in rare cases, cause life-threatening disease, typically in patients with no previous history of severe viral illness. Autosomal recessive (AR) complete IFNAR1 deficiency was reported in one 12-yr-old patient. Here, we studied seven other previously healthy patients aged 13 to 80 yr with unexplained life-threatening YFV vaccine-associated disease. One 13-yr-old patient had AR complete IFNAR2 deficiency. Three other patients vaccinated at the ages of 47, 57, and 64 yr had high titers of circulating auto-Abs against at least 14 of the 17 individual type I IFNs. These antibodies were recently shown to underlie at least 10% of cases of life-threatening COVID-19 pneumonia. The auto-Abs were neutralizing in vitro, blocking the protective effect of IFN-α2 against YFV vaccine strains. AR IFNAR1 or IFNAR2 deficiency and neutralizing auto-Abs against type I IFNs thus accounted for more than half the cases of life-threatening YFV vaccine-associated disease studied here. Previously healthy subjects could be tested for both predispositions before anti-YFV vaccination.
Keywords: Adolescent; Adult; Aged; Antibodies, Neutralizing; Autoantibodies; Autoimmune Diseases; COVID-19; Female; Genetic Diseases, Inborn; HEK293 Cells; Humans; Interferon-alpha; Male; Middle Aged; Receptor, Interferon alpha-beta; SARS-CoV-2; Vaccines, Attenuated; Yellow Fever Vaccine; Yellow fever virus

De novo TRIM8 variants impair its protein localization to nuclear bodies and cause developmental delay, epilepsy, and focal segmental glomerulosclerosis. - Weng, Patricia L; Majmundar, Amar J; Khan, Kamal; Lim, Tze Y; Shril, Shirlee; Jin, Gina; Musgrove, John; Wang, Minxian; Ahram, Dina F; Aggarwal, Vimla S; Bier, Louise E; Heinzen, Erin L; et al. (Am J Hum Genet, 2021)
Focal segmental glomerulosclerosis (FSGS) is the main pathology underlying steroid-resistant nephrotic syndrome (SRNS) and a leading cause of chronic kidney disease. Monogenic forms of pediatric SRNS are predominantly caused by recessive mutations, while the contribution of de novo variants (DNVs) to this trait is poorly understood. Using exome sequencing (ES) in a proband with FSGS/SRNS, developmental delay, and epilepsy, we discovered a nonsense DNV in TRIM8, which encodes the E3 ubiquitin ligase tripartite motif containing 8. To establish whether TRIM8 variants represent a cause of FSGS, we aggregated exome/genome-sequencing data for 2,501 pediatric FSGS/SRNS-affected individuals and 48,556 control subjects, detecting eight heterozygous TRIM8 truncating variants in affected subjects but none in control subjects (p = 3.28 × 10). In all six cases with available parental DNA, we demonstrated de novo inheritance (p = 2.21 × 10). Reverse phenotyping revealed neurodevelopmental disease in all eight families. We next analyzed ES from 9,067 individuals with epilepsy, yielding three additional families with truncating TRIM8 variants. Clinical review revealed FSGS in all. All TRIM8 variants cause protein truncation clustering within the last exon between residues 390 and 487 of the 551 amino acid protein, indicating a correlation between this syndrome and loss of the TRIM8 C-terminal region. Wild-type TRIM8 overexpressed in immortalized human podocytes and neuronal cells localized to nuclear bodies, while constructs harboring patient-specific variants mislocalized diffusely to the nucleoplasm. Co-localization studies demonstrated that Gemini and Cajal bodies frequently abut a TRIM8 nuclear body. Truncating TRIM8 DNVs cause a neuro-renal syndrome via aberrant TRIM8 localization, implicating nuclear bodies in FSGS and developmental brain disease.
Keywords: Adult; Animals; Carrier Proteins; Cell Line; Child; Child, Preschool; Codon, Nonsense; Developmental Disabilities; Epilepsy; Female; Glomerulosclerosis, Focal Segmental; Humans; Intranuclear Space; Kidney; Male; Mice; Mutation; Nephrotic Syndrome; Nerve Tissue Proteins; Phenotype; Podocytes; Whole Exome Sequencing

Deletion of CTCF sites in the SHH locus alters enhancer-promoter interactions and leads to acheiropodia. - Ushiki, Aki; Zhang, Yichi; Xiong, Chenling; Zhao, Jingjing; Georgakopoulos-Soares, Ilias; Kane, Lauren; Jamieson, Kirsty; Bamshad, Michael J; Nickerson, Deborah A; Shen, Yin; Lettice, Laura A; Silveira-Lucas, Elizabeth Lemos; et al. (Nat Commun, 2021)
Acheiropodia, congenital limb truncation, is associated with homozygous deletions in the LMBR1 gene around ZRS, an enhancer regulating SHH during limb development. How these deletions lead to this phenotype is unknown. Using whole-genome sequencing, we fine-mapped the acheiropodia-associated region to 12 kb and show that it does not function as an enhancer. CTCF and RAD21 ChIP-seq together with 4C-seq and DNA FISH identify three CTCF sites within the acheiropodia-deleted region that mediate the interaction between the ZRS and the SHH promoter. This interaction is substituted with other CTCF sites centromeric to the ZRS in the disease state. Mouse knockouts of the orthologous 12 kb sequence have no apparent abnormalities, showcasing the challenges in modelling CTCF alterations in animal models due to inherent motif differences between species. Our results show that alterations in CTCF motifs can lead to a Mendelian condition due to altered enhancer-promoter interactions.
Keywords: Animals; Binding Sites; CCCTC-Binding Factor; Chromatin Immunoprecipitation Sequencing; Disease Models, Animal; Embryo, Mammalian; Enhancer Elements, Genetic; Exons; Extremities; Female; Foot Deformities, Congenital; Gene Expression Regulation, Developmental; Genetic Loci; Genetic Testing; Hand Deformities, Congenital; Hedgehog Proteins; Humans; Introns; Male; Membrane Proteins; Mice; Mice, Knockout; Promoter Regions, Genetic; Sequence Deletion; Species Specificity; Whole Genome Sequencing

A DNA repair disorder caused by de novo monoallelic DDB1 variants is associated with a neurodevelopmental syndrome. - White, Susan M; Bhoj, Elizabeth; Nellaker, Christoffer; Lachmeijer, Augusta M A; Marshall, Aren E; Boycott, Kym M; Li, Dong; Smith, Wendy; Hartley, Taila; McBride, Arran; Ernst, Michelle E; May, Alison S; et al. (Am J Hum Genet, 2021)
The DNA damage-binding protein 1 (DDB1) is part of the CUL4-DDB1 ubiquitin E3 ligase complex (CRL4), which is essential for DNA repair, chromatin remodeling, DNA replication, and signal transduction. Loss-of-function variants in genes encoding the complex components CUL4 and PHIP have been reported to cause syndromic intellectual disability with hypotonia and obesity, but no phenotype has been reported in association with DDB1 variants. Here, we report eight unrelated individuals, identified through Matchmaker Exchange, with de novo monoallelic variants in DDB1, including one recurrent variant in four individuals. The affected individuals have a consistent phenotype of hypotonia, mild to moderate intellectual disability, and similar facies, including horizontal or slightly bowed eyebrows, deep-set eyes, full cheeks, a short nose, and large, fleshy and forward-facing earlobes, demonstrated in the composite face generated from the cohort. Digital anomalies, including brachydactyly and syndactyly, were common. Three older individuals have obesity. We show that cells derived from affected individuals have altered DDB1 function resulting in abnormal DNA damage signatures and histone methylation following UV-induced DNA damage. Overall, our study adds to the growing family of neurodevelopmental phenotypes mediated by disruption of the CRL4 ubiquitin ligase pathway and begins to delineate the phenotypic and molecular effects of DDB1 misregulation.
Keywords: Adolescent; Alleles; Child; Child, Preschool; DNA Repair; DNA-Binding Proteins; Female; Humans; Male; Mutation; Neurodevelopmental Disorders; Phenotype; Syndrome

Haplotype-resolved diverse human genomes and integrated analysis of structural variation. - Ebert, Peter; Audano, Peter A; Zhu, Qihui; Rodriguez-Martin, Bernardo; Porubsky, David; Bonder, Marc Jan; Sulovari, Arvis; Ebler, Jana; Zhou, Weichen; Serra Mari, Rebecca; Yilmaz, Feyza; Zhao, Xuefang; et al. (Science, 2021)
Long-read and strand-specific sequencing technologies together facilitate the de novo assembly of high-quality haplotype-resolved human genomes without parent-child trio data. We present 64 assembled haplotypes from 32 diverse human genomes. These highly contiguous haplotype assemblies (average minimum contig length needed to cover 50% of the genome: 26 million base pairs) integrate all forms of genetic variation, even across complex loci. We identified 107,590 structural variants (SVs), of which 68% were not discovered with short-read sequencing, and 278 SV hotspots (spanning megabases of gene-rich sequence). We characterized 130 of the most active mobile element source elements and found that 63% of all SVs arise through homology-mediated mechanisms. This resource enables reliable graph-based genotyping from short reads of up to 50,340 SVs, resulting in the identification of 1526 expression quantitative trait loci as well as SV candidates for adaptive selection within the human population.
Keywords: Female; Genetic Variation; Genome, Human; Genotype; Haplotypes; High-Throughput Nucleotide Sequencing; Humans; INDEL Mutation; Interspersed Repetitive Sequences; Male; Population Groups; Quantitative Trait Loci; Retroelements; Sequence Analysis, DNA; Sequence Inversion; Whole Genome Sequencing

Identification of homozygous mutations for hearing loss. - Dianatpour, Mehdi; Smith, Emily; Hashemi, Seyed Basir; Farazifard, Mohammad A; Nezafat, Navid; Razban, Vahid; Mani, Arya (Gene, 2021)
BACKGROUND: Hearing loss is the most common sensory disorder worldwide, affecting about 1 out of every 1000 newborns. The disease has major genetic components, and can be inherited as a single gene disorder either in autosomal dominant or recessive fashions. Due to the high rate of consanguineous unions, Iran has one of the highest prevalence of autosomal recessive nonsyndromic deafness (ARNSD) in the world. METHODS: We carried out a genetic screening of ten Iranian kindreds with more than one offspring affected by ARNSD caused by consanguineous unions. Sanger sequencing and whole exome sequencing together with in silico 3D structure modeling and protein stability prediction were used to identify the underlying disease causing genes. CONCLUSION: We identified the causes of deafness in all 10 kindred. In six kindreds homozygous mutations were identified in GJB2 gene by Sanger sequencing. By using whole exome sequencing (WES), a homozygous missense mutation was identified in ESRRB gene as the first ever reported disease gene in Iran. Also two novel homozygous frameshift and missense mutations were identified in MYO15A gene and one previously reported mutation in TMC1 gene in three independent kindred. Our study shows the efficacy of WES for unraveling new pathogenic mutations in ARNSD patients and expands the spectrum of genes contributing to ARNSD in the Iranian population. The findings of our study can facilitate future genetic screening of patients with ARNSD , early screening and optimal design of novel therapeutics.
Keywords: Connexin 26; Consanguinity; Female; Frameshift Mutation; Genetic Predisposition to Disease; Hearing Loss; Homozygote; Humans; Iran; Male; Membrane Proteins; Models, Molecular; Mutation, Missense; Myosins; Pedigree; Protein Stability; Receptors, Estrogen; Whole Exome Sequencing

Inhibition of HECT E3 ligases as potential therapy for COVID-19. - Novelli, Giuseppe; Liu, Jing; Biancolella, Michela; Alonzi, Tonino; Novelli, Antonio; Patten, J J; Cocciadiferro, Dario; Agolini, Emanuele; Colona, Vito Luigi; Rizzacasa, Barbara; Giannini, Rosalinda; Bigio, Benedetta; et al. (Cell Death Dis, 2021)
SARS-CoV-2 is responsible for the ongoing world-wide pandemic which has already taken more than two million lives. Effective treatments are urgently needed. The enzymatic activity of the HECT-E3 ligase family members has been implicated in the cell egression phase of deadly RNA viruses such as Ebola through direct interaction of its VP40 Protein. Here we report that HECT-E3 ligase family members such as NEDD4 and WWP1 interact with and ubiquitylate the SARS-CoV-2 Spike protein. Furthermore, we find that HECT family members are overexpressed in primary samples derived from COVID-19 infected patients and COVID-19 mouse models. Importantly, rare germline activating variants in the NEDD4 and WWP1 genes are associated with severe COVID-19 cases. Critically, I3C, a natural NEDD4 and WWP1 inhibitor from Brassicaceae, displays potent antiviral effects and inhibits viral egression. In conclusion, we identify the HECT family members of E3 ligases as likely novel biomarkers for COVID-19, as well as new potential targets of therapeutic strategy easily testable in clinical trials in view of the established well-tolerated nature of the Brassicaceae natural compounds.
Keywords: Adult; Aged; Animals; Antiviral Agents; Chlorocebus aethiops; COVID-19; Endosomal Sorting Complexes Required for Transport; Female; Humans; Indoles; Male; Mice; Mice, Inbred BALB C; Middle Aged; Nedd4 Ubiquitin Protein Ligases; SARS-CoV-2; Spike Glycoprotein, Coronavirus; Ubiquitin-Protein Ligases; Ubiquitination; Vero Cells

Loss of function mutations in GEMIN5 cause a neurodevelopmental disorder. - Kour, Sukhleen; Rajan, Deepa S; Fortuna, Tyler R; Anderson, Eric N; Ward, Caroline; Lee, Youngha; Lee, Sangmoon; Shin, Yong Beom; Chae, Jong-Hee; Choi, Murim; Siquier, Karine; Cantagrel, Vincent; et al. (Nat Commun, 2021)
GEMIN5, an RNA-binding protein is essential for assembly of the survival motor neuron (SMN) protein complex and facilitates the formation of small nuclear ribonucleoproteins (snRNPs), the building blocks of spliceosomes. Here, we have identified 30 affected individuals from 22 unrelated families presenting with developmental delay, hypotonia, and cerebellar ataxia harboring biallelic variants in the GEMIN5 gene. Mutations in GEMIN5 perturb the subcellular distribution, stability, and expression of GEMIN5 protein and its interacting partners in patient iPSC-derived neurons, suggesting a potential loss-of-function mechanism. GEMIN5 mutations result in disruption of snRNP complex assembly formation in patient iPSC neurons. Furthermore, knock down of rigor mortis, the fly homolog of human GEMIN5, leads to developmental defects, motor dysfunction, and a reduced lifespan. Interestingly, we observed that GEMIN5 variants disrupt a distinct set of transcripts and pathways as compared to SMA patient neurons, suggesting different molecular pathomechanisms. These findings collectively provide evidence that pathogenic variants in GEMIN5 perturb physiological functions and result in a neurodevelopmental delay and ataxia syndrome.
Keywords: Alleles; Amino Acid Sequence; Animals; Child, Preschool; Developmental Disabilities; Drosophila; Female; Gene Expression Regulation, Developmental; Gene Knockdown Techniques; Gene Ontology; HEK293 Cells; Humans; Induced Pluripotent Stem Cells; Loss of Function Mutation; Male; Muscle Hypotonia; Myoclonic Cerebellar Dyssynergia; Neurodevelopmental Disorders; Neurons; Pedigree; Polymorphism, Single Nucleotide; Ribonucleoproteins, Small Nuclear; Rigor Mortis; RNA-Seq; SMN Complex Proteins

Mutations in Spliceosomal Genes PPIL1 and PRP17 Cause Neurodegenerative Pontocerebellar Hypoplasia with Microcephaly. - Chai, Guoliang; Webb, Alice; Li, Chen; Antaki, Danny; Lee, Sangmoon; Breuss, Martin W; Lang, Nhi; Stanley, Valentina; Anzenberg, Paula; Yang, Xiaoxu; Marshall, Trevor; Gaffney, Patrick; et al. (Neuron, 2021)
Autosomal-recessive cerebellar hypoplasia and ataxia constitute a group of heterogeneous brain disorders caused by disruption of several fundamental cellular processes. Here, we identified 10 families showing a neurodegenerative condition involving pontocerebellar hypoplasia with microcephaly (PCHM). Patients harbored biallelic mutations in genes encoding the spliceosome components Peptidyl-Prolyl Isomerase Like-1 (PPIL1) or Pre-RNA Processing-17 (PRP17). Mouse knockouts of either gene were lethal in early embryogenesis, whereas PPIL1 patient mutation knockin mice showed neuron-specific apoptosis. Loss of either protein affected splicing integrity, predominantly affecting short and high GC-content introns and genes involved in brain disorders. PPIL1 and PRP17 form an active isomerase-substrate interaction, but we found that isomerase activity is not critical for function. Thus, we establish disrupted splicing integrity and "major spliceosome-opathies" as a new mechanism underlying PCHM and neurodegeneration and uncover a non-enzymatic function of a spliceosomal proline isomerase.
Keywords: Amino Acid Sequence; Animals; Cell Cycle Proteins; Cerebellar Diseases; Cohort Studies; Female; Gene Knockout Techniques; HEK293 Cells; Heredodegenerative Disorders, Nervous System; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Microcephaly; Mutation; Pedigree; Peptidylprolyl Isomerase; Protein Structure, Secondary; Protein Structure, Tertiary; RNA Splicing Factors; Spliceosomes

Plasma Exchange to Rescue Patients with Autoantibodies Against Type I Interferons and Life-Threatening COVID-19 Pneumonia. - de Prost, Nicolas; Bastard, Paul; Arrestier, Romain; Fourati, Slim; Mahévas, Mathieu; Burrel, Sonia; Dorgham, Karim; Gorochov, Guy; Tandjaoui-Lambiotte, Yacine; Azzaoui, Iname; Fernandes, Ignacio; Combes, Alain; et al. (J Clin Immunol, 2021)
PURPOSE: To report four cases of life-threatening COVID-19 pneumonia in patients with high blood concentrations of neutralizing autoantibodies against type I interferons (IFNs), who were treated with plasma exchange (PE) as a rescue therapy. METHODS: Prospective case series, which included patients, diagnosed with RT-PCR-confirmed SARS-CoV-2 infection and positive autoantibodies against type I IFNs in two French intensive care units (ICUs) between October 8 and November 14, 2020. Six critically ill COVID-19 patients with no anti-IFN antibodies were used as controls. Anti-IFN autoantibodies and IFN concentrations, together with the levels of anti-SARS-CoV-2 antibodies, were measured sequentially in serum. Viral load was determined in the upper and lower respiratory tract. Patients were followed during hospital stay. RESULTS: Three men and one woman were included. Three of the patients had four PE sessions each, while another had three PE sessions. PE decreased the concentrations of autoantibodies against type I IFN in all four patients, whereas anti-SARS-CoV-2 antibody levels remained stable. Autoantibodies against type I IFN levels were high in tracheal aspirates of one patient and decreased after three PE sessions. By contrast, anti-IFN autoantibodies were not detected in tracheal aspirates from five control patients without detectable anti-IFN autoantibodies in serum. During PE, serum IFN-α levels slightly increased in three out of four patients, and upper respiratory tract viral load decreased in all patients. All patients were alive at day 28 of ICU admission. Two patients eventually died in the ICU, while the two survivors were discharged from the ICU at days 50 and 66. CONCLUSIONS: PE efficiently removes autoantibodies against type I IFNs, including those detected in tracheal aspirates, without affecting anti-SARS-CoV-2 antibody levels, in patients with life-threatening COVID-19 pneumonia. The clinical benefit of PE in patients with autoantibodies against type I IFNs should be tested in a larger study.
Keywords: Adult; Aged; Autoantibodies; COVID-19; Female; Humans; Interferon Type I; Male; Plasma Exchange; Prospective Studies; SARS-CoV-2

POLRMT mutations impair mitochondrial transcription causing neurological disease. - Oláhová, Monika; Peter, Bradley; Szilagyi, Zsolt; Diaz-Maldonado, Hector; Singh, Meenakshi; Sommerville, Ewen W; Blakely, Emma L; Collier, Jack J; Hoberg, Emily; Stránecký, Viktor; Hartmannová, Hana; Bleyer, Anthony J; et al. (Nat Commun, 2021)
While >300 disease-causing variants have been identified in the mitochondrial DNA (mtDNA) polymerase γ, no mitochondrial phenotypes have been associated with POLRMT, the RNA polymerase responsible for transcription of the mitochondrial genome. Here, we characterise the clinical and molecular nature of POLRMT variants in eight individuals from seven unrelated families. Patients present with global developmental delay, hypotonia, short stature, and speech/intellectual disability in childhood; one subject displayed an indolent progressive external ophthalmoplegia phenotype. Massive parallel sequencing of all subjects identifies recessive and dominant variants in the POLRMT gene. Patient fibroblasts have a defect in mitochondrial mRNA synthesis, but no mtDNA deletions or copy number abnormalities. The in vitro characterisation of the recombinant POLRMT mutants reveals variable, but deleterious effects on mitochondrial transcription. Together, our in vivo and in vitro functional studies of POLRMT variants establish defective mitochondrial transcription as an important disease mechanism.
Keywords: Adolescent; Adult; Child; DNA, Mitochondrial; DNA-Directed RNA Polymerases; Female; Fibroblasts; Humans; Infant; Male; Mitochondria; Mutation; Nervous System Diseases; Oxidative Phosphorylation; Pedigree; Protein Domains; Protein Subunits; RNA, Messenger; Transcription, Genetic; Young Adult

Preexisting autoantibodies to type I IFNs underlie critical COVID-19 pneumonia in patients with APS-1. - Bastard, Paul; Orlova, Elizaveta; Sozaeva, Leila; Lévy, Romain; James, Alyssa; Schmitt, Monica M; Ochoa, Sebastian; Kareva, Maria; Rodina, Yulia; Gervais, Adrian; Le Voyer, Tom; Rosain, Jérémie; et al. (J Exp Med, 2021)
Patients with biallelic loss-of-function variants of AIRE suffer from autoimmune polyendocrine syndrome type-1 (APS-1) and produce a broad range of autoantibodies (auto-Abs), including circulating auto-Abs neutralizing most type I interferons (IFNs). These auto-Abs were recently reported to account for at least 10% of cases of life-threatening COVID-19 pneumonia in the general population. We report 22 APS-1 patients from 21 kindreds in seven countries, aged between 8 and 48 yr and infected with SARS-CoV-2 since February 2020. The 21 patients tested had auto-Abs neutralizing IFN-α subtypes and/or IFN-ω; one had anti-IFN-β and another anti-IFN-ε, but none had anti-IFN-κ. Strikingly, 19 patients (86%) were hospitalized for COVID-19 pneumonia, including 15 (68%) admitted to an intensive care unit, 11 (50%) who required mechanical ventilation, and four (18%) who died. Ambulatory disease in three patients (14%) was possibly accounted for by prior or early specific interventions. Preexisting auto-Abs neutralizing type I IFNs in APS-1 patients confer a very high risk of life-threatening COVID-19 pneumonia at any age.
Keywords: Adolescent; Adult; Autoantibodies; Child; COVID-19; Female; Humans; Interferon Type I; Male; Middle Aged; Pneumonia; Polyendocrinopathies, Autoimmune; SARS-CoV-2; Young Adult

SPEN haploinsufficiency causes a neurodevelopmental disorder overlapping proximal 1p36 deletion syndrome with an episignature of X chromosomes in females. - Radio, Francesca Clementina; Pang, Kaifang; Ciolfi, Andrea; Levy, Michael A; Hernandez-Garcia, Andres; Pedace, Lucia; Pantaleoni, Francesca; Liu, Zhandong; de Boer, Elke; Jackson, Adam; Bruselles, Alessandro; McConkey, Haley; et al. (Am J Hum Genet, 2021)
Deletion 1p36 (del1p36) syndrome is the most common human disorder resulting from a terminal autosomal deletion. This condition is molecularly and clinically heterogeneous. Deletions involving two non-overlapping regions, known as the distal (telomeric) and proximal (centromeric) critical regions, are sufficient to cause the majority of the recurrent clinical features, although with different facial features and dysmorphisms. SPEN encodes a transcriptional repressor commonly deleted in proximal del1p36 syndrome and is located centromeric to the proximal 1p36 critical region. Here, we used clinical data from 34 individuals with truncating variants in SPEN to define a neurodevelopmental disorder presenting with features that overlap considerably with those of proximal del1p36 syndrome. The clinical profile of this disease includes developmental delay/intellectual disability, autism spectrum disorder, anxiety, aggressive behavior, attention deficit disorder, hypotonia, brain and spine anomalies, congenital heart defects, high/narrow palate, facial dysmorphisms, and obesity/increased BMI, especially in females. SPEN also emerges as a relevant gene for del1p36 syndrome by co-expression analyses. Finally, we show that haploinsufficiency of SPEN is associated with a distinctive DNA methylation episignature of the X chromosome in affected females, providing further evidence of a specific contribution of the protein to the epigenetic control of this chromosome, and a paradigm of an X chromosome-specific episignature that classifies syndromic traits. We conclude that SPEN is required for multiple developmental processes and SPEN haploinsufficiency is a major contributor to a disorder associated with deletions centromeric to the previously established 1p36 critical regions.
Keywords: Adolescent; Autism Spectrum Disorder; Child; Child, Preschool; Chromosome Deletion; Chromosome Disorders; Chromosomes, Human, Pair 1; Chromosomes, Human, X; DNA Methylation; DNA-Binding Proteins; Epigenesis, Genetic; Female; Haploinsufficiency; Humans; Intellectual Disability; Male; Neurodevelopmental Disorders; Phenotype; RNA-Binding Proteins; Young Adult

Whole-genome sequencing of African Americans implicates differential genetic architecture in inflammatory bowel disease. - Somineni, Hari K; Nagpal, Sini; Venkateswaran, Suresh; Cutler, David J; Okou, David T; Haritunians, Talin; Simpson, Claire L; Begum, Ferdouse; Datta, Lisa W; Quiros, Antonio J; Seminerio, Jenifer; Mengesha, Emebet; et al. (Am J Hum Genet, 2021)
Whether or not populations diverge with respect to the genetic contribution to risk of specific complex diseases is relevant to understanding the evolution of susceptibility and origins of health disparities. Here, we describe a large-scale whole-genome sequencing study of inflammatory bowel disease encompassing 1,774 affected individuals and 1,644 healthy control Americans with African ancestry (African Americans). Although no new loci for inflammatory bowel disease are discovered at genome-wide significance levels, we identify numerous instances of differential effect sizes in combination with divergent allele frequencies. For example, the major effect at PTGER4 fine maps to a single credible interval of 22 SNPs corresponding to one of four independent associations at the locus in European ancestry individuals but with an elevated odds ratio for Crohn disease in African Americans. A rare variant aggregate analysis implicates Ca-binding neuro-immunomodulator CALB2 in ulcerative colitis. Highly significant overall overlap of common variant risk for inflammatory bowel disease susceptibility between individuals with African and European ancestries was observed, with 41 of 241 previously known lead variants replicated and overall correlations in effect sizes of 0.68 for combined inflammatory bowel disease. Nevertheless, subtle differences influence the performance of polygenic risk scores, and we show that ancestry-appropriate weights significantly improve polygenic prediction in the highest percentiles of risk. The median amount of variance explained per locus remains the same in African and European cohorts, providing evidence for compensation of effect sizes as allele frequencies diverge, as expected under a highly polygenic model of disease.
Keywords: African Americans; Aged; Aged, 80 and over; Calbindin 2; Colitis, Ulcerative; Crohn Disease; European Continental Ancestry Group; Female; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Inflammatory Bowel Diseases; Male; Multifactorial Inheritance; Polymorphism, Single Nucleotide; Receptors, Prostaglandin E, EP4 Subtype; Whole Genome Sequencing

8q24 genetic variation and comprehensive haplotypes altering familial risk of prostate cancer. - Dupont, William D; Breyer, Joan P; Plummer, W Dale; Chang, Sam S; Cookson, Michael S; Smith, Joseph A; Blue, Elizabeth E; Bamshad, Michael J; Smith, Jeffrey R (Nat Commun, 2020)
The 8q24 genomic locus is tied to the origin of numerous cancers. We investigate its contribution to hereditary prostate cancer (HPC) in independent study populations of the Nashville Familial Prostate Cancer Study and International Consortium for Prostate Cancer Genetics (combined: 2,836 HPC cases, 2,206 controls of European ancestry). Here we report 433 variants concordantly associated with HPC in both study populations, accounting for 9% of heritability and modifying age of diagnosis as well as aggressiveness; 183 reach genome-wide significance. The variants comprehensively distinguish independent risk-altering haplotypes overlapping the 648 kb locus (three protective, and four risk (peak odds ratios: 1.5, 4, 5, and 22)). Sequence of the near-Mendelian haplotype reveals eleven causal mutation candidates. We introduce a linkage disequilibrium-based algorithm discerning eight independent sentinel variants, carrying considerable risk prediction ability (AUC = 0.625) for a single locus. These findings elucidate 8q24 locus structure and correlates for clinical prediction of prostate cancer risk.
Keywords: Aged; Case-Control Studies; Chromosomes, Human, Pair 8; European Continental Ancestry Group; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Haplotypes; Heterozygote; Humans; Linkage Disequilibrium; Male; Middle Aged; Mutation; Prostatic Neoplasms; Protective Factors; Risk Factors

ASC-1 Is a Cell Cycle Regulator Associated with Severe and Mild Forms of Myopathy. - Villar-Quiles, Rocío N; Catervi, Fabio; Cabet, Eva; Juntas-Morales, Raul; Genetti, Casie A; Gidaro, Teresa; Koparir, Asuman; Yuksel, Adnan; Coppens, Sandra; Deconinck, Nicolas; Pierce-Hoffman, Emma; Lornage, Xavière; et al. (Ann Neurol, 2020)
OBJECTIVE: Recently, the ASC-1 complex has been identified as a mechanistic link between amyotrophic lateral sclerosis and spinal muscular atrophy (SMA), and 3 mutations of the ASC-1 gene TRIP4 have been associated with SMA or congenital myopathy. Our goal was to define ASC-1 neuromuscular function and the phenotypical spectrum associated with TRIP4 mutations. METHODS: Clinical, molecular, histological, and magnetic resonance imaging studies were made in 5 families with 7 novel TRIP4 mutations. Fluorescence activated cell sorting and Western blot were performed in patient-derived fibroblasts and muscles and in Trip4 knocked-down C2C12 cells. RESULTS: All mutations caused ASC-1 protein depletion. The clinical phenotype was purely myopathic, ranging from lethal neonatal to mild ambulatory adult patients. It included early onset axial and proximal weakness, scoliosis, rigid spine, dysmorphic facies, cutaneous involvement, respiratory failure, and in the older cases, dilated cardiomyopathy. Muscle biopsies showed multiminicores, nemaline rods, cytoplasmic bodies, caps, central nuclei, rimmed fibers, and/or mild endomysial fibrosis. ASC-1 depletion in C2C12 and in patient-derived fibroblasts and muscles caused accelerated proliferation, altered expression of cell cycle proteins, and/or shortening of the G0/G1 cell cycle phase leading to cell size reduction. INTERPRETATION: Our results expand the phenotypical and molecular spectrum of TRIP4-associated disease to include mild adult forms with or without cardiomyopathy, associate ASC-1 depletion with isolated primary muscle involvement, and establish TRIP4 as a causative gene for several congenital muscle diseases, including nemaline, core, centronuclear, and cytoplasmic-body myopathies. They also identify ASC-1 as a novel cell cycle regulator with a key role in cell proliferation, and underline transcriptional coregulation defects as a novel pathophysiological mechanism. ANN NEUROL 2020;87:217-232.
Keywords: Adult; Amino Acid Transport System y+; Cell Cycle; Cells, Cultured; Child; Child, Preschool; Female; Fibroblasts; Humans; Infant; Male; Middle Aged; Muscle Proteins; Muscle, Skeletal; Muscular Diseases; Mutation; Pedigree; Phenotype; Transcription Factors

Association of Rare Pathogenic DNA Variants for Familial Hypercholesterolemia, Hereditary Breast and Ovarian Cancer Syndrome, and Lynch Syndrome With Disease Risk in Adults According to Family History. - Patel, Aniruddh P; Wang, Minxian; Fahed, Akl C; Mason-Suares, Heather; Brockman, Deanna; Pelletier, Renee; Amr, Sami; Machini, Kalotina; Hawley, Megan; Witkowski, Leora; Koch, Christopher; Philippakis, Anthony; et al. (JAMA Netw Open, 2020)
Importance: Pathogenic DNA variants associated with familial hypercholesterolemia, hereditary breast and ovarian cancer syndrome, and Lynch syndrome are widely recognized as clinically important and actionable when identified, leading some clinicians to recommend population-wide genomic screening. Objectives: To assess the prevalence and clinical importance of pathogenic or likely pathogenic variants associated with each of 3 genomic conditions (familial hypercholesterolemia, hereditary breast and ovarian cancer syndrome, and Lynch syndrome) within the context of contemporary clinical care. Design, Setting, and Participants: This cohort study used gene-sequencing data from 49 738 participants in the UK Biobank who were recruited from 22 sites across the UK between March 21, 2006, and October 1, 2010. Inpatient hospital data date back to 1977; cancer registry data, to 1957; and death registry data, to 2006. Statistical analysis was performed from July 22, 2019, to November 15, 2019. Exposures: Pathogenic or likely pathogenic DNA variants classified by a clinical laboratory geneticist. Main Outcomes and Measures: Composite end point specific to each genomic condition based on atherosclerotic cardiovascular disease events for familial hypercholesterolemia, breast or ovarian cancer for hereditary breast and ovarian cancer syndrome, and colorectal or uterine cancer for Lynch syndrome. Results: Among 49 738 participants (mean [SD] age, 57 [8] years; 27 144 female [55%]), 441 (0.9%) harbored a pathogenic or likely pathogenic variant associated with any of 3 genomic conditions, including 131 (0.3%) for familial hypercholesterolemia, 235 (0.5%) for hereditary breast and ovarian cancer syndrome, and 76 (0.2%) for Lynch syndrome. Presence of these variants was associated with increased risk of disease: for familial hypercholesterolemia, 28 of 131 carriers (21.4%) vs 4663 of 49 607 noncarriers (9.4%) developed atherosclerotic cardiovascular disease; for hereditary breast and ovarian cancer syndrome, 32 of 116 female carriers (27.6%) vs 2080 of 27 028 female noncarriers (7.7%) developed associated cancers; and for Lynch syndrome, 17 of 76 carriers (22.4%) vs 929 of 49 662 noncarriers (1.9%) developed colorectal or uterine cancer. The predicted probability of disease at age 75 years despite contemporary clinical care was 45.3% for carriers of familial hypercholesterolemia, 41.1% for hereditary breast and ovarian cancer syndrome, and 38.3% for Lynch syndrome. Across the 3 conditions, 39.7% (175 of 441) of the carriers reported a family history of disease vs 23.2% (34 517 of 148 772) of noncarriers. Conclusions and Relevance: The findings suggest that approximately 1% of the middle-aged adult population in the UK Biobank harbored a pathogenic variant associated with any of 3 genomic conditions. These variants were associated with an increased risk of disease despite contemporary clinical care and were not reliably detected by family history.
Keywords: Aged; Cohort Studies; Colorectal Neoplasms, Hereditary Nonpolyposis; Female; Genetic Predisposition to Disease; Hereditary Breast and Ovarian Cancer Syndrome; Heterozygote; Humans; Hyperlipoproteinemia Type II; Male; Middle Aged; Pedigree; Proportional Hazards Models; United Kingdom; Whole Exome Sequencing

Autoantibodies against type I IFNs in patients with life-threatening COVID-19. - Bastard, Paul; Rosen, Lindsey B; Zhang, Qian; Michailidis, Eleftherios; Hoffmann, Hans-Heinrich; Zhang, Yu; Dorgham, Karim; Philippot, Quentin; Rosain, Jérémie; Béziat, Vivien; Manry, Jeremy; Shaw, Elana; et al. (Science, 2020)
Interindividual clinical variability in the course of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is vast. We report that at least 101 of 987 patients with life-threatening coronavirus disease 2019 (COVID-19) pneumonia had neutralizing immunoglobulin G (IgG) autoantibodies (auto-Abs) against interferon-ω (IFN-ω) (13 patients), against the 13 types of IFN-α (36), or against both (52) at the onset of critical disease; a few also had auto-Abs against the other three type I IFNs. The auto-Abs neutralize the ability of the corresponding type I IFNs to block SARS-CoV-2 infection in vitro. These auto-Abs were not found in 663 individuals with asymptomatic or mild SARS-CoV-2 infection and were present in only 4 of 1227 healthy individuals. Patients with auto-Abs were aged 25 to 87 years and 95 of the 101 were men. A B cell autoimmune phenocopy of inborn errors of type I IFN immunity accounts for life-threatening COVID-19 pneumonia in at least 2.6% of women and 12.5% of men.
Keywords: Adult; Aged; Aged, 80 and over; Antibodies, Neutralizing; Asymptomatic Infections; Autoantibodies; Betacoronavirus; Case-Control Studies; Coronavirus Infections; COVID-19; Critical Illness; Female; Humans; Immunoglobulin G; Interferon alpha-2; Interferon Type I; Male; Middle Aged; Pandemics; Pneumonia, Viral; SARS-CoV-2

Beyond the tubule: pathological variants of , encoding the megalin receptor, result in glomerular loss and early progressive chronic kidney disease. - Charlton, Jennifer R; Tan, Weizhen; Daouk, Ghaleb; Teot, Lisa; Rosen, Seymour; Bennett, Kevin M; Cwiek, Aleksandra; Nam, Sejin; Emma, Francesco; Jouret, François; Oliveira, João Paulo; Tranebjærg, Lisbeth; et al. (Am J Physiol Renal Physiol, 2020)
Pathogenic variants in the gene, encoding the multiligand receptor megalin, cause a rare autosomal recessive syndrome: Donnai-Barrow/Facio-Oculo-Acoustico-Renal (DB/FOAR) syndrome. Because of the rarity of the syndrome, the long-term consequences of the tubulopathy on human renal health have been difficult to ascertain, and the human clinical condition has hitherto been characterized as a benign tubular condition with asymptomatic low-molecular-weight proteinuria. We investigated renal function and morphology in a murine model of DB/FOAR syndrome and in patients with DB/FOAR. We analyzed glomerular filtration rate in mice by FITC-inulin clearance and clinically characterized six families, including nine patients with DB/FOAR and nine family members. Urine samples from patients were analyzed by Western blot analysis and biopsy materials were analyzed by histology. In the mouse model, we used histological methods to assess nephrogenesis and postnatal renal structure and contrast-enhanced magnetic resonance imaging to assess glomerular number. In megalin-deficient mice, we found a lower glomerular filtration rate and an increase in the abundance of injury markers, such as kidney injury molecule-1 and -acetyl-β-d-glucosaminidase. Renal injury was validated in patients, who presented with increased urinary kidney injury molecule-1, classical markers of chronic kidney disease, and glomerular proteinuria early in life. Megalin-deficient mice had normal nephrogenesis, but they had 19% fewer nephrons in early adulthood and an increased fraction of nephrons with disconnected glomerulotubular junction. In conclusion, megalin dysfunction, as present in DB/FOAR syndrome, confers an increased risk of progression into chronic kidney disease.
Keywords: Adolescent; Adult; Animals; Child; Child, Preschool; Female; Genetic Predisposition to Disease; Genetic Variation; Humans; Kidney Glomerulus; Low Density Lipoprotein Receptor-Related Protein-2; Male; Mice; Mice, Knockout; Middle Aged; Renal Insufficiency, Chronic; Young Adult

Bi-allelic ADARB1 Variants Associated with Microcephaly, Intellectual Disability, and Seizures. - Tan, Tiong Yang; Sedmík, Jiří; Fitzgerald, Mark P; Halevy, Rivka Sukenik; Keegan, Liam P; Helbig, Ingo; Basel-Salmon, Lina; Cohen, Lior; Straussberg, Rachel; Chung, Wendy K; Helal, Mayada; Maroofian, Reza; et al. (Am J Hum Genet, 2020)
The RNA editing enzyme ADAR2 is essential for the recoding of brain transcripts. Impaired ADAR2 editing leads to early-onset epilepsy and premature death in a mouse model. Here, we report bi-allelic variants in ADARB1, the gene encoding ADAR2, in four unrelated individuals with microcephaly, intellectual disability, and epilepsy. In one individual, a homozygous variant in one of the double-stranded RNA-binding domains (dsRBDs) was identified. In the others, variants were situated in or around the deaminase domain. To evaluate the effects of these variants on ADAR2 enzymatic activity, we performed in vitro assays with recombinant proteins in HEK293T cells and ex vivo assays with fibroblasts derived from one of the individuals. We demonstrate that these ADAR2 variants lead to reduced editing activity on a known ADAR2 substrate. We also demonstrate that one variant leads to changes in splicing of ADARB1 transcript isoforms. These findings reinforce the importance of RNA editing in brain development and introduce ADARB1 as a genetic etiology in individuals with intellectual disability, microcephaly, and epilepsy.
Keywords: Adenosine Deaminase; Alleles; Alternative Splicing; Child; Child, Preschool; Genetic Predisposition to Disease; Genetic Variation; HEK293 Cells; Humans; Intellectual Disability; Male; Microcephaly; RNA Splicing; RNA-Binding Proteins; Seizures

Bi-allelic GAD1 variants cause a neonatal onset syndromic developmental and epileptic encephalopathy. - Chatron, Nicolas; Becker, Felicitas; Morsy, Heba; Schmidts, Miriam; Hardies, Katia; Tuysuz, Beyhan; Roselli, Sandra; Najafi, Maryam; Alkaya, Dilek Uludag; Ashrafzadeh, Farah; Nabil, Amira; Omar, Tarek; et al. (Brain, 2020)
Developmental and epileptic encephalopathies are a heterogeneous group of early-onset epilepsy syndromes dramatically impairing neurodevelopment. Modern genomic technologies have revealed a number of monogenic origins and opened the door to therapeutic hopes. Here we describe a new syndromic developmental and epileptic encephalopathy caused by bi-allelic loss-of-function variants in GAD1, as presented by 11 patients from six independent consanguineous families. Seizure onset occurred in the first 2 months of life in all patients. All 10 patients, from whom early disease history was available, presented with seizure onset in the first month of life, mainly consisting of epileptic spasms or myoclonic seizures. Early EEG showed suppression-burst or pattern of burst attenuation or hypsarrhythmia if only recorded in the post-neonatal period. Eight patients had joint contractures and/or pes equinovarus. Seven patients presented a cleft palate and two also had an omphalocele, reproducing the phenotype of the knockout Gad1-/- mouse model. Four patients died before 4 years of age. GAD1 encodes the glutamate decarboxylase enzyme GAD67, a critical actor of the γ-aminobutyric acid (GABA) metabolism as it catalyses the decarboxylation of glutamic acid to form GABA. Our findings evoke a novel syndrome related to GAD67 deficiency, characterized by the unique association of developmental and epileptic encephalopathies, cleft palate, joint contractures and/or omphalocele.
Keywords: Abnormalities, Multiple; Epileptic Syndromes; Female; Glutamate Decarboxylase; Humans; Infant, Newborn; Male; Mutation; Pedigree

Biallelic GRM7 variants cause epilepsy, microcephaly, and cerebral atrophy. - Marafi, Dana; Mitani, Tadahiro; Isikay, Sedat; Hertecant, Jozef; Almannai, Mohammed; Manickam, Kandamurugu; Abou Jamra, Rami; El-Hattab, Ayman W; Rajah, Jaishen; Fatih, Jawid M; Du, Haowei; Karaca, Ender; et al. (Ann Clin Transl Neurol, 2020)
OBJECTIVE: Defects in ion channels and neurotransmitter receptors are implicated in developmental and epileptic encephalopathy (DEE). Metabotropic glutamate receptor 7 (mGluR7), encoded by GRM7, is a presynaptic G-protein-coupled glutamate receptor critical for synaptic transmission. We previously proposed GRM7 as a candidate disease gene in two families with neurodevelopmental disorders (NDDs). One additional family has been published since. Here, we describe three additional families with GRM7 biallelic variants and deeply characterize the associated clinical neurological and electrophysiological phenotype and molecular data in 11 affected individuals from six unrelated families. METHODS: Exome sequencing and family-based rare variant analyses on a cohort of 220 consanguineous families with NDDs revealed three families with GRM7 biallelic variants; three additional families were identified through literature search and collaboration with a clinical molecular laboratory. RESULTS: We compared the observed clinical features and variants of 11 affected individuals from the six unrelated families. Identified novel deleterious variants included two homozygous missense variants (c.2671G>A:p.Glu891Lys and c.1973G>A:p.Arg685Gln) and one homozygous stop-gain variant (c.1975C>T:p.Arg659Ter). Developmental delay, neonatal- or infantile-onset epilepsy, and microcephaly were universal. Three individuals had hypothalamic-pituitary-axis dysfunction without pituitary structural abnormality. Neuroimaging showed cerebral atrophy and hypomyelination in a majority of cases. Two siblings demonstrated progressive loss of myelination by 2 years in both and an acquired microcephaly pattern in one. Five individuals died in early or late childhood. CONCLUSION: Detailed clinical characterization of 11 individuals from six unrelated families demonstrates that rare biallelic GRM7 pathogenic variants can cause DEEs, microcephaly, hypomyelination, and cerebral atrophy.
Keywords: Adolescent; Alleles; Atrophy; Child; Child, Preschool; Cohort Studies; Consanguinity; Epilepsy; Female; Humans; Infant; Male; Microcephaly; Neurodevelopmental Disorders; Pedigree; Phenotype; Receptors, Metabotropic Glutamate; Whole Exome Sequencing

Biallelic loss of function variants in SYT2 cause a treatable congenital onset presynaptic myasthenic syndrome. - Donkervoort, Sandra; Mohassel, Payam; Laugwitz, Lucia; Zaki, MAH S; Kamsteeg, Erik-Jan; Maroofian, Reza; Chao, Katherine R; Verschuuren-Bemelmans, Corien C; Horber, Veronka; Fock, Annemarie J M; McCarty, Riley M; Jain, Minal S; et al. (Am J Med Genet A, 2020)
Synaptotagmins are integral synaptic vesicle membrane proteins that function as calcium sensors and regulate neurotransmitter release at the presynaptic nerve terminal. Synaptotagmin-2 (SYT2), is the major isoform expressed at the neuromuscular junction. Recently, dominant missense variants in SYT2 have been reported as a rare cause of distal motor neuropathy and myasthenic syndrome, manifesting with stable or slowly progressive distal weakness of variable severity along with presynaptic NMJ impairment. These variants are thought to have a dominant-negative effect on synaptic vesicle exocytosis, although the precise pathomechanism remains to be elucidated. Here we report seven patients of five families, with biallelic loss of function variants in SYT2, clinically manifesting with a remarkably consistent phenotype of severe congenital onset hypotonia and weakness, with variable degrees of respiratory involvement. Electrodiagnostic findings were consistent with a presynaptic congenital myasthenic syndrome (CMS) in some. Treatment with an acetylcholinesterase inhibitor pursued in three patients showed clinical improvement with increased strength and function. This series further establishes SYT2 as a CMS-disease gene and expands its clinical and genetic spectrum to include recessive loss-of-function variants, manifesting as a severe congenital onset presynaptic CMS with potential treatment implications.
Keywords: Adolescent; Child; Child, Preschool; Female; Genetic Predisposition to Disease; Humans; Male; Muscle Hypotonia; Muscle Weakness; Mutation, Missense; Myasthenic Syndromes, Congenital; Pedigree; Phenotype; Synaptic Transmission; Synaptotagmin II

Bi-allelic Variations of SMO in Humans Cause a Broad Spectrum of Developmental Anomalies Due to Abnormal Hedgehog Signaling. - Le, Thuy-Linh; Sribudiani, Yunia; Dong, Xiaomin; Huber, Celine; Kois, Chelsea; Baujat, Geneviève; Gordon, Christopher T; Mayne, Valerie; Galmiche, Louise; Serre, Valérie; Goudin, Nicolas; Zarhrate, Mohammed; et al. (Am J Hum Genet, 2020)
The evolutionarily conserved hedgehog (Hh) pathway is essential for organogenesis and plays critical roles in postnatal tissue maintenance and renewal. A unique feature of the vertebrate Hh pathway is that signal transduction requires the primary cilium (PC) where major pathway components are dynamically enriched. These factors include smoothened (SMO) and patched, which constitute the core reception system for sonic hedgehog (SHH) as well as GLI transcription factors, the key mediators of the pathway. Here, we report bi-allelic loss-of-function variations in SMO in seven individuals from five independent families; these variations cause a wide phenotypic spectrum of developmental anomalies affecting the brain (hypothalamic hamartoma and microcephaly), heart (atrioventricular septal defect), skeleton (postaxial polydactyly, narrow chest, and shortening of long bones), and enteric nervous system (aganglionosis). Cells derived from affected individuals showed normal ciliogenesis but severely altered Hh-signal transduction as a result of either altered PC trafficking or abnormal activation of the pathway downstream of SMO. In addition, Hh-independent GLI2 accumulation at the PC tip in cells from the affected individuals suggests a potential function of SMO in regulating basal ciliary trafficking of GLI2 when the pathway is off. Thus, loss of SMO function results in abnormal PC dynamics of key components of the Hh signaling pathway and leads to a large continuum of malformations in humans.
Keywords: Alleles; Base Sequence; Child; Child, Preschool; Cilia; Developmental Disabilities; Female; Hedgehog Proteins; Humans; Infant; Male; Models, Molecular; Neoplasms; Nerve Tissue Proteins; Nuclear Proteins; Pedigree; Signal Transduction; Smoothened Receptor; Zinc Finger Protein Gli2; Zinc Finger Protein Gli3

Combining Imaging and Genetics to Predict Recurrence of Anticoagulation-Associated Intracerebral Hemorrhage. - Biffi, Alessandro; Urday, Sebastian; Kubiszewski, Patryk; Gilkerson, Lee; Sekar, Padmini; Rodriguez-Torres, Axana; Bettin, Margaret; Charidimou, Andreas; Pasi, Marco; Kourkoulis, Christina; Schwab, Kristin; DiPucchio, Zora; et al. (Stroke, 2020)
BACKGROUND AND PURPOSE: For survivors of oral anticoagulation therapy (OAT)-associated intracerebral hemorrhage (OAT-ICH) who are at high risk for thromboembolism, the benefits of OAT resumption must be weighed against increased risk of recurrent hemorrhagic stroke. The ε2/ε4 alleles of the () gene, MRI-defined cortical superficial siderosis, and cerebral microbleeds are the most potent risk factors for recurrent ICH. We sought to determine whether combining MRI markers and genotype could have clinical impact by identifying ICH survivors in whom the risks of OAT resumption are highest. METHODS: Joint analysis of data from 2 longitudinal cohort studies of OAT-ICH survivors: (1) MGH-ICH study (Massachusetts General Hospital ICH) and (2) longitudinal component of the ERICH study (Ethnic/Racial Variations of Intracerebral Hemorrhage). We evaluated whether MRI markers and genotype predict ICH recurrence. We then developed and validated a combined -MRI classification scheme to predict ICH recurrence, using Classification and Regression Tree analysis. RESULTS: Cortical superficial siderosis, cerebral microbleed, and ε2/ε4 variants were independently associated with ICH recurrence after OAT-ICH (all <0.05). Combining genotype and MRI data resulted in improved prediction of ICH recurrence (Harrell C: 0.79 versus 0.55 for clinical data alone, =0.033). In the MGH (training) data set, CSS, cerebral microbleed, and ε2/ε4 stratified likelihood of ICH recurrence into high-, medium-, and low-risk categories. In the ERICH (validation) data set, yearly ICH recurrence rates for high-, medium-, and low-risk individuals were 6.6%, 2.5%, and 0.9%, respectively, with overall area under the curve of 0.91 for prediction of recurrent ICH. CONCLUSIONS: Combining MRI and genotype stratifies likelihood of ICH recurrence into high, medium, and low risk. If confirmed in prospective studies, this combined -MRI classification scheme may prove useful for selecting individuals for OAT resumption after ICH.
Keywords: Aged; Anticoagulants; Apolipoprotein E4; Cerebral Hemorrhage; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuroimaging; Recurrence

Community-based recruitment and exome sequencing indicates high diagnostic yield in adults with intellectual disability. - Sabo, Aniko; Murdock, David; Dugan, Shannon; Meng, Qingchang; Gingras, Marie-Claude; Hu, Jianhong; Muzny, Donna; Gibbs, Richard (Mol Genet Genomic Med, 2020)
BACKGROUND: Establishing a genetic diagnosis for individuals with intellectual disability (ID) benefits patients and their families as it may inform the prognosis, lead to appropriate therapy, and facilitate access to medical and supportive services. Exome sequencing has been successfully applied in a diagnostic setting, but most clinical exome referrals are pediatric patients, with many adults with ID lacking a comprehensive genetic evaluation. METHODS: Our unique recruitment strategy involved partnering with service and education providers for individuals with ID. We performed exome sequencing and analysis, and clinical variant interpretation for each recruited family. RESULTS: All five families enrolled in the study opted-in for the return of genetic results. In three out of five families exome sequencing analysis identified pathogenic or likely pathogenic variants in KANSL1, TUSC3, and MED13L genes. Families discussed the results and any potential medical follow-up in an appointment with a board certified clinical geneticist. CONCLUSION: Our study suggests high yield of exome sequencing as a diagnostic tool in adult patients with ID who have not undergone comprehensive sequencing-based genetic testing. Research studies including an option of return of results through a genetic clinic could help minimize the disparity in exome diagnostic testing between pediatric and adult patients with ID.
Keywords: Adult; Female; Genetic Testing; Humans; Independent Living; Intellectual Disability; Male; Mediator Complex; Membrane Proteins; Nuclear Proteins; Patient Selection; Sensitivity and Specificity; Tumor Suppressor Proteins; Whole Exome Sequencing

Congenital myasthenic syndrome with mild intellectual disability caused by a recurrent SLC25A1 variant. - Balaraju, Sunitha; Topf, Ana; McMacken, Grace; Kumar, Veeramani Preethish; Pechmann, Astrid; Roper, Helen; Vengalil, Seena; Polavarapu, Kiran; Nashi, Saraswati; MAHjan, Niranjan Prakash; Barbosa, Ines A; Deshpande, Charu; et al. (Eur J Hum Genet, 2020)
Congenital myasthenic syndromes (CMS) are a clinically and genetically heterogeneous group of disorders caused by mutations which lead to impaired neuromuscular transmission. SLC25A1 encodes a mitochondrial citrate carrier, associated mainly with the severe neurometabolic disease combined D-2- and L-2-hydroxyglutaric aciduria (D/L-2-HGA). We previously reported a single family with a homozygous missense variant in SLC25A1 with a phenotype restricted to relatively mild CMS with intellectual disability, but to date no additional cases of this CMS subtype had been reported. Here, we performed whole exome sequencing (WES) in three additional and unrelated families presenting with CMS and mild intellectual disability to identify the underlying causative gene. The WES analysis revealed the presence of a homozygous c.740G>A; p.(Arg247Gln) missense SLC25A1 variant, the same SLC25A1 variant as identified in the original family with this phenotype. Electron microscopy of muscle from two cases revealed enlarged and accumulated mitochondria. Haplotype analysis performed in two unrelated families suggested that this variant is a result of recurrent mutation and not a founder effect. This suggests that p.(Arg247Gln) is associated with a relatively mild CMS phenotype with subtle mitochondrial abnormalities, while other variants in this gene cause more severe neurometabolic disease. In conclusion, the p.(Arg247Gln) SLC25A1 variant should be considered in patients presenting with a presynaptic CMS phenotype, particularly with accompanying intellectual disability.
Keywords: Adult; Female; Haplotypes; Homozygote; Humans; Intellectual Disability; Male; Mitochondrial Proteins; Muscle, Skeletal; Mutation, Missense; Myasthenic Syndromes, Congenital; Organic Anion Transporters

Copy number variants and fixed duplications among 198 rhesus macaques (Macaca mulatta). - Brasó-Vives, Marina; Povolotskaya, Inna S; Hartasánchez, Diego A; Farré, Xavier; Fernandez-Callejo, Marcos; Raveendran, Muthuswamy; Harris, R Alan; Rosene, Douglas L; Lorente-Galdos, Belen; Navarro, Arcadi; Marques-Bonet, Tomas; Rogers, Jeffrey; et al. (PLoS Genet, 2020)
The rhesus macaque is an abundant species of Old World monkeys and a valuable model organism for biomedical research due to its close phylogenetic relationship to humans. Copy number variation is one of the main sources of genomic diversity within and between species and a widely recognized cause of inter-individual differences in disease risk. However, copy number differences among rhesus macaques and between the human and macaque genomes, as well as the relevance of this diversity to research involving this nonhuman primate, remain understudied. Here we present a high-resolution map of sequence copy number for the rhesus macaque genome constructed from a dataset of 198 individuals. Our results show that about one-eighth of the rhesus macaque reference genome is composed of recently duplicated regions, either copy number variable regions or fixed duplications. Comparison with human genomic copy number maps based on previously published data shows that, despite overall similarities in the genome-wide distribution of these regions, there are specific differences at the chromosome level. Some of these create differences in the copy number profile between human disease genes and their rhesus macaque orthologs. Our results highlight the importance of addressing the number of copies of target genes in the design of experiments and cautions against human-centered assumptions in research conducted with model organisms. Overall, we present a genome-wide copy number map from a large sample of rhesus macaque individuals representing an important novel contribution concerning the evolution of copy number in primate genomes.
Keywords: Animals; Chromosome Mapping; DNA Copy Number Variations; Female; Gene Duplication; Genetics, Population; Genome; High-Throughput Nucleotide Sequencing; Humans; Macaca mulatta; Male; Open Reading Frames; Phylogeny; Sequence Analysis, DNA; Species Specificity

Cytoplasmic "ciliary inclusions" in isolation are not sufficient for the diagnosis of primary ciliary dyskinesia. - Vece, Timothy J; Sagel, Scott D; Zariwala, Maimoona A; Sullivan, Kelli M; Burns, Kimberlie A; Dutcher, Susan K; Yusupov, Roman; Leigh, Margaret W; Knowles, Michael R (Pediatr Pulmonol, 2020)
BACKGROUND: The diagnosis of primary ciliary dyskinesia (PCD) is difficult and requires a combination of clinical features, nasal nitric oxide testing, cilia ultrastructural analysis by electron microscopy (EM), and genetics. A recently described cytoplasmic ultrastructural change termed "ciliary inclusions" was reported to be diagnostic of PCD; however, no supporting evidence of PCD was provided. In this study, we sought to confirm, or refute, the diagnosis of PCD in subjects with "ciliary inclusions" on EM. METHODS: Six subjects from five families with previous lab reports of "ciliary inclusions" on EMs of ciliated cells were identified and evaluated at a Genetic Disorders of Mucociliary Clearance Consortium site. We performed a detailed clinical history, nasal nitric oxide measurement, genetic testing including whole-exome sequencing (WES), and when possible, repeat ciliary EM study. RESULTS: Only one of six subjects had multiple and persistent clinical features congruent with PCD. No subject had situs inversus. Only one of six subjects had a very low nasal nitric oxide level. No "ciliary inclusions" were found in three subjects who had a repeat ciliary EM, and ciliary axonemal ultrastructures were normal. Genetic testing, including WES, was negative for PCD-causing genes, and for pathogenic variants in gene pathways that might cause "ciliary inclusions," such as ciliary biogenesis. CONCLUSION: "Ciliary Inclusions", in isolation, are not sufficient to diagnosis PCD. If seen, additional studies should be done to pursue an accurate diagnosis.
Keywords: Child, Preschool; Cilia; Ciliary Motility Disorders; Female; Genetic Testing; Humans; Infant; Male; Nasal Mucosa; Nitric Oxide; Whole Exome Sequencing

De novo and inherited variants in ZNF292 underlie a neurodevelopmental disorder with features of autism spectrum disorder. - Mirzaa, Ghayda M; Chong, Jessica X; Piton, Amélie; Popp, Bernt; Foss, Kimberly; Guo, Hui; Harripaul, Ricardo; Xia, Kun; Scheck, Joshua; Aldinger, Kimberly A; Sajan, Samin A; Tang, Sha; et al. (Genet Med, 2020)
PURPOSE: Intellectual disability (ID) and autism spectrum disorder (ASD) are genetically heterogeneous neurodevelopmental disorders. We sought to delineate the clinical, molecular, and neuroimaging spectrum of a novel neurodevelopmental disorder caused by variants in the zinc finger protein 292 gene (ZNF292). METHODS: We ascertained a cohort of 28 families with ID due to putatively pathogenic ZNF292 variants that were identified via targeted and exome sequencing. Available data were analyzed to characterize the canonical phenotype and examine genotype-phenotype relationships. RESULTS: Probands presented with ID as well as a spectrum of neurodevelopmental features including ASD, among others. All ZNF292 variants were de novo, except in one family with dominant inheritance. ZNF292 encodes a highly conserved zinc finger protein that acts as a transcription factor and is highly expressed in the developing human brain supporting its critical role in neurodevelopment. CONCLUSION: De novo and dominantly inherited variants in ZNF292 are associated with a range of neurodevelopmental features including ID and ASD. The clinical spectrum is broad, and most individuals present with mild to moderate ID with or without other syndromic features. Our results suggest that variants in ZNF292 are likely a recurrent cause of a neurodevelopmental disorder manifesting as ID with or without ASD.
Keywords: Adolescent; Autism Spectrum Disorder; Carrier Proteins; Child; Child, Preschool; Female; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Male; Nerve Tissue Proteins; Neurodevelopmental Disorders; Neuroimaging; Whole Exome Sequencing

De novo EIF2AK1 and EIF2AK2 Variants Are Associated with Developmental Delay, Leukoencephalopathy, and Neurologic Decompensation. - Mao, Dongxue; Reuter, Chloe M; Ruzhnikov, Maura R Z; Beck, Anita E; Farrow, Emily G; Emrick, Lisa T; Rosenfeld, Jill A; Mackenzie, Katherine M; Robak, Laurie; Wheeler, Matthew T; Burrage, Lindsay C; Jain, Mahim; et al. (Am J Hum Genet, 2020)
EIF2AK1 and EIF2AK2 encode members of the eukaryotic translation initiation factor 2 alpha kinase (EIF2AK) family that inhibits protein synthesis in response to physiologic stress conditions. EIF2AK2 is also involved in innate immune response and the regulation of signal transduction, apoptosis, cell proliferation, and differentiation. Despite these findings, human disorders associated with deleterious variants in EIF2AK1 and EIF2AK2 have not been reported. Here, we describe the identification of nine unrelated individuals with heterozygous de novo missense variants in EIF2AK1 (1/9) or EIF2AK2 (8/9). Features seen in these nine individuals include white matter alterations (9/9), developmental delay (9/9), impaired language (9/9), cognitive impairment (8/9), ataxia (6/9), dysarthria in probands with verbal ability (6/9), hypotonia (7/9), hypertonia (6/9), and involuntary movements (3/9). Individuals with EIF2AK2 variants also exhibit neurological regression in the setting of febrile illness or infection. We use mammalian cell lines and proband-derived fibroblasts to further confirm the pathogenicity of variants in these genes and found reduced kinase activity. EIF2AKs phosphorylate eukaryotic translation initiation factor 2 subunit 1 (EIF2S1, also known as EIF2α), which then inhibits EIF2B activity. Deleterious variants in genes encoding EIF2B proteins cause childhood ataxia with central nervous system hypomyelination/vanishing white matter (CACH/VWM), a leukodystrophy characterized by neurologic regression in the setting of febrile illness and other stressors. Our findings indicate that EIF2AK2 missense variants cause a neurodevelopmental syndrome that may share phenotypic and pathogenic mechanisms with CACH/VWM.
Keywords: Adolescent; Ataxia; Child; Child, Preschool; Developmental Disabilities; eIF-2 Kinase; Female; Genetic Variation; Hereditary Central Nervous System Demyelinating Diseases; Humans; Infant; Leukoencephalopathies; Male; Nervous System Malformations; White Matter

Defective glycosylation and multisystem abnormalities characterize the primary immunodeficiency XMEN disease. - Ravell, Juan C; Matsuda-Lennikov, Mami; Chauvin, Samuel D; Zou, Juan; Biancalana, Matthew; Deeb, Sally J; Price, Susan; Su, Helen C; Notarangelo, Giulia; Jiang, Ping; Morawski, Aaron; Kanellopoulou, Chrysi; et al. (J Clin Invest, 2020)
X-linked immunodeficiency with magnesium defect, EBV infection, and neoplasia (XMEN) disease are caused by deficiency of the magnesium transporter 1 (MAGT1) gene. We studied 23 patients with XMEN, 8 of whom were EBV naive. We observed lymphadenopathy (LAD), cytopenias, liver disease, cavum septum pellucidum (CSP), and increased CD4-CD8-B220-TCRαβ+ T cells (αβDNTs), in addition to the previously described features of an inverted CD4/CD8 ratio, CD4+ T lymphocytopenia, increased B cells, dysgammaglobulinemia, and decreased expression of the natural killer group 2, member D (NKG2D) receptor. EBV-associated B cell malignancies occurred frequently in EBV-infected patients. We studied patients with XMEN and patients with autoimmune lymphoproliferative syndrome (ALPS) by deep immunophenotyping (32 immune markers) using time-of-flight mass cytometry (CyTOF). Our analysis revealed that the abundance of 2 populations of naive B cells (CD20+CD27-CD22+IgM+HLA-DR+CXCR5+CXCR4++CD10+CD38+ and CD20+CD27-CD22+IgM+HLA-DR+CXCR5+CXCR4+CD10-CD38-) could differentially classify XMEN, ALPS, and healthy individuals. We also performed glycoproteomics analysis on T lymphocytes and show that XMEN disease is a congenital disorder of glycosylation that affects a restricted subset of glycoproteins. Transfection of MAGT1 mRNA enabled us to rescue proteins with defective glycosylation. Together, these data provide new clinical and pathophysiological foundations with important ramifications for the diagnosis and treatment of XMEN disease.
Keywords: Antigens, CD; Autoimmune Lymphoproliferative Syndrome; Cation Transport Proteins; CD4-CD8 Ratio; Female; Glycosylation; Humans; Magnesium Deficiency; Male; X-Linked Combined Immunodeficiency Diseases

Deficiencies in vesicular transport mediated by TRAPPC4 are associated with severe syndromic intellectual disability. - Van Bergen, Nicole J; Guo, Yiran; Al-Deri, Noraldin; Lipatova, Zhanna; Stanga, Daniela; Zhao, Sarah; Murtazina, Rakhilya; Gyurkovska, Valeriya; Pehlivan, Davut; Mitani, Tadahiro; Gezdirici, Alper; Antony, Jayne; et al. (Brain, 2020)
The conserved transport protein particle (TRAPP) complexes regulate key trafficking events and are required for autophagy. TRAPPC4, like its yeast Trs23 orthologue, is a core component of the TRAPP complexes and one of the essential subunits for guanine nucleotide exchange factor activity for Rab1 GTPase. Pathogenic variants in specific TRAPP subunits are associated with neurological disorders. We undertook exome sequencing in three unrelated families of Caucasian, Turkish and French-Canadian ethnicities with seven affected children that showed features of early-onset seizures, developmental delay, microcephaly, sensorineural deafness, spastic quadriparesis and progressive cortical and cerebellar atrophy in an effort to determine the genetic aetiology underlying neurodevelopmental disorders. All seven affected subjects shared the same identical rare, homozygous, potentially pathogenic variant in a non-canonical, well-conserved splice site within TRAPPC4 (hg19:chr11:g.118890966A>G; TRAPPC4: NM_016146.5; c.454+3A>G). Single nucleotide polymorphism array analysis revealed there was no haplotype shared between the tested Turkish and Caucasian families suggestive of a variant hotspot region rather than a founder effect. In silico analysis predicted the variant to cause aberrant splicing. Consistent with this, experimental evidence showed both a reduction in full-length transcript levels and an increase in levels of a shorter transcript missing exon 3, suggestive of an incompletely penetrant splice defect. TRAPPC4 protein levels were significantly reduced whilst levels of other TRAPP complex subunits remained unaffected. Native polyacrylamide gel electrophoresis and size exclusion chromatography demonstrated a defect in TRAPP complex assembly and/or stability. Intracellular trafficking through the Golgi using the marker protein VSVG-GFP-ts045 demonstrated significantly delayed entry into and exit from the Golgi in fibroblasts derived from one of the affected subjects. Lentiviral expression of wild-type TRAPPC4 in these fibroblasts restored trafficking, suggesting that the trafficking defect was due to reduced TRAPPC4 levels. Consistent with the recent association of the TRAPP complex with autophagy, we found that the fibroblasts had a basal autophagy defect and a delay in autophagic flux, possibly due to unsealed autophagosomes. These results were validated using a yeast trs23 temperature sensitive variant that exhibits constitutive and stress-induced autophagic defects at permissive temperature and a secretory defect at restrictive temperature. In summary we provide strong evidence for pathogenicity of this variant in a member of the core TRAPP subunit, TRAPPC4 that associates with vesicular trafficking and autophagy defects. This is the first report of a TRAPPC4 variant, and our findings add to the growing number of TRAPP-associated neurological disorders.
Keywords: Atrophy; Autophagy; Cerebellum; Cerebral Cortex; Child; Child, Preschool; Craniofacial Abnormalities; Deafness; Developmental Disabilities; Epilepsy; Female; Fibroblasts; Hearing Loss, Sensorineural; Humans; Infant; Infant, Newborn; Intellectual Disability; Male; Microcephaly; Microscopy, Fluorescence; Muscle Spasticity; Nerve Tissue Proteins; Neurodevelopmental Disorders; Pedigree; Quadriplegia; RNA Splice Sites; Syndrome; Vesicular Transport Proteins

Delineation of a Human Mendelian Disorder of the DNA Demethylation Machinery: TET3 Deficiency. - Beck, David B; Petracovici, Ana; He, Chongsheng; Moore, Hannah W; Louie, Raymond J; Ansar, Muhammad; Douzgou, Sofia; Sithambaram, Sivagamy; Cottrell, Trudie; Santos-Cortez, Regie Lyn P; Prijoles, Eloise J; Bend, Renee; et al. (Am J Hum Genet, 2020)
Germline pathogenic variants in chromatin-modifying enzymes are a common cause of pediatric developmental disorders. These enzymes catalyze reactions that regulate epigenetic inheritance via histone post-translational modifications and DNA methylation. Cytosine methylation (5-methylcytosine [5mC]) of DNA is the quintessential epigenetic mark, yet no human Mendelian disorder of DNA demethylation has yet been delineated. Here, we describe in detail a Mendelian disorder caused by the disruption of DNA demethylation. TET3 is a methylcytosine dioxygenase that initiates DNA demethylation during early zygote formation, embryogenesis, and neuronal differentiation and is intolerant to haploinsufficiency in mice and humans. We identify and characterize 11 cases of human TET3 deficiency in eight families with the common phenotypic features of intellectual disability and/or global developmental delay; hypotonia; autistic traits; movement disorders; growth abnormalities; and facial dysmorphism. Mono-allelic frameshift and nonsense variants in TET3 occur throughout the coding region. Mono-allelic and bi-allelic missense variants localize to conserved residues; all but one such variant occur within the catalytic domain, and most display hypomorphic function in an assay of catalytic activity. TET3 deficiency and other Mendelian disorders of the epigenetic machinery show substantial phenotypic overlap, including features of intellectual disability and abnormal growth, underscoring shared disease mechanisms.
Keywords: Adult; Amino Acid Sequence; Autistic Disorder; Child; Child, Preschool; Developmental Disabilities; Dioxygenases; DNA Demethylation; Embryonic Development; Female; Gene Expression Regulation, Developmental; Growth Disorders; Humans; Infant; Male; Middle Aged; Movement Disorders; Pedigree; Protein Conformation; Sequence Homology; Young Adult

Dominant-negative mutations in human IL6ST underlie hyper-IgE syndrome. - Béziat, Vivien; Tavernier, Simon J; Chen, Yin-Huai; Ma, Cindy S; Materna, Marie; Laurence, Arian; Staal, Jens; Aschenbrenner, Dominik; Roels, Lisa; Worley, Lisa; Claes, Kathleen; Gartner, Lisa; et al. (J Exp Med, 2020)
Autosomal dominant hyper-IgE syndrome (AD-HIES) is typically caused by dominant-negative (DN) STAT3 mutations. Patients suffer from cold staphylococcal lesions and mucocutaneous candidiasis, severe allergy, and skeletal abnormalities. We report 12 patients from 8 unrelated kindreds with AD-HIES due to DN IL6ST mutations. We identified seven different truncating mutations, one of which was recurrent. The mutant alleles encode GP130 receptors bearing the transmembrane domain but lacking both the recycling motif and all four STAT3-recruiting tyrosine residues. Upon overexpression, the mutant proteins accumulate at the cell surface and are loss of function and DN for cellular responses to IL-6, IL-11, LIF, and OSM. Moreover, the patients' heterozygous leukocytes and fibroblasts respond poorly to IL-6 and IL-11. Consistently, patients with STAT3 and IL6ST mutations display infectious and allergic manifestations of IL-6R deficiency, and some of the skeletal abnormalities of IL-11R deficiency. DN STAT3 and IL6ST mutations thus appear to underlie clinical phenocopies through impairment of the IL-6 and IL-11 response pathways.
Keywords: Adolescent; Alleles; C-Reactive Protein; Cell Membrane; Cells, Cultured; Child; Cytokine Receptor gp130; Cytokines; Female; Fibroblasts; Genes, Dominant; Genetics, Population; HEK293 Cells; Humans; Job Syndrome; Kinetics; Loss of Function Mutation; Male; Middle Aged; Models, Biological; Mutation; Pedigree; Phenotype; Th2 Cells; Up-Regulation; Young Adult

Epilepsy subtype-specific copy number burden observed in a genome-wide study of 17 458 subjects. - Niestroj, Lisa-Marie; Perez-Palma, Eduardo; Howrigan, Daniel P; Zhou, Yadi; Cheng, Feixiong; Saarentaus, Elmo; Nürnberg, Peter; Stevelink, Remi; Daly, Mark J; Palotie, Aarno; Lal, Dennis (Brain, 2020)
Cytogenic testing is routinely applied in most neurological centres for severe paediatric epilepsies. However, which characteristics of copy number variants (CNVs) confer most epilepsy risk and which epilepsy subtypes carry the most CNV burden, have not been explored on a genome-wide scale. Here, we present the largest CNV investigation in epilepsy to date with 10 712 European epilepsy cases and 6746 ancestry-matched controls. Patients with genetic generalized epilepsy, lesional focal epilepsy, non-acquired focal epilepsy, and developmental and epileptic encephalopathy were included. All samples were processed with the same technology and analysis pipeline. All investigated epilepsy types, including lesional focal epilepsy patients, showed an increase in CNV burden in at least one tested category compared to controls. However, we observed striking differences in CNV burden across epilepsy types and investigated CNV categories. Genetic generalized epilepsy patients have the highest CNV burden in all categories tested, followed by developmental and epileptic encephalopathy patients. Both epilepsy types also show association for deletions covering genes intolerant for truncating variants. Genome-wide CNV breakpoint association showed not only significant loci for genetic generalized and developmental and epileptic encephalopathy patients but also for lesional focal epilepsy patients. With a 34-fold risk for developing genetic generalized epilepsy, we show for the first time that the established epilepsy-associated 15q13.3 deletion represents the strongest risk CNV for genetic generalized epilepsy across the whole genome. Using the human interactome, we examined the largest connected component of the genes overlapped by CNVs in the four epilepsy types. We observed that genetic generalized epilepsy and non-acquired focal epilepsy formed disease modules. In summary, we show that in all common epilepsy types, 1.5-3% of patients carry epilepsy-associated CNVs. The characteristics of risk CNVs vary tremendously across and within epilepsy types. Thus, we advocate genome-wide genomic testing to identify all disease-associated types of CNVs.
Keywords: DNA Copy Number Variations; Epilepsy; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male

Estimation of the carrier frequency of fumarate hydratase alterations and implications for kidney cancer risk in hereditary leiomyomatosis and renal cancer. - Shuch, Brian; Li, Shantao; Risch, Harvey; Bindra, Ranjit S; McGillivray, Patrick D; Gerstein, Mark (Cancer, 2020)
BACKGROUND: Hereditary leiomyomatosis and renal cancer (HLRCC) is a cancer syndrome associated with a germline mutation in fumarate hydratase (FH). The syndrome is associated with cutaneous and uterine leiomyomas, and some patients develop a lethal form of kidney cancer. This study provides estimates for the FH carrier frequency and kidney cancer penetrance. METHODS: Data sets containing sequencing data for the FH gene were used: the 1000 Genomes Project (1000GP) and the Exome Aggregation Consortium (ExAC). Alterations in the FH gene were characterized on the basis of different variant risk tiers: 1) ClinVar annotated variants, 2) loss-of-function alterations, and 3) highly impactful missense alterations. The cumulative incidence of FH alterations overall and by different world populations was evaluated in 1000GP and ExAC. A lifetime penetrance of HLRCC kidney cancer risk was generated with 3 estimates of the annual incidence. RESULTS: The overall allele frequencies of tier 1 to 3 FH alterations in the ExAC and 1000GP data sets were 2.54 × 10 (1 in 393) and 1.20 × 10 (1 in 835), respectively. There were differences in the allele frequencies of FH alterations between world populations. Based on various estimates of the percentage of kidney cancers with FH alterations, the lifetime kidney cancer penetrance for carrier estimate 3 in ExAC was 1.7% to 5.8%. CONCLUSIONS: FH alterations are common and are carried by approximately 1 in 1000 individuals according to the more conservative estimates. The lifetime kidney cancer penetrance appears lower than previously estimated. Although databases are not population cohorts, they provide a useful quantitative estimate of rare variants with low penetrance.
Keywords: Adult; Exome; Female; Fumarate Hydratase; Gene Frequency; Genetic Predisposition to Disease; Germ-Line Mutation; Heterozygote; Humans; Kidney; Kidney Neoplasms; Leiomyomatosis; Male; Middle Aged; Neoplastic Syndromes, Hereditary; Risk Factors; Skin Neoplasms; Uterine Neoplasms

Exome sequencing implicates genetic disruption of prenatal neuro-gliogenesis in sporadic congenital hydrocephalus. - Jin, Sheng Chih; Dong, Weilai; Kundishora, Adam J; Panchagnula, Shreyas; Moreno-De-Luca, Andres; Furey, Charuta G; Allocco, August A; Walker, Rebecca L; Nelson-Williams, Carol; Smith, Hannah; Dunbar, Ashley; Conine, Sierra; et al. (Nat Med, 2020)
Congenital hydrocephalus (CH), characterized by enlarged brain ventricles, is considered a disease of excessive cerebrospinal fluid (CSF) accumulation and thereby treated with neurosurgical CSF diversion with high morbidity and failure rates. The poor neurodevelopmental outcomes and persistence of ventriculomegaly in some post-surgical patients highlight our limited knowledge of disease mechanisms. Through whole-exome sequencing of 381 patients (232 trios) with sporadic, neurosurgically treated CH, we found that damaging de novo mutations account for >17% of cases, with five different genes exhibiting a significant de novo mutation burden. In all, rare, damaging mutations with large effect contributed to ~22% of sporadic CH cases. Multiple CH genes are key regulators of neural stem cell biology and converge in human transcriptional networks and cell types pertinent for fetal neuro-gliogenesis. These data implicate genetic disruption of early brain development, not impaired CSF dynamics, as the primary pathomechanism of a significant number of patients with sporadic CH.
Keywords: Brain; Cerebral Ventricles; Exome; Female; Genetic Predisposition to Disease; Humans; Hydrocephalus; Male; Mutation; Neural Stem Cells; Neurogenesis; Neuroglia; Transcription Factors; Tripartite Motif Proteins; Ubiquitin-Protein Ligases; Whole Exome Sequencing

Exome sequencing reveals a novel variant in causing intracranial aneurysm in a Chinese family. - Ding, Xinghuan; Zhao, Sen; Zhang, Qianqian; Yan, Zihui; Wang, Yang; Wu, Yong; Li, Xiaoxin; Liu, Jian; Niu, Yuchen; Zhang, Yisen; Zhang, Mingqi; Wang, Huizi; et al. (J Neurointerv Surg, 2020)
BACKGROUND: Genetic risk factors play an important role in the pathogenesis of familial intracranial aneurysms (FIAs); however, the molecular mechanisms remain largely unknown. OBJECTIVE: To investigate potential FIA-causing genetic variants by rare variant interrogation and a family-based genomics approach in a large family with an extensive multigenerational pedigree with FIAs. METHOD: Exome sequencing (ES) was performed in a dominant likely family with intracranial aneurysms (IAs). Variants were analyzed by an in-house developed pipeline and prioritized using various filtering strategies, including population frequency, variant type, and predicted variant pathogenicity. Sanger sequencing was also performed to evaluate the segregation of the variants with the phenotype. RESULTS: Based on the ES data obtained from five individuals from a family with 7/21 living members affected with IAs, a total of 14 variants were prioritized as candidate variants. Familial segregation analysis revealed that c.2519T>C (p.Leu840Pro) segregated in accordance with Mendelian expectations with the phenotype within the family-that is, present in all IA-affected cases and absent from all unaffected members of the second generation. This missense variant is absent from public databases (1000genome, ExAC, gnomAD, ESP5400), and has damaging predictions by bioinformatics tools (Gerp ++ score = 5.88, CADD score = 16.43, MutationTaster score = 1, LRT score = 0). In addition, 840Leu in NFX1 is robustly conserved in mammals and maps in a region before the RING-type zinc finger domain. CONCLUSION: c.2519T>C (p.Leu840Pro) may contribute to the pathogenetics of a subset of FIAs.
Keywords: Adult; Asian Continental Ancestry Group; Computational Biology; Exome; Female; Genetic Variation; Humans; Intracranial Aneurysm; Male; Middle Aged; Pedigree; Phenotype; Repressor Proteins

Expanding the phenotypic spectrum in RDH12-associated retinal disease. - Scott, Hilary A; Place, Emily M; Ferenchak, Kevin; Zampaglione, Erin; Wagner, Naomi E; Chao, Katherine R; DiTroia, Stephanie P; Navarro-Gomez, Daniel; Mukai, Shizuo; Huckfeldt, Rachel M; Pierce, Eric A; Bujakowska, Kinga M (Cold Spring Harb Mol Case Stud, 2020)
Retinol dehydrogenase 12, RDH12, plays a pivotal role in the visual cycle to ensure the maintenance of normal vision. Alterations in activity of this protein result in photoreceptor death and decreased vision beginning at an early age and progressing to substantial vision loss later in life. Here we describe 11 patients with retinal degeneration that underwent next-generation sequencing (NGS) with a targeted panel of all currently known inherited retinal degeneration (IRD) genes and whole-exome sequencing to identify the genetic causality of their retinal disease. These patients display a range of phenotypic severity prompting clinical diagnoses of macular dystrophy, cone-rod dystrophy, retinitis pigmentosa, and early-onset severe retinal dystrophy all attributed to biallelic recessive mutations in We report 15 causal alleles and expand the repertoire of known mutations with four novel variants: c.215A > G (p.Asp72Gly); c.362T > C (p.Ile121Thr); c.440A > C (p.Asn147Thr); and c.697G > A (p.Val233Ille). The broad phenotypic spectrum observed with biallelic mutations has been observed in other genetic forms of IRDs, but the diversity is particularly notable here given the prior association of primarily with severe early-onset disease. This breadth emphasizes the importance of broad genetic testing for inherited retinal disorders and extends the pool of individuals who may benefit from imminent gene-targeted therapies.
Keywords: Adolescent; Adult; Alcohol Oxidoreductases; Alleles; Amino Acid Substitution; Child; Child, Preschool; Female; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Humans; Male; Mutation; Optical Imaging; Pedigree; Phenotype; Retinal Diseases; Tomography, Optical Coherence; Whole Exome Sequencing; Young Adult

Functional biology of the Steel syndrome founder allele and evidence for clan genomics derivation of COL27A1 pathogenic alleles worldwide. - Gonzaga-Jauregui, Claudia; Yesil, Gözde; Nistala, Harikiran; Gezdirici, Alper; Bayram, Yavuz; Nannuru, Kalyan C; Pehlivan, Davut; Yuan, Bo; Jimenez, Johanna; Sahin, Yavuz; Paine, Ingrid S; Akdemir, Zeynep Coban; et al. (Eur J Hum Genet, 2020)
Previously we reported the identification of a homozygous COL27A1 (c.2089G>C; p.Gly697Arg) missense variant and proposed it as a founder allele in Puerto Rico segregating with Steel syndrome (STLS, MIM #615155); a rare osteochondrodysplasia characterized by short stature, congenital bilateral hip dysplasia, carpal coalitions, and scoliosis. We now report segregation of this variant in five probands from the initial clinical report defining the syndrome and an additional family of Puerto Rican descent with multiple affected adult individuals. We modeled the orthologous variant in murine Col27a1 and found it recapitulates some of the major Steel syndrome associated skeletal features including reduced body length, scoliosis, and a more rounded skull shape. Characterization of the in vivo murine model shows abnormal collagen deposition in the extracellular matrix and disorganization of the proliferative zone of the growth plate. We report additional COL27A1 pathogenic variant alleles identified in unrelated consanguineous Turkish kindreds suggesting Clan Genomics and identity-by-descent homozygosity contributing to disease in this population. The hypothesis that carrier states for this autosomal recessive osteochondrodysplasia may contribute to common complex traits is further explored in a large clinical population cohort. Our findings augment our understanding of COL27A1 biology and its role in skeletal development; and expand the functional allelic architecture in this gene underlying both rare and common disease phenotypes.
Keywords: Abnormalities, Multiple; Adolescent; Animals; Bone Development; Child; Child, Preschool; Consanguinity; Extracellular Matrix; Female; Fibrillar Collagens; Founder Effect; Gene Frequency; Hip Dislocation; Homozygote; Humans; Male; Mice; Mice, Inbred C57BL; Mutation; Pedigree; Scoliosis; Syndrome

Gene-based analyses of the maternal genome implicate maternal effect genes as risk factors for conotruncal heart defects. - Sewda, Anshuman; Agopian, A J; Goldmuntz, Elizabeth; Hakonarson, Hakon; Morrow, Bernice E; Musfee, Fadi; Taylor, Deanne; Mitchell, Laura E (PLoS One, 2020)
Congenital heart defects (CHDs) affect approximately 1% of newborns. Epidemiological studies have identified several genetically-mediated maternal phenotypes (e.g., pregestational diabetes, chronic hypertension) that are associated with the risk of CHDs in offspring. However, the role of the maternal genome in determining CHD risk has not been defined. We present findings from gene-level, genome-wide studies that link CHDs to maternal effect genes as well as to maternal genes related to hypertension and proteostasis. Maternal effect genes, which provide the mRNAs and proteins in the oocyte that guide early embryonic development before zygotic gene activation, have not previously been implicated in CHD risk. Our findings support a role for and suggest new pathways by which the maternal genome may contribute to the development of CHDs in offspring.
Keywords: Adult; Case-Control Studies; Child, Preschool; Family; Female; Genetic Testing; Heart Defects, Congenital; Humans; Hypertension; Infant; Infant, Newborn; Male; Maternal Exposure; Maternal Inheritance; Middle Aged; Oocytes; Pregnancy; Prenatal Exposure Delayed Effects; Proteostasis; Risk Factors

Genetic diagnoses in epilepsy: The impact of dynamic exome analysis in a pediatric cohort. - Rochtus, Anne; Olson, Heather E; Smith, Lacey; Keith, Louisa G; El Achkar, Christelle; Taylor, Alan; Mahida, Sonal; Park, Meredith; Kelly, McKenna; Shain, Catherine; Rockowitz, Shira; Rosen Sheidley, Beth; et al. (Epilepsia, 2020)
OBJECTIVE: We evaluated the yield of systematic analysis and/or reanalysis of whole exome sequencing (WES) data from a cohort of well-phenotyped pediatric patients with epilepsy and suspected but previously undetermined genetic etiology. METHODS: We identified and phenotyped 125 participants with pediatric epilepsy. Etiology was unexplained at the time of enrollment despite clinical testing, which included chromosomal microarray (57 patients), epilepsy gene panel (n = 48), both (n = 28), or WES (n = 8). Clinical epilepsy diagnoses included developmental and epileptic encephalopathy (DEE), febrile infection-related epilepsy syndrome, Rasmussen encephalitis, and other focal and generalized epilepsies. We analyzed WES data and compared the yield in participants with and without prior clinical genetic testing. RESULTS: Overall, we identified pathogenic or likely pathogenic variants in 40% (50/125) of our study participants. Nine patients with DEE had genetic variants in recently published genes that had not been recognized as epilepsy-related at the time of clinical testing (FGF12, GABBR1, GABBR2, ITPA, KAT6A, PTPN23, RHOBTB2, SATB2), and eight patients had genetic variants in candidate epilepsy genes (CAMTA1, FAT3, GABRA6, HUWE1, PTCHD1). Ninety participants had concomitant or subsequent clinical genetic testing, which was ultimately explanatory for 26% (23/90). Of the 67 participants whose molecular diagnoses were "unsolved" through clinical genetic testing, we identified pathogenic or likely pathogenic variants in 17 (25%). SIGNIFICANCE: Our data argue for early consideration of WES with iterative reanalysis for patients with epilepsy, particularly those with DEE or epilepsy with intellectual disability. Rigorous analysis of WES data of well-phenotyped patients with epilepsy leads to a broader understanding of gene-specific phenotypic spectra as well as candidate disease gene identification. We illustrate the dynamic nature of genetic diagnosis over time, with analysis and in some cases reanalysis of exome data leading to the identification of disease-associated variants among participants with previously nondiagnostic results from a variety of clinical testing strategies.
Keywords: Adolescent; Adult; Age of Onset; Brain Diseases; Child; Child, Preschool; Chromosomes, Human; Cohort Studies; Epilepsy; Epilepsy, Generalized; Exome; Female; Genetic Testing; Genetic Variation; Humans; Infant; Male; Microarray Analysis; Phenotype; Whole Exome Sequencing; Young Adult

Genetics of schizophrenia in the South African Xhosa. - Gulsuner, S; Stein, D J; Susser, E S; Sibeko, G; Pretorius, A; Walsh, T; Majara, L; Mndini, M M; Mqulwana, S G; Ntola, O A; Casadei, S; Ngqengelele, L L; et al. (Science, 2020)
Africa, the ancestral home of all modern humans, is the most informative continent for understanding the human genome and its contribution to complex disease. To better understand the genetics of schizophrenia, we studied the illness in the Xhosa population of South Africa, recruiting 909 cases and 917 age-, gender-, and residence-matched controls. Individuals with schizophrenia were significantly more likely than controls to harbor private, severely damaging mutations in genes that are critical to synaptic function, including neural circuitry mediated by the neurotransmitters glutamine, γ-aminobutyric acid, and dopamine. Schizophrenia is genetically highly heterogeneous, involving severe ultrarare mutations in genes that are critical to synaptic plasticity. The depth of genetic variation in Africa revealed this relationship with a moderate sample size and informed our understanding of the genetics of schizophrenia worldwide.
Keywords: Age Factors; Autistic Disorder; Bipolar Disorder; Dopamine; Female; gamma-Aminobutyric Acid; Genetic Variation; Glutamine; Humans; Male; Mutation; Neural Pathways; Schizophrenia; Sex Factors; South Africa; Synapses; Synaptic Transmission

Genome-Wide Polygenic Score, Clinical Risk Factors, and Long-Term Trajectories of Coronary Artery Disease. - Hindy, George; Aragam, Krishna G; Ng, Kenney; Chaffin, Mark; Lotta, Luca A; Baras, Aris; Drake, Isabel; Orho-Melander, Marju; Melander, Olle; Kathiresan, Sekar; Khera, Amit V (Arterioscler Thromb Vasc Biol, 2020)
OBJECTIVE: To determine the relationship of a genome-wide polygenic score for coronary artery disease (GPS) with lifetime trajectories of CAD risk, directly compare its predictive capacity to traditional risk factors, and assess its interplay with the Pooled Cohort Equations (PCE) clinical risk estimator. Approach and Results: We studied GPS in 28 556 middle-aged participants of the Malmö Diet and Cancer Study, of whom 4122 (14.4%) developed CAD over a median follow-up of 21.3 years. A pronounced gradient in lifetime risk of CAD was observed-16% for those in the lowest GPS decile to 48% in the highest. We evaluated the discriminative capacity of the GPS-as assessed by change in the C-statistic from a baseline model including age and sex-among 5685 individuals with PCE risk estimates available. The increment for the GPS (+0.045, <0.001) was higher than for any of 11 traditional risk factors (range +0.007 to +0.032). Minimal correlation was observed between GPS and 10-year risk defined by the PCE (=0.03), and addition of GPS improved the C-statistic of the PCE model by 0.026. A significant gradient in lifetime risk was observed for the GPS, even among individuals within a given PCE clinical risk stratum. We replicated key findings-noting strikingly consistent results-in 325 003 participants of the UK Biobank. CONCLUSIONS: GPS-a risk estimator available from birth-stratifies individuals into varying trajectories of clinical risk for CAD. Implementation of GPS may enable identification of high-risk individuals early in life, decades in advance of manifest risk factors or disease.
Keywords: Adult; Aged; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Heart Disease Risk Factors; Heredity; Humans; Incidence; Male; Middle Aged; Multifactorial Inheritance; Phenotype; Prognosis; Risk Assessment; Sweden; Time Factors; United Kingdom

The GTEx Consortium atlas of genetic regulatory effects across human tissues. (Science, 2020)
The Genotype-Tissue Expression (GTEx) project was established to characterize genetic effects on the transcriptome across human tissues and to link these regulatory mechanisms to trait and disease associations. Here, we present analyses of the version 8 data, examining 15,201 RNA-sequencing samples from 49 tissues of 838 postmortem donors. We comprehensively characterize genetic associations for gene expression and splicing in cis and trans, showing that regulatory associations are found for almost all genes, and describe the underlying molecular mechanisms and their contribution to allelic heterogeneity and pleiotropy of complex traits. Leveraging the large diversity of tissues, we provide insights into the tissue specificity of genetic effects and show that cell type composition is a key factor in understanding gene regulatory mechanisms in human tissues.
Keywords: Datasets as Topic; Disease; Female; Gene Expression Regulation; Genome-Wide Association Study; Humans; Male; Organ Specificity; Quantitative Trait Loci; Sequence Analysis, RNA

Human CRY1 variants associate with attention deficit/hyperactivity disorder. - Onat, O Emre; Kars, M Ece; Gül, Şeref; Bilguvar, Kaya; Wu, Yiming; Özhan, Ayşe; Aydın, Cihan; Başak, A Nazlı; Trusso, M Allegra; Goracci, Arianna; Fallerini, Chiara; Renieri, Alessandra; et al. (J Clin Invest, 2020)
Attention deficit/hyperactivity disorder (ADHD) is a common and heritable phenotype frequently accompanied by insomnia, anxiety, and depression. Here, using a reverse phenotyping approach, we report heterozygous coding variations in the core circadian clock gene cryptochrome 1 in 15 unrelated multigenerational families with combined ADHD and insomnia. The variants led to functional alterations in the circadian molecular rhythms, providing a mechanistic link to the behavioral symptoms. One variant, CRY1Δ11 c.1657+3A>C, is present in approximately 1% of Europeans, therefore standing out as a diagnostic and therapeutic marker. We showed by exome sequencing in an independent cohort of patients with combined ADHD and insomnia that 8 of 62 patients and 0 of 369 controls carried CRY1Δ11. Also, we identified a variant, CRY1Δ6 c.825+1G>A, that shows reduced affinity for BMAL1/CLOCK and causes an arrhythmic phenotype. Genotype-phenotype correlation analysis revealed that this variant segregated with ADHD and delayed sleep phase disorder (DSPD) in the affected family. Finally, we found in a phenome-wide association study involving 9438 unrelated adult Europeans that CRY1Δ11 was associated with major depressive disorder, insomnia, and anxiety. These results defined a distinctive group of circadian psychiatric phenotypes that we propose to designate as "circiatric" disorders.
Keywords: Adult; ARNTL Transcription Factors; Attention Deficit Disorder with Hyperactivity; CLOCK Proteins; Cryptochromes; Female; Genetic Association Studies; HEK293 Cells; Humans; Male; Mutation; Sleep Disorders, Circadian Rhythm

Human NK cell deficiency as a result of biallelic mutations in MCM10. - Mace, Emily M; Paust, Silke; Conte, Matilde I; Baxley, Ryan M; Schmit, Megan M; Patil, Sagar L; Guilz, Nicole C; Mukherjee, Malini; Pezzi, Ashley E; Chmielowiec, Jolanta; Tatineni, Swetha; Chinn, Ivan K; et al. (J Clin Invest, 2020)
Human natural killer cell deficiency (NKD) arises from inborn errors of immunity that lead to impaired NK cell development, function, or both. Through the understanding of the biological perturbations in individuals with NKD, requirements for the generation of terminally mature functional innate effector cells can be elucidated. Here, we report a cause of NKD resulting from compound heterozygous mutations in minichromosomal maintenance complex member 10 (MCM10) that impaired NK cell maturation in a child with fatal susceptibility to CMV. MCM10 has not been previously associated with monogenic disease and plays a critical role in the activation and function of the eukaryotic DNA replisome. Through evaluation of patient primary fibroblasts, modeling patient mutations in fibroblast cell lines, and MCM10 knockdown in human NK cell lines, we have shown that loss of MCM10 function leads to impaired cell cycle progression and induction of DNA damage-response pathways. By modeling MCM10 deficiency in primary NK cell precursors, including patient-derived induced pluripotent stem cells, we further demonstrated that MCM10 is required for NK cell terminal maturation and acquisition of immunological system function. Together, these data define MCM10 as an NKD gene and provide biological insight into the requirement for the DNA replisome in human NK cell maturation and function.
Keywords: Alleles; Cell Cycle Checkpoints; Cell Differentiation; Cell Line; Codon, Nonsense; DNA Damage; Fatal Outcome; Female; Gene Knockdown Techniques; Heterozygote; Humans; Induced Pluripotent Stem Cells; Infant; Killer Cells, Natural; Male; Minichromosome Maintenance Proteins; Models, Immunological; Mutation; Mutation, Missense; Pedigree; Primary Immunodeficiency Diseases

The impact of sex on gene expression across human tissues. - Oliva, Meritxell; Muñoz-Aguirre, Manuel; Kim-Hellmuth, Sarah; Wucher, Valentin; Gewirtz, Ariel D H; Cotter, Daniel J; Parsana, Princy; Kasela, Silva; Balliu, Brunilda; Viñuela, Ana; Castel, Stephane E; Mohammadi, Pejman; et al. (Science, 2020)
Many complex human phenotypes exhibit sex-differentiated characteristics. However, the molecular mechanisms underlying these differences remain largely unknown. We generated a catalog of sex differences in gene expression and in the genetic regulation of gene expression across 44 human tissue sources surveyed by the Genotype-Tissue Expression project (GTEx, v8 release). We demonstrate that sex influences gene expression levels and cellular composition of tissue samples across the human body. A total of 37% of all genes exhibit sex-biased expression in at least one tissue. We identify cis expression quantitative trait loci (eQTLs) with sex-differentiated effects and characterize their cellular origin. By integrating sex-biased eQTLs with genome-wide association study data, we identify 58 gene-trait associations that are driven by genetic regulation of gene expression in a single sex. These findings provide an extensive characterization of sex differences in the human transcriptome and its genetic regulation.
Keywords: Chromosomes, Human, X; Disease; Epigenesis, Genetic; Female; Gene Expression; Gene Expression Regulation; Genetic Variation; Genome-Wide Association Study; Humans; Male; Organ Specificity; Promoter Regions, Genetic; Quantitative Trait Loci; Sex Characteristics; Sex Factors

Inborn errors of type I IFN immunity in patients with life-threatening COVID-19. - Zhang, Qian; Bastard, Paul; Liu, Zhiyong; Le Pen, Jérémie; Moncada-Velez, Marcela; Chen, Jie; Ogishi, Masato; Sabli, Ira K D; Hodeib, Stephanie; Korol, Cecilia; Rosain, Jérémie; Bilguvar, Kaya; et al. (Science, 2020)
Clinical outcome upon infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) ranges from silent infection to lethal coronavirus disease 2019 (COVID-19). We have found an enrichment in rare variants predicted to be loss-of-function (LOF) at the 13 human loci known to govern Toll-like receptor 3 (TLR3)- and interferon regulatory factor 7 (IRF7)-dependent type I interferon (IFN) immunity to influenza virus in 659 patients with life-threatening COVID-19 pneumonia relative to 534 subjects with asymptomatic or benign infection. By testing these and other rare variants at these 13 loci, we experimentally defined LOF variants underlying autosomal-recessive or autosomal-dominant deficiencies in 23 patients (3.5%) 17 to 77 years of age. We show that human fibroblasts with mutations affecting this circuit are vulnerable to SARS-CoV-2. Inborn errors of TLR3- and IRF7-dependent type I IFN immunity can underlie life-threatening COVID-19 pneumonia in patients with no prior severe infection.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alleles; Asymptomatic Infections; Betacoronavirus; Child; Child, Preschool; Coronavirus Infections; COVID-19; Female; Genetic Loci; Genetic Predisposition to Disease; Humans; Infant; Interferon Regulatory Factor-7; Interferon Type I; Loss of Function Mutation; Male; Middle Aged; Pandemics; Pneumonia, Viral; Receptor, Interferon alpha-beta; SARS-CoV-2; Toll-Like Receptor 3; Young Adult

Inherited causes of clonal haematopoiesis in 97,691 whole genomes. - Bick, Alexander G; Weinstock, Joshua S; Nandakumar, Satish K; Fulco, Charles P; Bao, Erik L; Zekavat, Seyedeh M; Szeto, Mindy D; Liao, Xiaotian; Leventhal, Matthew J; Nasser, Joseph; Chang, Kyle; Laurie, Cecelia; et al. (Nature, 2020)
Age is the dominant risk factor for most chronic human diseases, but the mechanisms through which ageing confers this risk are largely unknown. The age-related acquisition of somatic mutations that lead to clonal expansion in regenerating haematopoietic stem cell populations has recently been associated with both haematological cancer and coronary heart disease-this phenomenon is termed clonal haematopoiesis of indeterminate potential (CHIP). Simultaneous analyses of germline and somatic whole-genome sequences provide the opportunity to identify root causes of CHIP. Here we analyse high-coverage whole-genome sequences from 97,691 participants of diverse ancestries in the National Heart, Lung, and Blood Institute Trans-omics for Precision Medicine (TOPMed) programme, and identify 4,229 individuals with CHIP. We identify associations with blood cell, lipid and inflammatory traits that are specific to different CHIP driver genes. Association of a genome-wide set of germline genetic variants enabled the identification of three genetic loci associated with CHIP status, including one locus at TET2 that was specific to individuals of African ancestry. In silico-informed in vitro evaluation of the TET2 germline locus enabled the identification of a causal variant that disrupts a TET2 distal enhancer, resulting in increased self-renewal of haematopoietic stem cells. Overall, we observe that germline genetic variation shapes haematopoietic stem cell function, leading to CHIP through mechanisms that are specific to clonal haematopoiesis as well as shared mechanisms that lead to somatic mutations across tissues.
Keywords: Adult; Africa; African Continental Ancestry Group; Aged; Aged, 80 and over; alpha Karyopherins; Cell Self Renewal; Clonal Hematopoiesis; DNA-Binding Proteins; Female; Genetic Predisposition to Disease; Genome, Human; Germ-Line Mutation; Hematopoietic Stem Cells; Humans; Intracellular Signaling Peptides and Proteins; Male; Middle Aged; National Heart, Lung, and Blood Institute (U.S.); Phenotype; Precision Medicine; Proto-Oncogene Proteins; Tripartite Motif Proteins; United States; Whole Genome Sequencing

Inherited glomerular diseases in the gilded age of genomic advancements. - Gulati, Ashima; Dahl, Neera; Tufro, Alda (Pediatr Nephrol, 2020)
The synchronized advent of high-throughput next-generation sequencing technology and knowledge of the human genome has rendered exponential contributions to our understanding of the pathophysiology of glomerular kidney diseases. A genetic diagnosis can now be made or confirmed in about two-thirds of the suspected inherited glomerular diseases. Next-generation sequencing is adept at identifying single nucleotide variations and small insertions or deletions that constitute majority of the disease-causing mutations. Description of the complete mutation spectrum in syndromic glomerulopathies may require the use of both sequencing and cytogenetic methods to detect large structural DNA variation in addition to single nucleotide changes. The enthusiastic application of genetic and genomic knowledge to inherited glomerular diseases has uncovered anticipated and unforeseen challenges mainly related to the biological interpretation of variants of uncertain significance and the limited benefit on clinical management for the individual patient when a diagnosis is obtained. To attain the ultimate goal of transforming clinical decision-making based on accurate genetic diagnosis using genomic information, these challenges need to be addressed. Till then, the glory of genomic medicine stands the test of time in this gilded age of genomic advancements.
Keywords: Adolescent; Age Factors; Branchio-Oto-Renal Syndrome; Child; Female; High-Throughput Nucleotide Sequencing; Humans; Infant; Kidney Failure, Chronic; Male; Middle Aged; Mutation; Pedigree; Polymorphism, Single Nucleotide; Renal Insufficiency, Chronic; Whole Exome Sequencing

KIAA1217: A novel candidate gene associated with isolated and syndromic vertebral malformations. - Al Dhaheri, Noura; Wu, Nan; Zhao, Sen; Wu, Zhihong; Blank, Robert D; Zhang, Jianguo; Raggio, Cathy; Halanski, Matthew; Shen, Jianxiong; Noonan, Ken; Qiu, Guixing; Nemeth, Blaise; et al. (Am J Med Genet A, 2020)
Vertebral malformations (VMs) are caused by alterations in somitogenesis and may occur in association with other congenital anomalies. The genetic etiology of most VMs remains unknown and their identification may facilitate the development of novel therapeutic and prevention strategies. Exome sequencing was performed on both the discovery cohort of nine unrelated probands from the USA with VMs and the replication cohort from China (Deciphering Disorders Involving Scoliosis & COmorbidities study). The discovery cohort was analyzed using the PhenoDB analysis tool. Heterozygous and homozygous, rare and functional variants were selected and evaluated for their ClinVar, HGMD, OMIM, GWAS, mouse model phenotypes, and other annotations to identify the best candidates. Genes with candidate variants in three or more probands were selected. The replication cohort was analyzed by another in-house developed pipeline. We identified rare heterozygous variants in KIAA1217 in four out of nine probands in the discovery cohort and in five out of 35 probands in the replication cohort. Collectively, we identified 11 KIAA1217 rare variants in 10 probands, three of which have not been described in gnomAD and one of which is a nonsense variant. We propose that genetic variations of KIAA1217 may contribute to the etiology of VMs.
Keywords: Adolescent; Cervical Vertebrae; Child; Codon, Nonsense; Databases, Genetic; Female; Heterozygote; Homozygote; Humans; Male; Proteins; Spinal Diseases; Thoracic Vertebrae

KMT2B-related disorders: expansion of the phenotypic spectrum and long-term efficacy of deep brain stimulation. - Cif, Laura; Demailly, Diane; Lin, Jean-Pierre; Barwick, Katy E; Sa, Mario; Abela, Lucia; Malhotra, Sony; Chong, Wui K; Steel, Dora; Sanchis-Juan, Alba; Ngoh, Adeline; Trump, Natalie; et al. (Brain, 2020)
Heterozygous mutations in KMT2B are associated with an early-onset, progressive and often complex dystonia (DYT28). Key characteristics of typical disease include focal motor features at disease presentation, evolving through a caudocranial pattern into generalized dystonia, with prominent oromandibular, laryngeal and cervical involvement. Although KMT2B-related disease is emerging as one of the most common causes of early-onset genetic dystonia, much remains to be understood about the full spectrum of the disease. We describe a cohort of 53 patients with KMT2B mutations, with detailed delineation of their clinical phenotype and molecular genetic features. We report new disease presentations, including atypical patterns of dystonia evolution and a subgroup of patients with a non-dystonic neurodevelopmental phenotype. In addition to the previously reported systemic features, our study has identified co-morbidities, including the risk of status dystonicus, intrauterine growth retardation, and endocrinopathies. Analysis of this study cohort (n = 53) in tandem with published cases (n = 80) revealed that patients with chromosomal deletions and protein truncating variants had a significantly higher burden of systemic disease (with earlier onset of dystonia) than those with missense variants. Eighteen individuals had detailed longitudinal data available after insertion of deep brain stimulation for medically refractory dystonia. Median age at deep brain stimulation was 11.5 years (range: 4.5-37.0 years). Follow-up after deep brain stimulation ranged from 0.25 to 22 years. Significant improvement of motor function and disability (as assessed by the Burke Fahn Marsden's Dystonia Rating Scales, BFMDRS-M and BFMDRS-D) was evident at 6 months, 1 year and last follow-up (motor, P = 0.001, P = 0.004, and P = 0.012; disability, P = 0.009, P = 0.002 and P = 0.012). At 1 year post-deep brain stimulation, >50% of subjects showed BFMDRS-M and BFMDRS-D improvements of >30%. In the long-term deep brain stimulation cohort (deep brain stimulation inserted for >5 years, n = 8), improvement of >30% was maintained in 5/8 and 3/8 subjects for the BFMDRS-M and BFMDRS-D, respectively. The greatest BFMDRS-M improvements were observed for trunk (53.2%) and cervical (50.5%) dystonia, with less clinical impact on laryngeal dystonia. Improvements in gait dystonia decreased from 20.9% at 1 year to 16.2% at last assessment; no patient maintained a fully independent gait. Reduction of BFMDRS-D was maintained for swallowing (52.9%). Five patients developed mild parkinsonism following deep brain stimulation. KMT2B-related disease comprises an expanding continuum from infancy to adulthood, with early evidence of genotype-phenotype correlations. Except for laryngeal dysphonia, deep brain stimulation provides a significant improvement in quality of life and function with sustained clinical benefit depending on symptoms distribution.
Keywords: Adolescent; Adult; Child; Child, Preschool; Chromosome Deletion; Cohort Studies; Computer Simulation; Deep Brain Stimulation; Disease Progression; Dystonic Disorders; Endocrine System Diseases; Female; Fetal Growth Retardation; Gait Disorders, Neurologic; Histone-Lysine N-Methyltransferase; Humans; Laryngeal Diseases; Male; Mutation; Mutation, Missense; Phenotype; Quality of Life; Treatment Outcome; Young Adult

Large-Scale Exome Sequencing Study Implicates Both Developmental and Functional Changes in the Neurobiology of Autism. - Satterstrom, F Kyle; Kosmicki, Jack A; Wang, Jiebiao; Breen, Michael S; De Rubeis, Silvia; An, Joon-Yong; Peng, Minshi; Collins, Ryan; Grove, Jakob; Klei, Lambertus; Stevens, Christine; Reichert, Jennifer; et al. (Cell, 2020)
We present the largest exome sequencing study of autism spectrum disorder (ASD) to date (n = 35,584 total samples, 11,986 with ASD). Using an enhanced analytical framework to integrate de novo and case-control rare variation, we identify 102 risk genes at a false discovery rate of 0.1 or less. Of these genes, 49 show higher frequencies of disruptive de novo variants in individuals ascertained to have severe neurodevelopmental delay, whereas 53 show higher frequencies in individuals ascertained to have ASD; comparing ASD cases with mutations in these groups reveals phenotypic differences. Expressed early in brain development, most risk genes have roles in regulation of gene expression or neuronal communication (i.e., mutations effect neurodevelopmental and neurophysiological changes), and 13 fall within loci recurrently hit by copy number variants. In cells from the human cortex, expression of risk genes is enriched in excitatory and inhibitory neuronal lineages, consistent with multiple paths to an excitatory-inhibitory imbalance underlying ASD.
Keywords: Autistic Disorder; Case-Control Studies; Cell Lineage; Cerebral Cortex; Cohort Studies; Exome; Female; Gene Expression Regulation, Developmental; Gene Frequency; Genetic Predisposition to Disease; Humans; Male; Mutation, Missense; Neurobiology; Neurons; Phenotype; Sex Factors; Single-Cell Analysis; Whole Exome Sequencing

Loss of NARS1 impairs progenitor proliferation in cortical brain organoids and leads to microcephaly. - Wang, Lu; Li, Zhen; Sievert, David; Smith, Desirée E C; Mendes, Marisa I; Chen, Dillon Y; Stanley, Valentina; Ghosh, Shereen; Wang, Yulu; Kara, Majdi; Aslanger, Ayca Dilruba; Rosti, Rasim O; et al. (Nat Commun, 2020)
Asparaginyl-tRNA synthetase1 (NARS1) is a member of the ubiquitously expressed cytoplasmic Class IIa family of tRNA synthetases required for protein translation. Here, we identify biallelic missense and frameshift mutations in NARS1 in seven patients from three unrelated families with microcephaly and neurodevelopmental delay. Patient cells show reduced NARS1 protein, impaired NARS1 activity and impaired global protein synthesis. Cortical brain organoid modeling shows reduced proliferation of radial glial cells (RGCs), leading to smaller organoids characteristic of microcephaly. Single-cell analysis reveals altered constituents of both astrocytic and RGC lineages, suggesting a requirement for NARS1 in RGC proliferation. Our findings demonstrate that NARS1 is required to meet protein synthetic needs and to support RGC proliferation in human brain development.
Keywords: Adolescent; Adult; Aspartate-tRNA Ligase; Base Sequence; Cell Differentiation; Cell Proliferation; Cell Size; Cell Survival; Cerebral Cortex; Child; Family; Female; Fibroblasts; HEK293 Cells; Humans; Induced Pluripotent Stem Cells; Ki-67 Antigen; Male; Microcephaly; Mutation; Neural Stem Cells; Neuroglia; Organoids; Pedigree; RNA, Transfer, Amino Acyl; Young Adult

Mapping and characterization of structural variation in 17,795 human genomes. - Abel, Haley J; Larson, David E; Regier, Allison A; Chiang, Colby; Das, Indraniel; Kanchi, Krishna L; Layer, Ryan M; Neale, Benjamin M; Salerno, William J; Reeves, Catherine; Buyske, Steven; Matise, Tara C; et al. (Nature, 2020)
A key goal of whole-genome sequencing for studies of human genetics is to interrogate all forms of variation, including single-nucleotide variants, small insertion or deletion (indel) variants and structural variants. However, tools and resources for the study of structural variants have lagged behind those for smaller variants. Here we used a scalable pipeline to map and characterize structural variants in 17,795 deeply sequenced human genomes. We publicly release site-frequency data to create the largest, to our knowledge, whole-genome-sequencing-based structural variant resource so far. On average, individuals carry 2.9 rare structural variants that alter coding regions; these variants affect the dosage or structure of 4.2 genes and account for 4.0-11.2% of rare high-impact coding alleles. Using a computational model, we estimate that structural variants account for 17.2% of rare alleles genome-wide, with predicted deleterious effects that are equivalent to loss-of-function coding alleles; approximately 90% of such structural variants are noncoding deletions (mean 19.1 per genome). We report 158,991 ultra-rare structural variants and show that 2% of individuals carry ultra-rare megabase-scale structural variants, nearly half of which are balanced or complex rearrangements. Finally, we infer the dosage sensitivity of genes and noncoding elements, and reveal trends that relate to element class and conservation. This work will help to guide the analysis and interpretation of structural variants in the era of whole-genome sequencing.
Keywords: Alleles; Case-Control Studies; Continental Population Groups; Epigenesis, Genetic; Female; Gene Dosage; Genetic Variation; Genetics, Population; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Male; Molecular Sequence Annotation; Quantitative Trait Loci; Software; Whole Genome Sequencing

Missed diagnoses: Clinically relevant lessons learned through medical mysteries solved by the Undiagnosed Diseases Network. - Cope, Heidi; Spillmann, Rebecca; Rosenfeld, Jill A; Brokamp, Elly; Signer, Rebecca; Schoch, Kelly; Kelley, Emily G; Sullivan, Jennifer A; Macnamara, Ellen; Lincoln, Sharyn; Golden-Grant, Katie; Orengo, James P; et al. (Mol Genet Genomic Med, 2020)
BACKGROUND: Resources within the Undiagnosed Diseases Network (UDN), such as genome sequencing (GS) and model organisms aid in diagnosis and identification of new disease genes, but are currently difficult to access by clinical providers. While these resources do contribute to diagnoses in many cases, they are not always necessary to reach diagnostic resolution. The UDN experience has been that participants can also receive diagnoses through the thoughtful and customized application of approaches and resources that are readily available in clinical settings. METHODS: The UDN Genetic Counseling and Testing Working Group collected case vignettes that illustrated how clinically available methods resulted in diagnoses. The case vignettes were classified into three themes; phenotypic considerations, selection of genetic testing, and evaluating exome/GS variants and data. RESULTS: We present 12 participants that illustrate how clinical practices such as phenotype-driven genomic investigations, consideration of variable expressivity, selecting the relevant tissue of interest for testing, utilizing updated testing platforms, and recognition of alternate transcript nomenclature resulted in diagnoses. CONCLUSION: These examples demonstrate that when a diagnosis is elusive, an iterative patient-specific approach utilizing assessment options available to clinical providers may solve a portion of cases. However, this does require increased provider time commitment, a particular challenge in the current practice of genomics.
Keywords: Adolescent; Child; Child, Preschool; Databases, Factual; Diagnosis, Computer-Assisted; Female; Genetic Diseases, Inborn; Genetic Testing; Humans; Information Dissemination; Male; Middle Aged; Missed Diagnosis; National Institutes of Health (U.S.); Phenotype; Precision Medicine; Undiagnosed Diseases; United States; Young Adult

A missense variant in Mitochondrial Amidoxime Reducing Component 1 gene and protection against liver disease. - Emdin, Connor A; Haas, Mary E; Khera, Amit V; Aragam, Krishna; Chaffin, Mark; Klarin, Derek; Hindy, George; Jiang, Lan; Wei, Wei-Qi; Feng, Qiping; Karjalainen, Juha; Havulinna, Aki; et al. (PLoS Genet, 2020)
Analyzing 12,361 all-cause cirrhosis cases and 790,095 controls from eight cohorts, we identify a common missense variant in the Mitochondrial Amidoxime Reducing Component 1 gene (MARC1 p.A165T) that associates with protection from all-cause cirrhosis (OR 0.91, p = 2.3*10-11). This same variant also associates with lower levels of hepatic fat on computed tomographic imaging and lower odds of physician-diagnosed fatty liver as well as lower blood levels of alanine transaminase (-0.025 SD, 3.7*10-43), alkaline phosphatase (-0.025 SD, 1.2*10-37), total cholesterol (-0.030 SD, p = 1.9*10-36) and LDL cholesterol (-0.027 SD, p = 5.1*10-30) levels. We identified a series of additional MARC1 alleles (low-frequency missense p.M187K and rare protein-truncating p.R200Ter) that also associated with lower cholesterol levels, liver enzyme levels and reduced risk of cirrhosis (0 cirrhosis cases for 238 R200Ter carriers versus 17,046 cases of cirrhosis among 759,027 non-carriers, p = 0.04) suggesting that deficiency of the MARC1 enzyme may lower blood cholesterol levels and protect against cirrhosis.
Keywords: Alleles; Cholesterol, LDL; Coronary Artery Disease; Datasets as Topic; Fatty Liver; Female; Genetic Predisposition to Disease; Homozygote; Humans; Liver; Liver Cirrhosis; Liver Cirrhosis, Alcoholic; Loss of Function Mutation; Male; Middle Aged; Mitochondrial Proteins; Mutation, Missense; Oxidoreductases

MN1 C-terminal truncation syndrome is a novel neurodevelopmental and craniofacial disorder with partial rhombencephalosynapsis. - Mak, Christopher C Y; Doherty, Dan; Lin, Angela E; Vegas, Nancy; Cho, Megan T; Viot, Géraldine; Dimartino, Clémantine; Weisfeld-Adams, James D; Lessel, Davor; Joss, Shelagh; Li, Chumei; Gonzaga-Jauregui, Claudia; et al. (Brain, 2020)
MN1 encodes a transcriptional co-regulator without homology to other proteins, previously implicated in acute myeloid leukaemia and development of the palate. Large deletions encompassing MN1 have been reported in individuals with variable neurodevelopmental anomalies and non-specific facial features. We identified a cluster of de novo truncating mutations in MN1 in a cohort of 23 individuals with strikingly similar dysmorphic facial features, especially midface hypoplasia, and intellectual disability with severe expressive language delay. Imaging revealed an atypical form of rhombencephalosynapsis, a distinctive brain malformation characterized by partial or complete loss of the cerebellar vermis with fusion of the cerebellar hemispheres, in 8/10 individuals. Rhombencephalosynapsis has no previously known definitive genetic or environmental causes. Other frequent features included perisylvian polymicrogyria, abnormal posterior clinoid processes and persistent trigeminal artery. MN1 is encoded by only two exons. All mutations, including the recurrent variant p.Arg1295* observed in 8/21 probands, fall in the terminal exon or the extreme 3' region of exon 1, and are therefore predicted to result in escape from nonsense-mediated mRNA decay. This was confirmed in fibroblasts from three individuals. We propose that the condition described here, MN1 C-terminal truncation (MCTT) syndrome, is not due to MN1 haploinsufficiency but rather is the result of dominantly acting C-terminally truncated MN1 protein. Our data show that MN1 plays a critical role in human craniofacial and brain development, and opens the door to understanding the biological mechanisms underlying rhombencephalosynapsis.
Keywords: Abnormalities, Multiple; Adolescent; Basilar Artery; Carotid Arteries; Cerebellar Vermis; Cerebellum; Child; Child, Preschool; Cohort Studies; Comparative Genomic Hybridization; Craniofacial Abnormalities; Female; Fibroblasts; Humans; Imaging, Three-Dimensional; Infant; Intellectual Disability; Language Development Disorders; Magnetic Resonance Imaging; Male; Middle Aged; Mutation; Nervous System Malformations; Nonsense Mediated mRNA Decay; Polymicrogyria; Real-Time Polymerase Chain Reaction; RNA-Seq; Syndrome; Tomography, X-Ray Computed; Trans-Activators; Tumor Suppressor Proteins; Whole Exome Sequencing; Whole Genome Sequencing

Molecular diagnosis in recessive pediatric neurogenetic disease can help reduce disease recurrence in families. - Issa, Mahmoud Y; Chechlacz, Zinayida; Stanley, Valentina; George, Renee D; McEvoy-Venneri, Jennifer; Belandres, Denice; Elbendary, Hasnaa M; Gaber, Khaled R; Nabil, Ahmed; Abdel-Hamid, Mohamed S; Zaki, MAH S; Gleeson, Joseph G (BMC Med Genomics, 2020)
BACKGROUND: The causes for thousands of individually rare recessive diseases have been discovered since the adoption of next generation sequencing (NGS). Following the molecular diagnosis in older children in a family, parents could use this information to opt for fetal genotyping in subsequent pregnancies, which could inform decisions about elective termination of pregnancy. The use of NGS diagnostic sequencing in families has not been demonstrated to yield benefit in subsequent pregnancies to reduce recurrence. Here we evaluated whether genetic diagnosis in older children in families supports reduction in recurrence of recessive neurogenetic disease. METHODS: Retrospective study involving families with a child with a recessive pediatric brain disease (rPBD) that underwent NGS-based molecular diagnosis. Prenatal molecular testing was offered to couples in which a molecular diagnosis was made, to help couples seeking to prevent recurrence. With this information, families made decisions about elective termination. Pregnancies that were carried to term were assessed for the health of child and mother, and compared with historic recurrence risk of recessive disease. RESULTS: Between 2010 and 2016, 1172 families presented with a child a likely rPBD, 526 families received a molecular diagnosis, 91 families returned to the clinic with 101 subsequent pregnancies, and 84 opted for fetal genotyping. Sixty tested negative for recurrence for the biallelic mutation in the fetus, and all, except for one spontaneous abortion, carried to term, and were unaffected at follow-up. Of 24 that genotyped positive for the biallelic mutation, 16 were electively terminated, and 8 were carried to term and showed features of disease similar to that of the older affected sibling(s). Among the 101 pregnancies, disease recurrence in living offspring deviated from the expected 25% to the observed 12% ([95% CI 0·04 to 0·20], p = 0·011). CONCLUSIONS: Molecular diagnosis in an older child, coupled with prenatal fetal genotyping in subsequent pregnancies and genetic counselling, allows families to make informed decisions to reduce recessive neurogenetic disease recurrence.
Keywords: Child, Preschool; Female; Genes, Recessive; Genetic Markers; Genetic Predisposition to Disease; Genetic Testing; Genotype; High-Throughput Nucleotide Sequencing; Humans; Infant; Infant, Newborn; Male; Mutation; Nervous System Diseases; Pedigree; Pregnancy; Prenatal Diagnosis; Recurrence; Retrospective Studies

Monogenic variants in dystonia: an exome-wide sequencing study. - Zech, Michael; Jech, Robert; Boesch, Sylvia; Škorvánek, Matej; Weber, Sandrina; Wagner, Matias; Zhao, Chen; Jochim, Angela; Necpál, Ján; Dincer, Yasemin; Vill, Katharina; Distelmaier, Felix; et al. (Lancet Neurol, 2020)
BACKGROUND: Dystonia is a clinically and genetically heterogeneous condition that occurs in isolation (isolated dystonia), in combination with other movement disorders (combined dystonia), or in the context of multisymptomatic phenotypes (isolated or combined dystonia with other neurological involvement). However, our understanding of its aetiology is still incomplete. We aimed to elucidate the monogenic causes for the major clinical categories of dystonia. METHODS: For this exome-wide sequencing study, study participants were identified at 33 movement-disorder and neuropaediatric specialty centres in Austria, Czech Republic, France, Germany, Poland, Slovakia, and Switzerland. Each individual with dystonia was diagnosed in accordance with the dystonia consensus definition. Index cases were eligible for this study if they had no previous genetic diagnosis and no indication of an acquired cause of their illness. The second criterion was not applied to a subset of participants with a working clinical diagnosis of dystonic cerebral palsy. Genomic DNA was extracted from blood of participants and whole-exome sequenced. To find causative variants in known disorder-associated genes, all variants were filtered, and unreported variants were classified according to American College of Medical Genetics and Genomics guidelines. All considered variants were reviewed in expert round-table sessions to validate their clinical significance. Variants that survived filtering and interpretation procedures were defined as diagnostic variants. In the cases that went undiagnosed, candidate dystonia-causing genes were prioritised in a stepwise workflow. FINDINGS: We sequenced the exomes of 764 individuals with dystonia and 346 healthy parents who were recruited between June 1, 2015, and July 31, 2019. We identified causative or probable causative variants in 135 (19%) of 728 families, involving 78 distinct monogenic disorders. We observed a larger proportion of individuals with diagnostic variants in those with dystonia (either isolated or combined) with coexisting non-movement disorder-related neurological symptoms (100 [45%] of 222; excepting cases with evidence of perinatal brain injury) than in those with combined (19 [19%] of 98) or isolated (16 [4%] of 388) dystonia. Across all categories of dystonia, 104 (65%) of the 160 detected variants affected genes which are associated with neurodevelopmental disorders. We found diagnostic variants in 11 genes not previously linked to dystonia, and propose a predictive clinical score that could guide the implementation of exome sequencing in routine diagnostics. In cases without perinatal sentinel events, genomic alterations contributed substantively to the diagnosis of dystonic cerebral palsy. In 15 families, we delineated 12 candidate genes. These include IMPDH2, encoding a key purine biosynthetic enzyme, for which robust evidence existed for its involvement in a neurodevelopmental disorder with dystonia. We identified six variants in IMPDH2, collected from four independent cohorts, that were predicted to be deleterious de-novo variants and expected to result in deregulation of purine metabolism. INTERPRETATION: In this study, we have determined the role of monogenic variants across the range of dystonic disorders, providing guidance for the introduction of personalised care strategies and fostering follow-up pathophysiological explorations. FUNDING: Else Kröner-Fresenius-Stiftung, Technische Universität München, Helmholtz Zentrum München, Medizinische Universität Innsbruck, Charles University in Prague, Czech Ministry of Education, the Slovak Grant and Development Agency, the Slovak Research and Grant Agency.
Keywords: Adolescent; Child; Child, Preschool; Dystonia; Exome; Female; Genetic Variation; Humans; Infant; Infant, Newborn; Male; Pedigree; Whole Exome Sequencing; Young Adult

Multi-omic studies on missense PLG variants in families with otitis media. - Bootpetch, Tori C; Hafrén, Lena; Elling, Christina L; Baschal, Erin E; Manichaikul, Ani W; Pine, Harold S; Szeremeta, Wasyl; Scholes, Melissa A; Cass, Stephen P; Larson, Eric D; Chan, Kenny H; Ishaq, Rafaqat; et al. (Sci Rep, 2020)
Otitis media (OM), a very common disease in young children, can result in hearing loss. In order to potentially replicate previously reported associations between OM and PLG, exome and Sanger sequencing, RNA-sequencing of saliva and middle ear samples, 16S rRNA sequencing, molecular modeling, and statistical analyses including transmission disequilibrium tests (TDT) were performed in a multi-ethnic cohort of 718 families and simplex cases with OM. We identified four rare PLG variants c.112A > G (p.Lys38Glu), c.782G > A (p.Arg261His), c.1481C > T (p.Ala494Val) and c.2045 T > A (p.Ile682Asn), and one common variant c.1414G > A (p.Asp472Asn). However TDT analyses for these PLG variants did not demonstrate association with OM in 314 families. Additionally PLG expression is very low or absent in normal or diseased middle ear in mouse and human, and salivary expression and microbial α-diversity were non-significant in c.1414G > A (p.Asp472Asn) carriers. Based on molecular modeling, the novel rare variants particularly c.782G > A (p.Arg261His) and c.2045 T > A (p.Ile682Asn) were predicted to affect protein structure. Exploration of other potential disease mechanisms will help elucidate how PLG contributes to OM susceptibility in humans. Our results underline the importance of following up findings from genome-wide association through replication studies, preferably using multi-omic datasets.
Keywords: Animals; Ear, Middle; Female; Genomics; Humans; Male; Mice; Microbiota; Mutation, Missense; Otitis Media; Pedigree; Plasminogen; Polymorphism, Single Nucleotide; Saliva

A mutation affecting laminin alpha 5 polymerisation gives rise to a syndromic developmental disorder. - Jones, Lynelle K; Lam, Rachel; McKee, Karen K; Aleksandrova, Maya; Dowling, John; Alexander, Stephen I; Mallawaarachchi, Amali; Cottle, Denny L; Short, Kieran M; Pais, Lynn; Miner, Jeffery H; Mallett, Andrew J; et al. (Development, 2020)
Laminin alpha 5 (LAMA5) is a member of a large family of proteins that trimerise and then polymerise to form a central component of all basement membranes. Consequently, the protein plays an instrumental role in shaping the normal development of the kidney, skin, neural tube, lung and limb, and many other organs and tissues. Pathogenic mutations in some laminins have been shown to cause a range of largely syndromic conditions affecting the competency of the basement membranes to which they contribute. We report the identification of a mutation in the polymerisation domain of LAMA5 in a patient with a complex syndromic disease characterised by defects in kidney, craniofacial and limb development, and by a range of other congenital defects. Using CRISPR-generated mouse models and biochemical assays, we demonstrate the pathogenicity of this variant, showing that the change results in a failure of the polymerisation of α/β/γ laminin trimers. Comparing these phenotypes with those apparent upon gene deletion in mice provides insights into the specific functional importance of laminin polymerisation during development and tissue homeostasis.
Keywords: Amino Acid Sequence; Animals; Animals, Newborn; Child, Preschool; Developmental Disabilities; Fetal Development; Fetus; Humans; Hydronephrosis; Infant, Newborn; Kidney; Laminin; Lung; Male; Mice; Mutation; Polymerization; Protein Domains; Syndrome

Mutation Distribution and Type Suggests Genetic Differences between the Etiology of Orofacial Clefting and Gastric Cancer. - Selvanathan, Arthavan; Nixon, Cheng Yee; Zhu, Ying; Scietti, Luigi; Forneris, Federico; Uribe, Lina M Moreno; Lidral, Andrew C; Jezewski, Peter A; Mulliken, John B; Murray, Jeffrey C; Buckley, Michael F; Cox, Timothy C; et al. (Genes (Basel), 2020)
Pathogenic variants in , encoding epithelial cadherin (E-cadherin), have been implicated in hereditary diffuse gastric cancer (HDGC), lobular breast cancer, and both syndromic and non-syndromic cleft lip/palate (CL/P). Despite the large number of mutations described, the nature of the phenotypic consequence of such mutations is currently not able to be predicted, creating significant challenges for genetic counselling. This study collates the phenotype and molecular data for available variants that have been classified, using the American College of Medical Genetics and Genomics criteria, as at least 'likely pathogenic', and correlates their molecular and structural characteristics to phenotype. We demonstrate that variant type and location differ between HDGC and CL/P, and that there is clustering of CL/P variants within linker regions between the extracellular domains of the cadherin protein. While these differences do not provide for exact prediction of the phenotype for a given mutation, they may contribute to more accurate assessments of risk for HDGC or CL/P for individuals with specific variants.
Keywords: Antigens, CD; Brain; Cadherins; Cleft Lip; Cleft Palate; Female; Genetic Counseling; Genetic Predisposition to Disease; Germ-Line Mutation; Humans; Male; Pedigree; Phenotype; Stomach Neoplasms

Mutation of CFAP57, a protein required for the asymmetric targeting of a subset of inner dynein arms in Chlamydomonas, causes primary ciliary dyskinesia. - Bustamante-Marin, Ximena M; Horani, Amjad; Stoyanova, Mihaela; Charng, Wu-Lin; Bottier, Mathieu; Sears, Patrick R; Yin, Wei-Ning; Daniels, Leigh Anne; Bowen, Hailey; Conrad, Donald F; Knowles, Michael R; Ostrowski, Lawrence E; et al. (PLoS Genet, 2020)
Primary ciliary dyskinesia (PCD) is characterized by chronic airway disease, reduced fertility, and randomization of the left/right body axis. It is caused by defects of motile cilia and sperm flagella. We screened a cohort of affected individuals that lack an obvious axonemal defect for pathogenic variants using whole exome capture, next generation sequencing, and bioinformatic analysis assuming an autosomal recessive trait. We identified one subject with an apparently homozygous nonsense variant [(c.1762C>T), p.(Arg588*)] in the uncharacterized CFAP57 gene. Interestingly, the variant results in the skipping of exon 11 (58 amino acids), which may be due to disruption of an exonic splicing enhancer. In normal human nasal epithelial cells, CFAP57 localizes throughout the ciliary axoneme. Nasal cells from the PCD patient express a shorter, mutant version of CFAP57 and the protein is not incorporated into the axoneme. The missing 58 amino acids include portions of WD repeats that may be important for loading onto the intraflagellar transport (IFT) complexes for transport or docking onto the axoneme. A reduced beat frequency and an alteration in ciliary waveform was observed. Knockdown of CFAP57 in human tracheobronchial epithelial cells (hTECs) recapitulates these findings. Phylogenetic analysis showed that CFAP57 is highly conserved in organisms that assemble motile cilia. CFAP57 is allelic with the BOP2/IDA8/FAP57 gene identified previously in Chlamydomonas reinhardtii. Two independent, insertional fap57 Chlamydomonas mutant strains show reduced swimming velocity and altered waveforms. Tandem mass tag (TMT) mass spectroscopy shows that FAP57 is missing, and the "g" inner dyneins (DHC7 and DHC3) and the "d" inner dynein (DHC2) are reduced, but the FAP57 paralog FBB7 is increased. Together, our data identify a homozygous variant in CFAP57 that causes PCD that is likely due to a defect in the inner dynein arm assembly process.
Keywords: 3T3 Cells; Adult; Animals; Axoneme; Cells, Cultured; Chlamydomonas reinhardtii; Cilia; Ciliary Motility Disorders; Codon, Nonsense; Conserved Sequence; Dyneins; Humans; Male; Mice; Microtubule-Associated Proteins; Plant Proteins; Proteins; Respiratory Mucosa

The mutational constraint spectrum quantified from variation in 141,456 humans. - Karczewski, Konrad J; Francioli, Laurent C; Tiao, Grace; Cummings, Beryl B; Alföldi, Jessica; Wang, Qingbo; Collins, Ryan L; Laricchia, Kristen M; Ganna, Andrea; Birnbaum, Daniel P; Gauthier, Laura D; Brand, Harrison; et al. (Nature, 2020)
Genetic variants that inactivate protein-coding genes are a powerful source of information about the phenotypic consequences of gene disruption: genes that are crucial for the function of an organism will be depleted of such variants in natural populations, whereas non-essential genes will tolerate their accumulation. However, predicted loss-of-function variants are enriched for annotation errors, and tend to be found at extremely low frequencies, so their analysis requires careful variant annotation and very large sample sizes. Here we describe the aggregation of 125,748 exomes and 15,708 genomes from human sequencing studies into the Genome Aggregation Database (gnomAD). We identify 443,769 high-confidence predicted loss-of-function variants in this cohort after filtering for artefacts caused by sequencing and annotation errors. Using an improved model of human mutation rates, we classify human protein-coding genes along a spectrum that represents tolerance to inactivation, validate this classification using data from model organisms and engineered human cells, and show that it can be used to improve the power of gene discovery for both common and rare diseases.
Keywords: Adult; Brain; Cardiovascular Diseases; Cohort Studies; Databases, Genetic; Exome; Female; Genes, Essential; Genetic Predisposition to Disease; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Loss of Function Mutation; Male; Mutation Rate; Proprotein Convertase 9; Reproducibility of Results; RNA, Messenger; Whole Exome Sequencing; Whole Genome Sequencing

Mutations disrupting neuritogenesis genes confer risk for cerebral palsy. - Jin, Sheng Chih; Lewis, Sara A; Bakhtiari, Somayeh; Zeng, Xue; Sierant, Michael C; Shetty, Sheetal; Nordlie, Sandra M; Elie, Aureliane; Corbett, Mark A; Norton, Bethany Y; van Eyk, Clare L; Haider, Shozeb; et al. (Nat Genet, 2020)
In addition to commonly associated environmental factors, genomic factors may cause cerebral palsy. We performed whole-exome sequencing of 250 parent-offspring trios, and observed enrichment of damaging de novo mutations in cerebral palsy cases. Eight genes had multiple damaging de novo mutations; of these, two (TUBA1A and CTNNB1) met genome-wide significance. We identified two novel monogenic etiologies, FBXO31 and RHOB, and showed that the RHOB mutation enhances active-state Rho effector binding while the FBXO31 mutation diminishes cyclin D levels. Candidate cerebral palsy risk genes overlapped with neurodevelopmental disorder genes. Network analyses identified enrichment of Rho GTPase, extracellular matrix, focal adhesion and cytoskeleton pathways. Cerebral palsy risk genes in enriched pathways were shown to regulate neuromotor function in a Drosophila reverse genetics screen. We estimate that 14% of cases could be attributed to an excess of damaging de novo or recessive variants. These findings provide evidence for genetically mediated dysregulation of early neuronal connectivity in cerebral palsy.
Keywords: Animals; beta Catenin; Cerebral Palsy; Cyclin D; Cytoskeleton; Drosophila; Exome; Extracellular Matrix; F-Box Proteins; Female; Focal Adhesions; Genetic Predisposition to Disease; Genome, Human; Humans; Male; Mutation; Neurites; rhoB GTP-Binding Protein; Risk Factors; Sequence Analysis, DNA; Signal Transduction; Tubulin; Tumor Suppressor Proteins; Whole Exome Sequencing

Mutations in KRT10 in epidermolytic acanthoma. - Cheraghlou, Shayan; Atzmony, Lihi; Roy, Simon F; McNiff, Jennifer M; Choate, Keith A (J Cutan Pathol, 2020)
BACKGROUND: Epidermolytic acanthoma (EA) is a rare acquired lesion demonstrating a characteristic histopathological pattern of epidermal degeneration referred to as epidermolytic hyperkeratosis (EHK). On histopathological analysis, EA appears nearly identical to inherited EHK-associated dermatoses such as epidermolytic ichthyosis and ichthyosis bullosa of Siemens. While it has been speculated that EA is caused by mutations in KRT10, KRT1, or KRT2 found in these inherited dermatoses, none have yet been identified. Herein, we aim to identify the contributions of keratin mutations to EA. METHODS: Using genomic DNA extracted from paraffin-embedded samples from departmental archives, we evaluated a discovery cohort using whole-exome sequencing (WES) and assessed remaining samples using Sanger sequencing screening and restriction fragment length polymorphism (RFLP) analysis. RESULTS: DNA from 16/20 cases in our sample was of sufficient quality for polymerase chain reaction amplification. WES of genomic DNA from lesional tissue revealed KRT10 c.466C > T, p.Arg156Cys mutations in 2/3 samples submitted for examination. RFLP analysis of these samples as well as eight additional samples confirmed the mutations identified via WES and identified four additional cases with Arg156 mutations. In sum, 6/11 screened cases showed hotspot mutation in KRT10. CONCLUSIONS: Hotspot mutations in the Arg156 position of KRT10, known to cause epidermolytic ichthyosis, also underlie EA.
Keywords: Acanthoma; Adult; Aged; Aged, 80 and over; Female; Genomics; Humans; Hyperkeratosis, Epidermolytic; Ichthyosis Bullosa of Siemens; Keratin-10; Keratins; Male; Middle Aged; Mutation; Skin Neoplasms; Whole Exome Sequencing

Mutations in MYLPF Cause a Novel Segmental Amyoplasia that Manifests as Distal Arthrogryposis. - Chong, Jessica X; Talbot, Jared C; Teets, Emily M; Previs, Samantha; Martin, Brit L; Shively, Kathryn M; Marvin, Colby T; Aylsworth, Arthur S; Saadeh-Haddad, Reem; Schatz, Ulrich A; Inzana, Francesca; Ben-Omran, Tawfeg; et al. (Am J Hum Genet, 2020)
We identified ten persons in six consanguineous families with distal arthrogryposis (DA) who had congenital contractures, scoliosis, and short stature. Exome sequencing revealed that each affected person was homozygous for one of two different rare variants (c.470G>T [p.Cys157Phe] or c.469T>C [p.Cys157Arg]) affecting the same residue of myosin light chain, phosphorylatable, fast skeletal muscle (MYLPF). In a seventh family, a c.487G>A (p.Gly163Ser) variant in MYLPF arose de novo in a father, who transmitted it to his son. In an eighth family comprised of seven individuals with dominantly inherited DA, a c.98C>T (p.Ala33Val) variant segregated in all four persons tested. Variants in MYLPF underlie both dominant and recessively inherited DA. Mylpf protein models suggest that the residues associated with dominant DA interact with myosin whereas the residues altered in families with recessive DA only indirectly impair this interaction. Pathological and histological exam of a foot amputated from an affected child revealed complete absence of skeletal muscle (i.e., segmental amyoplasia). To investigate the mechanism for this finding, we generated an animal model for partial MYLPF impairment by knocking out zebrafish mylpfa. The mylpfa mutant had reduced trunk contractile force and complete pectoral fin paralysis, demonstrating that mylpf impairment most severely affects limb movement. mylpfa mutant muscle weakness was most pronounced in an appendicular muscle and was explained by reduced myosin activity and fiber degeneration. Collectively, our findings demonstrate that partial loss of MYLPF function can lead to congenital contractures, likely as a result of degeneration of skeletal muscle in the distal limb.
Keywords: Adolescent; Amino Acid Sequence; Animals; Arthrogryposis; Child; Contracture; Extremities; Female; Humans; Male; Muscle, Skeletal; Musculoskeletal Abnormalities; Mutation; Myosin Light Chains; Myosins; Pedigree; Young Adult; Zebrafish

Mutations of the Transcriptional Corepressor ZMYM2 Cause Syndromic Urinary Tract Malformations. - Connaughton, Dervla M; Dai, Rufeng; Owen, Danielle J; Marquez, Jonathan; Mann, Nina; GrAHm-Paquin, Adda L; Nakayama, Makiko; Coyaud, Etienne; Laurent, Estelle M N; St-Germain, Jonathan R; Blok, Lot Snijders; Vino, Arianna; et al. (Am J Hum Genet, 2020)
Congenital anomalies of the kidney and urinary tract (CAKUT) constitute one of the most frequent birth defects and represent the most common cause of chronic kidney disease in the first three decades of life. Despite the discovery of dozens of monogenic causes of CAKUT, most pathogenic pathways remain elusive. We performed whole-exome sequencing (WES) in 551 individuals with CAKUT and identified a heterozygous de novo stop-gain variant in ZMYM2 in two different families with CAKUT. Through collaboration, we identified in total 14 different heterozygous loss-of-function mutations in ZMYM2 in 15 unrelated families. Most mutations occurred de novo, indicating possible interference with reproductive function. Human disease features are replicated in X. tropicalis larvae with morpholino knockdowns, in which expression of truncated ZMYM2 proteins, based on individual mutations, failed to rescue renal and craniofacial defects. Moreover, heterozygous Zmym2-deficient mice recapitulated features of CAKUT with high penetrance. The ZMYM2 protein is a component of a transcriptional corepressor complex recently linked to the silencing of developmentally regulated endogenous retrovirus elements. Using protein-protein interaction assays, we show that ZMYM2 interacts with additional epigenetic silencing complexes, as well as confirming that it binds to FOXP1, a transcription factor that has also been linked to CAKUT. In summary, our findings establish that loss-of-function mutations of ZMYM2, and potentially that of other proteins in its interactome, as causes of human CAKUT, offering new routes for studying the pathogenesis of the disorder.
Keywords: Amphibian Proteins; Animals; Case-Control Studies; Child; Child, Preschool; DNA-Binding Proteins; Epigenesis, Genetic; Family; Female; Forkhead Transcription Factors; Heterozygote; Humans; Infant; Larva; Male; Mice; Mice, Knockout; Morpholinos; Mutation; Pedigree; Protein Binding; Repressor Proteins; Transcription Factors; Urinary Tract; Urogenital Abnormalities; Whole Exome Sequencing; Xenopus

Natural history of Ollier disease and Maffucci syndrome: Patient survey and review of clinical literature. - El Abiad, Jad M; Robbins, Sarah M; Cohen, Bernard; Levin, Adam S; Valle, David L; Morris, Carol D; de Macena Sobreira, Nara L (Am J Med Genet A, 2020)
Ollier disease (OD) and Maffucci syndrome (MS) are characterized by multiple enchondromas. Patients with MS also have benign vascular overgrowths that become malignant in 8.5% of cases. OD is characterized by multiple enchondromas, typically unilateral in distribution with a predilection for the appendicular skeleton. MS is characterized by multiple enchondromas bilaterally distributed in most of the cases. Both disorders feature multiple swellings on the extremity, deformity around the joints, limitations in joint mobility, scoliosis, bone shortening, leg-length discrepancy, gait disturbances, pain, loss of function, and pathological fractures. About 50% of patients with OD or MS develop a malignancy, such as chondrosarcoma, glioma, and ovarian juvenile granulosa cell tumor. To better understand the natural history of OD and MS, we reviewed 287 papers describing patients with OD and MS. We also created a survey that was distributed directly to 162 patients through Facebook. Here, we compare the review of the cases described in the literature to the survey's responses. The review of the literature showed that: the patients with OD are diagnosed at a younger age; the prevalence of chondrosarcomas among patients with OD or MS was ~30%; in four patients, vascular anomalies were identified in internal organs only; and, the prevalence of cancer among patients with OD or MS was ~50%. With these data, health care providers will better understand the natural history, severity, and prognosis of these diseases and the prevalence of malignancies in these patients. Here, we recommend new guidelines for the care of patients with OD and MS.
Keywords: Adolescent; Adult; Child; Child, Preschool; Chondrosarcoma; Enchondromatosis; Female; Granulosa Cell Tumor; Humans; Infant; Infant, Newborn; Male; Middle Aged; Ovarian Neoplasms; Prognosis; Young Adult

NEMF mutations that impair ribosome-associated quality control are associated with neuromuscular disease. - Martin, Paige B; Kigoshi-Tansho, Yu; Sher, Roger B; Ravenscroft, Gianina; Stauffer, Jennifer E; Kumar, Rajesh; Yonashiro, Ryo; Müller, Tina; Griffith, Christopher; Allen, William; Pehlivan, Davut; Harel, Tamar; et al. (Nat Commun, 2020)
A hallmark of neurodegeneration is defective protein quality control. The E3 ligase Listerin (LTN1/Ltn1) acts in a specialized protein quality control pathway-Ribosome-associated Quality Control (RQC)-by mediating proteolytic targeting of incomplete polypeptides produced by ribosome stalling, and Ltn1 mutation leads to neurodegeneration in mice. Whether neurodegeneration results from defective RQC and whether defective RQC contributes to human disease have remained unknown. Here we show that three independently-generated mouse models with mutations in a different component of the RQC complex, NEMF/Rqc2, develop progressive motor neuron degeneration. Equivalent mutations in yeast Rqc2 selectively interfere with its ability to modify aberrant translation products with C-terminal tails which assist with RQC-mediated protein degradation, suggesting a pathomechanism. Finally, we identify NEMF mutations expected to interfere with function in patients from seven families presenting juvenile neuromuscular disease. These uncover NEMF's role in translational homeostasis in the nervous system and implicate RQC dysfunction in causing neurodegeneration.
Keywords: Amino Acid Sequence; Animals; Female; Humans; Male; Mice; Mice, Knockout; Mutation; Neuromuscular Diseases; Proteolysis; Ribosomes; RNA-Binding Proteins; Saccharomyces cerevisiae; Saccharomyces cerevisiae Proteins; Sequence Alignment

Next Generation Sequencing of 134 Children with Autism Spectrum Disorder and Regression. - Yin, Jiani; Chun, Chun-An; Zavadenko, Nikolay N; Pechatnikova, Natalia L; Naumova, Oxana Yu; Doddapaneni, Harsha V; Hu, Jianhong; Muzny, Donna M; Schaaf, Christian P; Grigorenko, Elena L (Genes (Basel), 2020)
Approximately 30% of individuals with autism spectrum disorder (ASD) experience developmental regression, the etiology of which remains largely unknown. We performed a complete literature search and identified 47 genes that had been implicated in such cases. We sequenced these genes in a preselected cohort of 134 individuals with regressive autism. In total, 16 variants in 12 genes with evidence supportive of pathogenicity were identified. They were classified as variants of uncertain significance based on ACMG standards and guidelines. Among these were recurring variants in and , variants in genes that were linked to syndromic forms of ASD (, , , , , and ), and variants in the form of oligogenic heterozygosity (, , and ).
Keywords: Autism Spectrum Disorder; Child; Child, Preschool; Cohort Studies; Disease Progression; Female; Gene Expression Regulation; Genetic Markers; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Infant; Male; Mutation

Non-parametric Polygenic Risk Prediction via Partitioned GWAS Summary Statistics. - Chun, Sung; Imakaev, Maxim; Hui, Daniel; Patsopoulos, Nikolaos A; Neale, Benjamin M; Kathiresan, Sekar; Stitziel, Nathan O; Sunyaev, Shamil R (Am J Hum Genet, 2020)
In complex trait genetics, the ability to predict phenotype from genotype is the ultimate measure of our understanding of genetic architecture underlying the heritability of a trait. A complete understanding of the genetic basis of a trait should allow for predictive methods with accuracies approaching the trait's heritability. The highly polygenic nature of quantitative traits and most common phenotypes has motivated the development of statistical strategies focused on combining myriad individually non-significant genetic effects. Now that predictive accuracies are improving, there is a growing interest in the practical utility of such methods for predicting risk of common diseases responsive to early therapeutic intervention. However, existing methods require individual-level genotypes or depend on accurately specifying the genetic architecture underlying each disease to be predicted. Here, we propose a polygenic risk prediction method that does not require explicitly modeling any underlying genetic architecture. We start with summary statistics in the form of SNP effect sizes from a large GWAS cohort. We then remove the correlation structure across summary statistics arising due to linkage disequilibrium and apply a piecewise linear interpolation on conditional mean effects. In both simulated and real datasets, this new non-parametric shrinkage (NPS) method can reliably allow for linkage disequilibrium in summary statistics of 5 million dense genome-wide markers and consistently improves prediction accuracy. We show that NPS improves the identification of groups at high risk for breast cancer, type 2 diabetes, inflammatory bowel disease, and coronary heart disease, all of which have available early intervention or prevention treatments.
Keywords: Aged; Cohort Studies; Diabetes Mellitus, Type 2; Female; Genome-Wide Association Study; Genotype; Humans; Linkage Disequilibrium; Male; Middle Aged; Models, Genetic; Multifactorial Inheritance; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Novel congenital disorder of O-linked glycosylation caused by GALNT2 loss of function. - Zilmer, Monica; Edmondson, Andrew C; Khetarpal, Sumeet A; Alesi, Viola; Zaki, MAH S; Rostasy, Kevin; Madsen, Camilla G; Lepri, Francesca R; Sinibaldi, Lorenzo; Cusmai, Raffaella; Novelli, Antonio; Issa, Mahmoud Y; et al. (Brain, 2020)
Congenital disorders of glycosylation are a growing group of rare genetic disorders caused by deficient protein and lipid glycosylation. Here, we report the clinical, biochemical, and molecular features of seven patients from four families with GALNT2-congenital disorder of glycosylation (GALNT2-CDG), an O-linked glycosylation disorder. GALNT2 encodes the Golgi-localized polypeptide N-acetyl-d-galactosamine-transferase 2 isoenzyme. GALNT2 is widely expressed in most cell types and directs initiation of mucin-type protein O-glycosylation. All patients showed loss of O-glycosylation of apolipoprotein C-III, a non-redundant substrate for GALNT2. Patients with GALNT2-CDG generally exhibit a syndrome characterized by global developmental delay, intellectual disability with language deficit, autistic features, behavioural abnormalities, epilepsy, chronic insomnia, white matter changes on brain MRI, dysmorphic features, decreased stature, and decreased high density lipoprotein cholesterol levels. Rodent (mouse and rat) models of GALNT2-CDG recapitulated much of the human phenotype, including poor growth and neurodevelopmental abnormalities. In behavioural studies, GALNT2-CDG mice demonstrated cerebellar motor deficits, decreased sociability, and impaired sensory integration and processing. The multisystem nature of phenotypes in patients and rodent models of GALNT2-CDG suggest that there are multiple non-redundant protein substrates of GALNT2 in various tissues, including brain, which are critical to normal growth and development.
Keywords: Adolescent; Animals; Apolipoprotein C-III; Child; Child, Preschool; Developmental Disabilities; Female; Glycosylation; Humans; Loss of Function Mutation; Male; Mice; N-Acetylgalactosaminyltransferases; Pedigree; Rats; Young Adult

A novel homozygous KY variant causing a complex neurological disorder. - Arif, Beenish; Rasheed, Arisha; Kumar, Kishore R; Fatima, Amara; Abbas, Ghazanfar; Wohler, Elizabeth; Sobriera, Nara; Lohmann, Katja; Naz, Sadaf (Eur J Med Genet, 2020)
Mutations in the gene kyphoscoliosis peptidase (KY) are known to cause myofibrillar myopathy-7 and hereditary spastic paraplegia. We investigated the genetic cause of a complex neurological phenotype in a consanguineous Pakistani family with four affected members, manifesting lower limb spasticity and weakness, toe walking, pes equinovarus, and a speech disorder. Genome-wide linkage analysis with microsatellite markers delineated chromosome 3q22.2-q24 harboring the disease gene. Whole exome sequencing was performed for two subjects, identifying a homozygous 14-bp frameshift deletion NM_178554.6:c.842_855del; p(Val281GlyfsTer18) in KY. The variant segregated with the phenotype and was absent from public databases and 100 ethnically matched controls. We confirm a novel homozygous KY variant causing a complex neurological phenotype in this family. A review of previously reported KY variants suggests that variants in this gene can cause a spectrum of neurological phenotypes.
Keywords: Child; Female; Frameshift Mutation; Gait; Homozygote; Humans; Male; Myopathies, Structural, Congenital; Pedigree; Peptide Hydrolases; Phenotype; Spastic Paraplegia, Hereditary; Speech

A novel RFC1 repeat motif (ACAGG) in two Asia-Pacific CANVAS families. - Scriba, Carolin K; Beecroft, Sarah J; Clayton, Joshua S; Cortese, Andrea; Sullivan, Roisin; Yau, Wai Yan; Dominik, Natalia; Rodrigues, Miriam; Walker, Elizabeth; Dyer, Zoe; Wu, Teddy Y; Davis, Mark R; et al. (Brain, 2020)
Cerebellar ataxia, neuropathy and vestibular areflexia syndrome (CANVAS) is a progressive late-onset, neurological disease. Recently, a pentanucleotide expansion in intron 2 of RFC1 was identified as the genetic cause of CANVAS. We screened an Asian-Pacific cohort for CANVAS and identified a novel RFC1 repeat expansion motif, (ACAGG)exp, in three affected individuals. This motif was associated with additional clinical features including fasciculations and elevated serum creatine kinase. These features have not previously been described in individuals with genetically-confirmed CANVAS. Haplotype analysis showed our patients shared the same core haplotype as previously published, supporting the possibility of a single origin of the RFC1 disease allele. We analysed data from >26 000 genetically diverse individuals in gnomAD to show enrichment of (ACAGG) in non-European populations.
Keywords: Aged; Asian Continental Ancestry Group; Bilateral Vestibulopathy; Cerebellar Ataxia; Cohort Studies; DNA Repeat Expansion; Female; Humans; Indonesia; Male; Middle Aged; Pedigree; Replication Protein C

Organic Solute Transporter Alpha Deficiency: A Disorder With Cholestasis, Liver Fibrosis, and Congenital Diarrhea. - Gao, Emily; Cheema, Huma; Waheed, Nadia; Mushtaq, Iqra; Erden, Nihan; Nelson-Williams, Carol; Jain, Dhanpat; Soroka, Carol J; Boyer, James L; Khalil, Youssef; Clayton, Peter T; Mistry, Pramod K; et al. (Hepatology, 2020)
Keywords: Child, Preschool; Cholestasis; Diarrhea; Humans; Liver; Liver Cirrhosis; Male; Mutation; Pedigree; Receptors, G-Protein-Coupled

Paternal mosaicism for a novel PBX1 mutation associated with recurrent perinatal death: Phenotypic expansion of the PBX1-related syndrome. - Arts, Peer; Garland, Jessica; Byrne, Alicia B; Hardy, Tristan S E; Babic, Milena; Feng, Jinghua; Wang, Paul; Ha, Thuong; King-Smith, Sarah L; Schreiber, Andreas W; Crawford, April; Manton, Nick; et al. (Am J Med Genet A, 2020)
Autosomal dominant (de novo) mutations in PBX1 are known to cause congenital abnormalities of the kidney and urinary tract (CAKUT), with or without extra-renal abnormalities. Using trio exome sequencing, we identified a PBX1 p.(Arg107Trp) mutation in a deceased one-day-old neonate presenting with CAKUT, asplenia, and severe bilateral diaphragmatic thinning and eventration. Further investigation by droplet digital PCR revealed that the mutation had occurred post-zygotically in the father, with different variant allele frequencies of the mosaic PBX1 mutation in blood (10%) and sperm (20%). Interestingly, the father had subclinical hydronephrosis in childhood. With an expected recurrence risk of one in five, chorionic villus sampling and prenatal diagnosis for the PBX1 mutation identified recurrence in a subsequent pregnancy. The family opted to continue the pregnancy and the second affected sibling was stillborn at 35 weeks, presenting with similar severe bilateral diaphragmatic eventration, microsplenia, and complete sex reversal (46, XY female). This study highlights the importance of follow-up studies for presumed de novo and low-level mosaic variants and broadens the phenotypic spectrum of developmental abnormalities caused by PBX1 mutations.
Keywords: Congenital Abnormalities; Exome; Fathers; Female; Gene Frequency; Humans; Infant, Newborn; Kidney; Male; Mosaicism; Mutation; Perinatal Death; Pre-B-Cell Leukemia Transcription Factor 1; Pregnancy; Urinary Tract; Urogenital Abnormalities; Whole Exome Sequencing

Pathogenic Variants in CEP85L Cause Sporadic and Familial Posterior Predominant Lissencephaly. - Tsai, Meng-Han; Muir, Alison M; Wang, Won-Jing; Kang, Yi-Ning; Yang, Kun-Chuan; Chao, Nian-Hsin; Wu, Mei-Feng; Chang, Ying-Chao; Porter, Brenda E; Jansen, Laura A; Sebire, Guillaume; Deconinck, Nicolas; et al. (Neuron, 2020)
Lissencephaly (LIS), denoting a "smooth brain," is characterized by the absence of normal cerebral convolutions with abnormalities of cortical thickness. Pathogenic variants in over 20 genes are associated with LIS. The majority of posterior predominant LIS is caused by pathogenic variants in LIS1 (also known as PAFAH1B1), although a significant fraction remains without a known genetic etiology. We now implicate CEP85L as an important cause of posterior predominant LIS, identifying 13 individuals with rare, heterozygous CEP85L variants, including 2 families with autosomal dominant inheritance. We show that CEP85L is a centrosome protein localizing to the pericentriolar material, and knockdown of Cep85l causes a neuronal migration defect in mice. LIS1 also localizes to the centrosome, suggesting that this organelle is key to the mechanism of posterior predominant LIS.
Keywords: Adolescent; Adult; Age of Onset; Animals; Centrosome; Child; Child, Preschool; Chromosome Aberrations; Classical Lissencephalies and Subcortical Band Heterotopias; Cytoskeletal Proteins; Female; Gene Knockdown Techniques; Genetic Variation; Heterozygote; Humans; Infant; Magnetic Resonance Imaging; Male; Mice; Mutation; Oncogene Proteins, Fusion; Pedigree; Seizures; Young Adult

Phenotypic expansion of POGZ-related intellectual disability syndrome (White-Sutton syndrome). - Assia Batzir, Nurit; Posey, Jennifer E; Song, Xiaofei; Akdemir, Zeynep Coban; Rosenfeld, Jill A; Brown, Chester W; Chen, Emily; Holtrop, Shannon G; Mizerik, Elizabeth; Nieto Moreno, Margarita; Payne, Katelyn; Raas-Rothschild, Annick; et al. (Am J Med Genet A, 2020)
White-Sutton syndrome (WHSUS) is a recently-identified genetic disorder resulting from de novo heterozygous pathogenic variants in POGZ. Thus far, over 50 individuals have been reported worldwide, however phenotypic characterization and data regarding the natural history are still incomplete. Here we report the clinical features of 22 individuals with 21 unique loss of function POGZ variants. We observed a broad spectrum of intellectual disability and/or developmental delay with or without autism, and speech delay in all individuals. Other common problems included ocular abnormalities, hearing loss and gait abnormalities. A validated sleep disordered breathing questionnaire identified symptoms of obstructive sleep apnea in 4/12 (33%) individuals. A higher-than-expected proportion of cases also had gastrointestinal phenotypes, both functional and anatomical, as well as genitourinary anomalies. In line with previous publications, we observed an increased body mass index (BMI) z-score compared to the general population (mean 0.59, median 0.9; p 0.0253). Common facial features included microcephaly, broad forehead, midface hypoplasia, triangular mouth, broad nasal root and flat nasal bridge. Analysis of the Baylor Genetics clinical laboratory database revealed that POGZ variants were implicated in approximately 0.14% of cases who underwent clinical exome sequencing for neurological indications with or without involvement of other body systems. This study describes a greater allelic series and expands the phenotypic spectrum of this new syndromic form of intellectual disability and autism.
Keywords: Adolescent; Adult; Autistic Disorder; Child; Child, Preschool; Exome; Female; Heterozygote; Humans; Infant; Intellectual Disability; Language Development Disorders; Male; Microcephaly; Middle Aged; Mutation; Phenotype; Transposases; Whole Exome Sequencing; Young Adult

The pleiotropy associated with de novo variants in CHD4, CNOT3, and SETD5 extends to moyamoya angiopathy. - Pinard, Amelie; Guey, Stéphanie; Guo, Dongchuan; Cecchi, Alana C; Kharas, Natasha; Wallace, Stephanie; Regalado, Ellen S; Hostetler, Ellen M; Sharrief, Anjail Z; Bergametti, Françoise; Kossorotoff, Manoelle; Hervé, Dominique; et al. (Genet Med, 2020)
PURPOSE: Moyamoya angiopathy (MMA) is a cerebrovascular disease characterized by occlusion of large arteries, which leads to strokes starting in childhood. Twelve altered genes predispose to MMA but the majority of cases of European descent do not have an identified genetic trigger. METHODS: Exome sequencing from 39 trios were analyzed. RESULTS: We identified four de novo variants in three genes not previously associated with MMA: CHD4, CNOT3, and SETD5. Identification of additional rare variants in these genes in 158 unrelated MMA probands provided further support that rare pathogenic variants in CHD4 and CNOT3 predispose to MMA. Previous studies identified de novo variants in these genes in children with developmental disorders (DD), intellectual disability, and congenital heart disease. CONCLUSION: These genes encode proteins involved in chromatin remodeling, and taken together with previously reported genes leading to MMA-like cerebrovascular occlusive disease (YY1AP1, SMARCAL1), implicate disrupted chromatin remodeling as a molecular pathway predisposing to early onset, large artery occlusive cerebrovascular disease. Furthermore, these data expand the spectrum of phenotypic pleiotropy due to alterations of CHD4, CNOT3, and SETD5 beyond DD to later onset disease in the cerebrovascular arteries and emphasize the need to assess clinical complications into adulthood for genes associated with DD.
Keywords: Adult; Cell Cycle Proteins; Cerebrovascular Disorders; Child; Child, Preschool; Developmental Disabilities; DNA Helicases; Exome; Female; Genetic Predisposition to Disease; Humans; Intellectual Disability; Male; Methyltransferases; Mi-2 Nucleosome Remodeling and Deacetylase Complex; Middle Aged; Moyamoya Disease; Mutation; Nuclear Proteins; Transcription Factors; Whole Exome Sequencing

POGLUT1 biallelic mutations cause myopathy with reduced satellite cells, α-dystroglycan hypoglycosylation and a distinctive radiological pattern. - Servián-Morilla, E; Cabrera-Serrano, M; Johnson, K; Pandey, A; Ito, A; Rivas, E; Chamova, T; Muelas, N; Mongini, T; Nafissi, S; Claeys, K G; Grewal, R P; et al. (Acta Neuropathol, 2020)
Protein O-glucosyltransferase 1 (POGLUT1) activity is critical for the Notch signaling pathway, being one of the main enzymes responsible for the glycosylation of the extracellular domain of Notch receptors. A biallelic mutation in the POGLUT1 gene has been reported in one family as the cause of an adult-onset limb-girdle muscular dystrophy (LGMD R21; OMIM# 617232). As the result of a collaborative international effort, we have identified the first cohort of 15 patients with LGMD R21, from nine unrelated families coming from different countries, providing a reliable phenotype-genotype and mechanistic insight. Patients carrying novel mutations in POGLUT1 all displayed a clinical picture of limb-girdle muscle weakness. However, the age at onset was broadened from adult to congenital and infantile onset. Moreover, we now report that the unique muscle imaging pattern of "inside-to-outside" fatty degeneration observed in the original cases is indeed a defining feature of POGLUT1 muscular dystrophy. Experiments on muscle biopsies from patients revealed a remarkable and consistent decrease in the level of the NOTCH1 intracellular domain, reduction of the pool of satellite cells (SC), and evidence of α-dystroglycan hypoglycosylation. In vitro biochemical and cell-based assays suggested a pathogenic role of the novel POGLUT1 mutations, leading to reduced enzymatic activity and/or protein stability. The association between the POGLUT1 variants and the muscular phenotype was established by in vivo experiments analyzing the indirect flight muscle development in transgenic Drosophila, showing that the human POGLUT1 mutations reduced its myogenic activity. In line with the well-known role of the Notch pathway in the homeostasis of SC and muscle regeneration, SC-derived myoblasts from patients' muscle samples showed decreased proliferation and facilitated differentiation. Together, these observations suggest that alterations in SC biology caused by reduced Notch1 signaling result in muscular dystrophy in LGMD R21 patients, likely with additional contribution from α-dystroglycan hypoglycosylation. This study settles the muscular clinical phenotype linked to POGLUT1 mutations and establishes the pathogenic mechanism underlying this muscle disorder. The description of a specific imaging pattern of fatty degeneration and muscle pathology with a decrease of α-dystroglycan glycosylation provides excellent tools which will help diagnose and follow up LGMD R21 patients.
Keywords: Animals; Animals, Genetically Modified; Drosophila melanogaster; Dystroglycans; Female; Genetic Association Studies; Glucosyltransferases; Glycosylation; Humans; Male; Muscle, Skeletal; Muscular Dystrophies, Limb-Girdle; Mutation; Pedigree; Satellite Cells, Skeletal Muscle

Polygenic background modifies penetrance of monogenic variants for tier 1 genomic conditions. - Fahed, Akl C; Wang, Minxian; Homburger, Julian R; Patel, Aniruddh P; Bick, Alexander G; Neben, Cynthia L; Lai, Carmen; Brockman, Deanna; Philippakis, Anthony; Ellinor, Patrick T; Cassa, Christopher A; Lebo, Matthew; et al. (Nat Commun, 2020)
Genetic variation can predispose to disease both through (i) monogenic risk variants that disrupt a physiologic pathway with large effect on disease and (ii) polygenic risk that involves many variants of small effect in different pathways. Few studies have explored the interplay between monogenic and polygenic risk. Here, we study 80,928 individuals to examine whether polygenic background can modify penetrance of disease in tier 1 genomic conditions - familial hypercholesterolemia, hereditary breast and ovarian cancer, and Lynch syndrome. Among carriers of a monogenic risk variant, we estimate substantial gradients in disease risk based on polygenic background - the probability of disease by age 75 years ranged from 17% to 78% for coronary artery disease, 13% to 76% for breast cancer, and 11% to 80% for colon cancer. We propose that accounting for polygenic background is likely to increase accuracy of risk estimation for individuals who inherit a monogenic risk variant.
Keywords: Aged; Breast Neoplasms; Case-Control Studies; Colorectal Neoplasms; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Genome, Human; Humans; Male; Middle Aged; Multifactorial Inheritance; Odds Ratio; Penetrance; Risk Factors

Polymicrogyria is Associated With Pathogenic Variants in PTEN. - Shao, Diane D; Achkar, Christelle M; Lai, Abbe; Srivastava, Siddharth; Doan, Ryan N; Rodan, Lance H; Chen, Allen Y; Poduri, Annapurna; Yang, Edward; Walsh, Christopher A (Ann Neurol, 2020)
OBJECTIVE: Congenital structural brain malformations have been described in patients with pathogenic phosphatase and tensin homologue (PTEN) variants, but the frequency of cortical malformations in patients with PTEN variants and their impact on clinical phenotype are not well understood. Our goal was to systematically characterize brain malformations in patients with PTEN variants and assess the relevance of their brain malformations to clinical presentation. METHODS: We systematically searched a local radiology database for patients with PTEN variants who had available brain magnetic resonance imaging (MRI). The MRI scans were reviewed systematically for cortical abnormalities. We reviewed electroencephalogram (EEG) data and evaluated the electronic medical record for evidence of epilepsy and developmental delay. RESULTS: In total, we identified 22 patients with PTEN pathogenic variants for which brain MRIs were available (age range 0.4-17 years). Twelve among these 22 patients (54%) had polymicrogyria (PMG). Variants associated with PMG or atypical gyration encoded regions of the phosphatase or C2 domains of PTEN. Interestingly, epilepsy was present in only 2 of the 12 patients with PMG. We found a trend toward higher rates of global developmental delay (GDD), intellectual disability (ID), and motor delay in individuals with cortical abnormalities, although cohort size limited statistical significance. INTERPRETATION: Malformations of cortical development, PMG in particular, represent an under-recognized phenotype associated with PTEN pathogenic variants and may have an association with cognitive and motor delays. Epilepsy was infrequent compared to the previously reported high risk of epilepsy in patients with PMG. ANN NEUROL 2020;88:1153-1164.
Keywords: Adolescent; Brain; Child; Child, Preschool; Comorbidity; Databases, Genetic; Developmental Disabilities; Electroencephalography; Female; Humans; Infant; Intellectual Disability; Magnetic Resonance Imaging; Male; Massachusetts; Neuroimaging; Polymicrogyria; PTEN Phosphohydrolase

Posterior Neocortex-Specific Regulation of Neuronal Migration by CEP85L Identifies Maternal Centriole-Dependent Activation of CDK5. - Kodani, Andrew; Kenny, Connor; Lai, Abbe; Gonzalez, Dilenny M; Stronge, Edward; Sejourne, Gabrielle M; Isacco, Laura; Partlow, Jennifer N; O'Donnell, Anne; McWalter, Kirsty; Byrne, Alicia B; Barkovich, A James; et al. (Neuron, 2020)
Genes mutated in human neuronal migration disorders encode tubulin proteins and a variety of tubulin-binding and -regulating proteins, but it is very poorly understood how these proteins function together to coordinate migration. Additionally, the way in which regional differences in neocortical migration are controlled is completely unknown. Here we describe a new syndrome with remarkably region-specific effects on neuronal migration in the posterior cortex, reflecting de novo variants in CEP85L. We show that CEP85L is required cell autonomously in vivo and in vitro for migration, that it localizes to the maternal centriole, and that it forms a complex with many other proteins required for migration, including CDK5, LIS1, NDE1, KIF2A, and DYNC1H1. Loss of CEP85L disrupts CDK5 localization and activation, leading to centrosome disorganization and disrupted microtubule cytoskeleton organization. Together, our findings suggest that CEP85L highlights a complex that controls CDK5 activity to promote neuronal migration.
Keywords: Cell Movement; Centrioles; Child; Child, Preschool; Cyclin-Dependent Kinase 5; Cytoskeletal Proteins; Female; Humans; Lissencephaly; Male; Microtubules; Neocortex; Nerve Tissue Proteins; Neurons; Oncogene Proteins, Fusion; Young Adult

Rare deleterious variants of NOTCH1, GATA4, SMAD6, and ROBO4 are enriched in BAV with early onset complications but not in BAV with heritable thoracic aortic disease. - Musfee, Fadi I; Guo, Dongchuan; Pinard, Amélie C; Hostetler, Ellen M; Blue, Elizabeth E; Nickerson, Deborah A; Bamshad, Michael J; Milewicz, Dianna M; Prakash, Siddharth K (Mol Genet Genomic Med, 2020)
BACKGROUND: Bicuspid aortic valve (BAV) is the most common cardiovascular malformation in adults, with a prevalence of 0.5%-2%. The prevalence of BAV in cohorts who were ascertained due to thoracic aortic aneurysms or acute aortic dissections (TAD) is as high as 20%. However, the contribution of causal BAV genes to TAD is not known. Therefore, we evaluated rare deleterious variants of GATA4, NOTCH1, SMAD6, or ROBO4 in patients with BAV who presented with TAD. METHODS: Our cohort consisted of 487 probands with Heritable Thoracic Aortic Aneurysms or Dissections (HTAD, 12% BAV, 29% female) and 63 probands with Early onset complications of Bicuspid Aortic Valve disease (EBAV, 63% TAD, 34% female). After whole exome sequencing, we functionally annotated GATA4, NOTCH1, SMAD6, and ROBO4 variants and compared the prevalence of rare variants in these genes to controls without HTAD. RESULTS: We identified 11 rare deleterious variants of GATA4, SMAD6, or ROBO4 in 12 (18%) EBAV cases. The burden of rare SMAD6 and GATA4 variants was significantly enriched in EBAV but not in HTAD cases, even among HTAD cases with BAV (p < .003). CONCLUSION: Rare variants of NOTCH1, ROBO4, SMAD6, or GATA4 do not significantly contribute to BAV in cohorts with HTAD. We conclude that BAV patients who present with HTAD are a genetically distinct subgroup with implications for genetic testing and prognosis.
Keywords: Adult; Aortic Aneurysm, Thoracic; Bicuspid Aortic Valve Disease; Female; GATA4 Transcription Factor; Gene Frequency; Humans; Male; Middle Aged; Mutation; Receptor, Notch1; Receptors, Cell Surface; Smad6 Protein

Recurrent De Novo NAHR Reciprocal Duplications in the ATAD3 Gene Cluster Cause a Neurogenetic Trait with Perturbed Cholesterol and Mitochondrial Metabolism. - Gunning, Adam C; Strucinska, Klaudia; Muñoz Oreja, Mikel; Parrish, Andrew; Caswell, Richard; Stals, Karen L; Durigon, Romina; Durlacher-Betzer, Karina; Cunningham, Mitchell H; Grochowski, Christopher M; Baptista, Julia; Tysoe, Carolyn; et al. (Am J Hum Genet, 2020)
Recent studies have identified both recessive and dominant forms of mitochondrial disease that result from ATAD3A variants. The recessive form includes subjects with biallelic deletions mediated by non-allelic homologous recombination. We report five unrelated neonates with a lethal metabolic disorder characterized by cardiomyopathy, corneal opacities, encephalopathy, hypotonia, and seizures in whom a monoallelic reciprocal duplication at the ATAD3 locus was identified. Analysis of the breakpoint junction fragment indicated that these 67 kb heterozygous duplications were likely mediated by non-allelic homologous recombination at regions of high sequence identity in ATAD3A exon 11 and ATAD3C exon 7. At the recombinant junction, the duplication allele produces a fusion gene derived from ATAD3A and ATAD3C, the protein product of which lacks key functional residues. Analysis of fibroblasts derived from two affected individuals shows that the fusion gene product is expressed and stable. These cells display perturbed cholesterol and mitochondrial DNA organization similar to that observed for individuals with severe ATAD3A deficiency. We hypothesize that the fusion protein acts through a dominant-negative mechanism to cause this fatal mitochondrial disorder. Our data delineate a molecular diagnosis for this disorder, extend the clinical spectrum associated with structural variation at the ATAD3 locus, and identify a third mutational mechanism for ATAD3 gene cluster variants. These results further affirm structural variant mutagenesis mechanisms in sporadic disease traits, emphasize the importance of copy number analysis in molecular genomic diagnosis, and highlight some of the challenges of detecting and interpreting clinically relevant rare gene rearrangements from next-generation sequencing data.
Keywords: Amino Acid Sequence; ATPases Associated with Diverse Cellular Activities; Brain Diseases; Cardiomyopathies; Cholesterol; Corneal Opacity; DNA Copy Number Variations; Female; Gene Duplication; Gene Rearrangement; Homologous Recombination; Humans; Infant; Infant, Newborn; Male; Membrane Proteins; Mitochondria; Mitochondrial Diseases; Mitochondrial Proteins; Muscle Hypotonia; Mutation; Protein Conformation; Seizures; Sequence Homology

Recurrent homozygous damaging mutation in , encoding a protein disulfide isomerase, in four families with microlissencephaly. - Ghosh, Shereen Georges; Wang, Lu; Breuss, Martin W; Green, Joshua D; Stanley, Valentina; Yang, Xiaoxu; Ross, Danica; Traynor, Bryan J; Alhashem, Amal M; Azam, Matloob; Selim, Laila; Bastaki, Laila; et al. (J Med Genet, 2020)
BACKGROUND: Protein disulfide isomerase (PDI) proteins are part of the thioredoxin protein superfamily. PDIs are involved in the formation and rearrangement of disulfide bonds between cysteine residues during protein folding in the endoplasmic reticulum and are implicated in stress response pathways. METHODS: Eight children from four consanguineous families residing in distinct geographies within the Middle East and Central Asia were recruited for study. All probands showed structurally similar microcephaly with lissencephaly (microlissencephaly) brain malformations. DNA samples from each family underwent whole exome sequencing, assessment for repeat expansions and confirmatory segregation analysis. RESULTS: An identical homozygous variant in (c.500G>A), encoding thioredoxin-related transmembrane protein 2, segregated with disease in all four families. This variant changed the last coding base of exon 6, and impacted mRNA stability. All patients presented with microlissencephaly, global developmental delay, intellectual disability and epilepsy. While is an activator of cellular repeat expansion toxicity, patients showed no evidence of repeat expansions. CONCLUSION: The c.500G>A allele associates with recessive microlissencephaly, and patients show no evidence of expansions. is the first PDI implicated in a recessive disease, suggesting a protein isomerisation defect in microlissencephaly.
Keywords: Amino Acid Sequence; Child; Child, Preschool; Consanguinity; Endoplasmic Reticulum; Exons; Female; Genetic Predisposition to Disease; Homozygote; Humans; Male; Membrane Proteins; Microcephaly; Mutation; Protein Disulfide-Isomerases; Protein Folding; Thioredoxins; Whole Exome Sequencing

Recurrent Rare Copy Number Variants Increase Risk for Esotropia. - Whitman, Mary C; Di Gioia, Silvio Alessandro; Chan, Wai-Man; Gelber, Alon; Pratt, Brandon M; Bell, Jessica L; Collins, Thomas E; Knowles, James A; Armoskus, Christopher; Pato, Michele; Pato, Carlos; Shaaban, Sherin; et al. (Invest Ophthalmol Vis Sci, 2020)
Purpose: To determine whether rare copy number variants (CNVs) increase risk for comitant esotropia. Methods: CNVs were identified in 1614 Caucasian individuals with comitant esotropia and 3922 Caucasian controls from Illumina SNP genotyping using two Hidden Markov model (HMM) algorithms, PennCNV and QuantiSNP, which call CNVs based on logR ratio and B allele frequency. Deletions and duplications greater than 10 kb were included. Common CNVs were excluded. Association testing was performed with 1 million permutations in PLINK. Significant CNVs were confirmed with digital droplet polymerase chain reaction (ddPCR). Whole genome sequencing was performed to determine insertion location and breakpoints. Results: Esotropia patients have similar rates and proportions of CNVs compared with controls but greater total length and average size of both deletions and duplications. Three recurrent rare duplications significantly (P = 1 × 10-6) increase the risk of esotropia: chromosome 2p11.2 (hg19, 2:87428677-87965359), spanning one long noncoding RNA (lncRNA) and two microRNAs (OR 14.16; 95% confidence interval [CI] 5.4-38.1); chromosome 4p15.2 (hg19, 4:25554332-25577184), spanning one lncRNA (OR 11.1; 95% CI 4.6-25.2); chromosome 10q11.22 (hg19, 10:47049547-47703870) spanning seven protein-coding genes, one lncRNA, and four pseudogenes (OR 8.96; 95% CI 5.4-14.9). Overall, 114 cases (7%) and only 28 controls (0.7%) had one of the three rare duplications. No case nor control had more than one of these three duplications. Conclusions: Rare CNVs are a source of genetic variation that contribute to the genetic risk for comitant esotropia, which is likely polygenic. Future research into the functional consequences of these recurrent duplications may shed light on the pathophysiology of esotropia.
Keywords: Case-Control Studies; DNA Copy Number Variations; Esotropia; Female; Gene Duplication; Gene Frequency; Genetic Predisposition to Disease; Genotyping Techniques; Humans; Infant; Male; Markov Chains; Polymerase Chain Reaction; Risk Factors

RNA Identification of PRIME Cells Predicting Rheumatoid Arthritis Flares. - Orange, Dana E; Yao, Vicky; Sawicka, Kirsty; Fak, John; Frank, Mayu O; Parveen, Salina; Blachere, Nathalie E; Hale, Caryn; Zhang, Fan; Raychaudhuri, Soumya; Troyanskaya, Olga G; Darnell, Robert B (N Engl J Med, 2020)
BACKGROUND: Rheumatoid arthritis, like many inflammatory diseases, is characterized by episodes of quiescence and exacerbation (flares). The molecular events leading to flares are unknown. METHODS: We established a clinical and technical protocol for repeated home collection of blood in patients with rheumatoid arthritis to allow for longitudinal RNA sequencing (RNA-seq). Specimens were obtained from 364 time points during eight flares over a period of 4 years in our index patient, as well as from 235 time points during flares in three additional patients. We identified transcripts that were differentially expressed before flares and compared these with data from synovial single-cell RNA-seq. Flow cytometry and sorted-blood-cell RNA-seq in additional patients were used to validate the findings. RESULTS: Consistent changes were observed in blood transcriptional profiles 1 to 2 weeks before a rheumatoid arthritis flare. B-cell activation was followed by expansion of circulating CD45-CD31-PDPN+ preinflammatory mesenchymal, or PRIME, cells in the blood from patients with rheumatoid arthritis; these cells shared features of inflammatory synovial fibroblasts. Levels of circulating PRIME cells decreased during flares in all 4 patients, and flow cytometry and sorted-cell RNA-seq confirmed the presence of PRIME cells in 19 additional patients with rheumatoid arthritis. CONCLUSIONS: Longitudinal genomic analysis of rheumatoid arthritis flares revealed PRIME cells in the blood during the period before a flare and suggested a model in which these cells become activated by B cells in the weeks before a flare and subsequently migrate out of the blood into the synovium. (Funded by the National Institutes of Health and others.).
Keywords: Adult; Arthritis, Rheumatoid; B-Lymphocytes; Female; Fibroblasts; Flow Cytometry; Gene Expression; Humans; Male; Mesenchymal Stem Cells; Middle Aged; Patient Acuity; Sequence Analysis, RNA; Surveys and Questionnaires; Symptom Flare Up; Synovial Fluid

Serum sphingolipids and incident diabetes in a US population with high diabetes burden: the Hispanic Community Health Study/Study of Latinos (HCHS/SOL). - Chen, Guo-Chong; Chai, Jin Choul; Yu, Bing; Michelotti, Gregory A; Grove, Megan L; Fretts, Amanda M; Daviglus, Martha L; Garcia-Bedoya, Olga L; Thyagarajan, Bharat; Schneiderman, Neil; Cai, Jianwen; Kaplan, Robert C; et al. (Am J Clin Nutr, 2020)
BACKGROUND: Genetic or pharmacological inhibition of de novo sphingolipid synthases prevented diabetes in animal studies. OBJECTIVES: We sought to evaluate prospective associations of serum sphingolipids with incident diabetes in a population-based cohort. METHODS: We included 2010 participants of the Hispanic Community Health Study/Study of Latinos (HCHS/SOL) aged 18-74 y who were free of diabetes and other major chronic diseases at baseline (2008-2011). Metabolomic profiling of fasting serum was performed using a global, untargeted approach. A total of 43 sphingolipids were quantified and, considering subclasses and chemical structures of individual species, 6 sphingolipid scores were constructed. Diabetes status was assessed using standard procedures including blood tests. Multivariable survey Poisson regressions were applied to estimate RR and 95% CI of incident diabetes associated with individual sphingolipids or sphingolipid scores. RESULTS: There were 224 incident cases of diabetes identified during, on average, 6 y of follow-up. After adjustment for socioeconomic and lifestyle factors, a ceramide score (RR Q4 versus Q1 = 2.40; 95% CI: 1.24, 4.65; P-trend = 0.003) and a score of sphingomyelins with fully saturated sphingoid-fatty acid pairs (RR Q4 versus Q1 = 3.15; 95% CI: 1.75, 5.67; P-trend <0.001) both were positively associated with risk of diabetes, whereas scores of glycosylceramides, lactosylceramides, or other unsaturated sphingomyelins (even if having an SFA base) were not associated with risk of diabetes. After additional adjustment for numerous traditional risk factors (especially triglycerides), both associations were attenuated and only the saturated-sphingomyelin score remained associated with risk of diabetes (RR Q4 versus Q1 = 1.98; 95% CI: 1.09, 3.59; P-trend = 0.031). CONCLUSIONS: Our findings suggest that a cluster of saturated sphingomyelins may be associated with elevated risk of diabetes beyond traditional risk factors, which needs to be verified in other population studies. This study was registered at clinicaltrials.gov as NCT02060344.
Keywords: Adolescent; Adult; Aged; Diabetes Mellitus; Female; Hispanic Americans; Humans; Male; Middle Aged; Prospective Studies; Risk Factors; Sphingolipids; United States; Young Adult

Severe neurodevelopmental disease caused by a homozygous TLK2 variant. - Topf, Ana; Oktay, Yavuz; Balaraju, Sunitha; Yilmaz, Elmasnur; Sonmezler, Ece; Yis, Uluc; Laurie, Steven; Thompson, Rachel; Roos, Andreas; MacArthur, Daniel G; Yaramis, Ahmet; Güngör, Serdal; et al. (Eur J Hum Genet, 2020)
A distinct neurodevelopmental phenotype characterised mainly by mild motor and language delay and facial dysmorphism, caused by heterozygous de novo or dominant variants in the TLK2 gene has recently been described. All cases reported carried either truncating variants located throughout the gene, or missense changes principally located at the C-terminal end of the protein mostly resulting in haploinsufficiency of TLK2. Through whole exome sequencing, we identified a homozygous missense variant in TLK2 in a patient showing more severe symptoms than those previously described, including cerebellar vermis hypoplasia and West syndrome. Both parents are heterozygous for the variant and clinically unaffected highlighting that recessive variants in TLK2 can also be disease causing and may act through a different pathomechanism.
Keywords: Adult; Cerebellum; Child; Developmental Disabilities; Female; Heterozygote; Homozygote; Humans; Infant; Male; Mutation, Missense; Nervous System Malformations; Pedigree; Protein Kinases; Spasms, Infantile

A structural variation reference for medical and population genetics. - Collins, Ryan L; Brand, Harrison; Karczewski, Konrad J; Zhao, Xuefang; Alföldi, Jessica; Francioli, Laurent C; Khera, Amit V; Lowther, Chelsea; Gauthier, Laura D; Wang, Harold; Watts, Nicholas A; Solomonson, Matthew; et al. (Nature, 2020)
Structural variants (SVs) rearrange large segments of DNA and can have profound consequences in evolution and human disease. As national biobanks, disease-association studies, and clinical genetic testing have grown increasingly reliant on genome sequencing, population references such as the Genome Aggregation Database (gnomAD) have become integral in the interpretation of single-nucleotide variants (SNVs). However, there are no reference maps of SVs from high-coverage genome sequencing comparable to those for SNVs. Here we present a reference of sequence-resolved SVs constructed from 14,891 genomes across diverse global populations (54% non-European) in gnomAD. We discovered a rich and complex landscape of 433,371 SVs, from which we estimate that SVs are responsible for 25-29% of all rare protein-truncating events per genome. We found strong correlations between natural selection against damaging SNVs and rare SVs that disrupt or duplicate protein-coding sequence, which suggests that genes that are highly intolerant to loss-of-function are also sensitive to increased dosage. We also uncovered modest selection against noncoding SVs in cis-regulatory elements, although selection against protein-truncating SVs was stronger than all noncoding effects. Finally, we identified very large (over one megabase), rare SVs in 3.9% of samples, and estimate that 0.13% of individuals may carry an SV that meets the existing criteria for clinically important incidental findings. This SV resource is freely distributed via the gnomAD browser and will have broad utility in population genetics, disease-association studies, and diagnostic screening.
Keywords: Continental Population Groups; Disease; Female; Genetic Testing; Genetic Variation; Genetics, Medical; Genetics, Population; Genome, Human; Genotyping Techniques; Humans; Male; Middle Aged; Mutation; Polymorphism, Single Nucleotide; Reference Standards; Selection, Genetic; Whole Genome Sequencing

Successful treatment of intractable epilepsy with ketogenic diet therapy in twins with ALG3-CDG. - Paketci, C; Edem, P; Hiz, S; Sonmezler, E; Soydemir, D; Sarikaya Uzan, G; Oktay, Y; O'Heir, E; Beltran, S; Laurie, S; Töpf, A; Lochmuller, H; et al. (Brain Dev, 2020)
BACKGROUND: Congenital disorders of glycosylation (CDG) is a heterogeneous group of congenital metabolic diseases with multisystem clinical involvement. ALG3-CDG is a very rare subtype with only 24 cases reported so far. CASE: Here, we report two siblings with dysmorphic features, growth retardation, microcephaly, intractable epilepsy, and hemangioma in the frontal, occipital and lumbosacral regions. RESULTS: We studied two siblings by whole exome sequencing. A pathogenic variant in ALG3 (NM_005787.6: c.165C > T; p.Gly55=) that had been previously associated with congenital glycolysis defect type 1d was identified. Their intractable seizures were controlled by ketogenic diet. CONCLUSION: Although prominent findings of growth retardation and microcephaly seen in our patients have been extensively reported before, presence of hemangioma is a novel finding that may be used as an indication for ALG3-CDG diagnosis. Our patients are the first reported cases whose intractable seizures were controlled with ketogenic diet. This report adds ketogenic diet as an option for treatment of intractable epilepsy in ALG3-CDG.
Keywords: Central Nervous System Neoplasms; Congenital Disorders of Glycosylation; Craniofacial Abnormalities; Developmental Disabilities; Diet, Ketogenic; Drug Resistant Epilepsy; Female; Hemangioma; Humans; Infant; Male; Mannosyltransferases; Twins; Whole Exome Sequencing

TBX6 missense variants expand the mutational spectrum in a non-Mendelian inheritance disease. - Chen, Weisheng; Lin, Jiachen; Wang, Lianlei; Li, Xiaoxin; Zhao, Sen; Liu, Jiaqi; Akdemir, Zeynep C; Zhao, Yanxue; Du, Renqian; Ye, Yongyu; Song, Xiaofei; Zhang, Yuanqiang; et al. (Hum Mutat, 2020)
Congenital scoliosis (CS) is a birth defect with variable clinical and anatomical manifestations due to spinal malformation. The genetic etiology underlying about 10% of CS cases in the Chinese population is compound inheritance by which the gene dosage is reduced below that of haploinsufficiency. In this genetic model, the trait manifests as a result of the combined effect of a rare variant and common pathogenic variant allele at a locus. From exome sequencing (ES) data of 523 patients in Asia and two patients in Texas, we identified six TBX6 gene-disruptive variants from 11 unrelated CS patients via ES and in vitro functional testing. The in trans mild hypomorphic allele was identified in 10 of the 11 subjects; as anticipated these 10 shared a similar spinal deformity of hemivertebrae. The remaining case has a homozygous variant in TBX6 (c.418C>T) and presents a more severe spinal deformity phenotype. We found decreased transcriptional activity and abnormal cellular localization as the molecular mechanisms for TBX6 missense loss-of-function alleles. Expanding the mutational spectrum of TBX6 pathogenic alleles enabled an increased molecular diagnostic detection rate, provided further evidence for the gene dosage-dependent genetic model underlying CS, and refined clinical classification.
Keywords: Alleles; Cell Line; Female; Gene Expression; Genes, Reporter; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Inheritance Patterns; Male; Models, Molecular; Molecular Diagnostic Techniques; Mutation, Missense; Phenotype; Protein Conformation; Radiography; Sequence Analysis, DNA; Spine; Structure-Activity Relationship; T-Box Domain Proteins; Whole Exome Sequencing

Titin Truncating Variants in Adults Without Known Congestive Heart Failure. - Pirruccello, James P; Bick, Alexander; Chaffin, Mark; Aragam, Krishna G; Choi, Seung Hoan; Lubitz, Steven A; Ho, Carolyn Y; Ng, Kenney; Philippakis, Anthony; Ellinor, Patrick T; Kathiresan, Sekar; Khera, Amit V (J Am Coll Cardiol, 2020)
Keywords: Adult; Aged; Asymptomatic Diseases; Connectin; Female; Genetic Variation; Heart Failure; Humans; Male; Middle Aged

truncations cause arrhythmogenic right ventricular cardiomyopathy. - Brun, Francesca; Gigli, Marta; Graw, Sharon L; Judge, Daniel P; Merlo, Marco; Murray, Brittney; Calkins, Hugh; Sinagra, Gianfranco; Taylor, Matthew Rg; Mestroni, Luisa; James, Cynthia A (J Med Genet, 2020)
BACKGROUND: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a heart muscle disease that affects predominantly the right ventricle and is part of the spectrum of arrythmogenic cardiomyopathies (ACMs). ARVC is a genetic condition; however, a pathogenic gene variant is found in only half of patients. OBJECTIVE: Filamin C gene truncations () have recently been identified in dilated cardiomyopathy with ventricular arrhythmia and sudden cardiac death, a phenotype partially overlapping with ARVC and part of the ACM spectrum. We hypothesised that could be a novel gene associated with ARVC. METHODS: One hundred fifty-six patients meeting 2010 ARVC Task Force Criteria and lacking variants in known ARVC genes were evaluated for variants. Available family members were tested for cosegregation. RESULTS: We identified two unique variants in two families (c.6565 G>T, p.Glu2189Ter and c.8107delG, p.Asp2703ThrfsTer69), with phenotypes of dominant RV disease fulfilling 'definite' diagnosis of ARVC according to the 2010 Task Force Criteria. Variants in other cardiomyopathy genes were excluded in both kindreds, and segregation analysis revealed that p.Asp2703ThrfsTer69 was a de novo variant. In both families, the disease phenotype was characterised by prominent ventricular arrhythmias and sudden cardiac arrest. CONCLUSION: The identification of as a novel cause of ARVC in two unrelated families expands the spectrum of ARVC disease genes for this disorder. Our findings should prompt inclusion of genetic testing in ARVC to improve diagnostic yield and testing of at-risk relatives in ARVC.
Keywords: Adult; Aged; Arrhythmogenic Right Ventricular Dysplasia; Female; Filamins; Genetic Predisposition to Disease; Genetic Testing; Heart Ventricles; Humans; Male; Middle Aged; Mutation; Phenotype

Tyrosyl phosphorylation of PZR promotes hypertrophic cardiomyopathy in PTPN11-associated Noonan syndrome with multiple lentigines. - Yi, Jae-Sung; Perla, Sravan; Enyenihi, Liz; Bennett, Anton M (JCI Insight, 2020)
Noonan syndrome with multiple lentigines (NSML) is a rare autosomal dominant disorder that presents with cardio-cutaneous-craniofacial defects. Hypertrophic cardiomyopathy (HCM) represents the major life-threatening presentation in NSML. Mutations in the PTPN11 gene that encodes for the protein tyrosine phosphatase (PTP), SHP2, represents the predominant cause of HCM in NSML. NSML-associated PTPN11 mutations render SHP2 catalytically inactive with an "open" conformation. NSML-associated PTPN11 mutations cause hypertyrosyl phosphorylation of the transmembrane glycoprotein, protein zero-related (PZR), resulting in increased SHP2 binding. Here we show that NSML mice harboring a tyrosyl phosphorylation-defective mutant of PZR (NSML/PZRY242F) that is defective for SHP2 binding fail to develop HCM. Enhanced AKT/S6 kinase signaling in heart lysates of NSML mice was reversed in NSML/PZRY242F mice, demonstrating that PZR/SHP2 interactions promote aberrant AKT/S6 kinase activity in NSML. Enhanced PZR tyrosyl phosphorylation in the hearts of NSML mice was found to drive myocardial fibrosis by engaging an Src/NF-κB pathway, resulting in increased activation of IL-6. Increased expression of IL-6 in the hearts of NSML mice was reversed in NSML/PZRY242F mice, and PZRY242F mutant fibroblasts were defective for IL-6 secretion and STAT3-mediated fibrogenesis. These results demonstrate that NSML-associated PTPN11 mutations that induce PZR hypertyrosyl phosphorylation trigger pathophysiological signaling that promotes HCM and cardiac fibrosis.
Keywords: Animals; Cardiomyopathy, Hypertrophic; Disease Models, Animal; Female; Intracellular Signaling Peptides and Proteins; LEOPARD Syndrome; Male; Mice; Mice, Inbred C57BL; Mice, Knockout; Mutation; Myocytes, Cardiac; Phosphoproteins; Phosphorylation; Protein Tyrosine Phosphatase, Non-Receptor Type 11; Tyrosine

Validation of a Genome-Wide Polygenic Score for Coronary Artery Disease in South Asians. - Wang, Minxian; Menon, Ramesh; Mishra, Sanghamitra; Patel, Aniruddh P; Chaffin, Mark; Tanneeru, Deepak; Deshmukh, Manjari; Mathew, Oshin; Apte, Sanika; Devanboo, Christina S; Sundaram, Sumathi; Lakshmipathy, Praveena; et al. (J Am Coll Cardiol, 2020)
BACKGROUND: Genome-wide polygenic scores (GPS) integrate information from many common DNA variants into a single number. Because rates of coronary artery disease (CAD) are substantially higher among South Asians, a GPS to identify high-risk individuals may be particularly useful in this population. OBJECTIVES: This analysis used summary statistics from a prior genome-wide association study to derive a new GPS for South Asians. METHODS: This GPS was validated in 7,244 South Asian UK Biobank participants and tested in 491 individuals from a case-control study in Bangladesh. Next, a static ancestry and GPS reference distribution was built using whole-genome sequencing from 1,522 Indian individuals, and a framework was tested for projecting individuals onto this static ancestry and GPS reference distribution using 1,800 CAD cases and 1,163 control subjects newly recruited in India. RESULTS: The GPS, containing 6,630,150 common DNA variants, had an odds ratio (OR) per SD of 1.58 in South Asian UK Biobank participants and 1.60 in the Bangladeshi study (p < 0.001 for each). Next, individuals of the Indian case-control study were projected onto static reference distributions, observing an OR/SD of 1.66 (p < 0.001). Compared with the middle quintile, risk for CAD was most pronounced for those in the top 5% of the GPS distribution-ORs of 4.16, 2.46, and 3.22 in the South Asian UK Biobank, Bangladeshi, and Indian studies, respectively (p < 0.05 for each). CONCLUSIONS: The new GPS has been developed and tested using 3 distinct South Asian studies, and provides a generalizable framework for ancestry-specific GPS assessment.
Keywords: Adult; Aged; Bangladesh; Case-Control Studies; Coronary Artery Disease; Female; Genome-Wide Association Study; Humans; India; Male; Middle Aged; Multifactorial Inheritance

Wolff-Parkinson-White syndrome: De novo variants and evidence for mutational burden in genes associated with atrial fibrillation. - Coban-Akdemir, Zeynep H; Charng, Wu-Lin; Azamian, Mahshid; Paine, Ingrid S; Punetha, Jaya; Grochowski, Christopher M; Gambin, Tomasz; Valdes, Santiago O; Cannon, Bryan; Zapata, Gladys; Hernandez, Patricia P; Jhangiani, Shalini; et al. (Am J Med Genet A, 2020)
BACKGROUND: Wolff-Parkinson-White (WPW) syndrome is a relatively common arrhythmia affecting ~1-3/1,000 individuals. Mutations in PRKAG2 have been described in rare patients in association with cardiomyopathy. However, the genetic basis of WPW in individuals with a structurally normal heart remains poorly understood. Sudden death due to atrial fibrillation (AF) can also occur in these individuals. Several studies have indicated that despite ablation of an accessory pathway, the risk of AF remains high in patients compared to general population. METHODS: We applied exome sequencing in 305 subjects, including 65 trios, 80 singletons, and 6 multiple affected families. We used de novo analysis, candidate gene approach, and burden testing to explore the genetic contributions to WPW. RESULTS: A heterozygous deleterious variant in PRKAG2 was identified in one subject, accounting for 0.6% (1/151) of the genetic basis of WPW in this study. Another individual with WPW and left ventricular hypertrophy carried a known pathogenic variant in MYH7. We found rare de novo variants in genes associated with arrhythmia and cardiomyopathy (ANK2, NEBL, PITX2, and PRDM16) in this cohort. There was an increased burden of rare deleterious variants (MAF ≤ 0.005) with CADD score ≥ 25 in genes linked to AF in cases compared to controls (P = .0023). CONCLUSIONS: Our findings show an increased burden of rare deleterious variants in genes linked to AF in WPW syndrome, suggesting that genetic factors that determine the development of accessory pathways may be linked to an increased susceptibility of atrial muscle to AF in a subset of patients.
Keywords: Adolescent; Adult; AMP-Activated Protein Kinases; Ankyrins; Atrial Fibrillation; Carrier Proteins; Child; Cohort Studies; Cytoskeletal Proteins; DNA-Binding Proteins; Female; Genetic Association Studies; Genetic Predisposition to Disease; Heart Atria; Homeodomain Proteins; Humans; LIM Domain Proteins; Male; Mutation; Transcription Factors; Whole Exome Sequencing; Wolff-Parkinson-White Syndrome; Young Adult

X-chromosome association studies of congenital heart defects. - Agopian, A J; Hoang, Thanh T; Goldmuntz, Elizabeth; Hakonarson, Hakon; Musfee, Fadi I; Mitchell, Laura E (Am J Med Genet A, 2020)
Keywords: Chromosome Deletion; Chromosomes, Human, X; Female; Genes, X-Linked; Genetic Association Studies; Genetic Predisposition to Disease; Heart Defects, Congenital; Humans; Male

Xq22 deletions and correlation with distinct neurological disease traits in females: Further evidence for a contiguous gene syndrome. - Hijazi, Hadia; Coelho, Fernanda S; Gonzaga-Jauregui, Claudia; Bernardini, Laura; Mar, Soe S; Manning, Melanie A; Hanson-Kahn, Andrea; Naidu, Sakkubai; Srivastava, Siddharth; Lee, Jennifer A; Jones, Julie R; Friez, Michael J; et al. (Hum Mutat, 2020)
Xq22 deletions that encompass PLP1 (Xq22-PLP1-DEL) are notable for variable expressivity of neurological disease traits in females ranging from a mild late-onset form of spastic paraplegia type 2 (MIM# 312920), sometimes associated with skewed X-inactivation, to an early-onset neurological disease trait (EONDT) of severe developmental delay, intellectual disability, and behavioral abnormalities. Size and gene content of Xq22-PLP1-DEL vary and were proposed as potential molecular etiologies underlying variable expressivity in carrier females where two smallest regions of overlap (SROs) were suggested to influence disease. We ascertained a cohort of eight unrelated patients harboring Xq22-PLP1-DEL and performed high-density array comparative genomic hybridization and breakpoint-junction sequencing. Molecular characterization of Xq22-PLP1-DEL from 17 cases (eight herein and nine published) revealed an overrepresentation of breakpoints that reside within repeats (11/17, ~65%) and the clustering of ~47% of proximal breakpoints in a genomic instability hotspot with characteristic non-B DNA density. These findings implicate a potential role for genomic architecture in stimulating the formation of Xq22-PLP1-DEL. The correlation of Xq22-PLP1-DEL gene content with neurological disease trait in female cases enabled refinement of the associated SROs to a single genomic interval containing six genes. Our data support the hypothesis that genes contiguous to PLP1 contribute to EONDT.
Keywords: Child; Child, Preschool; Chromosome Breakpoints; Chromosome Deletion; Chromosome Mapping; Chromosomes, Human, X; Comparative Genomic Hybridization; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Male; Nervous System Diseases; Pedigree; Phenotype; Quantitative Trait, Heritable; Repetitive Sequences, Nucleic Acid; Sex Factors; Syndrome; X Chromosome Inactivation

Biallelic mutations in valyl-tRNA synthetase gene VARS are associated with a progressive neurodevelopmental epileptic encephalopathy. - Friedman, Jennifer; Smith, Desiree E; Issa, Mahmoud Y; Stanley, Valentina; Wang, Rengang; Mendes, Marisa I; Wright, Meredith S; Wigby, Kristen; Hildreth, Amber; Crawford, John R; Koehler, Alanna E; Chowdhury, Shimul; et al. (Nat Commun, 2019)
Aminoacyl-tRNA synthetases (ARSs) function to transfer amino acids to cognate tRNA molecules, which are required for protein translation. To date, biallelic mutations in 31 ARS genes are known to cause recessive, early-onset severe multi-organ diseases. VARS encodes the only known valine cytoplasmic-localized aminoacyl-tRNA synthetase. Here, we report seven patients from five unrelated families with five different biallelic missense variants in VARS. Subjects present with a range of global developmental delay, epileptic encephalopathy and primary or progressive microcephaly. Longitudinal assessment demonstrates progressive cortical atrophy and white matter volume loss. Variants map to the VARS tRNA binding domain and adjacent to the anticodon domain, and disrupt highly conserved residues. Patient primary cells show intact VARS protein but reduced enzymatic activity, suggesting partial loss of function. The implication of VARS in pediatric neurodegeneration broadens the spectrum of human diseases due to mutations in tRNA synthetase genes.
Keywords: Alleles; Anticodon; Child; Child, Preschool; Disease Progression; Epilepsy; Female; Genetic Predisposition to Disease; Humans; Longitudinal Studies; Loss of Function Mutation; Male; Microcephaly; Models, Molecular; Mutation; Neurodevelopmental Disorders; Pedigree; Protein Biosynthesis; Protein Interaction Domains and Motifs; RNA, Transfer; Valine-tRNA Ligase; Whole Exome Sequencing; Whole Genome Sequencing

Biallelic VARS variants cause developmental encephalopathy with microcephaly that is recapitulated in vars knockout zebrafish. - Siekierska, Aleksandra; Stamberger, Hannah; Deconinck, Tine; Oprescu, Stephanie N; Partoens, Michèle; Zhang, Yifan; Sourbron, Jo; Adriaenssens, Elias; Mullen, Patrick; Wiencek, Patrick; Hardies, Katia; Lee, Jeong-Soo; et al. (Nat Commun, 2019)
Aminoacyl tRNA synthetases (ARSs) link specific amino acids with their cognate transfer RNAs in a critical early step of protein translation. Mutations in ARSs have emerged as a cause of recessive, often complex neurological disease traits. Here we report an allelic series consisting of seven novel and two previously reported biallelic variants in valyl-tRNA synthetase (VARS) in ten patients with a developmental encephalopathy with microcephaly, often associated with early-onset epilepsy. In silico, in vitro, and yeast complementation assays demonstrate that the underlying pathomechanism of these mutations is most likely a loss of protein function. Zebrafish modeling accurately recapitulated some of the key neurological disease traits. These results provide both genetic and biological insights into neurodevelopmental disease and pave the way for further in-depth research on ARS related recessive disorders and precision therapies.
Keywords: Alleles; Animals; Brain Diseases; Cell Line; Disease Models, Animal; Epilepsy; Female; Fibroblasts; Gene Knockout Techniques; Genetic Predisposition to Disease; Humans; Loss of Function Mutation; Male; Microcephaly; Models, Molecular; Neurodevelopmental Disorders; Pedigree; Prosencephalon; Valine-tRNA Ligase; Zebrafish

Clinical exome sequencing reveals locus heterogeneity and phenotypic variability of cohesinopathies. - Yuan, Bo; Neira, Juanita; Pehlivan, Davut; Santiago-Sim, Teresa; Song, Xiaofei; Rosenfeld, Jill; Posey, Jennifer E; Patel, Vipulkumar; Jin, Weihong; Adam, Margaret P; Baple, Emma L; Dean, John; et al. (Genet Med, 2019)
PURPOSE: Defects in the cohesin pathway are associated with cohesinopathies, notably Cornelia de Lange syndrome (CdLS). We aimed to delineate pathogenic variants in known and candidate cohesinopathy genes from a clinical exome perspective. METHODS: We retrospectively studied patients referred for clinical exome sequencing (CES, N = 10,698). Patients with causative variants in novel or recently described cohesinopathy genes were enrolled for phenotypic characterization. RESULTS: Pathogenic or likely pathogenic single-nucleotide and insertion/deletion variants (SNVs/indels) were identified in established disease genes including NIPBL (N = 5), SMC1A (N = 14), SMC3 (N = 4), RAD21 (N = 2), and HDAC8 (N = 8). The phenotypes in this genetically defined cohort skew towards the mild end of CdLS spectrum as compared with phenotype-driven cohorts. Candidate or recently reported cohesinopathy genes were supported by de novo SNVs/indels in STAG1 (N = 3), STAG2 (N = 5), PDS5A (N = 1), and WAPL (N = 1), and one inherited SNV in PDS5A. We also identified copy-number deletions affecting STAG1 (two de novo, one of unknown inheritance) and STAG2 (one of unknown inheritance). Patients with STAG1 and STAG2 variants presented with overlapping features yet without characteristic facial features of CdLS. CONCLUSION: CES effectively identified disease-causing alleles at the mild end of the cohensinopathy spectrum and enabled characterization of candidate disease genes.
Keywords: Adolescent; Alleles; Antigens, Nuclear; Biological Variation, Population; Carrier Proteins; Cell Cycle Proteins; Child; Child, Preschool; Chromosomal Proteins, Non-Histone; Cohort Studies; De Lange Syndrome; Exome; Female; Gene Frequency; Genetic Heterogeneity; Humans; INDEL Mutation; Male; Mutation; Nuclear Proteins; Phenotype; Polymorphism, Single Nucleotide; Proto-Oncogene Proteins; Retrospective Studies; Whole Exome Sequencing

COL4A1 mutations as a potential novel cause of autosomal dominant CAKUT in humans. - Kitzler, Thomas M; Schneider, Ronen; Kohl, Stefan; Kolvenbach, Caroline M; Connaughton, Dervla M; Dai, Rufeng; Mann, Nina; Nakayama, Makiko; Majmundar, Amar J; Wu, Chen-Han W; Kari, Jameela A; El Desoky, Sherif M; et al. (Hum Genet, 2019)
Congenital anomalies of the kidney and urinary tract (CAKUT) are the most common cause of chronic kidney disease (~ 45%) that manifests before 30 years of age. The genetic locus containing COL4A1 (13q33-34) has been implicated in vesicoureteral reflux (VUR), but mutations in COL4A1 have not been reported in CAKUT. We hypothesized that COL4A1 mutations cause CAKUT in humans. We performed whole exome sequencing (WES) in 550 families with CAKUT. As negative control cohorts we used WES sequencing data from patients with nephronophthisis (NPHP) with no genetic cause identified (n = 257) and with nephrotic syndrome (NS) due to monogenic causes (n = 100). We identified a not previously reported heterozygous missense variant in COL4A1 in three siblings with isolated VUR. When examining 549 families with CAKUT, we identified nine additional different heterozygous missense mutations in COL4A1 in 11 individuals from 11 unrelated families with CAKUT, while no COL4A1 mutations were identified in a control cohort with NPHP and only one in the cohort with NS. Most individuals (12/14) had isolated CAKUT with no extrarenal features. The predominant phenotype was VUR (9/14). There were no clinical features of the COL4A1-related disorders (e.g., HANAC syndrome, porencephaly, tortuosity of retinal arteries). Whereas COL4A1-related disorders are typically caused by glycine substitutions in the collagenous domain (84.4% of variants), only one variant in our cohort is a glycine substitution within the collagenous domain (1/10). We identified heterozygous COL4A1 mutations as a potential novel autosomal dominant cause of CAKUT that is allelic to the established COL4A1-related disorders and predominantly caused by non-glycine substitutions.
Keywords: Alleles; Amino Acid Substitution; Collagen Type IV; Computational Biology; Congenital Abnormalities; Databases, Genetic; DNA Mutational Analysis; Evolution, Molecular; Female; Genetic Association Studies; Genetic Loci; Genomics; Heterozygote; Humans; Kidney; Kidney Diseases, Cystic; Male; Mutation; Nephrotic Syndrome; Phenotype; Urinary Tract; Web Browser; Whole Exome Sequencing

Complex Compound Inheritance of Lethal Lung Developmental Disorders Due to Disruption of the TBX-FGF Pathway. - Karolak, Justyna A; Vincent, Marie; Deutsch, Gail; Gambin, Tomasz; Cogné, Benjamin; Pichon, Olivier; Vetrini, Francesco; Mefford, Heather C; Dines, Jennifer N; Golden-Grant, Katie; Dipple, Katrina; Freed, Amanda S; et al. (Am J Hum Genet, 2019)
Primary defects in lung branching morphogenesis, resulting in neonatal lethal pulmonary hypoplasias, are incompletely understood. To elucidate the pathogenetics of human lung development, we studied a unique collection of samples obtained from deceased individuals with clinically and histopathologically diagnosed interstitial neonatal lung disorders: acinar dysplasia (n = 14), congenital alveolar dysplasia (n = 2), and other lethal lung hypoplasias (n = 10). We identified rare heterozygous copy-number variant deletions or single-nucleotide variants (SNVs) involving TBX4 (n = 8 and n = 2, respectively) or FGF10 (n = 2 and n = 2, respectively) in 16/26 (61%) individuals. In addition to TBX4, the overlapping ∼2 Mb recurrent and nonrecurrent deletions at 17q23.1q23.2 identified in seven individuals with lung hypoplasia also remove a lung-specific enhancer region. Individuals with coding variants involving either TBX4 or FGF10 also harbored at least one non-coding SNV in the predicted lung-specific enhancer region, which was absent in 13 control individuals with the overlapping deletions but without any structural lung anomalies. The occurrence of rare coding variants involving TBX4 or FGF10 with the putative hypomorphic non-coding SNVs implies a complex compound inheritance of these pulmonary hypoplasias. Moreover, they support the importance of TBX4-FGF10-FGFR2 epithelial-mesenchymal signaling in human lung organogenesis and help to explain the histopathological continuum observed in these rare lethal developmental disorders of the lung.
Keywords: DNA Copy Number Variations; Female; Fibroblast Growth Factor 10; Gene Expression Regulation; Gestational Age; Humans; Infant, Newborn; Infant, Newborn, Diseases; Lung; Lung Diseases; Male; Maternal Inheritance; Organogenesis; Paternal Inheritance; Pedigree; Polymorphism, Single Nucleotide; Receptor, Fibroblast Growth Factor, Type 2; Signal Transduction; T-Box Domain Proteins

Contribution of noncoding pathogenic variants to RPGRIP1-mediated inherited retinal degeneration. - Jamshidi, Farzad; Place, Emily M; Mehrotra, Sudeep; Navarro-Gomez, Daniel; Maher, Mathew; Branham, Kari E; Valkanas, Elise; Cherry, Timothy J; Lek, Monkol; Macarthur, Daniel; Pierce, Eric A; Bujakowska, Kinga M (Genet Med, 2019)
PURPOSE: With the advent of gene therapies for inherited retinal degenerations (IRDs), genetic diagnostics will have an increasing role in clinical decision-making. Yet the genetic cause of disease cannot be identified using exon-based sequencing for a significant portion of patients. We hypothesized that noncoding pathogenic variants contribute significantly to the genetic causality of IRDs and evaluated patients with single coding pathogenic variants in RPGRIP1 to test this hypothesis. METHODS: IRD families underwent targeted panel sequencing. Unsolved cases were explored by exome and genome sequencing looking for additional pathogenic variants. Candidate pathogenic variants were then validated by Sanger sequencing, quantitative polymerase chain reaction, and in vitro splicing assays in two cell lines analyzed through amplicon sequencing. RESULTS: Among 1722 families, 3 had biallelic loss-of-function pathogenic variants in RPGRIP1 while 7 had a single disruptive coding pathogenic variants. Exome and genome sequencing revealed potential noncoding pathogenic variants in these 7 families. In 6, the noncoding pathogenic variants were shown to lead to loss of function in vitro. CONCLUSION: Noncoding pathogenic variants were identified in 6 of 7 families with single coding pathogenic variants in RPGRIP1. The results suggest that noncoding pathogenic variants contribute significantly to the genetic causality of IRDs and RPGRIP1-mediated IRDs are more common than previously thought.
Keywords: Adult; Chromosome Mapping; DNA Mutational Analysis; DNA, Intergenic; Female; HEK293 Cells; Humans; Male; Mutation; Pedigree; Proteins; Retinal Degeneration; Whole Exome Sequencing; Whole Genome Sequencing

De novo and inherited TCF20 pathogenic variants are associated with intellectual disability, dysmorphic features, hypotonia, and neurological impairments with similarities to Smith-Magenis syndrome. - Vetrini, Francesco; McKee, Shane; Rosenfeld, Jill A; Suri, Mohnish; Lewis, Andrea M; Nugent, Kimberly Margaret; Roeder, Elizabeth; Littlejohn, Rebecca O; Holder, Sue; Zhu, Wenmiao; Alaimo, Joseph T; Graham, Brett; et al. (Genome Med, 2019)
BACKGROUND: Neurodevelopmental disorders are genetically and phenotypically heterogeneous encompassing developmental delay (DD), intellectual disability (ID), autism spectrum disorders (ASDs), structural brain abnormalities, and neurological manifestations with variants in a large number of genes (hundreds) associated. To date, a few de novo mutations potentially disrupting TCF20 function in patients with ID, ASD, and hypotonia have been reported. TCF20 encodes a transcriptional co-regulator structurally related to RAI1, the dosage-sensitive gene responsible for Smith-Magenis syndrome (deletion/haploinsufficiency) and Potocki-Lupski syndrome (duplication/triplosensitivity). METHODS: Genome-wide analyses by exome sequencing (ES) and chromosomal microarray analysis (CMA) identified individuals with heterozygous, likely damaging, loss-of-function alleles in TCF20. We implemented further molecular and clinical analyses to determine the inheritance of the pathogenic variant alleles and studied the spectrum of phenotypes. RESULTS: We report 25 unique inactivating single nucleotide variants/indels (1 missense, 1 canonical splice-site variant, 18 frameshift, and 5 nonsense) and 4 deletions of TCF20. The pathogenic variants were detected in 32 patients and 4 affected parents from 31 unrelated families. Among cases with available parental samples, the variants were de novo in 20 instances and inherited from 4 symptomatic parents in 5, including in one set of monozygotic twins. Two pathogenic loss-of-function variants were recurrent in unrelated families. Patients presented with a phenotype characterized by developmental delay, intellectual disability, hypotonia, variable dysmorphic features, movement disorders, and sleep disturbances. CONCLUSIONS: TCF20 pathogenic variants are associated with a novel syndrome manifesting clinical characteristics similar to those observed in Smith-Magenis syndrome. Together with previously described cases, the clinical entity of TCF20-associated neurodevelopmental disorders (TAND) emerges from a genotype-driven perspective.
Keywords: Adolescent; Child; Child, Preschool; Craniofacial Abnormalities; Developmental Disabilities; Female; Humans; INDEL Mutation; Infant; Intellectual Disability; Male; Muscle Hypotonia; Smith-Magenis Syndrome; Transcription Factors; Young Adult

De Novo SOX4 Variants Cause a Neurodevelopmental Disease Associated with Mild Dysmorphism. - Zawerton, Ash; Yao, Baojin; Yeager, J Paige; Pippucci, Tommaso; Haseeb, Abdul; Smith, Joshua D; Wischmann, Lisa; Kühl, Susanne J; Dean, John C S; Pilz, Daniela T; Holder, Susan E; McNeill, Alisdair; et al. (Am J Hum Genet, 2019)
SOX4, together with SOX11 and SOX12, forms group C of SRY-related (SOX) transcription factors. They play key roles, often in redundancy, in multiple developmental pathways, including neurogenesis and skeletogenesis. De novo SOX11 heterozygous mutations have been shown to cause intellectual disability, growth deficiency, and dysmorphic features compatible with mild Coffin-Siris syndrome. Using trio-based exome sequencing, we here identify de novo SOX4 heterozygous missense variants in four children who share developmental delay, intellectual disability, and mild facial and digital morphological abnormalities. SOX4 is highly expressed in areas of active neurogenesis in human fetuses, and sox4 knockdown in Xenopus embryos diminishes brain and whole-body size. The SOX4 variants cluster in the highly conserved, SOX family-specific HMG domain, but each alters a different residue. In silico tools predict that each variant affects a distinct structural feature of this DNA-binding domain, and functional assays demonstrate that these SOX4 proteins carrying these variants are unable to bind DNA in vitro and transactivate SOX reporter genes in cultured cells. These variants are not found in the gnomAD database of individuals with presumably normal development, but 12 other SOX4 HMG-domain missense variants are recorded and all demonstrate partial to full activity in the reporter assay. Taken together, these findings point to specific SOX4 HMG-domain missense variants as the cause of a characteristic human neurodevelopmental disorder associated with mild facial and digital dysmorphism.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; Animals; Child; Child, Preschool; Coffin-Lowry Syndrome; Cohort Studies; Conserved Sequence; DNA; Female; Heterozygote; HMG-Box Domains; Humans; Male; Mutation, Missense; Neurodevelopmental Disorders; SOXC Transcription Factors; Transcriptional Activation; Xenopus

Detailed genetic characteristics of an international large cohort of patients with Stargardt disease: ProgStar study report 8. - Fujinami, Kaoru; Strauss, Rupert W; Chiang, John Pei-Wen; Audo, Isabelle S; Bernstein, Paul S; Birch, David G; Bomotti, Samantha M; Cideciyan, Artur V; Ervin, Ann-Margret; Marino, Meghan J; Sahel, José-Alain; Mohand-Said, Saddek; et al. (Br J Ophthalmol, 2019)
BACKGROUND/AIMS: To describe the genetic characteristics of the cohort enrolled in the international multicentre progression of Stargardt disease 1 (STGD1) studies (ProgStar) and to determine geographic differences based on the allele frequency. METHODS: 345 participants with a clinical diagnosis of STGD1 and harbouring at least one disease-causing ABCA4 variant were enrolled from 9 centres in the USA and Europe. All variants were reviewed and analysis was performed including allele frequency in public databases and pathogenicity predictions. Participants with multiple likely pathogenic variants were classified into four national subgroups (USA, UK, France, Germany), with subsequent comparison analysis of the allele frequency for each prevalent allele. RESULTS: 211 likely pathogenic variants were identified in the total cohort, including missense (63%), splice site alteration (18%), stop (9%) and others. 50 variants were novel. Exclusively missense variants were detected in 139 (50%) of 279 patients with multiple pathogenic variants. The three most prevalent variants of these patients with multiple pathogenic variants were p.G1961E (15%), p.G863A (7%) and c.5461-10 T>C (5%). Subgroup analysis revealed a statistically significant difference between the four recruiting nations in the allele frequency of nine variants. CONCLUSIONS: There is a large spectrum of ABCA4 sequence variants, including 50 novel variants, in a well-characterised cohort thereby further adding to the unique allelic heterogeneity in STGD1. Approximately half of the cohort harbours missense variants only, indicating a relatively mild phenotype of the ProgStar cohort. There are significant differences in allele frequencies between nations, although the three most prevalent variants are shared as frequent variants.
Keywords: Adolescent; Adult; Age of Onset; Aged; ATP-Binding Cassette Transporters; Child; Child, Preschool; Cohort Studies; Databases, Factual; DNA Mutational Analysis; Female; Gene Frequency; Genotyping Techniques; Geography; Humans; Internationality; Macular Degeneration; Male; Middle Aged; Mutation; Polymerase Chain Reaction

Exploring by whole exome sequencing patients with initial diagnosis of Rubinstein-Taybi syndrome: the interconnections of epigenetic machinery disorders. - Negri, Gloria; Magini, Pamela; Milani, Donatella; Crippa, Milena; Biamino, Elisa; Piccione, Maria; Sotgiu, Stefano; Perrìa, Chiara; Vitiello, Giuseppina; Frontali, Marina; Boni, Antonella; Di Fede, Elisabetta; et al. (Hum Genet, 2019)
Rubinstein-Taybi syndrome (RSTS) is an autosomal-dominant neurodevelopmental disease affecting 1:125,000 newborns characterized by intellectual disability, growth retardation, facial dysmorphisms and skeletal abnormalities. RSTS is caused by mutations in genes encoding for writers of the epigenetic machinery: CREBBP (~ 60%) or its homologous EP300 (~ 10%). No causative mutation is identified in up to 30% of patients. We performed whole-exome sequencing (WES) on eight RSTS-like individuals who had normal high-resolution array CGH testing and were CREBBP- and EP300-mutation -negative, to identify the molecular cause. In four cases, we identified putatively causal variants in three genes (ASXL1, KMT2D and KMT2A) encoding members of the epigenetic machinery known to be associated with the Bohring-Opitz, Kabuki and Wiedemann-Steiner syndromes. Each variant is novel, de novo, fulfills the ACMG criteria and is predicted to result in loss-of-function leading to haploinsufficiency of the epi-gene. In two of the remaining cases, homozygous/compound heterozygous variants in XYLT2 and PLCB4 genes, respectively, associated with spondyloocular and auriculocondylar 2 syndromes and in the latter an additional candidate variant in XRN2, a gene yet unrelated to any disease, were detected, but their pathogenicity remains uncertain. These results underscore the broad clinical spectrum of Mendelian disorders of the epigenetic apparatus and the high rate of WES disclosure of the genetic basis in cases which may pose a challenge for phenotype encompassing distinct syndromes. The overlapping features of distinct intellectual disability syndromes reflect common pathogenic molecular mechanisms affecting the complex regulation of balance between open and closed chromatin.
Keywords: Child; Child, Preschool; Comparative Genomic Hybridization; CREB-Binding Protein; E1A-Associated p300 Protein; Epigenesis, Genetic; Facies; Female; Genetic Association Studies; Humans; Infant; Infant, Newborn; Male; Mutation; Phenotype; Rubinstein-Taybi Syndrome; Whole Exome Sequencing

Identification and association of recurrent ALOXE3 mutation with non-bullous congenital ichthyosiform erythroderma in two ethnically distinct Pakistani families. - Rahman, Simeen Ber; Mir, Asif; Ahmad, Nafees; Haider, Syed Husnain; Malik, Salman Akbar; Nasir, Muhammad (Congenit Anom (Kyoto), 2019)
Non-bullous congenital ichthyosiform erythroderma (NCIE) is characterized by skin scaling with erythema. In this study, two Pakistani families with NCIE are genetically characterized through Whole Exome and Sanger sequencing to identify molecular basis of the disease. We identified a nonsense homozygous c.2026C>T mutation of ALOXE3, causing premature termination of the eLOX3 protein (p.Q676X). In silico studies predicted impaired enzymatic activity of the premature truncated eLOX3, leading to abnormal synthesis of specific hepoxilin derivatives, essential for epidermal barrier formation. It is the first ever study reporting homozygotes of p.Q676X mutation in ethnically distinct two Pakistani families; otherwise, heterozygotes of the said mutation have been reported in South Asian population only. Hence, mutation seems to be region-specific and may be useful for molecular diagnosis of NCIE. Moreover, our findings should help in genetic counseling and career screening.
Keywords: 8,11,14-Eicosatrienoic Acid; Adolescent; Adult; Base Sequence; Case-Control Studies; Child; Child, Preschool; Codon, Nonsense; Ethnic Groups; Female; Flavanones; Gene Expression; Homozygote; Humans; Ichthyosis, Lamellar; Lipoxygenase; Male; Middle Aged; Molecular Docking Simulation; Pakistan; Pedigree; Protein Binding; Protein Structure, Secondary; Skin; Whole Exome Sequencing

Identification of CACNA1D variants associated with sinoatrial node dysfunction and deafness in additional Pakistani families reveals a clinical significance. - Liaqat, Khurram; Schrauwen, Isabelle; Raza, Syed Irfan; Lee, Kwanghyuk; Hussain, Shabir; Chakchouk, Imen; Nasir, Abdul; Acharya, Anushree; Abbe, Izoduwa; Umair, Muhammad; Ansar, Muhammad; Ullah, Irfan; et al. (J Hum Genet, 2019)
Sinoatrial node dysfunction and deafness (SANDD) syndrome is rare and characterized by a low heart beat and severe-to-profound deafness. Additional features include fatigue, dizziness, and episodic syncope. The sinoatrial node (SAN) drives heart automaticity and continuously regulates heart rate. The CACNA1D gene encoding the Ca1.3 protein expressed in inner hair cells, atria and SAN, induces loss-of-function in channel activity and underlies SANDD. To date, only one variant c.1208_1209insGGG:p.(G403_V404insG) has been reported for SANDD syndrome. We studied five Pakistani families with SANDD and characterized a new missense variant p.(A376V) in CACNA1D in one family, and further characterized the founder variant p.(G403_V404insG) in four additional pedigrees. We show that affected individuals in the four families which segregate p.(G403_V404insG) share a 1.03 MB haplotype on 3p21.1 suggesting they share a common distant ancestor. In conclusion, we identified new and known variants in CACNA1D in five Pakistani families with SANDD. This study is of clinical importance as the CACNA1D founder variant is only observed in families from the Khyber Pakhtunkhwa (KPK) province, in Pakistan. Therefore, screening patients with congenital deafness for SAN dysfunction in this province could ensure adequate follow-up and prevent cardiac failure associated with SAN.
Keywords: Adolescent; Calcium Channels, L-Type; Deafness; Female; Heart Diseases; Humans; Male; Mutation; Pakistan; Pedigree; Prognosis; Sinoatrial Node

Lack of GAS2L2 Causes PCD by Impairing Cilia Orientation and Mucociliary Clearance. - Bustamante-Marin, Ximena M; Yin, Wei-Ning; Sears, Patrick R; Werner, Michael E; Brotslaw, Eva J; Mitchell, Brian J; Jania, Corey M; Zeman, Kirby L; Rogers, Troy D; Herring, Laura E; Refabért, Luc; Thomas, Lucie; et al. (Am J Hum Genet, 2019)
Primary ciliary dyskinesia (PCD) is a genetic disorder in which impaired ciliary function leads to chronic airway disease. Exome sequencing of a PCD subject identified an apparent homozygous frameshift variant, c.887_890delTAAG (p.Val296Glyfs13), in exon 5; this frameshift introduces a stop codon in amino acid 308 of the growth arrest-specific protein 2-like 2 (GAS2L2). Further genetic screening of unrelated PCD subjects identified a second proband with a compound heterozygous variant carrying the identical frameshift variant and a large deletion (c.867_343+1207del; p.?) starting in exon 5. Both individuals had clinical features of PCD but normal ciliary axoneme structure. In this research, using human nasal cells, mouse models, and X.laevis embryos, we show that GAS2L2 is abundant at the apical surface of ciliated cells, where it localizes with basal bodies, basal feet, rootlets, and actin filaments. Cultured GAS2L2-deficient nasal epithelial cells from one of the affected individuals showed defects in ciliary orientation and had an asynchronous and hyperkinetic (GAS2L2-deficient = 19.8 Hz versus control = 15.8 Hz) ciliary-beat pattern. These results were recapitulated in Gas2l2 mouse tracheal epithelial cell (mTEC) cultures and in X. laevis embryos treated with Gas2l2 morpholinos. In mice, the absence of Gas2l2 caused neonatal death, and the conditional deletion of Gas2l2 impaired mucociliary clearance (MCC) and led to mucus accumulation. These results show that a pathogenic variant in GAS2L2 causes a genetic defect in ciliary orientation and impairs MCC and results in PCD.
Keywords: Animals; Cilia; Ciliary Motility Disorders; Disease Models, Animal; Exons; Female; Gene Deletion; Genes, Lethal; Humans; Male; Mice; Mice, Knockout; Microfilament Proteins; Microtubule-Associated Proteins; Phenotype; Rotation; Xenopus

Loss of function, missense, and intronic variants in NOTCH1 confer different risks for left ventricular outflow tract obstructive heart defects in two European cohorts. - Helle, Emmi; Córdova-Palomera, Aldo; Ojala, Tiina; Saha, Priyanka; Potiny, Praneetha; Gustafsson, Stefan; Ingelsson, Erik; Bamshad, Michael; Nickerson, Deborah; Chong, Jessica X; Ashley, Euan; Priest, James R (Genet Epidemiol, 2019)
Loss of function variants in NOTCH1 cause left ventricular outflow tract obstructive defects (LVOTO). However, the risk conferred by rare and noncoding variants in NOTCH1 for LVOTO remains largely uncharacterized. In a cohort of 49 families affected by hypoplastic left heart syndrome, a severe form of LVOTO, we discovered predicted loss of function NOTCH1 variants in 6% of individuals. Rare or low-frequency missense variants were found in 16% of families. To make a quantitative estimate of the genetic risk posed by variants in NOTCH1 for LVOTO, we studied associations of 400 coding and noncoding variants in NOTCH1 in 1,085 cases and 332,788 controls from the UK Biobank. Two rare intronic variants in strong linkage disequilibrium displayed significant association with risk for LVOTO amongst European-ancestry individuals. This result was replicated in an independent analysis of 210 cases and 68,762 controls of non-European and mixed ancestry. In conclusion, carrying rare predicted loss of function variants in NOTCH1 confer significant risk for LVOTO. In addition, the two intronic variants seem to be associated with an increased risk for these defects. Our approach demonstrates the utility of population-based data sets in quantifying the specific risk of individual variants for disease-related phenotypes.
Keywords: Cohort Studies; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Heart Defects, Congenital; Humans; Introns; Loss of Function Mutation; Male; Mutation, Missense; Pedigree; Receptor, Notch1; Risk Factors; Ventricular Outflow Obstruction; Whole Exome Sequencing

Novel SPEG mutations in congenital myopathies: Genotype-phenotype correlations. - Qualls, Anita E; Donkervoort, Sandra; Herkert, Johanna C; D'Gama, Alissa M; Bharucha-Goebel, Diana; Collins, James; Chao, Katherine R; Foley, A Reghan; Schoots, Mirthe H; Jongbloed, Jan D H; Bönnemann, Carsten G; Agrawal, Pankaj B (Muscle Nerve, 2019)
INTRODUCTION: Centronuclear myopathies (CNMs) are a subtype of congenital myopathies (CMs) characterized by muscle weakness, predominant type 1 fibers, and increased central nuclei. SPEG (striated preferentially expressed protein kinase) mutations have recently been identified in 7 CM patients (6 with CNMs). We report 2 additional patients with SPEG mutations expanding the phenotype and evaluate genotype-phenotype correlations associated with SPEG mutations. METHODS: Using whole exome/genome sequencing in CM families, we identified novel recessive SPEG mutations in 2 patients. RESULTS: Patient 1, with severe muscle weakness requiring respiratory support, dilated cardiomyopathy, ophthalmoplegia, and findings of nonspecific CM on muscle biopsy carried a homozygous SPEG mutation (p.Val3062del). Patient 2, with milder muscle weakness, ophthalmoplegia, and CNM carried compound heterozygous mutations (p.Leu728Argfs*82) and (p.Val2997Glyfs*52). CONCLUSIONS: The 2 patients add insight into genotype-phenotype correlations of SPEG-associated CMs. Clinicians should consider evaluating a CM patient for SPEG mutations even in the absence of CNM features. Muscle Nerve 59:357-362, 2019.
Keywords: Biopsy; Child; Child, Preschool; Consanguinity; Exome; Female; Genetic Association Studies; Humans; Infant; Male; Muscle Proteins; Muscle Weakness; Muscle, Skeletal; Mutation; Myopathies, Structural, Congenital; Protein-Serine-Threonine Kinases; Sequence Analysis

Primary Ciliary Dyskinesia: Longitudinal Study of Lung Disease by Ultrastructure Defect and Genotype. - Davis, Stephanie D; Rosenfeld, Margaret; Lee, Hye-Seung; Ferkol, Thomas W; Sagel, Scott D; Dell, Sharon D; Milla, Carlos; Pittman, Jessica E; Shapiro, Adam J; Sullivan, Kelli M; Nykamp, Keith R; Krischer, Jeffrey P; et al. (Am J Respir Crit Care Med, 2019)
RATIONALE: In primary ciliary dyskinesia, factors leading to disease heterogeneity are poorly understood. OBJECTIVES: To describe early lung disease progression in primary ciliary dyskinesia and identify associations between ultrastructural defects and genotypes with clinical phenotype. METHODS: This was a prospective, longitudinal (5 yr), multicenter, observational study. Inclusion criteria were less than 19 years at enrollment and greater than or equal to two annual study visits. Linear mixed effects models including random slope and random intercept were used to evaluate longitudinal associations between the ciliary defect group (or genotype group) and clinical features (percent predicted FEV and weight and height z-scores). MEASUREMENTS AND MAIN RESULTS: A total of 137 participants completed 732 visits. The group with absent inner dynein arm, central apparatus defects, and microtubular disorganization (IDA/CA/MTD) (n = 41) were significantly younger at diagnosis and in mixed effects models had significantly lower percent predicted FEV and weight and height z-scores than the isolated outer dynein arm defect (n = 55) group. Participants with CCDC39 or CCDC40 mutations (n = 34) had lower percent predicted FEV and weight and height z-scores than those with DNAH5 mutations (n = 36). For the entire cohort, percent predicted FEV decline was heterogeneous with a mean (SE) decline of 0.57 (0.25) percent predicted/yr. Rate of decline was different from zero only in the IDA/MTD/CA group (mean [SE], -1.11 [0.48] percent predicted/yr; P = 0.02). CONCLUSIONS: Participants with IDA/MTD/CA defects, which included individuals with CCDC39 or CCDC40 mutations, had worse lung function and growth indices compared with those with outer dynein arm defects and DNAH5 mutations, respectively. The only group with a significant lung function decline over time were participants with IDA/MTD/CA defects.
Keywords: Child; Cilia; Cohort Studies; Female; Genotype; Humans; Kartagener Syndrome; Longitudinal Studies; Lung; Male; Mutation; Phenotype; Prospective Studies; Respiratory Function Tests

ROBO4 variants predispose individuals to bicuspid aortic valve and thoracic aortic aneurysm. - Gould, Russell A; Aziz, Hamza; Woods, Courtney E; Seman-Senderos, Manuel Alejandro; Sparks, Elizabeth; Preuss, Christoph; Wünnemann, Florian; Bedja, Djahida; Moats, Cassandra R; McClymont, Sarah A; Rose, Rebecca; Sobreira, Nara; et al. (Nat Genet, 2019)
Bicuspid aortic valve (BAV) is a common congenital heart defect (population incidence, 1-2%) that frequently presents with ascending aortic aneurysm (AscAA). BAV/AscAA shows autosomal dominant inheritance with incomplete penetrance and male predominance. Causative gene mutations (for example, NOTCH1, SMAD6) are known for ≤1% of nonsyndromic BAV cases with and without AscAA, impeding mechanistic insight and development of therapeutic strategies. Here, we report the identification of variants in ROBO4 (which encodes a factor known to contribute to endothelial performance) that segregate with disease in two families. Targeted sequencing of ROBO4 showed enrichment for rare variants in BAV/AscAA probands compared with controls. Targeted silencing of ROBO4 or mutant ROBO4 expression in endothelial cell lines results in impaired barrier function and a synthetic repertoire suggestive of endothelial-to-mesenchymal transition. This is consistent with BAV/AscAA-associated findings in patients and in animal models deficient for ROBO4. These data identify a novel endothelial etiology for this common human disease phenotype.
Keywords: Animals; Aortic Aneurysm, Thoracic; Aortic Valve; Cells, Cultured; Disease Models, Animal; Endothelial Cells; Female; Heart Valve Diseases; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Knockout; Mutation; Phenotype; Receptors, Cell Surface; Zebrafish

TBX6 compound inheritance leads to congenital vertebral malformations in humans and mice. - Yang, Nan; Wu, Nan; Zhang, Ling; Zhao, Yanxue; Liu, Jiaqi; Liang, Xiangyu; Ren, Xiaojun; Li, Weiyu; Chen, Weisheng; Dong, Shuangshuang; Zhao, Sen; Lin, Jiachen; et al. (Hum Mol Genet, 2019)
Congenital vertebral malformations (CVMs) are associated with human TBX6 compound inheritance that combines a rare null allele and a common hypomorphic allele at the TBX6 locus. Our previous in vitro evidence suggested that this compound inheritance resulted in a TBX6 gene dosage of less than haploinsufficiency (i.e. <50%) as a potential mechanism of TBX6-associated CVMs. To further investigate this pathogenetic model, we ascertained and collected 108 Chinese CVM cases and found that 10 (9.3%) of them carried TBX6 null mutations in combination with common hypomorphic variants at the second TBX6 allele. For in vivo functional verification and genetic analysis of TBX6 compound inheritance, we generated both null and hypomorphic mutations in mouse Tbx6 using the CRISPR-Cas9 method. These Tbx6 mutants are not identical to the patient variants at the DNA sequence level, but instead functionally mimic disease-associated TBX6 variants. Intriguingly, as anticipated by the compound inheritance model, a high penetrance of CVM phenotype was only observed in the mice with combined null and hypomorphic alleles of Tbx6. These findings are consistent with our experimental observations in humans and supported the dosage effect of TBX6 in CVM etiology. In conclusion, our findings in the newly collected human CVM subjects and Tbx6 mouse models consistently support the contention that TBX6 compound inheritance causes CVMs, potentially via a gene dosage-dependent mechanism. Furthermore, mouse Tbx6 mutants mimicking human CVM-associated variants will be useful models for further mechanistic investigations of CVM pathogenesis in the cases associated with TBX6.
Keywords: Adolescent; Alleles; Animals; Child; Child, Preschool; Congenital Abnormalities; CRISPR-Cas Systems; Disease Models, Animal; Female; Haploinsufficiency; Humans; Infant; Male; Mice; Mutation; Phenotype; Scoliosis; Spine; T-Box Domain Proteins

Variants in KIAA0825 underlie autosomal recessive postaxial polydactyly. - Ullah, Irfan; Kakar, Naseebullah; Schrauwen, Isabelle; Hussain, Shabir; Chakchouk, Imen; Liaqat, Khurram; Acharya, Anushree; Wasif, Naveed; Santos-Cortez, Regie Lyn P; Khan, Saadullah; Aziz, Abdul; Lee, Kwanghyuk; et al. (Hum Genet, 2019)
Postaxial polydactyly (PAP) is a common limb malformation that often leads to cosmetic and functional complications. Molecular evaluation of polydactyly can serve as a tool to elucidate genetic and signaling pathways that regulate limb development, specifically, the anterior-posterior specification of the limb. To date, only five genes have been identified for nonsyndromic PAP: FAM92A, GLI1, GLI3, IQCE and ZNF141. In this study, two Pakistani multiplex consanguineous families with autosomal recessive nonsyndromic PAP were clinically and molecularly evaluated. From both pedigrees, a DNA sample from an affected member underwent exome sequencing. In each family, we identified a segregating frameshift (c.591dupA [p.(Q198Tfs*21)]) and nonsense variant (c.2173A > T [p.(K725*)]) in KIAA0825 (also known as C5orf36). Although KIAA0825 encodes a protein of unknown function, it has been demonstrated that its murine ortholog is expressed during limb development. Our data contribute to the establishment of a catalog of genes important in limb patterning, which can aid in diagnosis and obtaining a better understanding of the biology of polydactyly.
Keywords: Animals; Consanguinity; Family Health; Female; Fingers; Genes, Recessive; Genetic Predisposition to Disease; Genotype; Humans; Intracellular Signaling Peptides and Proteins; Male; Mice, Inbred C57BL; Mutation; Pedigree; Phenotype; Polydactyly; Toes; Whole Exome Sequencing

Whole-Exome Sequencing Enables a Precision Medicine Approach for Kidney Transplant Recipients. - Mann, Nina; Braun, Daniela A; Amann, Kassaundra; Tan, Weizhen; Shril, Shirlee; Connaughton, Dervla M; Nakayama, Makiko; Schneider, Ronen; Kitzler, Thomas M; van der Ven, Amelie T; Chen, Jing; Ityel, Hadas; et al. (J Am Soc Nephrol, 2019)
BACKGROUND: Whole-exome sequencing (WES) finds a CKD-related mutation in approximately 20% of patients presenting with CKD before 25 years of age. Although provision of a molecular diagnosis could have important implications for clinical management, evidence is lacking on the diagnostic yield and clinical utility of WES for pediatric renal transplant recipients. METHODS: To determine the diagnostic yield of WES in pediatric kidney transplant recipients, we recruited 104 patients who had received a transplant at Boston Children's Hospital from 2007 through 2017, performed WES, and analyzed results for likely deleterious variants in approximately 400 genes known to cause CKD. RESULTS: By WES, we identified a genetic cause of CKD in 34 out of 104 (32.7%) transplant recipients. The likelihood of detecting a molecular genetic diagnosis was highest for patients with urinary stone disease (three out of three individuals), followed by renal cystic ciliopathies (seven out of nine individuals), steroid-resistant nephrotic syndrome (nine out of 21 individuals), congenital anomalies of the kidney and urinary tract (ten out of 55 individuals), and chronic glomerulonephritis (one out of seven individuals). WES also yielded a molecular diagnosis for four out of nine individuals with ESRD of unknown etiology. The WES-related molecular genetic diagnosis had implications for clinical care for five patients. CONCLUSIONS: Nearly one third of pediatric renal transplant recipients had a genetic cause of their kidney disease identified by WES. Knowledge of this genetic information can help guide management of both transplant patients and potential living related donors.
Keywords: Adolescent; Boston; Child; Child, Preschool; Cohort Studies; Female; Genetic Predisposition to Disease; Genetic Testing; Graft Rejection; Graft Survival; Hospitals, Pediatric; Humans; Kidney Transplantation; Male; Precision Medicine; Prognosis; Renal Insufficiency, Chronic; Retrospective Studies; Risk Assessment; Severity of Illness Index; Survival Analysis; Transplant Recipients; Treatment Outcome; Whole Exome Sequencing

ZMIZ1 Variants Cause a Syndromic Neurodevelopmental Disorder. - Carapito, Raphael; Ivanova, Ekaterina L; Morlon, Aurore; Meng, Linyan; Molitor, Anne; Erdmann, Eva; Kieffer, Bruno; Pichot, Angélique; Naegely, Lydie; Kolmer, Aline; Paul, Nicodème; Hanauer, Antoine; et al. (Am J Hum Genet, 2019)
ZMIZ1 is a coactivator of several transcription factors, including p53, the androgen receptor, and NOTCH1. Here, we report 19 subjects with intellectual disability and developmental delay carrying variants in ZMIZ1. The associated features include growth failure, feeding difficulties, microcephaly, facial dysmorphism, and various other congenital malformations. Of these 19, 14 unrelated subjects carried de novo heterozygous single-nucleotide variants (SNVs) or single-base insertions/deletions, 3 siblings harbored a heterozygous single-base insertion, and 2 subjects had a balanced translocation disrupting ZMIZ1 or involving a regulatory region of ZMIZ1. In total, we identified 13 point mutations that affect key protein regions, including a SUMO acceptor site, a central disordered alanine-rich motif, a proline-rich domain, and a transactivation domain. All identified variants were absent from all available exome and genome databases. In vitro, ZMIZ1 showed impaired coactivation of the androgen receptor. In vivo, overexpression of ZMIZ1 mutant alleles in developing mouse brains using in utero electroporation resulted in abnormal pyramidal neuron morphology, polarization, and positioning, underscoring the importance of ZMIZ1 in neural development and supporting mutations in ZMIZ1 as the cause of a rare neurodevelopmental syndrome.
Keywords: Alleles; Animals; Child; Child, Preschool; Developmental Disabilities; Female; Humans; Infant; Intellectual Disability; Male; Mice; Point Mutation; Syndrome; Transcription Factors

Additional features of Gillespie syndrome in two Brazilian siblings with a novel ITPR1 homozygous pathogenic variant. - Carvalho, Daniel R; Medeiros, João Eugenio G; Ribeiro, Daniela Sebestyan M; Martins, Bernardo J A F; Sobreira, Nara L M (Eur J Med Genet, 2018)
Gillespie syndrome (GS) [MIM: 206700] is a very rare condition characterized by bilateral iris defect, congenital hypotonia, cerebellar ataxia and intellectual disability. The typical iris anomaly is considered necessary to the diagnosis of GS. Recently, variants in ITPR1 were described causing GS. Non-neurological features were reported in few patients. Here we describe two consanguineous siblings with GS and a novel homozygous ITPR1 pathogenic variant (p.N984fs). They also present a cardiac defect (pulmonary valve stenosis) and one sib had a genitourinary malformation (ureteropelvic junction obstruction). Our report reinforces ITPR1 as the cause of GS and suggests a possible role of ITPR1 in the development of other organs.
Keywords: Aniridia; Brazil; Cerebellar Ataxia; Child, Preschool; Consanguinity; Female; Homozygote; Humans; Infant; Inositol 1,4,5-Trisphosphate Receptors; Intellectual Disability; Male; Mutation; Pedigree; Siblings

Analyses of LMNA-negative juvenile progeroid cases confirms biallelic POLR3A mutations in Wiedemann-Rautenstrauch-like syndrome and expands the phenotypic spectrum of PYCR1 mutations. - Lessel, Davor; Ozel, Ayse Bilge; Campbell, Susan E; Saadi, Abdelkrim; Arlt, Martin F; McSweeney, Keisha Melodi; Plaiasu, Vasilica; Szakszon, Katalin; Szőllős, Anna; Rusu, Cristina; Rojas, Armando J; Lopez-Valdez, Jaime; et al. (Hum Genet, 2018)
Juvenile segmental progeroid syndromes are rare, heterogeneous disorders characterized by signs of premature aging affecting more than one tissue or organ starting in childhood. Hutchinson-Gilford progeria syndrome (HGPS), caused by a recurrent de novo synonymous LMNA mutation resulting in aberrant splicing and generation of a mutant product called progerin, is a prototypical example of such disorders. Here, we performed a joint collaborative study using massively parallel sequencing and targeted Sanger sequencing, aimed at delineating the underlying genetic cause of 14 previously undiagnosed, clinically heterogeneous, non-LMNA-associated juvenile progeroid patients. The molecular diagnosis was achieved in 11 of 14 cases (~ 79%). Furthermore, we firmly establish biallelic mutations in POLR3A as the genetic cause of a recognizable, neonatal, Wiedemann-Rautenstrauch-like progeroid syndrome. Thus, we suggest that POLR3A mutations are causal for a portion of under-diagnosed early-onset segmental progeroid syndromes. We additionally expand the clinical spectrum associated with PYCR1 mutations by showing that they can somewhat resemble HGPS in the first year of life. Moreover, our results lead to clinical reclassification in one single case. Our data emphasize the complex genetic and clinical heterogeneity underlying progeroid disorders.
Keywords: Adolescent; Alternative Splicing; Child; Female; Fetal Growth Retardation; Genetic Predisposition to Disease; Humans; Infant; Lamin Type A; Male; Mutation; Phenotype; Progeria; Pyrroline Carboxylate Reductases; RNA Polymerase III

Analysis of 17 genes detects mutations in 81% of 811 patients with lissencephaly. - Di Donato, Nataliya; Timms, Andrew E; Aldinger, Kimberly A; Mirzaa, Ghayda M; Bennett, James T; Collins, Sarah; Olds, Carissa; Mei, Davide; Chiari, Sara; Carvill, Gemma; Myers, Candace T; Rivière, Jean-Baptiste; et al. (Genet Med, 2018)
PURPOSE: To estimate diagnostic yield and genotype-phenotype correlations in a cohort of 811 patients with lissencephaly or subcortical band heterotopia. METHODS: We collected DNA from 756 children with lissencephaly over 30 years. Many were tested for deletion 17p13.3 and mutations of LIS1, DCX, and ARX, but few other genes. Among those tested, 216 remained unsolved and were tested by a targeted panel of 17 genes (ACTB, ACTG1, ARX, CRADD, DCX, LIS1, TUBA1A, TUBA8, TUBB2B, TUBB, TUBB3, TUBG1, KIF2A, KIF5C, DYNC1H1, RELN, and VLDLR) or by whole-exome sequencing. Fifty-five patients studied at another institution were added as a validation cohort. RESULTS: The overall mutation frequency in the entire cohort was 81%. LIS1 accounted for 40% of patients, followed by DCX (23%), TUBA1A (5%), and DYNC1H1 (3%). Other genes accounted for 1% or less of patients. Nineteen percent remained unsolved, which suggests that several additional genes remain to be discovered. The majority of unsolved patients had posterior pachygyria, subcortical band heterotopia, or mild frontal pachygyria. CONCLUSION: The brain-imaging pattern correlates with mutations in single lissencephaly-associated genes, as well as in biological pathways. We propose the first LIS classification system based on the underlying molecular mechanisms.
Keywords: Brain; Classical Lissencephalies and Subcortical Band Heterotopias; DNA Mutational Analysis; Female; Genetic Association Studies; Humans; Lissencephaly; Male; Mutation; Whole Exome Sequencing

Ari-1 Regulates Myonuclear Organization Together with Parkin and Is Associated with Aortic Aneurysms. - Tan, Kai Li; Haelterman, Nele A; Kwartler, Callie S; Regalado, Ellen S; Lee, Pei-Tseng; Nagarkar-Jaiswal, Sonal; Guo, Dong-Chuan; Duraine, Lita; Wangler, Michael F; Bamshad, Michael J; Nickerson, Deborah A; Lin, Guang; et al. (Dev Cell, 2018)
Nuclei are actively positioned and anchored to the cytoskeleton via the LINC (Linker of Nucleoskeleton and Cytoskeleton) complex. We identified mutations in the Parkin-like E3 ubiquitin ligase Ariadne-1 (Ari-1) that affect the localization and distribution of LINC complex members in Drosophila. ari-1 mutants exhibit nuclear clustering and morphology defects in larval muscles. We show that Ari-1 mono-ubiquitinates the core LINC complex member Koi. Surprisingly, we discovered functional redundancy between Parkin and Ari-1: increasing Parkin expression rescues ari-1 mutant phenotypes and vice versa. We further show that rare variants in the human homolog of ari-1 (ARIH1) are associated with thoracic aortic aneurysms and dissections, conditions resulting from smooth muscle cell (SMC) dysfunction. Human ARIH1 rescues fly ari-1 mutant phenotypes, whereas human variants found in patients fail to do so. In addition, SMCs obtained from patients display aberrant nuclear morphology. Hence, ARIH1 is critical in anchoring myonuclei to the cytoskeleton.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Animals; Aortic Aneurysm; Carrier Proteins; Cell Nucleus; Child, Preschool; Cytoskeleton; Drosophila melanogaster; Drosophila Proteins; Female; Humans; Male; Middle Aged; Mutation; Myocytes, Smooth Muscle; Pedigree; Phenotype; Ubiquitin-Protein Ligases; Young Adult

A biallelic ANTXR1 variant expands the anthrax toxin receptor associated phenotype to tooth agenesis. - Dinckan, Nuriye; Du, Renqian; Akdemir, Zeynep C; Bayram, Yavuz; Jhangiani, Shalini N; Doddapaneni, Harsha; Hu, Jianhong; Muzny, Donna M; Guven, Yeliz; Aktoren, Oya; Kayserili, Hülya; Boerwinkle, Eric; et al. (Am J Med Genet A, 2018)
Tooth development is regulated by multiple genetic pathways, which ultimately drive the complex interactions between the oral epithelium and mesenchyme. Disruptions at any time point during this process may lead to failure of tooth development, also known as tooth agenesis (TA). TA is a common craniofacial abnormality in humans and represents the failure to develop one or more permanent teeth. Many genes and potentially subtle variants in these genes contribute to the TA phenotype. We report the clinical and genetic impact of a rare homozygous ANTXR1 variant (c.1312C>T), identified by whole exome sequencing (WES), in a consanguineous Turkish family with TA. Mutations in ANTXR1 have been associated with GAPO (growth retardation, alopecia, pseudoanodontia, and optic atrophy) syndrome and infantile hemangioma, however no clinical characteristics associated with these conditions were observed in our study family. We detected the expression of Antxr1 in oral and dental tissues of developing mouse embryos, further supporting a role for this gene in tooth development. Our findings implicate ANTXR1 as a candidate gene for isolated TA, suggest the involvement of specific hypomorphic alleles, and expand the previously known ANTXR1-associated phenotypes.
Keywords: Alleles; Amino Acid Substitution; Animals; Anodontia; Child; Consanguinity; Facies; Genetic Association Studies; Genotype; Humans; Male; Mice; Mutation; Neoplasm Proteins; Pedigree; Phenotype; Radiography; Receptors, Cell Surface; Whole Exome Sequencing

Comprehensive genomic analysis of patients with disorders of cerebral cortical development. - Wiszniewski, Wojciech; Gawlinski, Pawel; Gambin, Tomasz; Bekiesinska-Figatowska, Monika; Obersztyn, Ewa; Antczak-Marach, Dorota; Akdemir, Zeynep Hande Coban; Harel, Tamar; Karaca, Ender; Jurek, Marta; Sobecka, Katarzyna; Nowakowska, Beata; et al. (Eur J Hum Genet, 2018)
Malformations of cortical development (MCDs) manifest with structural brain anomalies that lead to neurologic sequelae, including epilepsy, cerebral palsy, developmental delay, and intellectual disability. To investigate the underlying genetic architecture of patients with disorders of cerebral cortical development, a cohort of 54 patients demonstrating neuroradiologic signs of MCDs was investigated. Individual genomes were interrogated for single-nucleotide variants (SNV) and copy number variants (CNV) with whole-exome sequencing and chromosomal microarray studies. Variation affecting known MCDs-associated genes was found in 16/54 cases, including 11 patients with SNV, 2 patients with CNV, and 3 patients with both CNV and SNV, at distinct loci. Diagnostic pathogenic SNV and potentially damaging variants of unknown significance (VUS) were identified in two groups of seven individuals each. We demonstrated that de novo variants are important among patients with MCDs as they were identified in 10/16 individuals with a molecular diagnosis. Three patients showed changes in known MCDs genes  and a clinical phenotype beyond the usual characteristics observed, i.e., phenotypic expansion, for a particular known disease gene clinical entity. We also discovered 2 likely candidate genes, CDH4, and ASTN1, with human and animal studies supporting their roles in brain development, and 5 potential candidate genes. Our findings emphasize genetic heterogeneity of MCDs disorders and postulate potential novel candidate genes involved in cerebral cortical development.
Keywords: Cadherins; DNA Copy Number Variations; Exome; Female; Genetic Heterogeneity; Humans; Male; Malformations of Cortical Development; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Receptors, Cell Surface

Confirmation of the Role of DHX38 in the Etiology of Early-Onset Retinitis Pigmentosa. - Latif, Zahid; Chakchouk, Imen; Schrauwen, Isabelle; Lee, Kwanghyuk; Santos-Cortez, Regie Lyn P; Abbe, Izoduwa; Acharya, Anushree; Jarral, Afeefa; Ali, Imran; Ullah, Ehsan; Khan, Muhammad Nasim; Ali, Ghazanfar; et al. (Invest Ophthalmol Vis Sci, 2018)
Purpose: Retinitis pigmentosa (RP) is a genetically heterogeneous trait with autosomal-recessive (ar) inheritance underlying 50% of genetic disease cases. Sixty-one arRP genes have been identified, and recently, DHX38 has been reported as a potential candidate gene for arRP with only a single family reported with a variant of unknown significance. We identified a missense variant in DHX38 that co-segregates with the arRP phenotype in two Pakistani families confirming the involvement of DHX38 in the etiology of early-onset RP. Methods: Exome sequencing was performed using two DNA samples from affected members of Pakistani families (MA88 and MA157) with early onset arRP. Sanger sequencing of DNA samples from all family members confirmed the segregation of candidate variant within both families. Results: A novel missense DHX38 variant c.971G>A; p.(Arg324Gln) was identified which segregates with the arRP phenotype and yielded a logarithm of the odds (LOD) score of 5.0 and 4.3 for families MA88 and MA157, respectively. This variant is predicted to be conserved and deleterious by several bioinformatics tools. Conclusions: We identified a second deleterious DHX38 variant that segregates with arRP in two families, providing additional evidence that DHX38 is involved in RP etiology. DHX38 encodes for pre-mRNA splicing factor PRP16, which is important in catalyzing pre-mRNA splicing.
Keywords: Adolescent; Adult; Cataract; Computational Biology; DEAD-box RNA Helicases; Female; Genes, Recessive; Genetic Association Studies; Genetic Linkage; Humans; Male; Mutation, Missense; Nucleotide Mapping; Ophthalmoscopy; Pedigree; Retinitis Pigmentosa; RNA Splicing Factors; Sequence Analysis, DNA; Whole Exome Sequencing; Young Adult

The Congenital Heart Disease Genetic Network Study: Cohort description. - Hoang, Thanh T; Goldmuntz, Elizabeth; Roberts, Amy E; Chung, Wendy K; Kline, Jennie K; Deanfield, John E; Giardini, Alessandro; Aleman, Adolfo; Gelb, Bruce D; Mac Neal, Meghan; Porter, George A; Kim, Richard; et al. (PLoS One, 2018)
The Pediatric Cardiac Genomics Consortium (PCGC) designed the Congenital Heart Disease Genetic Network Study to provide phenotype and genotype data for a large congenital heart defects (CHDs) cohort. This article describes the PCGC cohort, overall and by major types of CHDs (e.g., conotruncal defects) and subtypes of conotrucal heart defects (e.g., tetralogy of Fallot) and left ventricular outflow tract obstructions (e.g., hypoplastic left heart syndrome). Cases with CHDs were recruited through ten sites, 2010-2014. Information on cases (N = 9,727) and their parents was collected through interviews and medical record abstraction. Four case characteristics, eleven parental characteristics, and thirteen parent-reported neurodevelopment outcomes were summarized using counts and frequencies and compared across CHD types and subtypes. Eleven percent of cases had a genetic diagnosis. Among cases without a genetic diagnosis, the majority had conotruncal heart defects (40%) or left ventricular outflow tract obstruction (21%). Across CHD types, there were significant differences (p<0.05) in the distribution of all four case characteristics (e.g., sex), four parental characteristics (e.g., maternal pregestational diabetes), and five neurodevelopmental outcomes (e.g., learning disabilities). Several characteristics (e.g., sex) were also significantly different across CHD subtypes. The PCGC cohort is one of the largest CHD cohorts available for the study of genetic determinants of risk and outcomes. The majority of cases do not have a genetic diagnosis. This description of the PCGC cohort, including differences across CHD types and subtypes, provides a reference work for investigators who are interested in collaborating with or using publically available resources from the PCGC.
Keywords: Adult; Cohort Studies; Female; Gene Regulatory Networks; Heart Defects, Congenital; Humans; Male; Phenotype

De novo variants in congenital diaphragmatic hernia identify MYRF as a new syndrome and reveal genetic overlaps with other developmental disorders. - Qi, Hongjian; Yu, Lan; Zhou, Xueya; Wynn, Julia; Zhao, Haoquan; Guo, Yicheng; Zhu, Na; Kitaygorodsky, Alexander; Hernan, Rebecca; Aspelund, Gudrun; Lim, Foong-Yen; Crombleholme, Timothy; et al. (PLoS Genet, 2018)
Congenital diaphragmatic hernia (CDH) is a severe birth defect that is often accompanied by other congenital anomalies. Previous exome sequencing studies for CDH have supported a role of de novo damaging variants but did not identify any recurrently mutated genes. To investigate further the genetics of CDH, we analyzed de novo coding variants in 362 proband-parent trios including 271 new trios reported in this study. We identified four unrelated individuals with damaging de novo variants in MYRF (P = 5.3x10(-8)), including one likely gene-disrupting (LGD) and three deleterious missense (D-mis) variants. Eight additional individuals with de novo LGD or missense variants were identified from our other genetic studies or from the literature. Common phenotypes of MYRF de novo variant carriers include CDH, congenital heart disease and genitourinary abnormalities, suggesting that it represents a novel syndrome. MYRF is a membrane associated transcriptional factor highly expressed in developing diaphragm and is depleted of LGD variants in the general population. All de novo missense variants aggregated in two functional protein domains. Analyzing the transcriptome of patient-derived diaphragm fibroblast cells suggest that disease associated variants abolish the transcription factor activity. Furthermore, we showed that the remaining genes with damaging variants in CDH significantly overlap with genes implicated in other developmental disorders. Gene expression patterns and patient phenotypes support pleiotropic effects of damaging variants in these genes on CDH and other developmental disorders. Finally, functional enrichment analysis implicates the disruption of regulation of gene expression, kinase activities, intra-cellular signaling, and cytoskeleton organization as pathogenic mechanisms in CDH.
Keywords: Child, Preschool; Developmental Disabilities; DNA Copy Number Variations; Female; Genetic Variation; Heart Defects, Congenital; Hernias, Diaphragmatic, Congenital; Humans; Infant, Newborn; Longitudinal Studies; Male; Membrane Proteins; Mutation; Mutation, Missense; Phenotype; Sequence Analysis, RNA; Syndrome; Transcription Factors; Whole Exome Sequencing; Whole Genome Sequencing

Detection of variants in dystroglycanopathy-associated genes through the application of targeted whole-exome sequencing analysis to a large cohort of patients with unexplained limb-girdle muscle weakness. - Johnson, Katherine; Bertoli, Marta; Phillips, Lauren; Topf, Ana; Van den Bergh, Peter; Vissing, John; Witting, Nanna; Nafissi, Shahriar; Jamal-Omidi, Shirin; Łusakowska, Anna; Kostera-Pruszczyk, Anna; Potulska-Chromik, Anna; et al. (Skelet Muscle, 2018)
BACKGROUND: Dystroglycanopathies are a clinically and genetically heterogeneous group of disorders that are typically characterised by limb-girdle muscle weakness. Mutations in 18 different genes have been associated with dystroglycanopathies, the encoded proteins of which typically modulate the binding of α-dystroglycan to extracellular matrix ligands by altering its glycosylation. This results in a disruption of the structural integrity of the myocyte, ultimately leading to muscle degeneration. METHODS: Deep phenotypic information was gathered using the PhenoTips online software for 1001 patients with unexplained limb-girdle muscle weakness from 43 different centres across 21 European and Middle Eastern countries. Whole-exome sequencing with at least 250 ng DNA was completed using an Illumina exome capture and a 38 Mb baited target. Genes known to be associated with dystroglycanopathies were analysed for disease-causing variants. RESULTS: Suspected pathogenic variants were detected in DPM3, ISPD, POMT1 and FKTN in one patient each, in POMK in two patients, in GMPPB in three patients, in FKRP in eight patients and in POMT2 in ten patients. This indicated a frequency of 2.7% for the disease group within the cohort of 1001 patients with unexplained limb-girdle muscle weakness. The phenotypes of the 27 patients were highly variable, yet with a fundamental presentation of proximal muscle weakness and elevated serum creatine kinase. CONCLUSIONS: Overall, we have identified 27 patients with suspected pathogenic variants in dystroglycanopathy-associated genes. We present evidence for the genetic and phenotypic diversity of the dystroglycanopathies as a disease group, while also highlighting the advantage of incorporating next-generation sequencing into the diagnostic pathway of rare diseases.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Child; Child, Preschool; Dystroglycans; Female; Genetic Predisposition to Disease; Genetic Variation; Glycosylation; Heterozygote; Homozygote; Humans; Male; Middle Aged; Muscle Proteins; Muscular Dystrophies, Limb-Girdle; Mutation; Phenotype; Whole Exome Sequencing; Young Adult

Discordance in the Dependence on Kisspeptin Signaling in Mini Puberty vs Adolescent Puberty: Human Genetic Evidence. - Shahab, Muhammad; Lippincott, Margaret; Chan, Yee-Ming; Davies, Addie; Merino, Paulina M; Plummer, Lacey; Mericq, Veronica; Seminara, Stephanie (J Clin Endocrinol Metab, 2018)
Context: Hypothalamic kisspeptin signaling plays a critical role in the initiation and maintenance of reproductive function. Biallelic mutations in the coding sequence of KISS1R (GPR54) have been identified in patients with idiopathic hypogonadotropic hypogonadism, but it is unknown whether biallelic variants can also be associated with related reproductive disorders. Case Description: A missense homozygous variant (c.890G>T p.R297L) in KISS1R was identified in a child who presented with microphallus and bilateral cryptorchidism. This variant has been reported to reduce, but not abolish, postreceptor signaling in vitro. Biochemical evaluation during the neonatal period revealed low testosterone levels. By 11 years and 8 months, the boy began demonstrating increases in testicular volume. By 17 years and 3 months, his testicular volume was 20 mL; his penile length was 7.3 cm; and he had adult levels of circulating gonadotropins and testosterone. Conclusion: This case report associates biallelic loss-of-function mutations in KISS1R with normal timing of adolescent puberty. Because these coding sequence variants occurred in a patient with microphallus and cryptorchidism, they demonstrate different levels of dependence of the hypothalamic-pituitary-gonadal cascade on kisspeptin signaling at distinct times in the reproductive life span. The suppression of the hypothalamic-pituitary-gonadal cascade during early life but not adolescence suggests that the mini puberty of infancy depends more on kisspeptin-induced, gonadotropin-releasing hormone-induced luteinizing hormone secretion than does adolescent puberty.
Keywords: Cryptorchidism; Follicle Stimulating Hormone; Follow-Up Studies; Humans; Infant; Kisspeptins; Luteinizing Hormone; Male; Mutation, Missense; Penis; Receptors, Kisspeptin-1; Sexual Maturation; Signal Transduction; Testosterone

Dissecting the Causal Mechanism of X-Linked Dystonia-Parkinsonism by Integrating Genome and Transcriptome Assembly. - Aneichyk, Tatsiana; Hendriks, William T; Yadav, Rachita; Shin, David; Gao, Dadi; Vaine, Christine A; Collins, Ryan L; Domingo, Aloysius; Currall, Benjamin; Stortchevoi, Alexei; Multhaupt-Buell, Trisha; Penney, Ellen B; et al. (Cell, 2018)
X-linked Dystonia-Parkinsonism (XDP) is a Mendelian neurodegenerative disease that is endemic to the Philippines and is associated with a founder haplotype. We integrated multiple genome and transcriptome assembly technologies to narrow the causal mutation to the TAF1 locus, which included a SINE-VNTR-Alu (SVA) retrotransposition into intron 32 of the gene. Transcriptome analyses identified decreased expression of the canonical cTAF1 transcript among XDP probands, and de novo assembly across multiple pluripotent stem-cell-derived neuronal lineages discovered aberrant TAF1 transcription that involved alternative splicing and intron retention (IR) in proximity to the SVA that was anti-correlated with overall TAF1 expression. CRISPR/Cas9 excision of the SVA rescued this XDP-specific transcriptional signature and normalized TAF1 expression in probands. These data suggest an SVA-mediated aberrant transcriptional mechanism associated with XDP and may provide a roadmap for layered technologies and integrated assembly-based analyses for other unsolved Mendelian disorders.
Keywords: Alternative Splicing; Alu Elements; Base Sequence; Cohort Studies; CRISPR-Cas Systems; Dystonic Disorders; Family; Female; Genetic Diseases, X-Linked; Genetic Loci; Genome, Human; Haplotypes; High-Throughput Nucleotide Sequencing; Histone Acetyltransferases; Humans; Induced Pluripotent Stem Cells; Introns; Male; Minisatellite Repeats; Models, Genetic; Nerve Degeneration; Neural Stem Cells; Neurons; RNA, Messenger; Short Interspersed Nucleotide Elements; TATA-Binding Protein Associated Factors; Transcription Factor TFIID; Transcriptome

Dual Molecular Effects of Dominant RORA Mutations Cause Two Variants of Syndromic Intellectual Disability with Either Autism or Cerebellar Ataxia. - Guissart, Claire; Latypova, Xénia; Rollier, Paul; Khan, Tahir N; Stamberger, Hannah; McWalter, Kirsty; Cho, Megan T; Kjaergaard, Susanne; Weckhuysen, Sarah; Lesca, Gaetan; Besnard, Thomas; Õunap, Katrin; et al. (Am J Hum Genet, 2018)
RORα, the RAR-related orphan nuclear receptor alpha, is essential for cerebellar development. The spontaneous mutant mouse staggerer, with an ataxic gait caused by neurodegeneration of cerebellar Purkinje cells, was discovered two decades ago to result from homozygous intragenic Rora deletions. However, RORA mutations were hitherto undocumented in humans. Through a multi-centric collaboration, we identified three copy-number variant deletions (two de novo and one dominantly inherited in three generations), one de novo disrupting duplication, and nine de novo point mutations (three truncating, one canonical splice site, and five missense mutations) involving RORA in 16 individuals from 13 families with variable neurodevelopmental delay and intellectual disability (ID)-associated autistic features, cerebellar ataxia, and epilepsy. Consistent with the human and mouse data, disruption of the D. rerio ortholog, roraa, causes significant reduction in the size of the developing cerebellum. Systematic in vivo complementation studies showed that, whereas wild-type human RORA mRNA could complement the cerebellar pathology, missense variants had two distinct pathogenic mechanisms of either haploinsufficiency or a dominant toxic effect according to their localization in the ligand-binding or DNA-binding domains, respectively. This dichotomous direction of effect is likely relevant to the phenotype in humans: individuals with loss-of-function variants leading to haploinsufficiency show ID with autistic features, while individuals with de novo dominant toxic variants present with ID, ataxia, and cerebellar atrophy. Our combined genetic and functional data highlight the complex mutational landscape at the human RORA locus and suggest that dual mutational effects likely determine phenotypic outcome.
Keywords: Adolescent; Adult; Aged, 80 and over; Alleles; Animals; Autistic Disorder; Brain; Cerebellar Ataxia; Child; Child, Preschool; Disease Models, Animal; DNA Copy Number Variations; Female; Genes, Dominant; Genetic Complementation Test; Humans; Intellectual Disability; Larva; Magnetic Resonance Imaging; Male; Middle Aged; Mutation, Missense; Nuclear Receptor Subfamily 1, Group F, Member 1; Purkinje Cells; Syndrome; Zebrafish

Enrolling Genomics Research Participants through a Clinical Setting: the Impact of Existing Clinical Relationships on Informed Consent and Expectations for Return of Research Results. - Berrios, Courtney; James, Cynthia A; Raraigh, Karen; Bollinger, Juli; Murray, Brittney; Tichnell, Crystal; Applegate, Carolyn D; Bergner, Amanda L (J Genet Couns, 2018)
Genetic counselors working in a clinical setting may find themselves recruiting, enrolling, and returning results for genomic research, and existing clinical relationships with study participants may impact these research interactions. We present a qualitative study using semi-structured interviews of participants enrolled in a genome sequencing/exome sequencing (GS/ES) study at the same institution where they receive clinical care. Interviews were coded for motivations to participate and expectations of this research. The interviews revealed common motivations for participation, including altruism and hope for benefit for themselves, family members, and/or others with their condition. Additionally, themes emerged related to unintentional influence based on trust of the clinical provider that recruited them to the study. Participant trust in the enrolling provider at times appeared to extend to the study team to decide which research results to return and to do so in an appropriate format. Participants also based expectations for research results return on previous clinical genetic testing experiences, which may or may not be realistic depending on study design. It is imperative that genetic counselors enrolling patients into research studies be aware of the potential influence of their clinical relationship on potential subjects, be transparent about their role on the study team, and help set expectations about the study process, including results return.
Keywords: Base Sequence; Decision Making; Family; Female; Genetic Testing; Humans; Informed Consent; Male; Motivation; Qualitative Research; Research Design; Trust

ERCC4 variants identified in a cohort of patients with segmental progeroid syndromes. - Mori, Takayasu; Yousefzadeh, Matthew J; Faridounnia, Maryam; Chong, Jessica X; Hisama, Fuki M; Hudgins, Louanne; Mercado, Gabriela; Wade, Erin A; Barghouthy, Amira S; Lee, Lin; Martin, George M; Nickerson, Deborah A; et al. (Hum Mutat, 2018)
Pathogenic variants in genes, which encode DNA repair and damage response proteins, result in a number of genomic instability syndromes with features of accelerated aging. ERCC4 (XPF) encodes a protein that forms a complex with ERCC1 and is required for the 5' incision during nucleotide excision repair. ERCC4 is also FANCQ, illustrating a critical role in interstrand crosslink repair. Pathogenic variants in this gene cause xeroderma pigmentosum, XFE progeroid syndrome, Cockayne syndrome (CS), and Fanconi anemia. We performed massive parallel sequencing for 42 unsolved cases submitted to the International Registry of Werner Syndrome. Two cases, each carrying two novel heterozygous ERCC4 variants, were identified. The first case was a compound heterozygote for: c.2395C > T (p.Arg799Trp) and c.388+1164_792+795del (p.Gly130Aspfs*18). Further molecular and cellular studies indicated that the ERCC4 variants in this patient are responsible for a phenotype consistent with a variant of CS. The second case was heterozygous for two variants in cis: c.[1488A > T; c.2579C > A] (p.[Gln496His; Ala860Asp]). While the second case also had several phenotypic features of accelerated aging, we were unable to provide biological evidence supporting the pathogenic roles of the associated ERCC4 variants. Precise genetic causes and disease mechanism of the second case remains to be determined.
Keywords: Actins; Aged; Cockayne Syndrome; DNA Repair; DNA-Binding Proteins; Fanconi Anemia; Female; Genetic Predisposition to Disease; Humans; Lamin Type A; Male; Middle Aged; Pedigree; Xeroderma Pigmentosum

FOXP3 mutations causing early-onset insulin-requiring diabetes but without other features of immune dysregulation, polyendocrinopathy, enteropathy, X-linked syndrome. - Hwang, Jessica L; Park, Soo-Young; Ye, Honggang; Sanyoura, May; Pastore, Ashley N; Carmody, David; Del Gaudio, Daniela; Wilson, Janna F; Hanis, Craig L; Liu, Xiaoming; Atzmon, Gil; Glaser, Benjamin; et al. (Pediatr Diabetes, 2018)
Diabetes occurs in 1/90 000 to 1/160 000 births and when diagnosed under 6 months of age is very likely to have a primary genetic cause. FOXP3 encodes a transcription factor critical for T regulatory cell function and mutations are known to cause "immune dysregulation, polyendocrinopathy (including insulin-requiring diabetes), enteropathy, X-linked" (IPEX) syndrome. This condition is often fatal unless patients receive a bone-marrow transplant. Here we describe the phenotype of male neonates and infants who had insulin-requiring diabetes without other features of IPEX syndrome and were found to have mutations in FOXP3. Whole-exome or next generation sequencing of genes of interest was carried out in subjects with isolated neonatal diabetes without a known genetic cause. RT-PCR was carried out to investigate the effects on RNA splicing of a novel intronic splice-site variant. Four male subjects were found to have FOXP3 variants in the hemizygous state: p.Arg114Trp, p.Arg347His, p.Lys393Met, and c.1044+5G>A which was detected in 2 unrelated probands and in a brother diagnosed with diabetes at 2.1 years of age. Of these, p.Arg114Trp is likely a benign rare variant found in individuals of Ashkenazi Jewish ancestry and p.Arg347His has been previously described in patients with classic IPEX syndrome. The p.Lys393Met and c.1044+5G>A variants are novel to this study. RT-PCR studies of the c.1044+5G>A splice variant confirmed it affected RNA splicing by generating both a wild type and truncated transcript. We conclude that FOXP3 mutations can cause early-onset insulin-requiring diabetes with or without other features of IPEX syndrome.
Keywords: Diabetes Mellitus; Diabetes Mellitus, Type 1; Diarrhea; Forkhead Transcription Factors; Genetic Diseases, X-Linked; Humans; Immune System Diseases; Infant; Infant, Newborn; Male; Registries

Genetic analysis of CHARGE syndrome identifies overlapping molecular biology. - Moccia, Amanda; Srivastava, Anshika; Skidmore, Jennifer M; Bernat, John A; Wheeler, Marsha; Chong, Jessica X; Nickerson, Deborah; Bamshad, Michael; Hefner, Margaret A; Martin, Donna M; Bielas, Stephanie L (Genet Med, 2018)
PURPOSE: CHARGE syndrome is an autosomal-dominant, multiple congenital anomaly condition characterized by vision and hearing loss, congenital heart disease, and malformations of craniofacial and other structures. Pathogenic variants in CHD7, encoding adenosine triphosphate-dependent chromodomain helicase DNA binding protein 7, are present in the majority of affected individuals. However, no causal variant can be found in 5-30% (depending on the cohort) of individuals with a clinical diagnosis of CHARGE syndrome. METHODS: We performed whole-exome sequencing (WES) on 28 families from which at least one individual presented with features highly suggestive of CHARGE syndrome. RESULTS: Pathogenic variants in CHD7 were present in 15 of 28 individuals (53.6%), whereas 4 (14.3%) individuals had pathogenic variants in other genes (RERE, KMT2D, EP300, or PUF60). A variant of uncertain clinical significance in KDM6A was identified in one (3.5%) individual. The remaining eight (28.6%) individuals were not found to have pathogenic variants by WES. CONCLUSION: These results demonstrate that the phenotypic features of CHARGE syndrome overlap with multiple other rare single-gene syndromes. Additionally, they implicate a shared molecular pathology that disrupts epigenetic regulation of multiple-organ development.
Keywords: Adolescent; Adult; Carrier Proteins; CHARGE Syndrome; Child; Child, Preschool; Cohort Studies; DNA Helicases; DNA-Binding Proteins; E1A-Associated p300 Protein; Epigenesis, Genetic; Female; Genetic Testing; Humans; Infant; Male; Mutation; Neoplasm Proteins; Phenotype; Repressor Proteins; RNA Splicing Factors

Genetic variants in components of the NALCN-UNC80-UNC79 ion channel complex cause a broad clinical phenotype (NALCN channelopathies). - Bramswig, Nuria C; Bertoli-Avella, Aida M; Albrecht, Beate; Al Aqeel, Aida I; Alhashem, Amal; Al-Sannaa, Nouriya; Bah, Maissa; Bröhl, Katharina; Depienne, Christel; Dorison, Nathalie; Doummar, Diane; Ehmke, Nadja; et al. (Hum Genet, 2018)
NALCN is a conserved cation channel, which conducts a permanent sodium leak current and regulates resting membrane potential and neuronal excitability. It is part of a large ion channel complex, the "NALCN channelosome", consisting of multiple proteins including UNC80 and UNC79. The predominant neuronal expression pattern and its function suggest an important role in neuronal function and disease. So far, biallelic NALCN and UNC80 variants have been described in a small number of individuals leading to infantile hypotonia, psychomotor retardation, and characteristic facies 1 (IHPRF1, OMIM 615419) and 2 (IHPRF2, OMIM 616801), respectively. Heterozygous de novo NALCN missense variants in the S5/S6 pore-forming segments lead to congenital contractures of the limbs and face, hypotonia, and developmental delay (CLIFAHDD, OMIM 616266) with some clinical overlap. In this study, we present detailed clinical information of 16 novel individuals with biallelic NALCN variants, 1 individual with a heterozygous de novo NALCN missense variant and an interesting clinical phenotype without contractures, and 12 individuals with biallelic UNC80 variants. We report for the first time a missense NALCN variant located in the predicted S6 pore-forming unit inherited in an autosomal-recessive manner leading to mild IHPRF1. We show evidence of clinical variability, especially among IHPRF1-affected individuals, and discuss differences between the IHPRF1- and IHPRF2 phenotypes. In summary, we provide a comprehensive overview of IHPRF1 and IHPRF2 phenotypes based on the largest cohort of individuals reported so far and provide additional insights into the clinical phenotypes of these neurodevelopmental diseases to help improve counseling of affected families.
Keywords: Adolescent; Adult; Carrier Proteins; Channelopathies; Child; Child, Preschool; Developmental Disabilities; Female; Genetic Markers; Genetic Variation; Humans; Infant; Infant, Newborn; Male; Membrane Proteins; Phenotype; Sodium Channels; Young Adult

Genotype-phenotype investigation of 35 patients from 11 unrelated families with camptodactyly-arthropathy-coxa vara-pericarditis (CACP) syndrome. - Yilmaz, Saliha; Uludağ Alkaya, Dilek; Kasapcopur, Ozgur; Barut, Kenan; Akdemir, Ekin S; Celen, Cemre; Youngblood, Mark W; Yasuno, Katsuhito; Bilguvar, Kaya; Günel, Murat; Tuysuz, Beyhan (Mol Genet Genomic Med, 2018)
BACKGROUND: The camptodactyly-arthropathy-coxa vara-pericarditis syndrome (CACP) is a rare autosomal recessive condition characterized by camptodactyly, noninflammatory arthropathy, coxa vara, and pericarditis. CACP is caused by mutations in the proteoglycan 4 (PRG4) gene, which encodes a lubricating glycoprotein present in the synovial fluid and at the surface of articular cartilage. METHODS: In the present study, we compared the clinical and molecular findings of CACP syndrome in 35 patients from 11 unrelated families. In 28 patients, whole exome sequencing was used to investigate genomic variations. RESULTS: We found that camptodactyly of hands was the first symptom presented by most patients. Swelling of wrists, knees, and elbows began before 4 years of age, while the age of joint involvement was variable. Patients reported an increased pain level after the age of 10, and severe hip involvement developed after 20 years old. All patients presented developmental coxa vara and seven patients (~22%) had pleural effusion, pericarditis, and/or ascites. We identified nine novel genomic alterations, including the first case of homozygous complete deletion of exon 1 in the PRG4 gene. CONCLUSION: With this study, we contribute to the catalog of CACP causing variants. We confirm that the skeletal component of this disease worsens with age, and presents the potential mechanisms for interfamily variability, by discussing the influence of a modifier gene and escape from nonsense-mediated mRNA decay. We believe that this report will increase awareness of this familial arthropathic condition and the characteristic clinical and radiological findings will facilitate the differentiation from the common childhood rheumatic diseases such as juvenile idiopathic arthritis.
Keywords: Adolescent; Adult; Arthropathy, Neurogenic; Child; Child, Preschool; Coxa Vara; Exons; Female; Genetic Association Studies; Hand Deformities, Congenital; Humans; Male; Middle Aged; Mutation; Proteoglycans; Retrospective Studies; Sequence Deletion; Synovitis; Whole Exome Sequencing

Heterozygous Truncating Variants in POMP Escape Nonsense-Mediated Decay and Cause a Unique Immune Dysregulatory Syndrome. - Poli, M Cecilia; Ebstein, Frédéric; Nicholas, Sarah K; de Guzman, Marietta M; Forbes, Lisa R; Chinn, Ivan K; Mace, Emily M; Vogel, Tiphanie P; Carisey, Alexandre F; Benavides, Felipe; Coban-Akdemir, Zeynep H; Gibbs, Richard A; et al. (Am J Hum Genet, 2018)
The proteasome processes proteins to facilitate immune recognition and host defense. When inherently defective, it can lead to aberrant immunity resulting in a dysregulated response that can cause autoimmunity and/or autoinflammation. Biallelic or digenic loss-of-function variants in some of the proteasome subunits have been described as causing a primary immunodeficiency disease that manifests as a severe dysregulatory syndrome: chronic atypical neutrophilic dermatosis with lipodystrophy and elevated temperature (CANDLE). Proteasome maturation protein (POMP) is a chaperone for proteasome assembly and is critical for the incorporation of catalytic subunits into the proteasome. Here, we characterize and describe POMP-related autoinflammation and immune dysregulation disease (PRAID) discovered in two unrelated individuals with a unique constellation of early-onset combined immunodeficiency, inflammatory neutrophilic dermatosis, and autoimmunity. We also begin to delineate a complex genetic mechanism whereby de novo heterozygous frameshift variants in the penultimate exon of POMP escape nonsense-mediated mRNA decay (NMD) and result in a truncated protein that perturbs proteasome assembly by a dominant-negative mechanism. To our knowledge, this mechanism has not been reported in any primary immunodeficiencies, autoinflammatory syndromes, or autoimmune diseases. Here, we define a unique hypo- and hyper-immune phenotype and report an immune dysregulation syndrome caused by frameshift mutations that escape NMD.
Keywords: Base Sequence; Cell Line; Endoplasmic Reticulum Stress; Exons; Family; Frameshift Mutation; Genetic Predisposition to Disease; Heterozygote; Humans; Immunologic Deficiency Syndromes; Immunophenotyping; Infant, Newborn; Inflammation; Interferon Type I; Male; Molecular Chaperones; Mutant Proteins; Mutation; Nonsense Mediated mRNA Decay; Phenotype; Proteasome Endopeptidase Complex; RNA, Messenger; Syndrome; Unfolded Protein Response

A homozygous missense variant in VWA2, encoding an interactor of the Fraser-complex, in a patient with vesicoureteral reflux. - van der Ven, Amelie T; Kobbe, Birgit; Kohl, Stefan; Shril, Shirlee; Pogoda, Hans-Martin; Imhof, Thomas; Ityel, Hadas; Vivante, Asaf; Chen, Jing; Hwang, Daw-Yang; Connaughton, Dervla M; Mann, Nina; et al. (PLoS One, 2018)
Congenital anomalies of the kidney and urinary tract (CAKUT) are the most common cause (40-50%) of chronic kidney disease (CKD) in children. About 40 monogenic causes of CAKUT have so far been discovered. To date less than 20% of CAKUT cases can be explained by mutations in these 40 genes. To identify additional monogenic causes of CAKUT, we performed whole exome sequencing (WES) and homozygosity mapping (HM) in a patient with CAKUT from Indian origin and consanguineous descent. We identified a homozygous missense mutation (c.1336C>T, p.Arg446Cys) in the gene Von Willebrand factor A domain containing 2 (VWA2). With immunohistochemistry studies on kidneys of newborn (P1) mice, we show that Vwa2 and Fraser extracellular matrix complex subunit 1 (Fras1) co-localize in the nephrogenic zone of the renal cortex. We identified a pronounced expression of Vwa2 in the basement membrane of the ureteric bud (UB) and derivatives of the metanephric mesenchyme (MM). By applying in vitro assays, we demonstrate that the Arg446Cys mutation decreases translocation of monomeric VWA2 protein and increases translocation of aggregated VWA2 protein into the extracellular space. This is potentially due to the additional, unpaired cysteine residue in the mutated protein that is used for intermolecular disulfide bond formation. VWA2 is a known, direct interactor of FRAS1 of the Fraser-Complex (FC). FC-encoding genes and interacting proteins have previously been implicated in the pathogenesis of syndromic and/or isolated CAKUT phenotypes in humans. VWA2 therefore constitutes a very strong candidate in the search for novel CAKUT-causing genes. Our results from in vitro experiments indicate a dose-dependent neomorphic effect of the Arg446Cys homozygous mutation in VWA2.
Keywords: Amino Acid Sequence; Amino Acid Substitution; Animals; Animals, Newborn; Biomarkers, Tumor; Child; Consanguinity; Conserved Sequence; Exons; Extracellular Matrix Proteins; Fraser Syndrome; Gene Expression Regulation, Developmental; Homozygote; Humans; Male; Mice; Models, Animal; Models, Molecular; Mutation, Missense; Pedigree; Sequence Homology, Amino Acid; Urogenital Abnormalities; Urogenital System; Vesico-Ureteral Reflux

Identification of likely pathogenic and known variants in TSPEAR, LAMB3, BCOR, and WNT10A in four Turkish families with tooth agenesis. - Du, Renqian; Dinckan, Nuriye; Song, Xiaofei; Coban-Akdemir, Zeynep; Jhangiani, Shalini N; Guven, Yeliz; Aktoren, Oya; Kayserili, Hülya; Petty, Lauren E; Muzny, Donna M; Below, Jennifer E; Boerwinkle, Eric; et al. (Hum Genet, 2018)
Tooth agenesis (TA), the failure of development of one or more permanent teeth, is a common craniofacial abnormality observed in different world populations. The genetic etiology of TA is heterogeneous; more than a dozen genes have been associated with isolated or nonsyndromic TA, and more than 80 genes with syndromic forms. In this study, we applied whole exome sequencing (WES) to identify candidate genes contributing to TA in four Turkish families. Likely pathogenic variants with a low allele frequency in the general population were identified in four disease-associated genes, including two distinct variants in TSPEAR, associated with syndromic and isolated TA in one family each; a variant in LAMB3 associated with syndromic TA in one family; and a variant in BCOR plus a disease-associated WNT10A variant in one family with syndromic TA. With the notable exception of WNT10A (Tooth agenesis, selective, 4, MIM #150400), the genotype-phenotype relationships described in the present cohort represent an expansion of the clinical spectrum associated with these genes: TSPEAR (Deafness, autosomal recessive 98, MIM #614861), LAMB3 (Amelogenesis imperfecta, type IA, MIM #104530; Epidermolysis bullosa, junctional, MIMs #226700 and #226650), and BCOR (Microphthalmia, syndromic 2, MIM #300166). We provide evidence supporting the candidacy of these genes with TA, and propose TSPEAR as a novel nonsyndromic TA gene. Our data also suggest potential multilocus genomic variation, or mutational burden, in a single family, involving the BCOR and WNT10A loci, underscoring the complexity of the genotype-phenotype relationship in the common complex trait of TA.
Keywords: Anodontia; Cell Adhesion Molecules; Child; Child, Preschool; Female; Genetic Markers; Humans; Male; Mutation; Pedigree; Phenotype; Proteins; Proto-Oncogene Proteins; Repressor Proteins; Turkey; Wnt Proteins

Insights into clonal haematopoiesis from 8,342 mosaic chromosomal alterations. - Loh, Po-Ru; Genovese, Giulio; Handsaker, Robert E; Finucane, Hilary K; Reshef, Yakir A; Palamara, Pier Francesco; Birmann, Brenda M; Talkowski, Michael E; Bakhoum, Samuel F; McCarroll, Steven A; Price, Alkes L (Nature, 2018)
The selective pressures that shape clonal evolution in healthy individuals are largely unknown. Here we investigate 8,342 mosaic chromosomal alterations, from 50 kb to 249 Mb long, that we uncovered in blood-derived DNA from 151,202 UK Biobank participants using phase-based computational techniques (estimated false discovery rate, 6-9%). We found six loci at which inherited variants associated strongly with the acquisition of deletions or loss of heterozygosity in cis. At three such loci (MPL, TM2D3-TARSL2, and FRA10B), we identified a likely causal variant that acted with high penetrance (5-50%). Inherited alleles at one locus appeared to affect the probability of somatic mutation, and at three other loci to be objects of positive or negative clonal selection. Several specific mosaic chromosomal alterations were strongly associated with future haematological malignancies. Our results reveal a multitude of paths towards clonal expansions with a wide range of effects on human health.
Keywords: Adult; Aged; Alleles; Biological Specimen Banks; Chromosome Aberrations; Chromosome Breakage; Chromosome Fragile Sites; Chromosomes, Human, Pair 10; Clone Cells; Female; Health; Hematologic Neoplasms; Hematopoiesis; Humans; Male; Middle Aged; Mosaicism; Penetrance; United Kingdom

LTBP3 Pathogenic Variants Predispose Individuals to Thoracic Aortic Aneurysms and Dissections. - Guo, Dong-Chuan; Regalado, Ellen S; Pinard, Amelie; Chen, Jiyuan; Lee, Kwanghyuk; Rigelsky, Christina; Zilberberg, Lior; Hostetler, Ellen M; Aldred, Micheala; Wallace, Stephanie E; Prakash, Siddharth K; Leal, Suzanne M; et al. (Am J Hum Genet, 2018)
The major diseases affecting the thoracic aorta are aneurysms and acute dissections, and pathogenic variants in 11 genes are confirmed to lead to heritable thoracic aortic disease. However, many families in which multiple members have thoracic aortic disease do not have alterations in the known aortopathy genes. Genes highly expressed in the aorta were assessed for rare variants in exome sequencing data from such families, and compound rare heterozygous variants (p.Pro45Argfs25 and p.Glu750) in LTBP3 were identified in affected members of one family. A homozygous variant (p.Asn678_Gly681delinsThrCys) that introduces an additional cysteine into an epidermal growth factor (EGF)-like domain in the corresponding protein, latent TGF-β binding protein (LTBP-3), was identified in a second family. Individuals with compound heterozygous or homozygous variants in these families have aneurysms and dissections of the thoracic aorta, as well as aneurysms of the abdominal aorta and other arteries, along with dental abnormalities and short stature. Heterozygous carriers of the p.Asn678_Gly681delinsThrCys variant have later onset of thoracic aortic disease, as well as dental abnormalities. In these families, LTBP3 variants segregated with thoracic aortic disease with a combined LOD score of 3.9. Additionally, heterozygous rare LTBP3 variants were found in individuals with early onset of acute aortic dissections, and some of these variants disrupted LTBP-3 levels or EGF-like domains. When compared to wild-type mice, Ltbp3 mice have enlarged aortic roots and ascending aortas. In summary, homozygous LTBP3 pathogenic variants predispose individuals to thoracic aortic aneurysms and dissections, along with the previously described skeletal and dental abnormalities.
Keywords: Adult; Aged, 80 and over; Aneurysm, Dissecting; Animals; Aortic Aneurysm, Thoracic; Blood Pressure; Female; Genetic Predisposition to Disease; Homozygote; Humans; Latent TGF-beta Binding Proteins; Male; Mice; Middle Aged; Mutation; Pedigree

Monoallelic Mutations to DNAJB11 Cause Atypical Autosomal-Dominant Polycystic Kidney Disease. - Cornec-Le Gall, Emilie; Olson, Rory J; Besse, Whitney; Heyer, Christina M; Gainullin, Vladimir G; Smith, Jessica M; Audrézet, Marie-Pierre; Hopp, Katharina; Porath, Binu; Shi, Beili; Baheti, Saurabh; Senum, Sarah R; et al. (Am J Hum Genet, 2018)
Autosomal-dominant polycystic kidney disease (ADPKD) is characterized by the progressive development of kidney cysts, often resulting in end-stage renal disease (ESRD). This disorder is genetically heterogeneous with ∼7% of families genetically unresolved. We performed whole-exome sequencing (WES) in two multiplex ADPKD-like pedigrees, and we analyzed a further 591 genetically unresolved, phenotypically similar families by targeted next-generation sequencing of 65 candidate genes. WES identified a DNAJB11 missense variant (p.Pro54Arg) in two family members presenting with non-enlarged polycystic kidneys and a frameshifting change (c.166_167insTT) in a second family with small renal and liver cysts. DNAJB11 is a co-factor of BiP, a key chaperone in the endoplasmic reticulum controlling folding, trafficking, and degradation of secreted and membrane proteins. Five additional multigenerational families carrying DNAJB11 mutations were identified by the targeted analysis. The clinical phenotype was consistent in the 23 affected members, with non-enlarged cystic kidneys that often evolved to kidney atrophy; 7 subjects reached ESRD from 59 to 89 years. The lack of kidney enlargement, histologically evident interstitial fibrosis in non-cystic parenchyma, and recurring episodes of gout (one family) suggested partial phenotypic overlap with autosomal-dominant tubulointerstitial diseases (ADTKD). Characterization of DNAJB11-null cells and kidney samples from affected individuals revealed a pathogenesis associated with maturation and trafficking defects involving the ADPKD protein, PC1, and ADTKD proteins, such as UMOD. DNAJB11-associated disease is a phenotypic hybrid of ADPKD and ADTKD, characterized by normal-sized cystic kidneys and progressive interstitial fibrosis resulting in late-onset ESRD.
Keywords: Adult; Aged; Aged, 80 and over; Alleles; Amino Acid Sequence; Base Sequence; Epithelial Cells; Family; Female; HSP40 Heat-Shock Proteins; Humans; Loop of Henle; Male; Middle Aged; Mutation; Pedigree; Polycystic Kidney, Autosomal Dominant; TRPP Cation Channels; Uromodulin; Whole Exome Sequencing; Young Adult

Mutations in the Epithelial Cadherin-p120-Catenin Complex Cause Mendelian Non-Syndromic Cleft Lip with or without Cleft Palate. - Cox, Liza L; Cox, Timothy C; Moreno Uribe, Lina M; Zhu, Ying; Richter, Chika T; Nidey, Nichole; Standley, Jennifer M; Deng, Mei; Blue, Elizabeth; Chong, Jessica X; Yang, Yueqin; Carstens, Russ P; et al. (Am J Hum Genet, 2018)
Non-syndromic cleft lip with or without cleft palate (NS-CL/P) is one of the most common human birth defects and is generally considered a complex trait. Despite numerous loci identified by genome-wide association studies, the effect sizes of common variants are relatively small, with much of the presumed genetic contribution remaining elusive. We report exome-sequencing results in 209 people from 72 multi-affected families with pedigree structures consistent with autosomal-dominant inheritance and variable penetrance. Herein, pathogenic variants are described in four genes encoding components of the p120-catenin complex (CTNND1, PLEKHA7, PLEKHA5) and an epithelial splicing regulator (ESRP2), in addition to the known CL/P-associated gene, CDH1, which encodes E-cadherin. The findings were also validated in a second cohort of 497 people with NS-CL/P, comprising small families and singletons with pathogenic variants in these genes identified in 14% of multi-affected families and 2% of the replication cohort of smaller families. Enriched expression of each gene/protein in human and mouse embryonic oro-palatal epithelia, demonstration of functional impact of CTNND1 and ESRP2 variants, and recapitulation of the CL/P spectrum in Ctnnd1 knockout mice support a causative role in CL/P pathogenesis. These data show that primary defects in regulators of epithelial cell adhesion are the most significant contributors to NS-CL/P identified to date and that inherited and de novo single gene variants explain a substantial proportion of NS-CL/P.
Keywords: Alleles; Amino Acid Sequence; Animals; Biotinylation; Cadherins; Catenins; Cleft Lip; Cleft Palate; Epithelium; Female; Gene Deletion; Genetic Predisposition to Disease; Humans; Infant; Infant, Newborn; Male; Mice; Mutation; Palate; Pedigree; Syndrome; Whole Exome Sequencing

Nemaline myopathy and distal arthrogryposis associated with an autosomal recessive TNNT3 splice variant. - Sandaradura, Sarah A; Bournazos, Adam; Mallawaarachchi, Amali; Cummings, Beryl B; Waddell, Leigh B; Jones, Kristi J; Troedson, Christopher; Sudarsanam, Annapurna; Nash, Benjamin M; Peters, Gregory B; Algar, Elizabeth M; MacArthur, Daniel G; et al. (Hum Mutat, 2018)
A male neonate presented with severe weakness, hypotonia, contractures and congenital scoliosis. Skeletal muscle specimens showed marked atrophy and degeneration of fast fibers with striking nemaline rods and hypertrophy of slow fibers that were ultrastructurally normal. A neuromuscular gene panel identified a homozygous essential splice variant in TNNT3 (chr11:1956150G > A, NM_006757.3:c.681+1G > A). TNNT3 encodes skeletal troponin-T and is associated with autosomal dominant distal arthrogryposis. TNNT3 has not previously been associated with nemaline myopathy (NM), a rare congenital myopathy linked to defects in proteins associated with thin filament structure and regulation. cDNA studies confirmed pathogenic consequences of the splice variant, eliciting exon-skipping and intron retention events leading to a frameshift. Western blot showed deficiency of troponin-T protein with secondary loss of troponin-I . We establish a homozygous splice variant in TNNT3 as the likely cause of severe congenital NM with distal arthrogryposis, characterized by specific involvement of Type-2 fibers and deficiency of troponin-T .
Keywords: Arthrogryposis; Genes, Recessive; Humans; Infant; Infant, Newborn; Male; Myopathies, Nemaline; RNA Splice Sites; RNA Splicing; RNA, Messenger; Troponin T

Novel candidate genes and variants underlying autosomal recessive neurodevelopmental disorders with intellectual disability. - Santos-Cortez, Regie Lyn P; Khan, Valeed; Khan, Falak Sher; Mughal, Zaib-Un-Nisa; Chakchouk, Imen; Lee, Kwanghyuk; Rasheed, Memoona; Hamza, Rifat; Acharya, Anushree; Ullah, Ehsan; Saqib, Muhammad Arif Nadeem; Abbe, Izoduwa; et al. (Hum Genet, 2018)
Identification of Mendelian genes for neurodevelopmental disorders using exome sequencing to study autosomal recessive (AR) consanguineous pedigrees has been highly successful. To identify causal variants for syndromic and non-syndromic intellectual disability (ID), exome sequencing was performed using DNA samples from 22 consanguineous Pakistani families with ARID, of which 21 have additional phenotypes including microcephaly. To aid in variant identification, homozygosity mapping and linkage analysis were performed. DNA samples from affected family member(s) from every pedigree underwent exome sequencing. Identified rare damaging exome variants were tested for co-segregation with ID using Sanger sequencing. For seven ARID families, variants were identified in genes not previously associated with ID, including: EI24, FXR1 and TET3 for which knockout mouse models have brain defects; and CACNG7 and TRAPPC10 where cell studies suggest roles in important neural pathways. For two families, the novel ARID genes CARNMT1 and GARNL3 lie within previously reported ID microdeletion regions. We also observed homozygous variants in two ID candidate genes, GRAMD1B and TBRG1, for which each has been previously reported in a single family. An additional 14 families have homozygous variants in established ID genes, of which 11 variants are novel. All ARID genes have increased expression in specific structures of the developing and adult human brain and 91% of the genes are differentially expressed in utero or during early childhood. The identification of novel ARID candidate genes and variants adds to the knowledge base that is required to further understand human brain function and development.
Keywords: Adult; Consanguinity; Family; Female; Genes, Recessive; Genetic Markers; Humans; Intellectual Disability; Male; Middle Aged; Mutation; Neurodevelopmental Disorders; Pedigree

Novel digenic inheritance of PCDH15 and USH1G underlies profound non-syndromic hearing impairment. - Schrauwen, Isabelle; Chakchouk, Imen; Acharya, Anushree; Liaqat, Khurram; Nickerson, Deborah A; Bamshad, Michael J; Shah, Khadim; Ahmad, Wasim; Leal, Suzanne M (BMC Med Genet, 2018)
BACKGROUND: Digenic inheritance is the simplest model of oligenic disease. It can be observed when there is a strong epistatic interaction between two loci. For both syndromic and non-syndromic hearing impairment, several forms of digenic inheritance have been reported. METHODS: We performed exome sequencing in a Pakistani family with profound non-syndromic hereditary hearing impairment to identify the genetic cause of disease. RESULTS: We found that this family displays digenic inheritance for two trans heterozygous missense mutations, one in PCDH15 [p.(Arg1034His)] and another in USH1G [p.(Asp365Asn)]. Both of these genes are known to cause autosomal recessive non-syndromic hearing impairment and Usher syndrome. The protein products of PCDH15 and USH1G function together at the stereocilia tips in the hair cells and are necessary for proper mechanotransduction. Epistasis between Pcdh15 and Ush1G has been previously reported in digenic heterozygous mice. The digenic mice displayed a significant decrease in hearing compared to age-matched heterozygous animals. Until now no human examples have been reported. CONCLUSIONS: The discovery of novel digenic inheritance mechanisms in hereditary hearing impairment will aid in understanding the interaction between defective proteins and further define inner ear function and its interactome.
Keywords: Adult; Animals; Cadherins; Hearing Loss; Heterozygote; Humans; Male; Mechanotransduction, Cellular; Multifactorial Inheritance; Mutation; Nerve Tissue Proteins; Pakistan; Pedigree; Usher Syndromes; Young Adult

A novel NAA10 variant with impaired acetyltransferase activity causes developmental delay, intellectual disability, and hypertrophic cardiomyopathy. - Støve, Svein Isungset; Blenski, Marina; Stray-Pedersen, Asbjørg; Wierenga, Klaas J; Jhangiani, Shalini N; Akdemir, Zeynep Coban; Crawford, David; McTiernan, Nina; Myklebust, Line M; Purcarin, Gabriela; McNall-Knapp, Rene; Wadley, Alexandrea; et al. (Eur J Hum Genet, 2018)
The NAA10-NAA15 complex (NatA) is an N-terminal acetyltransferase that catalyzes N-terminal acetylation of ~40% of all human proteins. N-terminal acetylation has several different roles in the cell, including altering protein stability and degradation, protein localization and protein-protein interactions. In recent years several X-linked NAA10 variants have been associated with genetic disorders. We have identified a previously undescribed NAA10 c.215T>C p.(Ile72Thr) variant in three boys from two unrelated families with a milder phenotypic spectrum in comparison to most of the previously described patients with NAA10 variants. These boys have development delay, intellectual disability, and cardiac abnormalities as overlapping phenotypes. Functional studies reveal that NAA10 Ile72Thr is destabilized, while binding to NAA15 most likely is intact. Surprisingly, the NatA activity of NAA10 Ile72Thr appears normal while its monomeric activity is decreased. This study further broadens the phenotypic spectrum associated with NAA10 deficiency, and adds to the evidence that genotype-phenotype correlations for NAA10 variants are much more complex than initially anticipated.
Keywords: Cardiomyopathy, Hypertrophic; Child, Preschool; Developmental Disabilities; Enzyme Stability; HeLa Cells; Humans; Infant; Intellectual Disability; Male; Mutation; N-Terminal Acetyltransferase A; N-Terminal Acetyltransferase E; Phenotype; Protein Binding; Syndrome

A novel pathogenic variant in a family with paroxysmal kinesigenic dyskinesia and benign familial infantile seizures. - Lu, Jacqueline G; Bishop, Juliet; Cheyette, Sarah; Zhulin, Igor B; Guo, Su; Sobreira, Nara; Brenner, Steven E (Cold Spring Harb Mol Case Stud, 2018)
Paroxysmal kinesigenic dyskinesia (PKD) is a rare neurological disorder characterized by recurrent attacks of dyskinetic movements without alteration of consciousness that are often triggered by the initiation of voluntary movements. Whole-exome sequencing has revealed a cluster of pathogenic variants in (proline-rich transmembrane protein), a gene with a function in synaptic regulation that remains poorly understood. Here, we report the discovery of a novel pathogenic variant inherited in an autosomal dominant pattern in a family with PKD and benign familial infantile seizures (BFIS). After targeted Sanger sequencing did not identify the presence of previously described pathogenic variants, we carried out whole-exome sequencing in the proband and her affected paternal grandfather. This led to the discovery of a novel variant, NM_001256442:exon3:c.C959T/NP_660282.2:p.A320V, altering an evolutionarily conserved alanine at the amino acid position 320 located in the M2 transmembrane region. Sanger sequencing further confirmed the presence of this variant in four affected family members (paternal grandfather, father, brother, and proband) and its absence in two unaffected ones (paternal grandmother and mother). This newly found variant further reinforces the importance of in PKD, BFIS, and possibly other movement disorders. Future functional studies using animal models and human pluripotent stem cell models will provide new insights into the role of and the significance of this variant in regulating neural development and/or function.
Keywords: Amino Acid Sequence; Base Sequence; Child; Chromosome Segregation; Conserved Sequence; Dystonia; Epilepsy, Benign Neonatal; Evolution, Molecular; Family; Female; Humans; Infant; Inheritance Patterns; Male; Membrane Proteins; Mutation; Nerve Tissue Proteins; Pedigree

The role of FREM2 and FRAS1 in the development of congenital diaphragmatic hernia. - Jordan, Valerie K; Beck, Tyler F; Hernandez-Garcia, Andres; Kundert, Peter N; Kim, Bum-Jun; Jhangiani, Shalini N; Gambin, Tomasz; Starkovich, Molly; Punetha, Jaya; Paine, Ingrid S; Posey, Jennifer E; Li, Alexander H; et al. (Hum Mol Genet, 2018)
Congenital diaphragmatic hernia (CDH) has been reported twice in individuals with a clinical diagnosis of Fraser syndrome, a genetic disorder that can be caused by recessive mutations affecting FREM2 and FRAS1. In the extracellular matrix, FREM2 and FRAS1 form a self-stabilizing complex with FREM1, a protein whose deficiency causes sac CDH in humans and mice. By sequencing FREM2 and FRAS1 in a CDH cohort, and searching online databases, we identified five individuals who carried recessive or double heterozygous, putatively deleterious variants in these genes which may represent susceptibility alleles. Three of these alleles were significantly enriched in our CDH cohort compared with ethnically matched controls. We subsequently demonstrated that 8% of Frem2ne/ne and 1% of Fras1Q1263*/Q1263* mice develop the same type of anterior sac CDH seen in FREM1-deficient mice. We went on to show that development of sac hernias in FREM1-deficient mice is preceded by failure of anterior mesothelial fold progression resulting in the persistence of an amuscular, poorly vascularized anterior diaphragm that is abnormally adherent to the underlying liver. Herniation occurs in the perinatal period when the expanding liver protrudes through this amuscular region of the anterior diaphragm that is juxtaposed to areas of muscular diaphragm. Based on these data, we conclude that deficiency of FREM2, and possibly FRAS1, are associated with an increased risk of developing CDH and that loss of the FREM1/FREM2/FRAS1 complex, or its function, leads to anterior sac CDH development through its effects on mesothelial fold progression.
Keywords: Animals; Child; Child, Preschool; Epithelium; Extracellular Matrix Proteins; Female; Hernias, Diaphragmatic, Congenital; Humans; Infant; Infant, Newborn; Male; Mice; Mice, Knockout; Mutation; Pregnancy; Receptors, Interleukin

Truncating Variants in NAA15 Are Associated with Variable Levels of Intellectual Disability, Autism Spectrum Disorder, and Congenital Anomalies. - Cheng, Hanyin; Dharmadhikari, Avinash V; Varland, Sylvia; Ma, Ning; Domingo, Deepti; Kleyner, Robert; Rope, Alan F; Yoon, Margaret; Stray-Pedersen, Asbjørg; Posey, Jennifer E; Crews, Sarah R; Eldomery, Mohammad K; et al. (Am J Hum Genet, 2018)
N-alpha-acetylation is a common co-translational protein modification that is essential for normal cell function in humans. We previously identified the genetic basis of an X-linked infantile lethal Mendelian disorder involving a c.109T>C (p.Ser37Pro) missense variant in NAA10, which encodes the catalytic subunit of the N-terminal acetyltransferase A (NatA) complex. The auxiliary subunit of the NatA complex, NAA15, is the dimeric binding partner for NAA10. Through a genotype-first approach with whole-exome or genome sequencing (WES/WGS) and targeted sequencing analysis, we identified and phenotypically characterized 38 individuals from 33 unrelated families with 25 different de novo or inherited, dominantly acting likely gene disrupting (LGD) variants in NAA15. Clinical features of affected individuals with LGD variants in NAA15 include variable levels of intellectual disability, delayed speech and motor milestones, and autism spectrum disorder. Additionally, mild craniofacial dysmorphology, congenital cardiac anomalies, and seizures are present in some subjects. RNA analysis in cell lines from two individuals showed degradation of the transcripts with LGD variants, probably as a result of nonsense-mediated decay. Functional assays in yeast confirmed a deleterious effect for two of the LGD variants in NAA15. Further supporting a mechanism of haploinsufficiency, individuals with copy-number variant (CNV) deletions involving NAA15 and surrounding genes can present with mild intellectual disability, mild dysmorphic features, motor delays, and decreased growth. We propose that defects in NatA-mediated N-terminal acetylation (NTA) lead to variable levels of neurodevelopmental disorders in humans, supporting the importance of the NatA complex in normal human development.
Keywords: Abnormalities, Multiple; Adolescent; Adult; Autism Spectrum Disorder; Cell Line; Child; Exons; Female; Gene Expression Regulation; Genetic Predisposition to Disease; Genetic Variation; Humans; Intellectual Disability; Male; Middle Aged; Mutation; N-Terminal Acetyltransferase A; N-Terminal Acetyltransferase E; Pedigree; Phenotype; RNA, Messenger; Saccharomyces cerevisiae

A variant in LMX1A causes autosomal recessive severe-to-profound hearing impairment. - Schrauwen, Isabelle; Chakchouk, Imen; Liaqat, Khurram; Jan, Abid; Nasir, Abdul; Hussain, Shabir; Nickerson, Deborah A; Bamshad, Michael J; Ullah, Asmat; Ahmad, Wasim; Leal, Suzanne M (Hum Genet, 2018)
Hereditary hearing impairment is a common sensory disorder that is genetically and phenotypically heterogeneous. In this study, we used a homozygosity mapping and exome sequencing strategy to study a consanguineous Pakistani family with autosomal recessive severe-to-profound hearing impairment. This led to the identification of a missense variant (p.Ile369Thr) in the LMX1A gene affecting a conserved residue in the C-terminus of the protein, which was predicted damaging by an in silico bioinformatics analysis. The p.Ile369Thr variant disrupts several C-terminal and homeodomain residue interactions, including an interaction with homeodomain residue p.Val241 that was previously found to be involved in autosomal dominant progressive HI. LIM-homeodomain factor Lmx1a is expressed in the inner ear through development, shows a progressive restriction to non-sensory epithelia, and is important in the separation of the sensory and non-sensory domains in the inner ear. Homozygous Lmx1a mutant mice (Dreher) are deaf with dysmorphic ears with an abnormal morphogenesis and fused and misshapen sensory organs; however, computed tomography performed on a hearing-impaired family member did not reveal any cochleovestibular malformations. Our results suggest that LMX1A is involved in both human autosomal recessive and dominant sensorineural hearing impairment.
Keywords: Adolescent; Adult; Animals; Child; Disease Models, Animal; Ear, Inner; Female; Genes, Dominant; Genes, Recessive; Hearing Loss; Hearing Loss, Sensorineural; Homozygote; Humans; LIM-Homeodomain Proteins; Male; Mice; Mutation, Missense; Pedigree; Transcription Factors; Whole Exome Sequencing

Variants in EXOSC9 Disrupt the RNA Exosome and Result in Cerebellar Atrophy with Spinal Motor Neuronopathy. - Burns, David T; Donkervoort, Sandra; Müller, Juliane S; Knierim, Ellen; Bharucha-Goebel, Diana; Faqeih, Eissa Ali; Bell, Stephanie K; AlFaifi, Abdullah Y; Monies, Dorota; Millan, Francisca; Retterer, Kyle; Dyack, Sarah; et al. (Am J Hum Genet, 2018)
The exosome is a conserved multi-protein complex that is essential for correct RNA processing. Recessive variants in exosome components EXOSC3, EXOSC8, and RBM7 cause various constellations of pontocerebellar hypoplasia (PCH), spinal muscular atrophy (SMA), and central nervous system demyelination. Here, we report on four unrelated affected individuals with recessive variants in EXOSC9 and the effect of the variants on the function of the RNA exosome in vitro in affected individuals' fibroblasts and skeletal muscle and in vivo in zebrafish. The clinical presentation was severe, early-onset, progressive SMA-like motor neuronopathy, cerebellar atrophy, and in one affected individual, congenital fractures of the long bones. Three affected individuals of different ethnicity carried the homozygous c.41T>C (p.Leu14Pro) variant, whereas one affected individual was compound heterozygous for c.41T>C (p.Leu14Pro) and c.481C>T (p.Arg161). We detected reduced EXOSC9 in fibroblasts and skeletal muscle and observed a reduction of the whole multi-subunit exosome complex on blue-native polyacrylamide gel electrophoresis. RNA sequencing of fibroblasts and skeletal muscle detected significant >2-fold changes in genes involved in neuronal development and cerebellar and motor neuron degeneration, demonstrating the widespread effect of the variants. Morpholino oligonucleotide knockdown and CRISPR/Cas9-mediated mutagenesis of exosc9 in zebrafish recapitulated aspects of the human phenotype, as they have in other zebrafish models of exosomal disease. Specifically, portions of the cerebellum and hindbrain were absent, and motor neurons failed to develop and migrate properly. In summary, we show that variants in EXOSC9 result in a neurological syndrome combining cerebellar atrophy and spinal motoneuronopathy, thus expanding the list of human exosomopathies.
Keywords: Amino Acid Sequence; Animals; Atrophy; Base Sequence; Cerebellum; Child, Preschool; Exosome Multienzyme Ribonuclease Complex; Exosomes; Female; Fibroblasts; Gene Knockdown Techniques; Genetic Variation; Haplotypes; Humans; Infant; Male; Motor Neurons; Muscle, Skeletal; Pedigree; RNA-Binding Proteins; Spinal Cord; Zebrafish

Whole exome sequencing analysis in severe chronic obstructive pulmonary disease. - Qiao, Dandi; Ameli, Asher; Prokopenko, Dmitry; Chen, Han; Kho, Alvin T; Parker, Margaret M; Morrow, Jarrett; Hobbs, Brian D; Liu, Yanhong; Beaty, Terri H; Crapo, James D; Barnes, Kathleen C; et al. (Hum Mol Genet, 2018)
Chronic obstructive pulmonary disease (COPD), one of the leading causes of death worldwide, is substantially influenced by genetic factors. Alpha-1 antitrypsin deficiency demonstrates that rare coding variants of large effect can influence COPD susceptibility. To identify additional rare coding variants in patients with severe COPD, we conducted whole exome sequencing analysis in 2543 subjects from two family-based studies (Boston Early-Onset COPD Study and International COPD Genetics Network) and one case-control study (COPDGene). Applying a gene-based segregation test in the family-based data, we identified significant segregation of rare loss of function variants in TBC1D10A and RFPL1 (P-value < 2x10-6), but were unable to find similar variants in the case-control study. In single-variant, gene-based and pathway association analyses, we were unable to find significant findings that replicated or were significant in meta-analysis. However, we found that the top results in the two datasets were in proximity to each other in the protein-protein interaction network (P-value = 0.014), suggesting enrichment of these results for similar biological processes. A network of these association results and their neighbors was significantly enriched in the transforming growth factor beta-receptor binding and cilia-related pathways. Finally, in a more detailed examination of candidate genes, we identified individuals with putative high-risk variants, including patients harboring homozygous mutations in genes associated with cutis laxa and Niemann-Pick Disease Type C. Our results likely reflect heterogeneity of genetic risk for COPD along with limitations of statistical power and functional annotation, and highlight the potential of network analysis to gain insight into genetic association studies.
Keywords: Adolescent; Adult; Aged; Case-Control Studies; DNA Mutational Analysis; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Mutation; Polymorphism, Single Nucleotide; Pulmonary Disease, Chronic Obstructive; Whole Exome Sequencing; Young Adult

Whole exome sequencing frequently detects a monogenic cause in early onset nephrolithiasis and nephrocalcinosis. - Daga, Ankana; Majmundar, Amar J; Braun, Daniela A; Gee, Heon Yung; Lawson, Jennifer A; Shril, Shirlee; Jobst-Schwan, Tilman; Vivante, Asaf; Schapiro, David; Tan, Weizhen; Warejko, Jillian K; Widmeier, Eugen; et al. (Kidney Int, 2018)
The incidence of nephrolithiasis continues to rise. Previously, we showed that a monogenic cause could be detected in 11.4% of individuals with adult-onset nephrolithiasis or nephrocalcinosis and in 16.7-20.8% of individuals with onset before 18 years of age, using gene panel sequencing of 30 genes known to cause nephrolithiasis/nephrocalcinosis. To overcome the limitations of panel sequencing, we utilized whole exome sequencing in 51 families, who presented before age 25 years with at least one renal stone or with a renal ultrasound finding of nephrocalcinosis to identify the underlying molecular genetic cause of disease. In 15 of 51 families, we detected a monogenic causative mutation by whole exome sequencing. A mutation in seven recessive genes (AGXT, ATP6V1B1, CLDN16, CLDN19, GRHPR, SLC3A1, SLC12A1), in one dominant gene (SLC9A3R1), and in one gene (SLC34A1) with both recessive and dominant inheritance was detected. Seven of the 19 different mutations were not previously described as disease-causing. In one family, a causative mutation in one of 117 genes that may represent phenocopies of nephrolithiasis-causing genes was detected. In nine of 15 families, the genetic diagnosis may have specific implications for stone management and prevention. Several factors that correlated with the higher detection rate in our cohort were younger age at onset of nephrolithiasis/nephrocalcinosis, presence of multiple affected members in a family, and presence of consanguinity. Thus, we established whole exome sequencing as an efficient approach toward a molecular genetic diagnosis in individuals with nephrolithiasis/nephrocalcinosis who manifest before age 25 years.
Keywords: Adolescent; Age of Onset; Child; Child, Preschool; Disease Progression; Female; Genetic Association Studies; Genetic Markers; Genetic Predisposition to Disease; Heredity; Humans; Infant; Male; Mutation; Nephrocalcinosis; Nephrolithiasis; Pedigree; Phenotype; Predictive Value of Tests; Prognosis; Risk Factors; Tomography, X-Ray Computed; Ultrasonography; Whole Exome Sequencing; Young Adult

Whole Exome Sequencing Reveals a Monogenic Cause of Disease in ≈43% of 35 Families With Midaortic Syndrome. - Warejko, Jillian K; Schueler, Markus; Vivante, Asaf; Tan, Weizhen; Daga, Ankana; Lawson, Jennifer A; Braun, Daniela A; Shril, Shirlee; Amann, Kassaundra; Somers, Michael J G; Rodig, Nancy M; Baum, Michelle A; et al. (Hypertension, 2018)
Midaortic syndrome (MAS) is a rare cause of severe childhood hypertension characterized by narrowing of the abdominal aorta in children and is associated with extensive vascular disease. It may occur as part of a genetic syndrome, such as neurofibromatosis, or as consequence of a pathological inflammatory disease. However, most cases are considered idiopathic. We hypothesized that in a high percentage of these patients, a monogenic cause of disease may be detected by evaluating whole exome sequencing data for mutations in 1 of 38 candidate genes previously described to cause vasculopathy. We studied a cohort of 36 individuals from 35 different families with MAS by exome sequencing. In 15 of 35 families (42.9%), we detected likely causal dominant mutations. In 15 of 35 (42.9%) families with MAS, whole exome sequencing revealed a mutation in one of the genes previously associated with vascular disease (, , , , and ). Ten of the 15 mutations have not previously been reported. This is the first report of , , or mutations in individuals with MAS. Mutations were detected in (6/15 families), (4/15 families), (3/15 families), and one family each for and Eight individuals had syndromic disease and 7 individuals had isolated MAS. Whole exome sequencing can provide conclusive molecular genetic diagnosis in a high fraction of individuals with syndromic or isolated MAS. Establishing an etiologic diagnosis may reveal genotype/phenotype correlations for MAS in the future and should, therefore, be performed routinely in MAS.
Keywords: Adolescent; Aorta, Abdominal; Aortic Valve Stenosis; Child; Child, Preschool; Cohort Studies; Female; Genetic Association Studies; Humans; Hypertension; Jagged-1 Protein; Male; Mutation; Neurofibromatoses; Neurofibromin 1; Pedigree; Syndrome; United States; Whole Exome Sequencing

Whole-Exome Sequencing Identifies Novel Variants for Tooth Agenesis. - Dinckan, N; Du, R; Petty, L E; Coban-Akdemir, Z; Jhangiani, S N; Paine, I; Baugh, E H; Erdem, A P; Kayserili, H; Doddapaneni, H; Hu, J; Muzny, D M; et al. (J Dent Res, 2018)
Tooth agenesis is a common craniofacial abnormality in humans and represents failure to develop 1 or more permanent teeth. Tooth agenesis is complex, and variations in about a dozen genes have been reported as contributing to the etiology. Here, we combined whole-exome sequencing, array-based genotyping, and linkage analysis to identify putative pathogenic variants in candidate disease genes for tooth agenesis in 10 multiplex Turkish families. Novel homozygous and heterozygous variants in LRP6, DKK1, LAMA3, and COL17A1 genes, as well as known variants in WNT10A, were identified as likely pathogenic in isolated tooth agenesis. Novel variants in KREMEN1 were identified as likely pathogenic in 2 families with suspected syndromic tooth agenesis. Variants in more than 1 gene were identified segregating with tooth agenesis in 2 families, suggesting oligogenic inheritance. Structural modeling of missense variants suggests deleterious effects to the encoded proteins. Functional analysis of an indel variant (c.3607+3_6del) in LRP6 suggested that the predicted resulting mRNA is subject to nonsense-mediated decay. Our results support a major role for WNT pathways genes in the etiology of tooth agenesis while revealing new candidate genes. Moreover, oligogenic cosegregation was suggestive for complex inheritance and potentially complex gene product interactions during development, contributing to improved understanding of the genetic etiology of familial tooth agenesis.
Keywords: Anodontia; Female; Genetic Linkage; Genetic Variation; Humans; Intercellular Signaling Peptides and Proteins; Laminin; Low Density Lipoprotein Receptor-Related Protein-6; Male; Membrane Proteins; Mutation, Missense; Pedigree; Real-Time Polymerase Chain Reaction; Turkey; Whole Exome Sequencing; Wnt Proteins

WNT Signaling Perturbations Underlie the Genetic Heterogeneity of Robinow Syndrome. - White, Janson J; Mazzeu, Juliana F; Coban-Akdemir, Zeynep; Bayram, Yavuz; Bahrambeigi, Vahid; Hoischen, Alexander; van Bon, Bregje W M; Gezdirici, Alper; Gulec, Elif Yilmaz; Ramond, Francis; Touraine, Renaud; Thevenon, Julien; et al. (Am J Hum Genet, 2018)
Locus heterogeneity characterizes a variety of skeletal dysplasias often due to interacting or overlapping signaling pathways. Robinow syndrome is a skeletal disorder historically refractory to molecular diagnosis, potentially stemming from substantial genetic heterogeneity. All current known pathogenic variants reside in genes within the noncanonical Wnt signaling pathway including ROR2, WNT5A, and more recently, DVL1 and DVL3. However, ∼70% of autosomal-dominant Robinow syndrome cases remain molecularly unsolved. To investigate this missing heritability, we recruited 21 families with at least one family member clinically diagnosed with Robinow or Robinow-like phenotypes and performed genetic and genomic studies. In total, four families with variants in FZD2 were identified as well as three individuals from two families with biallelic variants in NXN that co-segregate with the phenotype. Importantly, both FZD2 and NXN are relevant protein partners in the WNT5A interactome, supporting their role in skeletal development. In addition to confirming that clustered -1 frameshifting variants in DVL1 and DVL3 are the main contributors to dominant Robinow syndrome, we also found likely pathogenic variants in candidate genes GPC4 and RAC3, both linked to the Wnt signaling pathway. These data support an initial hypothesis that Robinow syndrome results from perturbation of the Wnt/PCP pathway, suggest specific relevant domains of the proteins involved, and reveal key contributors in this signaling cascade during human embryonic development. Contrary to the view that non-allelic genetic heterogeneity hampers gene discovery, this study demonstrates the utility of rare disease genomic studies to parse gene function in human developmental pathways.
Keywords: Adolescent; Adult; Base Sequence; Child; Child, Preschool; Chromosome Segregation; Craniofacial Abnormalities; Diagnosis, Differential; Dwarfism; Female; Genes, Dominant; Genetic Association Studies; Genetic Heterogeneity; Humans; Limb Deformities, Congenital; Male; Middle Aged; Mutation, Missense; Phenotype; Urogenital Abnormalities; Wnt Signaling Pathway

22q11.2q13 duplication including SOX10 causes sex-reversal and peripheral demyelinating neuropathy, central dysmyelinating leukodystrophy, Waardenburg syndrome, and Hirschsprung disease. - Falah, Nadia; Posey, Jennifer E; Thorson, Willa; Benke, Paul; Tekin, Mustafa; Tarshish, Brocha; Lupski, James R; Harel, Tamar (Am J Med Genet A, 2017)
Diagnosis of genetic syndromes may be difficult when specific components of a disorder manifest at a later age. We present a follow up of a previous report [Seeherunvong et al., (2004); AJMGA 127: 149-151], of an individual with 22q duplication and sex-reversal syndrome. The subject's phenotype evolved to include peripheral and central demyelination, Waardenburg syndrome type IV, and Hirschsprung disease (PCWH; MIM 609136). DNA microarray analysis defined the duplication at 22q11.2q13, including SOX10. Sequencing of the coding region of SOX10 did not reveal any mutations. Our data suggest that SOX10 duplication can cause disorders of sex development and PCWH, supporting the hypothesis that SOX10 toxic gain of function rather than dominant negative activity underlies PCWH.
Keywords: 46, XX Testicular Disorders of Sex Development; African Americans; Chromosome Duplication; Chromosomes, Human, Pair 22; Demyelinating Diseases; Hirschsprung Disease; Humans; Kidney Failure, Chronic; Male; Pelizaeus-Merzbacher Disease; SOXE Transcription Factors; Waardenburg Syndrome

Activation of a cryptic splice site in the mitochondrial elongation factor GFM1 causes combined OXPHOS deficiency. - Simon, Mariella T; Ng, Bobby G; Friederich, Marisa W; Wang, Raymond Y; Boyer, Monica; Kircher, Martin; Collard, Renata; Buckingham, Kati J; Chang, Richard; Shendure, Jay; Nickerson, Deborah A; Bamshad, Michael J; et al. (Mitochondrion, 2017)
We report the clinical, biochemical, and molecular findings in two brothers with encephalopathy and multi-systemic disease. Abnormal transferrin glycoforms were suggestive of a type I congenital disorder of glycosylation (CDG). While exome sequencing was negative for CDG related candidate genes, the testing revealed compound heterozygous mutations in the mitochondrial elongation factor G gene (GFM1). One of the mutations had been reported previously while the second, novel variant was found deep in intron 6, activating a cryptic splice site. Functional studies demonstrated decreased GFM1 protein levels, suggested disrupted assembly of mitochondrial complexes III and V and decreased activities of mitochondrial complexes I and IV, all indicating combined OXPHOS deficiency.
Keywords: Child; Child, Preschool; Congenital Abnormalities; Gene Expression; Humans; Infant; Infant, Newborn; Male; Mitochondrial Proteins; Oxidative Phosphorylation; Peptide Elongation Factor G; RNA Splice Sites

Advillin acts upstream of phospholipase C ϵ1 in steroid-resistant nephrotic syndrome. - Rao, Jia; Ashraf, Shazia; Tan, Weizhen; van der Ven, Amelie T; Gee, Heon Yung; Braun, Daniela A; Fehér, Krisztina; George, Sudeep P; Esmaeilniakooshkghazi, Amin; Choi, Won-Il; Jobst-Schwan, Tilman; Schneider, Ronen; et al. (J Clin Invest, 2017)
Steroid-resistant nephrotic syndrome (SRNS) is a frequent cause of chronic kidney disease. Here, we identified recessive mutations in the gene encoding the actin-binding protein advillin (AVIL) in 3 unrelated families with SRNS. While all AVIL mutations resulted in a marked loss of its actin-bundling ability, truncation of AVIL also disrupted colocalization with F-actin, thereby leading to impaired actin binding and severing. Additionally, AVIL colocalized and interacted with the phospholipase enzyme PLCE1 and with the ARP2/3 actin-modulating complex. Knockdown of AVIL in human podocytes reduced actin stress fibers at the cell periphery, prevented recruitment of PLCE1 to the ARP3-rich lamellipodia, blocked EGF-induced generation of diacylglycerol (DAG) by PLCE1, and attenuated the podocyte migration rate (PMR). These effects were reversed by overexpression of WT AVIL but not by overexpression of any of the 3 patient-derived AVIL mutants. The PMR was increased by overexpression of WT Avil or PLCE1, or by EGF stimulation; however, this increased PMR was ameliorated by inhibition of the ARP2/3 complex, indicating that ARP-dependent lamellipodia formation occurs downstream of AVIL and PLCE1 function. Together, these results delineate a comprehensive pathogenic axis of SRNS that integrates loss of AVIL function with alterations in the action of PLCE1, an established SRNS protein.
Keywords: Actin-Related Protein 2-3 Complex; Cell Movement; Diglycerides; Female; Humans; Male; Microfilament Proteins; Mutation; Nephrotic Syndrome; Phosphoinositide Phospholipase C; Podocytes; Pseudopodia

Asprosin is a centrally acting orexigenic hormone. - Duerrschmid, Clemens; He, Yanlin; Wang, Chunmei; Li, Chia; Bournat, Juan C; Romere, Chase; Saha, Pradip K; Lee, Mark E; Phillips, Kevin J; Jain, Mahim; Jia, Peilin; Zhao, Zhongming; et al. (Nat Med, 2017)
Asprosin is a recently discovered fasting-induced hormone that promotes hepatic glucose production. Here we demonstrate that asprosin in the circulation crosses the blood-brain barrier and directly activates orexigenic AgRP neurons via a cAMP-dependent pathway. This signaling results in inhibition of downstream anorexigenic proopiomelanocortin (POMC)-positive neurons in a GABA-dependent manner, which then leads to appetite stimulation and a drive to accumulate adiposity and body weight. In humans, a genetic deficiency in asprosin causes a syndrome characterized by low appetite and extreme leanness; this is phenocopied by mice carrying similar mutations and can be fully rescued by asprosin. Furthermore, we found that obese humans and mice had pathologically elevated concentrations of circulating asprosin, and neutralization of asprosin in the blood with a monoclonal antibody reduced appetite and body weight in obese mice, in addition to improving their glycemic profile. Thus, in addition to performing a glucogenic function, asprosin is a centrally acting orexigenic hormone that is a potential therapeutic target in the treatment of both obesity and diabetes.
Keywords: Adolescent; Adult; Animals; Appetite Depressants; Appetite Regulation; Female; Humans; Hypothalamus; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Microfilament Proteins; Neurons; Peptide Fragments; Peptide Hormones; Rats; Signal Transduction; Young Adult

Biallelic mutations in IRF8 impair human NK cell maturation and function. - Mace, Emily M; Bigley, Venetia; Gunesch, Justin T; Chinn, Ivan K; Angelo, Laura S; Care, Matthew A; Maisuria, Sheetal; Keller, Michael D; Togi, Sumihito; Watkin, Levi B; LaRosa, David F; Jhangiani, Shalini N; et al. (J Clin Invest, 2017)
Human NK cell deficiencies are rare yet result in severe and often fatal disease, particularly as a result of viral susceptibility. NK cells develop from hematopoietic stem cells, and few monogenic errors that specifically interrupt NK cell development have been reported. Here we have described biallelic mutations in IRF8, which encodes an interferon regulatory factor, as a cause of familial NK cell deficiency that results in fatal and severe viral disease. Compound heterozygous or homozygous mutations in IRF8 in 3 unrelated families resulted in a paucity of mature CD56dim NK cells and an increase in the frequency of the immature CD56bright NK cells, and this impairment in terminal maturation was also observed in Irf8-/-, but not Irf8+/-, mice. We then determined that impaired maturation was NK cell intrinsic, and gene expression analysis of human NK cell developmental subsets showed that multiple genes were dysregulated by IRF8 mutation. The phenotype was accompanied by deficient NK cell function and was stable over time. Together, these data indicate that human NK cells require IRF8 for development and functional maturation and that dysregulation of this function results in severe human disease, thereby emphasizing a critical role for NK cells in human antiviral defense.
Keywords: Alleles; Animals; CD56 Antigen; Female; Gene Expression Regulation; Genetic Predisposition to Disease; Humans; Interferon Regulatory Factors; Killer Cells, Natural; Male; Mice; Mice, Knockout; Mutation; Virus Diseases

Biallelic mutations in the 3' exonuclease TOE1 cause pontocerebellar hypoplasia and uncover a role in snRNA processing. - Lardelli, Rea M; Schaffer, Ashleigh E; Eggens, Veerle R C; Zaki, Maha S; Grainger, Stephanie; Sathe, Shashank; Van Nostrand, Eric L; Schlachetzki, Zinayida; Rosti, Basak; Akizu, Naiara; Scott, Eric; Silhavy, Jennifer L; et al. (Nat Genet, 2017)
Deadenylases are best known for degrading the poly(A) tail during mRNA decay. The deadenylase family has expanded throughout evolution and, in mammals, consists of 12 Mg-dependent 3'-end RNases with substrate specificity that is mostly unknown. Pontocerebellar hypoplasia type 7 (PCH7) is a unique recessive syndrome characterized by neurodegeneration and ambiguous genitalia. We studied 12 human families with PCH7, uncovering biallelic, loss-of-function mutations in TOE1, which encodes an unconventional deadenylase. toe1-morphant zebrafish displayed midbrain and hindbrain degeneration, modeling PCH-like structural defects in vivo. Surprisingly, we found that TOE1 associated with small nuclear RNAs (snRNAs) incompletely processed spliceosomal. These pre-snRNAs contained 3' genome-encoded tails often followed by post-transcriptionally added adenosines. Human cells with reduced levels of TOE1 accumulated 3'-end-extended pre-snRNAs, and the immunoisolated TOE1 complex was sufficient for 3'-end maturation of snRNAs. Our findings identify the cause of a neurodegenerative syndrome linked to snRNA maturation and uncover a key factor involved in the processing of snRNA 3' ends.
Keywords: Alleles; Animals; Cerebellar Diseases; Exonucleases; Female; Humans; Male; Mice; Mutation; Neurodegenerative Diseases; Nuclear Proteins; RNA, Messenger; RNA, Small Nuclear; Spliceosomes; Zebrafish

Choices for return of primary and secondary genomic research results of 790 members of families with Mendelian disease. - Fiallos, Katie; Applegate, Carolyn; Mathews, Debra Jh; Bollinger, Juli; Bergner, Amanda L; James, Cynthia A (Eur J Hum Genet, 2017)
Although consensus is building that primary (PR) and secondary findings (SF) from genomic research should be offered to participants under some circumstances, data describing (1) actual choices of study participants and (2) factors associated with these choices are limited, hampering study planning. We conducted a cross-sectional analysis of choices made for return of PR and SF during informed consent by members of the first 247 families (790 individuals) enrolled in the Baylor-Hopkins Center for Mendelian Genomics, a genome sequencing study. Most (619; 78.3%) chose to receive SF and PR, 66 (8.4%) chose PR only, 65 (8.2%) wanted no results, and 40 (5.1%) chose SF only. Choosing SF was associated with an established clinical diagnosis in the proband (87.8 vs 79%, P=0.009) and European ancestry (EA) (87.7 vs 73%, P<0.008). Participants of non-European ancestry (NEA) were as likely as those of EA to choose SF when consented by a genetic counselor (GC) (82% NEA vs 88.3% EA, P=0.09) but significantly less likely when consented by a physician (67.4% NEA vs 85.4% EA, P=0.001). Controlling for proband diagnosis, individuals of NEA were 2.13-fold (95% CI: 1.11-4.08) more likely to choose SF when consented by a GC rather than a physician. Participants of NEA were 3-fold more likely than those of EA to decline all study results (14.7% NEA vs 5.4% EA, P<0.008). In this ethnically diverse population, whereas most participants desired PR and SF, more than 20% declined some or all results, highlighting the importance of research participant choice.
Keywords: Databases, Genetic; Female; Genetic Diseases, Inborn; Genome, Human; Genome-Wide Association Study; Humans; Male; Pedigree; Research Subjects

Clinical report: A patient with a late diagnosis of cerebrotendinous xanthomatosis and a response to treatment. - Alhariri, Ahmad; Hamilton, Katherine; Oza, Vikash; Cordoro, Kelly; Sobreira, Nara L; Malloy, Mary; Slavotinek, Anne (Am J Med Genet A, 2017)
Cerebrotendinous xanthomatosis (CTX) is a rare, autosomal recessive, inborn error of bile acid metabolism characterized by diarrhea in infancy, juvenile cataracts in childhood, tendon xanthomas developing in the second to third decades of life, and progressive neurologic dysfunction in adulthood. The condition is caused by mutations in the CYP27A1 gene that result in decreased production of chenodeoxycholic acid (CDCA) and elevated levels of cholestanol and bile alcohols. We present a 36-year-old male of Han ethnicity who developed xanthomas of his Achilles tendons and suffered neurocognitive declines and gait deterioration in his second decade. The diagnosis of CTX was confirmed by marked elevation of the serum cholestanol level. Sequencing of CYP27A1 showed a paternally inherited splice mutation, c.446 + 1G>T, and a maternally inherited nonsense mutation, c.808C>T, predicting p.(Arg270*). Despite the advanced disease in this patient, treatment with CDCA reduced the xanthoma size and improved his cognition and strength, and the patient made significant gains in his ambulation and coordination. We report this case to illustrate the potential benefits of therapy in patients with CTX who have advanced disease at the time of diagnosis.
Keywords: Achilles Tendon; Adult; Bile Acids and Salts; Chenodeoxycholic Acid; Cholestanetriol 26-Monooxygenase; Cholestanol; Codon, Nonsense; Humans; Male; Xanthomatosis, Cerebrotendinous

Clinically severe CACNA1A alleles affect synaptic function and neurodegeneration differentially. - Luo, Xi; Rosenfeld, Jill A; Yamamoto, Shinya; Harel, Tamar; Zuo, Zhongyuan; Hall, Melissa; Wierenga, Klaas J; Pastore, Matthew T; Bartholomew, Dennis; Delgado, Mauricio R; Rotenberg, Joshua; Lewis, Richard Alan; et al. (PLoS Genet, 2017)
Dominant mutations in CACNA1A, encoding the α-1A subunit of the neuronal P/Q type voltage-dependent Ca2+ channel, can cause diverse neurological phenotypes. Rare cases of markedly severe early onset developmental delay and congenital ataxia can be due to de novo CACNA1A missense alleles, with variants affecting the S4 transmembrane segments of the channel, some of which are reported to be loss-of-function. Exome sequencing in five individuals with severe early onset ataxia identified one novel variant (p.R1673P), in a girl with global developmental delay and progressive cerebellar atrophy, and a recurrent, de novo p.R1664Q variant, in four individuals with global developmental delay, hypotonia, and ophthalmologic abnormalities. Given the severity of these phenotypes we explored their functional impact in Drosophila. We previously generated null and partial loss-of-function alleles of cac, the homolog of CACNA1A in Drosophila. Here, we created transgenic wild type and mutant genomic rescue constructs with the two noted conserved point mutations. The p.R1673P mutant failed to rescue cac lethality, displayed a gain-of-function phenotype in electroretinograms (ERG) recorded from mutant clones, and evolved a neurodegenerative phenotype in aging flies, based on ERGs and transmission electron microscopy. In contrast, the p.R1664Q variant exhibited loss of function and failed to develop a neurodegenerative phenotype. Hence, the novel R1673P allele produces neurodegenerative phenotypes in flies and human, likely due to a toxic gain of function.
Keywords: Alleles; Animals; Animals, Genetically Modified; Calcium Channels; Cerebellar Ataxia; Child; Child, Preschool; Drosophila melanogaster; Female; Genome, Human; Genome-Wide Association Study; Humans; Male; Microscopy, Electron, Transmission; Mutation, Missense; Neurodegenerative Diseases; Neuroimaging; Phenotype; Point Mutation

Complex phenotypes associated with STIM1 mutations in both coiled coil and EF-hand domains. - Harris, Elizabeth; Burki, Umar; Marini-Bettolo, Chiara; Neri, Marcella; Scotton, Chiara; Hudson, Judith; Bertoli, Marta; Evangelista, Teresinha; Vroling, Bas; Polvikoski, Tuomo; Roberts, Mark; Topf, Ana; et al. (Neuromuscul Disord, 2017)
Dominant mutations in STIM1 are a cause of three allelic conditions: tubular aggregate myopathy, Stormorken syndrome (a complex phenotype including myopathy, hyposplenism, hypocalcaemia and bleeding diathesis), and a platelet dysfunction disorder, York platelet syndrome. Previous reports have suggested a genotype-phenotype correlation with mutations in the N-terminal EF-hand domain associated with tubular aggregate myopathy, and a common mutation at p.R304W in a coiled coil domain associated with Stormorken syndrome. In this study individuals with STIM1 variants were identified by exome sequencing or STIM1 direct sequencing, and assessed for neuromuscular, haematological and biochemical evidence of the allelic disorders of STIM1. STIM1 mutations were investigated by fibroblast calcium imaging and 3D modelling. Six individuals with STIM1 mutations, including two novel mutations (c.262A>G (p.S88G) and c.911G>A (p.R304Q)), were identified. Extra-neuromuscular symptoms including thrombocytopenia, platelet dysfunction, hypocalcaemia or hyposplenism were present in 5/6 patients with mutations in both the EF-hand and CC domains. 3/6 patients had psychiatric disorders, not previously reported in STIM1 disease. Review of published STIM1 patients (n = 49) confirmed that neuromuscular symptoms are present in most patients. We conclude that the phenotype associated with activating STIM1 mutations frequently includes extra-neuromuscular features such as hypocalcaemia, hypo-/asplenia and platelet dysfunction regardless of mutation domain.
Keywords: Adult; Blood Platelet Disorders; Calcium; Cell Culture Techniques; DNA Mutational Analysis; Dyslexia; Erythrocytes, Abnormal; Family Health; Female; Fibroblasts; Genetic Association Studies; Humans; Ichthyosis; Magnetic Resonance Imaging; Male; Microscopy, Electron; Middle Aged; Migraine Disorders; Miosis; Models, Molecular; Muscle Fatigue; Muscle, Skeletal; Mutation; Myopathies, Structural, Congenital; NAD; Neoplasm Proteins; Spleen; Stromal Interaction Molecule 1

Congenital heart defects and left ventricular non-compaction in males with loss-of-function variants in NONO. - Scott, Daryl A; Hernandez-Garcia, Andres; Azamian, Mahshid S; Jordan, Valerie K; Kim, Bum Jun; Starkovich, Molly; Zhang, Jinglan; Wong, Lee-Jun; Darilek, Sandra A; Breman, Amy M; Yang, Yaping; Lupski, James R; et al. (J Med Genet, 2017)
BACKGROUND: The non-POU domain containing octamer-binding gene (NONO) is located on chromosome Xq13.1 and encodes a member of a small family of RNA-binding and DNA-binding proteins that perform a variety of tasks involved in RNA synthesis, transcriptional regulation and DNA repair. Loss-of-function variants in NONO have been described as a cause of intellectual disability in males but have not been described in association with congenital heart defects or cardiomyopathy. In this article, we seek to further define the phenotypic consequences of NONO depletion in human subjects. METHODS: We searched a clinical database of over 6000 individuals referred for exome sequencing and over 60 000 individuals referred for CNV analysis. RESULTS: We identified two males with atrial and ventricular septal defects, left ventricular non-compaction (LVNC), developmental delay and intellectual disability, who harboured de novo, loss-of-function variants in NONO. We also identified a male infant with developmental delay, congenital brain anomalies and severe LVNC requiring cardiac transplantation, who inherited a single-gene deletion of NONO from his asymptomatic mother. CONCLUSIONS: We conclude that in addition to global developmental delay and intellectual disability, males with loss-of-function variants in NONO may also be predisposed to developing congenital heart defects and LVNC with the penetrance of these cardiac-related problems being influenced by genetic, epigenetic, environmental or stochastic factors. Brain imaging of males with NONO deficiency may reveal structural defects with abnormalities of the corpus callosum being the most common. Although dysmorphic features vary between affected individuals, relative macrocephaly is a common feature.
Keywords: Child; Child, Preschool; Developmental Disabilities; DNA-Binding Proteins; Exome; Heart Defects, Congenital; Heart Ventricles; Humans; Infant; Male; Nuclear Matrix-Associated Proteins; Octamer Transcription Factors; RNA-Binding Proteins

Contribution of rare inherited and de novo variants in 2,871 congenital heart disease probands. - Jin, Sheng Chih; Homsy, Jason; Zaidi, Samir; Lu, Qiongshi; Morton, Sarah; DePalma, Steven R; Zeng, Xue; Qi, Hongjian; Chang, Weni; Sierant, Michael C; Hung, Wei-Chien; Haider, Shozeb; et al. (Nat Genet, 2017)
Congenital heart disease (CHD) is the leading cause of mortality from birth defects. Here, exome sequencing of a single cohort of 2,871 CHD probands, including 2,645 parent-offspring trios, implicated rare inherited mutations in 1.8%, including a recessive founder mutation in GDF1 accounting for ∼5% of severe CHD in Ashkenazim, recessive genotypes in MYH6 accounting for ∼11% of Shone complex, and dominant FLT4 mutations accounting for 2.3% of Tetralogy of Fallot. De novo mutations (DNMs) accounted for 8% of cases, including ∼3% of isolated CHD patients and ∼28% with both neurodevelopmental and extra-cardiac congenital anomalies. Seven genes surpassed thresholds for genome-wide significance, and 12 genes not previously implicated in CHD had >70% probability of being disease related. DNMs in ∼440 genes were inferred to contribute to CHD. Striking overlap between genes with damaging DNMs in probands with CHD and autism was also found.
Keywords: Adult; Autistic Disorder; Cardiac Myosins; Case-Control Studies; Child; Exome; Female; Gene Expression; Genetic Predisposition to Disease; Genome-Wide Association Study; Growth Differentiation Factor 1; Heart Defects, Congenital; Heterozygote; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Male; Mutation; Myosin Heavy Chains; Pedigree; Risk; Vascular Endothelial Growth Factor Receptor-3

Copy Number Changes Identified Using Whole Exome Sequencing in Nonsyndromic Cleft Lip and Palate in a Honduran Population. - Cai, Yi; Patterson, Karynne E; Reinier, Frederic; Keesecker, Sarah E; Blue, Elizabeth; Bamshad, Michael; Haddad, Joseph (Birth Defects Res, 2017)
BACKGROUND: The majority of cleft lip with or without cleft palate cases appear as an isolated, nonsyndromic entity (NSCLP). With the advent of next generation sequencing, whole exome sequencing (WES) has been used to identify single nucleotide variants and insertion/deletions which cause or increase the risk of NSCLP. However, to our knowledge, there are no published studies using WES in NSCLP to investigate copy number changes (CNCs), which are a major component of human genetic variation. Our study aimed to identify CNCs associated with NSCLP in a Honduran population using WES. METHODS: WES was performed on two to four members of 27 multiplex Honduran families. CNCs were identified using two algorithms, CoNIFER and XHMM. Priority was given to CNCs that were identified in more than one patient and had variant frequencies of less than 5% in reference data sets. RESULTS: WES completion was defined as >90% of the WES target at >8 × coverage and >80% of the WES target at >20 × coverage. Twenty-four CNCs that met our inclusion criteria were identified by both CoNIFER and XHMM. These CNCs were confirmed using quantitative PCR. Pedigree analysis produced three CNCs corresponding to ADH7, AHR, and CRYZ segregating with NSCLP. Two of the three CNCs implicate genes, AHR and ADH7, whose known biological functions could plausibly play a role in NSCLP. CONCLUSION: WES can be used to detect candidate CNCs that may be involved in the pathophysiology of NSCLP. Birth Defects Research 109:1257-1267, 2017. © 2017 Wiley Periodicals, Inc.
Keywords: Adolescent; Adult; Alcohol Dehydrogenase; Alleles; Basic Helix-Loop-Helix Transcription Factors; Child; Child, Preschool; Cleft Lip; Cleft Palate; DNA Copy Number Variations; Family; Female; Gene Frequency; Genetic Variation; High-Throughput Nucleotide Sequencing; Honduras; Humans; Male; Middle Aged; Pedigree; Polymorphism, Single Nucleotide; Receptors, Aryl Hydrocarbon; Whole Exome Sequencing

Corner fracture type spondylometaphyseal dysplasia: Overlap with type II collagenopathies. - Machol, Keren; Jain, Mahim; Almannai, Mohammed; Orand, Thibault; Lu, James T; Tran, Alyssa; Chen, Yuqing; Schlesinger, Alan; Gibbs, Richard; Bonafe, Luisa; Campos-Xavier, Ana Belinda; Unger, Sheila; et al. (Am J Med Genet A, 2017)
Spondylometaphyseal dysplasia (SMD) corner fracture type (also known as SMD "Sutcliffe" type, MIM 184255) is a rare skeletal dysplasia that presents with mild to moderate short stature, developmental coxa vara, mild platyspondyly, corner fracture-like lesions, and metaphyseal abnormalities with sparing of the epiphyses. The molecular basis for this disorder has yet to be clarified. We describe two patients with SMD corner fracture type and heterozygous pathogenic variants in COL2A1. These two cases together with a third case of SMD corner fracture type with a heterozygous COL2A1 pathogenic variant previously described suggest that this disorder overlaps with type II collagenopathies. The finding of one of the pathogenic variants in a previously reported case of spondyloepimetaphyseal dysplasia (SEMD) Strudwick type and the significant clinical similarity suggest an overlap between SMD corner fracture and SEMD Strudwick types. © 2016 Wiley Periodicals, Inc.
Keywords: Alleles; Amino Acid Substitution; Bone Diseases, Developmental; Child, Preschool; Collagen Type II; Diagnosis, Differential; Exome; Genetic Association Studies; Genotype; Growth Disorders; High-Throughput Nucleotide Sequencing; Hip Joint; Humans; Infant; Male; Mutation; Osteochondrodysplasias; Phenotype; Radiography; Tibial Fractures

De Novo Disruption of the Proteasome Regulatory Subunit PSMD12 Causes a Syndromic Neurodevelopmental Disorder. - Küry, Sébastien; Besnard, Thomas; Ebstein, Frédéric; Khan, Tahir N; Gambin, Tomasz; Douglas, Jessica; Bacino, Carlos A; Craigen, William J; Sanders, Stephan J; Lehmann, Andrea; Latypova, Xénia; Khan, Kamal; et al. (Am J Hum Genet, 2017)
Degradation of proteins by the ubiquitin-proteasome system (UPS) is an essential biological process in the development of eukaryotic organisms. Dysregulation of this mechanism leads to numerous human neurodegenerative or neurodevelopmental disorders. Through a multi-center collaboration, we identified six de novo genomic deletions and four de novo point mutations involving PSMD12, encoding the non-ATPase subunit PSMD12 (aka RPN5) of the 19S regulator of 26S proteasome complex, in unrelated individuals with intellectual disability, congenital malformations, ophthalmologic anomalies, feeding difficulties, deafness, and subtle dysmorphic facial features. We observed reduced PSMD12 levels and an accumulation of ubiquitinated proteins without any impairment of proteasome catalytic activity. Our PSMD12 loss-of-function zebrafish CRISPR/Cas9 model exhibited microcephaly, decreased convolution of the renal tubules, and abnormal craniofacial morphology. Our data support the biological importance of PSMD12 as a scaffolding subunit in proteasome function during development and neurogenesis in particular; they enable the definition of a neurodevelopmental disorder due to PSMD12 variants, expanding the phenotypic spectrum of UPS-dependent disorders.
Keywords: Adolescent; Animals; Child; Child, Preschool; Disease Models, Animal; DNA Copy Number Variations; Down-Regulation; Female; Gene Deletion; Humans; Infant; Intellectual Disability; Male; Microcephaly; Neurodevelopmental Disorders; Polymorphism, Single Nucleotide; Proteasome Endopeptidase Complex; Zebrafish

De Novo Missense Mutations in DHX30 Impair Global Translation and Cause a Neurodevelopmental Disorder. - Lessel, Davor; Schob, Claudia; Küry, Sébastien; Reijnders, Margot R F; Harel, Tamar; Eldomery, Mohammad K; Coban-Akdemir, Zeynep; Denecke, Jonas; Edvardson, Shimon; Colin, Estelle; Stegmann, Alexander P A; Gerkes, Erica H; et al. (Am J Hum Genet, 2017)
DHX30 is a member of the family of DExH-box helicases, which use ATP hydrolysis to unwind RNA secondary structures. Here we identified six different de novo missense mutations in DHX30 in twelve unrelated individuals affected by global developmental delay (GDD), intellectual disability (ID), severe speech impairment and gait abnormalities. While four mutations are recurrent, two are unique with one affecting the codon of one recurrent mutation. All amino acid changes are located within highly conserved helicase motifs and were found to either impair ATPase activity or RNA recognition in different in vitro assays. Moreover, protein variants exhibit an increased propensity to trigger stress granule (SG) formation resulting in global translation inhibition. Thus, our findings highlight the prominent role of translation control in development and function of the central nervous system and also provide molecular insight into how DHX30 dysfunction might cause a neurodevelopmental disorder.
Keywords: Adenosine Triphosphatases; Adolescent; Amino Acids; Cell Line; Cell Line, Tumor; Central Nervous System; Child; Child, Preschool; Developmental Disabilities; Female; HEK293 Cells; Humans; Intellectual Disability; Male; Mutation, Missense; RNA; RNA Helicases

De novo mutations in HNRNPU result in a neurodevelopmental syndrome. - Yates, T Michael; Vasudevan, Pradeep C; Chandler, Kate E; Donnelly, Deirdre E; Stark, Zornitza; Sadedin, Simon; Willoughby, Josh; Balasubramanian, Meena (Am J Med Genet A, 2017)
Exome sequencing in the context of developmental disorders is a useful technique, but variants found need to be interpreted in the context of detailed phenotypic information. Whole gene deletions and loss-of-function-mutations in the HNRNPU gene have been associated with intellectual disability and seizures in some patients. However, a unifying syndromic phenotype has not been previously elucidated. Here, we report a total of seven patients (six patients identified through the Wellcome Trust Deciphering Developmental Disorders study, with one additional patient), who have heterozygous de novo mutations in HNRNPU. These were found via trio-based exome sequencing. All but one of the mutations is predicted to cause loss-of-function. These patients have dysmorphic features in common, including prominent eyebrows, long palpebral fissures, overhanging columella, and thin upper lip. All patients have developmental delay and intellectual disability (ID), ranging from moderate to severe. Seizures are common from early childhood. These initially occur in the context of febrile episodes. This series demonstrates common phenotypic features, including emerging dysmorphism, associated with heterozygous HNRNPU mutations. This allows us to define a novel neurodevelopmental syndrome, with a likely mechanism of haploinsufficiency.
Keywords: Adolescent; Adult; Child; Child, Preschool; Developmental Disabilities; Exome; Female; Genetic Predisposition to Disease; Haploinsufficiency; Heterogeneous-Nuclear Ribonucleoprotein U; Heterozygote; Humans; Infant; Intellectual Disability; Male; Mutation; Neurodevelopmental Disorders; Phenotype; Seizures; Young Adult

De novo mutations in inhibitors of Wnt, BMP, and Ras/ERK signaling pathways in non-syndromic midline craniosynostosis. - Timberlake, Andrew T; Furey, Charuta G; Choi, Jungmin; Nelson-Williams, Carol; Loring, Erin; Galm, Amy; Kahle, Kristopher T; Steinbacher, Derek M; Larysz, Dawid; Persing, John A; Lifton, Richard P (Proc Natl Acad Sci U S A, 2017)
Non-syndromic craniosynostosis (NSC) is a frequent congenital malformation in which one or more cranial sutures fuse prematurely. Mutations causing rare syndromic craniosynostoses in humans and engineered mouse models commonly increase signaling of the Wnt, bone morphogenetic protein (BMP), or Ras/ERK pathways, converging on shared nuclear targets that promote bone formation. In contrast, the genetics of NSC is largely unexplored. More than 95% of NSC is sporadic, suggesting a role for de novo mutations. Exome sequencing of 291 parent-offspring trios with midline NSC revealed 15 probands with heterozygous damaging de novo mutations in 12 negative regulators of Wnt, BMP, and Ras/ERK signaling (10.9-fold enrichment, = 2.4 × 10). had 4 de novo and 14 transmitted mutations; no other gene had more than 1. Four familial NSC kindreds had mutations in genes previously implicated in syndromic disease. Collectively, these mutations contribute to 10% of probands. Mutations are predominantly loss-of-function, implicating haploinsufficiency as a frequent mechanism. A common risk variant near increased the penetrance of mutations and was overtransmitted to patients with de novo mutations in other genes in these pathways, supporting a frequent two-locus pathogenesis. These findings implicate new genes in NSC and demonstrate related pathophysiology of common non-syndromic and rare syndromic craniosynostoses. These findings have implications for diagnosis, risk of recurrence, and risk of adverse neurodevelopmental outcomes. Finally, the use of pathways identified in rare syndromic disease to find genes accounting for non-syndromic cases may prove broadly relevant to understanding other congenital disorders featuring high locus heterogeneity.
Keywords: Adult; Animals; Bone Morphogenetic Proteins; Child; Child, Preschool; Cranial Sutures; Craniosynostoses; Exome; Female; Humans; Male; MAP Kinase Signaling System; Mutation; Osteogenesis; Penetrance; Phenotype; ras Proteins; Sequence Analysis, DNA; Signal Transduction; Smad6 Protein; Whole Exome Sequencing

A defect in myoblast fusion underlies Carey-Fineman-Ziter syndrome. - Di Gioia, Silvio Alessandro; Connors, Samantha; Matsunami, Norisada; Cannavino, Jessica; Rose, Matthew F; Gilette, Nicole M; Artoni, Pietro; de Macena Sobreira, Nara Lygia; Chan, Wai-Man; Webb, Bryn D; Robson, Caroline D; Cheng, Long; et al. (Nat Commun, 2017)
Multinucleate cellular syncytial formation is a hallmark of skeletal muscle differentiation. Myomaker, encoded by Mymk (Tmem8c), is a well-conserved plasma membrane protein required for myoblast fusion to form multinucleated myotubes in mouse, chick, and zebrafish. Here, we report that autosomal recessive mutations in MYMK (OMIM 615345) cause Carey-Fineman-Ziter syndrome in humans (CFZS; OMIM 254940) by reducing but not eliminating MYMK function. We characterize MYMK-CFZS as a congenital myopathy with marked facial weakness and additional clinical and pathologic features that distinguish it from other congenital neuromuscular syndromes. We show that a heterologous cell fusion assay in vitro and allelic complementation experiments in mymk knockdown and mymk zebrafish in vivo can differentiate between MYMK wild type, hypomorphic and null alleles. Collectively, these data establish that MYMK activity is necessary for normal muscle development and maintenance in humans, and expand the spectrum of congenital myopathies to include cell-cell fusion deficits.
Keywords: Adult; Amino Acid Sequence; Animals; Cell Fusion; Child; Disease Models, Animal; Embryo, Nonmammalian; Female; Gene Expression; Genes, Recessive; Genetic Complementation Test; Humans; Infant; Male; Membrane Proteins; Mobius Syndrome; Morphogenesis; Muscle Proteins; Muscle, Skeletal; Muscular Diseases; Mutation; Myoblasts; Pedigree; Pierre Robin Syndrome; Sequence Alignment; Sequence Homology, Amino Acid; Zebrafish; Zebrafish Proteins

Diagnosis of Chronic Intestinal Pseudo-obstruction and Megacystis by Sequencing the ACTG2 Gene. - Milunsky, Aubrey; Baldwin, Clinton; Zhang, Xiaoying; Primack, Daniel; Curnow, Adrian; Milunsky, Jeff (J Pediatr Gastroenterol Nutr, 2017)
OBJECTIVES: The diagnosis of chronic intestinal pseudo-obstruction has depended on clinical features, manometry, and imaging. This report aimed to determine the efficacy of sequencing the actin γ-2 (ACTG2) gene for diagnosis. In addition, the goal was to determine how often a mutation would be found in our randomly collected cohort of probands and those probands published previously. METHODS: Whole exome sequencing was performed in 4 probands with chronic intestinal pseudo-obstruction. Subsequently, only the ACTG2 gene was sequenced in another 24 probands (total 28). We analyzed published data of 83 probands and our 28 (total 111) and determined how many had pathogenic variants and the precise genotype. RESULTS: Whole exome and Sanger sequencing revealed a pathogenic variant in the ACTG2 gene in 4 out of 28 of our probands and in 45 out of 83 published probands (49/111 [44.1%]). Moreover, a mutational hotspot in the ACTG2 gene was recognized. Genetic heterogeneity is evident. CONCLUSIONS: Pooled gene sequencing results from 1 individual in each of 111 families enabled a precise diagnosis of an ACTG2 mutation in 49 (44%). The benefit to patients and families of early confirmation of a motility disorder not only helps avoid unnecessary intervention, but also enables institution of appropriate treatments and avoidance of secondary disorders such as malnutrition and poor growth. Knowledge of a pathogenic variant in a parent, with a 50% risk of recurrence, provides an opportunity for genetic counseling.
Keywords: Actins; Adult; Child; Child, Preschool; Chronic Disease; Duodenum; Female; Fetal Diseases; Genetic Markers; Genetic Testing; Humans; Infant; Infant, Newborn; Intestinal Pseudo-Obstruction; Male; Mutation; Sequence Analysis, DNA; Urinary Bladder; Whole Exome Sequencing

Disruptions in asymmetric centrosome inheritance and WDR62-Aurora kinase B interactions in primary microcephaly. - Sgourdou, Paraskevi; Mishra-Gorur, Ketu; Saotome, Ichiko; Henagariu, Octavian; Tuysuz, Beyhan; Campos, Cynthia; Ishigame, Keiko; Giannikou, Krinio; Quon, Jennifer L; Šestan, Nenad; Çağlayan, Ahmet O; Günel, Murat; et al. (Sci Rep, 2017)
Recessive mutations in WD repeat domain 62 (WDR62) cause microcephaly and a wide spectrum of severe brain malformations. Disruption of the mouse ortholog results in microcephaly underlain by reduced proliferation of neocortical progenitors during late neurogenesis, abnormalities in asymmetric centrosome inheritance leading to neuronal migration delays, and altered neuronal differentiation. Spindle pole localization of WDR62 and mitotic progression are defective in patient-derived fibroblasts, which, similar to mouse neocortical progenitors, transiently arrest at prometaphase. Expression of WDR62 is closely correlated with components of the chromosome passenger complex (CPC), a key regulator of mitosis. Wild type WDR62, but not disease-associated mutant forms, interacts with the CPC core enzyme Aurora kinase B and staining of CPC components at centromeres is altered in patient-derived fibroblasts. Our findings demonstrate critical and diverse functions of WDR62 in neocortical development and provide insight into the mechanisms by which its disruption leads to a plethora of structural abnormalities.
Keywords: Animals; Aurora Kinase B; Brain; Cell Cycle; Cell Differentiation; Cell Proliferation; Centrosome; Consanguinity; Disease Models, Animal; Epistasis, Genetic; Fluorescent Antibody Technique; Gene Expression; Humans; Inheritance Patterns; Male; Mice; Mice, Knockout; Microcephaly; Mutation; Nerve Tissue Proteins; Neural Stem Cells; Pedigree; Whole Genome Sequencing

Dominant Transmission Observed in Adolescents and Families With Orthostatic Intolerance. - Posey, Jennifer E; Martinez, Rebecca; Lankford, Jeremy E; Lupski, James R; Numan, Mohammed T; Butler, Ian J (Pediatr Neurol, 2017)
BACKGROUND: Orthostatic intolerance is typically thought to be sporadic and attributed to cerebral autonomic dysfunction. We sought to identify families with inherited autonomic dysfunction manifest as symptomatic orthostatic intolerance to characterize mode of inheritance and clinical features. METHODS: Sixteen families with two or more first- or second-degree relatives with autonomic dysfunction and orthostatic intolerance were enrolled. A clinical diagnosis of autonomic dysfunction defined by symptomatic orthostatic intolerance diagnosed by head-up tilt table testing was confirmed for each proband. Clinical features and evaluation were obtained from each proband using a standardized intake questionnaire, and family history information was obtained from probands and available relatives. RESULTS: Comprehensive pedigree analysis of 16 families (39 individuals with orthostatic intolerance and 40 individuals suspected of having orthostatic intolerance) demonstrated dominant transmission of autonomic dysfunction with incomplete penetrance. Affected individuals were predominantly female (71.8%, 28/39; F:M, 2.5:1). Male-to-male transmission, although less common, was observed and demonstrated to transmit through unaffected males with an affected parent. Similar to sporadic orthostatic intolerance, probands report a range of symptoms across multiple organ systems, with headaches and neuromuscular features being most common. CONCLUSIONS: Familial occurrence and vertical transmission of autonomic dysfunction in 16 families suggest a novel genetic syndrome with dominant transmission, incomplete penetrance, and skewing of the sex ratio. Elucidation of potential genetic contributions to orthostatic intolerance may inform therapeutic management and identification of individuals at risk. Adolescent evaluation should include identification and treatment of potential at-risk relatives.
Keywords: Adolescent; Cohort Studies; Family; Female; Genetic Testing; Humans; Male; Orthostatic Intolerance; Pedigree; Posture; Surveys and Questionnaires; Tilt-Table Test

DUOX2 Gene Mutation Manifesting as Resistance to Thyrotropin Phenotype. - Srichomkwun, Panudda; Takamatsu, Junta; Nickerson, Deborah A; Bamshad, Michael J; Chong, Jessica X; Refetoff, Samuel (Thyroid, 2017)
Resistance to thyrotropin (TSH) (RTSH; defined by elevated TSH and a normal or hypoplastic thyroid gland) can be caused by mutations in genes encoding the TSH receptor and PAX8, and it has been linked to a locus on chromosome 15. In two nonconsanguineous families with nongoitrous euthyroid hyperthyrotropinemia, typical of the RTSH phenotype, exome analysis identified five rare DUOX2 gene variants (p.A649E, p.P1391A, p.R885L, p.G488R, and p.SF965-6SfsX29) found to be pathogenic. This form of nongoitrous dyshormonogenesis masquerades both clinically and biochemically as RTSH. Accordingly, mutations in DUOX2 should be added to those of SLC26A4 as causes of RTSH.
Keywords: Child, Preschool; Congenital Hypothyroidism; Dual Oxidases; Female; Genotype; Humans; Male; Mutation; Pedigree; Phenotype; Thyroid Hormone Resistance Syndrome; Thyrotropin

Efficient CNV breakpoint analysis reveals unexpected structural complexity and correlation of dosage-sensitive genes with clinical severity in genomic disorders. - Zhang, Ling; Wang, Jingmin; Zhang, Cheng; Li, Dongxiao; Carvalho, Claudia M B; Ji, Haoran; Xiao, Jianqiu; Wu, Ye; Zhou, Weichen; Wang, Hongyan; Jin, Li; Luo, Yang; et al. (Hum Mol Genet, 2017)
Genomic disorders are the clinical conditions manifested by submicroscopic genomic rearrangements including copy number variants (CNVs). The CNVs can be identified by array-based comparative genomic hybridization (aCGH), the most commonly used technology for molecular diagnostics of genomic disorders. However, clinical aCGH only informs CNVs in the probe-interrogated regions. Neither orientational information nor the resulting genomic rearrangement structure is provided, which is a key to uncovering mutational and pathogenic mechanisms underlying genomic disorders. Long-range polymerase chain reaction (PCR) is a traditional approach to obtain CNV breakpoint junction, but this method is inefficient when challenged by structural complexity such as often found at the PLP1 locus in association with Pelizaeus-Merzbacher disease (PMD). Here we introduced 'capture and single-molecule real-time sequencing' (cap-SMRT-seq) and newly developed 'asymmetry linker-mediated nested PCR walking' (ALN-walking) for CNV breakpoint sequencing in 49 subjects with PMD-associated CNVs. Remarkably, 29 (94%) of the 31 CNV breakpoint junctions unobtainable by conventional long-range PCR were resolved by cap-SMRT-seq and ALN-walking. Notably, unexpected CNV complexities, including inter-chromosomal rearrangements that cannot be resolved by aCGH, were revealed by efficient breakpoint sequencing. These sequence-based structures of PMD-associated CNVs further support the role of DNA replicative mechanisms in CNV mutagenesis, and facilitate genotype-phenotype correlation studies. Intriguingly, the lengths of gained segments by CNVs are strongly correlated with clinical severity in PMD, potentially reflecting the functional contribution of other dosage-sensitive genes besides PLP1. Our study provides new efficient experimental approaches (especially ALN-walking) for CNV breakpoint sequencing and highlights their importance in uncovering CNV mutagenesis and pathogenesis in genomic disorders.
Keywords: Base Sequence; Comparative Genomic Hybridization; DNA Copy Number Variations; DNA Replication; Female; Gene Dosage; Gene Duplication; Gene Rearrangement; Genetic Association Studies; Genome, Human; Genomics; Humans; Male; Mutation; Pelizaeus-Merzbacher Disease; Sequence Analysis, DNA

Enrichment of mutations in chromatin regulators in people with Rett syndrome lacking mutations in MECP2. - Sajan, Samin A; Jhangiani, Shalini N; Muzny, Donna M; Gibbs, Richard A; Lupski, James R; Glaze, Daniel G; Kaufmann, Walter E; Skinner, Steven A; Annese, Fran; Friez, Michael J; Lane, Jane; Percy, Alan K; et al. (Genet Med, 2017)
PURPOSE: Rett syndrome (RTT) is a neurodevelopmental disorder caused primarily by de novo mutations in MECP2 and sometimes in CDKL5 and FOXG1. However, some RTT patients lack mutations in these genes. METHODS: Twenty-two RTT patients without apparent MECP2, CDKL5, and FOXG1 mutations were subjected to both whole-exome sequencing and single-nucleotide polymorphism array-based copy-number variant (CNV) analyses. RESULTS: Three patients had MECP2 mutations initially missed by clinical testing. Of the remaining 19, 17 (89.5%) had 29 other likely pathogenic intragenic mutations and/or CNVs (10 patients had 2 or more). Interestingly, 13 patients had mutations in a gene/region previously reported in other neurodevelopmental disorders (NDDs), thereby providing a potential diagnostic yield of 68.4%. These mutations were significantly enriched in chromatin regulators (corrected P = 0.0068) and moderately enriched in postsynaptic cell membrane molecules (corrected P = 0.076), implicating glutamate receptor signaling. CONCLUSION: The genetic etiology of RTT without MECP2, CDKL5, and FOXG1 mutations is heterogeneous, overlaps with other NDDs, and complicated by a high mutation burden. Dysregulation of chromatin structure and abnormal excitatory synaptic signaling may form two common pathological bases of RTT.Genet Med 19 1, 13-19.
Keywords: Adolescent; Adult; Child; Child, Preschool; Chromatin; DNA Copy Number Variations; Female; Forkhead Transcription Factors; Humans; Infant; Male; Methyl-CpG-Binding Protein 2; Mutation; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Protein-Serine-Threonine Kinases; Rett Syndrome; Whole Exome Sequencing

An exome sequencing study of Moebius syndrome including atypical cases reveals an individual with CFEOM3A and a mutation. - Patel, Ronak M; Liu, David; Gonzaga-Jauregui, Claudia; Jhangiani, Shalini; Lu, James T; Sutton, V Reid; Fernbach, Susan D; Azamian, Mahshid; White, Lisa; Edmond, Jane C; Paysse, Evelyn A; Belmont, John W; et al. (Cold Spring Harb Mol Case Stud, 2017)
Moebius syndrome is characterized by congenital unilateral or bilateral facial and abducens nerve palsies (sixth and seventh cranial nerves) causing facial weakness, feeding difficulties, and restricted ocular movements. Abnormalities of the chest wall such as Poland anomaly and variable limb defects are frequently associated with this syndrome. Most cases are isolated; however, rare families with autosomal dominant transmission with incomplete penetrance and variable expressivity have been described. The genetic basis of this condition remains unknown. In a cohort study of nine individuals suspected to have Moebius syndrome (six typical, three atypical), we performed whole-exome sequencing to try to identify a commonly mutated gene. Although no such gene was identified and we did not find mutations in and , we found a de novo heterozygous mutation, p.E410K, in the gene encoding tubulin beta 3 class III (), in an individual with atypical Moebius syndrome. This individual was diagnosed with near-complete ophthalmoplegia, agenesis of the corpus callosum, and absence of the septum pellucidum. No substantial limb abnormalities were noted. Mutations in have been associated with complex cortical dysplasia and other brain malformations and congenital fibrosis of extraocular muscles type 3A (CFEOM3A). Our report highlights the overlap of genetic etiology and clinical differences between CFEOM and Moebius syndrome and describes our approach to identifying candidate genes for typical and atypical Moebius syndrome.
Keywords: Child; Child, Preschool; Cohort Studies; Exome; Eye Diseases, Hereditary; Facial Paralysis; Female; Humans; Infant; Male; Malformations of Cortical Development; Mobius Syndrome; Muscular Diseases; Mutation; Ocular Motility Disorders; Ophthalmoplegia; Orbital Diseases; Pedigree; Tubulin; Whole Exome Sequencing

Exome-wide Association Study Identifies GREB1L Mutations in Congenital Kidney Malformations. - Sanna-Cherchi, Simone; Khan, Kamal; Westland, Rik; Krithivasan, Priya; Fievet, Lorraine; Rasouly, Hila Milo; Ionita-Laza, Iuliana; Capone, Valentina P; Fasel, David A; Kiryluk, Krzysztof; Kamalakaran, Sitharthan; Bodria, Monica; et al. (Am J Hum Genet, 2017)
Renal agenesis and hypodysplasia (RHD) are major causes of pediatric chronic kidney disease and are highly genetically heterogeneous. We conducted whole-exome sequencing in 202 case subjects with RHD and identified diagnostic mutations in genes known to be associated with RHD in 7/202 case subjects. In an additional affected individual with RHD and a congenital heart defect, we found a homozygous loss-of-function (LOF) variant in SLIT3, recapitulating phenotypes reported with Slit3 inactivation in the mouse. To identify genes associated with RHD, we performed an exome-wide association study with 195 unresolved case subjects and 6,905 control subjects. The top signal resided in GREB1L, a gene implicated previously in Hoxb1 and Shha signaling in zebrafish. The significance of the association, which was p = 2.0 × 10 for novel LOF, increased to p = 4.1 × 10 for LOF and deleterious missense variants combined, and augmented further after accounting for segregation and de novo inheritance of rare variants (joint p = 2.3 × 10). Finally, CRISPR/Cas9 disruption or knockdown of greb1l in zebrafish caused specific pronephric defects, which were rescued by wild-type human GREB1L mRNA, but not mRNA containing alleles identified in case subjects. Together, our study provides insight into the genetic landscape of kidney malformations in humans, presents multiple candidates, and identifies SLIT3 and GREB1L as genes implicated in the pathogenesis of RHD.
Keywords: Alleles; Animals; Case-Control Studies; Clustered Regularly Interspaced Short Palindromic Repeats; Congenital Abnormalities; Exome; Female; Genetic Heterogeneity; Genome-Wide Association Study; Genotype; Heredity; Homozygote; Humans; Kidney; Kidney Diseases; Male; Membrane Proteins; Mice; Mutation; Neoplasm Proteins; Phenotype; RNA, Long Noncoding; Urinary Tract; Urogenital Abnormalities; Zebrafish

Genetic Drivers of Kidney Defects in the DiGeorge Syndrome. - Lopez-Rivera, Esther; Liu, Yangfan P; Verbitsky, Miguel; Anderson, Blair R; Capone, Valentina P; Otto, Edgar A; Yan, Zhonghai; Mitrotti, Adele; Martino, Jeremiah; Steers, Nicholas J; Fasel, David A; Vukojevic, Katarina; et al. (N Engl J Med, 2017)
BACKGROUND: The DiGeorge syndrome, the most common of the microdeletion syndromes, affects multiple organs, including the heart, the nervous system, and the kidney. It is caused by deletions on chromosome 22q11.2; the genetic driver of the kidney defects is unknown. METHODS: We conducted a genomewide search for structural variants in two cohorts: 2080 patients with congenital kidney and urinary tract anomalies and 22,094 controls. We performed exome and targeted resequencing in samples obtained from 586 additional patients with congenital kidney anomalies. We also carried out functional studies using zebrafish and mice. RESULTS: We identified heterozygous deletions of 22q11.2 in 1.1% of the patients with congenital kidney anomalies and in 0.01% of population controls (odds ratio, 81.5; P=4.5×10). We localized the main drivers of renal disease in the DiGeorge syndrome to a 370-kb region containing nine genes. In zebrafish embryos, an induced loss of function in snap29, aifm3, and crkl resulted in renal defects; the loss of crkl alone was sufficient to induce defects. Five of 586 patients with congenital urinary anomalies had newly identified, heterozygous protein-altering variants, including a premature termination codon, in CRKL. The inactivation of Crkl in the mouse model induced developmental defects similar to those observed in patients with congenital urinary anomalies. CONCLUSIONS: We identified a recurrent 370-kb deletion at the 22q11.2 locus as a driver of kidney defects in the DiGeorge syndrome and in sporadic congenital kidney and urinary tract anomalies. Of the nine genes at this locus, SNAP29, AIFM3, and CRKL appear to be critical to the phenotype, with haploinsufficiency of CRKL emerging as the main genetic driver. (Funded by the National Institutes of Health and others.).
Keywords: Adaptor Proteins, Signal Transducing; Adolescent; Animals; Child; Chromosome Deletion; Chromosomes, Human, Pair 22; DiGeorge Syndrome; Exome; Female; Haploinsufficiency; Heterozygote; Humans; Infant; Infant, Newborn; Kidney; Male; Mice; Models, Animal; Nuclear Proteins; Sequence Analysis, DNA; Urinary Tract; Young Adult; Zebrafish

Genome-Wide Association Studies and Meta-Analyses for Congenital Heart Defects. - Agopian, A J; Goldmuntz, Elizabeth; Hakonarson, Hakon; Sewda, Anshuman; Taylor, Deanne; Mitchell, Laura E (Circ Cardiovasc Genet, 2017)
BACKGROUND: Maternal and inherited (ie, case) genetic factors likely contribute to the pathogenesis of congenital heart defects, but it is unclear whether individual common variants confer a large risk. METHODS AND RESULTS: To evaluate the relationship between individual common maternal/inherited genotypes and risk for heart defects, we conducted genome-wide association studies in 5 cohorts. Three cohorts were recruited at the Children's Hospital of Philadelphia: 670 conotruncal heart defect (CTD) case-parent trios, 317 left ventricular obstructive tract defect (LVOTD) case-parent trios, and 406 CTD cases (n=406) and 2976 pediatric controls. Two cohorts were recruited through the Pediatric Cardiac Genomics Consortium: 355 CTD trios and 192 LVOTD trios. We also conducted meta-analyses using the genome-wide association study results from the CTD cohorts, the LVOTD cohorts, and from the combined CTD and LVOTD cohorts. In the individual genome-wide association studies, several genome-wide significant associations (≤5×10) were observed. In our meta-analyses, 1 genome-wide significant association was detected: the case genotype for rs72820264, an intragenetic single-nucleotide polymorphism associated with LVOTDs (=2.1×10). CONCLUSIONS: We identified 1 novel candidate region associated with LVOTDs and report on several additional regions with suggestive evidence for association with CTD and LVOTD. These studies were constrained by the relatively small samples sizes and thus have limited power to detect small to moderate associations. Approaches that minimize the multiple testing burden (eg, gene or pathway based) may, therefore, be required to uncover common variants contributing to the risk of these relatively rare conditions.
Keywords: Cohort Studies; Databases, Factual; Female; Gene Frequency; Genome-Wide Association Study; Genotype; Heart Defects, Congenital; Humans; Introns; Male; Membrane Proteins; Polymorphism, Single Nucleotide

Germline mutations in ABL1 cause an autosomal dominant syndrome characterized by congenital heart defects and skeletal malformations. - Wang, Xia; Charng, Wu-Lin; Chen, Chun-An; Rosenfeld, Jill A; Al Shamsi, Aisha; Al-Gazali, Lihadh; McGuire, Marianne; Mew, Nicholas Ah; Arnold, Georgianne L; Qu, Chunjing; Ding, Yan; Muzny, Donna M; et al. (Nat Genet, 2017)
ABL1 is a proto-oncogene well known as part of the fusion gene BCR-ABL1 in the Philadelphia chromosome of leukemia cancer cells. Inherited germline ABL1 changes have not been associated with genetic disorders. Here we report ABL1 germline variants cosegregating with an autosomal dominant disorder characterized by congenital heart disease, skeletal abnormalities, and failure to thrive. The variant c.734A>G (p.Tyr245Cys) was found to occur de novo or cosegregate with disease in five individuals (families 1-3). Additionally, a de novo c.1066G>A (p.Ala356Thr) variant was identified in a sixth individual (family 4). We overexpressed the mutant constructs in HEK 293T cells and observed increased tyrosine phosphorylation, suggesting increased ABL1 kinase activities associated with both the p.Tyr245Cys and p.Ala356Thr substitutions. Our clinical and experimental findings, together with previously reported teratogenic effects of selective BCR-ABL inhibitors in humans and developmental defects in Abl1 knockout mice, suggest that ABL1 has an important role during organismal development.
Keywords: Abnormalities, Multiple; Animals; Bone Diseases, Developmental; Cell Line; Chromosome Disorders; Craniofacial Abnormalities; Feeding and Eating Disorders; Female; Fusion Proteins, bcr-abl; Germ-Line Mutation; Heart Defects, Congenital; HEK293 Cells; Humans; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Limb Deformities, Congenital; Male; Mice; Mice, Knockout; Philadelphia Chromosome; Phosphorylation; Signal Transduction

Haploinsufficiency of the E3 ubiquitin-protein ligase gene TRIP12 causes intellectual disability with or without autism spectrum disorders, speech delay, and dysmorphic features. - Zhang, Jing; Gambin, Tomasz; Yuan, Bo; Szafranski, Przemyslaw; Rosenfeld, Jill A; Balwi, Mohammed Al; Alswaid, Abdulrahman; Al-Gazali, Lihadh; Shamsi, Aisha M Al; Komara, Makanko; Ali, Bassam R; Roeder, Elizabeth; et al. (Hum Genet, 2017)
Impairment of ubiquitin-proteasome system activity involving ubiquitin ligase genes UBE3A, UBE3B, and HUWE1 and deubiquitinating enzyme genes USP7 and USP9X has been reported in patients with neurodevelopmental delays. To date, only a handful of single-nucleotide variants (SNVs) and copy-number variants (CNVs) involving TRIP12, encoding a member of the HECT domain E3 ubiquitin ligases family on chromosome 2q36.3 have been reported. Using chromosomal microarray analysis and whole-exome sequencing (WES), we have identified, respectively, five deletion CNVs and four inactivating SNVs (two frameshifts, one missense, and one splicing) in TRIP12. Seven of these variants were found to be de novo; parental studies could not be completed in two families. Quantitative PCR analyses of the splicing mutation showed a dramatically decreased level of TRIP12 mRNA in the proband compared to the family controls, indicating a loss-of-function mechanism. The shared clinical features include intellectual disability with or without autistic spectrum disorders, speech delay, and facial dysmorphism. Our findings demonstrate that E3 ubiquitin ligase TRIP12 plays an important role in nervous system development and function. The nine presented pathogenic variants further document that TRIP12 haploinsufficiency causes a childhood-onset neurodevelopmental disorder. Finally, our data enable expansion of the phenotypic spectrum of ubiquitin-proteasome dependent disorders.
Keywords: Adolescent; Autism Spectrum Disorder; Carrier Proteins; Child; Child, Preschool; Cohort Studies; DNA Copy Number Variations; Facies; Female; Haploinsufficiency; Humans; Infant; Intellectual Disability; Language Development Disorders; Male; Ubiquitin-Protein Ligases

Heterozygous De Novo UBTF Gain-of-Function Variant Is Associated with Neurodegeneration in Childhood. - Edvardson, Simon; Nicolae, Claudia M; Agrawal, Pankaj B; Mignot, Cyril; Payne, Katelyn; Prasad, Asuri Narayan; Prasad, Chitra; Sadler, Laurie; Nava, Caroline; Mullen, Thomas E; Begtrup, Amber; Baskin, Berivan; et al. (Am J Hum Genet, 2017)
Ribosomal RNA (rRNA) is transcribed from rDNA by RNA polymerase I (Pol I) to produce the 45S precursor of the 28S, 5.8S, and 18S rRNA components of the ribosome. Two transcription factors have been defined for Pol I in mammals, the selectivity factor SL1, and the upstream binding transcription factor (UBF), which interacts with the upstream control element to facilitate the assembly of the transcription initiation complex including SL1 and Pol I. In seven unrelated affected individuals, all suffering from developmental regression starting at 2.5-7 years, we identified a heterozygous variant, c.628G>A in UBTF, encoding p.Glu210Lys in UBF, which occurred de novo in all cases. While the levels of UBF, Ser388 phosphorylated UBF, and other Pol I-related components (POLR1E, TAF1A, and TAF1C) remained unchanged in cells of an affected individual, the variant conferred gain of function to UBF, manifesting by markedly increased UBF binding to the rDNA promoter and to the 5'- external transcribed spacer. This was associated with significantly increased 18S expression, and enlarged nucleoli which were reduced in number per cell. The data link neurodegeneration in childhood with altered rDNA chromatin status and rRNA metabolism.
Keywords: Adolescent; Adult; Atrophy; Brain; Brain Diseases; Cell Nucleolus; Child; Chromatin; DNA-Binding Proteins; Female; Humans; Male; Neurodegenerative Diseases; Pol1 Transcription Initiation Complex Proteins; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; RNA, Ribosomal, 18S; Young Adult

Heterozygous variants in ACTL6A, encoding a component of the BAF complex, are associated with intellectual disability. - Marom, Ronit; Jain, Mahim; Burrage, Lindsay C; Song, I-Wen; Graham, Brett H; Brown, Chester W; Stevens, Servi J C; Stegmann, Alexander P A; Gunter, Andrew T; Kaplan, Julie D; Gavrilova, Ralitza H; Shinawi, Marwan; et al. (Hum Mutat, 2017)
Pathogenic variants in genes encoding components of the BRG1-associated factor (BAF) chromatin remodeling complex have been associated with intellectual disability syndromes. We identified heterozygous, novel variants in ACTL6A, a gene encoding a component of the BAF complex, in three subjects with varying degrees of intellectual disability. Two subjects have missense variants affecting highly conserved amino acid residues within the actin-like domain. Missense mutations in the homologous region in yeast actin were previously reported to be dominant lethal and were associated with impaired binding of the human ACTL6A to β-actin and BRG1. A third subject has a splicing variant that creates an in-frame deletion. Our findings suggest that the variants identified in our subjects may have a deleterious effect on the function of the protein by disturbing the integrity of the BAF complex. Thus, ACTL6A gene mutation analysis should be considered in patients with intellectual disability, learning disabilities, or developmental language disorder.
Keywords: Actins; Adolescent; Child; Chromatin Assembly and Disassembly; Chromosomal Proteins, Non-Histone; DNA Helicases; DNA-Binding Proteins; Exome; Face; Female; Hand Deformities, Congenital; Heterozygote; Humans; Intellectual Disability; Male; Micrognathism; Multiprotein Complexes; Mutation, Missense; Nuclear Proteins; Protein Binding; Transcription Factors

High Rate of Recurrent De Novo Mutations in Developmental and Epileptic Encephalopathies. - Hamdan, Fadi F; Myers, Candace T; Cossette, Patrick; Lemay, Philippe; Spiegelman, Dan; Laporte, Alexandre Dionne; Nassif, Christina; Diallo, Ousmane; Monlong, Jean; Cadieux-Dion, Maxime; Dobrzeniecka, Sylvia; Meloche, Caroline; et al. (Am J Hum Genet, 2017)
Developmental and epileptic encephalopathy (DEE) is a group of conditions characterized by the co-occurrence of epilepsy and intellectual disability (ID), typically with developmental plateauing or regression associated with frequent epileptiform activity. The cause of DEE remains unknown in the majority of cases. We performed whole-genome sequencing (WGS) in 197 individuals with unexplained DEE and pharmaco-resistant seizures and in their unaffected parents. We focused our attention on de novo mutations (DNMs) and identified candidate genes containing such variants. We sought to identify additional subjects with DNMs in these genes by performing targeted sequencing in another series of individuals with DEE and by mining various sequencing datasets. We also performed meta-analyses to document enrichment of DNMs in candidate genes by leveraging our WGS dataset with those of several DEE and ID series. By combining these strategies, we were able to provide a causal link between DEE and the following genes: NTRK2, GABRB2, CLTC, DHDDS, NUS1, RAB11A, GABBR2, and SNAP25. Overall, we established a molecular diagnosis in 63/197 (32%) individuals in our WGS series. The main cause of DEE in these individuals was de novo point mutations (53/63 solved cases), followed by inherited mutations (6/63 solved cases) and de novo CNVs (4/63 solved cases). De novo missense variants explained a larger proportion of individuals in our series than in other series that were primarily ascertained because of ID. Moreover, these DNMs were more frequently recurrent than those identified in ID series. These observations indicate that the genetic landscape of DEE might be different from that of ID without epilepsy.
Keywords: Brain Diseases; Child; Child, Preschool; Epilepsy; Female; Genome, Human; Genome-Wide Association Study; Humans; Intellectual Disability; Male; Mutation; Recurrence; Seizures

Homozygous Mutations in TBC1D23 Lead to a Non-degenerative Form of Pontocerebellar Hypoplasia. - Marin-Valencia, Isaac; Gerondopoulos, Andreas; Zaki, Maha S; Ben-Omran, Tawfeg; Almureikhi, Mariam; Demir, Ercan; Guemez-Gamboa, Alicia; Gregor, Anne; Issa, Mahmoud Y; Appelhof, Bart; Roosing, Susanne; Musaev, Damir; et al. (Am J Hum Genet, 2017)
Pontocerebellar hypoplasia (PCH) represents a group of recessive developmental disorders characterized by impaired growth of the pons and cerebellum, which frequently follows a degenerative course. Currently, there are 10 partially overlapping clinical subtypes and 13 genes known mutated in PCH. Here, we report biallelic TBC1D23 mutations in six individuals from four unrelated families manifesting a non-degenerative form of PCH. In addition to reduced volume of pons and cerebellum, affected individuals had microcephaly, psychomotor delay, and ataxia. In zebrafish, tbc1d23 morphants replicated the human phenotype showing hindbrain volume loss. TBC1D23 localized at the trans-Golgi and was regulated by the small GTPases Arl1 and Arl8, suggesting a role in trans-Golgi membrane trafficking. Altogether, this study provides a causative link between TBC1D23 mutations and PCH and suggests a less severe clinical course than other PCH subtypes.
Keywords: Adolescent; Animals; Cerebellar Diseases; Child; Child, Preschool; Female; GTPase-Activating Proteins; HeLa Cells; Homozygote; Humans; Male; Microcephaly; Mutation; Pedigree; Phenotype; Zebrafish

Hypogonadotropic Hypogonadism due to Novel FGFR1 Mutations. - Akkuş, Gamze; Kotan, Leman Damla; Durmaz, Erdem; Mengen, Eda; Turan, İhsan; Ulubay, Ayça; Gürbüz, Fatih; Yüksel, Bilgin; Tetiker, Tamer; Topaloğlu, A Kemal (J Clin Res Pediatr Endocrinol, 2017)
OBJECTIVE: The underlying genetic etiology of hypogonadotropic hypogonadism (HH) is heterogeneous. Fibroblast growth factor signaling is pivotal in the ontogeny of gonadotropin-releasing hormone neurons. Loss-of-function mutations in FGFR1 gene cause variable HH phenotypes encompassing pubertal delay to idiopathic HH (IHH) or Kallmann syndrome (KS). As FGFR1 mutations are common, recognizing mutations and associated phenotypes may enhance clinical management. METHODS: Using a candidate gene approach, we screened 52 IHH/KS patients. RESULTS: We identified three novel (IVS3-1G>C and p.W2X, p.R209C) FGFR1 gene mutations. Despite predictive null protein function, patients from the novel mutation families had normosmic IHH without non-reproductive phenotype. CONCLUSION: These findings further emphasize the great variability of FGFR1 mutation phenotypes in IHH/KS.
Keywords: Adolescent; Adult; Family Health; Female; Genetic Predisposition to Disease; Genotype; Humans; Hypogonadism; Klinefelter Syndrome; Male; Mutation; Pedigree; Phenotype; Puberty, Delayed; Receptor, Fibroblast Growth Factor, Type 1; Young Adult

Identification of ASAH1 as a susceptibility gene for familial keloids. - Santos-Cortez, Regie Lyn P; Hu, Ying; Sun, Fanyue; Benahmed-Miniuk, Fairouz; Tao, Jian; Kanaujiya, Jitendra K; Ademola, Samuel; Fadiora, Solomon; Odesina, Victoria; Nickerson, Deborah A; Bamshad, Michael J; Olaitan, Peter B; et al. (Eur J Hum Genet, 2017)
Keloids result from abnormal proliferative scar formation with scar tissue expanding beyond the margin of the original wound and are mostly found in individuals of sub-Saharan African descent. The etiology of keloids has not been resolved but previous studies suggest that keloids are a genetically heterogeneous disorder. Although possible candidate genes have been suggested by genome-wide association studies using common variants, by upregulation in keloids or their involvement in syndromes that include keloid formation, rare coding variants that contribute to susceptibility in non-syndromic keloid formation have not been previously identified. Through analysis of whole-genome data we mapped a locus to chromosome 8p23.3-p21.3 with a statistically significant maximum multipoint LOD score of 4.48. This finding was followed up using exome sequencing and led to the identification of a c.1202T>C (p.(Leu401Pro)) variant in the N-acylsphingosine amidohydrolase (ASAH1) gene that co-segregates with the keloid phenotype in a large Yoruba family. ASAH1 is an acid ceramidase known to be involved in tumor formation by controlling the ratio of ceramide and sphingosine. ASAH1 is also involved in cell proliferation and inflammation, and may affect the development of keloids via multiple mechanisms. Functional studies need to clarify the role of the ASAH1 variant in wound healing.
Keywords: Acid Ceramidase; Adult; Female; Humans; Keloid; Male; Mutation, Missense; Pedigree

Identification of GAA variants through whole exome sequencing targeted to a cohort of 606 patients with unexplained limb-girdle muscle weakness. - Johnson, Katherine; Topf, Ana; Bertoli, Marta; Phillips, Lauren; Claeys, Kristl G; Stojanovic, Vidosava Rakocevic; Perić, Stojan; Hahn, Andreas; Maddison, Paul; Akay, Ela; Bastian, Alexandra E; Łusakowska, Anna; et al. (Orphanet J Rare Dis, 2017)
BACKGROUND: Late-onset Pompe disease is a rare genetic neuromuscular disorder caused by a primary deficiency of α-glucosidase and the associated accumulation of glycogen in lysosomal vacuoles. The deficiency of α-glucosidase can often be detected using an inexpensive and readily accessible dried blood spot test when Pompe disease is suspected. Like several neuromuscular disorders, Pompe disease typically presents with progressive weakness of limb-girdle muscles and respiratory insufficiency. Due to the phenotypic heterogeneity of these disorders, however, it is often difficult for clinicians to reach a diagnosis for patients with Pompe disease. Six hundred and six patients from a European population were recruited onto our study. Inclusion criteria stipulated that index cases must present with limb-girdle weakness or elevated serum creatine kinase activity. Whole exome sequencing with at least 250 ng DNA was completed using an Illumina exome capture and a 38 Mb baited target. A panel of 169 candidate genes for limb-girdle weakness was analysed for disease-causing variants. RESULTS: A total of 35 variants within GAA were detected. Ten distinct variants in eight unrelated index cases (and four siblings not sequenced in our study) were considered disease-causing, with the patients presenting with heterogeneous phenotypes. The eight unrelated individuals were compound heterozygotes for two variants. Six patients carried the intronic splice site c.-13 T > G transversion and two of the six patients also carried the exonic p.Glu176ArgfsTer45 frameshift. Four of the ten variants were novel in their association with Pompe disease. CONCLUSIONS: Here, we highlight the advantage of using whole exome sequencing as a tool for detecting, diagnosing and treating patients with rare, clinically variable genetic disorders.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; alpha-Glucosidases; Child; Child, Preschool; Cohort Studies; Female; Genetic Variation; Glycogen Storage Disease Type II; Humans; Male; Middle Aged; Muscle Weakness; Muscular Dystrophies, Limb-Girdle; Whole Exome Sequencing; Young Adult

Identification of STAC3 variants in non-Native American families with overlapping features of Carey-Fineman-Ziter syndrome and Moebius syndrome. - Telegrafi, Aida; Webb, Bryn D; Robbins, Sarah M; Speck-Martins, Carlos E; FitzPatrick, David; Fleming, Leah; Redett, Richard; Dufke, Andreas; Houge, Gunnar; van Harssel, Jeske J T; Verloes, Alain; Robles, Angela; et al. (Am J Med Genet A, 2017)
Horstick et al. (2013) previously reported a homozygous p.Trp284Ser variant in STAC3 as the cause of Native American myopathy (NAM) in 5 Lumbee Native American families with congenital hypotonia and weakness, cleft palate, short stature, ptosis, kyphoscoliosis, talipes deformities, and susceptibility to malignant hyperthermia (MH). Here we present two non-Native American families, who were found to have STAC3 pathogenic variants. The first proband and her affected older sister are from a consanguineous Qatari family with a suspected clinical diagnosis of Carey-Fineman-Ziter syndrome (CFZS) based on features of hypotonia, myopathic facies with generalized weakness, ptosis, normal extraocular movements, cleft palate, growth delay, and kyphoscoliosis. We identified the homozygous c.851G>C;p.Trp284Ser variant in STAC3 in both sisters. The second proband and his affected sister are from a non-consanguineous, Puerto Rican family who was evaluated for a possible diagnosis of Moebius syndrome (MBS). His features included facial and generalized weakness, minimal limitation of horizontal gaze, cleft palate, and hypotonia, and he has a history of MH. The siblings were identified to be compound heterozygous for STAC3 variants c.851G>C;p.Trp284Ser and c.763_766delCTCT;p.Leu255IlefsX58. Given the phenotypic overlap of individuals with CFZS, MBS, and NAM, we screened STAC3 in 12 individuals diagnosed with CFZS and in 50 individuals diagnosed with MBS or a congenital facial weakness disorder. We did not identify any rare coding variants in STAC3. NAM should be considered in patients presenting with facial and generalized weakness, normal or mildly abnormal extraocular movement, hypotonia, cleft palate, and scoliosis, particularly if there is a history of MH.
Keywords: Adaptor Proteins, Signal Transducing; Adolescent; Adult; Child; Female; Humans; Male; Mobius Syndrome; Muscular Diseases; Mutation; Pedigree; Pierre Robin Syndrome; Prognosis; Young Adult

Isolated polycystic liver disease genes define effectors of polycystin-1 function. - Besse, Whitney; Dong, Ke; Choi, Jungmin; Punia, Sohan; Fedeles, Sorin V; Choi, Murim; Gallagher, Anna-Rachel; Huang, Emily B; Gulati, Ashima; Knight, James; Mane, Shrikant; Tahvanainen, Esa; et al. (J Clin Invest, 2017)
Dominantly inherited isolated polycystic liver disease (PCLD) consists of liver cysts that are radiologically and pathologically identical to those seen in autosomal dominant polycystic kidney disease, but without clinically relevant kidney cysts. The causative genes are known for fewer than 40% of PCLD index cases. Here, we have used whole exome sequencing in a discovery cohort of 102 unrelated patients who were excluded for mutations in the 2 most common PCLD genes, PRKCSH and SEC63, to identify heterozygous loss-of-function mutations in 3 additional genes, ALG8, GANAB, and SEC61B. Similarly to PRKCSH and SEC63, these genes encode proteins that are integral to the protein biogenesis pathway in the endoplasmic reticulum. We inactivated these candidate genes in cell line models to show that loss of function of each results in defective maturation and trafficking of polycystin-1, the central determinant of cyst pathogenesis. Despite acting in a common pathway, each PCLD gene product demonstrated distinct effects on polycystin-1 biogenesis. We also found enrichment on a genome-wide basis of heterozygous mutations in the autosomal recessive polycystic kidney disease gene PKHD1, indicating that adult PKHD1 carriers can present with clinical PCLD. These findings define genetic and biochemical modulators of polycystin-1 function and provide a more complete definition of the spectrum of dominant human polycystic diseases.
Keywords: Adult; Animals; Cell Line, Transformed; Cysts; Endoplasmic Reticulum; Female; Genome-Wide Association Study; Glucosidases; Glucosyltransferases; Heterozygote; Humans; Intracellular Signaling Peptides and Proteins; Liver Diseases; Male; Membrane Proteins; Mice; Mutation; SEC Translocation Channels; TRPP Cation Channels

Kaufman oculo-cerebro-facial syndrome in a child with small and absent terminal phalanges and absent nails. - Kariminejad, Ariana; Ajeawung, Norbert Fonya; Bozorgmehr, Bita; Dionne-Laporte, Alexandre; Molidperee, Sirinart; Najafi, Kimia; Gibbs, Richard A; Lee, Brendan H; Hennekam, Raoul C; Campeau, Philippe M (J Hum Genet, 2017)
Kaufman oculo-cerebro-facial syndrome (KOS) is caused by recessive UBE3B mutations and presents with microcephaly, ocular abnormalities, distinctive facial morphology, low cholesterol levels and intellectual disability. We describe a child with microcephaly, brachycephaly, hearing loss, ptosis, blepharophimosis, hypertelorism, cleft palate, multiple renal cysts, absent nails, small or absent terminal phalanges, absent speech and intellectual disability. Syndromes that were initially considered include DOORS syndrome, Coffin-Siris syndrome and Dubowitz syndrome. Clinical investigations coupled with karyotype analysis, array-comparative genomic hybridization, exome and Sanger sequencing were performed to characterize the condition in this child. Sanger sequencing was negative for the DOORS syndrome gene TBC1D24 but exome sequencing identified a homozygous deletion in UBE3B (NM_183415:c.3139_3141del, p.1047_1047del) located within the terminal portion of the HECT domain. This finding coupled with the presence of characteristic features such as brachycephaly, ptosis, blepharophimosis, hypertelorism, short palpebral fissures, cleft palate and developmental delay allowed us to make a diagnosis of KOS. In conclusion, our findings highlight the importance of considering KOS as a differential diagnosis for patients under evaluation for DOORS syndrome and expand the phenotype of KOS to include small or absent terminal phalanges, nails, and the presence of hallux varus and multicystic dysplastic kidneys.
Keywords: Abnormalities, Multiple; Adult; Carrier Proteins; Child; Child, Preschool; Diagnosis, Differential; Eczema; Eye Abnormalities; Face; Facies; Female; Growth Disorders; Hand Deformities, Congenital; Humans; Intellectual Disability; Karyotype; Limb Deformities, Congenital; Male; Microcephaly; Micrognathism; Mutation; Neck; Pathology, Molecular; Sequence Analysis, DNA; Ubiquitin-Protein Ligases

Lessons learned from additional research analyses of unsolved clinical exome cases. - Eldomery, Mohammad K; Coban-Akdemir, Zeynep; Harel, Tamar; Rosenfeld, Jill A; Gambin, Tomasz; Stray-Pedersen, Asbjørg; Küry, Sébastien; Mercier, Sandra; Lessel, Davor; Denecke, Jonas; Wiszniewski, Wojciech; Penney, Samantha; et al. (Genome Med, 2017)
BACKGROUND: Given the rarity of most single-gene Mendelian disorders, concerted efforts of data exchange between clinical and scientific communities are critical to optimize molecular diagnosis and novel disease gene discovery. METHODS: We designed and implemented protocols for the study of cases for which a plausible molecular diagnosis was not achieved in a clinical genomics diagnostic laboratory (i.e. unsolved clinical exomes). Such cases were recruited to a research laboratory for further analyses, in order to potentially: (1) accelerate novel disease gene discovery; (2) increase the molecular diagnostic yield of whole exome sequencing (WES); and (3) gain insight into the genetic mechanisms of disease. Pilot project data included 74 families, consisting mostly of parent-offspring trios. Analyses performed on a research basis employed both WES from additional family members and complementary bioinformatics approaches and protocols. RESULTS: Analysis of all possible modes of Mendelian inheritance, focusing on both single nucleotide variants (SNV) and copy number variant (CNV) alleles, yielded a likely contributory variant in 36% (27/74) of cases. If one includes candidate genes with variants identified within a single family, a potential contributory variant was identified in a total of ~51% (38/74) of cases enrolled in this pilot study. The molecular diagnosis was achieved in 30/63 trios (47.6%). Besides this, the analysis workflow yielded evidence for pathogenic variants in disease-associated genes in 4/6 singleton cases (66.6%), 1/1 multiplex family involving three affected siblings, and 3/4 (75%) quartet families. Both the analytical pipeline and the collaborative efforts between the diagnostic and research laboratories provided insights that allowed recent disease gene discoveries (PURA, TANGO2, EMC1, GNB5, ATAD3A, and MIPEP) and increased the number of novel genes, defined in this study as genes identified in more than one family (DHX30 and EBF3). CONCLUSION: An efficient genomics pipeline in which clinical sequencing in a diagnostic laboratory is followed by the detailed reanalysis of unsolved cases in a research environment, supplemented with WES data from additional family members, and subject to adjuvant bioinformatics analyses including relaxed variant filtering parameters in informatics pipelines, can enhance the molecular diagnostic yield and provide mechanistic insights into Mendelian disorders. Implementing these approaches requires collaborative clinical molecular diagnostic and research efforts.
Keywords: Adenosine Triphosphatases; ATPases Associated with Diverse Cellular Activities; Computational Biology; DNA Copy Number Variations; DNA-Binding Proteins; Exome; Female; Genetic Diseases, Inborn; Genomics; GTP-Binding Protein beta Subunits; Humans; Male; Membrane Proteins; Metalloendopeptidases; Mitochondrial Proteins; Pilot Projects; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Transcription Factors

Loss-of-Function Mutations in YY1AP1 Lead to Grange Syndrome and a Fibromuscular Dysplasia-Like Vascular Disease. - Guo, Dong-Chuan; Duan, Xue-Yan; Regalado, Ellen S; Mellor-Crummey, Lauren; Kwartler, Callie S; Kim, Dong; Lieberman, Kenneth; de Vries, Bert B A; Pfundt, Rolph; Schinzel, Albert; Kotzot, Dieter; Shen, Xuetong; et al. (Am J Hum Genet, 2017)
Fibromuscular dysplasia (FMD) is a heterogeneous group of non-atherosclerotic and non-inflammatory arterial diseases that primarily involves the renal and cerebrovascular arteries. Grange syndrome is an autosomal-recessive condition characterized by severe and early-onset vascular disease similar to FMD and variable penetrance of brachydactyly, syndactyly, bone fragility, and learning disabilities. Exome-sequencing analysis of DNA from three affected siblings with Grange syndrome identified compound heterozygous nonsense variants in YY1AP1, and homozygous nonsense or frameshift YY1AP1 variants were subsequently identified in additional unrelated probands with Grange syndrome. YY1AP1 encodes yin yang 1 (YY1)-associated protein 1 and is an activator of the YY1 transcription factor. We determined that YY1AP1 localizes to the nucleus and is a component of the INO80 chromatin remodeling complex, which is responsible for transcriptional regulation, DNA repair, and replication. Molecular studies revealed that loss of YY1AP1 in vascular smooth muscle cells leads to cell cycle arrest with decreased proliferation and increased levels of the cell cycle regulator p21/WAF/CDKN1A and disrupts TGF-β-driven differentiation of smooth muscle cells. Identification of YY1AP1 mutations as a cause of FMD indicates that this condition can result from underlying genetic variants that significantly alter the phenotype of vascular smooth muscle cells.
Keywords: Adolescent; Adult; Bone and Bones; Brachydactyly; Cell Cycle Checkpoints; Exome; Female; Fibromuscular Dysplasia; Genes, Recessive; Heterozygote; Homozygote; Humans; Learning Disorders; Male; Middle Aged; Muscle, Smooth, Vascular; Mutation; Nuclear Proteins; Pedigree; Syndactyly; Syndrome; Transcription Factors

Loss-of-Function Variants in MYLK Cause Recessive Megacystis Microcolon Intestinal Hypoperistalsis Syndrome. - Halim, Danny; Brosens, Erwin; Muller, Françoise; Wangler, Michael F; Beaudet, Arthur L; Lupski, James R; Akdemir, Zeynep H Coban; Doukas, Michael; Stoop, Hans J; de Graaf, Bianca M; Brouwer, Rutger W W; van Ijcken, Wilfred F J; et al. (Am J Hum Genet, 2017)
Megacystis microcolon intestinal hypoperistalsis syndrome (MMIHS) is a congenital disorder characterized by loss of smooth muscle contraction in the bladder and intestine. To date, three genes are known to be involved in MMIHS pathogenesis: ACTG2, MYH11, and LMOD1. However, for approximately 10% of affected individuals, the genetic cause of the disease is unknown, suggesting that other loci are most likely involved. Here, we report on three MMIHS-affected subjects from two consanguineous families with no variants in the known MMIHS-associated genes. By performing homozygosity mapping and whole-exome sequencing, we found homozygous variants in myosin light chain kinase (MYLK) in both families. We identified a 7 bp duplication (c.3838_3844dupGAAAGCG [p.Glu1282_Glyfs51]) in one family and a putative splice-site variant (c.3985+5C>A) in the other. Expression studies and splicing assays indicated that both variants affect normal MYLK expression. Because MYLK encodes an important kinase required for myosin activation and subsequent interaction with actin filaments, it is likely that in its absence, contraction of smooth muscle cells is impaired. The existence of a conditional-Mylk-knockout mouse model with severe gut dysmotility and abnormal function of the bladder supports the involvement of this gene in MMIHS pathogenesis. In aggregate, our findings implicate MYLK as a gene involved in the recessive form of MMIHS, confirming that this disease of the visceral organs is heterogeneous with a myopathic origin.
Keywords: Abnormalities, Multiple; Base Sequence; Colon; Female; Genes, Recessive; Homozygote; Humans; Intestinal Pseudo-Obstruction; Male; Mutation; Myosin-Light-Chain Kinase; Pedigree; Urinary Bladder

MED resulting from recessively inherited mutations in the gene encoding calcium-activated nucleotidase CANT1. - Balasubramanian, Karthika; Li, Bing; Krakow, Deborah; Nevarez, Lisette; Ho, Patric J; Ainsworth, Julia A; Nickerson, Deborah A; Bamshad, Michael J; Immken, LaDonna; Lachman, Ralph S; Cohn, Daniel H (Am J Med Genet A, 2017)
Multiple Epiphyseal Dysplasia (MED) is a relatively mild skeletal dysplasia characterized by mild short stature, joint pain, and early-onset osteoarthropathy. Dominantly inherited mutations in COMP, MATN3, COL9A1, COL9A2, and COL9A3, and recessively inherited mutations in SLC26A2, account for the molecular basis of disease in about 80-85% of the cases. In two families with recurrent MED of an unknown molecular basis, we used exome sequencing and candidate gene analysis to identify homozygosity for recessively inherited missense mutations in CANT1, which encodes calcium-activated nucleotidase 1. The MED phenotype is thus allelic to the more severe Desbuquois dysplasia phenotype and the results identify CANT1 as a second locus for recessively inherited MED.
Keywords: Adult; Base Sequence; Child; Child, Preschool; Exome; Female; Genes, Recessive; Humans; Male; Mutation, Missense; Nucleotidases; Osteochondrodysplasias; Pedigree; Radiography

Molecular outcomes, clinical consequences, and genetic diagnosis of Oculocutaneous Albinism in Pakistani population. - Shahzad, Mohsin; Yousaf, Sairah; Waryah, Yar M; Gul, Hadia; Kausar, Tasleem; Tariq, Nabeela; Mahmood, Umair; Ali, Muhammad; Khan, Muzammil A; Waryah, Ali M; Shaikh, Rehan S; Riazuddin, Saima; et al. (Sci Rep, 2017)
Nonsyndromic oculocutaneous Albinism (nsOCA) is clinically characterized by the loss of pigmentation in the skin, hair, and iris. OCA is amongst the most common causes of vision impairment in children. To date, pathogenic variants in six genes have been identified in individuals with nsOCA. Here, we determined the identities, frequencies, and clinical consequences of OCA alleles in 94 previously unreported Pakistani families. Combination of Sanger and Exome sequencing revealed 38 alleles, including 22 novel variants, segregating with nsOCA phenotype in 80 families. Variants of TYR and OCA2 genes were the most common cause of nsOCA, occurring in 43 and 30 families, respectively. Twenty-two novel variants include nine missense, four splice site, two non-sense, one insertion and six gross deletions. In vitro studies revealed retention of OCA proteins harboring novel missense alleles in the endoplasmic reticulum (ER) of transfected cells. Exon-trapping assays with constructs containing splice site alleles revealed errors in splicing. As eight alleles account for approximately 56% (95% CI: 46.52-65.24%) of nsOCA cases, primarily enrolled from Punjab province of Pakistan, hierarchical strategies for variant detection would be feasible and cost-efficient genetic tests for OCA in families with similar origin. Thus, we developed Tetra-primer ARMS assays for rapid, reliable, reproducible and economical screening of most of these common alleles.
Keywords: Albinism, Oculocutaneous; Alleles; Female; Gene Frequency; Humans; Male; Membrane Transport Proteins; Mutation, Missense; Pakistan

Multilevel analyses of SCN5A mutations in arrhythmogenic right ventricular dysplasia/cardiomyopathy suggest non-canonical mechanisms for disease pathogenesis. - Te Riele, Anneline S J M; Agullo-Pascual, Esperanza; James, Cynthia A; Leo-Macias, Alejandra; Cerrone, Marina; Zhang, Mingliang; Lin, Xianming; Lin, Bin; Sobreira, Nara L; Amat-Alarcon, Nuria; Marsman, Roos F; Murray, Brittney; et al. (Cardiovasc Res, 2017)
AIMS: Arrhythmogenic Right Ventricular Dysplasia/Cardiomyopathy (ARVD/C) is often associated with desmosomal mutations. Recent studies suggest an interaction between the desmosome and sodium channel protein Na1.5. We aimed to determine the prevalence and biophysical properties of mutations in SCN5A (the gene encoding Na1.5) in ARVD/C. METHODS AND RESULTS: We performed whole-exome sequencing in six ARVD/C patients (33% male, 38.2 ± 12.1 years) without a desmosomal mutation. We found a rare missense variant (p.Arg1898His; R1898H) in SCN5A in one patient. We generated induced pluripotent stem cell-derived cardiomyocytes (hIPSC-CMs) from the patient's peripheral blood mononuclear cells. The variant was then corrected (R1898R) using Clustered Regularly Interspaced Short Palindromic Repeats/Cas9 technology, allowing us to study the impact of the R1898H substitution in the same cellular background. Whole-cell patch clamping revealed a 36% reduction in peak sodium current (P = 0.002); super-resolution fluorescence microscopy showed reduced abundance of Na1.5 (P = 0.005) and N-Cadherin (P = 0.026) clusters at the intercalated disc. Subsequently, we sequenced SCN5A in an additional 281 ARVD/C patients (60% male, 34.8 ± 13.7 years, 52% desmosomal mutation-carriers). Five (1.8%) subjects harboured a putatively pathogenic SCN5A variant (p.Tyr416Cys, p.Leu729del, p.Arg1623Ter, p.Ser1787Asn, and p.Val2016Met). SCN5A variants were associated with prolonged QRS duration (119 ± 15 vs. 94 ± 14 ms, P < 0.01) and all SCN5A variant carriers had major structural abnormalities on cardiac imaging. CONCLUSIONS: Almost 2% of ARVD/C patients harbour rare SCN5A variants. For one of these variants, we demonstrated reduced sodium current, Na1.5 and N-Cadherin clusters at junctional sites. This suggests that Na1.5 is in a functional complex with adhesion molecules, and reveals potential non-canonical mechanisms by which Na1.5 dysfunction causes cardiomyopathy.
Keywords: Adult; Antigens, CD; Arrhythmogenic Right Ventricular Dysplasia; Cadherins; Cell Differentiation; CRISPR-Cas Systems; DNA Mutational Analysis; Electrocardiography; Exome; Female; Gene Editing; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; HEK293 Cells; Humans; Induced Pluripotent Stem Cells; Magnetic Resonance Imaging; Male; Membrane Potentials; Middle Aged; Multilevel Analysis; Mutation, Missense; Myocytes, Cardiac; NAV1.5 Voltage-Gated Sodium Channel; Netherlands; Phenotype; Sodium; Transfection; United States; Young Adult

Mutations in EBF3 Disturb Transcriptional Profiles and Cause Intellectual Disability, Ataxia, and Facial Dysmorphism. - Harms, Frederike Leonie; Girisha, Katta M; Hardigan, Andrew A; Kortüm, Fanny; Shukla, Anju; Alawi, Malik; Dalal, Ashwin; Brady, Lauren; Tarnopolsky, Mark; Bird, Lynne M; Ceulemans, Sophia; Bebin, Martina; et al. (Am J Hum Genet, 2017)
From a GeneMatcher-enabled international collaboration, we identified ten individuals affected by intellectual disability, speech delay, ataxia, and facial dysmorphism and carrying a deleterious EBF3 variant detected by whole-exome sequencing. One 9-bp duplication and one splice-site, five missense, and two nonsense variants in EBF3 were found; the mutations occurred de novo in eight individuals, and the missense variant c.625C>T (p.Arg209Trp) was inherited by two affected siblings from their healthy mother, who is mosaic. EBF3 belongs to the early B cell factor family (also known as Olf, COE, or O/E) and is a transcription factor involved in neuronal differentiation and maturation. Structural assessment predicted that the five amino acid substitutions have damaging effects on DNA binding of EBF3. Transient expression of EBF3 mutant proteins in HEK293T cells revealed mislocalization of all but one mutant in the cytoplasm, as well as nuclear localization. By transactivation assays, all EBF3 mutants showed significantly reduced or no ability to activate transcription of the reporter gene CDKN1A, and in situ subcellular fractionation experiments demonstrated that EBF3 mutant proteins were less tightly associated with chromatin. Finally, in RNA-seq and ChIP-seq experiments, EBF3 acted as a transcriptional regulator, and mutant EBF3 had reduced genome-wide DNA binding and gene-regulatory activity. Our findings demonstrate that variants disrupting EBF3-mediated transcriptional regulation cause intellectual disability and developmental delay and are present in ∼0.1% of individuals with unexplained neurodevelopmental disorders.
Keywords: Adolescent; Adult; Amino Acid Substitution; Ataxia; Child; Child, Preschool; Chromatin; Cyclin-Dependent Kinase Inhibitor p21; Developmental Disabilities; Exome; Face; Female; Gene Expression Regulation; Genes, Reporter; HEK293 Cells; Humans; Intellectual Disability; Language Development Disorders; Male; Models, Molecular; Mosaicism; Mutation; Neurodevelopmental Disorders; Protein Transport; Syndrome; Transcription Factors; Transcription, Genetic

Mutations in Fibronectin Cause a Subtype of Spondylometaphyseal Dysplasia with "Corner Fractures". - Lee, Chae Syng; Fu, He; Baratang, Nissan; Rousseau, Justine; Kumra, Heena; Sutton, V Reid; Niceta, Marcello; Ciolfi, Andrea; Yamamoto, Guilherme; Bertola, Débora; Marcelis, Carlo L; Lugtenberg, Dorien; et al. (Am J Hum Genet, 2017)
Fibronectin is a master organizer of extracellular matrices (ECMs) and promotes the assembly of collagens, fibrillin-1, and other proteins. It is also known to play roles in skeletal tissues through its secretion by osteoblasts, chondrocytes, and mesenchymal cells. Spondylometaphyseal dysplasias (SMDs) comprise a diverse group of skeletal dysplasias and often manifest as short stature, growth-plate irregularities, and vertebral anomalies, such as scoliosis. By comparing the exomes of individuals with SMD with the radiographic appearance of "corner fractures" at metaphyses, we identified three individuals with fibronectin (FN1) variants affecting highly conserved residues. Furthermore, using matching tools and the SkelDys emailing list, we identified other individuals with de novo FN1 variants and a similar phenotype. The severe scoliosis in most individuals and rare developmental coxa vara distinguish individuals with FN1 mutations from those with classical Sutcliffe-type SMD. To study functional consequences of these FN1 mutations on the protein level, we introduced three disease-associated missense variants (p.Cys87Phe [c.260G>T], p.Tyr240Asp [c.718T>G], and p.Cys260Gly [c.778T>G]) into a recombinant secreted N-terminal 70 kDa fragment (rF70K) and the full-length fibronectin (rFN). The wild-type rF70K and rFN were secreted into the culture medium, whereas all mutant proteins were either not secreted or secreted at significantly lower amounts. Immunofluorescence analysis demonstrated increased intracellular retention of the mutant proteins. In summary, FN1 mutations that cause defective fibronectin secretion are found in SMD, and we thus provide additional evidence for a critical function of fibronectin in cartilage and bone.
Keywords: Adolescent; Adult; Bone and Bones; Bone Diseases, Developmental; Cartilage; Child; Child, Preschool; Exome; Female; Fibronectins; Fractures, Bone; Humans; Male; Mutation; Osteochondrodysplasias; Phenotype; Scoliosis

Mutations in GPAA1, Encoding a GPI Transamidase Complex Protein, Cause Developmental Delay, Epilepsy, Cerebellar Atrophy, and Osteopenia. - Nguyen, Thi Tuyet Mai; Murakami, Yoshiko; Sheridan, Eamonn; Ehresmann, Sophie; Rousseau, Justine; St-Denis, Anik; Chai, Guoliang; Ajeawung, Norbert F; Fairbrother, Laura; Reimschisel, Tyler; Bateman, Alexandra; Berry-Kravis, Elizabeth; et al. (Am J Hum Genet, 2017)
Approximately one in every 200 mammalian proteins is anchored to the cell membrane through a glycosylphosphatidylinositol (GPI) anchor. These proteins play important roles notably in neurological development and function. To date, more than 20 genes have been implicated in the biogenesis of GPI-anchored proteins. GPAA1 (glycosylphosphatidylinositol anchor attachment 1) is an essential component of the transamidase complex along with PIGK, PIGS, PIGT, and PIGU (phosphatidylinositol-glycan biosynthesis classes K, S, T, and U, respectively). This complex orchestrates the attachment of the GPI anchor to the C terminus of precursor proteins in the endoplasmic reticulum. Here, we report bi-allelic mutations in GPAA1 in ten individuals from five families. Using whole-exome sequencing, we identified two frameshift mutations (c.981_993del [p.Gln327Hisfs102] and c.920delG [p.Gly307Alafs11]), one intronic splicing mutation (c.1164+5C>T), and six missense mutations (c.152C>T [p.Ser51Leu], c.160_161delinsAA [p.Ala54Asn], c.527G>C [p.Trp176Ser], c.869T>C [p.Leu290Pro], c.872T>C [p.Leu291Pro], and c.1165G>C [p.Ala389Pro]). Most individuals presented with global developmental delay, hypotonia, early-onset seizures, cerebellar atrophy, and osteopenia. The splicing mutation was found to decrease GPAA1 mRNA. Moreover, flow-cytometry analysis of five available individual samples showed that several GPI-anchored proteins had decreased cell-surface abundance in leukocytes (FLAER, CD16, and CD59) or fibroblasts (CD73 and CD109). Transduction of fibroblasts with a lentivirus encoding the wild-type protein partially rescued the deficiency of GPI-anchored proteins. These findings highlight the role of the transamidase complex in the development and function of the cerebellum and the skeletal system.
Keywords: Acyltransferases; Adolescent; Adult; Alleles; Atrophy; Bone Diseases, Metabolic; Cerebellum; Child; Child, Preschool; Developmental Disabilities; Epilepsy; Exome; Female; Fibroblasts; Glycosylphosphatidylinositols; Humans; Male; Membrane Glycoproteins; Muscle Hypotonia; Mutation; Pedigree; RNA, Messenger; Seizures

Mutations in sphingosine-1-phosphate lyase cause nephrosis with ichthyosis and adrenal insufficiency. - Lovric, Svjetlana; Goncalves, Sara; Gee, Heon Yung; Oskouian, Babak; Srinivas, Honnappa; Choi, Won-Il; Shril, Shirlee; Ashraf, Shazia; Tan, Weizhen; Rao, Jia; Airik, Merlin; Schapiro, David; et al. (J Clin Invest, 2017)
Steroid-resistant nephrotic syndrome (SRNS) causes 15% of chronic kidney disease cases. A mutation in 1 of over 40 monogenic genes can be detected in approximately 30% of individuals with SRNS whose symptoms manifest before 25 years of age. However, in many patients, the genetic etiology remains unknown. Here, we have performed whole exome sequencing to identify recessive causes of SRNS. In 7 families with SRNS and facultative ichthyosis, adrenal insufficiency, immunodeficiency, and neurological defects, we identified 9 different recessive mutations in SGPL1, which encodes sphingosine-1-phosphate (S1P) lyase. All mutations resulted in reduced or absent SGPL1 protein and/or enzyme activity. Overexpression of cDNA representing SGPL1 mutations resulted in subcellular mislocalization of SGPL1. Furthermore, expression of WT human SGPL1 rescued growth of SGPL1-deficient dpl1Δ yeast strains, whereas expression of disease-associated variants did not. Immunofluorescence revealed SGPL1 expression in mouse podocytes and mesangial cells. Knockdown of Sgpl1 in rat mesangial cells inhibited cell migration, which was partially rescued by VPC23109, an S1P receptor antagonist. In Drosophila, Sply mutants, which lack SGPL1, displayed a phenotype reminiscent of nephrotic syndrome in nephrocytes. WT Sply, but not the disease-associated variants, rescued this phenotype. Together, these results indicate that SGPL1 mutations cause a syndromic form of SRNS.
Keywords: Aldehyde-Lyases; Animals; Cell Line; Cell Movement; Drosophila melanogaster; Drosophila Proteins; Female; Humans; Ichthyosis, Lamellar; Male; Mesangial Cells; Mice; Mice, Knockout; Mutation; Nephrotic Syndrome; Protein Transport; Rats

Neonatal fractures as a presenting feature of LMOD3-associated congenital myopathy. - Abbott, Megan; Jain, Mahim; Pferdehirt, Rachel; Chen, Yuqing; Tran, Alyssa; Duz, Mehmet B; Seven, Mehmet; Gibbs, Richard A; Muzny, Donna; Lee, Brendan; Marom, Ronit; Burrage, Lindsay C (Am J Med Genet A, 2017)
Nemaline myopathy is a rare inherited disorder characterized by weakness, hypotonia, and depressed deep tendon reflexes. It is clinically and genetically heterogeneous, with the most severe phenotype presenting as perinatal akinesia, severe muscle weakness, feeding difficulties and respiratory failure, leading to early mortality. Pathogenic variants in 12 genes, encoding components of the sarcomere or factors related to myogenesis, have been reported in patients affected with the disorder. Here, we describe an early, lethal presentation of decreased fetal movements, hypotonia, muscle weakness, and neonatal respiratory failure requiring ventilator support in three siblings from a consanguineous family. All exhibited perinatal fractures, and thus, a skeletal dysplasia was considered as possibly contributing to the phenotype. However, whole exome sequencing revealed a homozygous, loss-of-function pathogenic variant in LMOD3, which has recently been associated with nemaline myopathy and, in a subset of patients, perinatal fractures. This case demonstrates the importance of considering congenital neuromuscular disorders in the differential diagnosis of perinatal fractures.
Keywords: Female; Fractures, Bone; Homozygote; Humans; Infant, Newborn; Male; Muscle Proteins; Mutation; Myopathies, Structural, Congenital; Pedigree

Novel Genetic Triggers and Genotype-Phenotype Correlations in Patients With Left Ventricular Noncompaction. - Miszalski-Jamka, Karol; Jefferies, John L; Mazur, Wojciech; Głowacki, Jan; Hu, Jianhong; Lazar, Monika; Gibbs, Richard A; Liczko, Jacek; Kłyś, Jan; Venner, Eric; Muzny, Donna M; Rycaj, Jarosław; et al. (Circ Cardiovasc Genet, 2017)
BACKGROUND: Left ventricular noncompaction (LVNC) is a genetically and phenotypically heterogeneous disease and, although increasingly recognized in clinical practice, there is a lack of widely accepted diagnostic criteria. We sought to identify novel genetic causes of LVNC and describe genotype-phenotype correlations. METHODS AND RESULTS: A total of 190 patients from 174 families with left ventricular hypertrabeculation (LVHT) or LVNC were referred for cardiac magnetic resonance and whole-exome sequencing. A total of 425 control individuals were included to identify variants of interest (VOIs). We found an excess of 138 VOIs in 102 (59%) unrelated patients in 54 previously identified LVNC or other known cardiomyopathy genes. VOIs were found in 68 of 90 probands with LVNC and 34 of 84 probands with LVHT (76% and 40%, respectively; <0.001). We identified 0, 1, and ≥2 VOIs in 72, 74, and 28 probands, respectively. We found increasing number of VOIs in a patient strongly correlated with several markers of disease severity, including ratio of noncompacted to compacted myocardium (<0.001) and left ventricular ejection fraction (=0.01). The presence of sarcomeric gene mutations was associated with increased occurrence of late gadolinium enhancement (=0.004). CONCLUSIONS: LVHT and LVNC likely represent a continuum of genotypic disease with differences in severity and variable phenotype explained, in part, by the number of VOIs and whether mutations are present in sarcomeric or nonsarcomeric genes. Presence of VOIs is common in patients with LVHT. Our findings expand the current clinical and genetic diagnostic approaches for patients with LVHT and LVNC.
Keywords: Adaptor Proteins, Signal Transducing; Adolescent; Adult; Aged; Cardiac Myosins; Carrier Proteins; Child; Connectin; Female; Genetic Association Studies; Genetic Variation; Heart Ventricles; Humans; LIM Domain Proteins; Magnetic Resonance Imaging, Cine; Male; Middle Aged; Muscle Proteins; Myocardium; Myosin Heavy Chains; Prospective Studies; Severity of Illness Index; Tropomyosin; Ventricular Dysfunction, Left; Young Adult

An Organismal CNV Mutator Phenotype Restricted to Early Human Development. - Liu, Pengfei; Yuan, Bo; Carvalho, Claudia M B; Wuster, Arthur; Walter, Klaudia; Zhang, Ling; Gambin, Tomasz; Chong, Zechen; Campbell, Ian M; Coban Akdemir, Zeynep; Gelowani, Violet; Writzl, Karin; et al. (Cell, 2017)
De novo copy number variants (dnCNVs) arising at multiple loci in a personal genome have usually been considered to reflect cancer somatic genomic instabilities. We describe a multiple dnCNV (MdnCNV) phenomenon in which individuals with genomic disorders carry five to ten constitutional dnCNVs. These CNVs originate from independent formation incidences, are predominantly tandem duplications or complex gains, exhibit breakpoint junction features reminiscent of replicative repair, and show increased de novo point mutations flanking the rearrangement junctions. The active CNV mutation shower appears to be restricted to a transient perizygotic period. We propose that a defect in the CNV formation process is responsible for the "CNV-mutator state," and this state is dampened after early embryogenesis. The constitutional MdnCNV phenomenon resembles chromosomal instability in various cancers. Investigations of this phenomenon may provide unique access to understanding genomic disorders, structural variant mutagenesis, human evolution, and cancer biology.
Keywords: Chromosome Aberrations; Chromosome Breakpoints; Chromosome Duplication; DNA Copy Number Variations; DNA Replication; Embryonic Development; Female; Gametogenesis; Genetic Diseases, Inborn; Genomic Instability; Humans; Male; Mutation

P4HA1 mutations cause a unique congenital disorder of connective tissue involving tendon, bone, muscle and the eye. - Zou, Yaqun; Donkervoort, Sandra; Salo, Antti M; Foley, A Reghan; Barnes, Aileen M; Hu, Ying; Makareeva, Elena; Leach, Meganne E; Mohassel, Payam; Dastgir, Jahannaz; Deardorff, Matthew A; Cohn, Ronald D; et al. (Hum Mol Genet, 2017)
Collagen prolyl 4-hydroxylases (C-P4Hs) play a central role in the formation and stabilization of the triple helical domain of collagens. P4HA1 encodes the catalytic α(I) subunit of the main C-P4H isoenzyme (C-P4H-I). We now report human bi-allelic P4HA1 mutations in a family with a congenital-onset disorder of connective tissue, manifesting as early-onset joint hypermobility, joint contractures, muscle weakness and bone dysplasia as well as high myopia, with evidence of clinical improvement of motor function over time in the surviving patient. Similar to P4ha1 null mice, which die prenatally, the muscle tissue from P1 and P2 was found to have reduced collagen IV immunoreactivity at the muscle basement membrane. Patients were compound heterozygous for frameshift and splice site mutations leading to reduced, but not absent, P4HA1 protein level and C-P4H activity in dermal fibroblasts compared to age-matched control samples. Differential scanning calorimetry revealed reduced thermal stability of collagen in patient-derived dermal fibroblasts versus age-matched control samples. Mutations affecting the family of C-P4Hs, and in particular C-P4H-I, should be considered in patients presenting with congenital connective tissue/myopathy overlap disorders with joint hypermobility, contractures, mild skeletal dysplasia and high myopia.
Keywords: Animals; Basement Membrane; Bone and Bones; Child; Collagen Type IV; Connective Tissue; Humans; Male; Mice; Mice, Knockout; Muscles; Mutation; Osteochondrodysplasias; Procollagen-Proline Dioxygenase; Prolyl Hydroxylases; Tendons

Patients with a Kabuki syndrome phenotype demonstrate DNA methylation abnormalities. - Sobreira, Nara; Brucato, Martha; Zhang, Li; Ladd-Acosta, Christine; Ongaco, Chrissie; Romm, Jane; Doheny, Kimberly F; Mingroni-Netto, Regina C; Bertola, Débora; Kim, Chong A; Perez, Ana Ba; Melaragno, Maria I; et al. (Eur J Hum Genet, 2017)
Kabuki syndrome is a monogenic disorder caused by loss of function variants in either of two genes encoding histone-modifying enzymes. We performed targeted sequencing in a cohort of 27 probands with a clinical diagnosis of Kabuki syndrome. Of these, 12 had causative variants in the two known Kabuki syndrome genes. In 2, we identified presumptive loss of function de novo variants in KMT2A (missense and splice site variants), a gene that encodes another histone modifying enzyme previously exclusively associated with Wiedermann-Steiner syndrome. Although Kabuki syndrome is a disorder of histone modification, we also find alterations in DNA methylation among individuals with a Kabuki syndrome diagnosis relative to matched normal controls, regardless of whether they carry a variant in KMT2A or KMT2D or not. Furthermore, we observed characteristic global abnormalities of DNA methylation that distinguished patients with a loss of function variant in KMT2D or missense or splice site variants in either KMT2D or KMT2A from normal controls. Our results provide new insights into the relationship of genotype to epigenotype and phenotype and indicate cross-talk between histone and DNA methylation machineries exposed by inborn errors of the epigenetic apparatus.
Keywords: Abnormalities, Multiple; Case-Control Studies; Child; DNA Methylation; Face; Female; Hematologic Diseases; Histone-Lysine N-Methyltransferase; Humans; Loss of Function Mutation; Male; Myeloid-Lymphoid Leukemia Protein; Phenotype; Vestibular Diseases

Phenotypic and molecular characterisation of CDK13-related congenital heart defects, dysmorphic facial features and intellectual developmental disorders. - Bostwick, Bret L; McLean, Scott; Posey, Jennifer E; Streff, Haley E; Gripp, Karen W; Blesson, Alyssa; Powell-Hamilton, Nina; Tusi, Jessica; Stevenson, David A; Farrelly, Ellyn; Hudgins, Louanne; Yang, Yaping; et al. (Genome Med, 2017)
BACKGROUND: De novo missense variants in CDK13 have been described as the cause of syndromic congenital heart defects in seven individuals ascertained from a large congenital cardiovascular malformations cohort. We aimed to further define the phenotypic and molecular spectrum of this newly described disorder. METHODS: To minimise ascertainment bias, we recruited nine additional individuals with CDK13 pathogenic variants from clinical and research exome laboratory sequencing cohorts. Each individual underwent dysmorphology exam and comprehensive medical history review. RESULTS: We demonstrate greater than expected phenotypic heterogeneity, including 33% (3/9) of individuals without structural heart disease on echocardiogram. There was a high penetrance for a unique constellation of facial dysmorphism and global developmental delay, as well as less frequently seen renal and sacral anomalies. Two individuals had novel CDK13 variants (p.Asn842Asp, p.Lys734Glu), while the remaining seven unrelated individuals had a recurrent, previously published p.Asn842Ser variant. Summary of all variants published to date demonstrates apparent restriction of pathogenic variants to the protein kinase domain with clustering in the ATP and magnesium binding sites. CONCLUSIONS: Here we provide detailed phenotypic and molecular characterisation of individuals with pathogenic variants in CDK13 and propose management guidelines based upon the estimated prevalence of anomalies identified.
Keywords: Adolescent; Adult; CDC2 Protein Kinase; Child; Child, Preschool; Face; Female; Heart Defects, Congenital; Humans; Infant; Intellectual Disability; Male; Mutation; Phenotype; Syndrome

Phenotypic spectrum of autosomal recessive congenital ichthyosis due to PNPLA1 mutation. - Boyden, L M; Craiglow, B G; Hu, R H; Zhou, J; Browning, J; Eichenfield, L; Lim, Y L; Luu, M; Randolph, L M; Ginarte, M; Fachal, L; Rodriguez-Pazos, L; et al. (Br J Dermatol, 2017)
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Child; Child, Preschool; Female; Heterozygote; Homozygote; Humans; Ichthyosis; Infant; Lipase; Male; Middle Aged; Mutation, Missense; Pedigree; Phenotype; Young Adult

A postnatal role for embryonic myosin revealed by MYH3 mutations that alter TGFβ signaling and cause autosomal dominant spondylocarpotarsal synostosis. - Zieba, Jennifer; Zhang, Wenjuan; Chong, Jessica X; Forlenza, Kimberly N; Martin, Jorge H; Heard, Kelly; Grange, Dorothy K; Butler, Merlin G; Kleefstra, Tjitske; Lachman, Ralph S; Nickerson, Deborah; Regnier, Michael; et al. (Sci Rep, 2017)
Spondylocarpotarsal synostosis (SCT) is a skeletal disorder characterized by progressive vertebral, carpal and tarsal fusions, and mild short stature. The majority of affected individuals have an autosomal recessive form of SCT and are homozygous or compound heterozygous for nonsense mutations in the gene that encodes the cytoskeletal protein filamin B (FLNB), but a subset do not have FLNB mutations. Exome sequence analysis of three SCT patients negative for FLNB mutations identified an autosomal dominant form of the disease due to heterozygosity for missense or nonsense mutations in MYH3, which encodes embryonic myosin. Cells transfected with the MYH3 missense mutations had reduced TGFβ signaling, revealing a regulatory role for embryonic myosin in the TGFβ signaling pathway. In wild-type mice, there was persistent postnatal expression of embryonic myosin in the small muscles joining the neural arches of the spine suggesting that loss of myosin function in these muscles contribute to the disease. Our findings demonstrate that dominant mutations in MYH3 underlie autosomal dominant SCT, identify a postnatal role for embryonic myosin and suggest that altered regulation of signal transduction in the muscles within the spine may lead to the development of vertebral fusions.
Keywords: Abnormalities, Multiple; Alleles; Bone Morphogenetic Proteins; Cytoskeletal Proteins; Female; Genes, Dominant; Genotype; Humans; Lumbar Vertebrae; Male; Musculoskeletal Diseases; Mutation; Myosins; Phenotype; Radiography; Scoliosis; Signal Transduction; Synostosis; Thoracic Vertebrae; Transforming Growth Factor beta; Whole Exome Sequencing

Primary immunodeficiency diseases: Genomic approaches delineate heterogeneous Mendelian disorders. - Stray-Pedersen, Asbjørg; Sorte, Hanne Sørmo; Samarakoon, Pubudu; Gambin, Tomasz; Chinn, Ivan K; Coban Akdemir, Zeynep H; Erichsen, Hans Christian; Forbes, Lisa R; Gu, Shen; Yuan, Bo; Jhangiani, Shalini N; Muzny, Donna M; et al. (J Allergy Clin Immunol, 2017)
BACKGROUND: Primary immunodeficiency diseases (PIDDs) are clinically and genetically heterogeneous disorders thus far associated with mutations in more than 300 genes. The clinical phenotypes derived from distinct genotypes can overlap. Genetic etiology can be a prognostic indicator of disease severity and can influence treatment decisions. OBJECTIVE: We sought to investigate the ability of whole-exome screening methods to detect disease-causing variants in patients with PIDDs. METHODS: Patients with PIDDs from 278 families from 22 countries were investigated by using whole-exome sequencing. Computational copy number variant (CNV) prediction pipelines and an exome-tiling chromosomal microarray were also applied to identify intragenic CNVs. Analytic approaches initially focused on 475 known or candidate PIDD genes but were nonexclusive and further tailored based on clinical data, family history, and immunophenotyping. RESULTS: A likely molecular diagnosis was achieved in 110 (40%) unrelated probands. Clinical diagnosis was revised in about half (60/110) and management was directly altered in nearly a quarter (26/110) of families based on molecular findings. Twelve PIDD-causing CNVs were detected, including 7 smaller than 30 Kb that would not have been detected with conventional diagnostic CNV arrays. CONCLUSION: This high-throughput genomic approach enabled detection of disease-related variants in unexpected genes; permitted detection of low-grade constitutional, somatic, and revertant mosaicism; and provided evidence of a mutational burden in mixed PIDD immunophenotypes.
Keywords: Adolescent; Adult; Aged; Child; Child, Preschool; DNA Copy Number Variations; Female; Genomics; High-Throughput Nucleotide Sequencing; Humans; Immunologic Deficiency Syndromes; Infant; Male; Middle Aged; Young Adult

PRUNE is crucial for normal brain development and mutated in microcephaly with neurodevelopmental impairment. - Zollo, Massimo; Ahmed, Mustafa; Ferrucci, Veronica; Salpietro, Vincenzo; Asadzadeh, Fatemeh; Carotenuto, Marianeve; Maroofian, Reza; Al-Amri, Ahmed; Singh, Royana; Scognamiglio, Iolanda; Mojarrad, Majid; Musella, Luca; et al. (Brain, 2017)
PRUNE is a member of the DHH (Asp-His-His) phosphoesterase protein superfamily of molecules important for cell motility, and implicated in cancer progression. Here we investigated multiple families from Oman, India, Iran and Italy with individuals affected by a new autosomal recessive neurodevelopmental and degenerative disorder in which the cardinal features include primary microcephaly and profound global developmental delay. Our genetic studies identified biallelic mutations of PRUNE1 as responsible. Our functional assays of disease-associated variant alleles revealed impaired microtubule polymerization, as well as cell migration and proliferation properties, of mutant PRUNE. Additionally, our studies also highlight a potential new role for PRUNE during microtubule polymerization, which is essential for the cytoskeletal rearrangements that occur during cellular division and proliferation. Together these studies define PRUNE as a molecule fundamental for normal human cortical development and define cellular and clinical consequences associated with PRUNE mutation.
Keywords: Adolescent; Brain; Carrier Proteins; Cell Differentiation; Cell Movement; Cerebral Cortex; Child; Child, Preschool; Cytoskeleton; Developmental Disabilities; Female; Genes, Recessive; Heredodegenerative Disorders, Nervous System; Humans; Infant; Male; Microcephaly; Microtubules; Mutation; Pedigree; Young Adult

A Recurrent De Novo Variant in NACC1 Causes a Syndrome Characterized by Infantile Epilepsy, Cataracts, and Profound Developmental Delay. - Schoch, Kelly; Meng, Linyan; Szelinger, Szabolcs; Bearden, David R; Stray-Pedersen, Asbjorg; Busk, Oyvind L; Stong, Nicholas; Liston, Eriskay; Cohn, Ronald D; Scaglia, Fernando; Rosenfeld, Jill A; Tarpinian, Jennifer; et al. (Am J Hum Genet, 2017)
Whole-exome sequencing (WES) has increasingly enabled new pathogenic gene variant identification for undiagnosed neurodevelopmental disorders and provided insights into both gene function and disease biology. Here, we describe seven children with a neurodevelopmental disorder characterized by microcephaly, profound developmental delays and/or intellectual disability, cataracts, severe epilepsy including infantile spasms, irritability, failure to thrive, and stereotypic hand movements. Brain imaging in these individuals reveals delay in myelination and cerebral atrophy. We observe an identical recurrent de novo heterozygous c.892C>T (p.Arg298Trp) variant in the nucleus accumbens associated 1 (NACC1) gene in seven affected individuals. One of the seven individuals is mosaic for this variant. NACC1 encodes a transcriptional repressor implicated in gene expression and has not previously been associated with germline disorders. The probability of finding the same missense NACC1 variant by chance in 7 out of 17,228 individuals who underwent WES for diagnoses of neurodevelopmental phenotypes is extremely small and achieves genome-wide significance (p = 1.25 × 10). Selective constraint against missense variants in NACC1 makes this excess of an identical missense variant in all seven individuals more remarkable. Our findings are consistent with a germline recurrent mutational hotspot associated with an allele-specific neurodevelopmental phenotype in NACC1.
Keywords: Alleles; Amino Acid Sequence; Brain; Cataract; Child; Child, Preschool; Female; Genetic Variation; Genome-Wide Association Study; Humans; Infant; Intellectual Disability; Magnetic Resonance Imaging; Male; Microcephaly; Mutation, Missense; Neoplasm Proteins; Pedigree; Phenotype; Repressor Proteins; Spasms, Infantile

REST Final-Exon-Truncating Mutations Cause Hereditary Gingival Fibromatosis. - Bayram, Yavuz; White, Janson J; Elcioglu, Nursel; Cho, Megan T; Zadeh, Neda; Gedikbasi, Asuman; Palanduz, Sukru; Ozturk, Sukru; Cefle, Kivanc; Kasapcopur, Ozgur; Coban Akdemir, Zeynep; Pehlivan, Davut; et al. (Am J Hum Genet, 2017)
Hereditary gingival fibromatosis (HGF) is the most common genetic form of gingival fibromatosis that develops as a slowly progressive, benign, localized or generalized enlargement of keratinized gingiva. HGF is a genetically heterogeneous disorder and can be transmitted either as an autosomal-dominant or autosomal-recessive trait or appear sporadically. To date, four loci (2p22.1, 2p23.3-p22.3, 5q13-q22, and 11p15) have been mapped to autosomes and one gene (SOS1) has been associated with the HGF trait observed to segregate in a dominant inheritance pattern. Here we report 11 individuals with HGF from three unrelated families. Whole-exome sequencing (WES) revealed three different truncating mutations including two frameshifts and one nonsense variant in RE1-silencing transcription factor (REST) in the probands from all families and further genetic and genomic analyses confirmed the WES-identified findings. REST is a transcriptional repressor that is expressed throughout the body; it has different roles in different cellular contexts, such as oncogenic and tumor-suppressor functions and hematopoietic and cardiac differentiation. Here we show the consequences of germline final-exon-truncating mutations in REST for organismal development and the association with the HGF phenotype.
Keywords: Adolescent; Base Sequence; Chromosome Segregation; Exons; Family; Female; Fibromatosis, Gingival; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Mutation; Pedigree; Repressor Proteins

The sensitivity of exome sequencing in identifying pathogenic mutations for LGMD in the United States. - Reddy, Hemakumar M; Cho, Kyung-Ah; Lek, Monkol; Estrella, Elicia; Valkanas, Elise; Jones, Michael D; Mitsuhashi, Satomi; Darras, Basil T; Amato, Anthony A; Lidov, Hart Gw; Brownstein, Catherine A; Margulies, David M; et al. (J Hum Genet, 2017)
The current study characterizes a cohort of limb-girdle muscular dystrophy (LGMD) in the United States using whole-exome sequencing. Fifty-five families affected by LGMD were recruited using an institutionally approved protocol. Exome sequencing was performed on probands and selected parental samples. Pathogenic mutations and cosegregation patterns were confirmed by Sanger sequencing. Twenty-two families (40%) had novel and previously reported pathogenic mutations, primarily in LGMD genes, and also in genes for Duchenne muscular dystrophy, facioscapulohumeral muscular dystrophy, congenital myopathy, myofibrillar myopathy, inclusion body myopathy and Pompe disease. One family was diagnosed via clinical testing. Dominant mutations were identified in COL6A1, COL6A3, FLNC, LMNA, RYR1, SMCHD1 and VCP, recessive mutations in ANO5, CAPN3, GAA, LAMA2, SGCA and SGCG, and X-linked mutations in DMD. A previously reported variant in DMD was confirmed to be benign. Exome sequencing is a powerful diagnostic tool for LGMD. Despite careful phenotypic screening, pathogenic mutations were found in other muscle disease genes, largely accounting for the increased sensitivity of exome sequencing. Our experience suggests that broad sequencing panels are useful for these analyses because of the phenotypic overlap of many neuromuscular conditions. The confirmation of a benign DMD variant illustrates the potential of exome sequencing to help determine pathogenicity.
Keywords: Base Sequence; Distal Myopathies; Exome; Female; Genetic Testing; Glycogen Storage Disease Type II; Humans; Male; Muscular Dystrophies, Limb-Girdle; Muscular Dystrophy, Duchenne; Muscular Dystrophy, Facioscapulohumeral; Mutation; Myopathies, Structural, Congenital; Sequence Analysis, DNA; United States

Sequence variants in nine different genes underlying rare skin disorders in 10 consanguineous families. - Shah, Khadim; Mehmood, Sabba; Jan, Abid; Abbe, Izoduwa; Hussain Ali, Raja; Khan, Anwar; Chishti, Muhammad S; Lee, Kwanghyuk; Ahmad, Farooq; Ansar, Muhammad; Shahzad, Shaheen; Nickerson, Deborah A; et al. (Int J Dermatol, 2017)
BACKGROUND: Genodermatoses represent genetic anomalies of skin tissues including hair follicles, sebaceous glands, eccrine glands, nails, and teeth. Ten consanguineous families segregating various genodermatosis phenotypes were investigated in the present study. METHODS: Homozygosity mapping, exome, and Sanger sequencing were employed to search for the disease-causing variants in the 10 families. RESULTS: Exome sequencing identified seven homozygous sequence variants in different families, including: c.27delT in FERMT1; c.836delA in ABHD5; c.2453C>T in ERCC5; c.5314C>T in COL7A1; c.1630C>T in ALOXE3; c.502C>T in PPOX; and c.10G>T in ALDH3A2. Sanger sequencing revealed three homozygous variants: c.1718 + 2A>G in FERMT1; c.10459A>T in FLG; and c.92delT in the KRT14 genes as the underlying genetic cause of skin phenotypes. CONCLUSION: This study supports the use of exome sequencing as a powerful, efficient tool for identifying genes that underlie rare monogenic skin disorders.
Keywords: 1-Acylglycerol-3-Phosphate O-Acyltransferase; Aldehyde Oxidoreductases; Blister; Collagen Type VII; Consanguinity; DNA Mutational Analysis; DNA-Binding Proteins; Endonucleases; Epidermolysis Bullosa; Epidermolysis Bullosa Dystrophica; Epidermolysis Bullosa Simplex; Exome; Female; Flavoproteins; Homozygote; Humans; Ichthyosiform Erythroderma, Congenital; Ichthyosis Vulgaris; Ichthyosis, Lamellar; INDEL Mutation; Intermediate Filament Proteins; Keratin-14; Lipid Metabolism, Inborn Errors; Lipoxygenase; Male; Membrane Proteins; Mitochondrial Proteins; Muscular Diseases; Neoplasm Proteins; Nuclear Proteins; Pedigree; Periodontal Diseases; Phenotype; Photosensitivity Disorders; Porphyria, Variegate; Protoporphyrinogen Oxidase; Rare Diseases; Sjogren-Larsson Syndrome; Skin Diseases, Genetic; Transcription Factors; Xeroderma Pigmentosum

Sequencing of sporadic Attention-Deficit Hyperactivity Disorder (ADHD) identifies novel and potentially pathogenic de novo variants and excludes overlap with genes associated with autism spectrum disorder. - Kim, Daniel Seung; Burt, Amber A; Ranchalis, Jane E; Wilmot, Beth; Smith, Joshua D; Patterson, Karynne E; Coe, Bradley P; Li, Yatong K; Bamshad, Michael J; Nikolas, Molly; Eichler, Evan E; Swanson, James M; et al. (Am J Med Genet B Neuropsychiatr Genet, 2017)
Attention-Deficit Hyperactivity Disorder (ADHD) has high heritability; however, studies of common variation account for <5% of ADHD variance. Using data from affected participants without a family history of ADHD, we sought to identify de novo variants that could account for sporadic ADHD. Considering a total of 128 families, two analyses were conducted in parallel: first, in 11 unaffected parent/affected proband trios (or quads with the addition of an unaffected sibling) we completed exome sequencing. Six de novo missense variants at highly conserved bases were identified and validated from four of the 11 families: the brain-expressed genes TBC1D9, DAGLA, QARS, CSMD2, TRPM2, and WDR83. Separately, in 117 unrelated probands with sporadic ADHD, we sequenced a panel of 26 genes implicated in intellectual disability (ID) and autism spectrum disorder (ASD) to evaluate whether variation in ASD/ID-associated genes were also present in participants with ADHD. Only one putative deleterious variant (Gln600STOP) in CHD1L was identified; this was found in a single proband. Notably, no other nonsense, splice, frameshift, or highly conserved missense variants in the 26 gene panel were identified and validated. These data suggest that de novo variant analysis in families with independently adjudicated sporadic ADHD diagnosis can identify novel genes implicated in ADHD pathogenesis. Moreover, that only one of the 128 cases (0.8%, 11 exome, and 117 MIP sequenced participants) had putative deleterious variants within our data in 26 genes related to ID and ASD suggests significant independence in the genetic pathogenesis of ADHD as compared to ASD and ID phenotypes. © 2017 Wiley Periodicals, Inc.
Keywords: Adult; Attention Deficit Disorder with Hyperactivity; Autism Spectrum Disorder; Biomarkers; Child; Exome; Female; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Male; Mutation, Missense; Phenotype

SLC13A5 is the second gene associated with Kohlschütter-Tönz syndrome. - Schossig, Anna; Bloch-Zupan, Agnès; Lussi, Adrian; Wolf, Nicole I; Raskin, Salmo; Cohen, Monika; Giuliano, Fabienne; Jurgens, Julie; Krabichler, Birgit; Koolen, David A; de Macena Sobreira, Nara Lygia; Maurer, Elisabeth; et al. (J Med Genet, 2017)
BACKGROUND: Kohlschütter-Tönz syndrome (KTZS) is a rare autosomal-recessive disease characterised by epileptic encephalopathy, intellectual disability and amelogenesis imperfecta (AI). It is frequently caused by biallelic mutations in ROGDI. Here, we report on individuals with ROGDI-negative KTZS carrying biallelic SLC13A5 mutations. METHODS: In the present cohort study, nine individuals from four families with the clinical diagnosis of KTZS and absence of ROGDI mutations as well as one patient with unexplained epileptic encephalopathy were investigated by clinical and dental evaluation, parametric linkage analysis (one family), and exome and/or Sanger sequencing. Dental histological investigations were performed on teeth from individuals with SLC13A5-associated and ROGDI-associated KTZS. RESULTS: Biallelic mutations in SLC13A5 were identified in 10 affected individuals. Epileptic encephalopathy usually presents in the neonatal and (less frequently) early infantile period. Yellowish to orange discolouration of both deciduous and permanent teeth, as well as wide interdental spaces and abnormal crown forms are major clinical signs of individuals with biallelic SLC13A5 mutations. Histological dental investigations confirmed the clinical diagnosis of hypoplastic AI. In comparison, the histological evaluation of a molar assessed from an individual with ROGDI-associated KTZS revealed hypocalcified AI. CONCLUSIONS: We conclude that SLC13A5 is the second major gene associated with the clinical diagnosis of KTZS, characterised by neonatal epileptic encephalopathy and hypoplastic AI. Careful clinical and dental delineation provides clues whether ROGDI or SLC13A5 is the causative gene. Hypersensitivity of teeth as well as high caries risk requires individual dental prophylaxis and attentive dental management.
Keywords: Alleles; Amelogenesis Imperfecta; Brain Diseases; Cohort Studies; Dementia; Epilepsy; Exome; Female; Genetic Linkage; Genetic Predisposition to Disease; Humans; Male; Membrane Proteins; Mutation; Nuclear Proteins; Pedigree; Symporters; Tooth

SMCHD1 mutations associated with a rare muscular dystrophy can also cause isolated arhinia and Bosma arhinia microphthalmia syndrome. - Shaw, Natalie D; Brand, Harrison; Kupchinsky, Zachary A; Bengani, Hemant; Plummer, Lacey; Jones, Takako I; Erdin, Serkan; Williamson, Kathleen A; Rainger, Joe; Stortchevoi, Alexei; Samocha, Kaitlin; Currall, Benjamin B; et al. (Nat Genet, 2017)
Arhinia, or absence of the nose, is a rare malformation of unknown etiology that is often accompanied by ocular and reproductive defects. Sequencing of 40 people with arhinia revealed that 84% of probands harbor a missense mutation localized to a constrained region of SMCHD1 encompassing the ATPase domain. SMCHD1 mutations cause facioscapulohumeral muscular dystrophy type 2 (FSHD2) via a trans-acting loss-of-function epigenetic mechanism. We discovered shared mutations and comparable DNA hypomethylation patterning between these distinct disorders. CRISPR/Cas9-mediated alteration of smchd1 in zebrafish yielded arhinia-relevant phenotypes. Transcriptome and protein analyses in arhinia probands and controls showed no differences in SMCHD1 mRNA or protein abundance but revealed regulatory changes in genes and pathways associated with craniofacial patterning. Mutations in SMCHD1 thus contribute to distinct phenotypic spectra, from craniofacial malformation and reproductive disorders to muscular dystrophy, which we speculate to be consistent with oligogenic mechanisms resulting in pleiotropic outcomes.
Keywords: Adolescent; Child; Child, Preschool; Choanal Atresia; Chromosomal Proteins, Non-Histone; Female; Genetic Predisposition to Disease; Humans; Infant; Male; Microphthalmos; Muscular Dystrophies; Mutation; Nose; Phenotype

Survival beyond the perinatal period expands the phenotypes caused by mutations in GLE1. - Said, Edith; Chong, Jessica X; Hempel, Maja; Denecke, Jonas; Soler, Paul; Strom, Tim; Nickerson, Deborah A; Kubisch, Christian; Bamshad, Michael J; Lessel, Davor (Am J Med Genet A, 2017)
Mutations in GLE1 underlie Lethal Congenital Contracture syndrome (LCCS) and Lethal Arthrogryposis with Anterior Horn Cell Disease (LAAHD). Both LCCS and LAAHD are characterized by reduced fetal movements, congenital contractures, and a severe form of motor neuron disease that results in fetal death or death in the perinatal period, respectively. We identified bi-allelic mutations in GLE1 in two unrelated individuals with motor delays, feeding difficulties, and respiratory insufficiency who survived beyond the perinatal period. Each affected child had missense variants predicted to result in amino acid substitutions near the C-terminus of GLE1 that are predicted to disrupt protein-protein interaction or GLE1 protein targeting. We hypothesize that mutations that preserve function of the coiled-coil domain of GLE1 cause LAAHD whereas mutations that abolish the function of the coiled-coil domain cause LCCS. The phenotype of LAAHD is now expanded to include multiple individuals surviving into childhood suggesting that LAAHD is a misnomer and should be re-named Arthrogryposis with Anterior Horn Cell Disease (AAHD).
Keywords: Arthrogryposis; Child, Preschool; Female; Genetic Predisposition to Disease; Humans; Male; Motor Disorders; Motor Neuron Disease; Mutation; Nucleocytoplasmic Transport Proteins; Pedigree; Pregnancy

Unraveling genetic predisposition to familial or early onset gastric cancer using germline whole-exome sequencing. - Vogelaar, Ingrid P; van der Post, Rachel S; van Krieken, J Han Jm; Spruijt, Liesbeth; van Zelst-Stams, Wendy Ag; Kets, C Marleen; Lubinski, Jan; Jakubowska, Anna; Teodorczyk, Urszula; Aalfs, Cora M; van Hest, Liselotte P; Pinheiro, Hugo; et al. (Eur J Hum Genet, 2017)
Recognition of individuals with a genetic predisposition to gastric cancer (GC) enables preventive measures. However, the underlying cause of genetic susceptibility to gastric cancer remains largely unexplained. We performed germline whole-exome sequencing on leukocyte DNA of 54 patients from 53 families with genetically unexplained diffuse-type and intestinal-type GC to identify novel GC-predisposing candidate genes. As young age at diagnosis and familial clustering are hallmarks of genetic tumor susceptibility, we selected patients that were diagnosed below the age of 35, patients from families with two cases of GC at or below age 60 and patients from families with three GC cases at or below age 70. All included individuals were tested negative for germline CDH1 mutations before or during the study. Variants that were possibly deleterious according to in silico predictions were filtered using several independent approaches that were based on gene function and gene mutation burden in controls. Despite a rigorous search, no obvious candidate GC predisposition genes were identified. This negative result stresses the importance of future research studies in large, homogeneous cohorts.
Keywords: Adult; Aged; Antigens, CD; Cadherins; Early Detection of Cancer; Exome; Female; Genetic Predisposition to Disease; Genetic Testing; Germ-Line Mutation; Humans; Male; Middle Aged; Sequence Analysis, DNA; Stomach Neoplasms

Whole exome sequencing in 342 congenital cardiac left sided lesion cases reveals extensive genetic heterogeneity and complex inheritance patterns. - Li, Alexander H; Hanchard, Neil A; Furthner, Dieter; Fernbach, Susan; Azamian, Mahshid; Nicosia, Annarita; Rosenfeld, Jill; Muzny, Donna; D'Alessandro, Lisa C A; Morris, Shaine; Jhangiani, Shalini; Parekh, Dhaval R; et al. (Genome Med, 2017)
BACKGROUND: Left-sided lesions (LSLs) account for an important fraction of severe congenital cardiovascular malformations (CVMs). The genetic contributions to LSLs are complex, and the mutations that cause these malformations span several diverse biological signaling pathways: TGFB, NOTCH, SHH, and more. Here, we use whole exome sequence data generated in 342 LSL cases to identify likely damaging variants in putative candidate CVM genes. METHODS: Using a series of bioinformatics filters, we focused on genes harboring population-rare, putative loss-of-function (LOF), and predicted damaging variants in 1760 CVM candidate genes constructed a priori from the literature and model organism databases. Gene variants that were not observed in a comparably sequenced control dataset of 5492 samples without severe CVM were then subjected to targeted validation in cases and parents. Whole exome sequencing data from 4593 individuals referred for clinical sequencing were used to bolster evidence for the role of candidate genes in CVMs and LSLs. RESULTS: Our analyses revealed 28 candidate variants in 27 genes, including 17 genes not previously associated with a human CVM disorder, and revealed diverse patterns of inheritance among LOF carriers, including 9 confirmed de novo variants in both novel and newly described human CVM candidate genes (ACVR1, JARID2, NR2F2, PLRG1, SMURF1) as well as established syndromic CVM genes (KMT2D, NF1, TBX20, ZEB2). We also identified two genes (DNAH5, OFD1) with evidence of recessive and hemizygous inheritance patterns, respectively. Within our clinical cohort, we also observed heterozygous LOF variants in JARID2 and SMAD1 in individuals with cardiac phenotypes, and collectively, carriers of LOF variants in our candidate genes had a four times higher odds of having CVM (odds ratio = 4.0, 95% confidence interval 2.5-6.5). CONCLUSIONS: Our analytical strategy highlights the utility of bioinformatic resources, including human disease records and model organism phenotyping, in novel gene discovery for rare human disease. The results underscore the extensive genetic heterogeneity underlying non-syndromic LSLs, and posit potential novel candidate genes and complex modes of inheritance in this important group of birth defects.
Keywords: Female; Genetic Heterogeneity; Heart Defects, Congenital; Humans; Inheritance Patterns; Male; Whole Exome Sequencing

Whole-exome sequencing in the molecular diagnosis of individuals with congenital anomalies of the kidney and urinary tract and identification of a new causative gene. - Bekheirnia, Mir Reza; Bekheirnia, Nasim; Bainbridge, Matthew N; Gu, Shen; Coban Akdemir, Zeynep Hande; Gambin, Tomek; Janzen, Nicolette K; Jhangiani, Shalini N; Muzny, Donna M; Michael, Mini; Brewer, Eileen D; Elenberg, Ewa; et al. (Genet Med, 2017)
PURPOSE: To investigate the utility of whole-exome sequencing (WES) to define a molecular diagnosis for patients clinically diagnosed with congenital anomalies of kidney and urinary tract (CAKUT). METHODS: WES was performed in 62 families with CAKUT. WES data were analyzed for single-nucleotide variants (SNVs) in 35 known CAKUT genes, putatively deleterious sequence changes in new candidate genes, and potentially disease-associated copy-number variants (CNVs). RESULTS: In approximately 5% of families, pathogenic SNVs were identified in PAX2, HNF1B, and EYA1. Observed phenotypes in these families expand the current understanding about the role of these genes in CAKUT. Four pathogenic CNVs were also identified using two CNV detection tools. In addition, we found one deleterious de novo SNV in FOXP1 among the 62 families with CAKUT. The clinical database of the Baylor Miraca Genetics laboratory was queried and seven additional unrelated individuals with novel de novo SNVs in FOXP1 were identified. Six of these eight individuals with FOXP1 SNVs have syndromic urinary tract defects, implicating this gene in urinary tract development. CONCLUSION: We conclude that WES can be used to identify molecular etiology (SNVs, CNVs) in a subset of individuals with CAKUT. WES can also help identify novel CAKUT genes.Genet Med 19 4, 412-420.
Keywords: Adolescent; Child; Child, Preschool; DNA Copy Number Variations; Exome Sequencing; Female; Forkhead Transcription Factors; Genetic Predisposition to Disease; Hepatocyte Nuclear Factor 1-beta; Humans; Infant; Intracellular Signaling Peptides and Proteins; Male; Nuclear Proteins; PAX2 Transcription Factor; Pedigree; Polymorphism, Single Nucleotide; Protein Tyrosine Phosphatases; Repressor Proteins; Urogenital Abnormalities; Vesico-Ureteral Reflux; Young Adult

Whole-Genome Sequencing of Cytogenetically Balanced Chromosome Translocations Identifies Potentially Pathological Gene Disruptions and Highlights the Importance of Microhomology in the Mechanism of Formation. - Nilsson, Daniel; Pettersson, Maria; Gustavsson, Peter; Förster, Alisa; Hofmeister, Wolfgang; Wincent, Josephine; Zachariadis, Vasilios; Anderlid, Britt-Marie; Nordgren, Ann; Mäkitie, Outi; Wirta, Valtteri; Käller, Max; et al. (Hum Mutat, 2017)
Most balanced translocations are thought to result mechanistically from nonhomologous end joining or, in rare cases of recurrent events, by nonallelic homologous recombination. Here, we use low-coverage mate pair whole-genome sequencing to fine map rearrangement breakpoint junctions in both phenotypically normal and affected translocation carriers. In total, 46 junctions from 22 carriers of balanced translocations were characterized. Genes were disrupted in 48% of the breakpoints; recessive genes in four normal carriers and known dominant intellectual disability genes in three affected carriers. Finally, seven candidate disease genes were disrupted in five carriers with neurocognitive disabilities (SVOPL, SUSD1, TOX, NCALD, SLC4A10) and one XX-male carrier with Tourette syndrome (LYPD6, GPC5). Breakpoint junction analyses revealed microhomology and small templated insertions in a substantive fraction of the analyzed translocations (17.4%; n = 4); an observation that was substantiated by reanalysis of 37 previously published translocation junctions. Microhomology associated with templated insertions is a characteristic seen in the breakpoint junctions of rearrangements mediated by error-prone replication-based repair mechanisms. Our data implicate that a mechanism involving template switching might contribute to the formation of at least 15% of the interchromosomal translocation events.
Keywords: Base Sequence; Chromosome Breakage; Chromosome Mapping; Comparative Genomic Hybridization; DNA Copy Number Variations; Female; Genetic Association Studies; Genomics; Genotype; Homologous Recombination; Humans; In Situ Hybridization, Fluorescence; Karyotype; Male; Phenotype; Translocation, Genetic; Whole Genome Sequencing

ACOX2 deficiency: A disorder of bile acid synthesis with transaminase elevation, liver fibrosis, ataxia, and cognitive impairment. - Vilarinho, Sílvia; Sari, Sinan; Mazzacuva, Francesca; Bilguvar, Kaya; Esendagli-Yilmaz, Güldal; Jain, Dhanpat; Akyol, Gülen; Dalgiç, Buket; Günel, Murat; Clayton, Peter T; Lifton, Richard P (Proc Natl Acad Sci U S A, 2016)
Acyl CoA Oxidase 2 (ACOX2) encodes branched-chain acyl-CoA oxidase, a peroxisomal enzyme believed to be involved in the metabolism of branched-chain fatty acids and bile acid intermediates. Deficiency of this enzyme has not been described previously. We report an 8-y-old male with intermittently elevated transaminase levels, liver fibrosis, mild ataxia, and cognitive impairment. Exome sequencing revealed a previously unidentified homozygous premature termination mutation (p.Y69*) in ACOX2 Immunohistochemistry confirmed the absence of ACOX2 expression in the patient's liver, and biochemical analysis showed marked elevation of intermediate bile acids upstream of ACOX2. These findings define a potentially treatable inborn error of bile acid biosynthesis caused by ACOX2 deficiency.
Keywords: Ataxia; Bile Acids and Salts; Child; Cognitive Dysfunction; Homozygote; Humans; Infant; Infant, Newborn; Liver; Liver Cirrhosis; Loss of Function Mutation; Male; Mutation; Oxidation-Reduction; Oxidoreductases; Transaminases

Aggressive tumor growth and clinical evolution in a patient with X-linked acro-gigantism syndrome. - Naves, Luciana A; Daly, Adrian F; Dias, Luiz Augusto; Yuan, Bo; Zakir, Juliano Coelho Oliveira; Barra, Gustavo Barcellos; Palmeira, Leonor; Villa, Chiara; Trivellin, Giampaolo; Júnior, Armindo Jreige; Neto, Florêncio Figueiredo Cavalcante; Liu, Pengfei; et al. (Endocrine, 2016)
X-linked acro-gigantism (X-LAG) syndrome is a newly described disease caused by microduplications on chromosome Xq26.3 leading to copy number gain of GPR101. We describe the clinical progress of a sporadic male X-LAG syndrome patient with an Xq26.3 microduplication, highlighting the aggressive natural history of pituitary tumor growth in the absence of treatment. The patient first presented elsewhere aged 5 years 8 months with a history of excessive growth for >2 years. His height was 163 cm, his weight was 36 kg, and he had markedly elevated GH and IGF-1. MRI showed a non-invasive sellar mass measuring 32.5 × 23.9 × 29.1 mm. Treatment was declined and the family was lost to follow-up. At the age of 10 years and 7 months, he presented again with headaches, seizures, and visual disturbance. His height had increased to 197 cm. MRI showed an invasive mass measuring 56.2 × 58.1 × 45.0 mm, with compression of optic chiasma, bilateral cavernous sinus invasion, and hydrocephalus. His thyrotrope, corticotrope, and gonadotrope axes were deficient. Surgery, somatostatin analogs, and cabergoline did not control vertical growth and pegvisomant was added, although vertical growth continues (currently 207 cm at 11 years 7 months of age). X-LAG syndrome is a new genomic disorder in which early-onset pituitary tumorigenesis can lead to marked overgrowth and gigantism. This case illustrates the aggressive nature of tumor evolution and the challenging clinical management in X-LAG syndrome.
Keywords: Adenoma; Child; Genetic Diseases, X-Linked; Gigantism; Humans; Male; Pituitary Neoplasms; Treatment Outcome

ALG1-CDG: Clinical and Molecular Characterization of 39 Unreported Patients. - Ng, Bobby G; Shiryaev, Sergey A; Rymen, Daisy; Eklund, Erik A; Raymond, Kimiyo; Kircher, Martin; Abdenur, Jose E; Alehan, Fusun; Midro, Alina T; Bamshad, Michael J; Barone, Rita; Berry, Gerard T; et al. (Hum Mutat, 2016)
Congenital disorders of glycosylation (CDG) arise from pathogenic mutations in over 100 genes leading to impaired protein or lipid glycosylation. ALG1 encodes a β1,4 mannosyltransferase that catalyzes the addition of the first of nine mannose moieties to form a dolichol-lipid linked oligosaccharide intermediate required for proper N-linked glycosylation. ALG1 mutations cause a rare autosomal recessive disorder termed ALG1-CDG. To date 13 mutations in 18 patients from 14 families have been described with varying degrees of clinical severity. We identified and characterized 39 previously unreported cases of ALG1-CDG from 32 families and add 26 new mutations. Pathogenicity of each mutation was confirmed based on its inability to rescue impaired growth or hypoglycosylation of a standard biomarker in an alg1-deficient yeast strain. Using this approach we could not establish a rank order comparison of biomarker glycosylation and patient phenotype, but we identified mutations with a lethal outcome in the first two years of life. The recently identified protein-linked xeno-tetrasaccharide biomarker, NeuAc-Gal-GlcNAc2 , was seen in all 27 patients tested. Our study triples the number of known patients and expands the molecular and clinical correlates of this disorder.
Keywords: Biomarkers; Congenital Disorders of Glycosylation; Female; Genes, Lethal; Glycosylation; Humans; Male; Mannosyltransferases; Mutation; Polysaccharides; Sequence Analysis, DNA; Survival Analysis

Asprosin, a Fasting-Induced Glucogenic Protein Hormone. - Romere, Chase; Duerrschmid, Clemens; Bournat, Juan; Constable, Petra; Jain, Mahim; Xia, Fan; Saha, Pradip K; Del Solar, Maria; Zhu, Bokai; York, Brian; Sarkar, Poonam; Rendon, David A; et al. (Cell, 2016)
Hepatic glucose release into the circulation is vital for brain function and survival during periods of fasting and is modulated by an array of hormones that precisely regulate plasma glucose levels. We have identified a fasting-induced protein hormone that modulates hepatic glucose release. It is the C-terminal cleavage product of profibrillin, and we name it Asprosin. Asprosin is secreted by white adipose, circulates at nanomolar levels, and is recruited to the liver, where it activates the G protein-cAMP-PKA pathway, resulting in rapid glucose release into the circulation. Humans and mice with insulin resistance show pathologically elevated plasma asprosin, and its loss of function via immunologic or genetic means has a profound glucose- and insulin-lowering effect secondary to reduced hepatic glucose release. Asprosin represents a glucogenic protein hormone, and therapeutically targeting it may be beneficial in type II diabetes and metabolic syndrome.
Keywords: Adipose Tissue, White; Amino Acid Sequence; Animals; Antibodies; Circadian Rhythm; Cyclic AMP; Cyclic AMP-Dependent Protein Kinases; Fasting; Female; Fetal Growth Retardation; Glucose; Humans; Insulin; Liver; Male; Mice; Mice, Inbred C57BL; Mice, Obese; Microfilament Proteins; Molecular Sequence Data; Peptide Fragments; Peptide Hormones; Progeria; Recombinant Proteins; Sequence Alignment

Assessment of estimated retinal atrophy progression in Stargardt macular dystrophy using spectral-domain optical coherence tomography. - Strauss, Rupert W; Muñoz, Beatriz; Wolfson, Yulia; Sophie, Raafay; Fletcher, Emily; Bittencourt, Millena G; Scholl, Hendrik P N (Br J Ophthalmol, 2016)
AIMS: To estimate disease progression based on analysis of macular volume measured by spectral-domain optical coherence tomography (SD-OCT) in patients affected by Stargardt macular dystrophy (STGD1) and to evaluate the influence of software errors on these measurements. METHODS: 58 eyes of 29 STGD1 patients were included. Numbers and types of algorithm errors were recorded and manually corrected. In a subgroup of 36 eyes of 18 patients with at least two examinations over time, total macular volume (TMV) and volumes of all nine Early Treatment of Diabetic Retinopathy Study (ETDRS) subfields were obtained. Random effects models were used to estimate the rate of change per year for the population, and empirical Bayes slopes were used to estimate yearly decline in TMV for individual eyes. RESULTS: 6958 single B-scans from 190 macular cube scans were analysed. 2360 (33.9%) showed algorithm errors. Mean observation period for follow-up data was 15 months (range 3-40). The median (IQR) change in TMV using the empirical Bayes estimates for the individual eyes was -0.103 (-0.145, -0.059) mm per year. The mean (±SD) TMV was 6.321±1.000 mm at baseline, and rate of decline was -0.118 mm per year (p=0.003). Yearly mean volume change was -0.004 mm in the central subfield (mean baseline=0.128 mm), -0.032 mm in the inner (mean baseline=1.484 mm) and -0.079 mm in the outer ETDRS subfields (mean baseline=5.206 mm). CONCLUSIONS: SD-OCT measurements allow monitoring the decline in retinal volume in STGD1; however, they require significant manual correction of software errors.
Keywords: Adolescent; Adult; Aged; Child; Disease Progression; Female; Humans; Macula Lutea; Macular Degeneration; Male; Middle Aged; Reproducibility of Results; Retrospective Studies; Tomography, Optical Coherence; Visual Acuity; Young Adult

Association Between Absolute Neutrophil Count and Variation at TCIRG1: The NHLBI Exome Sequencing Project. - Rosenthal, Elisabeth A; Makaryan, Vahagn; Burt, Amber A; Crosslin, David R; Kim, Daniel Seung; Smith, Joshua D; Nickerson, Deborah A; Reiner, Alex P; Rich, Stephen S; Jackson, Rebecca D; Ganesh, Santhi K; Polfus, Linda M; et al. (Genet Epidemiol, 2016)
Neutrophils are a key component of innate immunity. Individuals with low neutrophil count are susceptible to frequent infections. Linkage and association between congenital neutropenia and a single rare missense variant in TCIRG1 have been reported in a single family. Here, we report on nine rare missense variants at evolutionarily conserved sites in TCIRG1 that are associated with lower absolute neutrophil count (ANC; p = 0.005) in 1,058 participants from three cohorts: Atherosclerosis Risk in Communities (ARIC), Coronary Artery Risk Development in Young Adults (CARDIA), and Jackson Heart Study (JHS) of the NHLBI Grand Opportunity Exome Sequencing Project (GO ESP). These results validate the effects of TCIRG1 coding variation on ANC and suggest that this gene may be associated with a spectrum of mild to severe effects on ANC.
Keywords: Adult; Aged; Aged, 80 and over; Alleles; Cohort Studies; Female; Gene Frequency; Genotype; High-Throughput Nucleotide Sequencing; Humans; Leukocyte Count; Male; Middle Aged; Mutation, Missense; National Heart, Lung, and Blood Institute (U.S.); Neutropenia; Neutrophils; Sequence Analysis, DNA; United States; Vacuolar Proton-Translocating ATPases

Association of MTOR Mutations With Developmental Brain Disorders, Including Megalencephaly, Focal Cortical Dysplasia, and Pigmentary Mosaicism. - Mirzaa, Ghayda M; Campbell, Catarina D; Solovieff, Nadia; Goold, Carleton; Jansen, Laura A; Menon, Suchithra; Timms, Andrew E; Conti, Valerio; Biag, Jonathan D; Adams, Carissa; Boyle, Evan August; Collins, Sarah; et al. (JAMA Neurol, 2016)
IMPORTANCE: Focal cortical dysplasia (FCD), hemimegalencephaly, and megalencephaly constitute a spectrum of malformations of cortical development with shared neuropathologic features. These disorders are associated with significant childhood morbidity and mortality. OBJECTIVE: To identify the underlying molecular cause of FCD, hemimegalencephaly, and diffuse megalencephaly. DESIGN, SETTING, AND PARTICIPANTS: Patients with FCD, hemimegalencephaly, or megalencephaly (mean age, 11.7 years; range, 2-32 years) were recruited from Pediatric Hospital A. Meyer, the University of Hong Kong, and Seattle Children's Research Institute from June 2012 to June 2014. Whole-exome sequencing (WES) was performed on 8 children with FCD or hemimegalencephaly using standard-depth (50-60X) sequencing in peripheral samples (blood, saliva, or skin) from the affected child and their parents and deep (150-180X) sequencing in affected brain tissue. Targeted sequencing and WES were used to screen 93 children with molecularly unexplained diffuse or focal brain overgrowth. Histopathologic and functional assays of phosphatidylinositol 3-kinase-AKT (serine/threonine kinase)-mammalian target of rapamycin (mTOR) pathway activity in resected brain tissue and cultured neurons were performed to validate mutations. MAIN OUTCOMES AND MEASURES: Whole-exome sequencing and targeted sequencing identified variants associated with this spectrum of developmental brain disorders. RESULTS: Low-level mosaic mutations of MTOR were identified in brain tissue in 4 children with FCD type 2a with alternative allele fractions ranging from 0.012 to 0.086. Intermediate-level mosaic mutation of MTOR (p.Thr1977Ile) was also identified in 3 unrelated children with diffuse megalencephaly and pigmentary mosaicism in skin. Finally, a constitutional de novo mutation of MTOR (p.Glu1799Lys) was identified in 3 unrelated children with diffuse megalencephaly and intellectual disability. Molecular and functional analysis in 2 children with FCD2a from whom multiple affected brain tissue samples were available revealed a mutation gradient with an epicenter in the most epileptogenic area. When expressed in cultured neurons, all MTOR mutations identified here drive constitutive activation of mTOR complex 1 and enlarged neuronal size. CONCLUSIONS AND RELEVANCE: In this study, mutations of MTOR were associated with a spectrum of brain overgrowth phenotypes extending from FCD type 2a to diffuse megalencephaly, distinguished by different mutations and levels of mosaicism. These mutations may be sufficient to cause cellular hypertrophy in cultured neurons and may provide a demonstration of the pattern of mosaicism in brain and substantiate the link between mosaic mutations of MTOR and pigmentary mosaicism in skin.
Keywords: Adolescent; Adult; Amino Acids; Animals; Cells, Cultured; Cerebral Cortex; Child; Child, Preschool; Developmental Disabilities; Embryo, Mammalian; Female; Gene Expression Regulation; Genetic Association Studies; Humans; Intercellular Signaling Peptides and Proteins; Male; Malformations of Cortical Development; Mechanistic Target of Rapamycin Complex 1; Megalencephaly; Mosaicism; Multiprotein Complexes; Mutation; Nerve Tissue Proteins; Neurons; Rats; Retrospective Studies; TOR Serine-Threonine Kinases; Young Adult

Ataxia-Pancytopenia Syndrome Is Caused by Missense Mutations in SAMD9L. - Chen, Dong-Hui; Below, Jennifer E; Shimamura, Akiko; Keel, Sioban B; Matsushita, Mark; Wolff, John; Sul, Youngmee; Bonkowski, Emily; Castella, Maria; Taniguchi, Toshiyasu; Nickerson, Deborah; Papayannopoulou, Thalia; et al. (Am J Hum Genet, 2016)
Ataxia-pancytopenia (AP) syndrome is characterized by cerebellar ataxia, variable hematologic cytopenias, and predisposition to marrow failure and myeloid leukemia, sometimes associated with monosomy 7. Here, in the four-generation family UW-AP, linkage analysis revealed four regions that provided the maximal LOD scores possible, one of which was in a commonly microdeleted chromosome 7q region. Exome sequencing identified a missense mutation (c.2640C>A, p.His880Gln) in the sterile alpha motif domain containing 9-like gene (SAMD9L) that completely cosegregated with disease. By targeted sequencing of SAMD9L, we subsequently identified a different missense mutation (c.3587G>C, p.Cys1196Ser) in affected members of the first described family with AP syndrome, Li-AP. Neither variant is reported in the public databases, both affect highly conserved amino acid residues, and both are predicted to be damaging. With time in culture, lymphoblastic cell lines (LCLs) from two affected individuals in family UW-AP exhibited copy-neutral loss of heterozygosity for large portions of the long arm of chromosome 7, resulting in retention of only the wild-type SAMD9L allele. Newly established LCLs from both individuals demonstrated the same phenomenon. In addition, targeted capture and sequencing of SAMD9L in uncultured blood DNA from both individuals showed bias toward the wild-type allele. These observations indicate in vivo hematopoietic mosaicism. The hematopoietic cytopenias that characterize AP syndrome and the selective advantage for clones that have lost the mutant allele support the postulated role of SAMD9L in the regulation of cell proliferation. Furthermore, we show that AP syndrome is distinct from the dyskeratoses congenita telomeropathies, with which it shares some clinical characteristics.
Keywords: Adolescent; Adult; Cerebellar Ataxia; Child; Chromosome Aberrations; Chromosomes, Human, Pair 7; Exome; Female; Genetic Linkage; Genotype; High-Throughput Nucleotide Sequencing; Humans; Intracellular Signaling Peptides and Proteins; Loss of Heterozygosity; Male; Middle Aged; Mutation, Missense; Pancytopenia; Pedigree; Proteins; Tumor Suppressor Proteins; Young Adult

Biallelic Mutations in Citron Kinase Link Mitotic Cytokinesis to Human Primary Microcephaly. - Li, Hongda; Bielas, Stephanie L; Zaki, Maha S; Ismail, Samira; Farfara, Dorit; Um, Kyongmi; Rosti, Rasim O; Scott, Eric C; Tu, Shu; Chi, Neil C; Gabriel, Stacey; Erson-Omay, Emine Z; et al. (Am J Hum Genet, 2016)
Cell division terminates with cytokinesis and cellular separation. Autosomal-recessive primary microcephaly (MCPH) is a neurodevelopmental disorder characterized by a reduction in brain and head size at birth in addition to non-progressive intellectual disability. MCPH is genetically heterogeneous, and 16 loci are known to be associated with loss-of-function mutations predominantly affecting centrosomal-associated proteins, but the multiple roles of centrosomes in cellular function has left questions about etiology. Here, we identified three families affected by homozygous missense mutations in CIT, encoding citron rho-interacting kinase (CIT), which has established roles in cytokinesis. All mutations caused substitution of conserved amino acid residues in the kinase domain and impaired kinase activity. Neural progenitors that were differentiated from induced pluripotent stem cells (iPSCs) derived from individuals with these mutations exhibited abnormal cytokinesis with delayed mitosis, multipolar spindles, and increased apoptosis, rescued by CRISPR/Cas9 genome editing. Our results highlight the importance of cytokinesis in the pathology of primary microcephaly.
Keywords: Alleles; Apoptosis; Centrosome; Child; Child, Preschool; Cytokinesis; Female; Genes, Recessive; Humans; Infant, Newborn; Intracellular Signaling Peptides and Proteins; Male; Microcephaly; Mitosis; Mutation, Missense; Pedigree; Protein Serine-Threonine Kinases

Bi-allelic Mutations in PKD1L1 Are Associated with Laterality Defects in Humans. - Vetrini, Francesco; D'Alessandro, Lisa C A; Akdemir, Zeynep C; Braxton, Alicia; Azamian, Mahshid S; Eldomery, Mohammad K; Miller, Kathryn; Kois, Chelsea; Sack, Virginia; Shur, Natasha; Rijhsinghani, Asha; Chandarana, Jignesh; et al. (Am J Hum Genet, 2016)
Disruption of the establishment of left-right (L-R) asymmetry leads to situs anomalies ranging from situs inversus totalis (SIT) to situs ambiguus (heterotaxy). The genetic causes of laterality defects in humans are highly heterogeneous. Via whole-exome sequencing (WES), we identified homozygous mutations in PKD1L1 from three affected individuals in two unrelated families. PKD1L1 encodes a polycystin-1-like protein and its loss of function is known to cause laterality defects in mouse and medaka fish models. Family 1 had one fetus and one deceased child with heterotaxy and complex congenital heart malformations. WES identified a homozygous splicing mutation, c.6473+2_6473+3delTG, which disrupts the invariant splice donor site in intron 42, in both affected individuals. In the second family, a homozygous c.5072G>C (p.Cys1691Ser) missense mutation was detected in an individual with SIT and congenital heart disease. The p.Cys1691Ser substitution affects a highly conserved cysteine residue and is predicted by molecular modeling to disrupt a disulfide bridge essential for the proper folding of the G protein-coupled receptor proteolytic site (GPS) motif. Damaging effects associated with substitutions of this conserved cysteine residue in the GPS motif have also been reported in other genes, namely GPR56, BAI3, and PKD1 in human and lat-1 in C. elegans, further supporting the likely pathogenicity of p.Cys1691Ser in PKD1L1. The identification of bi-allelic PKD1L1 mutations recapitulates previous findings regarding phenotypic consequences of loss of function of the orthologous genes in mice and medaka fish and further expands our understanding of genetic contributions to laterality defects in humans.
Keywords: Alleles; Amino Acid Motifs; Amino Acid Sequence; Animals; Caenorhabditis elegans; Cysteine; Exome; Female; Fetal Diseases; Functional Laterality; Heart Defects, Congenital; Heterotaxy Syndrome; Homozygote; Humans; Infant, Newborn; Introns; Male; Membrane Proteins; Mice; Middle Aged; Models, Molecular; Mutation; Mutation, Missense; Oryzias; Pedigree; RNA Splicing; Situs Inversus

Biallelic Mutations in TMTC3, Encoding a Transmembrane and TPR-Containing Protein, Lead to Cobblestone Lissencephaly. - Jerber, Julie; Zaki, Maha S; Al-Aama, Jumana Y; Rosti, Rasim Ozgur; Ben-Omran, Tawfeg; Dikoglu, Esra; Silhavy, Jennifer L; Caglar, Caner; Musaev, Damir; Albrecht, Beate; Campbell, Kevin P; Willer, Tobias; et al. (Am J Hum Genet, 2016)
Cobblestone lissencephaly (COB) is a severe brain malformation in which overmigration of neurons and glial cells into the arachnoid space results in the formation of cortical dysplasia. COB occurs in a wide range of genetic disorders known as dystroglycanopathies, which are congenital muscular dystrophies associated with brain and eye anomalies and range from Walker-Warburg syndrome to Fukuyama congenital muscular dystrophy. Each of these conditions has been associated with alpha-dystroglycan defects or with mutations in genes encoding basement membrane components, which are known to interact with alpha-dystroglycan. Our screening of a cohort of 25 families with recessive forms of COB identified six families affected by biallelic mutations in TMTC3 (encoding transmembrane and tetratricopeptide repeat containing 3), a gene without obvious functional connections to alpha-dystroglycan. Most affected individuals showed brainstem and cerebellum hypoplasia, as well as ventriculomegaly. However, the minority of the affected individuals had eye defects or elevated muscle creatine phosphokinase, separating the TMTC3 COB phenotype from typical congenital muscular dystrophies. Our data suggest that loss of TMTC3 causes COB with minimal eye or muscle involvement.
Keywords: Alleles; Amino Acid Sequence; Basement Membrane; Brain; Carrier Proteins; Cerebellum; Cobblestone Lissencephaly; Developmental Disabilities; Dystroglycans; Eye Abnormalities; Female; Humans; Infant; Male; Membrane Proteins; Mutation; Nervous System Malformations; Neuroglia; Neurons; Pedigree; Phenotype

Chimeric transcripts resulting from complex duplications in chromosome Xq28. - Zuccherato, Luciana W; Alleva, Benjamin; Whiters, Marjorie A; Carvalho, Claudia M B; Lupski, James R (Hum Genet, 2016)
Gene fusions have been observed in somatic alterations in cancer and in schizophrenia. However, the underlying mechanism(s) for their formation are poorly understood. We experimentally demonstrated the expression of splicing variants of in silico predicted chimeric genes F8/CSAG1 and BCAP31/TEX28 in two individuals with de novo complex genomic rearrangements of Xq28; F8/CSAG1 includes exonization of an ERVL-MaLR intronic repetitive element. We provide evidence that replicative repair may contribute to exon shuffling processes and diversify the repertoire of expressed transcripts.
Keywords: Antigens, Neoplasm; Base Sequence; Cell Line; Chromosomes, Human, X; Exons; Gene Duplication; Gene Expression Regulation; Gene Rearrangement; Humans; Introns; Male; Membrane Proteins; Molecular Sequence Data; Neoplasm Proteins; RNA Splicing; RNA, Messenger; Transcription, Genetic

Comparison of Short-Wavelength Reduced-Illuminance and Conventional Autofluorescence Imaging in Stargardt Macular Dystrophy. - Strauss, Rupert W; Muñoz, Beatriz; Jha, Anamika; Ho, Alexander; Cideciyan, Artur V; Kasilian, Melissa L; Wolfson, Yulia; Sadda, SriniVas; West, Sheila; Scholl, Hendrik P N; Michaelides, Michel (Am J Ophthalmol, 2016)
PURPOSE: To compare grading results between short-wavelength reduced-illuminance and conventional autofluorescence imaging in Stargardt macular dystrophy. DESIGN: Reliability study. METHODS: setting: Moorfields Eye Hospital, London (United Kingdom). PATIENTS: Eighteen patients (18 eyes) with Stargardt macular dystrophy. OBSERVATION PROCEDURES: A series of 3 fundus autofluorescence images using 3 different acquisition parameters on a custom-patched device were obtained: (1) 25% laser power and total sensitivity 87; (2) 25% laser power and freely adjusted sensitivity; and (3) 100% laser power and freely adjusted total sensitivity (conventional). The total area of 2 hypoautofluorescent lesion types (definitely decreased autofluorescence and poorly demarcated questionably decreased autofluorescence) was measured. MAIN OUTCOME MEASURES: Agreement in grading between the 3 imaging methods was assessed by kappa coefficients (κ) and intraclass correlation coefficients. RESULTS: The mean ± standard deviation area for images acquired with 25% laser power and freely adjusted total sensitivity was 2.04 ± 1.87 mm(2) for definitely decreased autofluorescence (n = 15) and 1.86 ± 2.14 mm(2) for poorly demarcated questionably decreased autofluorescence (n = 12). The intraclass correlation coefficient (95% confidence interval) was 0.964 (0.929, 0.999) for definitely decreased autofluorescence and 0.268 (0.000, 0.730) for poorly demarcated questionably decreased autofluorescence. CONCLUSIONS: Short-wavelength reduced-illuminance and conventional fundus autofluorescence imaging showed good concordance in assessing areas of definitely decreased autofluorescence. However, there was significantly higher variability between imaging modalities for assessing areas of poorly demarcated questionably decreased autofluorescence.
Keywords: Adult; Female; Fluorescein Angiography; Fundus Oculi; Humans; Macula Lutea; Macular Degeneration; Male; Middle Aged; Ophthalmoscopy; Optical Imaging; Reproducibility of Results; Stargardt Disease

Complex inheritance of ABCA4 disease: four mutations in a family with multiple macular phenotypes. - Lee, Winston; Xie, Yajing; Zernant, Jana; Yuan, Bo; Bearelly, Srilaxmi; Tsang, Stephen H; Lupski, James R; Allikmets, Rando (Hum Genet, 2016)
Over 800 mutations in the ABCA4 gene cause autosomal recessive Stargardt disease. Due to extensive genetic heterogeneity, observed variant-associated phenotypes can manifest tremendous variability of expression. Furthermore, the high carrier frequency of pathogenic ABCA4 alleles in the general population (~1:20) often results in pseudo-dominant inheritance patterns further complicating the diagnosis and characterization of affected individuals. This study describes a genotype/phenotype analysis of an unusual family with multiple macular disease phenotypes spanning across two generations and segregating four distinct ABCA4 mutant alleles. Complete sequencing of ABCA4 discovered two known missense mutations, p.C54Y and p.G1961E. Array comparative genomic hybridization revealed a large novel deletion combined with a small insertion, c.6148-698_c.6670del/insTGTGCACCTCCCTAG, and complete sequencing of the entire ABCA4 genomic locus uncovered a new deep intronic variant, c.302+68C>T. Patients with the p.G1961E mutation had the mildest, confined maculopathy phenotype with peripheral flecks while those with all other mutant allele combinations exhibited a more advanced stage of generalized retinal and choriocapillaris atrophy. This family epitomizes the clinical and genetic complexity of ABCA4-associated diseases. It contained variants from all classes of mutations, in the coding region, deep intronic, both single nucleotide variants and copy number variants that accounted for varying phenotypes segregating in an apparent dominant fashion. Unequivocally defining disease-associated alleles in the ABCA4 locus requires a multifaceted approach that includes advanced mutation detection methods and a thorough analysis of clinical phenotypes.
Keywords: Adult; Aged; ATP-Binding Cassette Transporters; Comparative Genomic Hybridization; DNA Copy Number Variations; Electroretinography; Female; High-Throughput Nucleotide Sequencing; Humans; Macula Lutea; Macular Degeneration; Male; Middle Aged; Mutation; Pedigree; Phenotype

Congenital nephrotic syndrome in an infant with ALG1-congenital disorder of glycosylation. - Harshman, Lyndsay A; Ng, Bobby G; Freeze, Hudson H; Trapane, Pamela; Dolezal, Anna; Brophy, Patrick D; Brumbaugh, Jane E (Pediatr Int, 2016)
Congenital nephrotic syndrome (NS) in the newborn is most frequently related to mutations in genes specific for structural integrity of the glomerular basement membrane and associated filtration structures within the kidney, resulting in massive leakage of plasma proteins into the urine. Occurrence of congenital NS in a multi-system syndrome is less common. We describe the case of an infant with deteriorating neurological status, seizures, edema, and proteinuria who was found to have a mutation in gene ALG1 and a renal biopsy consistent with congenital NS. Furthermore, we briefly review rare existing case reports documenting congenital NS in patients with mutations in ALG1, and treatment strategies, including novel use of peritoneal dialysis.
Keywords: Abnormalities, Multiple; Congenital Disorders of Glycosylation; DNA; DNA Mutational Analysis; Glycosylation; Humans; Infant, Newborn; Male; Mannosyltransferases; Mutation; Nephrotic Syndrome; Peritoneal Dialysis

Copy-Number Variation Contributes to the Mutational Load of Bardet-Biedl Syndrome. - Lindstrand, Anna; Frangakis, Stephan; Carvalho, Claudia M B; Richardson, Ellen B; McFadden, Kelsey A; Willer, Jason R; Pehlivan, Davut; Liu, Pengfei; Pediaditakis, Igor L; Sabo, Aniko; Lewis, Richard Alan; Banin, Eyal; et al. (Am J Hum Genet, 2016)
Bardet-Biedl syndrome (BBS) is a defining ciliopathy, notable for extensive allelic and genetic heterogeneity, almost all of which has been identified through sequencing. Recent data have suggested that copy-number variants (CNVs) also contribute to BBS. We used a custom oligonucleotide array comparative genomic hybridization (aCGH) covering 20 genes that encode intraflagellar transport (IFT) components and 74 ciliopathy loci to screen 92 unrelated individuals with BBS, irrespective of their known mutational burden. We identified 17 individuals with exon-disruptive CNVs (18.5%), including 13 different deletions in eight BBS genes (BBS1, BBS2, ARL6/BBS3, BBS4, BBS5, BBS7, BBS9, and NPHP1) and a deletion and a duplication in other ciliopathy-associated genes (ALMS1 and NPHP4, respectively). By contrast, we found a single heterozygous exon-disruptive event in a BBS-associated gene (BBS9) in 229 control subjects. Superimposing these data with resequencing revealed CNVs to (1) be sufficient to cause disease, (2) Mendelize heterozygous deleterious alleles, and (3) contribute oligogenic alleles by combining point mutations and exonic CNVs in multiple genes. Finally, we report a deletion and a splice site mutation in IFT74, inherited under a recessive paradigm, defining a candidate BBS locus. Our data suggest that CNVs contribute pathogenic alleles to a substantial fraction of BBS-affected individuals and highlight how either deletions or point mutations in discrete splice isoforms can induce hypomorphic mutations in genes otherwise intolerant to deleterious variation. Our data also suggest that CNV analyses and resequencing studies unbiased for previous mutational burden is necessary to delineate the complexity of disease architecture.
Keywords: Adolescent; Adult; Alleles; Animals; Bardet-Biedl Syndrome; Child; Child, Preschool; Chromosome Breakpoints; Cytoskeletal Proteins; DNA Copy Number Variations; Exons; Female; Gastrulation; Genes, Recessive; Humans; Infant; Male; Mutation; Pedigree; Young Adult; Zebrafish; Zebrafish Proteins

De Novo and Rare Variants at Multiple Loci Support the Oligogenic Origins of Atrioventricular Septal Heart Defects. - Priest, James R; Osoegawa, Kazutoyo; Mohammed, Nebil; Nanda, Vivek; Kundu, Ramendra; Schultz, Kathleen; Lammer, Edward J; Girirajan, Santhosh; Scheetz, Todd; Waggott, Daryl; Haddad, Francois; Reddy, Sushma; et al. (PLoS Genet, 2016)
Congenital heart disease (CHD) has a complex genetic etiology, and recent studies suggest that high penetrance de novo mutations may account for only a small fraction of disease. In a multi-institutional cohort surveyed by exome sequencing, combining analysis of 987 individuals (discovery cohort of 59 affected trios and 59 control trios, and a replication cohort of 100 affected singletons and 533 unaffected singletons) we observe variation at novel and known loci related to a specific cardiac malformation the atrioventricular septal defect (AVSD). In a primary analysis, by combining developmental coexpression networks with inheritance modeling, we identify a de novo mutation in the DNA binding domain of NR1D2 (p.R175W). We show that p.R175W changes the transcriptional activity of Nr1d2 using an in vitro transactivation model in HUVEC cells. Finally, we demonstrate previously unrecognized cardiovascular malformations in the Nr1d2tm1-Dgen knockout mouse. In secondary analyses we map genetic variation to protein-interaction networks suggesting a role for two collagen genes in AVSD, which we corroborate by burden testing in a second replication cohort of 100 AVSDs and 533 controls (p = 8.37e-08). Finally, we apply a rare-disease inheritance model to identify variation in genes previously associated with CHD (ZFPM2, NSD1, NOTCH1, VCAN, and MYH6), cardiac malformations in mouse models (ADAM17, CHRD, IFT140, PTPRJ, RYR1 and ATE1), and hypomorphic alleles of genes causing syndromic CHD (EHMT1, SRCAP, BBS2, NOTCH2, and KMT2D) in 14 of 59 trios, greatly exceeding variation in control trios without CHD (p = 9.60e-06). In total, 32% of trios carried at least one putatively disease-associated variant across 19 loci,suggesting that inherited and de novo variation across a heterogeneous group of loci may contribute to disease risk.
Keywords: Animals; Female; Heart Septal Defects; Heterozygote; Homozygote; Humans; Male; Mice; Mice, Knockout; Mutation; Pedigree

De novo missense variants in PPP1CB are associated with intellectual disability and congenital heart disease. - Ma, Lijiang; Bayram, Yavuz; McLaughlin, Heather M; Cho, Megan T; Krokosky, Alyson; Turner, Clesson E; Lindstrom, Kristin; Bupp, Caleb P; Mayberry, Katey; Mu, Weiyi; Bodurtha, Joann; Weinstein, Veronique; et al. (Hum Genet, 2016)
Intellectual disabilities are genetically heterogeneous and can be associated with congenital anomalies. Using whole-exome sequencing (WES), we identified five different de novo missense variants in the protein phosphatase-1 catalytic subunit beta (PPP1CB) gene in eight unrelated individuals who share an overlapping phenotype of dysmorphic features, macrocephaly, developmental delay or intellectual disability (ID), congenital heart disease, short stature, and skeletal and connective tissue abnormalities. Protein phosphatase-1 (PP1) is a serine/threonine-specific protein phosphatase involved in the dephosphorylation of a variety of proteins. The PPP1CB gene encodes a PP1 subunit that regulates the level of protein phosphorylation. All five altered amino acids we observed are highly conserved among the PP1 subunit family, and all are predicted to disrupt PP1 subunit binding and impair dephosphorylation. Our data suggest that our heterozygous de novo PPP1CB pathogenic variants are associated with syndromic intellectual disability.
Keywords: Adolescent; Adult; Child; Child, Preschool; Exome; Female; Genetic Association Studies; Genetic Predisposition to Disease; Heart Defects, Congenital; Humans; Intellectual Disability; Male; Mutation, Missense; Phosphorylation; Protein Phosphatase 1

De Novo Mutations in SON Disrupt RNA Splicing of Genes Essential for Brain Development and Metabolism, Causing an Intellectual-Disability Syndrome. - Kim, Jung-Hyun; Shinde, Deepali N; Reijnders, Margot R F; Hauser, Natalie S; Belmonte, Rebecca L; Wilson, Gregory R; Bosch, Daniëlle G M; Bubulya, Paula A; Shashi, Vandana; Petrovski, Slavé; Stone, Joshua K; Park, Eun Young; et al. (Am J Hum Genet, 2016)
The overall understanding of the molecular etiologies of intellectual disability (ID) and developmental delay (DD) is increasing as next-generation sequencing technologies identify genetic variants in individuals with such disorders. However, detailed analyses conclusively confirming these variants, as well as the underlying molecular mechanisms explaining the diseases, are often lacking. Here, we report on an ID syndrome caused by de novo heterozygous loss-of-function (LoF) mutations in SON. The syndrome is characterized by ID and/or DD, malformations of the cerebral cortex, epilepsy, vision problems, musculoskeletal abnormalities, and congenital malformations. Knockdown of son in zebrafish resulted in severe malformation of the spine, brain, and eyes. Importantly, analyses of RNA from affected individuals revealed that genes critical for neuronal migration and cortex organization (TUBG1, FLNA, PNKP, WDR62, PSMD3, and HDAC6) and metabolism (PCK2, PFKL, IDH2, ACY1, and ADA) are significantly downregulated because of the accumulation of mis-spliced transcripts resulting from erroneous SON-mediated RNA splicing. Our data highlight SON as a master regulator governing neurodevelopment and demonstrate the importance of SON-mediated RNA splicing in human development.
Keywords: Animals; Brain; Developmental Disabilities; DNA-Binding Proteins; Eye Abnormalities; Female; Genes, Essential; Haploinsufficiency; Head; Heterozygote; Humans; Intellectual Disability; Male; Metabolic Diseases; Minor Histocompatibility Antigens; Mutation; Pedigree; RNA Splicing; RNA, Messenger; Spine; Syndrome; Zebrafish

Disrupted nitric oxide signaling due to GUCY1A3 mutations increases risk for moyamoya disease, achalasia and hypertension. - Wallace, S; Guo, D-C; Regalado, E; Mellor-Crummey, L; Bamshad, M; Nickerson, D A; Dauser, R; Hanchard, N; Marom, R; Martin, E; Berka, V; Sharina, I; et al. (Clin Genet, 2016)
Moyamoya disease (MMD) is a progressive vasculopathy characterized by occlusion of the terminal portion of the internal carotid arteries and its branches, and the formation of compensatory moyamoya collateral vessels. Homozygous mutations in GUCY1A3 have been reported as a cause of MMD and achalasia. Probands (n = 96) from unrelated families underwent sequencing of GUCY1A3. Functional studies were performed to confirm the pathogenicity of identified GUCY1A3 variants. Two affected individuals from the unrelated families were found to have compound heterozygous mutations in GUCY1A3. MM041 was diagnosed with achalasia at 4 years of age, hypertension and MMD at 18 years of age. MM149 was diagnosed with MMD and hypertension at the age of 20 months. Both individuals carry one allele that is predicted to lead to haploinsufficiency and a second allele that is predicted to produce a mutated protein. Biochemical studies of one of these alleles, GUCY1A3 Cys517Tyr, showed that the mutant protein (a subunit of soluble guanylate cyclase) has a significantly blunted signaling response with exposure to nitric oxide (NO). GUCY1A3 missense and haploinsufficiency mutations disrupt NO signaling leading to MMD and hypertension, with or without achalasia.
Keywords: Adolescent; Adult; Animals; Child; Child, Preschool; Cohort Studies; Esophageal Achalasia; Female; Humans; Hypertension; Infant; Male; Middle Aged; Moyamoya Disease; Mutation; Nitric Oxide; Nonlinear Dynamics; Regression Analysis; Sf9 Cells; Signal Transduction; Soluble Guanylyl Cyclase

Dominant de novo DSP mutations cause erythrokeratodermia-cardiomyopathy syndrome. - Boyden, Lynn M; Kam, Chen Y; Hernández-Martín, Angela; Zhou, Jing; Craiglow, Brittany G; Sidbury, Robert; Mathes, Erin F; Maguiness, Sheilagh M; Crumrine, Debra A; Williams, Mary L; Hu, Ronghua; Lifton, Richard P; et al. (Hum Mol Genet, 2016)
Disorders of keratinization (DOK) show marked genotypic and phenotypic heterogeneity. In most cases, disease is primarily cutaneous, and further clinical evaluation is therefore rarely pursued. We have identified subjects with a novel DOK featuring erythrokeratodermia and initially-asymptomatic, progressive, potentially fatal cardiomyopathy, a finding not previously associated with erythrokeratodermia. We show that de novo missense mutations clustered tightly within a single spectrin repeat of DSP cause this novel cardio-cutaneous disorder, which we term erythrokeratodermia-cardiomyopathy (EKC) syndrome. We demonstrate that DSP mutations in our EKC syndrome subjects affect localization of desmosomal proteins and connexin 43 in the skin, and result in desmosome aggregation, widening of intercellular spaces, and lipid secretory defects. DSP encodes desmoplakin, a primary component of desmosomes, intercellular adhesion junctions most abundant in the epidermis and heart. Though mutations in DSP are known to cause other disorders, our cohort features the unique clinical finding of severe whole-body erythrokeratodermia, with distinct effects on localization of desmosomal proteins and connexin 43. These findings add a severe, previously undescribed syndrome featuring erythrokeratodermia and cardiomyopathy to the spectrum of disease caused by mutation in DSP, and identify a specific region of the protein critical to the pathobiology of EKC syndrome and to DSP function in the heart and skin.
Keywords: Amino Acid Sequence; Cardiomyopathies; Child; Child, Preschool; Connexin 43; Desmoplakins; Desmosomes; Female; Humans; Infant; Male; Molecular Sequence Data; Mutation, Missense; Myocardium; Protein Transport; Sequence Alignment; Skin; Skin Diseases, Genetic; Syndrome

DVL3 Alleles Resulting in a -1 Frameshift of the Last Exon Mediate Autosomal-Dominant Robinow Syndrome. - White, Janson J; Mazzeu, Juliana F; Hoischen, Alexander; Bayram, Yavuz; Withers, Marjorie; Gezdirici, Alper; Kimonis, Virginia; Steehouwer, Marloes; Jhangiani, Shalini N; Muzny, Donna M; Gibbs, Richard A; van Bon, Bregje W M; et al. (Am J Hum Genet, 2016)
Robinow syndrome is a rare congenital disorder characterized by mesomelic limb shortening, genital hypoplasia, and distinctive facial features. Recent reports have identified, in individuals with dominant Robinow syndrome, a specific type of variant characterized by being uniformly located in the penultimate exon of DVL1 and resulting in a -1 frameshift allele with a premature termination codon that escapes nonsense-mediated decay. Here, we studied a cohort of individuals who had been clinically diagnosed with Robinow syndrome but who had not received a molecular diagnosis from variant studies of DVL1, WNT5A, and ROR2. Because of the uniform location of frameshift variants in DVL1-mediated Robinow syndrome and the functional redundancy of DVL1, DVL2, and DVL3, we elected to pursue direct Sanger sequencing of the penultimate exon of DVL1 and its paralogs DVL2 and DVL3 to search for potential disease-associated variants. Remarkably, targeted sequencing identified five unrelated individuals harboring heterozygous, de novo frameshift variants in DVL3, including two splice acceptor mutations and three 1 bp deletions. Similar to the variants observed in DVL1-mediated Robinow syndrome, all variants in DVL3 result in a -1 frameshift, indicating that these highly specific alterations might be a common cause of dominant Robinow syndrome. Here, we review the current knowledge of these peculiar variant alleles in DVL1- and DVL3-mediated Robinow syndrome and further elucidate the phenotypic features present in subjects with DVL1 and DVL3 frameshift mutations.
Keywords: Adaptor Proteins, Signal Transducing; Alleles; Base Sequence; Codon, Nonsense; Craniofacial Abnormalities; Dishevelled Proteins; Dwarfism; Exons; Female; Frameshift Mutation; Genetic Variation; Humans; Limb Deformities, Congenital; Male; Molecular Sequence Data; Phosphoproteins; Proto-Oncogene Proteins; Receptor Tyrosine Kinase-like Orphan Receptors; Sequence Analysis, DNA; Sequence Deletion; Urogenital Abnormalities; Wnt Proteins; Wnt-5a Protein

Evidence of macular pigment in the central macula in albinism. - Wolfson, Yulia; Fletcher, Emily; Strauss, Rupert W; Scholl, Hendrik P N (Exp Eye Res, 2016)
PURPOSE: Albinism represents a spectrum of disorders with diminished to absent amounts of melanin pigmentation including the posterior segment of the eye. Macular pigment (MP) consists of two main carotenoids, lutein and zeaxanthin, concentrated in the macula. MP serves as blue light absorbent, antioxidant, and may reduce chromatic aberration and glare. It remains unclear if albinos have detectable MP. The purpose was to investigate the distribution of MP in albino patients with psychophysical and imaging techniques. METHODS: MP was measured at the eccentricity of 0.5° by heterochromatic flicker perimetry (QuantifEye(®); Tinsley Precision Instruments Ltd.) or by scanning laser ophthalmoscopy (MPOD module, MultiColor Spectralis(®), Heidelberg Engineering, Heidelberg, Germany) in four albino patients, who were also investigated with multimodal ophthalmic imaging. RESULTS: Visual acuity ranged from 20/32 to 20/125, nystagmus was present in three patients, and all patients showed typical foveal hypoplasia on fundus exam and optical coherence tomography. Fundus autofluorescence (FAF) demonstrated various degrees of central FAF signal attenuation. Genetic testing was available in three patients and confirmed the diagnosis. Measurable amounts of MP were detected in all four patients and ranged from 0.05 to 0.24, which is below the normal range. CONCLUSIONS: We conclude that MP can be demonstrated and measured in albinos. Further studies are needed to investigate MP accumulation following carotenoid supplementation and its impact on visual performance.
Keywords: Adult; Aged; Albinism, Ocular; Fluorescein Angiography; Humans; Macula Lutea; Macular Pigment; Male; Middle Aged; Tomography, Optical Coherence; Visual Acuity; Visual Field Tests; Visual Fields

Exome Sequencing Analysis in Severe, Early-Onset Chronic Obstructive Pulmonary Disease. - Qiao, Dandi; Lange, Christoph; Beaty, Terri H; Crapo, James D; Barnes, Kathleen C; Bamshad, Michael; Hersh, Craig P; Morrow, Jarrett; Pinto-Plata, Victor M; Marchetti, Nathaniel; Bueno, Raphael; Celli, Bartolome R; et al. (Am J Respir Crit Care Med, 2016)
RATIONALE: Genomic regions identified by genome-wide association studies explain only a small fraction of heritability for chronic obstructive pulmonary disease (COPD). Alpha-1 antitrypsin deficiency shows that rare coding variants of large effect also influence COPD susceptibility. We hypothesized that exome sequencing in families identified through a proband with severe, early-onset COPD would identify additional rare genetic determinants of large effect. OBJECTIVES: To identify rare genetic determinants of severe COPD. METHODS: We applied filtering approaches to identify potential causal variants for COPD in whole exomes from 347 subjects in 49 extended pedigrees from the Boston Early-Onset COPD Study. We assessed the power of this approach under different levels of genetic heterogeneity using simulations. We tested genes identified in these families using gene-based association tests in exomes of 204 cases with severe COPD and 195 resistant smokers from the COPDGene study. In addition, we examined previously described loci associated with COPD using these datasets. MEASUREMENTS AND MAIN RESULTS: We identified 69 genes with predicted deleterious nonsynonymous, stop, or splice variants that segregated with severe COPD in at least two pedigrees. Four genes (DNAH8, ALCAM, RARS, and GBF1) also demonstrated an increase in rare nonsynonymous, stop, and/or splice mutations in cases compared with resistant smokers from the COPDGene study; however, these results were not statistically significant. We demonstrate the limitations of the power of this approach under genetic heterogeneity through simulation. CONCLUSIONS: Rare deleterious coding variants may increase risk for COPD, but multiple genes likely contribute to COPD susceptibility.
Keywords: Adult; alpha 1-Antitrypsin Deficiency; Boston; Exome; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Pulmonary Disease, Chronic Obstructive; Severity of Illness Index

Exome Sequencing Identifies Biallelic MSH3 Germline Mutations as a Recessive Subtype of Colorectal Adenomatous Polyposis. - Adam, Ronja; Spier, Isabel; Zhao, Bixiao; Kloth, Michael; Marquez, Jonathan; Hinrichsen, Inga; Kirfel, Jutta; Tafazzoli, Aylar; Horpaopan, Sukanya; Uhlhaas, Siegfried; Stienen, Dietlinde; Friedrichs, Nicolaus; et al. (Am J Hum Genet, 2016)
In ∼30% of families affected by colorectal adenomatous polyposis, no germline mutations have been identified in the previously implicated genes APC, MUTYH, POLE, POLD1, and NTHL1, although a hereditary etiology is likely. To uncover further genes with high-penetrance causative mutations, we performed exome sequencing of leukocyte DNA from 102 unrelated individuals with unexplained adenomatous polyposis. We identified two unrelated individuals with differing compound-heterozygous loss-of-function (LoF) germline mutations in the mismatch-repair gene MSH3. The impact of the MSH3 mutations (c.1148delA, c.2319-1G>A, c.2760delC, and c.3001-2A>C) was indicated at the RNA and protein levels. Analysis of the diseased individuals' tumor tissue demonstrated high microsatellite instability of di- and tetranucleotides (EMAST), and immunohistochemical staining illustrated a complete loss of nuclear MSH3 in normal and tumor tissue, confirming the LoF effect and causal relevance of the mutations. The pedigrees, genotypes, and frequency of MSH3 mutations in the general population are consistent with an autosomal-recessive mode of inheritance. Both index persons have an affected sibling carrying the same mutations. The tumor spectrum in these four persons comprised colorectal and duodenal adenomas, colorectal cancer, gastric cancer, and an early-onset astrocytoma. Additionally, we detected one unrelated individual with biallelic PMS2 germline mutations, representing constitutional mismatch-repair deficiency. Potentially causative variants in 14 more candidate genes identified in 26 other individuals require further workup. In the present study, we identified biallelic germline MSH3 mutations in individuals with a suspected hereditary tumor syndrome. Our data suggest that MSH3 mutations represent an additional recessive subtype of colorectal adenomatous polyposis.
Keywords: Adenomatous Polyposis Coli; Adolescent; Adult; Alleles; Child, Preschool; Colorectal Neoplasms; DNA Mutational Analysis; DNA-Binding Proteins; Exome; Female; Genes, Recessive; Germ-Line Mutation; Humans; Male; Middle Aged; Mismatch Repair Endonuclease PMS2; MutS Homolog 3 Protein; Pedigree

Exome sequencing identifies potential novel candidate genes in patients with unexplained colorectal adenomatous polyposis. - Spier, Isabel; Kerick, Martin; Drichel, Dmitriy; Horpaopan, Sukanya; Altmüller, Janine; Laner, Andreas; Holzapfel, Stefanie; Peters, Sophia; Adam, Ronja; Zhao, Bixiao; Becker, Tim; Lifton, Richard P; et al. (Fam Cancer, 2016)
In up to 30% of patients with colorectal adenomatous polyposis, no germline mutation in the known genes APC, causing familial adenomatous polyposis, MUTYH, causing MUTYH-associated polyposis, and POLE or POLD1, causing Polymerase-Proofreading-associated polyposis can be identified, although a hereditary etiology is likely. To uncover new causative genes, exome sequencing was performed using DNA from leukocytes and a total of 12 colorectal adenomas from seven unrelated patients with unexplained sporadic adenomatous polyposis. For data analysis and variant filtering, an established bioinformatics pipeline including in-house tools was applied. Variants were filtered for rare truncating point mutations and copy-number variants assuming a dominant, recessive, or tumor suppressor model of inheritance. Subsequently, targeted sequence analysis of the most promising candidate genes was performed in a validation cohort of 191 unrelated patients. All relevant variants were validated by Sanger sequencing. The analysis of exome sequencing data resulted in the identification of rare loss-of-function germline mutations in three promising candidate genes (DSC2, PIEZO1, ZSWIM7). In the validation cohort, further variants predicted to be pathogenic were identified in DSC2 and PIEZO1. According to the somatic mutation spectra, the adenomas in this patient cohort follow the classical pathways of colorectal tumorigenesis. The present study identified three candidate genes which might represent rare causes for a predisposition to colorectal adenoma formation. Especially PIEZO1 (FAM38A) and ZSWIM7 (SWS1) warrant further exploration. To evaluate the clinical relevance of these genes, investigation of larger patient cohorts and functional studies are required.
Keywords: Adenomatous Polyposis Coli; Adenomatous Polyps; Aged; Desmocollins; Exome; Female; Genetic Predisposition to Disease; Germ-Line Mutation; High-Throughput Nucleotide Sequencing; Humans; Ion Channels; Male; Middle Aged; Reproducibility of Results

Exome sequencing in mostly consanguineous Arab families with neurologic disease provides a high potential molecular diagnosis rate. - Charng, Wu-Lin; Karaca, Ender; Coban Akdemir, Zeynep; Gambin, Tomasz; Atik, Mehmed M; Gu, Shen; Posey, Jennifer E; Jhangiani, Shalini N; Muzny, Donna M; Doddapaneni, Harsha; Hu, Jianhong; Boerwinkle, Eric; et al. (BMC Med Genomics, 2016)
BACKGROUND: Neurodevelopment is orchestrated by a wide range of genes, and the genetic causes of neurodevelopmental disorders are thus heterogeneous. We applied whole exome sequencing (WES) for molecular diagnosis and in silico analysis to identify novel disease gene candidates in a cohort from Saudi Arabia with primarily Mendelian neurologic diseases. METHODS: We performed WES in 31 mostly consanguineous Arab families and analyzed both single nucleotide and copy number variants (CNVs) from WES data. Interaction/expression network and pathway analyses, as well as paralog studies were utilized to investigate potential pathogenicity and disease association of novel candidate genes. Additional cases for candidate genes were identified through the clinical WES database at Baylor Miraca Genetics Laboratories and GeneMatcher. RESULTS: We found known pathogenic or novel variants in known disease genes with phenotypic expansion in 6 families, disease-associated CNVs in 2 families, and 12 novel disease gene candidates in 11 families, including KIF5B, GRM7, FOXP4, MLLT1, and KDM2B. Overall, a potential molecular diagnosis was provided by variants in known disease genes in 17 families (54.8 %) and by novel candidate disease genes in an additional 11 families, making the potential molecular diagnostic rate ~90 %. CONCLUSIONS: Molecular diagnostic rate from WES is improved by exome-predicted CNVs. Novel candidate disease gene discovery is facilitated by paralog studies and through the use of informatics tools and available databases to identify additional evidence for pathogenicity. TRIAL REGISTRATION: Not applicable.
Keywords: Arabs; Cohort Studies; Consanguinity; Data Mining; Databases, Genetic; DNA Copy Number Variations; Exome; Female; High-Throughput Nucleotide Sequencing; Humans; Male; Molecular Diagnostic Techniques; Nervous System Diseases; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Expansion of the spectrum of ITGB6-related disorders to adolescent alopecia, dentogingival abnormalities and intellectual disability. - Ansar, Muhammad; Jan, Abid; Santos-Cortez, Regie Lyn P; Wang, Xin; Suliman, Muhammad; Acharya, Anushree; Habib, Rabia; Abbe, Izoduwa; Ali, Ghazanfar; Lee, Kwanghyuk; Smith, Joshua D; Nickerson, Deborah A; et al. (Eur J Hum Genet, 2016)
Alopecia with mental retardation (APMR) is a very rare disorder. In this study, we report on a consanguineous Pakistani family (AP91) with mild-to-moderate intellectual disability, adolescent alopecia and dentogingival abnormalities. Using homozygosity mapping, linkage analysis and exome sequencing, we identified a novel rare missense variant c.898G>A (p.(Glu300Lys)) in ITGB6, which co-segregates with the phenotype within the family and is predicted to be deleterious. Structural modeling shows that Glu300 lies in the β-propeller domain, and is surrounded by several residues that are important for heterodimerization with α integrin. Previous studies showed that ITGB6 variants can cause amelogenesis imperfecta in humans, but patients from family AP91 who are homozygous for the c.898G>A variant present with neurological and dermatological features, indicating a role for ITGB6 beyond enamel formation. Our study demonstrates that a rare deleterious variant within ITGB6 causes not only dentogingival anomalies but also intellectual disability and alopecia.
Keywords: Adolescent; Adult; Alopecia; Child; Female; Humans; Integrin beta Chains; Intellectual Disability; Male; Mutation, Missense; Pedigree; Phenotype; Protein Domains; Syndrome; Tooth Abnormalities

Family Based Whole Exome Sequencing Reveals the Multifaceted Role of Notch Signaling in Congenital Heart Disease. - Preuss, Christoph; Capredon, Melanie; Wünnemann, Florian; Chetaille, Philippe; Prince, Andrea; Godard, Beatrice; Leclerc, Severine; Sobreira, Nara; Ling, Hua; Awadalla, Philip; Thibeault, Maryse; Khairy, Paul; et al. (PLoS Genet, 2016)
Left-ventricular outflow tract obstructions (LVOTO) encompass a wide spectrum of phenotypically heterogeneous heart malformations which frequently cluster in families. We performed family based whole-exome and targeted re-sequencing on 182 individuals from 51 families with multiple affected members. Central to our approach is the family unit which serves as a reference to identify causal genotype-phenotype correlations. Screening a multitude of 10 overlapping phenotypes revealed disease associated and co-segregating variants in 12 families. These rare or novel protein altering mutations cluster predominantly in genes (NOTCH1, ARHGAP31, MAML1, SMARCA4, JARID2, JAG1) along the Notch signaling cascade. This is in line with a significant enrichment (Wilcoxon, p< 0.05) of variants with a higher pathogenicity in the Notch signaling pathway in patients compared to controls. The significant enrichment of novel protein truncating and missense mutations in NOTCH1 highlights the allelic and phenotypic heterogeneity in our pediatric cohort. We identified novel co-segregating pathogenic mutations in NOTCH1 associated with left and right-sided cardiac malformations in three independent families with a total of 15 affected individuals. In summary, our results suggest that a small but highly pathogenic fraction of family specific mutations along the Notch cascade are a common cause of LVOTO.
Keywords: Aortic Valve; Codon, Nonsense; Constriction, Pathologic; Exome; Female; Genetic Association Studies; Genetic Linkage; Genome, Human; Heart Defects, Congenital; Humans; Male; Pedigree; Receptor, Notch1; Receptors, Notch; Sequence Deletion; Signal Transduction; Ventricular Outflow Obstruction

FOXE3 mutations predispose to thoracic aortic aneurysms and dissections. - Kuang, Shao-Qing; Medina-Martinez, Olga; Guo, Dong-Chuan; Gong, Limin; Regalado, Ellen S; Reynolds, Corey L; Boileau, Catherine; Jondeau, Guillaume; Prakash, Siddharth K; Kwartler, Callie S; Zhu, Lawrence Yang; Peters, Andrew M; et al. (J Clin Invest, 2016)
The ascending thoracic aorta is designed to withstand biomechanical forces from pulsatile blood. Thoracic aortic aneurysms and acute aortic dissections (TAADs) occur as a result of genetically triggered defects in aortic structure and a dysfunctional response to these forces. Here, we describe mutations in the forkhead transcription factor FOXE3 that predispose mutation-bearing individuals to TAAD. We performed exome sequencing of a large family with multiple members with TAADs and identified a rare variant in FOXE3 with an altered amino acid in the DNA-binding domain (p.Asp153His) that segregated with disease in this family. Additional pathogenic FOXE3 variants were identified in unrelated TAAD families. In mice, Foxe3 deficiency reduced smooth muscle cell (SMC) density and impaired SMC differentiation in the ascending aorta. Foxe3 expression was induced in aortic SMCs after transverse aortic constriction, and Foxe3 deficiency increased SMC apoptosis and ascending aortic rupture with increased aortic pressure. These phenotypes were rescued by inhibiting p53 activity, either by administration of a p53 inhibitor (pifithrin-α), or by crossing Foxe3-/- mice with p53-/- mice. Our data demonstrate that FOXE3 mutations lead to a reduced number of aortic SMCs during development and increased SMC apoptosis in the ascending aorta in response to increased biomechanical forces, thus defining an additional molecular pathway that leads to familial thoracic aortic disease.
Keywords: Adult; Aneurysm, Dissecting; Animals; Aorta; Aortic Aneurysm, Thoracic; Apoptosis; Cells, Cultured; Cyclin-Dependent Kinase Inhibitor p21; Female; Forkhead Transcription Factors; Gene Expression; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Male; Mice, Inbred C57BL; Mice, Knockout; Middle Aged; Muscle, Smooth, Vascular; Mutation, Missense; Myocytes, Smooth Muscle; Pedigree; Tumor Suppressor Protein p53; Vascular Remodeling; Zebrafish

Gene discovery for Mendelian conditions via social networking: de novo variants in KDM1A cause developmental delay and distinctive facial features. - Chong, Jessica X; Yu, Joon-Ho; Lorentzen, Peter; Park, Karen M; Jamal, Seema M; Tabor, Holly K; Rauch, Anita; Saenz, Margarita Sifuentes; Boltshauser, Eugen; Patterson, Karynne E; Nickerson, Deborah A; Bamshad, Michael J (Genet Med, 2016)
PURPOSE: The pace of Mendelian gene discovery is slowed by the "n-of-1 problem"-the difficulty of establishing the causality of a putatively pathogenic variant in a single person or family. Identification of an unrelated person with an overlapping phenotype and suspected pathogenic variant in the same gene can overcome this barrier, but it is often impeded by lack of a convenient or widely available way to share data on candidate variants/genes among families, clinicians, and researchers. METHODS: Social networking among families, clinicians, and researchers was used to identify three children with variants of unknown significance in KDM1A and similar phenotypes. RESULTS: De novo variants in KDM1A underlie a new syndrome characterized by developmental delay and distinctive facial features. CONCLUSION: Social networking is a potentially powerful strategy to discover genes for rare Mendelian conditions, particularly those with nonspecific phenotypic features. To facilitate the efforts of families to share phenotypic and genomic information with each other, clinicians, and researchers, we developed the Repository for Mendelian Genomics Family Portal (RMD-FP; http://uwcmg.org/#/family). Design and development of MyGene2 (http://www.mygene2.org), a Web-based tool that enables families, clinicians, and researchers to search for gene matches based on analysis of phenotype and exome data deposited into the RMD-FP, is under way.Genet Med 18 8, 788-795.
Keywords: Child; Child, Preschool; Databases, Factual; Developmental Disabilities; Female; Genetic Association Studies; Histone Demethylases; Humans; Information Dissemination; Male; Mutation, Missense; Phenotype; Social Networking; Web Browser

Genetic Candidate Variants in Two Multigenerational Families with Childhood Apraxia of Speech. - Peter, Beate; Wijsman, Ellen M; Nato, Alejandro Q; Matsushita, Mark M; Chapman, Kathy L; Stanaway, Ian B; Wolff, John; Oda, Kaori; Gabo, Virginia B; Raskind, Wendy H (PLoS One, 2016)
Childhood apraxia of speech (CAS) is a severe and socially debilitating form of speech sound disorder with suspected genetic involvement, but the genetic etiology is not yet well understood. Very few known or putative causal genes have been identified to date, e.g., FOXP2 and BCL11A. Building a knowledge base of the genetic etiology of CAS will make it possible to identify infants at genetic risk and motivate the development of effective very early intervention programs. We investigated the genetic etiology of CAS in two large multigenerational families with familial CAS. Complementary genomic methods included Markov chain Monte Carlo linkage analysis, copy-number analysis, identity-by-descent sharing, and exome sequencing with variant filtering. No overlaps in regions with positive evidence of linkage between the two families were found. In one family, linkage analysis detected two chromosomal regions of interest, 5p15.1-p14.1, and 17p13.1-q11.1, inherited separately from the two founders. Single-point linkage analysis of selected variants identified CDH18 as a primary gene of interest and additionally, MYO10, NIPBL, GLP2R, NCOR1, FLCN, SMCR8, NEK8, and ANKRD12, possibly with additive effects. Linkage analysis in the second family detected five regions with LOD scores approaching the highest values possible in the family. A gene of interest was C4orf21 (ZGRF1) on 4q25-q28.2. Evidence for previously described causal copy-number variations and validated or suspected genes was not found. Results are consistent with a heterogeneous CAS etiology, as is expected in many neurogenic disorders. Future studies will investigate genome variants in these and other families with CAS.
Keywords: Apraxias; DNA Copy Number Variations; Exome; Female; Genetic Linkage; Genetic Predisposition to Disease; Genotype; Humans; Lod Score; Male; Pedigree; Risk; Speech

A genome-wide association study of congenital cardiovascular left-sided lesions shows association with a locus on chromosome 20. - Hanchard, Neil A; Swaminathan, Shanker; Bucasas, Kristine; Furthner, Dieter; Fernbach, Susan; Azamian, Mahshid S; Wang, Xueqing; Lewin, Mark; Towbin, Jeffrey A; D'Alessandro, Lisa C A; Morris, Shaine A; Dreyer, William; et al. (Hum Mol Genet, 2016)
Congenital heart defects involving left-sided lesions (LSLs) are relatively common birth defects with substantial morbidity and mortality. Previous studies have suggested a high heritability with a complex genetic architecture, such that only a few LSL loci have been identified. We performed a genome-wide case-control association study to address the role of common variants using a discovery cohort of 778 cases and 2756 controls. We identified a genome-wide significant association mapping to a 200 kb region on chromosome 20q11 [P= 1.72 × 10 for rs3746446; imputed Single Nucleotide Polymorphism (SNP) rs6088703 P= 3.01 × 10, odds ratio (OR)= 1.6 for both]. This result was supported by transmission disequilibrium analyses using a subset of 541 case families (lowest P in region= 4.51 × 10, OR= 1.5). Replication in a cohort of 367 LSL cases and 5159 controls showed nominal association (P= 0.03 for rs3746446) resulting in P= 9.49 × 10 for rs3746446 upon meta-analysis of the combined cohorts. In addition, a group of seven SNPs on chromosome 1q21.3 met threshold for suggestive association (lowest P= 9.35 × 10 for rs12045807). Both regions include genes involved in cardiac development-MYH7B/miR499A on chromosome 20 and CTSK, CTSS and ARNT on chromosome 1. Genome-wide heritability analysis using case-control genotyped SNPs suggested that the mean heritability of LSLs attributable to common variants is moderately high ([Formula: see text] range= 0.26-0.34) and consistent with previous assertions. These results provide evidence for the role of common variation in LSLs, proffer new genes as potential biological candidates, and give further insight to the complex genetic architecture of congenital heart disease.
Keywords: Chromosome Mapping; Chromosomes, Human, Pair 20; Cohort Studies; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Heart Defects, Congenital; Heart Ventricles; Humans; Male; Polymorphism, Single Nucleotide

Germline De Novo Mutations in GNB1 Cause Severe Neurodevelopmental Disability, Hypotonia, and Seizures. - Petrovski, Slavé; Küry, Sébastien; Myers, Candace T; Anyane-Yeboa, Kwame; Cogné, Benjamin; Bialer, Martin; Xia, Fan; Hemati, Parisa; Riviello, James; Mehaffey, Michele; Besnard, Thomas; Becraft, Emily; et al. (Am J Hum Genet, 2016)
Whole-exome sequencing of 13 individuals with developmental delay commonly accompanied by abnormal muscle tone and seizures identified de novo missense mutations enriched within a sub-region of GNB1, a gene encoding the guanine nucleotide-binding protein subunit beta-1, Gβ. These 13 individuals were identified among a base of 5,855 individuals recruited for various undiagnosed genetic disorders. The probability of observing 13 or more de novo mutations by chance among 5,855 individuals is very low (p = 7.1 × 10(-21)), implicating GNB1 as a genome-wide-significant disease-associated gene. The majority of these 13 mutations affect known Gβ binding sites, which suggests that a likely disease mechanism is through the disruption of the protein interface required for Gα-Gβγ interaction (resulting in a constitutively active Gβγ) or through the disruption of residues relevant for interaction between Gβγ and certain downstream effectors (resulting in reduced interaction with the effectors). Strikingly, 8 of the 13 individuals recruited here for a neurodevelopmental disorder have a germline de novo GNB1 mutation that overlaps a set of five recurrent somatic tumor mutations for which recent functional studies demonstrated a gain-of-function effect due to constitutive activation of G protein downstream signaling cascades for some of the affected residues.
Keywords: Adolescent; Adult; Child; Child, Preschool; Developmental Disabilities; Exome; Female; Germ-Line Mutation; GTP-Binding Protein beta Subunits; Humans; Infant; Intellectual Disability; Male; Muscle Hypotonia; Phenotype; Protein Conformation; Seizures; Signal Transduction; Young Adult

A germline ERBB3 variant is a candidate for predisposition to erythroid MDS/erythroleukemia. - Braunstein, E M; Li, R; Sobreira, N; Marosy, B; Hetrick, K; Doheny, K; Gocke, C D; Valle, D; Brodsky, R A; Cheng, L (Leukemia, 2016)
Keywords: Adult; Aged; Female; Genetic Predisposition to Disease; Germ-Line Mutation; Humans; Leukemia, Erythroblastic, Acute; Male; Middle Aged; Myelodysplastic Syndromes; Pedigree; Receptor, ErbB-3

Germline or somatic GPR101 duplication leads to X-linked acrogigantism: a clinico-pathological and genetic study. - Iacovazzo, Donato; Caswell, Richard; Bunce, Benjamin; Jose, Sian; Yuan, Bo; Hernández-Ramírez, Laura C; Kapur, Sonal; Caimari, Francisca; Evanson, Jane; Ferraù, Francesco; Dang, Mary N; Gabrovska, Plamena; et al. (Acta Neuropathol Commun, 2016)
Non-syndromic pituitary gigantism can result from AIP mutations or the recently identified Xq26.3 microduplication causing X-linked acrogigantism (XLAG). Within Xq26.3, GPR101 is believed to be the causative gene, and the c.924G > C (p.E308D) variant in this orphan G protein-coupled receptor has been suggested to play a role in the pathogenesis of acromegaly.We studied 153 patients (58 females and 95 males) with pituitary gigantism. AIP mutation-negative cases were screened for GPR101 duplication through copy number variation droplet digital PCR and high-density aCGH. The genetic, clinical and histopathological features of XLAG patients were studied in detail. 395 peripheral blood and 193 pituitary tumor DNA samples from acromegaly patients were tested for GPR101 variants.We identified 12 patients (10 females and 2 males; 7.8 %) with XLAG. In one subject, the duplicated region only contained GPR101, but not the other three genes in found to be duplicated in the previously reported patients, defining a new smallest region of overlap of duplications. While females presented with germline mutations, the two male patients harbored the mutation in a mosaic state. Nine patients had pituitary adenomas, while three had hyperplasia. The comparison of the features of XLAG, AIP-positive and GPR101&AIP-negative patients revealed significant differences in sex distribution, age at onset, height, prolactin co-secretion and histological features. The pathological features of XLAG-related adenomas were remarkably similar. These tumors had a sinusoidal and lobular architecture. Sparsely and densely granulated somatotrophs were admixed with lactotrophs; follicle-like structures and calcifications were commonly observed. Patients with sporadic of familial acromegaly did not have an increased prevalence of the c.924G > C (p.E308D) GPR101 variant compared to public databases.In conclusion, XLAG can result from germline or somatic duplication of GPR101. Duplication of GPR101 alone is sufficient for the development of XLAG, implicating it as the causative gene within the Xq26.3 region. The pathological features of XLAG-associated pituitary adenomas are typical and, together with the clinical phenotype, should prompt genetic testing.
Keywords: Acromegaly; Adenoma; Adolescent; Child; Child, Preschool; Female; Gene Duplication; Germ-Line Mutation; Gigantism; Humans; Infant; Intracellular Signaling Peptides and Proteins; Male; Pituitary Neoplasms; Receptors, G-Protein-Coupled; Treatment Outcome; Young Adult

GNA14 Somatic Mutation Causes Congenital and Sporadic Vascular Tumors by MAPK Activation. - Lim, Young H; Bacchiocchi, Antonella; Qiu, Jingyao; Straub, Robert; Bruckner, Anna; Bercovitch, Lionel; Narayan, Deepak; McNiff, Jennifer; Ko, Christine; Robinson-Bostom, Leslie; Antaya, Richard; Halaban, Ruth; et al. (Am J Hum Genet, 2016)
Vascular tumors are among the most common neoplasms in infants and children; 5%-10% of newborns present with or develop lesions within the first 3 months of life. Most are benign infantile hemangiomas that typically regress by 5 years of age; other vascular tumors include congenital tufted angiomas (TAs), kaposiform hemangioendotheliomas (KHEs), and childhood lobular capillary hemangiomas (LCHs). Some of these lesions can become locally invasive and unresponsive to pharmacologic intervention, leading to significant complications. Recent investigation has revealed that activating mutations in HRAS, KRAS, NRAS, GNAQ, and GNA11 can cause certain types of rare childhood vascular tumors, and we have now identified causal recurrent somatic activating mutations in GNA14 by whole-exome and targeted sequencing. We found somatic activating GNA14 c.614A>T (p.Gln205Leu) mutations in one KHE, one TA, and one LCH and a GNA11 c.547C>T (p.Arg183Cys) mutation in two LCH lesions. We examined mutation pathobiology via expression of mutant GNA14 or GNA11 in primary human endothelial cells and melanocytes. GNA14 and GNA11 mutations induced changes in cellular morphology and rendered cells growth-factor independent by upregulating the MAPK pathway. Our findings identify GNA14 mutations as a cause of childhood vascular tumors, offer insight into mechanisms of oncogenic transformation by mutations affecting Gaq family members, and identify potential targets for therapeutic intervention.
Keywords: Cells, Cultured; Child, Preschool; Enzyme Activation; GTP-Binding Protein alpha Subunits; GTP-Binding Protein alpha Subunits, Gq-G11; Human Umbilical Vein Endothelial Cells; Humans; Infant; Infant, Newborn; Intercellular Signaling Peptides and Proteins; Male; MAP Kinase Signaling System; Melanocytes; Mitogen-Activated Protein Kinases; Mutation; Proto-Oncogene Proteins c-akt; Vascular Neoplasms

Gonadal mosaicism in ARID1B gene causes intellectual disability and dysmorphic features in three siblings. - Ben-Salem, Salma; Sobreira, Nara; Akawi, Nadia A; Al-Shamsi, Aisha M; John, Anne; Pramathan, Thachillath; Valle, David; Ali, Bassam R; Al-Gazali, Lihadh (Am J Med Genet A, 2016)
The gene encoding the AT-rich interaction domain-containing protein 1B (ARID1B) has recently been shown to be one of the most frequently mutated genes in patients with intellectual disability (ID). The phenotypic spectrums associated with variants in this gene vary widely ranging for mild to severe non-specific ID to Coffin-Siris syndrome. In this study, we evaluated three children from a consanguineous Emirati family affected with ID and dysmorphic features. Genomic DNA from all affected siblings was analyzed using CGH array and whole-exome sequencing (WES). Based on a recessive mode of inheritance, homozygous or compound heterozygous variants shared among all three affected children could not be identified. However, further analysis revealed a heterozygous variant (c.4318C>T; p.Q1440*) in the three affected children in an autosomal dominant ID causing gene, ARID1B. This variant was absent in peripheral blood samples obtained from both parents and unaffected siblings. Therefore, we propose that the most likely explanation for this situation is that one of the parents is a gonadal mosaic for the variant. To the best of our knowledge, this is the first report of a gonadal mosaicism inheritance of an ARID1B variant leading to familial ID recurrence.
Keywords: Abnormalities, Multiple; Adolescent; Child; DNA-Binding Proteins; Exome; Face; Female; Hand Deformities, Congenital; Heterozygote; Humans; Intellectual Disability; Male; Micrognathism; Mosaicism; Mutation; Neck; Pedigree; Siblings; Transcription Factors

Identification and clinical characterization of Hermansky-Pudlak syndrome alleles in the Pakistani population. - Yousaf, Sairah; Shahzad, Mohsin; Kausar, Tasleem; Sheikh, Shakeel A; Tariq, Nabeela; Shabbir, Asra S; Ali, Muhammad; Waryah, Ali M; Shaikh, Rehan S; Riazuddin, Saima; Ahmed, Zubair M (Pigment Cell Melanoma Res, 2016)
Keywords: Adolescent; Adult; Alleles; Child; Child, Preschool; Female; Hermanski-Pudlak Syndrome; Humans; Infant; Male; Membrane Proteins; Middle Aged; Pakistan; Pedigree

Identification of a RAI1-associated disease network through integration of exome sequencing, transcriptomics, and 3D genomics. - Loviglio, Maria Nicla; Beck, Christine R; White, Janson J; Leleu, Marion; Harel, Tamar; Guex, Nicolas; Niknejad, Anne; Bi, Weimin; Chen, Edward S; Crespo, Isaac; Yan, Jiong; Charng, Wu-Lin; et al. (Genome Med, 2016)
BACKGROUND: Smith-Magenis syndrome (SMS) is a developmental disability/multiple congenital anomaly disorder resulting from haploinsufficiency of RAI1. It is characterized by distinctive facial features, brachydactyly, sleep disturbances, and stereotypic behaviors. METHODS: We investigated a cohort of 15 individuals with a clinical suspicion of SMS who showed neither deletion in the SMS critical region nor damaging variants in RAI1 using whole exome sequencing. A combination of network analysis (co-expression and biomedical text mining), transcriptomics, and circularized chromatin conformation capture (4C-seq) was applied to verify whether modified genes are part of the same disease network as known SMS-causing genes. RESULTS: Potentially deleterious variants were identified in nine of these individuals using whole-exome sequencing. Eight of these changes affect KMT2D, ZEB2, MAP2K2, GLDC, CASK, MECP2, KDM5C, and POGZ, known to be associated with Kabuki syndrome 1, Mowat-Wilson syndrome, cardiofaciocutaneous syndrome, glycine encephalopathy, mental retardation and microcephaly with pontine and cerebellar hypoplasia, X-linked mental retardation 13, X-linked mental retardation Claes-Jensen type, and White-Sutton syndrome, respectively. The ninth individual carries a de novo variant in JAKMIP1, a regulator of neuronal translation that was recently found deleted in a patient with autism spectrum disorder. Analyses of co-expression and biomedical text mining suggest that these pathologies and SMS are part of the same disease network. Further support for this hypothesis was obtained from transcriptome profiling that showed that the expression levels of both Zeb2 and Map2k2 are perturbed in Rai1 mice. As an orthogonal approach to potentially contributory disease gene variants, we used chromatin conformation capture to reveal chromatin contacts between RAI1 and the loci flanking ZEB2 and GLDC, as well as between RAI1 and human orthologs of the genes that show perturbed expression in our Rai1 mouse model. CONCLUSIONS: These holistic studies of RAI1 and its interactions allow insights into SMS and other disorders associated with intellectual disability and behavioral abnormalities. Our findings support a pan-genomic approach to the molecular diagnosis of a distinctive disorder.
Keywords: Animals; Embryo, Mammalian; Exome; Female; Gene Regulatory Networks; Genomics; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Knockout; Mutation; Phenotype; Real-Time Polymerase Chain Reaction; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Smith-Magenis Syndrome; Trans-Activators; Transcription Factors; Transcriptome

Identification of Rare Variants in Metabolites of the Carnitine Pathway by Whole Genome Sequencing Analysis. - Yazdani, Akram; Yazdani, Azam; Liu, Xiaoming; Boerwinkle, Eric (Genet Epidemiol, 2016)
We use whole genome sequence data and rare variant analysis methods to investigate a subset of the human serum metabolome, including 16 carnitine-related metabolites that are important components of mammalian energy metabolism. Medium pass sequence data consisting of 12,820,347 rare variants and serum metabolomics data were available on 1,456 individuals. By applying a penalization method, we identified two genes FGF8 and MDGA2 with significant effects on lysine and cis-4-decenoylcarnitine, respectively, using Δ-AIC and likelihood ratio test statistics. Single variant analyses in these regions did not identify a single low-frequency variant (minor allele count > 3) responsible for the underlying signal. The results demonstrate the utility of whole genome sequence and innovative analyses for identifying candidate regions influencing complex phenotypes.
Keywords: Biomarkers; Carnitine; Female; Fibroblast Growth Factor 8; Genetic Variation; GPI-Linked Proteins; High-Throughput Nucleotide Sequencing; Humans; Linkage Disequilibrium; Lysine; Male; Metabolomics; Middle Aged; Neural Cell Adhesion Molecules; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Impaired Amino Acid Transport at the Blood Brain Barrier Is a Cause of Autism Spectrum Disorder. - Tărlungeanu, Dora C; Deliu, Elena; Dotter, Christoph P; Kara, Majdi; Janiesch, Philipp Christoph; Scalise, Mariafrancesca; Galluccio, Michele; Tesulov, Mateja; Morelli, Emanuela; Sonmez, Fatma Mujgan; Bilguvar, Kaya; Ohgaki, Ryuichi; et al. (Cell, 2016)
Autism spectrum disorders (ASD) are a group of genetic disorders often overlapping with other neurological conditions. We previously described abnormalities in the branched-chain amino acid (BCAA) catabolic pathway as a cause of ASD. Here, we show that the solute carrier transporter 7a5 (SLC7A5), a large neutral amino acid transporter localized at the blood brain barrier (BBB), has an essential role in maintaining normal levels of brain BCAAs. In mice, deletion of Slc7a5 from the endothelial cells of the BBB leads to atypical brain amino acid profile, abnormal mRNA translation, and severe neurological abnormalities. Furthermore, we identified several patients with autistic traits and motor delay carrying deleterious homozygous mutations in the SLC7A5 gene. Finally, we demonstrate that BCAA intracerebroventricular administration ameliorates abnormal behaviors in adult mutant mice. Our data elucidate a neurological syndrome defined by SLC7A5 mutations and support an essential role for the BCAA in human brain function.
Keywords: Amino Acids; Animals; Autism Spectrum Disorder; Blood-Brain Barrier; Brain; Female; Humans; Infant; Infant, Newborn; Large Neutral Amino Acid-Transporter 1; Male; Mice; Mice, Knockout; Mutation; Pedigree; Protein Biosynthesis; Receptor, TIE-2

Increasing Generality and Power of Rare-Variant Tests by Utilizing Extended Pedigrees. - Sul, Jae Hoon; Cade, Brian E; Cho, Michael H; Qiao, Dandi; Silverman, Edwin K; Redline, Susan; Sunyaev, Shamil (Am J Hum Genet, 2016)
Recently, multiple studies have performed whole-exome or whole-genome sequencing to identify groups of rare variants associated with complex traits and diseases. They have primarily utilized case-control study designs that often require thousands of individuals to reach acceptable statistical power. Family-based studies can be more powerful because a rare variant can be enriched in an extended pedigree and segregate with the phenotype. Although many methods have been proposed for using family data to discover rare variants involved in a disease, a majority of them focus on a specific pedigree structure and are designed to analyze either binary or continuously measured outcomes. In this article, we propose RareIBD, a general and powerful approach to identifying rare variants involved in disease susceptibility. Our method can be applied to large extended families of arbitrary structure, including pedigrees with only affected individuals. The method accommodates both binary and quantitative traits. A series of simulation experiments suggest that RareIBD is a powerful test that outperforms existing approaches. In addition, our method accounts for individuals in top generations, which are not usually genotyped in extended families. In contrast to available statistical tests, RareIBD generates accurate p values even when genetic data from these individuals are missing. We applied RareIBD, as well as other methods, to two extended family datasets generated by different genotyping technologies and representing different ethnicities. The analysis of real data confirmed that RareIBD is the only method that properly controls type I error.
Keywords: Datasets as Topic; Ethnic Groups; Family; Female; Genetic Predisposition to Disease; Genetic Variation; Genotype; Humans; Male; Models, Genetic; Pedigree; Phenotype; Research Design

Keratoacanthoma Shares Driver Mutations with Cutaneous Squamous Cell Carcinoma. - Lim, Young H; Fisher, Jonathan M; Bosenberg, Marcus W; Choate, Keith A; Ko, Christine J (J Invest Dermatol, 2016)
Keywords: Aged; Aged, 80 and over; Biomarkers, Tumor; Biopsy; Carcinoma, Squamous Cell; Cohort Studies; Diagnosis, Differential; Exome; Female; Humans; Keratoacanthoma; Loss of Heterozygosity; Male; Middle Aged; Mutation; Polymorphism, Single Nucleotide; Skin; Skin Neoplasms; Whole Exome Sequencing

KIF5A mutations cause an infantile onset phenotype including severe myoclonus with evidence of mitochondrial dysfunction. - Duis, Jessica; Dean, Shannon; Applegate, Carolyn; Harper, Amy; Xiao, Rui; He, Weimin; Dollar, James D; Sun, Lisa R; Waberski, Marta Biderman; Crawford, Thomas O; Hamosh, Ada; Stafstrom, Carl E (Ann Neurol, 2016)
Missense mutations in kinesin family member 5A (KIF5A) cause spastic paraplegia 10. We report on 2 patients with de novo stop-loss frameshift variants in KIF5A resulting in a novel phenotype that includes severe infantile onset myoclonus, hypotonia, optic nerve abnormalities, dysphagia, apnea, and early developmental arrest. We propose that alteration and elongation of the carboxy-terminus of the protein has a dominant-negative effect, causing mitochondrial dysfunction in the setting of an abnormal kinesin "motor." These results highlight the role of expanded testing and whole-exome sequencing in critically ill infants and emphasize the importance of accurate test interpretation. Ann Neurol 2016;80:633-637.
Keywords: Apnea; Child, Preschool; Deglutition Disorders; Developmental Disabilities; Fatal Outcome; Female; Frameshift Mutation; Humans; Infant; Kinesins; Male; Mitochondrial Diseases; Muscle Hypotonia; Mutation; Myoclonus; Optic Nerve

Loss of B Cells in Patients with Heterozygous Mutations in IKAROS. - Kuehn, H S; Boisson, B; Cunningham-Rundles, C; Reichenbach, J; Stray-Pedersen, A; Gelfand, E W; Maffucci, P; Pierce, K R; Abbott, J K; Voelkerding, K V; South, S T; Augustine, N H; et al. (N Engl J Med, 2016)
BACKGROUND: Common variable immunodeficiency (CVID) is characterized by late-onset hypogammaglobulinemia in the absence of predisposing factors. The genetic cause is unknown in the majority of cases, and less than 10% of patients have a family history of the disease. Most patients have normal numbers of B cells but lack plasma cells. METHODS: We used whole-exome sequencing and array-based comparative genomic hybridization to evaluate a subset of patients with CVID and low B-cell numbers. Mutant proteins were analyzed for DNA binding with the use of an electrophoretic mobility-shift assay (EMSA) and confocal microscopy. Flow cytometry was used to analyze peripheral-blood lymphocytes and bone marrow aspirates. RESULTS: Six different heterozygous mutations in IKZF1, the gene encoding the transcription factor IKAROS, were identified in 29 persons from six families. In two families, the mutation was a de novo event in the proband. All the mutations, four amino acid substitutions, an intragenic deletion, and a 4.7-Mb multigene deletion involved the DNA-binding domain of IKAROS. The proteins bearing missense mutations failed to bind target DNA sequences on EMSA and confocal microscopy; however, they did not inhibit the binding of wild-type IKAROS. Studies in family members showed progressive loss of B cells and serum immunoglobulins. Bone marrow aspirates in two patients had markedly decreased early B-cell precursors, but plasma cells were present. Acute lymphoblastic leukemia developed in 2 of the 29 patients. CONCLUSIONS: Heterozygous mutations in the transcription factor IKAROS caused an autosomal dominant form of CVID that is associated with a striking decrease in B-cell numbers. (Funded by the National Institutes of Health and others.).
Keywords: Adolescent; Adult; Antigens, CD; B-Lymphocytes; Bone Marrow; Bone Marrow Examination; Child; Child, Preschool; Chromosomes, Human, Pair 7; Common Variable Immunodeficiency; Exome; Female; Heterozygote; Humans; Ikaros Transcription Factor; Immunoglobulin G; Lymphocyte Count; Male; Mutation; Pedigree; Sequence Analysis, DNA

Loss of carbonic anhydrase XII function in individuals with elevated sweat chloride concentration and pulmonary airway disease. - Lee, Melissa; Vecchio-Pagán, Briana; Sharma, Neeraj; Waheed, Abdul; Li, Xiaopeng; Raraigh, Karen S; Robbins, Sarah; Han, Sangwoo T; Franca, Arianna L; Pellicore, Matthew J; Evans, Taylor A; Arcara, Kristin M; et al. (Hum Mol Genet, 2016)
Elevated sweat chloride levels, failure to thrive (FTT), and lung disease are characteristic features of cystic fibrosis (CF, OMIM #219700). Here we describe variants in CA12 encoding carbonic anhydrase XII in two pedigrees exhibiting CF-like phenotypes. Exome sequencing of a white American adult diagnosed with CF due to elevated sweat chloride, recurrent hyponatremia, infantile FTT and lung disease identified deleterious variants in each CA12 gene: c.908-1 G>A in a splice acceptor and a novel frameshift insertion c.859_860insACCT. In an unrelated consanguineous Omani family, two children with elevated sweat chloride, infantile FTT, and recurrent hyponatremia were homozygous for a novel missense variant (p.His121Gln). Deleterious CFTR variants were absent in both pedigrees. CA XII protein was localized apically in human bronchiolar epithelia and basolaterally in the reabsorptive duct of human sweat glands. Respiratory epithelial cell RNA from the adult proband revealed only aberrant CA12 transcripts and in vitro analysis showed greatly reduced CA XII protein. Studies of ion transport across respiratory epithelial cells in vivo and in culture revealed intact CFTR-mediated chloride transport in the adult proband. CA XII protein bearing either p.His121Gln or a previously identified p.Glu143Lys missense variant localized to the basolateral membranes of polarized Madin-Darby canine kidney (MDCK) cells, but enzyme activity was severely diminished when assayed at physiologic concentrations of extracellular chloride. Our findings indicate that loss of CA XII function should be considered in individuals without CFTR mutations who exhibit CF-like features in the sweat gland and lung.
Keywords: Adolescent; Adult; Animals; Carbonic Anhydrases; Child; Child, Preschool; Chlorides; Cystic Fibrosis; Cystic Fibrosis Transmembrane Conductance Regulator; Dogs; Female; Gene Expression Regulation, Enzymologic; Homozygote; Humans; Lung; Lung Diseases; Madin Darby Canine Kidney Cells; Male; Mutation; Pedigree; Phenotype; Sweat

Loss-of-Function Mutations in FRRS1L Lead to an Epileptic-Dyskinetic Encephalopathy. - Madeo, Marianna; Stewart, Michelle; Sun, Yuyang; Sahir, Nadia; Wiethoff, Sarah; Chandrasekar, Indra; Yarrow, Anna; Rosenfeld, Jill A; Yang, Yaping; Cordeiro, Dawn; McCormick, Elizabeth M; Muraresku, Colleen C; et al. (Am J Hum Genet, 2016)
Glutamatergic neurotransmission governs excitatory signaling in the mammalian brain, and abnormalities of glutamate signaling have been shown to contribute to both epilepsy and hyperkinetic movement disorders. The etiology of many severe childhood movement disorders and epilepsies remains uncharacterized. We describe a neurological disorder with epilepsy and prominent choreoathetosis caused by biallelic pathogenic variants in FRRS1L, which encodes an AMPA receptor outer-core protein. Loss of FRRS1L function attenuates AMPA-mediated currents, implicating chronic abnormalities of glutamatergic neurotransmission in this monogenic neurological disease of childhood.
Keywords: alpha-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic Acid; Brain Diseases; Electrophysiology; Epilepsy; Female; Humans; Hyperkinesis; Infant; Male; Membrane Proteins; Mutation; Nerve Tissue Proteins; Pedigree; Synaptic Transmission

Loss-of-function variants influence the human serum metabolome. - Yu, Bing; Li, Alexander H; Metcalf, Ginger A; Muzny, Donna M; Morrison, Alanna C; White, Simon; Mosley, Thomas H; Gibbs, Richard A; Boerwinkle, Eric (Sci Adv, 2016)
The metabolome is a collection of small molecules resulting from multiple cellular and biological processes that can act as biomarkers of disease, and African-Americans exhibit high levels of genetic diversity. Exome sequencing of a sample of deeply phenotyped African-Americans allowed us to analyze the effects of annotated loss-of-function (LoF) mutations on 308 serum metabolites measured by untargeted liquid and gas chromatography coupled with mass spectrometry. In an independent sample, we identified and replicated four genes harboring six LoF mutations that significantly affected five metabolites. These sites were related to a 19 to 45% difference in geometric mean metabolite levels, with an average effect size of 25%. We show that some of the affected metabolites are risk predictors or diagnostic biomarkers of disease and, using the principle of Mendelian randomization, are in the causal pathway of disease. For example, LoF mutations in SLCO1B1 elevate the levels of hexadecanedioate, a fatty acid significantly associated with increased blood pressure levels and risk of incident heart failure in both African-Americans and an independent sample of European-Americans. We show that SLCO1B1 LoF mutations significantly increase the risk of incident heart failure, thus implicating the metabolite in the causal pathway of disease. These results reveal new avenues into gene function and the understanding of disease etiology by integrating -omic technologies into a deeply phenotyped population study.
Keywords: Aged; Biomarkers; Black or African American; Exome; Female; Genetic Variation; Heart Failure; High-Throughput Nucleotide Sequencing; Humans; Hypertension; Liver-Specific Organic Anion Transporter 1; Male; Metabolome; Middle Aged; Mutation; Risk Factors; White People

LOX Mutations Predispose to Thoracic Aortic Aneurysms and Dissections. - Guo, Dong-Chuan; Regalado, Ellen S; Gong, Limin; Duan, Xueyan; Santos-Cortez, Regie Lyn P; Arnaud, Pauline; Ren, Zhao; Cai, Bo; Hostetler, Ellen M; Moran, Rocio; Liang, David; Estrera, Anthony; et al. (Circ Res, 2016)
RATIONALE: Mutations in several genes have been identified that are responsible for 25% of families with familial thoracic aortic aneurysms and dissections. However, the causative gene remains unknown in 75% of families. OBJECTIVES: To identify the causative mutation in families with autosomal dominant inheritance of thoracic aortic aneurysms and dissections. METHODS AND RESULTS: Exome sequencing was used to identify the mutation responsible for a large family with thoracic aortic aneurysms and dissections. A heterozygous rare variant, c.839G>T (p.Ser280Arg), was identified in LOX, encoding a lysyl oxidase, that segregated with disease in the family. Sanger and exome sequencing was used to investigate mutations in LOX in an additional 410 probands from unrelated families. Additional LOX rare variants that segregated with disease in families were identified, including c.125G>A (p.Trp42*), c.604G>T (p.Gly202*), c.743C>T (p.Thr248Ile), c.800A>C (p.Gln267Pro), and c.1044T>A (p.Ser348Arg). The altered amino acids cause haploinsufficiency for LOX or are located at a highly conserved LOX catalytic domain, which is relatively invariant in the population. Expression of the LOX variants p.Ser280Arg and p.Ser348Arg resulted in significantly lower lysyl oxidase activity when compared with the wild-type protein. Individuals with LOX variants had fusiform enlargement of the root and ascending thoracic aorta, leading to ascending aortic dissections. CONCLUSIONS: These data, along with previous studies showing that the deficiency of LOX in mice or inhibition of lysyl oxidases in turkeys and rats causes aortic dissections, support the conclusion that rare genetic variants in LOX predispose to thoracic aortic disease.
Keywords: Adult; Aged; Amino Acid Sequence; Aneurysm, Dissecting; Aortic Aneurysm, Thoracic; Female; Genetic Variation; Humans; Male; Middle Aged; Molecular Sequence Data; Mutation; Pedigree; Protein-Lysine 6-Oxidase

Mechanisms for the Generation of Two Quadruplications Associated with Split-Hand Malformation. - Gu, Shen; Posey, Jennifer E; Yuan, Bo; Carvalho, Claudia M B; Luk, H M; Erikson, Kelly; Lo, Ivan F M; Leung, Gordon K C; Pickering, Curtis R; Chung, Brian H Y; Lupski, James R (Hum Mutat, 2016)
Germline copy-number variants (CNVs) involving quadruplications are rare and the mechanisms generating them are largely unknown. Previously, we reported a 20-week gestation fetus with split-hand malformation; clinical microarray detected two maternally inherited triplications separated by a copy-number neutral region at 17p13.3, involving BHLHA9 and part of YWHAE. Here, we describe an 18-month-old male sibling of the previously described fetus with split-hand malformation. Custom high-density microarray and digital droplet PCR revealed the copy-number gains were actually quadruplications in the mother, the fetus, and her later born son. This quadruplication-normal-quadruplication pattern was shown to be expanded from the triplication-normal-triplication CNV at the same loci in the maternal grandmother. We mapped two breakpoint junctions and demonstrated that both are mediated by Alu repetitive elements and identical in these four individuals. We propose a three-step process combining Alu-mediated replicative-repair-based mechanism(s) and intergenerational, intrachromosomal nonallelic homologous recombination to generate the quadruplications in this family.
Keywords: 14-3-3 Proteins; Adult; Aged; Alu Elements; Base Sequence; Basic Helix-Loop-Helix Transcription Factors; Chromosome Duplication; Chromosomes, Human, Pair 17; DNA Copy Number Variations; Female; Genetic Loci; Genome, Human; Hand Deformities, Congenital; Humans; Infant; Male; Molecular Sequence Data; Pedigree; Sequence Alignment; Sequence Analysis, DNA

MECR Mutations Cause Childhood-Onset Dystonia and Optic Atrophy, a Mitochondrial Fatty Acid Synthesis Disorder. - Heimer, Gali; Kerätär, Juha M; Riley, Lisa G; Balasubramaniam, Shanti; Eyal, Eran; Pietikäinen, Laura P; Hiltunen, J Kalervo; Marek-Yagel, Dina; Hamada, Jeffrey; Gregory, Allison; Rogers, Caleb; Hogarth, Penelope; et al. (Am J Hum Genet, 2016)
Mitochondrial fatty acid synthesis (mtFAS) is an evolutionarily conserved pathway essential for the function of the respiratory chain and several mitochondrial enzyme complexes. We report here a unique neurometabolic human disorder caused by defective mtFAS. Seven individuals from five unrelated families presented with childhood-onset dystonia, optic atrophy, and basal ganglia signal abnormalities on MRI. All affected individuals were found to harbor recessive mutations in MECR encoding the mitochondrial trans-2-enoyl-coenzyme A-reductase involved in human mtFAS. All six mutations are extremely rare in the general population, segregate with the disease in the families, and are predicted to be deleterious. The nonsense c.855T>G (p.Tyr285), c.247_250del (p.Asn83Hisfs4), and splice site c.830+2_830+3insT mutations lead to C-terminal truncation variants of MECR. The missense c.695G>A (p.Gly232Glu), c.854A>G (p.Tyr285Cys), and c.772C>T (p.Arg258Trp) mutations involve conserved amino acid residues, are located within the cofactor binding domain, and are predicted by structural analysis to have a destabilizing effect. Yeast modeling and complementation studies validated the pathogenicity of the MECR mutations. Fibroblast cell lines from affected individuals displayed reduced levels of both MECR and lipoylated proteins as well as defective respiration. These results suggest that mutations in MECR cause a distinct human disorder of the mtFAS pathway. The observation of decreased lipoylation raises the possibility of a potential therapeutic strategy.
Keywords: Basal Ganglia; Cells, Cultured; Child; Child, Preschool; Dystonic Disorders; Fatty Acids; Female; Fibroblasts; Genetic Complementation Test; Humans; Infant; Male; Mitochondria; Mitochondrial Diseases; Models, Molecular; Mutation; Mutation, Missense; Optic Atrophy; Oxidoreductases Acting on CH-CH Group Donors; Pedigree; RNA Splice Sites; Saccharomyces cerevisiae

MIPEP recessive variants cause a syndrome of left ventricular non-compaction, hypotonia, and infantile death. - Eldomery, Mohammad K; Akdemir, Zeynep C; Vögtle, F-Nora; Charng, Wu-Lin; Mulica, Patrycja; Rosenfeld, Jill A; Gambin, Tomasz; Gu, Shen; Burrage, Lindsay C; Al Shamsi, Aisha; Penney, Samantha; Jhangiani, Shalini N; et al. (Genome Med, 2016)
BACKGROUND: Mitochondrial presequence proteases perform fundamental functions as they process about 70 % of all mitochondrial preproteins that are encoded in the nucleus and imported posttranslationally. The mitochondrial intermediate presequence protease MIP/Oct1, which carries out precursor processing, has not yet been established to have a role in human disease. METHODS: Whole exome sequencing was performed on four unrelated probands with left ventricular non-compaction (LVNC), developmental delay (DD), seizures, and severe hypotonia. Proposed pathogenic variants were confirmed by Sanger sequencing or array comparative genomic hybridization. Functional analysis of the identified MIP variants was performed using the model organism Saccharomyces cerevisiae as the protein and its functions are highly conserved from yeast to human. RESULTS: Biallelic single nucleotide variants (SNVs) or copy number variants (CNVs) in MIPEP, which encodes MIP, were present in all four probands, three of whom had infantile/childhood death. Two patients had compound heterozygous SNVs (p.L582R/p.L71Q and p.E602*/p.L306F) and one patient from a consanguineous family had a homozygous SNV (p.K343E). The fourth patient, identified through the GeneMatcher tool, a part of the Matchmaker Exchange Project, was found to have inherited a paternal SNV (p.H512D) and a maternal CNV (1.4-Mb deletion of 13q12.12) that includes MIPEP. All amino acids affected in the patients' missense variants are highly conserved from yeast to human and therefore S. cerevisiae was employed for functional analysis (for p.L71Q, p.L306F, and p.K343E). The mutations p.L339F (human p.L306F) and p.K376E (human p.K343E) resulted in a severe decrease of Oct1 protease activity and accumulation of non-processed Oct1 substrates and consequently impaired viability under respiratory growth conditions. The p.L83Q (human p.L71Q) failed to localize to the mitochondria. CONCLUSIONS: Our findings reveal for the first time the role of the mitochondrial intermediate peptidase in human disease. Loss of MIP function results in a syndrome which consists of LVNC, DD, seizures, hypotonia, and cataracts. Our approach highlights the power of data exchange and the importance of an interrelationship between clinical and research efforts for disease gene discovery.
Keywords: Adult; Amino Acid Sequence; Female; Genes, Recessive; Heart Defects, Congenital; Humans; Infant; Infant, Newborn; Male; Metalloendopeptidases; Muscle Hypotonia; Pedigree; Phenotype; Sequence Homology, Amino Acid; Sudden Infant Death; Syndrome

Mitral regurgitation as a phenotypic manifestation of nonphotosensitive trichothiodystrophy due to a splice variant in MPLKIP. - Shah, Khadim; Ali, Raja Hussain; Ansar, Muhammad; Lee, Kwanghyuk; Chishti, Muhammad Salman; Abbe, Izoduwa; Li, Biao; Smith, Joshua D; Nickerson, Deborah A; Shendure, Jay; Coucke, Paul J; Steyaert, Wouter; et al. (BMC Med Genet, 2016)
BACKGROUND: Nonphotosensitive trichothiodystrophy (TTDN) is a rare autosomal recessive disorder of neuroectodermal origin. The condition is marked by hair abnormalities, intellectual impairment, nail dystrophies and susceptibility to infections but with no UV sensitivity. METHODS: We identified three consanguineous Pakistani families with varied TTDN features and used homozygosity mapping, linkage analysis, and Sanger and exome sequencing in order to identify pathogenic variants. Haplotype analysis was performed and haplotype age estimated. A splicing assay was used to validate the effect of the MPLKIP splice variant on expression. RESULTS: Affected individuals from all families exhibit several TTDN features along with a heart-specific feature, i.e. mitral regurgitation. Exome sequencing in the probands from families ED168 and ED241 identified a homozygous splice mutation c.339 + 1G > A within MPLKIP. The same splice variant co-segregates with TTDN in a third family ED210. The MPLKIP splice variant was not found in public databases, e.g. the Exome Aggregation Consortium, and in unrelated Pakistani controls. Functional analysis of the splice variant confirmed intron retention, which leads to protein truncation and loss of a phosphorylation site. Haplotype analysis identified a 585.1-kb haplotype which includes the MPLKIP variant, supporting the existence of a founder haplotype that is estimated to be 25,900 years old. CONCLUSION: This study extends the allelic and phenotypic spectra of MPLKIP-related TTDN, to include a splice variant that causes cardiomyopathy as part of the TTDN phenotype.
Keywords: Adaptor Proteins, Signal Transducing; Adolescent; Adult; Alleles; Asian Continental Ancestry Group; Child; Cloning, Molecular; Exome; Female; Genetic Linkage; Haplotypes; HEK293 Cells; Homozygote; Humans; Introns; Male; Mitral Valve Insufficiency; Pakistan; Pedigree; Phenotype; Polymorphism, Single Nucleotide; RNA Splicing; Sequence Analysis, DNA; Trichothiodystrophy Syndromes; Young Adult

Molecular diagnostic experience of whole-exome sequencing in adult patients. - Posey, Jennifer E; Rosenfeld, Jill A; James, Regis A; Bainbridge, Matthew; Niu, Zhiyv; Wang, Xia; Dhar, Shweta; Wiszniewski, Wojciech; Akdemir, Zeynep H C; Gambin, Tomasz; Xia, Fan; Person, Richard E; et al. (Genet Med, 2016)
PURPOSE: Whole-exome sequencing (WES) is increasingly used as a diagnostic tool in medicine, but prior reports focus on predominantly pediatric cohorts with neurologic or developmental disorders. We describe the diagnostic yield and characteristics of WES in adults. METHODS: We performed a retrospective analysis of consecutive WES reports for adults from a diagnostic laboratory. Phenotype composition was determined using Human Phenotype Ontology terms. RESULTS: Molecular diagnoses were reported for 17.5% (85/486) of adults, which is lower than that for a primarily pediatric population (25.2%; P = 0.0003); the diagnostic rate was higher (23.9%) for those 18-30 years of age compared to patients older than 30 years (10.4%; P = 0.0001). Dual Mendelian diagnoses contributed to 7% of diagnoses, revealing blended phenotypes. Diagnoses were more frequent among individuals with abnormalities of the nervous system, skeletal system, head/neck, and growth. Diagnostic rate was independent of family history information, and de novo mutations contributed to 61.4% of autosomal dominant diagnoses. CONCLUSION: Early WES experience in adults demonstrates molecular diagnoses in a substantial proportion of patients, informing clinical management, recurrence risk, and recommendations for relatives. A positive family history was not predictive, consistent with molecular diagnoses often revealed by de novo events, informing the Mendelian basis of genetic disease in adults.Genet Med 18 7, 678-685.
Keywords: Adult; Exome; Female; Genetic Diseases, Inborn; Genetic Predisposition to Disease; Genetic Testing; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Male; Pathology, Molecular

Molecular etiology of arthrogryposis in multiple families of mostly Turkish origin. - Bayram, Yavuz; Karaca, Ender; Coban Akdemir, Zeynep; Yilmaz, Elif Ozdamar; Tayfun, Gulsen Akay; Aydin, Hatip; Torun, Deniz; Bozdogan, Sevcan Tug; Gezdirici, Alper; Isikay, Sedat; Atik, Mehmed M; Gambin, Tomasz; et al. (J Clin Invest, 2016)
BACKGROUND: Arthrogryposis, defined as congenital joint contractures in 2 or more body areas, is a clinical sign rather than a specific disease diagnosis. To date, more than 400 different disorders have been described that present with arthrogryposis, and variants of more than 220 genes have been associated with these disorders; however, the underlying molecular etiology remains unknown in the considerable majority of these cases. METHODS: We performed whole exome sequencing (WES) of 52 patients with clinical presentation of arthrogryposis from 48 different families. RESULTS: Affected individuals from 17 families (35.4%) had variants in known arthrogryposis-associated genes, including homozygous variants of cholinergic γ nicotinic receptor (CHRNG, 6 subjects) and endothelin converting enzyme-like 1 (ECEL1, 4 subjects). Deleterious variants in candidate arthrogryposis-causing genes (fibrillin 3 [FBN3], myosin IXA [MYO9A], and pleckstrin and Sec7 domain containing 3 [PSD3]) were identified in 3 families (6.2%). Moreover, in 8 families with a homozygous mutation in an arthrogryposis-associated gene, we identified a second locus with either a homozygous or compound heterozygous variant in a candidate gene (myosin binding protein C, fast type [MYBPC2] and vacuolar protein sorting 8 [VPS8], 2 families, 4.2%) or in another disease-associated genes (6 families, 12.5%), indicating a potential mutational burden contributing to disease expression. CONCLUSION: In 58.3% of families, the arthrogryposis manifestation could be explained by a molecular diagnosis; however, the molecular etiology in subjects from 20 families remained unsolved by WES. Only 5 of these 20 unrelated subjects had a clinical presentation consistent with amyoplasia; a phenotype not thought to be of genetic origin. Our results indicate that increased use of genome-wide technologies will provide opportunities to better understand genetic models for diseases and molecular mechanisms of genetically heterogeneous disorders, such as arthrogryposis. FUNDING: This work was supported in part by US National Human Genome Research Institute (NHGRI)/National Heart, Lung, and Blood Institute (NHLBI) grant U54HG006542 to the Baylor-Hopkins Center for Mendelian Genomics, and US National Institute of Neurological Disorders and Stroke (NINDS) grant R01NS058529 to J.R. Lupski.
Keywords: Arthrogryposis; Exome; Family; Female; Genome-Wide Association Study; Humans; Male; Turkey

Monoallelic and Biallelic Variants in EMC1 Identified in Individuals with Global Developmental Delay, Hypotonia, Scoliosis, and Cerebellar Atrophy. - Harel, Tamar; Yesil, Gözde; Bayram, Yavuz; Coban-Akdemir, Zeynep; Charng, Wu-Lin; Karaca, Ender; Al Asmari, Ali; Eldomery, Mohammad K; Hunter, Jill V; Jhangiani, Shalini N; Rosenfeld, Jill A; Pehlivan, Davut; et al. (Am J Hum Genet, 2016)
The paradigm of a single gene associated with one specific phenotype and mode of inheritance has been repeatedly challenged. Genotype-phenotype correlations can often be traced to different mutation types, localization of the variants in distinct protein domains, or the trigger of or escape from nonsense-mediated decay. Using whole-exome sequencing, we identified homozygous variants in EMC1 that segregated with a phenotype of developmental delay, hypotonia, scoliosis, and cerebellar atrophy in three families. In addition, a de novo heterozygous EMC1 variant was seen in an individual with a similar clinical and MRI imaging phenotype. EMC1 encodes a member of the endoplasmic reticulum (ER)-membrane protein complex (EMC), an evolutionarily conserved complex that has been proposed to have multiple roles in ER-associated degradation, ER-mitochondria tethering, and proper assembly of multi-pass transmembrane proteins. Perturbations of protein folding and organelle crosstalk have been implicated in neurodegenerative processes including cerebellar atrophy. We propose EMC1 as a gene in which either biallelic or monoallelic variants might lead to a syndrome including intellectual disability and preferential degeneration of the cerebellum.
Keywords: Adolescent; Alleles; Amino Acid Sequence; Atrophy; Cerebellum; Child; Child, Preschool; Developmental Disabilities; Endoplasmic Reticulum-Associated Degradation; Female; Genetic Association Studies; Genetic Variation; Heterozygote; Humans; Magnetic Resonance Imaging; Male; Molecular Sequence Data; Muscle Hypotonia; Mutation; Pedigree; Protein Folding; Proteins; Scoliosis

Mosaic Activating Mutations in FGFR1 Cause Encephalocraniocutaneous Lipomatosis. - Bennett, James T; Tan, Tiong Yang; Alcantara, Diana; Tétrault, Martine; Timms, Andrew E; Jensen, Dana; Collins, Sarah; Nowaczyk, Malgorzata J M; Lindhurst, Marjorie J; Christensen, Katherine M; Braddock, Stephen R; Brandling-Bennett, Heather; et al. (Am J Hum Genet, 2016)
Encephalocraniocutaneous lipomatosis (ECCL) is a sporadic condition characterized by ocular, cutaneous, and central nervous system anomalies. Key clinical features include a well-demarcated hairless fatty nevus on the scalp, benign ocular tumors, and central nervous system lipomas. Seizures, spasticity, and intellectual disability can be present, although affected individuals without seizures and with normal intellect have also been reported. Given the patchy and asymmetric nature of the malformations, ECCL has been hypothesized to be due to a post-zygotic, mosaic mutation. Despite phenotypic overlap with several other disorders associated with mutations in the RAS-MAPK and PI3K-AKT pathways, the molecular etiology of ECCL remains unknown. Using exome sequencing of DNA from multiple affected tissues from five unrelated individuals with ECCL, we identified two mosaic mutations, c.1638C>A (p.Asn546Lys) and c.1966A>G (p.Lys656Glu) within the tyrosine kinase domain of FGFR1, in two affected individuals each. These two residues are the most commonly mutated residues in FGFR1 in human cancers and are associated primarily with CNS tumors. Targeted resequencing of FGFR1 in multiple tissues from an independent cohort of individuals with ECCL identified one additional individual with a c.1638C>A (p.Asn546Lys) mutation in FGFR1. Functional studies of ECCL fibroblast cell lines show increased levels of phosphorylated FGFRs and phosphorylated FRS2, a direct substrate of FGFR1, as well as constitutive activation of RAS-MAPK signaling. In addition to identifying the molecular etiology of ECCL, our results support the emerging overlap between mosaic developmental disorders and tumorigenesis.
Keywords: Adolescent; Cell Line, Tumor; Central Nervous System Neoplasms; Child, Preschool; Exome; Eye; Eye Diseases; Female; Humans; Infant; Lipomatosis; Male; Mutation; Mutation, Missense; Neurocutaneous Syndromes; Phosphatidylinositol 3-Kinases; Proto-Oncogene Proteins c-akt; Receptor, Fibroblast Growth Factor, Type 1; Seizures; Sequence Analysis, DNA

Mutations in CEP120 cause Joubert syndrome as well as complex ciliopathy phenotypes. - Roosing, Susanne; Romani, Marta; Isrie, Mala; Rosti, Rasim Ozgur; Micalizzi, Alessia; Musaev, Damir; Mazza, Tommaso; Al-Gazali, Lihadh; Altunoglu, Umut; Boltshauser, Eugen; D'Arrigo, Stefano; De Keersmaecker, Bart; et al. (J Med Genet, 2016)
BACKGROUND: Ciliopathies are an extensive group of autosomal recessive or X-linked disorders with considerable genetic and clinical overlap, which collectively share multiple organ involvement and may result in lethal or viable phenotypes. In large numbers of cases the genetic defect remains yet to be determined. The aim of this study is to describe the mutational frequency and phenotypic spectrum of the CEP120 gene. METHODS: Exome sequencing was performed in 145 patients with Joubert syndrome (JS), including 15 children with oral-facial-digital syndrome type VI (OFDVI) and 21 Meckel syndrome (MKS) fetuses. Moreover, exome sequencing was performed in one fetus with tectocerebellar dysraphia with occipital encephalocele (TCDOE), molar tooth sign and additional skeletal abnormalities. As a parallel study, 346 probands with a phenotype consistent with JS or related ciliopathies underwent next-generation sequencing-based targeted sequencing of 120 previously described and candidate ciliopathy genes. RESULTS: We present six probands carrying nine distinct mutations (of which eight are novel) in the CEP120 gene, previously found mutated only in Jeune asphyxiating thoracic dystrophy (JATD). The CEP120-associated phenotype ranges from mild classical JS in four patients to more severe conditions in two fetuses, with overlapping features of distinct ciliopathies that include TCDOE, MKS, JATD and OFD syndromes. No obvious correlation is evident between the type or location of identified mutations and the ciliopathy phenotype. CONCLUSION: Our findings broaden the spectrum of phenotypes caused by CEP120 mutations that account for nearly 1% of patients with JS as well as for more complex ciliopathy phenotypes. The lack of clear genotype-phenotype correlation highlights the relevance of comprehensive genetic analyses in the diagnostics of ciliopathies.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; Cell Cycle Proteins; Cerebellar Diseases; Cerebellum; Child; Ciliopathies; Encephalocele; Eye Abnormalities; Female; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Testing; Humans; Kidney Diseases, Cystic; Male; Mutation; Mutation Rate; Orofaciodigital Syndromes; Pedigree; Phenotype; Retina; Sequence Alignment

Mutations in DCDC2 (doublecortin domain containing protein 2) in neonatal sclerosing cholangitis. - Grammatikopoulos, Tassos; Sambrotta, Melissa; Strautnieks, Sandra; Foskett, Pierre; Knisely, A S; Wagner, Bart; Deheragoda, Maesha; Starling, Chris; Mieli-Vergani, Giorgina; Smith, Joshua; Bull, Laura; Thompson, Richard J (J Hepatol, 2016)
BACKGROUND & AIMS: Neonatal sclerosing cholangitis (NSC) is a severe neonatal-onset cholangiopathy commonly leading to liver transplantation (LT) for end-stage liver disease in childhood. Liver biopsy findings histopathologically resemble those in biliary atresia (BA); however, in NSC extrahepatic bile ducts are patent, whilst in BA their lumina are obliterated. NSC is commonly seen in consanguineous kindreds, suggesting autosomal recessive inheritance. METHODS: From 29 NSC patients (24 families) identified, DNA was available in 24 (21 families). Thirteen (7 male) patients (12 families) of consanguineous parentage were selected for whole exome sequencing. Sequence variants were filtered for homozygosity, pathogenicity, minor allele frequency, quality score, and encoded protein expression pattern. RESULTS: Four of 13 patients were homozygous and two were compound heterozygous for mutations in the doublecortin domain containing 2 gene (DCDC2), which encodes DCDC2 protein and is expressed in cholangiocyte cilia. Another 11 patients were sequenced: one (with one sibling pair) was compound heterozygous for DCDC2 mutations. All mutations were protein-truncating. In available liver tissue from patients with DCDC2 mutations, immunostaining for human DCDC2 and the ciliary protein acetylated alpha-tubulin (ACALT) showed no expression (n=6) and transmission electron microscopy found that cholangiocytes lacked primary cilia (n=5). DCDC2 and ACALT were expressed in NSC patients without DCDC2 mutations (n=22). Of the patients carrying DCDC2 mutations, one died awaiting LT; five came to LT, of whom one died 2years later. The other 4 are well. CONCLUSION: Among 24 NSC patients with available DNA, 7 had mutations in DCDC2 (6 of 19 families). NSC patients in substantial proportion harbour mutations in DCDC2. Their disease represents a novel liver-based ciliopathy. LAY SUMMARY: Neonatal sclerosing cholangitis (NSC) is a rare genetic form of liver disease presenting in infancy. Through next generation sequencing we identified mutations in the gene encoding for doublecortin domain containing 2 (DCDC2) protein in a group of NSC children. DCDC2 is a signalling and structural protein found in primary cilia of cholangiocytes. Cholangiocytes are the cells forming the biliary system which is the draining system of the liver.
Keywords: Cholangitis, Sclerosing; Female; High-Throughput Nucleotide Sequencing; Humans; Infant, Newborn; Male; Microtubule-Associated Proteins; Mutation

Mutations in MBOAT7, Encoding Lysophosphatidylinositol Acyltransferase I, Lead to Intellectual Disability Accompanied by Epilepsy and Autistic Features. - Johansen, Anide; Rosti, Rasim O; Musaev, Damir; Sticca, Evan; Harripaul, Ricardo; Zaki, Maha; Çağlayan, Ahmet Okay; Azam, Matloob; Sultan, Tipu; Froukh, Tawfiq; Reis, André; Popp, Bernt; et al. (Am J Hum Genet, 2016)
The risk of epilepsy among individuals with intellectual disability (ID) is approximately ten times that of the general population. From a cohort of >5,000 families affected by neurodevelopmental disorders, we identified six consanguineous families harboring homozygous inactivating variants in MBOAT7, encoding lysophosphatidylinositol acyltransferase (LPIAT1). Subjects presented with ID frequently accompanied by epilepsy and autistic features. LPIAT1 is a membrane-bound phospholipid-remodeling enzyme that transfers arachidonic acid (AA) to lysophosphatidylinositol to produce AA-containing phosphatidylinositol. This study suggests a role for AA-containing phosphatidylinositols in the development of ID accompanied by epilepsy and autistic features.
Keywords: Acyltransferases; Arachidonic Acid; Autistic Disorder; Child; Child, Preschool; Consanguinity; Epilepsy; Female; Homozygote; Humans; Infant; Intellectual Disability; Lysophospholipids; Male; Membrane Proteins; Mutation; Pedigree; Phosphatidylinositols

Mutations in nuclear pore genes NUP93, NUP205 and XPO5 cause steroid-resistant nephrotic syndrome. - Braun, Daniela A; Sadowski, Carolin E; Kohl, Stefan; Lovric, Svjetlana; Astrinidis, Susanne A; Pabst, Werner L; Gee, Heon Yung; Ashraf, Shazia; Lawson, Jennifer A; Shril, Shirlee; Airik, Merlin; Tan, Weizhen; et al. (Nat Genet, 2016)
Nucleoporins are essential components of the nuclear pore complex (NPC). Only a few diseases have been attributed to NPC dysfunction. Steroid-resistant nephrotic syndrome (SRNS), a frequent cause of chronic kidney disease, is caused by dysfunction of glomerular podocytes. Here we identify in eight families with SRNS mutations in NUP93, its interaction partner NUP205 or XPO5 (encoding exportin 5) as hitherto unrecognized monogenic causes of SRNS. NUP93 mutations caused disrupted NPC assembly. NUP93 knockdown reduced the presence of NUP205 in the NPC, and, reciprocally, a NUP205 alteration abrogated NUP93 interaction. We demonstrate that NUP93 and exportin 5 interact with the signaling protein SMAD4 and that NUP93 mutations abrogated interaction with SMAD4. Notably, NUP93 mutations interfered with BMP7-induced SMAD transcriptional reporter activity. We hereby demonstrate that mutations of NUP genes cause a distinct renal disease and identify aberrant SMAD signaling as a new disease mechanism of SRNS, opening a potential new avenue for treatment.
Keywords: Age of Onset; Amino Acid Sequence; Animals; Cell Movement; Cell Proliferation; Cells, Cultured; Child; Child, Preschool; Drug Resistance; Female; Genes, Recessive; Genetic Association Studies; Genetic Linkage; HEK293 Cells; Humans; Infant; Karyopherins; Male; Mice; Molecular Sequence Data; Mutation; Nephrotic Syndrome; Nuclear Pore Complex Proteins; Oxidative Stress; Podocytes; Sequence Analysis, DNA; Steroids; Xenopus laevis

Mutations in the Histone Modifier PRDM6 Are Associated with Isolated Nonsyndromic Patent Ductus Arteriosus. - Li, Na; Subrahmanyan, Lakshman; Smith, Emily; Yu, Xiaoqing; Zaidi, Samir; Choi, Murim; Mane, Shrikant; Nelson-Williams, Carol; Behjati, Mohaddeseh; Kazemi, Mohammad; Hashemi, Mohammad; Fathzadeh, Mohsen; et al. (Am J Hum Genet, 2016)
Nonsyndromic patent ductus arteriosus (PDA) is a common congenital heart defect (CHD) with both inherited and acquired causes, but the disease mechanisms have remained elusive. Using combined genome-wide linkage analysis and whole-exome sequencing (WES), we identified independent mutations in PRDM6, which encodes a nuclear protein that is specific to vascular smooth muscle cells (VSMC), has histone methyl transferase activities, and acts as a transcriptional suppressor of contractile proteins. In vitro assays showed that the mutations cause loss of function either by intracellular redistribution of the protein and/or by alteration of its methyltransferase activities. Wild-type embryonic ductus arteriosus (DA) exhibited high levels of PRDM6, which rapidly declined postnatally as the number of VSMCs necessary for ductus contraction increased. This dynamic change suggests that PRDM6 plays a key role in maintaining VSMCs in an undifferentiated stage in order to promote their proliferation and that its loss of activity results in premature differentiation and impaired remodeling of the DA. Our findings identify PRDM6 mutations as underlying genetic causes of nonsyndromic isolated PDA in humans and implicates the wild-type protein in epigenetic regulation of ductus remodeling.
Keywords: Cell Differentiation; Cells, Cultured; Ductus Arteriosus, Patent; Epigenesis, Genetic; Female; Fluorescent Antibody Technique; Histones; Humans; Immunoblotting; Male; Muscle Proteins; Muscle, Smooth, Vascular; Mutation; Pedigree; Transcription Factors

Mutations in the nuclear bile acid receptor FXR cause progressive familial intrahepatic cholestasis. - Gomez-Ospina, Natalia; Potter, Carol J; Xiao, Rui; Manickam, Kandamurugu; Kim, Mi-Sun; Kim, Kang Ho; Shneider, Benjamin L; Picarsic, Jennifer L; Jacobson, Theodora A; Zhang, Jing; He, Weimin; Liu, Pengfei; et al. (Nat Commun, 2016)
Neonatal cholestasis is a potentially life-threatening condition requiring prompt diagnosis. Mutations in several different genes can cause progressive familial intrahepatic cholestasis, but known genes cannot account for all familial cases. Here we report four individuals from two unrelated families with neonatal cholestasis and mutations in NR1H4, which encodes the farnesoid X receptor (FXR), a bile acid-activated nuclear hormone receptor that regulates bile acid metabolism. Clinical features of severe, persistent NR1H4-related cholestasis include neonatal onset with rapid progression to end-stage liver disease, vitamin K-independent coagulopathy, low-to-normal serum gamma-glutamyl transferase activity, elevated serum alpha-fetoprotein and undetectable liver bile salt export pump (ABCB11) expression. Our findings demonstrate a pivotal function for FXR in bile acid homeostasis and liver protection.
Keywords: ATP Binding Cassette Transporter, Subfamily B, Member 11; ATP-Binding Cassette Transporters; Bile Acids and Salts; Cholestasis, Intrahepatic; Female; Humans; Male; Mutation; Receptors, Cytoplasmic and Nuclear; Young Adult

Nonrecurrent PMP22-RAI1 contiguous gene deletions arise from replication-based mechanisms and result in Smith-Magenis syndrome with evident peripheral neuropathy. - Yuan, Bo; Neira, Juanita; Gu, Shen; Harel, Tamar; Liu, Pengfei; Briceño, Ignacio; Elsea, Sarah H; Gómez, Alberto; Potocki, Lorraine; Lupski, James R (Hum Genet, 2016)
Hereditary neuropathy with liability to pressure palsies (HNPP) and Smith-Magenis syndrome (SMS) are genomic disorders associated with deletion copy number variants involving chromosome 17p12 and 17p11.2, respectively. Nonallelic homologous recombination (NAHR)-mediated recurrent deletions are responsible for the majority of HNPP and SMS cases; the rearrangement products encompass the key dosage-sensitive genes PMP22 and RAI1, respectively, and result in haploinsufficiency for these genes. Less frequently, nonrecurrent genomic rearrangements occur at this locus. Contiguous gene duplications encompassing both PMP22 and RAI1, i.e., PMP22-RAI1 duplications, have been investigated, and replication-based mechanisms rather than NAHR have been proposed for these rearrangements. In the current study, we report molecular and clinical characterizations of six subjects with the reciprocal phenomenon of deletions spanning both genes, i.e., PMP22-RAI1 deletions. Molecular studies utilizing high-resolution array comparative genomic hybridization and breakpoint junction sequencing identified mutational signatures that were suggestive of replication-based mechanisms. Systematic clinical studies revealed features consistent with SMS, including features of intellectual disability, speech and gross motor delays, behavioral problems and ocular abnormalities. Five out of six subjects presented clinical signs and/or objective electrophysiologic studies of peripheral neuropathy. Clinical profiling may improve the clinical management of this unique group of subjects, as the peripheral neuropathy can be more severe or of earlier onset as compared to SMS patients having the common recurrent deletion. Moreover, the current study, in combination with the previous report of PMP22-RAI1 duplications, contributes to the understanding of rare complex phenotypes involving multiple dosage-sensitive genes from a genetic mechanistic standpoint.
Keywords: Adolescent; Adult; Child; Child, Preschool; Chromosomes, Human, Pair 17; DNA Copy Number Variations; DNA Replication; Female; Gene Deletion; Haploinsufficiency; Homologous Recombination; Humans; Intellectual Disability; Male; Mutation; Myelin Proteins; Smith-Magenis Syndrome; Trans-Activators; Transcription Factors

Novel genetic causes for cerebral visual impairment. - Bosch, Daniëlle G M; Boonstra, F Nienke; de Leeuw, Nicole; Pfundt, Rolph; Nillesen, Willy M; de Ligt, Joep; Gilissen, Christian; Jhangiani, Shalini; Lupski, James R; Cremers, Frans P M; de Vries, Bert B A (Eur J Hum Genet, 2016)
Cerebral visual impairment (CVI) is a major cause of low vision in children due to impairment in projection and/or interpretation of the visual input in the brain. Although acquired causes for CVI are well known, genetic causes underlying CVI are largely unidentified. DNAs of 25 patients with CVI and intellectual disability, but without acquired (eg, perinatal) damage, were investigated by whole-exome sequencing. The data were analyzed for de novo, autosomal-recessive, and X-linked variants, and subsequently classified into known, candidate, or unlikely to be associated with CVI. This classification was based on the Online Mendelian Inheritance in Man database, literature reports, variant characteristics, and functional relevance of the gene. After classification, variants in four genes known to be associated with CVI (AHDC1, NGLY1, NR2F1, PGAP1) in 5 patients (20%) were identified, establishing a conclusive genetic diagnosis for CVI. In addition, in 11 patients (44%) with CVI, variants in one or more candidate genes were identified (ACP6, AMOT, ARHGEF10L, ATP6V1A, DCAF6, DLG4, GABRB2, GRIN1, GRIN2B, KCNQ3, KCTD19, RERE, SLC1A1, SLC25A16, SLC35A2, SOX5, UFSP2, UHMK1, ZFP30). Our findings show that diverse genetic causes underlie CVI, some of which will provide insight into the biology underlying this disease process.
Keywords: Adolescent; Blindness, Cortical; Child; Child, Preschool; Female; Genetic Loci; Humans; Male; Polymorphism, Single Nucleotide; Young Adult

A novel missense variant in the PNPLA1 gene underlies congenital ichthyosis in three consanguineous families. - Ahmad, F; Ansar, M; Mehmood, S; Izoduwa, A; Lee, K; Nasir, A; Abrar, M; Mehmood, S; Ullah, A; Aziz, A; Smith, J D; Shendure, J; et al. (J Eur Acad Dermatol Venereol, 2016)
Keywords: Amino Acid Sequence; Consanguinity; Female; Genes, Recessive; Humans; Ichthyosiform Erythroderma, Congenital; Lipase; Male; Mutation, Missense; Pakistan; Pedigree; Sequence Homology, Amino Acid

Novel mutations in LRP6 highlight the role of WNT signaling in tooth agenesis. - Ockeloen, Charlotte W; Khandelwal, Kriti D; Dreesen, Karoline; Ludwig, Kerstin U; Sullivan, Robert; van Rooij, Iris A L M; Thonissen, Michelle; Swinnen, Steven; Phan, Milien; Conte, Federica; Ishorst, Nina; Gilissen, Christian; et al. (Genet Med, 2016)
PURPOSE: We aimed to identify a novel genetic cause of tooth agenesis (TA) and/or orofacial clefting (OFC) by combining whole-exome sequencing (WES) and targeted resequencing in a large cohort of TA and OFC patients. METHODS: WES was performed in two unrelated patients: one with severe TA and OFC and another with severe TA only. After deleterious mutations were identified in a gene encoding low-density lipoprotein receptor-related protein 6 (LRP6), all its exons were resequenced with molecular inversion probes in 67 patients with TA, 1,072 patients with OFC, and 706 controls. RESULTS: We identified a frameshift (c.4594delG, p.Cys1532fs) and a canonical splice-site mutation (c.3398-2A>C, p.?) in LRP6, respectively, in the patient with TA and OFC and in the patient with severe TA only. The targeted resequencing showed significant enrichment of unique LRP6 variants in TA patients but not in nonsyndromic OFC patients. Of the five variants in patients with TA, two affected the canonical splice site and three were missense variants; all variants segregated with the dominant phenotype, and in one case the missense mutation occurred de novo. CONCLUSION: Mutations in LRP6 cause TA in humans.Genet Med 18 11, 1158-1162.
Keywords: Adolescent; Anodontia; Child; Exome; Female; Frameshift Mutation; Genetic Predisposition to Disease; Humans; Low Density Lipoprotein Receptor-Related Protein-6; Male; Mutation, Missense; Pedigree; Sequence Analysis, DNA; Wnt Signaling Pathway

Novel mutations in the genes TGM1 and ALOXE3 underlying autosomal recessive congenital ichthyosis. - Ullah, Rahim; Ansar, Muhammad; Durrani, Zaka Ullah; Lee, Kwanghyuk; Santos-Cortez, Regie Lyn P; Muhammad, Dost; Ali, Mahboob; Zia, Muhammad; Ayub, Muhammad; Khan, Suliman; Smith, Josh D; Nickerson, Deborah A; et al. (Int J Dermatol, 2016)
BACKGROUND: Ichthyoses are clinically characterized by scaling or hyperkeratosis of the skin or both. It can be an isolated condition limited to the skin or appear secondarily with involvement of other cutaneous or systemic abnormalities. METHODS: The present study investigated clinical and molecular characterization of three consanguineous families (A, B, C) segregating two different forms of autosomal recessive congenital ichthyosis (ARCI). Linkage in three consanguineous families (A, B, C) segregating two different forms of ARCI was searched by typing microsatellite and single nucleotide polymorphism marker analysis. Sequencing of the two genes TGM1 and ALOXE3 was performed by the dideoxy chain termination method. RESULTS: Genome-wide linkage analysis established linkage in family A to TGM1 gene on chromosome 14q11 and in families B and C to ALOXE3 gene on chromosome 17p13. Subsequently, sequencing of these genes using samples from affected family members led to the identification of three novel mutations: a missense variant p.Trp455Arg in TGM1 (family A); a nonsense variant p.Arg140* in ALOXE3 (family B); and a complex rearrangement in ALOXE3 (family C). CONCLUSION: The present study further extends the spectrum of mutations in the two genes involved in causing ARCI. Characterizing the clinical spectrum resulting from mutations in the TGM1 and ALOXE3 genes will improve diagnosis and may direct clinical care of the family members.
Keywords: Adolescent; Chromosomes, Human, Pair 14; Chromosomes, Human, Pair 17; Codon, Nonsense; Consanguinity; Female; Gene Rearrangement; Genotype; Humans; Ichthyosiform Erythroderma, Congenital; Ichthyosis, Lamellar; Lipoxygenase; Male; Mutation, Missense; Pakistan; Pedigree; Phenotype; Transglutaminases; Young Adult

Overlapping 16p13.11 deletion and gain of copies variations associated with childhood onset psychosis include genes with mechanistic implications for autism associated pathways: Two case reports. - Brownstein, Catherine A; Kleiman, Robin J; Engle, Elizabeth C; Towne, Meghan C; D'Angelo, Eugene J; Yu, Timothy W; Beggs, Alan H; Picker, Jonathan; Fogler, Jason M; Carroll, Devon; Schmitt, Rachel C O; Wolff, Robert R; et al. (Am J Med Genet A, 2016)
Copy number variability at 16p13.11 has been associated with intellectual disability, autism, schizophrenia, epilepsy, and attention-deficit hyperactivity disorder. Adolescent/adult- onset psychosis has been reported in a subset of these cases. Here, we report on two children with CNVs in 16p13.11 that developed psychosis before the age of 7. The genotype and neuropsychiatric abnormalities of these patients highlight several overlapping genes that have possible mechanistic relevance to pathways previously implicated in Autism Spectrum Disorders, including the mTOR signaling and the ubiquitin-proteasome cascades. A careful screening of the 16p13.11 region is warranted in patients with childhood onset psychosis.
Keywords: Autistic Disorder; Child; Child, Preschool; Chromosome Deletion; Chromosomes, Human, Pair 16; Comparative Genomic Hybridization; Developmental Disabilities; DNA Copy Number Variations; Female; Genetic Association Studies; Humans; Male; Psychotic Disorders; Schizophrenia; Signal Transduction

PADRE: Pedigree-Aware Distant-Relationship Estimation. - Staples, Jeffrey; Witherspoon, David J; Jorde, Lynn B; Nickerson, Deborah A; Below, Jennifer E; Huff, Chad D (Am J Hum Genet, 2016)
Accurate estimation of shared ancestry is an important component of many genetic studies; current prediction tools accurately estimate pairwise genetic relationships up to the ninth degree. Pedigree-aware distant-relationship estimation (PADRE) combines relationship likelihoods generated by estimation of recent shared ancestry (ERSA) with likelihoods from family networks reconstructed by pedigree reconstruction and identification of a maximum unrelated set (PRIMUS), improving the power to detect distant relationships between pedigrees. Using PADRE, we estimated relationships from simulated pedigrees and three extended pedigrees, correctly predicting 20% more fourth- through ninth-degree simulated relationships than when using ERSA alone. By leveraging pedigree information, PADRE can even identify genealogical relationships between individuals who are genetically unrelated. For example, although 95% of 13(th)-degree relatives are genetically unrelated, in simulations, PADRE correctly predicted 50% of 13(th)-degree relationships to within one degree of relatedness. The improvement in prediction accuracy was consistent between simulated and actual pedigrees. We also applied PADRE to the HapMap3 CEU samples and report new cryptic relationships and validation of previously described relationships between families. PADRE greatly expands the range of relationships that can be estimated by using genetic data in pedigrees.
Keywords: Algorithms; Female; Haplotypes; Humans; Male; Models, Genetic; Pedigree; Reproducibility of Results

Pathogenetics of alveolar capillary dysplasia with misalignment of pulmonary veins. - Szafranski, Przemyslaw; Gambin, Tomasz; Dharmadhikari, Avinash V; Akdemir, Kadir Caner; Jhangiani, Shalini N; Schuette, Jennifer; Godiwala, Nihal; Yatsenko, Svetlana A; Sebastian, Jessica; Madan-Khetarpal, Suneeta; Surti, Urvashi; Abellar, Rosanna G; et al. (Hum Genet, 2016)
Alveolar capillary dysplasia with misalignment of pulmonary veins (ACDMPV) is a lethal lung developmental disorder caused by heterozygous point mutations or genomic deletion copy-number variants (CNVs) of FOXF1 or its upstream enhancer involving fetal lung-expressed long noncoding RNA genes LINC01081 and LINC01082. Using custom-designed array comparative genomic hybridization, Sanger sequencing, whole exome sequencing (WES), and bioinformatic analyses, we studied 22 new unrelated families (20 postnatal and two prenatal) with clinically diagnosed ACDMPV. We describe novel deletion CNVs at the FOXF1 locus in 13 unrelated ACDMPV patients. Together with the previously reported cases, all 31 genomic deletions in 16q24.1, pathogenic for ACDMPV, for which parental origin was determined, arose de novo with 30 of them occurring on the maternally inherited chromosome 16, strongly implicating genomic imprinting of the FOXF1 locus in human lungs. Surprisingly, we have also identified four ACDMPV families with the pathogenic variants in the FOXF1 locus that arose on paternal chromosome 16. Interestingly, a combination of the severe cardiac defects, including hypoplastic left heart, and single umbilical artery were observed only in children with deletion CNVs involving FOXF1 and its upstream enhancer. Our data demonstrate that genomic imprinting at 16q24.1 plays an important role in variable ACDMPV manifestation likely through long-range regulation of FOXF1 expression, and may be also responsible for key phenotypic features of maternal uniparental disomy 16. Moreover, in one family, WES revealed a de novo missense variant in ESRP1, potentially implicating FGF signaling in the etiology of ACDMPV.
Keywords: Chromosomes, Human, Pair 16; Comparative Genomic Hybridization; Female; Forkhead Transcription Factors; Genes, Lethal; Genome, Human; Genomic Imprinting; High-Throughput Nucleotide Sequencing; Humans; Infant, Newborn; Male; Pedigree; Persistent Fetal Circulation Syndrome; Pulmonary Alveoli; Pulmonary Veins; Sequence Deletion

Pathogenic FBN1 variants in familial thoracic aortic aneurysms and dissections. - Regalado, E S; Guo, D C; Santos-Cortez, R L P; Hostetler, E; Bensend, T A; Pannu, H; Estrera, A; Safi, H; Mitchell, A L; Evans, J P; Leal, S M; Bamshad, M; et al. (Clin Genet, 2016)
Marfan syndrome (MFS) due to mutations in FBN1 is a known cause of thoracic aortic aneurysms and acute aortic dissections (TAAD) associated with pleiotropic manifestations. Genetic predisposition to TAAD can also be inherited in families in the absence of syndromic features, termed familial TAAD (FTAAD), and several causative genes have been identified to date. FBN1 mutations can also be identified in FTAAD families, but the frequency of these mutations has not been established. We performed exome sequencing of 183 FTAAD families and identified pathogenic FBN1 variants in five (2.7%) of these families. We also identified eight additional FBN1 rare variants that could not be unequivocally classified as disease-causing in six families. FBN1 sequencing should be considered in individuals with FTAAD even without significant systemic features of MFS.
Keywords: Adult; Aged; Aneurysm, Dissecting; Aortic Aneurysm, Thoracic; Exome; Family Health; Female; Fibrillin-1; Genetic Predisposition to Disease; Humans; Male; Marfan Syndrome; Middle Aged; Mutation; Pedigree; Sequence Analysis, DNA

PEHO Syndrome May Represent Phenotypic Expansion at the Severe End of the Early-Onset Encephalopathies. - Gawlinski, Pawel; Posmyk, Renata; Gambin, Tomasz; Sielicka, Danuta; Chorazy, Monika; Nowakowska, Beata; Jhangiani, Shalini N; Muzny, Donna M; Bekiesinska-Figatowska, Monika; Bal, Jerzy; Boerwinkle, Eric; Gibbs, Richard A; et al. (Pediatr Neurol, 2016)
BACKGROUND: Progressive encephalopathy with edema, hypsarrhythmia and optic atrophy (PEHO) syndrome is a distinct neurodevelopmental disorder. Patients without optic nerve atrophy and brain imaging abnormalities but fulfilling other PEHO criteria are often described as a PEHO-like syndrome. The molecular bases of both clinically defined conditions remain unknown in spite of the widespread application of genome analyses in both clinic and research. METHODS: We enrolled two patients with a prior diagnosis of PEHO and two individuals with PEHO-like syndrome. All four individuals subsequently underwent whole-exome sequencing and comprehensive genomic analysis. RESULTS: We identified disease-causing mutations in known genes associated with neurodevelopmental disorders including GNAO1 and CDKL5 in two of four individuals. One patient with PEHO syndrome and a de novoGNAO1 mutation was found to have an additional de novo mutation in HESX1 that is associated with optic atrophy. CONCLUSIONS: We hypothesize that PEHO and PEHO-like syndrome may represent a severe end of the spectrum of the early-onset encephalopathies and, in some instances, its complex phenotype may result from an aggregated effect of mutations at two loci.
Keywords: Brain Edema; Child; Child, Preschool; Female; GTP-Binding Protein alpha Subunits, Gi-Go; Humans; Infant; Male; Mutation; Neurodegenerative Diseases; Optic Atrophy; Phenotype; Protein Serine-Threonine Kinases; Spasms, Infantile

Periodontal Ehlers-Danlos Syndrome Is Caused by Mutations in C1R and C1S, which Encode Subcomponents C1r and C1s of Complement. - Kapferer-Seebacher, Ines; Pepin, Melanie; Werner, Roland; Aitman, Timothy J; Nordgren, Ann; Stoiber, Heribert; Thielens, Nicole; Gaboriaud, Christine; Amberger, Albert; Schossig, Anna; Gruber, Robert; Giunta, Cecilia; et al. (Am J Hum Genet, 2016)
Periodontal Ehlers-Danlos syndrome (pEDS) is an autosomal-dominant disorder characterized by early-onset periodontitis leading to premature loss of teeth, joint hypermobility, and mild skin findings. A locus was mapped to an approximately 5.8 Mb region at 12p13.1 but no candidate gene was identified. In an international consortium we recruited 19 independent families comprising 107 individuals with pEDS to identify the locus, characterize the clinical details in those with defined genetic causes, and try to understand the physiological basis of the condition. In 17 of these families, we identified heterozygous missense or in-frame insertion/deletion mutations in C1R (15 families) or C1S (2 families), contiguous genes in the mapped locus that encode subunits C1r and C1s of the first component of the classical complement pathway. These two proteins form a heterotetramer that then combines with six C1q subunits. Pathogenic variants involve the subunit interfaces or inter-domain hinges of C1r and C1s and are associated with intracellular retention and mild endoplasmic reticulum enlargement. Clinical features of affected individuals in these families include rapidly progressing periodontitis with onset in the teens or childhood, a previously unrecognized lack of attached gingiva, pretibial hyperpigmentation, skin and vascular fragility, easy bruising, and variable musculoskeletal symptoms. Our findings open a connection between the inflammatory classical complement pathway and connective tissue homeostasis.
Keywords: Adolescent; Adult; Child; Child, Preschool; Chromosome Mapping; Chromosomes, Human, Pair 12; Complement C1r; Complement C1s; Ehlers-Danlos Syndrome; Endoplasmic Reticulum; Exome; Female; Gene Deletion; Genetic Loci; Humans; Male; Mutation, Missense; Pedigree; Periodontitis; Protein Conformation; Young Adult

POGZ truncating alleles cause syndromic intellectual disability. - White, Janson; Beck, Christine R; Harel, Tamar; Posey, Jennifer E; Jhangiani, Shalini N; Tang, Sha; Farwell, Kelly D; Powis, Zöe; Mendelsohn, Nancy J; Baker, Janice A; Pollack, Lynda; Mason, Kati J; et al. (Genome Med, 2016)
BACKGROUND: Large-scale cohort-based whole exome sequencing of individuals with neurodevelopmental disorders (NDDs) has identified numerous novel candidate disease genes; however, detailed phenotypic information is often lacking in such studies. De novo mutations in pogo transposable element with zinc finger domain (POGZ) have been identified in six independent and diverse cohorts of individuals with NDDs ranging from autism spectrum disorder to developmental delay. METHODS: Whole exome sequencing was performed on five unrelated individuals. Sanger sequencing was used to validate variants and segregate mutations with the phenotype in available family members. RESULTS: We identified heterozygous truncating mutations in POGZ in five unrelated individuals, which were confirmed to be de novo or not present in available parental samples. Careful review of the phenotypes revealed shared features that included developmental delay, intellectual disability, hypotonia, behavioral abnormalities, and similar facial characteristics. Variable features included short stature, microcephaly, strabismus and hearing loss. CONCLUSIONS: While POGZ has been associated with neurodevelopmental disorders in large cohort studies, our data suggest that loss of function variants in POGZ lead to an identifiable syndrome of NDD with specific phenotypic traits. This study exemplifies the era of human reverse clinical genomics ushered in by large disease-directed cohort studies; first defining a new syndrome molecularly and, only subsequently, phenotypically.
Keywords: Adolescent; Adult; Alleles; Child, Preschool; Exome; Female; Heterozygote; Humans; Infant; Intellectual Disability; Male; Mutation; Sequence Analysis, DNA; Transposases

PYCR2 Mutations cause a lethal syndrome of microcephaly and failure to thrive. - Zaki, Maha S; Bhat, Gifty; Sultan, Tipu; Issa, Mahmoud; Jung, Hea-Jin; Dikoglu, Esra; Selim, Laila; G Mahmoud, Imam; Abdel-Hamid, Mohamed S; Abdel-Salam, Ghada; Marin-Valencia, Isaac; Gleeson, Joseph G (Ann Neurol, 2016)
OBJECTIVE: A study was undertaken to characterize the clinical features of the newly described hypomyelinating leukodystrophy type 10 with microcephaly. This is an autosomal recessive disorder mapped to chromosome 1q42.12 due to mutations in the PYCR2 gene, encoding an enzyme involved in proline synthesis in mitochondria. METHODS: From several international clinics, 11 consanguineous families were identified with PYCR2 mutations by whole exome or targeted sequencing, with detailed clinical and radiological phenotyping. Selective mutations from patients were tested for effect on protein function. RESULTS: The characteristic clinical presentation of patients with PYCR2 mutations included failure to thrive, microcephaly, craniofacial dysmorphism, progressive psychomotor disability, hyperkinetic movements, and axial hypotonia with variable appendicular spasticity. Patients did not survive beyond the first decade of life. Brain magnetic resonance imaging showed global brain atrophy and white matter T2 hyperintensities. Routine serum metabolic profiles were unremarkable. Both nonsense and missense mutations were identified, which impaired protein multimerization. INTERPRETATION: PYCR2-related syndrome represents a clinically recognizable condition in which PYCR2 mutations lead to protein dysfunction, not detectable on routine biochemical assessments. Mutations predict a poor outcome, probably as a result of impaired mitochondrial function. Ann Neurol 2016;80:59-70.
Keywords: Adolescent; Child; Child, Preschool; Codon, Nonsense; Exome; Failure to Thrive; Female; Fibroblasts; Gene Expression; Genetic Predisposition to Disease; Genotype; Humans; Infant; Male; Microcephaly; Mutation, Missense; Phenotype; Primary Cell Culture; Pyrroline Carboxylate Reductases; Syndrome; Transfection; Young Adult

Rapid molecular diagnostics of severe primary immunodeficiency determined by using targeted next-generation sequencing. - Yu, Hui; Zhang, Victor Wei; Stray-Pedersen, Asbjørg; Hanson, Imelda Celine; Forbes, Lisa R; de la Morena, M Teresa; Chinn, Ivan K; Gorman, Elizabeth; Mendelsohn, Nancy J; Pozos, Tamara; Wiszniewski, Wojciech; Nicholas, Sarah K; et al. (J Allergy Clin Immunol, 2016)
BACKGROUND: Primary immunodeficiency diseases (PIDDs) are inherited disorders of the immune system. The most severe form, severe combined immunodeficiency (SCID), presents with profound deficiencies of T cells, B cells, or both at birth. If not treated promptly, affected patients usually do not live beyond infancy because of infections. Genetic heterogeneity of SCID frequently delays the diagnosis; a specific diagnosis is crucial for life-saving treatment and optimal management. OBJECTIVE: We developed a next-generation sequencing (NGS)-based multigene-targeted panel for SCID and other severe PIDDs requiring rapid therapeutic actions in a clinical laboratory setting. METHODS: The target gene capture/NGS assay provides an average read depth of approximately 1000×. The deep coverage facilitates simultaneous detection of single nucleotide variants and exonic copy number variants in one comprehensive assessment. Exons with insufficient coverage (<20× read depth) or high sequence homology (pseudogenes) are complemented by amplicon-based sequencing with specific primers to ensure 100% coverage of all targeted regions. RESULTS: Analysis of 20 patient samples with low T-cell receptor excision circle numbers on newborn screening or a positive family history or clinical suspicion of SCID or other severe PIDD identified deleterious mutations in 14 of them. Identified pathogenic variants included both single nucleotide variants and exonic copy number variants, such as hemizygous nonsense, frameshift, and missense changes in IL2RG; compound heterozygous changes in ATM, RAG1, and CIITA; homozygous changes in DCLRE1C and IL7R; and a heterozygous nonsense mutation in CHD7. CONCLUSION: High-throughput deep sequencing analysis with complete clinical validation greatly increases the diagnostic yield of severe primary immunodeficiency. Establishing a molecular diagnosis enables early immune reconstitution through prompt therapeutic intervention and guides management for improved long-term quality of life.
Keywords: Adolescent; Child; Female; Genetic Variation; Humans; Male; Pathology, Molecular; Sequence Analysis, DNA; Severe Combined Immunodeficiency

Recessive Inactivating Mutations in TBCK, Encoding a Rab GTPase-Activating Protein, Cause Severe Infantile Syndromic Encephalopathy. - Chong, Jessica X; Caputo, Viviana; Phelps, Ian G; Stella, Lorenzo; Worgan, Lisa; Dempsey, Jennifer C; Nguyen, Alina; Leuzzi, Vincenzo; Webster, Richard; Pizzuti, Antonio; Marvin, Colby T; Ishak, Gisele E; et al. (Am J Hum Genet, 2016)
Infantile encephalopathies are a group of clinically and biologically heterogeneous disorders for which the genetic basis remains largely unknown. Here, we report a syndromic neonatal encephalopathy characterized by profound developmental disability, severe hypotonia, seizures, diminished respiratory drive requiring mechanical ventilation, brain atrophy, dysgenesis of the corpus callosum, cerebellar vermis hypoplasia, and facial dysmorphism. Biallelic inactivating mutations in TBCK (TBC1-domain-containing kinase) were independently identified by whole-exome sequencing as the cause of this condition in four unrelated families. Matching these families was facilitated by the sharing of phenotypic profiles and WES data in a recently released web-based tool (Geno2MP) that links phenotypic information to rare variants in families with Mendelian traits. TBCK is a putative GTPase-activating protein (GAP) for small GTPases of the Rab family and has been shown to control cell growth and proliferation, actin-cytoskeleton dynamics, and mTOR signaling. Two of the three mutations (c.376C>T [p.Arg126(∗)] and c.1363A>T [p.Lys455(∗)]) are predicted to truncate the protein, and loss of the major TBCK isoform was confirmed in primary fibroblasts from one affected individual. The third mutation, c.1532G>A (p.Arg511His), alters a conserved residue within the TBC1 domain. Structural analysis implicated Arg511 as a required residue for Rab-GAP function, and in silico homology modeling predicted impaired GAP function in the corresponding mutant. These results suggest that loss of Rab-GAP activity is the underlying mechanism of disease. In contrast to other disorders caused by dysregulated mTOR signaling associated with focal or global brain overgrowth, impaired TBCK function results in progressive loss of brain volume.
Keywords: Adolescent; Alleles; Amino Acid Sequence; Brain Diseases; Child; Child, Preschool; Corpus Callosum; Female; GTPase-Activating Proteins; Humans; Magnetic Resonance Imaging; Male; Molecular Sequence Data; Mutation; Pedigree; Protein Conformation; Protein-Serine-Threonine Kinases; Signal Transduction; TOR Serine-Threonine Kinases

Recurrent De Novo and Biallelic Variation of ATAD3A, Encoding a Mitochondrial Membrane Protein, Results in Distinct Neurological Syndromes. - Harel, Tamar; Yoon, Wan Hee; Garone, Caterina; Gu, Shen; Coban-Akdemir, Zeynep; Eldomery, Mohammad K; Posey, Jennifer E; Jhangiani, Shalini N; Rosenfeld, Jill A; Cho, Megan T; Fox, Stephanie; Withers, Marjorie; et al. (Am J Hum Genet, 2016)
ATPase family AAA-domain containing protein 3A (ATAD3A) is a nuclear-encoded mitochondrial membrane protein implicated in mitochondrial dynamics, nucleoid organization, protein translation, cell growth, and cholesterol metabolism. We identified a recurrent de novo ATAD3A c.1582C>T (p.Arg528Trp) variant by whole-exome sequencing (WES) in five unrelated individuals with a core phenotype of global developmental delay, hypotonia, optic atrophy, axonal neuropathy, and hypertrophic cardiomyopathy. We also describe two families with biallelic variants in ATAD3A, including a homozygous variant in two siblings, and biallelic ATAD3A deletions mediated by nonallelic homologous recombination (NAHR) between ATAD3A and gene family members ATAD3B and ATAD3C. Tissue-specific overexpression of bor, the Drosophila mutation homologous to the human c.1582C>T (p.Arg528Trp) variant, resulted in a dramatic decrease in mitochondrial content, aberrant mitochondrial morphology, and increased autophagy. Homozygous null bor larvae showed a significant decrease of mitochondria, while overexpression of bor resulted in larger, elongated mitochondria. Finally, fibroblasts of an affected individual exhibited increased mitophagy. We conclude that the p.Arg528Trp variant functions through a dominant-negative mechanism that results in small mitochondria that trigger mitophagy, resulting in a reduction in mitochondrial content. ATAD3A variation represents an additional link between mitochondrial dynamics and recognizable neurological syndromes, as seen with MFN2, OPA1, DNM1L, and STAT2 mutations.
Keywords: Adenosine Triphosphatases; Adult; Alleles; Animals; ATPases Associated with Diverse Cellular Activities; Axons; Cardiomyopathies; Child; Child, Preschool; Developmental Disabilities; DNA Copy Number Variations; Drosophila melanogaster; Female; Fibroblasts; Homozygote; Humans; Infant; Infant, Newborn; Male; Membrane Proteins; Mitochondria; Mitochondrial Proteins; Muscle Hypotonia; Muscles; Mutation; Nervous System Diseases; Neurons; Optic Atrophy; Phenotype; Polymorphism, Single Nucleotide; Syndrome; Young Adult

Recurrent Muscle Weakness with Rhabdomyolysis, Metabolic Crises, and Cardiac Arrhythmia Due to Bi-allelic TANGO2 Mutations. - Lalani, Seema R; Liu, Pengfei; Rosenfeld, Jill A; Watkin, Levi B; Chiang, Theodore; Leduc, Magalie S; Zhu, Wenmiao; Ding, Yan; Pan, Shujuan; Vetrini, Francesco; Miyake, Christina Y; Shinawi, Marwan; et al. (Am J Hum Genet, 2016)
The underlying genetic etiology of rhabdomyolysis remains elusive in a significant fraction of individuals presenting with recurrent metabolic crises and muscle weakness. Using exome sequencing, we identified bi-allelic mutations in TANGO2 encoding transport and Golgi organization 2 homolog (Drosophila) in 12 subjects with episodic rhabdomyolysis, hypoglycemia, hyperammonemia, and susceptibility to life-threatening cardiac tachyarrhythmias. A recurrent homozygous c.460G>A (p.Gly154Arg) mutation was found in four unrelated individuals of Hispanic/Latino origin, and a homozygous ∼34 kb deletion affecting exons 3-9 was observed in two families of European ancestry. One individual of mixed Hispanic/European descent was found to be compound heterozygous for c.460G>A (p.Gly154Arg) and the deletion of exons 3-9. Additionally, a homozygous exons 4-6 deletion was identified in a consanguineous Middle Eastern Arab family. No homozygotes have been reported for these changes in control databases. Fibroblasts derived from a subject with the recurrent c.460G>A (p.Gly154Arg) mutation showed evidence of increased endoplasmic reticulum stress and a reduction in Golgi volume density in comparison to control. Our results show that the c.460G>A (p.Gly154Arg) mutation and the exons 3-9 heterozygous deletion in TANGO2 are recurrent pathogenic alleles present in the Latino/Hispanic and European populations, respectively, causing considerable morbidity in the homozygotes in these populations.
Keywords: Alleles; Arabs; Arrhythmias, Cardiac; Base Sequence; Child; Child, Preschool; Endoplasmic Reticulum Stress; European Continental Ancestry Group; Exome; Exons; Female; Gene Deletion; Golgi Apparatus; Hispanic Americans; Homozygote; Humans; Infant; Male; Molecular Sequence Data; Muscle Weakness; Pedigree; Rhabdomyolysis

Recurrent recessive mutation in deoxyguanosine kinase causes idiopathic noncirrhotic portal hypertension. - Vilarinho, Sílvia; Sari, Sinan; Yilmaz, Güldal; Stiegler, Amy L; Boggon, Titus J; Jain, Dhanpat; Akyol, Gülen; Dalgiç, Buket; Günel, Murat; Lifton, Richard P (Hepatology, 2016)
UNLABELLED: Despite advances in the diagnosis and management of idiopathic noncirrhotic portal hypertension, its pathogenesis remains elusive. Insight may be gained from study of early-onset familial idiopathic noncirrhotic portal hypertension, in which Mendelian mutations may account for disease. We performed exome sequencing of eight subjects from six kindreds with onset of portal hypertension of indeterminate etiology during infancy or childhood. Three subjects from two consanguineous families shared the identical rare homozygous p.N46S mutation in DGUOK, a deoxyguanosine kinase required for mitochondrial DNA replication; haplotype sharing demonstrated that the mutation in the two families was inherited from a remote common ancestor. All three affected subjects had stable portal hypertension with noncirrhotic liver disease for 6-16 years of follow-up. This mutation impairs adenosine triphosphate binding and reduces catalytic activity. Loss-of-function mutations in DGUOK have previously been implicated in cirrhosis and liver failure but not in isolated portal hypertension. Interestingly, treatment of patients with human immunodeficiency viral infection with the nucleoside analogue didanosine is known to cause portal hypertension in a subset of patients and lowers deoxyguanosine kinase levels in vitro; the current findings implicate these effects on deoxyguanosine kinase in the causal mechanism. CONCLUSION: Our findings provide new insight into the mechanisms mediating inherited and acquired noncirrhotic portal hypertension, expand the phenotypic spectrum of DGUOK deficiency, and provide a new genetic test for a specific cause of idiopathic noncirrhotic portal hypertension. (Hepatology 2016;63:1977-1986).
Keywords: Adolescent; Amino Acid Sequence; Animals; Cattle; Child; Child, Preschool; DNA Mutational Analysis; Dogs; Female; Genes, Recessive; Homozygote; Humans; Hypertension, Portal; Infant; Liver Failure; Male; Molecular Sequence Data; Pedigree; Phosphotransferases (Alcohol Group Acceptor); Principal Component Analysis; Rats; Young Adult

The role of combined SNV and CNV burden in patients with distal symmetric polyneuropathy. - Pehlivan, Davut; Beck, Christine R; Okamoto, Yuji; Harel, Tamar; Akdemir, Zeynep H C; Jhangiani, Shalini N; Withers, Marjorie A; Goksungur, Meryem Tuba; Carvalho, Claudia M B; Czesnik, Dirk; Gonzaga-Jauregui, Claudia; Wiszniewski, Wojciech; et al. (Genet Med, 2016)
PURPOSE: Charcot-Marie-Tooth (CMT) disease is a heterogeneous group of genetic disorders of the peripheral nervous system. Copy-number variants (CNVs) contribute significantly to CMT, as duplication of PMP22 underlies the majority of CMT1 cases. We hypothesized that CNVs and/or single-nucleotide variants (SNVs) might exist in patients with CMT with an unknown molecular genetic etiology. METHODS: Two hundred patients with CMT, negative for both SNV mutations in several CMT genes and for CNVs involving PMP22, were screened for CNVs by high-resolution oligonucleotide array comparative genomic hybridization. Whole-exome sequencing was conducted on individuals with rare, potentially pathogenic CNVs. RESULTS: Putatively causative CNVs were identified in five subjects (~2.5%); four of the five map to known neuropathy genes. Breakpoint sequencing revealed Alu-Alu-mediated junctions as a predominant contributor. Exome sequencing identified MFN2 SNVs in two of the individuals. CONCLUSION: Neuropathy-associated CNV outside of the PMP22 locus is rare in CMT. Nevertheless, there is potential clinical utility in testing for CNVs and exome sequencing in CMT cases negative for the CMT1A duplication. These findings suggest that complex phenotypes including neuropathy can potentially be caused by a combination of SNVs and CNVs affecting more than one disease-associated locus and contributing to a mutational burden.Genet Med 18 5, 443-451.
Keywords: Adult; Age of Onset; Charcot-Marie-Tooth Disease; Child, Preschool; Comparative Genomic Hybridization; DNA Copy Number Variations; Exome; Female; Genetic Predisposition to Disease; GTP Phosphohydrolases; High-Throughput Nucleotide Sequencing; Humans; Male; Mitochondrial Proteins; Motor Neurons; Myelin P0 Protein; Myelin Proteins; Neural Conduction; Polymorphism, Single Nucleotide; Polyneuropathies

Somatic mosaicism underlies X-linked acrogigantism syndrome in sporadic male subjects. - Daly, Adrian F; Yuan, Bo; Fina, Frederic; Caberg, Jean-Hubert; Trivellin, Giampaolo; Rostomyan, Liliya; de Herder, Wouter W; Naves, Luciana A; Metzger, Daniel; Cuny, Thomas; Rabl, Wolfgang; Shah, Nalini; et al. (Endocr Relat Cancer, 2016)
Somatic mosaicism has been implicated as a causative mechanism in a number of genetic and genomic disorders. X-linked acrogigantism (XLAG) syndrome is a recently characterized genomic form of pediatric gigantism due to aggressive pituitary tumors that is caused by submicroscopic chromosome Xq26.3 duplications that include GPR101 We studied XLAG syndrome patients (n= 18) to determine if somatic mosaicism contributed to the genomic pathophysiology. Eighteen subjects with XLAG syndrome caused by Xq26.3 duplications were identified using high-definition array comparative genomic hybridization (HD-aCGH). We noted that males with XLAG had a decreased log2ratio (LR) compared with expected values, suggesting potential mosaicism, whereas females showed no such decrease. Compared with familial male XLAG cases, sporadic males had more marked evidence for mosaicism, with levels of Xq26.3 duplication between 16.1 and 53.8%. These characteristics were replicated using a novel, personalized breakpoint junction-specific quantification droplet digital polymerase chain reaction (ddPCR) technique. Using a separate ddPCR technique, we studied the feasibility of identifying XLAG syndrome cases in a distinct patient population of 64 unrelated subjects with acromegaly/gigantism, and identified one female gigantism patient who had had increased copy number variation (CNV) threshold for GPR101 that was subsequently diagnosed as having XLAG syndrome on HD-aCGH. Employing a combination of HD-aCGH and novel ddPCR approaches, we have demonstrated, for the first time, that XLAG syndrome can be caused by variable degrees of somatic mosaicism for duplications at chromosome Xq26.3. Somatic mosaicism was shown to occur in sporadic males but not in females with XLAG syndrome, although the clinical characteristics of the disease were similarly severe in both sexes.
Keywords: Adult; Female; Genetic Diseases, X-Linked; Gigantism; Humans; Male; Middle Aged; Mosaicism; Polymerase Chain Reaction; Syndrome; Young Adult

Somatic Mutations in NEK9 Cause Nevus Comedonicus. - Levinsohn, Jonathan L; Sugarman, Jeffrey L; McNiff, Jennifer M; Antaya, Richard J; Choate, Keith A (Am J Hum Genet, 2016)
Acne vulgaris (AV) affects most adolescents, and of those affected, moderate to severe disease occurs in 20%. Comedones, follicular plugs consisting of desquamated keratinocytes and sebum, are central to its pathogenesis. Despite high heritability in first-degree relatives, AV genetic determinants remain incompletely understood. We therefore employed whole-exome sequencing (WES) in nevus comedonicus (NC), a rare disorder that features comedones and inflammatory acne cysts in localized, linear configurations. WES identified somatic NEK9 mutations, each affecting highly conserved residues within its kinase or RCC1 domains, in affected tissue of three out of three NC-affected subjects. All mutations are gain of function, resulting in increased phosphorylation at Thr210, a hallmark of NEK9 kinase activation. We found that comedo formation in NC is marked by loss of follicular differentiation markers, expansion of keratin-15-positive cells from localization within the bulge to the entire sub-bulge follicle and cyst, and ectopic expression of keratin 10, a marker of interfollicular differentiation not present in normal follicles. These findings suggest that NEK9 mutations in NC disrupt normal follicular differentiation and identify NEK9 as a potential regulator of follicular homeostasis.
Keywords: Adolescent; Adult; Child; Female; Fluorescent Antibody Technique; High-Throughput Nucleotide Sequencing; Humans; Male; Mutation; Nevus; NIMA-Related Kinases; Prognosis; Skin Neoplasms; Young Adult

SRD5A3-CDG: Expanding the phenotype of a congenital disorder of glycosylation with emphasis on adult onset features. - Wheeler, Patricia G; Ng, Bobby G; Sanford, Laura; Sutton, V Reid; Bartholomew, Dennis W; Pastore, Matthew T; Bamshad, Michael J; Kircher, Martin; Buckingham, Kati J; Nickerson, Deborah A; Shendure, Jay; Freeze, Hudson H (Am J Med Genet A, 2016)
Increasing numbers of congenital disorders of glycosylation (CDG) have been reported recently resulting in an expansion of the phenotypes associated with this group of disorders. SRD5A3 codes for polyprenol reductase which converts polyprenol to dolichol. This is a major pathway for dolichol biosynthesis for N-glycosylation, O-mannosylation, C-mannosylation, and GPI anchor synthesis. We present the features of five individuals (three children and two adults) with mutations in SRD5A3 focusing on the variable eye and skin involvement. We compare that to 13 affected individuals from the literature including five adults allowing us to delineate the features that may develop over time with this disorder including kyphosis, retinitis pigmentosa, and cataracts. © 2016 Wiley Periodicals, Inc.
Keywords: 3-Oxo-5-alpha-Steroid 4-Dehydrogenase; Adult; Child; Congenital Disorders of Glycosylation; Dolichols; Eye; Female; Glycosylation; Homozygote; Humans; Male; Membrane Proteins; Mutation; Phenotype; Skin; Tretinoin

A Syndromic Intellectual Disability Disorder Caused by Variants in TELO2, a Gene Encoding a Component of the TTT Complex. - You, Jing; Sobreira, Nara L; Gable, Dustin L; Jurgens, Julie; Grange, Dorothy K; Belnap, Newell; Siniard, Ashley; Szelinger, Szabolcs; Schrauwen, Isabelle; Richholt, Ryan F; Vallee, Stephanie E; Dinulos, Mary Beth P; et al. (Am J Hum Genet, 2016)
The proteins encoded by TELO2, TTI1, and TTI2 interact to form the TTT complex, a co-chaperone for maturation of the phosphatidylinositol 3-kinase-related protein kinases (PIKKs). Here we report six affected individuals from four families with intellectual disability (ID) and neurological and other congenital abnormalities associated with compound heterozygous variants in TELO2. Although their fibroblasts showed reduced steady-state levels of TELO2 and the other components of the TTT complex, PIKK functions were normal in cellular assays. Our results suggest that these TELO2 missense variants result in loss of function, perturb TTT complex stability, and cause an autosomal-recessive syndromic form of ID.
Keywords: Adolescent; Carrier Proteins; Child; Female; Humans; Intellectual Disability; Male; Molecular Chaperones; Pedigree; Phosphatidylinositol 3-Kinases; Protein-Serine-Threonine Kinases; Telomere-Binding Proteins

Two novel germline DDX41 mutations in a family with inherited myelodysplasia/acute myeloid leukemia. - Li, Ruijuan; Sobreira, Nara; Witmer, P Dane; Pratz, Keith W; Braunstein, Evan M (Haematologica, 2016)
Keywords: DEAD-box RNA Helicases; Family; Female; Germ-Line Mutation; Humans; Leukemia, Myeloid, Acute; Male; Myelodysplastic Syndromes; Neoplasm Proteins

Update on the Toriello-Carey syndrome. - Toriello, Helga V; Colley, Chelsey; Bamshad, Michael (Am J Med Genet A, 2016)
Toriello and Carey described a provisionally-unique syndrome comprised of agenesis of the corpus callosum, Pierre Robin anomaly, and a characteristic facial phenotype. Because the condition affected siblings, this entity was postulated to be an autosomal recessive multiple anomaly syndrome. Several patients were subsequently reported, and over time, it became apparent that the Toriello-Carey syndrome was etiologically heterogeneous. Based on previous reports, it is estimated that at least 20% of patients with a clinical diagnosis of Toriello-Carey syndrome have a chromosomal anomaly as the basis of the phenotype. However, no basis for the non-chromosomal cases has been found. This review summarizes the literature to date and provides speculation regarding the possible explanations for failing to find the cause of Toriello-Carey syndrome. © 2016 Wiley Periodicals, Inc.
Keywords: Agenesis of Corpus Callosum; Chromosome Aberrations; Craniofacial Abnormalities; Female; Genetic Association Studies; Heart Defects, Congenital; Humans; Limb Deformities, Congenital; Male; Phenotype; Pierre Robin Syndrome; Urogenital Abnormalities

Using Whole Exome Sequencing to Identify Candidate Genes With Rare Variants In Nonsyndromic Cleft Lip and Palate. - Aylward, Alana; Cai, Yi; Lee, Andrew; Blue, Elizabeth; Rabinowitz, Daniel; Haddad, Joseph (Genet Epidemiol, 2016)
Studies suggest that nonsyndromic cleft lip and palate (NSCLP) is polygenic with variable penetrance, presenting a challenge in identifying all causal genetic variants. Despite relatively high prevalence of NSCLP among Amerindian populations, no large whole exome sequencing (WES) studies have been completed in this population. Our goal was to identify candidate genes with rare genetic variants for NSCLP in a Honduran population using WES. WES was performed on two to four members of 27 multiplex Honduran families. Genetic variants with a minor allele frequency > 1% in reference databases were removed. Heterozygous variants consistent with dominant disease with incomplete penetrance were ascertained, and variants with predicted functional consequence were prioritized for analysis. Pedigree-specific P-values were calculated as the probability of all affected members in the pedigree being carriers, given that at least one is a carrier. Preliminary results identified 3,727 heterozygous rare variants; 1,282 were predicted to be functionally consequential. Twenty-three genes had variants of interest in ≥3 families, where some genes had different variants in each family, giving a total of 50 variants. Variant validation via Sanger sequencing of the families and unrelated unaffected controls excluded variants that were sequencing errors or common variants not in databases, leaving four genes with candidate variants in ≥3 families. Of these, candidate variants in two genes consistently segregate with NSCLP as a dominant variant with incomplete penetrance: ACSS2 and PHYH. Rare variants found at the same gene in all affected individuals in several families are likely to be directly related to NSCLP.
Keywords: Acetate-CoA Ligase; Alleles; Cleft Lip; Cleft Palate; Female; Gene Frequency; Genotype; Heterozygote; Hexokinase; High-Throughput Nucleotide Sequencing; Humans; Male; Mixed Function Oxygenases; Pedigree; Penetrance; Sequence Analysis, DNA; von Willebrand Factor

Variants in SKP1, PROB1, and IL17B genes at keratoconus 5q31.1-q35.3 susceptibility locus identified by whole-exome sequencing. - Karolak, Justyna A; Gambin, Tomasz; Pitarque, Jose A; Molinari, Andrea; Jhangiani, Shalini; Stankiewicz, Pawel; Lupski, James R; Gajecka, Marzena (Eur J Hum Genet, 2016)
Keratoconus (KTCN) is a protrusion and thinning of the cornea, resulting in impairment of visual function. The extreme genetic heterogeneity makes it difficult to discover factors unambiguously influencing the KTCN phenotype. In this study, we used whole-exome sequencing (WES) and Sanger sequencing to reduce the number of candidate genes at the 5q31.1-q35.3 locus and to prioritize other potentially relevant variants in an Ecuadorian family with KTCN. We applied WES in two affected KTCN individuals from the Ecuadorian family that showed a suggestive linkage between the KTCN phenotype and the 5q31.1-q35.3 locus. Putative variants identified by WES were further evaluated in this family using Sanger sequencing. Exome capture discovered a total of 173 rare (minor allele frequency <0.001 in control population) nonsynonymous variants in both affected individuals. Among them, 16 SNVs were selected for further evaluation. Segregation analysis revealed that variants c.475T>G in SKP1, c.671G>A in PROB1, and c.527G>A in IL17B in the 5q31.1-q35.3 linkage region, and c.850G>A in HKDC1 in the 10q22 locus completely segregated with the phenotype in the studied KTCN family. We demonstrate that a combination of various techniques significantly narrowed the studied genomic region and reduced the list of the putative exonic variants. Moreover, since this locus overlapped two other chromosomal regions previously recognized in distinct KTCN studies, our findings suggest that this 5q31.1-q35.3 locus might be linked with KTCN.
Keywords: Chromosomes, Human, Pair 5; Exome; Female; Gene Frequency; Genetic Linkage; Genetic Predisposition to Disease; Genome, Human; Hexokinase; High-Throughput Nucleotide Sequencing; Humans; Interleukin-17; Keratoconus; Male; Pedigree; Phenotype; Proteins; S-Phase Kinase-Associated Proteins

Variants in SLC18A3, vesicular acetylcholine transporter, cause congenital myasthenic syndrome. - O'Grady, Gina L; Verschuuren, Corien; Yuen, Michaela; Webster, Richard; Menezes, Manoj; Fock, Johanna M; Pride, Natalie; Best, Heather A; Benavides Damm, Tatiana; Turner, Christian; Lek, Monkol; Engel, Andrew G; et al. (Neurology, 2016)
OBJECTIVE: To describe the clinical and genetic characteristics of presynaptic congenital myasthenic syndrome secondary to biallelic variants in SLC18A3. METHODS: Individuals from 2 families were identified with biallelic variants in SLC18A3, the gene encoding the vesicular acetylcholine transporter (VAChT), through whole-exome sequencing. RESULTS: The patients demonstrated features seen in presynaptic congenital myasthenic syndrome, including ptosis, ophthalmoplegia, fatigable weakness, apneic crises, and deterioration of symptoms in cold water for patient 1. Both patients demonstrated moderate clinical improvement on pyridostigmine. Patient 1 had a broader phenotype, including learning difficulties and left ventricular dysfunction. Electrophysiologic studies were typical for a presynaptic defect. Both patients showed profound electrodecrement on low-frequency repetitive stimulation followed by a prolonged period of postactivation exhaustion. In patient 1, this was unmasked only after isometric contraction, a recognized feature of presynaptic disease, emphasizing the importance of activation procedures. CONCLUSIONS: VAChT is responsible for uptake of acetylcholine into presynaptic vesicles. The clinical and electrographic characteristics of the patients described are consistent with previously reported mouse models of VAChT deficiency. These findings make it very likely that defects in VAChT due to variants in SLC18A3 are a cause of congenital myasthenic syndrome in humans.
Keywords: Adolescent; Child; Diagnosis, Differential; Female; Genetic Variation; Humans; Male; Myasthenic Syndromes, Congenital; Vesicular Acetylcholine Transport Proteins

Variants in the Oxidoreductase PYROXD1 Cause Early-Onset Myopathy with Internalized Nuclei and Myofibrillar Disorganization. - O'Grady, Gina L; Best, Heather A; Sztal, Tamar E; Schartner, Vanessa; Sanjuan-Vazquez, Myriam; Donkervoort, Sandra; Abath Neto, Osorio; Sutton, Roger Bryan; Ilkovski, Biljana; Romero, Norma Beatriz; Stojkovic, Tanya; Dastgir, Jahannaz; et al. (Am J Hum Genet, 2016)
This study establishes PYROXD1 variants as a cause of early-onset myopathy and uses biospecimens and cell lines, yeast, and zebrafish models to elucidate the fundamental role of PYROXD1 in skeletal muscle. Exome sequencing identified recessive variants in PYROXD1 in nine probands from five families. Affected individuals presented in infancy or childhood with slowly progressive proximal and distal weakness, facial weakness, nasal speech, swallowing difficulties, and normal to moderately elevated creatine kinase. Distinctive histopathology showed abundant internalized nuclei, myofibrillar disorganization, desmin-positive inclusions, and thickened Z-bands. PYROXD1 is a nuclear-cytoplasmic pyridine nucleotide-disulphide reductase (PNDR). PNDRs are flavoproteins (FAD-binding) and catalyze pyridine-nucleotide-dependent (NAD/NADH) reduction of thiol residues in other proteins. Complementation experiments in yeast lacking glutathione reductase glr1 show that human PYROXD1 has reductase activity that is strongly impaired by the disease-associated missense mutations. Immunolocalization studies in human muscle and zebrafish myofibers demonstrate that PYROXD1 localizes to the nucleus and to striated sarcomeric compartments. Zebrafish with ryroxD1 knock-down recapitulate features of PYROXD1 myopathy with sarcomeric disorganization, myofibrillar aggregates, and marked swimming defect. We characterize variants in the oxidoreductase PYROXD1 as a cause of early-onset myopathy with distinctive histopathology and introduce altered redox regulation as a primary cause of congenital muscle disease.
Keywords: Amino Acid Sequence; Animals; Cell Nucleus; Cercopithecus aethiops; Cohort Studies; COS Cells; Creatine Kinase; Cytoplasm; Distal Myopathies; ELAV-Like Protein 4; Female; Flavoproteins; Gene Deletion; Genetic Variation; Genome-Wide Association Study; Glutathione Reductase; HEK293 Cells; Humans; Male; Muscle, Skeletal; Mutation, Missense; Myopathies, Structural, Congenital; Oxidoreductases; Pedigree; Protein Conformation; Saccharomyces cerevisiae Proteins; Zebrafish

Visceral myopathy: Clinical and molecular survey of a cohort of seven new patients and state of the art of overlapping phenotypes. - Moreno, Carolina Araujo; Metze, Konradin; Lomazi, Elizete Aparecida; Bertola, Débora Romeo; Barbosa, Ricardo Henrique Almeida; Cosentino, Viviana; Sobreira, Nara; Cavalcanti, Denise Pontes (Am J Med Genet A, 2016)
Visceral motility dysfunction is a key feature of genetic disorders such as megacystis-microcolon-intestinal hypoperistalsis syndrome (MMIHS, MIM moved from 249210 to 155310), chronic intestinal pseudo-obstruction (CIPO, MIM609629), and multisystemic smooth muscle dysfunction syndrome (MSMDS, MIM613834). The genetic bases of these conditions recently begun to be clarified with the identification of pathogenic variants in ACTG2, ACTA2, and MYH11 in individuals with visceral motility dysfunction. The MMIHS was associated with the heterozygous variant in ACTG2 and homozygous variant in MYH11, while the heterozygous variant in ACTA2 was observed in patients with MSMDS. In this study, we describe the clinical data as well as the molecular investigation of seven individuals with visceral myopathy phenotypes. Five patients presented with MMIHS, including two siblings from consanguineous parents, one had CIPO, and the other had MSMDS. In three individuals with MMIHS and in one with CIPO we identified heterozygous variant in ACTG2, one being a novel variant (c.584C>T-p.Thr195Ile). In the individual with MSMDS we identified a heterozygous variant in ACTA2. We performed the whole-exome sequencing in one sibling with MMIHS and her parents; however, the pathogenic variant responsible for her phenotype could not be identified. These results reinforce the clinical and genetic heterogeneity of the visceral myopathies. Although many cases of MMIHS are associated with ACTG2 variants, we suggest that other genes, besides MYH11, could cause the MMIHS with autosomal recessive pattern. © 2016 Wiley Periodicals, Inc.
Keywords: Abnormalities, Multiple; Actins; Child, Preschool; Colon; Consanguinity; DNA Mutational Analysis; Fatal Outcome; Female; Genetic Association Studies; Humans; Infant; Infant, Newborn; Intestinal Pseudo-Obstruction; Male; Mutation; Phenotype; Polymorphism, Single Nucleotide; Treatment Outcome; Ultrasonography, Prenatal; Urinary Bladder

Whole-exome sequencing identifies novel variants in PNPT1 causing oxidative phosphorylation defects and severe multisystem disease. - Alodaib, Ahmad; Sobreira, Nara; Gold, Wendy A; Riley, Lisa G; Van Bergen, Nicole J; Wilson, Meredith J; Bennetts, Bruce; Thorburn, David R; Boehm, Corinne; Christodoulou, John (Eur J Hum Genet, 2016)
Recent advances in next-generation sequencing strategies have led to the discovery of many novel disease genes. We describe here a non-consanguineous family with two affected boys presenting with early onset of severe axonal neuropathy, optic atrophy, intellectual disability, auditory neuropathy and chronic respiratory and gut disturbances. Whole-exome sequencing (WES) was performed on all family members and we identified compound heterozygous variants (c.[760C>A];[1528G>C];p.[(Gln254Lys);(Ala510Pro)] in the polyribonucleotide nucleotidyltransferase 1 (PNPT1) gene in both affected individuals. PNPT1 encodes the polynucleotide phosphorylase (PNPase) protein, which is involved in the transport of small RNAs into the mitochondria. These RNAs are involved in the mitochondrial translation machinery, responsible for the synthesis of mitochondrially encoded subunits of the oxidative phosphorylation (OXPHOS) complexes. Both PNPT1 variants are within highly conserved regions and predicted to be damaging. These variants resulted in quaternary defects in the PNPase protein and a clear reduction in protein and mRNA expression of PNPT1 in patient fibroblasts compared with control cells. Protein analysis of the OXPHOS complexes showed a significant reduction in complex I (CI), complex III (CIII) and complex IV (CIV). Enzyme activity of CI and CIV was clearly reduced in patient fibroblasts compared with controls along with a 33% reduction in total mitochondrial protein synthesis. In vitro rescue experiments, using exogenous expression of wild-type PNPT1 in patient fibroblasts, ameliorated the deficiencies in the OXPHOS complex protein expression, supporting the likely pathogenicity of these variants and the importance of WES in efficiently identifying rare genetic disease genes.
Keywords: Axons; Exome; Exoribonucleases; High-Throughput Nucleotide Sequencing; Humans; Intellectual Disability; Male; Mitochondria; Mutation; Optic Atrophy; Oxidative Phosphorylation; Pedigree; Protein Structure, Quaternary

Whole-Exome Sequencing in Familial Parkinson Disease. - Farlow, Janice L; Robak, Laurie A; Hetrick, Kurt; Bowling, Kevin; Boerwinkle, Eric; Coban-Akdemir, Zeynep H; Gambin, Tomasz; Gibbs, Richard A; Gu, Shen; Jain, Preti; Jankovic, Joseph; Jhangiani, Shalini; et al. (JAMA Neurol, 2016)
IMPORTANCE: Parkinson disease (PD) is a progressive neurodegenerative disease for which susceptibility is linked to genetic and environmental risk factors. OBJECTIVE: To identify genetic variants contributing to disease risk in familial PD. DESIGN, SETTING, AND PARTICIPANTS: A 2-stage study design that included a discovery cohort of families with PD and a replication cohort of familial probands was used. In the discovery cohort, rare exonic variants that segregated in multiple affected individuals in a family and were predicted to be conserved or damaging were retained. Genes with retained variants were prioritized if expressed in the brain and located within PD-relevant pathways. Genes in which prioritized variants were observed in at least 4 families were selected as candidate genes for replication in the replication cohort. The setting was among individuals with familial PD enrolled from academic movement disorder specialty clinics across the United States. All participants had a family history of PD. MAIN OUTCOMES AND MEASURES: Identification of genes containing rare, likely deleterious, genetic variants in individuals with familial PD using a 2-stage exome sequencing study design. RESULTS: The 93 individuals from 32 families in the discovery cohort (49.5% [46 of 93] female) had a mean (SD) age at onset of 61.8 (10.0) years. The 49 individuals with familial PD in the replication cohort (32.6% [16 of 49] female) had a mean (SD) age at onset of 50.1 (15.7) years. Discovery cohort recruitment dates were 1999 to 2009, and replication cohort recruitment dates were 2003 to 2014. Data analysis dates were 2011 to 2015. Three genes containing a total of 13 rare and potentially damaging variants were prioritized in the discovery cohort. Two of these genes (TNK2 and TNR) also had rare variants that were predicted to be damaging in the replication cohort. All 9 variants identified in the 2 replicated genes in 12 families across the discovery and replication cohorts were confirmed via Sanger sequencing. CONCLUSIONS AND RELEVANCE: TNK2 and TNR harbored rare, likely deleterious, variants in individuals having familial PD, with similar findings in an independent cohort. To our knowledge, these genes have not been previously associated with PD, although they have been linked to critical neuronal functions. Further studies are required to confirm a potential role for these genes in the pathogenesis of PD.
Keywords: Adult; Aged; Cohort Studies; Exome; Female; Genetic Predisposition to Disease; Genetic Variation; Humans; Male; Middle Aged; Parkinsonian Disorders; Protein-Tyrosine Kinases; Sequence Analysis, DNA; Tenascin

Activating Mutations Affecting the Dbl Homology Domain of SOS2 Cause Noonan Syndrome. - Cordeddu, Viviana; Yin, Jiani C; Gunnarsson, Cecilia; Virtanen, Carl; Drunat, Séverine; Lepri, Francesca; De Luca, Alessandro; Rossi, Cesare; Ciolfi, Andrea; Pugh, Trevor J; Bruselles, Alessandro; Priest, James R; et al. (Hum Mutat, 2015)
The RASopathies constitute a family of autosomal-dominant disorders whose major features include facial dysmorphism, cardiac defects, reduced postnatal growth, variable cognitive deficits, ectodermal and skeletal anomalies, and susceptibility to certain malignancies. Noonan syndrome (NS), the commonest RASopathy, is genetically heterogeneous and caused by functional dysregulation of signal transducers and regulatory proteins with roles in the RAS/extracellular signal-regulated kinase (ERK) signal transduction pathway. Mutations in known disease genes account for approximately 80% of affected individuals. Here, we report that missense mutations altering Son of Sevenless, Drosophila, homolog 2 (SOS2), which encodes a RAS guanine nucleotide exchange factor, occur in a small percentage of subjects with NS. Four missense mutations were identified in five unrelated sporadic cases and families transmitting NS. Disease-causing mutations affected three conserved residues located in the Dbl homology (DH) domain, of which two are directly involved in the intramolecular binding network maintaining SOS2 in its autoinhibited conformation. All mutations were found to promote enhanced signaling from RAS to ERK. Similar to NS-causing SOS1 mutations, the phenotype associated with SOS2 defects is characterized by normal development and growth, as well as marked ectodermal involvement. Unlike SOS1 mutations, however, those in SOS2 are restricted to the DH domain.
Keywords: Adolescent; Adult; Alleles; Amino Acid Substitution; Child; DNA Mutational Analysis; Exome; Facies; Female; Genetic Association Studies; Genotype; Humans; Male; Models, Molecular; Mutation; Noonan Syndrome; Phenotype; Protein Conformation; Protein Interaction Domains and Motifs; Son of Sevenless Proteins; Young Adult

Allelic Mutations of KITLG, Encoding KIT Ligand, Cause Asymmetric and Unilateral Hearing Loss and Waardenburg Syndrome Type 2. - Zazo Seco, Celia; Serrão de Castro, Luciana; van Nierop, Josephine W; Morín, Matías; Jhangiani, Shalini; Verver, Eva J J; Schraders, Margit; Maiwald, Nadine; Wesdorp, Mieke; Venselaar, Hanka; Spruijt, Liesbeth; Oostrik, Jaap; et al. (Am J Hum Genet, 2015)
Linkage analysis combined with whole-exome sequencing in a large family with congenital and stable non-syndromic unilateral and asymmetric hearing loss (NS-UHL/AHL) revealed a heterozygous truncating mutation, c.286_303delinsT (p.Ser96Ter), in KITLG. This mutation co-segregated with NS-UHL/AHL as a dominant trait with reduced penetrance. By screening a panel of probands with NS-UHL/AHL, we found an additional mutation, c.200_202del (p.His67_Cys68delinsArg). In vitro studies revealed that the p.His67_Cys68delinsArg transmembrane isoform of KITLG is not detectable at the cell membrane, supporting pathogenicity. KITLG encodes a ligand for the KIT receptor. Also, KITLG-KIT signaling and MITF are suggested to mutually interact in melanocyte development. Because mutations in MITF are causative of Waardenburg syndrome type 2 (WS2), we screened KITLG in suspected WS2-affected probands. A heterozygous missense mutation, c.310C>G (p.Leu104Val), that segregated with WS2 was identified in a small family. In vitro studies revealed that the p.Leu104Val transmembrane isoform of KITLG is located at the cell membrane, as is wild-type KITLG. However, in culture media of transfected cells, the p.Leu104Val soluble isoform of KITLG was reduced, and no soluble p.His67_Cys68delinsArg and p.Ser96Ter KITLG could be detected. These data suggest that mutations in KITLG associated with NS-UHL/AHL have a loss-of-function effect. We speculate that the mechanism of the mutation underlying WS2 and leading to membrane incorporation and reduced secretion of KITLG occurs via a dominant-negative or gain-of-function effect. Our study unveils different phenotypes associated with KITLG, previously associated with pigmentation abnormalities, and will thereby improve the genetic counseling given to individuals with KITLG variants.
Keywords: Alleles; Animals; Female; Fluorescent Antibody Technique; Genetic Linkage; Hearing Loss, Unilateral; Humans; Male; Mice; Mutation; NIH 3T3 Cells; Pedigree; Phenotype; Prognosis; Real-Time Polymerase Chain Reaction; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Stem Cell Factor; Waardenburg Syndrome

Alu-mediated diverse and complex pathogenic copy-number variants within human chromosome 17 at p13.3. - Gu, Shen; Yuan, Bo; Campbell, Ian M; Beck, Christine R; Carvalho, Claudia M B; Nagamani, Sandesh C S; Erez, Ayelet; Patel, Ankita; Bacino, Carlos A; Shaw, Chad A; Stankiewicz, Paweł; Cheung, Sau Wai; et al. (Hum Mol Genet, 2015)
Alu repetitive elements are known to be major contributors to genome instability by generating Alu-mediated copy-number variants (CNVs). Most of the reported Alu-mediated CNVs are simple deletions and duplications, and the mechanism underlying Alu-Alu-mediated rearrangement has been attributed to non-allelic homologous recombination (NAHR). Chromosome 17 at the p13.3 genomic region lacks extensive low-copy repeat architecture; however, it is highly enriched for Alu repetitive elements, with a fraction of 30% of total sequence annotated in the human reference genome, compared with the 10% genome-wide and 18% on chromosome 17. We conducted mechanistic studies of the 17p13.3 CNVs by performing high-density oligonucleotide array comparative genomic hybridization, specifically interrogating the 17p13.3 region with ∼150 bp per probe density; CNV breakpoint junctions were mapped to nucleotide resolution by polymerase chain reaction and Sanger sequencing. Studied rearrangements include 5 interstitial deletions, 14 tandem duplications, 7 terminal deletions and 13 complex genomic rearrangements (CGRs). Within the 17p13.3 region, Alu-Alu-mediated rearrangements were identified in 80% of the interstitial deletions, 46% of the tandem duplications and 50% of the CGRs, indicating that this mechanism was a major contributor for formation of breakpoint junctions. Our studies suggest that Alu repetitive elements facilitate formation of non-recurrent CNVs, CGRs and other structural aberrations of chromosome 17 at p13.3. The common observation of Alu-mediated rearrangement in CGRs and breakpoint junction sequences analysis further demonstrates that this type of mechanism is unlikely attributed to NAHR, but rather may be due to a recombination-coupled DNA replicative repair process.
Keywords: Alleles; Alu Elements; Base Sequence; Chromosomes, Human, Pair 17; Comparative Genomic Hybridization; DNA Copy Number Variations; Female; Gene Duplication; Gene Rearrangement; Genome, Human; Genomic Instability; Genomics; Homologous Recombination; Humans; Male; Molecular Sequence Data; Segmental Duplications, Genomic; Sequence Deletion

An anadysplasia-like, spontaneously remitting spondylometaphyseal dysplasia secondary to lamin B receptor (LBR) gene mutations: further definition of the phenotypic heterogeneity of LBR-bone dysplasias. - Sobreira, Nara; Modaff, Peggy; Steel, Gary; You, Jing; Nanda, Sonia; Hoover-Fong, Julie; Valle, David; Pauli, Richard M (Am J Med Genet A, 2015)
We describe a boy who has an anadysplasia-like spondylometaphyseal dysplasia. By whole exome sequencing he was shown to have compound heterozygous mutations of LBR that codes for the lamin B receptor. He shares many similarities with a case previously described, but in whom the early natural history could not be established [Borovik et al., 2013]. Thus, in addition to Greenberg dysplasia (a perinatal lethal disorder), homozygosity or compound heterozygosity of mutations in LBR can result in a mild, spontaneously regressing bone dysplasia.
Keywords: Adolescent; Adult; Child; Child, Preschool; Female; Humans; Infant; Infant, Newborn; Male; Mutation; Osteochondrodysplasias; Phenotype; Pregnancy; Radiography; Receptors, Cytoplasmic and Nuclear; Spine

Assessment of incidental findings in 232 whole-exome sequences from the Baylor-Hopkins Center for Mendelian Genomics. - Jurgens, Julie; Ling, Hua; Hetrick, Kurt; Pugh, Elizabeth; Schiettecatte, François; Doheny, Kimberly; Hamosh, Ada; Avramopoulos, Dimitri; Valle, David; Sobreira, Nara (Genet Med, 2015)
PURPOSE: In March 2013 the American College of Medical Genetics and Genomics published a list of 56 genes with the recommendation that pathogenic and likely pathogenic variants detected incidentally by clinical sequencing be reported to patients. As an initial step in determining the practical consequences of this recommendation in the research setting, we searched for variants in these genes in 232 whole-exome sequences from the Baylor-Hopkins Center for Mendelian Genomics. METHODS: We identified rare, nonsynonymous, and splicing single-nucleotide variants and insertions/deletions and assessed variant classification using the Human Gene Mutation, Emory, and ClinVar databases. We analyzed the burden of mutation in each of the 56 genes and determined which variants should be reported to patients. RESULTS: Our filtering resulted in 249 distinct variants, with a mean of 1.69 variants per individual. Half of these were novel missense mutations not classified by any of the three reference databases. Of 101 variants listed in the Human Gene Mutation Database, 48 were also in ClinVar and 3 were also in Emory; half of these shared variants were classified discordantly between databases. Some genes consistently had greater variation than others. In total, 0.86% of individuals had a reportable incidental variant. CONCLUSION: These observations demonstrate some current challenges of assessing phenotypic consequences of incidental variants for counseling patients.
Keywords: Databases, Nucleic Acid; Exome; Female; Genetic Diseases, Inborn; Genomics; High-Throughput Nucleotide Sequencing; Humans; Incidental Findings; Male; Mutation; Polymorphism, Single Nucleotide

Association of Rare Loss-Of-Function Alleles in HAL, Serum Histidine: Levels and Incident Coronary Heart Disease. - Yu, Bing; Li, Alexander H; Muzny, Donna; Veeraraghavan, Narayanan; de Vries, Paul S; Bis, Joshua C; Musani, Solomon K; Alexander, Danny; Morrison, Alanna C; Franco, Oscar H; Uitterlinden, André; Hofman, Albert; et al. (Circ Cardiovasc Genet, 2015)
BACKGROUND: Histidine is a semiessential amino acid with antioxidant and anti-inflammatory properties. Few data are available on the associations between genetic variants, histidine levels, and incident coronary heart disease (CHD) in a population-based sample. METHODS AND RESULTS: By conducting whole exome sequencing on 1152 African Americans in the Atherosclerosis Risk in Communities (ARIC) study and focusing on loss-of-function (LoF) variants, we identified 3 novel rare LoF variants in HAL, a gene that encodes histidine ammonia-lyase in the first step of histidine catabolism. These LoF variants had large effects on blood histidine levels (β=0.26; P=1.2×10(-13)). The positive association with histidine levels was replicated by genotyping an independent sample of 718 ARIC African Americans (minor allele frequency=1%; P=1.2×10(-4)). In addition, high blood histidine levels were associated with reduced risk of developing incident CHD with an average of 21.5 years of follow-up among African Americans (hazard ratio=0.18; P=1.9×10(-4)). This finding was validated in an independent sample of European Americans from the Framingham Heart Study (FHS) Offspring Cohort. However, LoF variants in HAL were not directly significantly associated with incident CHD after meta-analyzing results from the CHARGE Consortium. CONCLUSIONS: Three LoF mutations in HAL were associated with increased histidine levels, which in turn were shown to be inversely related to the risk of CHD among both African Americans and European Americans. Future investigations on the association between HAL gene variation and CHD are warranted.
Keywords: Adult; African Americans; Alleles; Coronary Disease; European Continental Ancestry Group; Female; Histidine; Histidine Ammonia-Lyase; Humans; Male; Mutation

Biallelic mutations in SNX14 cause a syndromic form of cerebellar atrophy and lysosome-autophagosome dysfunction. - Akizu, Naiara; Cantagrel, Vincent; Zaki, Maha S; Al-Gazali, Lihadh; Wang, Xin; Rosti, Rasim Ozgur; Dikoglu, Esra; Gelot, Antoinette Bernabe; Rosti, Basak; Vaux, Keith K; Scott, Eric M; Silhavy, Jennifer L; et al. (Nat Genet, 2015)
Pediatric-onset ataxias often present clinically as developmental delay and intellectual disability, with prominent cerebellar atrophy as a key neuroradiographic finding. Here we describe a new clinically distinguishable recessive syndrome in 12 families with cerebellar atrophy together with ataxia, coarsened facial features and intellectual disability, due to truncating mutations in the sorting nexin gene SNX14, encoding a ubiquitously expressed modular PX domain-containing sorting factor. We found SNX14 localized to lysosomes and associated with phosphatidylinositol (3,5)-bisphosphate, a key component of late endosomes/lysosomes. Patient-derived cells showed engorged lysosomes and a slower autophagosome clearance rate upon autophagy induction by starvation. Zebrafish morphants for snx14 showed dramatic loss of cerebellar parenchyma, accumulation of autophagosomes and activation of apoptosis. Our results characterize a unique ataxia syndrome due to biallelic SNX14 mutations leading to lysosome-autophagosome dysfunction.
Keywords: Animals; Atrophy; Autophagy; Cerebellar Diseases; Cerebellum; Child, Preschool; Female; Gene Frequency; Humans; Infant; Lod Score; Lysosomal Storage Diseases; Lysosomes; Male; Mutation; Phagosomes; Sorting Nexins; Spinocerebellar Ataxias; Syndrome; Zebrafish

Cerebral visual impairment and intellectual disability caused by PGAP1 variants. - Bosch, Daniëlle G M; Boonstra, F Nienke; Kinoshita, Taroh; Jhangiani, Shalini; de Ligt, Joep; Cremers, Frans P M; Lupski, James R; Murakami, Yoshiko; de Vries, Bert B A (Eur J Hum Genet, 2015)
Homozygous variants in PGAP1 (post-GPI attachment to proteins 1) have recently been identified in two families with developmental delay, seizures and/or spasticity. PGAP1 is a member of the glycosylphosphatidylinositol anchor biosynthesis and remodeling pathway and defects in this pathway are a subclass of congenital disorders of glycosylation. Here we performed whole-exome sequencing in an individual with cerebral visual impairment (CVI), intellectual disability (ID), and factor XII deficiency and revealed compound heterozygous variants in PGAP1, c.274_276del (p.(Pro92del)) and c.921_925del (p.(Lys308Asnfs*25)). Subsequently, PGAP1-deficient Chinese hamster ovary (CHO)-cell lines were transfected with either mutant or wild-type constructs and their sensitivity to phosphatidylinositol-specific phospholipase C (PI-PLC) treatment was measured. The mutant constructs could not rescue the PGAP1-deficient CHO cell lines resistance to PI-PLC treatment. In addition, lymphoblastoid cell lines (LCLs) of the affected individual showed no sensitivity to PI-PLC treatment, whereas the LCLs of the heterozygous carrier parents were partially resistant. In conclusion, we report novel PGAP1 variants in a boy with CVI and ID and a proven functional loss of PGAP1 and show, to our knowledge, for the first time this genetic association with CVI.
Keywords: Animals; Cell Line, Tumor; Child; CHO Cells; Cricetinae; Cricetulus; Humans; Intellectual Disability; Male; Membrane Proteins; Mutation; Phosphoinositide Phospholipase C; Phosphoric Monoester Hydrolases; Syndrome; Vision Disorders; Visual Perception

Challenges and solutions for gene identification in the presence of familial locus heterogeneity. - Rehman, Atteeq U; Santos-Cortez, Regie Lyn P; Drummond, Meghan C; Shahzad, Mohsin; Lee, Kwanghyuk; Morell, Robert J; Ansar, Muhammad; Jan, Abid; Wang, Xin; Aziz, Abdul; Riazuddin, Saima; Smith, Joshua D; et al. (Eur J Hum Genet, 2015)
Next-generation sequencing (NGS) of exomes and genomes has accelerated the identification of genes involved in Mendelian phenotypes. However, many NGS studies fall short of identifying causal variants, with estimates for success rates as low as 25% for uncovering the pathological variant underlying disease etiology. An important reason for such failures is familial locus heterogeneity, where within a single pedigree causal variants in two or more genes underlie Mendelian trait etiology. As examples of intra- and inter-sibship familial locus heterogeneity, we present 10 consanguineous Pakistani families segregating hearing impairment due to homozygous variants in two different hearing impairment genes and a European-American pedigree in which hearing impairment is caused by four variants in three different genes. We have identified 41 additional pedigrees with syndromic and nonsyndromic hearing impairment for which a single previously reported hearing impairment gene has been identified but only segregates with the phenotype in a subset of affected pedigree members. We estimate that locus heterogeneity occurs in 15.3% (95% confidence interval: 11.9%, 19.9%) of the families in our collection. We demonstrate novel approaches to apply linkage analysis and homozygosity mapping (for autosomal recessive consanguineous pedigrees), which can be used to detect locus heterogeneity using either NGS or SNP array data. Results from linkage analysis and homozygosity mapping can also be used to group sibships or individuals most likely to be segregating the same causal variants and thereby increase the success rate of gene identification.
Keywords: Asian Continental Ancestry Group; Calcium-Binding Proteins; Chromosome Mapping; Connexin 26; Connexins; Consanguinity; European Continental Ancestry Group; Female; Genes, Recessive; Genetic Heterogeneity; Genetic Linkage; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genotype; Hearing Loss; Hepatocyte Growth Factor; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Male; Membrane Transport Proteins; Mutation; Pedigree; Phenotype; Sulfate Transporters

Characterization of a New DGKE Intronic Mutation in Genetically Unsolved Cases of Familial Atypical Hemolytic Uremic Syndrome. - Mele, Caterina; Lemaire, Mathieu; Iatropoulos, Paraskevas; Piras, Rossella; Bresin, Elena; Bettoni, Serena; Bick, David; Helbling, Daniel; Veith, Regan; Valoti, Elisabetta; Donadelli, Roberta; Murer, Luisa; et al. (Clin J Am Soc Nephrol, 2015)
BACKGROUND AND OBJECTIVES: Genetic and acquired abnormalities causing dysregulation of the complement alternative pathway contribute to atypical hemolytic uremic syndrome (aHUS), a rare disorder characterized by thrombocytopenia, nonimmune microangiopathic hemolytic anemia, and acute kidney failure. However, in a substantial proportion of patients the disease-associated alterations are still unknown. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: Whole-exome and whole-genome sequencing were performed in two unrelated families with infantile recessive aHUS. Sequencing of cDNA from affected individuals was used to test for the presence of aberrant mRNA species. Expression of mutant diacylglycerol kinase epsilon (DGKE) protein was evaluated with western blotting. RESULTS: Whole-exome sequencing analysis with conventional variant filtering parameters did not reveal any obvious candidate mutation in the first family. The report of aHUS-associated mutations in DGKE, encoding DGKE, led to re-examination of the noncoding DGKE variants obtained from next-generation sequencing, allowing identification of a novel intronic DGKE mutation (c.888+40A>G) that segregated with disease. Sequencing of cDNA from affected individuals revealed aberrant forms of DGKE mRNA predicted to cause profound abnormalities in the protein catalytic site. By whole-genome sequencing, the same mutation was found in compound heterozygosity with a second nonsense DGKE mutation in all affected siblings of another unrelated family. Homozygous and compound heterozygous patients presented similar clinical features, including aHUS presentation in the first year of life, multiple relapsing episodes, and proteinuria, which are prototypical of DGKE-associated aHUS. CONCLUSIONS: This is the first report of a mutation located beyond the exon-intron boundaries in aHUS. Intronic mutations such as these are underreported because conventional filtering parameters used to process next-generation sequencing data routinely exclude these regions from downstream analyses in both research and clinical settings. The results suggest that analysis of noncoding regions of aHUS-associated genes coupled with mRNA sequencing might provide a tool to explain genetically unsolved aHUS cases.
Keywords: Adolescent; Atypical Hemolytic Uremic Syndrome; Base Sequence; Blotting, Western; Child; Diacylglycerol Kinase; DNA Mutational Analysis; Female; Genetic Association Studies; Genetic Predisposition to Disease; Heterozygote; Homozygote; Humans; Infant; Introns; Male; Molecular Sequence Data; Mutation; Phenotype; Predictive Value of Tests; Risk Factors

Cognitive phenotypes and genomic copy number variations. - Lupski, James R (JAMA, 2015)
Keywords: DNA Copy Number Variations; Female; Heterozygote; Humans; Intellectual Disability; Male; Mental Disorders

COPA mutations impair ER-Golgi transport and cause hereditary autoimmune-mediated lung disease and arthritis. - Watkin, Levi B; Jessen, Birthe; Wiszniewski, Wojciech; Vece, Timothy J; Jan, Max; Sha, Youbao; Thamsen, Maike; Santos-Cortez, Regie L P; Lee, Kwanghyuk; Gambin, Tomasz; Forbes, Lisa R; Law, Christopher S; et al. (Nat Genet, 2015)
Unbiased genetic studies have uncovered surprising molecular mechanisms in human cellular immunity and autoimmunity. We performed whole-exome sequencing and targeted sequencing in five families with an apparent mendelian syndrome of autoimmunity characterized by high-titer autoantibodies, inflammatory arthritis and interstitial lung disease. We identified four unique deleterious variants in the COPA gene (encoding coatomer subunit α) affecting the same functional domain. Hypothesizing that mutant COPA leads to defective intracellular transport via coat protein complex I (COPI), we show that COPA variants impair binding to proteins targeted for retrograde Golgi-to-ER transport. Additionally, expression of mutant COPA results in ER stress and the upregulation of cytokines priming for a T helper type 17 (TH17) response. Patient-derived CD4(+) T cells also demonstrate significant skewing toward a TH17 phenotype that is implicated in autoimmunity. Our findings uncover an unexpected molecular link between a vesicular transport protein and a syndrome of autoimmunity manifested by lung and joint disease.
Keywords: Amino Acid Sequence; Arthritis; Autoimmune Diseases; Child, Preschool; Coatomer Protein; Endoplasmic Reticulum; Endoplasmic Reticulum Stress; Female; Genetic Association Studies; Genetic Predisposition to Disease; Golgi Apparatus; HEK293 Cells; Humans; Infant; Lod Score; Lung Diseases, Interstitial; Male; Molecular Sequence Data; Pedigree; Protein Transport

De Novo GMNN Mutations Cause Autosomal-Dominant Primordial Dwarfism Associated with Meier-Gorlin Syndrome. - Burrage, Lindsay C; Charng, Wu-Lin; Eldomery, Mohammad K; Willer, Jason R; Davis, Erica E; Lugtenberg, Dorien; Zhu, Wenmiao; Leduc, Magalie S; Akdemir, Zeynep C; Azamian, Mahshid; Zapata, Gladys; Hernandez, Patricia P; et al. (Am J Hum Genet, 2015)
Meier-Gorlin syndrome (MGS) is a genetically heterogeneous primordial dwarfism syndrome known to be caused by biallelic loss-of-function mutations in one of five genes encoding pre-replication complex proteins: ORC1, ORC4, ORC6, CDT1, and CDC6. Mutations in these genes cause disruption of the origin of DNA replication initiation. To date, only an autosomal-recessive inheritance pattern has been described in individuals with this disorder, with a molecular etiology established in about three-fourths of cases. Here, we report three subjects with MGS and de novo heterozygous mutations in the 5' end of GMNN, encoding the DNA replication inhibitor geminin. We identified two truncating mutations in exon 2 (the 1(st) coding exon), c.16A>T (p.Lys6(∗)) and c.35_38delTCAA (p.Ile12Lysfs(∗)4), and one missense mutation, c.50A>G (p.Lys17Arg), affecting the second-to-last nucleotide of exon 2 and possibly RNA splicing. Geminin is present during the S, G2, and M phases of the cell cycle and is degraded during the metaphase-anaphase transition by the anaphase-promoting complex (APC), which recognizes the destruction box sequence near the 5' end of the geminin protein. All three GMNN mutations identified alter sites 5' to residue Met28 of the protein, which is located within the destruction box. We present data supporting a gain-of-function mechanism, in which the GMNN mutations result in proteins lacking the destruction box and hence increased protein stability and prolonged inhibition of replication leading to autosomal-dominant MGS.
Keywords: Adolescent; Amino Acid Sequence; Base Sequence; Cell Cycle; Child, Preschool; Congenital Microtia; Dwarfism; Exons; Female; Geminin; Gene Expression; Genes, Dominant; Growth Disorders; Heterozygote; High-Throughput Nucleotide Sequencing; Humans; Inheritance Patterns; Male; Micrognathism; Molecular Sequence Data; Mutation; Patella; Pedigree; Protein Stability; Proteolysis; RNA Splicing; Sequence Alignment

De novo mutations in NALCN cause a syndrome characterized by congenital contractures of the limbs and face, hypotonia, and developmental delay. - Chong, Jessica X; McMillin, Margaret J; Shively, Kathryn M; Beck, Anita E; Marvin, Colby T; Armenteros, Jose R; Buckingham, Kati J; Nkinsi, Naomi T; Boyle, Evan A; Berry, Margaret N; Bocian, Maureen; Foulds, Nicola; et al. (Am J Hum Genet, 2015)
Freeman-Sheldon syndrome, or distal arthrogryposis type 2A (DA2A), is an autosomal-dominant condition caused by mutations in MYH3 and characterized by multiple congenital contractures of the face and limbs and normal cognitive development. We identified a subset of five individuals who had been putatively diagnosed with "DA2A with severe neurological abnormalities" and for whom congenital contractures of the limbs and face, hypotonia, and global developmental delay had resulted in early death in three cases; this is a unique condition that we now refer to as CLIFAHDD syndrome. Exome sequencing identified missense mutations in the sodium leak channel, non-selective (NALCN) in four families affected by CLIFAHDD syndrome. We used molecular-inversion probes to screen for NALCN in a cohort of 202 distal arthrogryposis (DA)-affected individuals as well as concurrent exome sequencing of six other DA-affected individuals, thus revealing NALCN mutations in ten additional families with "atypical" forms of DA. All 14 mutations were missense variants predicted to alter amino acid residues in or near the S5 and S6 pore-forming segments of NALCN, highlighting the functional importance of these segments. In vitro functional studies demonstrated that NALCN alterations nearly abolished the expression of wild-type NALCN, suggesting that alterations that cause CLIFAHDD syndrome have a dominant-negative effect. In contrast, homozygosity for mutations in other regions of NALCN has been reported in three families affected by an autosomal-recessive condition characterized mainly by hypotonia and severe intellectual disability. Accordingly, mutations in NALCN can cause either a recessive or dominant condition characterized by varied though overlapping phenotypic features, perhaps based on the type of mutation and affected protein domain(s).
Keywords: Arthrogryposis; Contracture; Craniofacial Dysostosis; Cytoskeletal Proteins; Exome; Extremities; Face; Female; Gene Frequency; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Infant; Male; Muscle Hypotonia; Mutation, Missense; Sodium Channels

Dominant De Novo Mutations in GJA1 Cause Erythrokeratodermia Variabilis et Progressiva, without Features of Oculodentodigital Dysplasia. - Boyden, Lynn M; Craiglow, Brittany G; Zhou, Jing; Hu, Ronghua; Loring, Erin C; Morel, Kimberly D; Lauren, Christine T; Lifton, Richard P; Bilguvar, Kaya; Paller, Amy S; Choate, Keith A (J Invest Dermatol, 2015)
Genetic investigation of inherited skin disorders has informed the understanding of skin self-renewal, differentiation, and barrier function. Erythrokeratodermia variabilis et progressiva (EKVP) is a rare, inherited skin disease that is characterized by transient figurate patches of erythema, localized or generalized scaling, and frequent palmoplantar keratoderma. By using exome sequencing, we show that de novo missense mutations in GJA1 (gap junction protein alpha 1) cause EKVP. The severe, progressive skin disease in EKVP subjects with GJA1 mutations is distinct from limited cutaneous findings rarely found in the systemic disorder oculodentodigital dysplasia, also caused by dominant GJA1 mutations. GJA1 encodes connexin 43 (Cx43), the most widely expressed gap junction protein. We show that the GJA1 mutations in EKVP subjects lead to disruption of Cx43 membrane localization and aggregation within the Golgi. These findings reveal a critical role for Cx43 in epidermal homeostasis, and they provide evidence of organ-specific pathobiology resulting from different mutations within GJA1.
Keywords: Amino Acid Sequence; Cell Membrane; Child; Child, Preschool; Connexin 43; Connexins; Craniofacial Abnormalities; Disease Progression; Erythrokeratodermia Variabilis; Exome; Eye Abnormalities; Female; Foot Deformities, Congenital; Golgi Apparatus; HeLa Cells; Humans; Immunohistochemistry; Male; Molecular Sequence Data; Mutagenesis, Site-Directed; Mutation; Phenotype; Sequence Analysis, DNA; Sequence Homology, Amino Acid; Skin Diseases; Syndactyly; Tooth Abnormalities

Early-onset lymphoproliferation and autoimmunity caused by germline STAT3 gain-of-function mutations. - Milner, Joshua D; Vogel, Tiphanie P; Forbes, Lisa; Ma, Chi A; Stray-Pedersen, Asbjørg; Niemela, Julie E; Lyons, Jonathan J; Engelhardt, Karin R; Zhang, Yu; Topcagic, Nermina; Roberson, Elisha D O; Matthews, Helen; et al. (Blood, 2015)
Germline loss-of-function mutations in the transcription factor signal transducer and activator of transcription 3 (STAT3) cause immunodeficiency, whereas somatic gain-of-function mutations in STAT3 are associated with large granular lymphocytic leukemic, myelodysplastic syndrome, and aplastic anemia. Recently, germline mutations in STAT3 have also been associated with autoimmune disease. Here, we report on 13 individuals from 10 families with lymphoproliferation and early-onset solid-organ autoimmunity associated with 9 different germline heterozygous mutations in STAT3. Patients exhibited a variety of clinical features, with most having lymphadenopathy, autoimmune cytopenias, multiorgan autoimmunity (lung, gastrointestinal, hepatic, and/or endocrine dysfunction), infections, and short stature. Functional analyses demonstrate that these mutations confer a gain-of-function in STAT3 leading to secondary defects in STAT5 and STAT1 phosphorylation and the regulatory T-cell compartment. Treatment targeting a cytokine pathway that signals through STAT3 led to clinical improvement in 1 patient, suggesting a potential therapeutic option for such patients. These results suggest that there is a broad range of autoimmunity caused by germline STAT3 gain-of-function mutations, and that hematologic autoimmunity is a major component of this newly described disorder. Some patients for this study were enrolled in a trial registered at www.clinicaltrials.gov as #NCT00001350.
Keywords: Adolescent; Adult; Autoimmune Diseases; Child; Child, Preschool; Female; Genetic Diseases, Inborn; Humans; Infant; Lymphoproliferative Disorders; Male; Mutation; Phosphorylation; STAT1 Transcription Factor; STAT3 Transcription Factor; STAT5 Transcription Factor; T-Lymphocytes, Regulatory

Exome analysis of a family with Wolff-Parkinson-White syndrome identifies a novel disease locus. - Bowles, Neil E; Jou, Chuanchau J; Arrington, Cammon B; Kennedy, Brett J; Earl, Aubree; Matsunami, Norisada; Meyers, Lindsay L; Etheridge, Susan P; Saarel, Elizabeth V; Bleyl, Steven B; Yost, H Joseph; Yandell, Mark; et al. (Am J Med Genet A, 2015)
Wolff-Parkinson-White (WPW) syndrome is a common cause of supraventricular tachycardia that carries a risk of sudden cardiac death. To date, mutations in only one gene, PRKAG2, which encodes the 5'-AMP-activated protein kinase subunit γ-2, have been identified as causative for WPW. DNA samples from five members of a family with WPW were analyzed by exome sequencing. We applied recently designed prioritization strategies (VAAST/pedigree VAAST) coupled with an ontology-based algorithm (Phevor) that reduced the number of potentially damaging variants to 10: a variant in KCNE2 previously associated with Long QT syndrome was also identified. Of these 11 variants, only MYH6 p.E1885K segregated with the WPW phenotype in all affected individuals and was absent in 10 unaffected family members. This variant was predicted to be damaging by in silico methods and is not present in the 1,000 genome and NHLBI exome sequencing project databases. Screening of a replication cohort of 47 unrelated WPW patients did not identify other likely causative variants in PRKAG2 or MYH6. MYH6 variants have been identified in patients with atrial septal defects, cardiomyopathies, and sick sinus syndrome. Our data highlight the pleiotropic nature of phenotypes associated with defects in this gene.
Keywords: Adult; AMP-Activated Protein Kinases; Cardiac Myosins; Exome; Female; Genetic Loci; Humans; Male; Myosin Heavy Chains; Pedigree; Potassium Channels, Voltage-Gated; Wolff-Parkinson-White Syndrome

Exome Sequence Analysis Suggests that Genetic Burden Contributes to Phenotypic Variability and Complex Neuropathy. - Gonzaga-Jauregui, Claudia; Harel, Tamar; Gambin, Tomasz; Kousi, Maria; Griffin, Laurie B; Francescatto, Ludmila; Ozes, Burcak; Karaca, Ender; Jhangiani, Shalini N; Bainbridge, Matthew N; Lawson, Kim S; Pehlivan, Davut; et al. (Cell Rep, 2015)
Charcot-Marie-Tooth (CMT) disease is a clinically and genetically heterogeneous distal symmetric polyneuropathy. Whole-exome sequencing (WES) of 40 individuals from 37 unrelated families with CMT-like peripheral neuropathy refractory to molecular diagnosis identified apparent causal mutations in ∼ 45% (17/37) of families. Three candidate disease genes are proposed, supported by a combination of genetic and in vivo studies. Aggregate analysis of mutation data revealed a significantly increased number of rare variants across 58 neuropathy-associated genes in subjects versus controls, confirmed in a second ethnically discrete neuropathy cohort, suggesting that mutation burden potentially contributes to phenotypic variability. Neuropathy genes shown to have highly penetrant Mendelizing variants (HPMVs) and implicated by burden in families were shown to interact genetically in a zebrafish assay exacerbating the phenotype established by the suppression of single genes. Our findings suggest that the combinatorial effect of rare variants contributes to disease burden and variable expressivity.
Keywords: Animals; Charcot-Marie-Tooth Disease; Exome; Female; Genetic Load; Genetic Variation; HSP40 Heat-Shock Proteins; Humans; Male; Mutation; Myelin P2 Protein; Pedigree; Penetrance; Peripheral Nervous System Diseases; Phenotype; Serine C-Palmitoyltransferase; Suppression, Genetic; Zebrafish

Exome sequencing identifies a homozygous C5orf42 variant in a Turkish kindred with oral-facial-digital syndrome type VI. - Bayram, Yavuz; Aydin, Hatip; Gambin, Tomasz; Akdemir, Zeynep Coban; Atik, Mehmed M; Karaca, Ender; Karaman, Ali; Pehlivan, Davut; Jhangiani, Shalini N; Gibbs, Richard A; Lupski, James R (Am J Med Genet A, 2015)
Oral-facial-digital syndrome type VI (OFDVI) is a rare ciliopathy in the spectrum of Joubert syndrome (JS) and distinguished from other oral-facial-digital syndromes by metacarpal abnormalities with central polydactyly and by a molar tooth sign on cranial MRI. Additional characteristic features include short stature, micrognathia, posteriorly rotated low-set ears, hypertelorism, epicanthal folds, broad nasal tip, tongue hamartoma, upper lip notch, intraoral frenula, cleft lip/palate, and renal anomalies. Recently, novel mutations in C5orf42 were identified in 9 out of 11 OFDVI families. In a subsequent study C5orf42 was found to be mutated in only 2 out of 17 OFDVI probands while 28 patients with a pure JS phenotype also had pathogenic mutations of C5orf42. We report on two affected cousins diagnosed with OFDVI who were born from first degree cousin marriages. Whole exome sequencing (WES) identified a homozygous predicted damaging missense mutation (c.4034A > G; p.Gln1345Arg) in the C5orf42 gene. Our data contribute to the evidence that C5orf42 is one of the causative genes for OFDVI.
Keywords: Abnormalities, Multiple; Cerebellar Diseases; Cerebellum; Child; Cleft Palate; Exome; Eye Abnormalities; Female; Genetic Predisposition to Disease; Hamartoma; Homozygote; Humans; Kidney Diseases, Cystic; Magnetic Resonance Imaging; Male; Membrane Proteins; Middle Aged; Mutation; Orofaciodigital Syndromes; Phenotype; Retina; Turkey

Exome sequencing links mutations in PARN and RTEL1 with familial pulmonary fibrosis and telomere shortening. - Stuart, Bridget D; Choi, Jungmin; Zaidi, Samir; Xing, Chao; Holohan, Brody; Chen, Rui; Choi, Mihwa; Dharwadkar, Pooja; Torres, Fernando; Girod, Carlos E; Weissler, Jonathan; Fitzgerald, John; et al. (Nat Genet, 2015)
Idiopathic pulmonary fibrosis (IPF) is an age-related disease featuring progressive lung scarring. To elucidate the molecular basis of IPF, we performed exome sequencing of familial kindreds with pulmonary fibrosis. Gene burden analysis comparing 78 European cases and 2,816 controls implicated PARN, an exoribonuclease with no previous connection to telomere biology or disease, with five new heterozygous damaging mutations in unrelated cases and none in controls (P = 1.3 × 10(-8)); mutations were shared by all affected relatives (odds in favor of linkage = 4,096:1). RTEL1, an established locus for dyskeratosis congenita, harbored significantly more new damaging and missense variants at conserved residues in cases than in controls (P = 1.6 × 10(-6)). PARN and RTEL1 mutation carriers had shortened leukocyte telomere lengths, and we observed epigenetic inheritance of short telomeres in family members. Together, these genes explain ~7% of familial pulmonary fibrosis and strengthen the link between lung fibrosis and telomere dysfunction.
Keywords: Adult; Aged; Aged, 80 and over; Amino Acid Sequence; Case-Control Studies; Cells, Cultured; DNA Helicases; DNA Mutational Analysis; Exome; Exoribonucleases; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Idiopathic Pulmonary Fibrosis; Leukocytes; Lod Score; Male; Middle Aged; Molecular Sequence Data; Pedigree; Telomere; Telomere Shortening

Exome sequencing reveals homozygous TRIM2 mutation in a patient with early onset CMT and bilateral vocal cord paralysis. - Pehlivan, Davut; Coban Akdemir, Zeynep; Karaca, Ender; Bayram, Yavuz; Jhangiani, Shalini; Yildiz, Edibe Pembegul; Muzny, Donna; Uluc, Kayihan; Gibbs, Richard A; Elcioglu, Nursel; Lupski, James R; Harel, Tamar (Hum Genet, 2015)
Charcot-Marie-Tooth disease is a heterogeneous group of inherited distal symmetric polyneuropathies associated with mutations in genes encoding components essential for normal functioning of the Schwann cell and axon. TRIM2, encoding a ligase that ubiquitinates the neurofilament light chain, was recently associated with early-onset neuropathy in a single patient. We report a TRIM2 homozygous missense mutation (c.2000A>C; p.D667A) in a patient with peripheral neuropathy and bilateral vocal cord paralysis, allowing for further delineation of the associated phenotypic spectrum.
Keywords: Adult; Charcot-Marie-Tooth Disease; Exome; Female; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Infant, Newborn; Male; Mutation, Missense; Nuclear Proteins; Vocal Cord Paralysis

Exome sequencing reveals pathogenic mutations in 91 strains of mice with Mendelian disorders. - Fairfield, Heather; Srivastava, Anuj; Ananda, Guruprasad; Liu, Rangjiao; Kircher, Martin; Lakshminarayana, Anuradha; Harris, Belinda S; Karst, Son Yong; Dionne, Louise A; Kane, Coleen C; Curtain, Michelle; Berry, Melissa L; et al. (Genome Res, 2015)
Spontaneously arising mouse mutations have served as the foundation for understanding gene function for more than 100 years. We have used exome sequencing in an effort to identify the causative mutations for 172 distinct, spontaneously arising mouse models of Mendelian disorders, including a broad range of clinically relevant phenotypes. To analyze the resulting data, we developed an analytics pipeline that is optimized for mouse exome data and a variation database that allows for reproducible, user-defined data mining as well as nomination of mutation candidates through knowledge-based integration of sample and variant data. Using these new tools, putative pathogenic mutations were identified for 91 (53%) of the strains in our study. Despite the increased power offered by potentially unlimited pedigrees and controlled breeding, about half of our exome cases remained unsolved. Using a combination of manual analyses of exome alignments and whole-genome sequencing, we provide evidence that a large fraction of unsolved exome cases have underlying structural mutations. This result directly informs efforts to investigate the similar proportion of apparently Mendelian human phenotypes that are recalcitrant to exome sequencing.
Keywords: Animals; Exome; Female; Genetic Diseases, Inborn; Genetic Linkage; Genetic Variation; Genome-Wide Association Study; Genomics; High-Throughput Nucleotide Sequencing; Male; Mice; Mutation; Phenotype; Reproducibility of Results

Expanding the Molecular and Clinical Phenotype of SSR4-CDG. - Ng, Bobby G; Raymond, Kimiyo; Kircher, Martin; Buckingham, Kati J; Wood, Tim; Shendure, Jay; Nickerson, Deborah A; Bamshad, Michael J; Wong, Jonathan T S; Monteiro, Fabiola Paoli; Graham, Brett H; Jackson, Sheryl; et al. (Hum Mutat, 2015)
Congenital disorders of glycosylation (CDG) are a group of mostly autosomal recessive disorders primarily characterized by neurological abnormalities. Recently, we described a single CDG patient with a de novo mutation in the X-linked gene, Signal Sequence Receptor 4 (SSR4). We performed whole-exome sequencing to identify causal variants in several affected individuals who had either an undifferentiated neurological disorder or unsolved CDG of unknown etiology based on abnormal transferrin glycosylation. We now report eight affected males with either de novo (4) or inherited (4) loss of function mutations in SSR4. Western blot analysis revealed that the mutations caused a complete loss of SSR4 protein. In nearly all cases, the abnormal glycosylation of serum transferrin was only slightly above the accepted normal cutoff range.
Keywords: Calcium-Binding Proteins; Congenital Disorders of Glycosylation; DNA Mutational Analysis; Exome; Gene Order; Genes, X-Linked; Genetic Loci; Humans; Male; Membrane Glycoproteins; Mutation; Phenotype; Receptors, Cytoplasmic and Nuclear; Receptors, Peptide

FBN1 contributing to familial congenital diaphragmatic hernia. - Beck, Tyler F; Campeau, Philippe M; Jhangiani, Shalini N; Gambin, Tomasz; Li, Alexander H; Abo-Zahrah, Reem; Jordan, Valerie K; Hernandez-Garcia, Andres; Wiszniewski, Wojciech K; Muzny, Donna; Gibbs, Richard A; Boerwinkle, Eric; et al. (Am J Med Genet A, 2015)
Congenital diaphragmatic hernia (CDH) is a relatively common, life--threatening birth defect. We present a family with recurrent CDH--paraesophageal and central--for whom exome sequencing (ES) revealed a frameshift mutation (c.4969_4970insA, p.Ile1657Asnfs*30) in the fibrillin 1 gene (FBN1) that causes Marfan syndrome. A diagnosis of Marfan syndrome had not been considered previously in this family. However, a review of the literature demonstrated that FBN1 mutations have an unusual pattern of CDH in which paraesophageal hernias are particularly common. Subsequent clinical evaluations revealed evidence for ectopia lentis in affected family members supporting a clinical diagnosis of Marfan syndrome. Since only two other cases of familial CDH have been described in association with FBN1 mutations, we investigated an oligogenic hypothesis by examining ES data for deleterious sequence changes in other CDH-related genes. This search revealed putatively deleterious sequence changes in four other genes that have been shown to cause diaphragm defects in humans and/or mice--FREM1, DES, PAX3 and MET. It is unclear whether these changes, alone or in aggregate, are contributing to the development of CDH in this family. However, their individual contribution is likely to be small compared to that of the frameshift mutation in FBN1. We conclude that ES can be used to identify both major and minor genetic factors that may contribute to CDH. These results also suggest that ES should be considered in the diagnostic evaluation of individuals and families with CDH, particularly when other diagnostic modalities have failed to reveal a molecular etiology.
Keywords: Adult; Child, Preschool; DNA Mutational Analysis; Exome; Female; Fibrillin-1; Fibrillins; Frameshift Mutation; Genetic Association Studies; Hernias, Diaphragmatic, Congenital; Humans; Male; Marfan Syndrome; Microfilament Proteins; Pedigree

Frequency and phenotypic spectrum of germline mutations in POLE and seven other polymerase genes in 266 patients with colorectal adenomas and carcinomas. - Spier, Isabel; Holzapfel, Stefanie; Altmüller, Janine; Zhao, Bixiao; Horpaopan, Sukanya; Vogt, Stefanie; Chen, Sophia; Morak, Monika; Raeder, Susanne; Kayser, Katrin; Stienen, Dietlinde; Adam, Ronja; et al. (Int J Cancer, 2015)
In a number of families with colorectal adenomatous polyposis or suspected Lynch syndrome/HNPCC, no germline alteration in the APC, MUTYH, or mismatch repair (MMR) genes are found. Missense mutations in the polymerase genes POLE and POLD1 have recently been identified as rare cause of multiple colorectal adenomas and carcinomas, a condition termed polymerase proofreading-associated polyposis (PPAP). The aim of the present study was to evaluate the clinical relevance and phenotypic spectrum of polymerase germline mutations. Therefore, targeted sequencing of the polymerase genes POLD1, POLD2, POLD3, POLD4, POLE, POLE2, POLE3 and POLE4 was performed in 266 unrelated patients with polyposis or fulfilled Amsterdam criteria. The POLE mutation c.1270C>G;p.Leu424Val was detected in four unrelated patients. The mutation was present in 1.5% (4/266) of all patients, 4% (3/77) of all familial cases and 7% (2/30) of familial polyposis cases. The colorectal phenotype in 14 affected individuals ranged from typical adenomatous polyposis to a HNPCC phenotype, with high intrafamilial variability. Multiple colorectal carcinomas and duodenal adenomas were common, and one case of duodenal carcinoma was reported. Additionally, various extraintestinal lesions were evident. Nine further putative pathogenic variants were identified. The most promising was c.1306C>T;p.Pro436Ser in POLE. In conclusion, a PPAP was identified in a substantial number of polyposis and familial colorectal cancer patients. Screening for polymerase proofreading mutations should therefore be considered, particularly in unexplained familial cases. The present study broadens the phenotypic spectrum of PPAP to duodenal adenomas and carcinomas, and identified novel, potentially pathogenic variants in four polymerase genes.
Keywords: Adenoma; Adolescent; Adult; Aged; Aged, 80 and over; Child; Colorectal Neoplasms; DNA Polymerase II; DNA-Directed DNA Polymerase; Family Health; Female; Gene Frequency; Genetic Predisposition to Disease; Germ-Line Mutation; Humans; Isoenzymes; Male; Middle Aged; Mutation, Missense; Pedigree; Phenotype; Phospholipase D; Poly-ADP-Ribose Binding Proteins; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Young Adult

Frequent somatic reversion of KRT1 mutations in ichthyosis with confetti. - Choate, Keith A; Lu, Yin; Zhou, Jing; Elias, Peter M; Zaidi, Samir; Paller, Amy S; Farhi, Anita; Nelson-Williams, Carol; Crumrine, Debra; Milstone, Leonard M; Lifton, Richard P (J Clin Invest, 2015)
Widespread reversion of genetic disease is rare; however, such events are particularly evident in some skin disorders in which normal clones develop on a background of affected skin. We previously demonstrated that mutations in keratin 10 (KRT10) cause ichthyosis with confetti (IWC), a severe dominant disorder that is characterized by progressive development of hundreds of normal skin spots via revertant mosaicism. Here, we report on a clinical and histological IWC subtype in which affected subjects have red, scaly skin at birth, experience worsening palmoplantar keratoderma in childhood, and develop hundreds of normal skin spots, beginning at around 20 years of age, that increase in size and number over time. We identified a causal de novo mutation in keratin 1 (KRT1). Similar to IWC-causing KRT10 mutations, this mutation in KRT1 resulted in a C-terminal frameshift, replacing 22 C-terminal amino acids with an alternate 30-residue peptide. Mutant KRT1 caused partial collapse of the cytoplasmic intermediate filament network and mislocalized to the nucleus. As with KRT10 mutations causing IWC, reversion of KRT1 mutations occurred via mitotic recombination. Because reversion is not observed with other disease-causing keratin mutations, the results of this study implicate KRT1 and KRT10 C-terminal frameshift mutations in the high frequency of revertant mosaicism in IWC.
Keywords: Adult; Age of Onset; Amino Acid Sequence; Cell Line, Tumor; Cell Nucleus; Child; Child, Preschool; Chromosomes, Human, Pair 12; Cytoskeleton; Frameshift Mutation; Humans; Ichthyosis; Intermediate Filaments; Keratin-1; Keratinocytes; Loss of Heterozygosity; Male; Molecular Sequence Data; Mosaicism; Phenotype; Polymorphism, Single Nucleotide; Protein Transport; Transfection

GeneMatcher aids in the identification of a new malformation syndrome with intellectual disability, unique facial dysmorphisms, and skeletal and connective tissue abnormalities caused by de novo variants in HNRNPK. - Au, P Y Billie; You, Jing; Caluseriu, Oana; Schwartzentruber, Jeremy; Majewski, Jacek; Bernier, Francois P; Ferguson, Marcia; Valle, David; Parboosingh, Jillian S; Sobreira, Nara; Innes, A Micheil; Kline, Antonie D (Hum Mutat, 2015)
We report a new syndrome due to loss-of-function variants in the heterogeneous nuclear ribonucleoprotein K gene (HNRNPK). We describe two probands: one with a de novo frameshift (NM_002140.3: c.953+1dup), and the other with a de novo splice donor site variant (NM_002140.3: c.257G>A). Both probands have intellectual disability, a shared unique craniofacial phenotype, and connective tissue and skeletal abnormalities. The identification of this syndrome was made possible by a new online tool, GeneMatcher, which facilitates connections between clinicians and researchers based on shared interest in candidate genes. This report demonstrates that new Web-based approaches can be effective in helping investigators solve exome sequencing projects, and also highlights the newer paradigm of "reverse phenotyping," where characterization of syndromic features follows the identification of genetic variants.
Keywords: Abnormalities, Multiple; Adolescent; Child; Craniofacial Abnormalities; Databases, Genetic; Genetic Predisposition to Disease; Heterogeneous-Nuclear Ribonucleoprotein K; Humans; Information Dissemination; Intellectual Disability; Male; Muscular Atrophy; Phenotype; Polymorphism, Single Nucleotide; Ribonucleoproteins; Software; Web Browser

Genes that Affect Brain Structure and Function Identified by Rare Variant Analyses of Mendelian Neurologic Disease. - Karaca, Ender; Harel, Tamar; Pehlivan, Davut; Jhangiani, Shalini N; Gambin, Tomasz; Coban Akdemir, Zeynep; Gonzaga-Jauregui, Claudia; Erdin, Serkan; Bayram, Yavuz; Campbell, Ian M; Hunter, Jill V; Atik, Mehmed M; et al. (Neuron, 2015)
Development of the human nervous system involves complex interactions among fundamental cellular processes and requires a multitude of genes, many of which remain to be associated with human disease. We applied whole exome sequencing to 128 mostly consanguineous families with neurogenetic disorders that often included brain malformations. Rare variant analyses for both single nucleotide variant (SNV) and copy number variant (CNV) alleles allowed for identification of 45 novel variants in 43 known disease genes, 41 candidate genes, and CNVs in 10 families, with an overall potential molecular cause identified in >85% of families studied. Among the candidate genes identified, we found PRUNE, VARS, and DHX37 in multiple families and homozygous loss-of-function variants in AGBL2, SLC18A2, SMARCA1, UBQLN1, and CPLX1. Neuroimaging and in silico analysis of functional and expression proximity between candidate and known disease genes allowed for further understanding of genetic networks underlying specific types of brain malformations.
Keywords: Brain; Cohort Studies; Databases, Genetic; Female; Gene Regulatory Networks; Genetic Association Studies; Genetic Variation; Humans; Male; Mendelian Randomization Analysis; Nervous System Diseases; Pedigree

Genetic linkage analysis in the age of whole-genome sequencing. - Ott, Jurg; Wang, Jing; Leal, Suzanne M (Nat Rev Genet, 2015)
For many years, linkage analysis was the primary tool used for the genetic mapping of Mendelian and complex traits with familial aggregation. Linkage analysis was largely supplanted by the wide adoption of genome-wide association studies (GWASs). However, with the recent increased use of whole-genome sequencing (WGS), linkage analysis is again emerging as an important and powerful analysis method for the identification of genes involved in disease aetiology, often in conjunction with WGS filtering approaches. Here, we review the principles of linkage analysis and provide practical guidelines for carrying out linkage studies using WGS data.
Keywords: Algorithms; Female; Genetic Linkage; Genome, Human; Genome-Wide Association Study; Genotyping Techniques; Humans; Lod Score; Male; Pedigree; Penetrance; Phenotype; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Software

Germline PRKACA amplification causes variable phenotypes that may depend on the extent of the genomic defect: molecular mechanisms and clinical presentations. - Lodish, Maya B; Yuan, Bo; Levy, Isaac; Braunstein, Glenn D; Lyssikatos, Charalampos; Salpea, Paraskevi; Szarek, Eva; Karageorgiadis, Alexander S; Belyavskaya, Elena; Raygada, Margarita; Faucz, Fabio Rueda; Izzat, Louise; et al. (Eur J Endocrinol, 2015)
OBJECTIVE: We have recently reported five patients with bilateral adrenocortical hyperplasia (BAH) and Cushing's syndrome (CS) caused by constitutive activation of the catalytic subunit of protein kinase A (PRKACA). By doing new in-depth analysis of their cytogenetic abnormality, we attempted a better genotype-phenotype correlation of their PRKACA amplification. DESIGN: This study is a case series. METHODS: Molecular cytogenetic, genomic, clinical, and histopathological analyses were performed in five patients with CS. RESULTS: Reinvestigation of the defects of previously described patients by state-of-the-art molecular cytogenetics showed complex genomic rearrangements in the chromosome 19p13.2p13.12 locus, resulting in copy number gains encompassing the entire PRKACA gene; three patients (one sporadic case and two related cases) were observed with gains consistent with duplications, while two sporadic patients were observed with gains consistent with triplications. Although all five patients presented with ACTH-independent CS, the three sporadic patients had micronodular BAH and underwent bilateral adrenalectomy in early childhood, whereas the two related patients, a mother and a son, presented with macronodular BAH as adults. In at least one patient, PRKACA triplication was associated with a more severe phenotype. CONCLUSIONS: Constitutional chromosomal PRKACA gene amplification is a recently identified genetic defect associated with CS, a trait that may be inherited in an autosomal dominant manner or occur de novo. Genomic rearrangements can be complex and can result in different copy number states of dosage-sensitive genes, e.g., duplication and triplication. PRKACA amplification can lead to variable phenotypes clinically and pathologically, both micro- and macro-nodular BAH, the latter of which we speculate may depend on the extent of amplification.
Keywords: Adrenal Glands; Adrenalectomy; Adult; Child; Child, Preschool; Cushing Syndrome; Cyclic AMP-Dependent Protein Kinase Catalytic Subunits; DNA Copy Number Variations; Female; Gene Amplification; Humans; Hyperplasia; Male; Phenotype; Young Adult

Global transcriptional disturbances underlie Cornelia de Lange syndrome and related phenotypes. - Yuan, Bo; Pehlivan, Davut; Karaca, Ender; Patel, Nisha; Charng, Wu-Lin; Gambin, Tomasz; Gonzaga-Jauregui, Claudia; Sutton, V Reid; Yesil, Gözde; Bozdogan, Sevcan Tug; Tos, Tulay; Koparir, Asuman; et al. (J Clin Invest, 2015)
Cornelia de Lange syndrome (CdLS) is a genetically heterogeneous disorder that presents with extensive phenotypic variability, including facial dysmorphism, developmental delay/intellectual disability (DD/ID), abnormal extremities, and hirsutism. About 65% of patients harbor mutations in genes that encode subunits or regulators of the cohesin complex, including NIPBL, SMC1A, SMC3, RAD21, and HDAC8. Wiedemann-Steiner syndrome (WDSTS), which shares CdLS phenotypic features, is caused by mutations in lysine-specific methyltransferase 2A (KMT2A). Here, we performed whole-exome sequencing (WES) of 2 male siblings clinically diagnosed with WDSTS; this revealed a hemizygous, missense mutation in SMC1A that was predicted to be deleterious. Extensive clinical evaluation and WES of 32 Turkish patients clinically diagnosed with CdLS revealed the presence of a de novo heterozygous nonsense KMT2A mutation in 1 patient without characteristic WDSTS features. We also identified de novo heterozygous mutations in SMC3 or SMC1A that affected RNA splicing in 2 independent patients with combined CdLS and WDSTS features. Furthermore, in families from 2 separate world populations segregating an autosomal-recessive disorder with CdLS-like features, we identified homozygous mutations in TAF6, which encodes a core transcriptional regulatory pathway component. Together, our data, along with recent transcriptome studies, suggest that CdLS and related phenotypes may be "transcriptomopathies" rather than cohesinopathies.
Keywords: Adolescent; Adult; Cell Cycle Proteins; Child; Child, Preschool; Chondroitin Sulfate Proteoglycans; Chromosomal Proteins, Non-Histone; Codon, Nonsense; De Lange Syndrome; Exome; Exonucleases; Gene Expression Profiling; Gene Expression Regulation; Genome-Wide Association Study; Heterozygote; Histone Deacetylases; Histone-Lysine N-Methyltransferase; Humans; Infant; Male; Myeloid-Lymphoid Leukemia Protein; Phenotype; Proteins; Repressor Proteins; Transcriptome

A homozygous missense variant in type I keratin KRT25 causes autosomal recessive woolly hair. - Ansar, Muhammad; Raza, Syed Irfan; Lee, Kwanghyuk; Shahi, Shamim; Acharya, Anushree; Dai, Hang; Smith, Joshua D; Shendure, Jay; Bamshad, Michael J; Nickerson, Deborah A; Santos-Cortez, Regie Lyn P; Ahmad, Wasim; et al. (J Med Genet, 2015)
BACKGROUND: Woolly hair (WH) is a hair abnormality that is primarily characterised by tightly curled hair with abnormal growth. METHODS: In two unrelated consanguineous Pakistani families with non-syndromic autosomal recessive (AR) WH, homozygosity mapping and linkage analysis identified a locus within 17q21.1-q22, which contains the type I keratin gene cluster. A DNA sample from an affected individual from each family underwent exome sequencing. RESULTS: A homozygous missense variant c.950T>C (p.(Leu317Pro)) within KRT25 segregated with ARWH in both families, and has a combined maximum two-point LOD score of 7.9 at ϴ=0. The KRT25 variant is predicted to result in disruption of the second α-helical rod domain and the entire protein structure, thus possibly interfering with heterodimerisation of K25 with type II keratins within the inner root sheath (IRS) of the hair follicle and the medulla of the hair shaft. CONCLUSIONS: Our findings implicate a novel gene involved in human hair abnormality, and are consistent with the curled, fragile hair found in mice with Krt25 mutations, and further support the role of IRS-specific type I keratins in hair follicle development and maintenance of hair texture.
Keywords: Child; Child, Preschool; Consanguinity; Hair; Hair Diseases; Humans; Keratins, Type I; Male; Mutation, Missense; Pakistan; Pedigree; Sequence Analysis, DNA

Identification and functional characterization of natural human melanocortin 1 receptor mutant alleles in Pakistani population. - Shahzad, Mohsin; Sires Campos, Julia; Tariq, Nabeela; Herraiz Serrano, Cecilia; Yousaf, Rizwan; Jiménez-Cervantes, Celia; Yousaf, Sairah; Waryah, Yar M; Dad, Haseeb A; Blue, Elizabeth M; Sobreira, Nara; López-Giráldez, Francesc; et al. (Pigment Cell Melanoma Res, 2015)
Melanocortin 1 receptor (MC1R), a Gs protein-coupled receptor of the melanocyte's plasma membrane, is a major determinant of skin pigmentation and phototype. Upon activation by α-melanocyte stimulating hormone, MC1R triggers the cAMP cascade to stimulate eumelanogenesis. We used whole-exome sequencing to identify causative alleles in Pakistani families with skin and hair hypopigmentation. Six MC1R mutations segregated with the phenotype in seven families, including a p.Val174del in-frame deletion and a p.Tyr298* nonsense mutation, that were analyzed for function in heterologous HEK293 cells. p.Tyr298* MC1R showed no agonist-induced signaling to the cAMP or ERK pathways, nor detectable agonist binding. Conversely, signaling was comparable for p.Val174del and wild-type in HEK cells overexpressing the proteins, but binding analysis suggested impaired cell surface expression. Flow cytometry and confocal imaging studies revealed reduced plasma membrane expression of p.Val174del and p.Tyr298*. Therefore, p.Tyr298* was a total loss-of-function (LOF) allele, while p.Val174del displayed a partial LOF attribute.
Keywords: Alleles; Family; Female; Humans; Hypopigmentation; Male; Mutation; Pakistan; Pedigree; Phenotype; Receptor, Melanocortin, Type 1

Inactivating mutations in MFSD2A, required for omega-3 fatty acid transport in brain, cause a lethal microcephaly syndrome. - Guemez-Gamboa, Alicia; Nguyen, Long N; Yang, Hongbo; Zaki, Maha S; Kara, Majdi; Ben-Omran, Tawfeg; Akizu, Naiara; Rosti, Rasim Ozgur; Rosti, Basak; Scott, Eric; Schroth, Jana; Copeland, Brett; et al. (Nat Genet, 2015)
Docosahexanoic acid (DHA) is the most abundant omega-3 fatty acid in brain, and, although it is considered essential, deficiency has not been linked to disease. Despite the large mass of DHA in phospholipids, the brain does not synthesize it. DHA is imported across the blood-brain barrier (BBB) through the major facilitator superfamily domain-containing 2a (MFSD2A) protein. MFSD2A transports DHA as well as other fatty acids in the form of lysophosphatidylcholine (LPC). We identify two families displaying MFSD2A mutations in conserved residues. Affected individuals exhibited a lethal microcephaly syndrome linked to inadequate uptake of LPC lipids. The MFSD2A mutations impaired transport activity in a cell-based assay. Moreover, when expressed in mfsd2aa-morphant zebrafish, mutants failed to rescue microcephaly, BBB breakdown and lethality. Our results establish a link between transport of DHA and LPCs by MFSD2A and human brain growth and function, presenting the first evidence of monogenic disease related to transport of DHA in humans.
Keywords: Adolescent; Animals; Biological Transport; Blood-Brain Barrier; Brain; Case-Control Studies; Child; Child, Preschool; Consanguinity; Fatty Acids, Omega-3; Female; Genes, Lethal; Genetic Association Studies; HEK293 Cells; Humans; Infant; Male; Mice, Knockout; Microcephaly; Mutation, Missense; Syndrome; Tumor Suppressor Proteins; Zebrafish

Mutation of ATF6 causes autosomal recessive achromatopsia. - Ansar, Muhammad; Santos-Cortez, Regie Lyn P; Saqib, Muhammad Arif Nadeem; Zulfiqar, Fareeha; Lee, Kwanghyuk; Ashraf, Naeem Mahmood; Ullah, Ehsan; Wang, Xin; Sajid, Sundus; Khan, Falak Sher; Amin-ud-Din, Muhammad; Smith, Joshua D; et al. (Hum Genet, 2015)
Achromatopsia (ACHM) is an early-onset retinal dystrophy characterized by photophobia, nystagmus, color blindness and severely reduced visual acuity. Currently mutations in five genes CNGA3, CNGB3, GNAT2, PDE6C and PDE6H have been implicated in ACHM. We performed homozygosity mapping and linkage analysis in a consanguineous Pakistani ACHM family and mapped the locus to a 15.12-Mb region on chromosome 1q23.1-q24.3 with a maximum LOD score of 3.6. A DNA sample from an affected family member underwent exome sequencing. Within the ATF6 gene, a single-base insertion variant c.355_356dupG (p.Glu119Glyfs*8) was identified, which completely segregates with the ACHM phenotype within the family. The frameshift variant was absent in public variant databases, in 130 exomes from unrelated Pakistani individuals, and in 235 ethnically matched controls. The variant is predicted to result in a truncated protein that lacks the DNA binding and transmembrane domains and therefore affects the function of ATF6 as a transcription factor that initiates the unfolded protein response during endoplasmic reticulum (ER) stress. Immunolabeling with anti-ATF6 antibodies showed localization throughout the mouse neuronal retina, including retinal pigment epithelium, photoreceptor cells, inner nuclear layer, inner and outer plexiform layers, with a more prominent signal in retinal ganglion cells. In contrast to cytoplasmic expression of wild-type protein, in heterologous cells ATF6 protein with the p.Glu119Glyfs*8 variant is mainly confined to the nucleus. Our results imply that response to ER stress as mediated by the ATF6 pathway is essential for color vision in humans.
Keywords: Activating Transcription Factor 6; Adolescent; Animals; Asian Continental Ancestry Group; Color Vision Defects; Consanguinity; DNA Mutational Analysis; Exome; Female; Frameshift Mutation; Genotyping Techniques; Homozygote; Humans; Limit of Detection; Male; Mice; Mice, Inbred C57BL; Pakistan; Pedigree; Phenotype; Retina; Signal Transduction

Mutations in COL27A1 cause Steel syndrome and suggest a founder mutation effect in the Puerto Rican population. - Gonzaga-Jauregui, Claudia; Gamble, Candace N; Yuan, Bo; Penney, Samantha; Jhangiani, Shalini; Muzny, Donna M; Gibbs, Richard A; Lupski, James R; Hecht, Jacqueline T (Eur J Hum Genet, 2015)
Osteochondrodysplasias represent a large group of developmental structural disorders that can be caused by mutations in a variety of genes responsible for chondrocyte development, differentiation, mineralization and early ossification. The application of whole-exome sequencing to disorders apparently segregating as Mendelian traits has proven to be an effective approach to disease gene identification for conditions with unknown molecular etiology. We identified a homozygous missense variant p.(Gly697Arg) in COL27A1, in a family with Steel syndrome and no consanguinity. Interestingly, the identified variant seems to have arisen as a founder mutation in the Puerto Rican population.
Keywords: Amino Acid Sequence; Child, Preschool; Comparative Genomic Hybridization; Exome; Female; Fibrillar Collagens; Follow-Up Studies; Founder Effect; Genotype; Hispanic Americans; Humans; Infant; Male; Molecular Sequence Data; Mutation; Osteochondrodysplasias; Pedigree; Polymorphism, Single Nucleotide; Prostaglandins F; Puerto Rico; Sequence Alignment

Mutations in DYNC2LI1 disrupt cilia function and cause short rib polydactyly syndrome. - Taylor, S Paige; Dantas, Tiago J; Duran, Ivan; Wu, Sulin; Lachman, Ralph S; Nelson, Stanley F; Cohn, Daniel H; Vallee, Richard B; Krakow, Deborah (Nat Commun, 2015)
The short rib polydactyly syndromes (SRPSs) are a heterogeneous group of autosomal recessive, perinatal lethal skeletal disorders characterized primarily by short, horizontal ribs, short limbs and polydactyly. Mutations in several genes affecting intraflagellar transport (IFT) cause SRPS but they do not account for all cases. Here we identify an additional SRPS gene and further unravel the functional basis for IFT. We perform whole-exome sequencing and identify mutations in a new disease-producing gene, cytoplasmic dynein-2 light intermediate chain 1, DYNC2LI1, segregating with disease in three families. Using primary fibroblasts, we show that DYNC2LI1 is essential for dynein-2 complex stability and that mutations in DYNC2LI1 result in variable length, including hyperelongated, cilia, Hedgehog pathway impairment and ciliary IFT accumulations. The findings in this study expand our understanding of SRPS locus heterogeneity and demonstrate the importance of DYNC2LI1 in dynein-2 complex stability, cilium function, Hedgehog regulation and skeletogenesis.
Keywords: Biological Transport; Cilia; Cytoplasmic Dyneins; Cytoskeleton; Female; Fibroblasts; Flagella; Hedgehog Proteins; Humans; Male; Mutation; Pedigree; Short Rib-Polydactyly Syndrome

Mutations in Either TUBB or MAPRE2 Cause Circumferential Skin Creases Kunze Type. - Isrie, Mala; Breuss, Martin; Tian, Guoling; Hansen, Andi Harley; Cristofoli, Francesca; Morandell, Jasmin; Kupchinsky, Zachari A; Sifrim, Alejandro; Rodriguez-Rodriguez, Celia Maria; Dapena, Elena Porta; Doonanco, Kurston; Leonard, Norma; et al. (Am J Hum Genet, 2015)
Circumferential skin creases Kunze type (CSC-KT) is a specific congenital entity with an unknown genetic cause. The disease phenotype comprises characteristic circumferential skin creases accompanied by intellectual disability, a cleft palate, short stature, and dysmorphic features. Here, we report that mutations in either MAPRE2 or TUBB underlie the genetic origin of this syndrome. MAPRE2 encodes a member of the microtubule end-binding family of proteins that bind to the guanosine triphosphate cap at growing microtubule plus ends, and TUBB encodes a β-tubulin isotype that is expressed abundantly in the developing brain. Functional analyses of the TUBB mutants show multiple defects in the chaperone-dependent tubulin heterodimer folding and assembly pathway that leads to a compromised yield of native heterodimers. The TUBB mutations also have an impact on microtubule dynamics. For MAPRE2, we show that the mutations result in enhanced MAPRE2 binding to microtubules, implying an increased dwell time at microtubule plus ends. Further, in vivo analysis of MAPRE2 mutations in a zebrafish model of craniofacial development shows that the variants most likely perturb the patterning of branchial arches, either through excessive activity (under a recessive paradigm) or through haploinsufficiency (dominant de novo paradigm). Taken together, our data add CSC-KT to the growing list of tubulinopathies and highlight how multiple inheritance paradigms can affect dosage-sensitive biological systems so as to result in the same clinical defect.
Keywords: Adolescent; Animals; Brain; Child; Cutis Laxa; Female; Gene Dosage; Gene Expression Regulation, Developmental; Genes, Recessive; Hamartoma; Haploinsufficiency; Humans; Infant; Inheritance Patterns; Male; Microtubule-Associated Proteins; Microtubules; Mutation; Protein Folding; Protein Multimerization; Skin; Skin Abnormalities; Tubulin; Young Adult; Zebrafish

Mutations in RAD21 disrupt regulation of APOB in patients with chronic intestinal pseudo-obstruction. - Bonora, Elena; Bianco, Francesca; Cordeddu, Lina; Bamshad, Michael; Francescatto, Ludmila; Dowless, Dustin; Stanghellini, Vincenzo; Cogliandro, Rosanna F; Lindberg, Greger; Mungan, Zeynel; Cefle, Kivanc; Ozcelik, Tayfun; et al. (Gastroenterology, 2015)
BACKGROUND & AIMS: Chronic intestinal pseudo-obstruction (CIPO) is characterized by severe intestinal dysmotility that mimics a mechanical subocclusion with no evidence of gut obstruction. We searched for genetic variants associated with CIPO to increase our understanding of its pathogenesis and to identify potential biomarkers. METHODS: We performed whole-exome sequencing of genomic DNA from patients with familial CIPO syndrome. Blood and lymphoblastoid cells were collected from patients and controls (individuals without CIPO); levels of messenger RNA (mRNA) and proteins were analyzed by quantitative reverse-transcription polymerase chain reaction, immunoblot, and mobility shift assays. Complementary DNAs were transfected into HEK293 cells. Expression of rad21 was suppressed in zebrafish embryos using a splice-blocking morpholino (rad21a). Gut tissues were collected and analyzed. RESULTS: We identified a homozygous mutation (p.622, encodes Ala>Thr) in RAD21 in patients from a consanguineous family with CIPO. Expression of RUNX1, a target of RAD21, was reduced in cells from patients with CIPO compared with controls. In zebrafish, suppression of rad21a reduced expression of runx1; this phenotype was corrected by injection of human RAD21 mRNA, but not with the mRNA from the mutated p.622 allele. rad21a Morpholino zebrafish had delayed intestinal transit and greatly reduced numbers of enteric neurons, similar to patients with CIPO. This defect was greater in zebrafish with suppressed expression of ret and rad21, indicating their interaction in the regulation of gut neurogenesis. The promoter region of APOB bound RAD21 but not RAD21 p.622 Ala>Thr; expression of wild-type RAD21 in HEK293 cells repressed expression of APOB, compared with control vector. The gut-specific isoform of APOB (APOB48) is overexpressed in sera from patients with CIPO who carry the RAD21 mutation. APOB48 also is overexpressed in sporadic CIPO in sera and gut biopsy specimens. CONCLUSIONS: Some patients with CIPO carry mutations in RAD21 that disrupt the ability of its product to regulate genes such as RUNX1 and APOB. Reduced expression of rad21 in zebrafish, and dysregulation of these target genes, disrupts intestinal transit and the development of enteric neurons.
Keywords: Adult; Animals; Apolipoprotein B-100; Case-Control Studies; Cell Cycle Proteins; Chronic Disease; Core Binding Factor Alpha 2 Subunit; Enteric Nervous System; Female; Gastrointestinal Motility; Gene Expression Profiling; Gene Knockdown Techniques; HEK293 Cells; Humans; Intestinal Pseudo-Obstruction; Male; Middle Aged; Nuclear Proteins; Phosphoproteins; RNA, Messenger; Sequence Analysis, DNA; Young Adult; Zebrafish; Zebrafish Proteins

Mutations in SPATA5 Are Associated with Microcephaly, Intellectual Disability, Seizures, and Hearing Loss. - Tanaka, Akemi J; Cho, Megan T; Millan, Francisca; Juusola, Jane; Retterer, Kyle; Joshi, Charuta; Niyazov, Dmitriy; Garnica, Adolfo; Gratz, Edward; Deardorff, Matthew; Wilkins, Alisha; Ortiz-Gonzalez, Xilma; et al. (Am J Hum Genet, 2015)
Using whole-exome sequencing, we have identified in ten families 14 individuals with microcephaly, developmental delay, intellectual disability, hypotonia, spasticity, seizures, sensorineural hearing loss, cortical visual impairment, and rare autosomal-recessive predicted pathogenic variants in spermatogenesis-associated protein 5 (SPATA5). SPATA5 encodes a ubiquitously expressed member of the ATPase associated with diverse activities (AAA) protein family and is involved in mitochondrial morphogenesis during early spermatogenesis. It might also play a role in post-translational modification during cell differentiation in neuronal development. Mutations in SPATA5 might affect brain development and function, resulting in microcephaly, developmental delay, and intellectual disability.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; ATPases Associated with Diverse Cellular Activities; Base Sequence; Exome; Female; Gene Frequency; Genes, Recessive; Hearing Loss; Homeodomain Proteins; Humans; Intellectual Disability; Male; Microcephaly; Molecular Sequence Data; Mutation; Seizures; Sequence Alignment; Sequence Analysis, DNA

New mutations in the RAB28 gene in 2 Spanish families with cone-rod dystrophy. - Riveiro-Álvarez, Rosa; Xie, Yajing Angela; López-Martínez, Miguel-Ángel; Gambin, Tomasz; Pérez-Carro, Raquel; Ávila-Fernández, Almudena; López-Molina, María-Isabel; Zernant, Jana; Jhangiani, Shalini; Muzny, Donna; Yuan, Bo; Boerwinkle, Eric; et al. (JAMA Ophthalmol, 2015)
IMPORTANCE: The families evaluated in this study represent the second report of cone-rod dystrophy (CRD) cases caused by mutations in RAB28, a recently discovered gene associated with CRD. OBJECTIVE: To determine the disease-causing gene in 2 families of Spanish descent presenting with CRD who do not have ABCA4 mutations. DESIGN, SETTING, AND PARTICIPANTS: Molecular genetics and observational case studies of 2 families, each with 1 affected proband with CRD and 3 or 5 unaffected family members. The affected individual from each family received a complete ophthalmic examination including assessment of refractive errors and best-corrected visual acuity, biomicroscopy, color fundus photography, electroretinography analysis, and visual-evoked potential analysis. After complete sequencing of the ABCA4 gene with negative results, the screening for disease-causing mutations was performed by whole-exome sequencing. Possible disease-associated variants were determined by filtering based on minor allele frequency, predicted pathogenicity, and segregation analysis in all family members. MAIN OUTCOMES AND MEASURES: The appearance of the macula was evaluated by clinical examination, fundus photography, and fundus autofluorescence imaging, and visual function was assessed by electroretinography. Disease-causing mutations were assessed by sequence analyses. RESULTS: Ophthalmologic findings included markedly reduced visual acuity, bull's eye maculopathy, foveal hyperpigmentation, peripapillary atrophy, dyschromatopsia, extinguished photopic responses, and reduced scotopic responses observed on electroretinography consistent with the CRD phenotype often associated with ABCA4 mutations. Although no ABCA4 mutations were detected in either patient, whole-exome sequencing analysis identified 2 new homozygous mutations in the recently described RAB28 gene, the c.172 + 1G>C splice site variant in IVS2 and the missense c.T651G:p.C217W substitution. Both variants were determined as deleterious by predictive programs and were segregated with the disease in both families. Sequencing of 107 additional patients of Spanish descent with CRD did not reveal other cases with RAB28 mutations. CONCLUSIONS AND RELEVANCE: Deleterious mutations in RAB28 result in a classic CRD phenotype and are an infrequent cause of CRD in the Spanish population.
Keywords: Adolescent; Adult; Child; Diagnosis, Differential; DNA Mutational Analysis; Female; Follow-Up Studies; Genetic Predisposition to Disease; Hispanic Americans; Humans; Male; Microscopy, Acoustic; Mutation; Pedigree; Phenotype; rab GTP-Binding Proteins; Retinitis Pigmentosa; Retrospective Studies; Young Adult

NGLY1 mutation causes neuromotor impairment, intellectual disability, and neuropathy. - Çağlayan, Ahmet Okay; Comu, Sinan; Baranoski, Jacob F; Parman, Yesim; Kaymakçalan, Hande; Akgümüş, Gözde Tuğce; Caglar, Caner; Dölen, Duygu; Erson-Omay, Emine Zeynep; Harmanci, Akdes Serin; Mishra-Gorur, Ketu; Freeze, Hudson H; et al. (Eur J Med Genet, 2015)
N-glycanase 1 (NGLY1) is a conserved enzyme that is responsible for the deglycosylation of misfolded N-glycosylated proteins in the cytoplasm prior to their proteasome-mediated degradation. Disruption of this degradation process has been associated with various neurologic diseases including amyotrophic lateral sclerosis and Parkinson's disease. Here, we describe two siblings with neuromotor impairment, apparent intellectual disability, corneal opacities, and neuropathy who were found to possess a novel homozygous frame-shift mutation due to a 4 base pair deletion in NGLY1 (c.1533_1536delTCAA, p.Asn511LysfsX51). We hypothesize that this mutation likely limits the capability of neuronal cells to respond to stress due to accumulation of misfolded proteins, thereby impairing their survival and resulting in progressive loss of neurological function.
Keywords: Abnormalities, Multiple; Adolescent; Child; Corneal Opacity; Developmental Disabilities; Female; Frameshift Mutation; Genotype; Humans; Intellectual Disability; Male; Movement Disorders; Peptide-N4-(N-acetyl-beta-glucosaminyl) Asparagine Amidase; Peripheral Nervous System Diseases

Nonrecurrent 17p11.2p12 Rearrangement Events that Result in Two Concomitant Genomic Disorders: The PMP22-RAI1 Contiguous Gene Duplication Syndrome. - Yuan, Bo; Harel, Tamar; Gu, Shen; Liu, Pengfei; Burglen, Lydie; Chantot-Bastaraud, Sandra; Gelowani, Violet; Beck, Christine R; Carvalho, Claudia M B; Cheung, Sau Wai; Coe, Andrew; Malan, Valérie; et al. (Am J Hum Genet, 2015)
The genomic duplication associated with Potocki-Lupski syndrome (PTLS) maps in close proximity to the duplication associated with Charcot-Marie-Tooth disease type 1A (CMT1A). PTLS is characterized by hypotonia, failure to thrive, reduced body weight, intellectual disability, and autistic features. CMT1A is a common autosomal dominant distal symmetric peripheral polyneuropathy. The key dosage-sensitive genes RAI1 and PMP22 are respectively associated with PTLS and CMT1A. Recurrent duplications accounting for the majority of subjects with these conditions are mediated by nonallelic homologous recombination between distinct low-copy repeat (LCR) substrates. The LCRs flanking a contiguous genomic interval encompassing both RAI1 and PMP22 do not share extensive homology; thus, duplications encompassing both loci are rare and potentially generated by a different mutational mechanism. We characterized genomic rearrangements that simultaneously duplicate PMP22 and RAI1, including nine potential complex genomic rearrangements, in 23 subjects by high-resolution array comparative genomic hybridization and breakpoint junction sequencing. Insertions and microhomologies were found at the breakpoint junctions, suggesting potential replicative mechanisms for rearrangement formation. At the breakpoint junctions of these nonrecurrent rearrangements, enrichment of repetitive DNA sequences was observed, indicating that they might predispose to genomic instability and rearrangement. Clinical evaluation revealed blended PTLS and CMT1A phenotypes with a potential earlier onset of neuropathy. Moreover, additional clinical findings might be observed due to the extra duplicated material included in the rearrangements. Our genomic analysis suggests replicative mechanisms as a predominant mechanism underlying PMP22-RAI1 contiguous gene duplications and provides further evidence supporting the role of complex genomic architecture in genomic instability.
Keywords: Abnormalities, Multiple; Charcot-Marie-Tooth Disease; Child; Child, Preschool; Chromosome Disorders; Chromosome Duplication; Chromosomes, Human, Pair 17; Comparative Genomic Hybridization; Female; Follow-Up Studies; Gene Duplication; Gene Rearrangement; Genome, Human; Genomics; Humans; Infant; Male; Models, Genetic; Myelin Proteins; Phenotype; Prognosis; Recombination, Genetic; Transcription Factors

Novel COL2A1 variant (c.619G>A, p.Gly207Arg) manifesting as a phenotype similar to progressive pseudorheumatoid dysplasia and spondyloepiphyseal dysplasia, Stanescu type. - Jurgens, Julie; Sobreira, Nara; Modaff, Peggy; Reiser, Catherine A; Seo, Soo Hyun; Seong, Moon-Woo; Park, Sung Sup; Kim, Ok Hwa; Cho, Tae-Joon; Pauli, Richard M (Hum Mutat, 2015)
Progressive pseudorheumatoid dysplasia (PPRD) is a rare, autosomal-recessive condition characterized by mild spondyloepiphyseal dysplasia (SED) and severe, progressive, early-onset arthritis due to WISP3 mutations. SED, Stanescu type, is a vaguely delineated autosomal-dominant dysplasia of unknown genetic etiology. Here, we report three individuals from two unrelated families with radiological features similar to PPRD and SED, Stanescu type who share the same novel COL2A1 variant and were matched following discussion at an academic conference. In the first family, we performed whole-exome sequencing on three family members, two of whom have a PPRD-like phenotype, and identified a heterozygous variant (c.619G>A, p.Gly207Arg) in both affected individuals. Independently, targeted sequencing of the COL2A1 gene in an unrelated proband with a similar phenotype identified the same heterozygous variant. We suggest that the p.Gly207Arg variant causes a distinct type II collagenopathy with features of PPRD and SED, Stanescu type.
Keywords: Adolescent; Adult; Child; Collagen Type II; Exome; Female; Humans; Joint Diseases; Male; Osteochondrodysplasias; Pedigree; Polymorphism, Single Nucleotide; Radiography; Sequence Analysis, DNA

Rare A2ML1 variants confer susceptibility to otitis media. - Santos-Cortez, Regie Lyn P; Chiong, Charlotte M; Reyes-Quintos, Ma Rina T; Tantoco, Ma Leah C; Wang, Xin; Acharya, Anushree; Abbe, Izoduwa; Giese, Arnaud P; Smith, Joshua D; Allen, E Kaitlynn; Li, Biao; Cutiongco-de la Paz, Eva Maria; et al. (Nat Genet, 2015)
A duplication variant within the middle ear-specific gene A2ML1 cosegregates with otitis media in an indigenous Filipino pedigree (LOD score = 7.5 at reduced penetrance) and lies within a founder haplotype that is also shared by 3 otitis-prone European-American and Hispanic-American children but is absent in non-otitis-prone children and >62,000 next-generation sequences. We identified seven additional A2ML1 variants in six otitis-prone children. Collectively, our studies support a role for A2ML1 in the pathophysiology of otitis media.
Keywords: alpha-Macroglobulins; Animals; Base Sequence; Child; Cochlea; Exome; Family Health; Female; Gene Duplication; Gene Frequency; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Male; Mice, Inbred C57BL; Models, Molecular; Otitis Media; Pedigree; Principal Component Analysis; Protein Conformation; Sequence Analysis, DNA

Rare variants in RTEL1 are associated with familial interstitial pneumonia. - Cogan, Joy D; Kropski, Jonathan A; Zhao, Min; Mitchell, Daphne B; Rives, Lynette; Markin, Cheryl; Garnett, Errine T; Montgomery, Keri H; Mason, Wendi R; McKean, David F; Powers, Julia; Murphy, Elissa; et al. (Am J Respir Crit Care Med, 2015)
RATIONALE: Up to 20% of cases of idiopathic interstitial pneumonia cluster in families, comprising the syndrome of familial interstitial pneumonia (FIP); however, the genetic basis of FIP remains uncertain in most families. OBJECTIVES: To determine if new disease-causing rare genetic variants could be identified using whole-exome sequencing of affected members from FIP families, providing additional insights into disease pathogenesis. METHODS: Affected subjects from 25 kindreds were selected from an ongoing FIP registry for whole-exome sequencing from genomic DNA. Candidate rare variants were confirmed by Sanger sequencing, and cosegregation analysis was performed in families, followed by additional sequencing of affected individuals from another 163 kindreds. MEASUREMENTS AND MAIN RESULTS: We identified a potentially damaging rare variant in the gene encoding for regulator of telomere elongation helicase 1 (RTEL1) that segregated with disease and was associated with very short telomeres in peripheral blood mononuclear cells in 1 of 25 families in our original whole-exome sequencing cohort. Evaluation of affected individuals in 163 additional kindreds revealed another eight families (4.7%) with heterozygous rare variants in RTEL1 that segregated with clinical FIP. Probands and unaffected carriers of these rare variants had short telomeres (<10% for age) in peripheral blood mononuclear cells and increased T-circle formation, suggesting impaired RTEL1 function. CONCLUSIONS: Rare loss-of-function variants in RTEL1 represent a newly defined genetic predisposition for FIP, supporting the importance of telomere-related pathways in pulmonary fibrosis.
Keywords: Aged; Aged, 80 and over; DNA Helicases; Female; Genetic Variation; Heterozygote; Humans; Lung; Lung Diseases, Interstitial; Male; Middle Aged; Pedigree; Telomere

Rare variants in the notch signaling pathway describe a novel type of autosomal recessive Klippel-Feil syndrome. - Karaca, Ender; Yuregir, Ozge O; Bozdogan, Sevcan T; Aslan, Huseyin; Pehlivan, Davut; Jhangiani, Shalini N; Akdemir, Zeynep C; Gambin, Tomasz; Bayram, Yavuz; Atik, Mehmed M; Erdin, Serkan; Muzny, Donna; et al. (Am J Med Genet A, 2015)
Klippel-Feil syndrome is a rare disorder represented by a subgroup of segmentation defects of the vertebrae and characterized by fusion of the cervical vertebrae, low posterior hairline, and short neck with limited motion. Both autosomal dominant and recessive inheritance patterns were reported in families with Klippel-Feil. Mutated genes for both dominant (GDF6 and GDF3) and recessive (MEOX1) forms of Klippel-Feil syndrome have been shown to be involved in somite development via transcription regulation and signaling pathways. Heterotaxy arises from defects in proteins that function in the development of left-right asymmetry of the developing embryo. We describe a consanguineous family with a male proband who presents with classical Klippel-Feil syndrome together with heterotaxy (situs inversus totalis). The present patient also had Sprengel's deformity, deformity of the sternum, and a solitary kidney. Using exome sequencing, we identified a homozygous frameshift mutation (c.299delT; p.L100fs) in RIPPLY2, a gene shown to play a crucial role in somitogenesis and participate in the Notch signaling pathway via negatively regulating Tbx6. Our data confirm RIPPLY2 as a novel gene for autosomal recessive Klippel-Feil syndrome, and in addition-from a mechanistic standpoint-suggest the possibility that mutations in RIPPLY2 could also lead to heterotaxy. © 2015 Wiley Periodicals, Inc.
Keywords: Adolescent; Base Sequence; Female; Humans; Klippel-Feil Syndrome; Male; Molecular Sequence Data; Mutation; Pedigree; Radiography; Receptors, Notch; Signal Transduction; Spine

Recurrent gain of function mutation in calcium channel CACNA1H causes early-onset hypertension with primary aldosteronism. - Scholl, Ute I; Stölting, Gabriel; Nelson-Williams, Carol; Vichot, Alfred A; Choi, Murim; Loring, Erin; Prasad, Manju L; Goh, Gerald; Carling, Tobias; Juhlin, C Christofer; Quack, Ivo; Rump, Lars C; et al. (Elife, 2015)
Many Mendelian traits are likely unrecognized owing to absence of traditional segregation patterns in families due to causation by de novo mutations, incomplete penetrance, and/or variable expressivity. Genome-level sequencing can overcome these complications. Extreme childhood phenotypes are promising candidates for new Mendelian traits. One example is early onset hypertension, a rare form of a global cause of morbidity and mortality. We performed exome sequencing of 40 unrelated subjects with hypertension due to primary aldosteronism by age 10. Five subjects (12.5%) shared the identical, previously unidentified, heterozygous CACNA1H(M1549V) mutation. Two mutations were demonstrated to be de novo events, and all mutations occurred independently. CACNA1H encodes a voltage-gated calcium channel (CaV3.2) expressed in adrenal glomerulosa. CACNA1H(M1549V) showed drastically impaired channel inactivation and activation at more hyperpolarized potentials, producing increased intracellular Ca(2+), the signal for aldosterone production. This mutation explains disease pathogenesis and provides new insight into mechanisms mediating aldosterone production and hypertension.
Keywords: Adolescent; Adult; Age of Onset; Aldosterone; Amino Acid Sequence; Calcium; Calcium Channels, T-Type; Calcium Signaling; Child; Child, Preschool; Female; Gene Expression; Genotype; Heterozygote; Humans; Hyperaldosteronism; Hypertension; Infant; Male; Membrane Potentials; Middle Aged; Molecular Sequence Data; Mutation; Phenotype; Recurrence; Sequence Alignment; Zona Glomerulosa

Root anomalies and dentin dysplasia in autosomal recessive hyperphosphatemic familial tumoral calcinosis (HFTC). - Vieira, Alexandre R; Lee, Moses; Vairo, Filippo; Loguercio Leite, Julio Cesar; Munerato, Maria Cristina; Visioli, Fernanda; D'Ávila, Stéphanie Rodrigues; Wang, Shih-Kai; Choi, Murim; Simmer, James P; Hu, Jan C-C (Oral Surg Oral Med Oral Pathol Oral Radiol, 2015)
Hyperphosphatemic familial tumoral calcinosis (HFTC, OMIM #211900) is an autosomal recessive metabolic disorder characterized by hyperphosphatemia, tooth root defects, and the progressive deposition of calcium phosphate crystals in periarticular spaces, soft tissues, and sometimes bone.(1) In this HFTC case report, we document the dental phenotype associated with a homozygous missense mutation (g.29077 C>T; c.484 C>T; p.Arg162*) in GALNT3 (OMIM 6017563), a gene encoding UDP-GalNAc transferase 3 that catalyzes the first step of O-linked oligosaccharide biosynthesis in the Golgi. The medical and dental pathology is believed to be caused primarily by high serum phosphate levels (hyperphosphatemia), which, in turn, is caused by failure of GALNT3 to glycosylate the phosphate regulator protein FGF23, impairing its ability inhibit reabsorption of filtered phosphate in the kidneys.
Keywords: Adolescent; Calcinosis; Dentin Dysplasia; Humans; Hyperostosis, Cortical, Congenital; Hyperphosphatemia; Male; Mutation, Missense; N-Acetylgalactosaminyltransferases; Pedigree; Phenotype; Radiography, Panoramic; Tooth Root

Safety and Proof-of-Concept Study of Oral QLT091001 in Retinitis Pigmentosa Due to Inherited Deficiencies of Retinal Pigment Epithelial 65 Protein (RPE65) or Lecithin:Retinol Acyltransferase (LRAT). - Scholl, Hendrik P N; Moore, Anthony T; Koenekoop, Robert K; Wen, Yuquan; Fishman, Gerald A; van den Born, L Ingeborgh; Bittner, Ava; Bowles, Kristen; Fletcher, Emily C; Collison, Frederick T; Dagnelie, Gislin; Degli Eposti, Simona; et al. (PLoS One, 2015)
UNLABELLED: Restoring vision in inherited retinal degenerations remains an unmet medical need. In mice exhibiting a genetically engineered block of the visual cycle, vision was recently successfully restored by oral administration of 9-cis-retinyl acetate (QLT091001). Safety and visual outcomes of a once-daily oral dose of 40 mg/m2/day QLT091001 for 7 consecutive days was investigated in an international, multi-center, open-label, proof-of-concept study in 18 patients with RPE65- or LRAT-related retinitis pigmentosa. Eight of 18 patients (44%) showed a ≥20% increase and 4 of 18 (22%) showed a ≥40% increase in functional retinal area determined from Goldmann visual fields; 12 (67%) and 5 (28%) of 18 patients showed a ≥5 and ≥10 ETDRS letter score increase of visual acuity, respectively, in one or both eyes at two or more visits within 2 months of treatment. In two patients who underwent fMRI, a significant positive response was measured to stimuli of medium contrast, moving, pattern targets in both left and right hemispheres of the occipital cortex. There were no serious adverse events. Treatment-related adverse events were transient and the most common included headache, photophobia, nausea, vomiting, and minor biochemical abnormalities. Measuring the outer segment length of the photoreceptor layer with high-definition optical coherence tomography was highly predictive of treatment responses with responders having a significantly larger baseline outer segment thickness (11.7 ± 4.8 μm, mean ± 95% CI) than non-responders (3.5 ± 1.2 μm). This structure-function relationship suggests that treatment with QLT091001 is more likely to be efficacious if there is sufficient photoreceptor integrity. TRIAL REGISTRATION: ClinicalTrials.gov NCT01014052.
Keywords: Acyltransferases; Administration, Oral; Adult; Anticarcinogenic Agents; Cerebral Cortex; Child; cis-trans-Isomerases; Drug Dosage Calculations; Female; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Radiography; Retinal Ganglion Cells; Retinal Neurons; Retinitis Pigmentosa; Treatment Outcome; Visual Acuity; Visual Fields; Vitamin A; Young Adult

A second locus for Schneckenbecken dysplasia identified by a mutation in the gene encoding inositol polyphosphate phosphatase-like 1 (INPPL1). - Lee, Hane; Nevarez, Lisette; Lachman, Ralph S; Wilcox, William R; Krakow, Deborah; Cohn, Daniel H (Am J Med Genet A, 2015)
Keywords: Exome; Gene Expression; Genetic Loci; Gestational Age; Homozygote; Humans; Hydrops Fetalis; Infant, Newborn; Male; Mutation; Osteochondrodysplasias; Phosphatidylinositol-3,4,5-Trisphosphate 5-Phosphatases; Phosphoric Monoester Hydrolases; Stillbirth

Somatic Activating RAS Mutations Cause Vascular Tumors Including Pyogenic Granuloma. - Lim, Young H; Douglas, Stephanie R; Ko, Christine J; Antaya, Richard J; McNiff, Jennifer M; Zhou, Jing; Choate, Keith A; Narayan, Deepak (J Invest Dermatol, 2015)
Keywords: Adolescent; Cell Proliferation; Child; Child, Preschool; Female; Gene Expression Regulation, Neoplastic; Granuloma, Pyogenic; Humans; Infant; Infant, Newborn; Male; Mutation; ras Proteins; Vascular Neoplasms

Somatic p.T771R KDR (VEGFR2) Mutation Arising in a Sporadic Angioma During Ramucirumab Therapy. - Lim, Young H; Odell, Ian D; Ko, Christine J; Choate, Keith A (JAMA Dermatol, 2015)
IMPORTANCE: Inhibition of angiogenesis is an effective anticancer strategy because neoplasms require a rich blood supply. Ramucirumab, approved by the US Food and Drug Administration in 2014 to treat gastric adenocarcinomas and non-small cell lung carcinomas, targets vascular endothelial growth factor 2 (VEGFR2). We identified a patient prescribed a regimen of irinotecan hydrochloride, cetuximab, and ramucirumab for metastatic rectal cancer (diagnosed in November 2013 and treated through early January 2015) who developed a new-onset, expanding vascular lesion on his right leg. Via exome sequencing, we found that the lesion contained a single somatic mutation in KDR (encodes VEGFR2), possibly in response to ramucirumab. Vascular tumors are not a known complication of antiangiogenic therapeutics. OBSERVATIONS: Exome sequencing of the well-demarcated, blanching vascular lesion on the lateral right shin revealed a somatic p.T771R mutation in KDR, without evidence of other somatic mutations or loss of heterozygosity. Histological features included lobules of small vessels within the dermis, resembling a tufted angioma. CONCLUSIONS AND RELEVANCE: A potential adverse effect of ramucirumab in combination therapy is the development of sporadic angiomas. The p.T771R mutation was previously implicated in autophosphorylation of VEGFR2 and reported in angiosarcomas alongside other driver mutations. Our observations suggest that this mutation confers a proliferative advantage in the setting of ramucirumab therapy. Patients receiving ramucirumab should be monitored for the development of new vascular lesions.
Keywords: Adult; Angiogenesis Inhibitors; Antibodies, Monoclonal; Antineoplastic Combined Chemotherapy Protocols; Camptothecin; Cetuximab; Hemangioma; Humans; Irinotecan; Male; Mutation; Rectal Neoplasms; Skin Neoplasms; Vascular Endothelial Growth Factor Receptor-2

Successful diagnosis of HIBCH deficiency from exome sequencing and positive retrospective analysis of newborn screening cards in two siblings presenting with Leigh's disease. - Stiles, Ashlee R; Ferdinandusse, Sacha; Besse, Arnaud; Appadurai, Vivek; Leydiker, Karen B; Cambray-Forker, E J; Bonnen, Penelope E; Abdenur, Jose E (Mol Genet Metab, 2015)
PURPOSE: 3-Hydroxyisobutryl-CoA hydrolase (HIBCH) deficiency is a rare disorder of valine metabolism. We present a family with the oldest reported subjects with HIBCH deficiency and provide support that HIBCH deficiency should be included in the differential for elevated hydroxy-C4-carnitine in newborn screening (NBS). METHODS: Whole exome sequencing (WES) was performed on one affected sibling. HIBCH enzymatic activity was measured in patient fibroblasts. Acylcarnitines were measured by electrospray ionization tandem mass spectrometry (ESI-MS/MS). Disease incidence was estimated using a cohort of 61,434 individuals. RESULTS: Two siblings presented with infantile-onset, progressive neurodegenerative disease. WES identified a novel homozygous variant in HIBCH c.196C>T; p.Arg66Trp. HIBCH enzymatic activity was significantly reduced in patients' fibroblasts. Acylcarnitine analysis showed elevated hydroxy-C4-carnitine in blood spots of both affected siblings, including in their NBS cards, while plasma acylcarnitines were normal. Estimates show HIBCH deficiency incidence as high as 1 in ~130,000 individuals. CONCLUSION: We describe a novel family with HIBCH deficiency at the biochemical, enzymatic and molecular level. Disease incidence estimates indicate HIBCH deficiency may be under-diagnosed. This together with the elevated hydroxy-C4-carnitine found in the retrospective analysis of our patient's NBS cards suggests that this disorder could be screened for by NBS programs and should be added to the differential diagnosis for elevated hydroxy-C4-carnitine which is already measured in most NBS programs using MS/MS.
Keywords: Abnormalities, Multiple; Adolescent; Amino Acid Metabolism, Inborn Errors; Carnitine; Child; Child, Preschool; Cohort Studies; Exome; Female; Fibroblasts; Humans; Infant; Infant, Newborn; Leigh Disease; Male; Mass Spectrometry; Neonatal Screening; Prognosis; Retrospective Studies; Sequence Analysis, DNA; Siblings; Thiolester Hydrolases

TBX6 null variants and a common hypomorphic allele in congenital scoliosis. - Wu, N; Ming, X; Xiao, J; Wu, Z; Chen, X; Shinawi, M; Shen, Y; Yu, G; Liu, J; Xie, H; Gucev, Z S; Liu, S; et al. (N Engl J Med, 2015)
BACKGROUND: Congenital scoliosis is a common type of vertebral malformation. Genetic susceptibility has been implicated in congenital scoliosis. METHODS: We evaluated 161 Han Chinese persons with sporadic congenital scoliosis, 166 Han Chinese controls, and 2 pedigrees, family members of which had a 16p11.2 deletion, using comparative genomic hybridization, quantitative polymerase-chain-reaction analysis, and DNA sequencing. We carried out tests of replication using an additional series of 76 Han Chinese persons with congenital scoliosis and a multicenter series of 42 persons with 16p11.2 deletions. RESULTS: We identified a total of 17 heterozygous TBX6 null mutations in the 161 persons with sporadic congenital scoliosis (11%); we did not observe any null mutations in TBX6 in 166 controls (P<3.8×10(-6)). These null alleles include copy-number variants (12 instances of a 16p11.2 deletion affecting TBX6) and single-nucleotide variants (1 nonsense and 4 frame-shift mutations). However, the discordant intrafamilial phenotypes of 16p11.2 deletion carriers suggest that heterozygous TBX6 null mutation is insufficient to cause congenital scoliosis. We went on to identify a common TBX6 haplotype as the second risk allele in all 17 carriers of TBX6 null mutations (P<1.1×10(-6)). Replication studies involving additional persons with congenital scoliosis who carried a deletion affecting TBX6 confirmed this compound inheritance model. In vitro functional assays suggested that the risk haplotype is a hypomorphic allele. Hemivertebrae are characteristic of TBX6-associated congenital scoliosis. CONCLUSIONS: Compound inheritance of a rare null mutation and a hypomorphic allele of TBX6 accounted for up to 11% of congenital scoliosis cases in the series that we analyzed. (Funded by the National Basic Research Program of China and others.).
Keywords: Adolescent; Asian Continental Ancestry Group; Child; Child, Preschool; Chromosomes, Human, Pair 16; DNA Copy Number Variations; Female; Genetic Predisposition to Disease; Genotype; Humans; Male; Mutation; Pedigree; Phenotype; Radiography; Scoliosis; Sequence Deletion; Spine; T-Box Domain Proteins

Truncating mutations in the last exon of NOTCH3 cause lateral meningocele syndrome. - Gripp, Karen W; Robbins, Katherine M; Sobreira, Nara L; Witmer, P Dane; Bird, Lynne M; Avela, Kristiina; Mäkitie, Outi; Alves, Daniela; Hogue, Jacob S; Zackai, Elaine H; Doheny, Kimberly F; Stabley, Deborah L; et al. (Am J Med Genet A, 2015)
Lateral meningocele syndrome (LMS, OMIM%130720), also known as Lehman syndrome, is a very rare skeletal disorder with facial anomalies, hypotonia and meningocele-related neurologic dysfunction. The characteristic lateral meningoceles represent the severe end of the dural ectasia spectrum and are typically most severe in the lower spine. Facial features of LMS include hypertelorism and telecanthus, high arched eyebrows, ptosis, midfacial hypoplasia, micrognathia, high and narrow palate, low-set ears and a hypotonic appearance. Hyperextensibility, hernias and scoliosis reflect a connective tissue abnormality, and aortic dilation, a high-pitched nasal voice, wormian bones and osteolysis may be present. Lateral meningocele syndrome has phenotypic overlap with Hajdu-Cheney syndrome. We performed exome resequencing in five unrelated individuals with LMS and identified heterozygous truncating NOTCH3 mutations. In an additional unrelated individual Sanger sequencing revealed a deleterious variant in the same exon 33. In total, five novel de novo NOTCH3 mutations were identified in six unrelated patients. One had a 26 bp deletion (c.6461_6486del, p.G2154fsTer78), two carried the same single base pair insertion (c.6692_93insC, p.P2231fsTer11), and three individuals had a nonsense point mutation at c.6247A > T (pK2083*), c.6663C > G (p.Y2221*) or c.6732C > A, (p.Y2244*). All mutations cluster into the last coding exon, resulting in premature termination of the protein and truncation of the negative regulatory proline-glutamate-serine-threonine rich PEST domain. Our results suggest that mutant mRNA products escape nonsense mediated decay. The truncated NOTCH3 may cause gain-of-function through decreased clearance of the active intracellular product, resembling NOTCH2 mutations in the clinically related Hajdu-Cheney syndrome and contrasting the NOTCH3 missense mutations causing CADASIL.
Keywords: Abnormalities, Multiple; Child; Child, Preschool; DNA Mutational Analysis; Exome; Exons; Facies; High-Throughput Nucleotide Sequencing; Humans; Magnetic Resonance Imaging; Male; Meningocele; Mutation; Phenotype; Receptor, Notch3; Receptors, Notch; Young Adult

Whole exome sequencing identifies de novo heterozygous CAV1 mutations associated with a novel neonatal onset lipodystrophy syndrome. - Garg, Abhimanyu; Kircher, Martin; Del Campo, Miguel; Amato, R Stephen; Agarwal, Anil K (Am J Med Genet A, 2015)
Despite remarkable progress in identifying causal genes for many types of genetic lipodystrophies in the last decade, the molecular basis of many extremely rare lipodystrophy patients with distinctive phenotypes remains unclear. We conducted whole exome sequencing of the parents and probands from six pedigrees with neonatal onset of generalized loss of subcutaneous fat with additional distinctive phenotypic features and report de novo heterozygous null mutations, c.424C>T (p.Q142*) and c.479_480delTT (p.F160*), in CAV1 in a 7-year-old male and a 3-year-old female of European origin, respectively. Both the patients had generalized fat loss, thin mottled skin and progeroid features at birth. The male patient had cataracts requiring extraction at age 30 months and the female patient had pulmonary arterial hypertension. Dermal fibroblasts of the female patient revealed negligible CAV1 immunofluorescence staining compared to control but there were no differences in the number and morphology of caveolae upon electron microscopy examination. Based upon the similarities in the clinical features of these two patients, previous reports of CAV1 mutations in patients with lipodystrophies and pulmonary hypertension, and similar features seen in CAV1 null mice, we conclude that these variants are the most likely cause of one subtype of neonatal onset generalized lipodystrophy syndrome.
Keywords: Caveolin 1; Cells, Cultured; Exome; Female; Heterozygote; Humans; Infant, Newborn; Lipodystrophy; Male; Mutation; Pedigree

Whole-exome sequencing identifies novel homozygous mutation in NPAS2 in family with nonobstructive azoospermia. - Ramasamy, Ranjith; Bakırcıoğlu, M Emre; Cengiz, Cenk; Karaca, Ender; Scovell, Jason; Jhangiani, Shalini N; Akdemir, Zeynep C; Bainbridge, Matthew; Yu, Yao; Huff, Chad; Gibbs, Richard A; Lupski, James R; et al. (Fertil Steril, 2015)
OBJECTIVE: To investigate the genetic cause of nonobstructive azoospermia (NOA) in a consanguineous Turkish family through homozygosity mapping followed by targeted exon/whole-exome sequencing to identify genetic variations. DESIGN: Whole-exome sequencing (WES). SETTING: Research laboratory. PATIENT(S): Two siblings in a consanguineous family with NOA. INTERVENTION(S): Validating all variants passing filter criteria with Sanger sequencing to confirm familial segregation and absence in the control population. MAIN OUTCOME MEASURE(S): Discovery of a mutation that could potentially cause NOA. RESULT(S): A novel nonsynonymous mutation in the neuronal PAS-2 domain (NPAS2) was identified in a consanguineous family from Turkey. This mutation in exon 14 (chr2: 101592000 C>G) of NPAS2 is likely a disease-causing mutation as it is predicted to be damaging, it is a novel variant, and it segregates with the disease. Family segregation of the variants showed the presence of the homozygous mutation in the three brothers with NOA and a heterozygous mutation in the mother as well as one brother and one sister who were both fertile. The mutation is not found in the single-nucleotide polymorphism database, the 1000 Genomes Project, the Baylor College of Medicine cohort of 500 Turkish patients (not a population-specific polymorphism), or the matching 50 fertile controls. CONCLUSION(S): With the use of WES we identified a novel homozygous mutation in NPAS2 as a likely disease-causing variant in a Turkish family diagnosed with NOA. Our data reinforce the clinical role of WES in the molecular diagnosis of highly heterogeneous genetic diseases for which conventional genetic approaches have previously failed to find a molecular diagnosis.
Keywords: Adult; Azoospermia; Base Sequence; Basic Helix-Loop-Helix Transcription Factors; Exome; Homozygote; Humans; Male; Molecular Sequence Data; Mutation; Nerve Tissue Proteins; Pedigree

X-linked acrogigantism syndrome: clinical profile and therapeutic responses. - Beckers, Albert; Lodish, Maya Beth; Trivellin, Giampaolo; Rostomyan, Liliya; Lee, Misu; Faucz, Fabio R; Yuan, Bo; Choong, Catherine S; Caberg, Jean-Hubert; Verrua, Elisa; Naves, Luciana Ansaneli; Cheetham, Tim D; et al. (Endocr Relat Cancer, 2015)
X-linked acrogigantism (X-LAG) is a new syndrome of pituitary gigantism, caused by microduplications on chromosome Xq26.3, encompassing the gene GPR101, which is highly upregulated in pituitary tumors. We conducted this study to explore the clinical, radiological, and hormonal phenotype and responses to therapy in patients with X-LAG syndrome. The study included 18 patients (13 sporadic) with X-LAG and microduplication of chromosome Xq26.3. All sporadic cases had unique duplications and the inheritance pattern in two families was dominant, with all Xq26.3 duplication carriers being affected. Patients began to grow rapidly as early as 2-3 months of age (median 12 months). At diagnosis (median delay 27 months), patients had a median height and weight standard deviation scores (SDS) of >+3.9 SDS. Apart from the increased overall body size, the children had acromegalic symptoms including acral enlargement and facial coarsening. More than a third of cases had increased appetite. Patients had marked hypersecretion of GH/IGF1 and usually prolactin, due to a pituitary macroadenoma or hyperplasia. Primary neurosurgical control was achieved with extensive anterior pituitary resection, but postoperative hypopituitarism was frequent. Control with somatostatin analogs was not readily achieved despite moderate to high levels of expression of somatostatin receptor subtype-2 in tumor tissue. Postoperative use of adjuvant pegvisomant resulted in control of IGF1 in all five cases where it was employed. X-LAG is a new infant-onset gigantism syndrome that has a severe clinical phenotype leading to challenging disease management.
Keywords: Acromegaly; Adenoma; Adolescent; Child; Child, Preschool; Chromosomes, Human, X; Female; Gigantism; Humans; Infant; Male; Pituitary Neoplasms; Young Adult

Adenylate cyclase 1 (ADCY1) mutations cause recessive hearing impairment in humans and defects in hair cell function and hearing in zebrafish. - Santos-Cortez, Regie Lyn P; Lee, Kwanghyuk; Giese, Arnaud P; Ansar, Muhammad; Amin-ud-Din, Muhammad; Rehn, Kira; Wang, Xin; Aziz, Abdul; Chiu, Ilene; Hussain Ali, Raja; Smith, Joshua D; Shendure, Jay; et al. (Hum Mol Genet, 2014)
Cyclic AMP (cAMP) production, which is important for mechanotransduction within the inner ear, is catalyzed by adenylate cyclases (AC). However, knowledge of the role of ACs in hearing is limited. Previously, a novel autosomal recessive non-syndromic hearing impairment locus DFNB44 was mapped to chromosome 7p14.1-q11.22 in a consanguineous family from Pakistan. Through whole-exome sequencing of DNA samples from hearing-impaired family members, a nonsense mutation c.3112C>T (p.Arg1038*) within adenylate cyclase 1 (ADCY1) was identified. This stop-gained mutation segregated with hearing impairment within the family and was not identified in ethnically matched controls or within variant databases. This mutation is predicted to cause the loss of 82 amino acids from the carboxyl tail, including highly conserved residues within the catalytic domain, plus a calmodulin-stimulation defect, both of which are expected to decrease enzymatic efficiency. Individuals who are homozygous for this mutation had symmetric, mild-to-moderate mixed hearing impairment. Zebrafish adcy1b morphants had no FM1-43 dye uptake and lacked startle response, indicating hair cell dysfunction and gross hearing impairment. In the mouse, Adcy1 expression was observed throughout inner ear development and maturation. ADCY1 was localized to the cytoplasm of supporting cells and hair cells of the cochlea and vestibule and also to cochlear hair cell nuclei and stereocilia. Ex vivo studies in COS-7 cells suggest that the carboxyl tail of ADCY1 is essential for localization to actin-based microvilli. These results demonstrate that ADCY1 has an evolutionarily conserved role in hearing and that cAMP signaling is important to hair cell function within the inner ear.
Keywords: Adenylyl Cyclases; Animals; Cercopithecus aethiops; Codon, Nonsense; COS Cells; Cyclic AMP; Cytoplasm; Ear, Inner; Female; Hair Cells, Auditory; Hearing Loss; Humans; Labyrinth Supporting Cells; Male; Mice; Zebrafish

Attitudes of non-African American focus group participants toward return of results from exome and whole genome sequencing. - Yu, Joon-Ho; Crouch, Julia; Jamal, Seema M; Bamshad, Michael J; Tabor, Holly K (Am J Med Genet A, 2014)
Exome sequencing and whole genome sequencing (ES/WGS) present individuals with the opportunity to benefit from a broad scope of genetic results of clinical and personal utility. Yet, it is unclear which genetic results people want to receive (i.e., what type of genetic information they want to learn about themselves) or conversely not receive, and how they want to receive or manage results over time. Very little is known about whether and how attitudes toward receiving individual results from ES/WGS vary among racial/ethnic populations. We conducted 13 focus groups with a racially and ethnically diverse parent population (n = 76) to investigate attitudes toward return of individual results from WGS. We report on our findings for non-African American (non-AA) participants. Non-AA participants were primarily interested in genetic results on which they could act or "do something about." They defined "actionability" broadly to include individual medical treatment and disease prevention. The ability to plan for the future was both a motivation for and an expected benefit of receiving results. Their concerns focused on the meaning of results, specifically the potential inaccuracy and uncertainty of results. Non-AA participants expected healthcare providers to be involved in results management by helping them interpret results in the context of their own health and by providing counseling support. We compare and contrast these themes with those we previously reported from our analysis of African American (AA) perspectives to highlight the importance of varying preferences for results, characterize the central role of temporal orientation in framing expectations about the possibility of receiving ES/WGS results, and identify potential avenues by which genomic healthcare disparities may be inadvertently perpetuated.
Keywords: Adult; African Americans; Aged; Attitude to Health; Exome; Female; Focus Groups; Genome, Human; Humans; Male; Middle Aged; Sequence Analysis, DNA

Biallelic truncating mutations in FMN2, encoding the actin-regulatory protein Formin 2, cause nonsyndromic autosomal-recessive intellectual disability. - Law, Rosalind; Dixon-Salazar, Tracy; Jerber, Julie; Cai, Na; Abbasi, Ansar A; Zaki, Maha S; Mittal, Kirti; Gabriel, Stacey B; Rafiq, Muhammad Arshad; Khan, Valeed; Nguyen, Maria; Ali, Ghazanfar; et al. (Am J Hum Genet, 2014)
Dendritic spines represent the major site of neuronal activity in the brain; they serve as the receiving point for neurotransmitters and undergo rapid activity-dependent morphological changes that correlate with learning and memory. Using a combination of homozygosity mapping and next-generation sequencing in two consanguineous families affected by nonsyndromic autosomal-recessive intellectual disability, we identified truncating mutations in formin 2 (FMN2), encoding a protein that belongs to the formin family of actin cytoskeleton nucleation factors and is highly expressed in the maturing brain. We found that FMN2 localizes to punctae along dendrites and that germline inactivation of mouse Fmn2 resulted in animals with decreased spine density; such mice were previously demonstrated to have a conditioned fear-learning defect. Furthermore, patient neural cells derived from induced pluripotent stem cells showed correlated decreased synaptic density. Thus, FMN2 mutations link intellectual disability either directly or indirectly to the regulation of actin-mediated synaptic spine density.
Keywords: Adolescent; Adult; Base Sequence; Chromosome Disorders; Cohort Studies; Consanguinity; Egypt; Exome; Female; Genes, Recessive; Genetic Linkage; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Intellectual Disability; Male; Microfilament Proteins; Molecular Sequence Data; Nuclear Proteins; Pakistan; Pedigree; Sequence Analysis, DNA; Sequence Deletion

Brain malformations associated with Knobloch syndrome--review of literature, expanding clinical spectrum, and identification of novel mutations. - Çağlayan, Ahmet Okay; Baranoski, Jacob F; Aktar, Fesih; Han, Wengi; Tuysuz, Beyhan; Guzel, Aslan; Guclu, Bulent; Kaymakçalan, Hande; Aktekin, Berrin; Akgümüş, Gözde Tuğce; Murray, Phillip B; Erson-Omay, Emine Z; et al. (Pediatr Neurol, 2014)
BACKGROUND: Knobloch syndrome is a rare, autosomal recessive, developmental disorder characterized by stereotyped ocular abnormalities with or without occipital skull deformities (encephalocele, bone defects, and cutis aplasia). Although there is clear heterogeneity in clinical presentation, central nervous system malformations, aside from the characteristic encephalocele, have not typically been considered a component of the disease phenotype. METHODS: Four patients originally presented for genetic evaluation of symptomatic structural brain malformations. Whole-genome genotyping, whole-exome sequencing, and confirmatory Sanger sequencing were performed. Using immunohistochemical analysis, we investigated the protein expression pattern of COL18A1 in the mid-fetal and adult human cerebral cortex and then analyzed the spatial and temporal changes in the expression pattern of COL18A1 during human cortical development using the Human Brain Transcriptome database. RESULTS: We identified two novel homozygous deleterious frame-shift mutations in the COL18A1 gene. On further investigation of these patients and their families, we found that many exhibited certain characteristics of Knobloch syndrome, including pronounced ocular defects. Our data strongly support an important role for COL18A1 in brain development, and this report contributes to an enhanced characterization of the brain malformations that can result from deficiencies of collagen XVIII. CONCLUSIONS: This case series highlights the diagnostic power and clinical utility of whole-exome sequencing technology-allowing clinicians and physician scientists to better understand the pathophysiology and presentations of rare diseases. We suggest that patients who are clinically diagnosed with Knobloch syndrome and/or found to have COL18A1 mutations via genetic screening should be investigated for potential structural brain abnormalities even in the absence of an encephalocele.
Keywords: Adolescent; Adult; Cerebral Cortex; Collagen Type XVIII; Consanguinity; Encephalocele; Exome; Female; Fetus; Humans; Male; Mutation; Retinal Degeneration; Retinal Detachment; Young Adult

CLP1 founder mutation links tRNA splicing and maturation to cerebellar development and neurodegeneration. - Schaffer, Ashleigh E; Eggens, Veerle R C; Çağlayan, Ahmet Okay; Reuter, Miriam S; Scott, Eric; Coufal, Nicole G; Silhavy, Jennifer L; Xue, Yuanchao; Kayserili, Hülya; Yasuno, Katsuhito; Rosti, Rasim Ozgur; Abdellateef, Mostafa; et al. (Cell, 2014)
Neurodegenerative diseases can occur so early as to affect neurodevelopment. From a cohort of more than 2,000 consanguineous families with childhood neurological disease, we identified a founder mutation in four independent pedigrees in cleavage and polyadenylation factor I subunit 1 (CLP1). CLP1 is a multifunctional kinase implicated in tRNA, mRNA, and siRNA maturation. Kinase activity of the CLP1 mutant protein was defective, and the tRNA endonuclease complex (TSEN) was destabilized, resulting in impaired pre-tRNA cleavage. Germline clp1 null zebrafish showed cerebellar neurodegeneration that was rescued by wild-type, but not mutant, human CLP1 expression. Patient-derived induced neurons displayed both depletion of mature tRNAs and accumulation of unspliced pre-tRNAs. Transfection of partially processed tRNA fragments into patient cells exacerbated an oxidative stress-induced reduction in cell survival. Our data link tRNA maturation to neuronal development and neurodegeneration through defective CLP1 function in humans.
Keywords: Animals; Brain; Cerebellum; Cleavage And Polyadenylation Specificity Factor; Female; Humans; Male; Mice; Models, Molecular; Neurodegenerative Diseases; Nuclear Proteins; Pedigree; Phosphotransferases; RNA Splicing; RNA, Transfer; Saccharomyces cerevisiae; Transcription Factors; Zebrafish; Zebrafish Proteins

Compound heterozygous CORO1A mutations in siblings with a mucocutaneous-immunodeficiency syndrome of epidermodysplasia verruciformis-HPV, molluscum contagiosum and granulomatous tuberculoid leprosy. - Stray-Pedersen, Asbjorg; Jouanguy, Emmanuelle; Crequer, Amandine; Bertuch, Alison A; Brown, Betty S; Jhangiani, Shalini N; Muzny, Donna M; Gambin, Tomasz; Sorte, Hanne; Sasa, Ghadir; Metry, Denise; Campbell, Judith; et al. (J Clin Immunol, 2014)
PURPOSE: Coronin-1A deficiency is a recently recognized autosomal recessive primary immunodeficiency caused by mutations in CORO1A (OMIM 605000) that results in T-cell lymphopenia and is classified as T(-)B(+)NK(+)severe combined immunodeficiency (SCID). Only two other CORO1A-kindred are known to date, thus the defining characteristics are not well delineated. We identified a unique CORO1A-kindred. METHODS: We captured a 10-year analysis of the immune-clinical phenotypes in two affected siblings from disease debut of age 7 years. Target-specific genetic studies were pursued but unrevealing. Telomere lengths were also assessed. Whole exome sequencing (WES) uncovered the molecular diagnosis and Western blot validated findings. RESULTS: We found the compound heterozygous CORO1A variants: c.248_249delCT (p.P83RfsX10) and a novel mutation c.1077delC (p.Q360RfsX44) (NM_007074.3) in two affected non-consanguineous siblings that manifested as absent CD4CD45RA(+) (naïve) T and memory B cells, low NK cells and abnormally increased double-negative (DN) ϒδ T-cells. Distinguishing characteristics were late clinical debut with an unusual mucocutaneous syndrome of epidermodysplasia verruciformis-human papilloma virus (EV-HPV), molluscum contagiosum and oral-cutaneous herpetic ulcers; the older female sibling also had a disfiguring granulomatous tuberculoid leprosy. Both had bilateral bronchiectasis and the female died of EBV+ lymphomas at age 16 years. The younger surviving male, without malignancy, had reproducibly very short telomere lengths, not before appreciated in CORO1A mutations. CONCLUSION: We reveal the third CORO1A-mutated kindred, with the immune phenotype of abnormal naïve CD4 and DN T-cells and newfound characteristics of a late/hypomorphic-like SCID of an EV-HPV mucocutaneous syndrome with also B and NK defects and shortened telomeres. Our findings contribute to the elucidation of the CORO1A-SCID-CID spectrum.
Keywords: Adolescent; B-Lymphocytes; CD4-Positive T-Lymphocytes; Child; DNA Mutational Analysis; Epidermodysplasia Verruciformis; Female; Genetic Predisposition to Disease; Granuloma; Heterozygote; Humans; Immunologic Memory; Killer Cells, Natural; Leprosy, Tuberculoid; Male; Microfilament Proteins; Molluscum Contagiosum; Mucous Membrane; Mutation; Papillomavirus Infections; Polymorphism, Genetic; Severe Combined Immunodeficiency; Siblings; Skin; Telomere Shortening

Cytogenomic delineation and clinical follow-up of two siblings with an 8.5 Mb 6q24.2-q25.2 deletion inherited from a paternal insertion. - Meloni, Vera Ayres; Guilherme, Roberta Santos; Oliveira, Mariana Moyses; Migliavacca, Michele; Takeno, Sylvia Satomi; Sobreira, Nara Lygia Macena; de Fatima Faria Soares, Maria; de Mello, Claudia Berlim; Melaragno, Maria Isabel (Am J Med Genet A, 2014)
The chromosomal segment 6q24-q25 comprises a contiguous gene microdeletion syndrome characterized by intrauterine growth retardation, growth delay, intellectual disability, cardiac anomalies, and a dysmorphic facial phenotype. We describe here a 10-year follow-up with detailed clinical, neuropsychological, and cytomolecular data of two siblings, male and female, who presented with developmental delay, microcephaly, short stature, characteristic facial dysmorphisms, multiple organ anomalies, and intellectual disability. Microarray analysis showed an 8.5 Mb 6q24.2-q25.2 interstitial deletion. Fluorescence in situ hybridization analyses confirmed the deletions and identified an insertion of 6q into 8q13 in their father, resulting in a high recurrence risk. This is the first report in sibs with distinct neuropsychological involvement, one of them with stenosis of the descending branch of the aorta.
Keywords: Adolescent; Base Pairing; Child; Child, Preschool; Chromosome Deletion; Chromosomes, Human, Pair 6; Cytogenetic Analysis; Fathers; Female; Follow-Up Studies; Humans; Infant, Newborn; Inheritance Patterns; Male; Mutagenesis, Insertional; Siblings

De novo truncating mutations in AHDC1 in individuals with syndromic expressive language delay, hypotonia, and sleep apnea. - Xia, Fan; Bainbridge, Matthew N; Tan, Tiong Yang; Wangler, Michael F; Scheuerle, Angela E; Zackai, Elaine H; Harr, Margaret H; Sutton, V Reid; Nalam, Roopa L; Zhu, Wenmiao; Nash, Margot; Ryan, Monique M; et al. (Am J Hum Genet, 2014)
Clinical whole-exome sequencing (WES) for identification of mutations leading to Mendelian disease has been offered to the medical community since 2011. Clinically undiagnosed neurological disorders are the most frequent basis for test referral, and currently, approximately 25% of such cases are diagnosed at the molecular level. To date, there are approximately 4,000 "known" disease-associated loci, and many are associated with striking dysmorphic features, making genotype-phenotype correlations relatively straightforward. A significant fraction of cases, however, lack characteristic dysmorphism or clinical pathognomonic traits and are dependent upon molecular tests for definitive diagnoses. Further, many molecular diagnoses are guided by recent gene-disease association discoveries. Hence, there is a critical interplay between clinical testing and research leading to gene-disease association discovery. Here, we describe four probands, all of whom presented with hypotonia, intellectual disability, global developmental delay, and mildly dysmorphic facial features. Three of the four also had sleep apnea. Each was a simplex case without a remarkable family history. Using WES, we identified AHDC1 de novo truncating mutations that most likely cause this genetic syndrome.
Keywords: Child; Child, Preschool; DNA-Binding Proteins; Exome; Female; Humans; Infant; Intellectual Disability; Language Development Disorders; Male; Muscle Hypotonia; Mutation; Sleep Apnea Syndromes; Syndrome

Diamond-Blackfan anemia with mandibulofacial dystostosis is heterogeneous, including the novel DBA genes TSR2 and RPS28. - Gripp, Karen W; Curry, Cynthia; Olney, Ann Haskins; Sandoval, Claudio; Fisher, Jamie; Chong, Jessica Xiao-Ling; Pilchman, Lisa; Sahraoui, Rebecca; Stabley, Deborah L; Sol-Church, Katia (Am J Med Genet A, 2014)
Patients with physical findings suggestive of Treacher Collins syndrome (TCS) or mandibulofacial dysostosis (MFD) and macrocytic anemia diagnostic of Diamond-Blackfan anemia (DBA) have been reported. Disease-causing genes have been identified for TCS and other MFDs. Mutations in several ribosomal protein genes and the transcription factor GATA1 result in DBA. However, no disease-causing mutation had been identified in the reported patients with the combination of TCS/MFD and DBA phenotype, and we hypothesized that pathogenic mutations in a single gene could be identified using whole exome analysis. We studied probands from six unrelated families. Combining exome analysis and Sanger sequencing, we identified likely pathogenic mutations in 5/6 families. Two mutations in unrelated families were seen in RPS26, the known DBA10 gene. One variant was predicted to affect mRNA splicing, and the other to lead to protein truncation. In another family a likely pathogenic X-linked mutation affecting a highly conserved residue was found in TSR2, which encodes a direct binding partner of RPS26. De novo mutations affecting the RPS28 start codon were found in two unrelated probands, identifying RPS28 as a novel disease gene. We conclude that the phenotype combining features of TCS with DBA is genetically heterogeneous. Each of the pathogenic variants identified is predicted to impede ribosome biogenesis, which in turn could result in altered cell growth and proliferation, causing abnormal embryologic development, defective erythropoiesis and reduced growth. The phenotype combining TCS/MFD and DBA is highly variable, overlaps with DBA and lies within the phenotypic spectrum of ribosomopathies. © 2014 Wiley Periodicals, Inc.
Keywords: Adult; Anemia, Diamond-Blackfan; Apoptosis Regulatory Proteins; Child, Preschool; Exome; Family; Female; Genetic Heterogeneity; Humans; Infant; Infant, Newborn; Male; Mandibulofacial Dysostosis; Pedigree; Phenotype; Pregnancy; Ribosomal Proteins; Young Adult

Exonic duplication CNV of NDRG1 associated with autosomal-recessive HMSN-Lom/CMT4D. - Okamoto, Yuji; Goksungur, Meryem Tuba; Pehlivan, Davut; Beck, Christine R; Gonzaga-Jauregui, Claudia; Muzny, Donna M; Atik, Mehmed M; Carvalho, Claudia M B; Matur, Zeliha; Bayraktar, Serife; Boone, Philip M; Akyuz, Kaya; et al. (Genet Med, 2014)
PURPOSE: Copy-number variations as a mutational mechanism contribute significantly to human disease. Approximately one-half of the patients with Charcot-Marie-Tooth (CMT) disease have a 1.4 Mb duplication copy-number variation as the cause of their neuropathy. However, non-CMT1A neuropathy patients rarely have causative copy-number variations, and to date, autosomal-recessive disease has not been associated with copy-number variation as a mutational mechanism. METHODS: We performed Agilent 8 × 60 K array comparative genomic hybridization on DNA from 12 recessive Turkish families with CMT disease. Additional molecular studies were conducted to detect breakpoint junctions and to evaluate gene expression levels in a family in which we detected an intragenic duplication copy-number variation. RESULTS: We detected an ~6.25 kb homozygous intragenic duplication in NDRG1, a gene known to be causative for recessive HMSNL/CMT4D, in three individuals from a Turkish family with CMT neuropathy. Further studies showed that this intragenic copy-number variation resulted in a homozygous duplication of exons 6-8 that caused decreased mRNA expression of NDRG1. CONCLUSION: Exon-focused high-resolution array comparative genomic hybridization enables the detection of copy-number variation carrier states in recessive genes, particularly small copy-number variations encompassing or disrupting single genes. In families for whom a molecular diagnosis has not been elucidated by conventional clinical assays, an assessment for copy-number variations in known CMT genes might be considered.
Keywords: Adult; Base Sequence; Cell Cycle Proteins; Charcot-Marie-Tooth Disease; Comparative Genomic Hybridization; DNA Copy Number Variations; Female; Gene Duplication; Gene Expression; Genes, Recessive; Humans; Intracellular Signaling Peptides and Proteins; Male; Mutation; Refsum Disease; Sequence Analysis, DNA; Turkey; Young Adult

Expanding the phenotypic spectrum of ARID1B-mediated disorders and identification of altered cell-cycle dynamics due to ARID1B haploinsufficiency. - Sim, Joe C H; White, Susan M; Fitzpatrick, Elizabeth; Wilson, Gabrielle R; Gillies, Greta; Pope, Kate; Mountford, Hayley S; Torring, Pernille M; McKee, Shane; Vulto-van Silfhout, Anneke T; Jhangiani, Shalini N; Muzny, Donna M; et al. (Orphanet J Rare Dis, 2014)
BACKGROUND: Mutations in genes encoding components of the Brahma-associated factor (BAF) chromatin remodeling complex have recently been shown to contribute to multiple syndromes characterised by developmental delay and intellectual disability. ARID1B mutations have been identified as the predominant cause of Coffin-Siris syndrome and have also been shown to be a frequent cause of nonsyndromic intellectual disability. Here, we investigate the molecular basis of a patient with an overlapping but distinctive phenotype of intellectual disability, plantar fat pads and facial dysmorphism. METHODS/RESULTS: High density microarray analysis of the patient demonstrated a heterozygous deletion at 6q25.3, which resulted in the loss of four genes including AT Rich Interactive Domain 1B (ARID1B). Subsequent quantitative real-time PCR analysis revealed ARID1B haploinsufficiency in the patient. Analysis of both patient-derived and ARID1B knockdown fibroblasts after serum starvation demonstrated delayed cell cycle re-entry associated with reduced cell number in the S1 phase. Based on the patient's distinctive phenotype, we ascertained four additional patients and identified heterozygous de novo ARID1B frameshift or nonsense mutations in all of them. CONCLUSIONS: This study broadens the spectrum of ARID1B associated phenotypes by describing a distinctive phenotype including plantar fat pads but lacking the hypertrichosis or fifth nail hypoplasia associated with Coffin-Siris syndrome. We present the first direct evidence in patient-derived cells that alterations in cell cycle contribute to the underlying pathogenesis of syndromes associated with ARID1B haploinsufficiency.
Keywords: Abnormalities, Multiple; Cell Cycle; Chromatin Assembly and Disassembly; DNA-Binding Proteins; Face; Female; Hand Deformities, Congenital; Haploinsufficiency; Humans; Intellectual Disability; Male; Micrognathism; Neck; Transcription Factors

A form of the metabolic syndrome associated with mutations in DYRK1B. - Keramati, Ali R; Fathzadeh, Mohsen; Go, Gwang-Woong; Singh, Rajvir; Choi, Murim; Faramarzi, Saeed; Mane, Shrikant; Kasaei, Mohammad; Sarajzadeh-Fard, Kazem; Hwa, John; Kidd, Kenneth K; Babaee Bigi, Mohammad A; et al. (N Engl J Med, 2014)
BACKGROUND: Genetic analysis has been successful in identifying causative mutations for individual cardiovascular risk factors. Success has been more limited in mapping susceptibility genes for clusters of cardiovascular risk traits, such as those in the metabolic syndrome. METHODS: We identified three large families with coinheritance of early-onset coronary artery disease, central obesity, hypertension, and diabetes. We used linkage analysis and whole-exome sequencing to identify the disease-causing gene. RESULTS: A founder mutation was identified in DYRK1B, substituting cysteine for arginine at position 102 in the highly conserved kinase-like domain. The mutation precisely cosegregated with the clinical syndrome in all the affected family members and was absent in unaffected family members and unrelated controls. Functional characterization of the disease gene revealed that nonmutant protein encoded by DYRK1B inhibits the SHH (sonic hedgehog) and Wnt signaling pathways and consequently enhances adipogenesis. Furthermore, DYRK1B promoted the expression of the key gluconeogenic enzyme glucose-6-phosphatase. The R102C allele showed gain-of-function activities by potentiating these effects. A second mutation, substituting proline for histidine 90, was found to cosegregate with a similar clinical syndrome in an ethnically distinct family. CONCLUSIONS: These findings indicate a role for DYRK1B in adipogenesis and glucose homeostasis and associate its altered function with an inherited form of the metabolic syndrome. (Funded by the National Institutes of Health.).
Keywords: Coronary Artery Disease; Diabetes Mellitus, Type 2; Exome; Female; Founder Effect; Genetic Linkage; Genetic Predisposition to Disease; Glucose-6-Phosphatase; Humans; Hypertension; Male; Metabolic Syndrome; Mutation; Obesity, Abdominal; Pedigree; Protein-Serine-Threonine Kinases; Protein-Tyrosine Kinases

The genetic basis of DOORS syndrome: an exome-sequencing study. - Campeau, Philippe M; Kasperaviciute, Dalia; Lu, James T; Burrage, Lindsay C; Kim, Choel; Hori, Mutsuki; Powell, Berkley R; Stewart, Fiona; Félix, Têmis Maria; van den Ende, Jenneke; Wisniewska, Marzena; Kayserili, Hülya; et al. (Lancet Neurol, 2014)
BACKGROUND: Deafness, onychodystrophy, osteodystrophy, mental retardation, and seizures (DOORS) syndrome is a rare autosomal recessive disorder of unknown cause. We aimed to identify the genetic basis of this syndrome by sequencing most coding exons in affected individuals. METHODS: Through a search of available case studies and communication with collaborators, we identified families that included at least one individual with at least three of the five main features of the DOORS syndrome: deafness, onychodystrophy, osteodystrophy, intellectual disability, and seizures. Participants were recruited from 26 centres in 17 countries. Families described in this study were enrolled between Dec 1, 2010, and March 1, 2013. Collaborating physicians enrolling participants obtained clinical information and DNA samples from the affected child and both parents if possible. We did whole-exome sequencing in affected individuals as they were enrolled, until we identified a candidate gene, and Sanger sequencing to confirm mutations. We did expression studies in human fibroblasts from one individual by real-time PCR and western blot analysis, and in mouse tissues by immunohistochemistry and real-time PCR. FINDINGS: 26 families were included in the study. We did exome sequencing in the first 17 enrolled families; we screened for TBC1D24 by Sanger sequencing in subsequent families. We identified TBC1D24 mutations in 11 individuals from nine families (by exome sequencing in seven families, and Sanger sequencing in two families). 18 families had individuals with all five main features of DOORS syndrome, and TBC1D24 mutations were identified in half of these families. The seizure types in individuals with TBC1D24 mutations included generalised tonic-clonic, complex partial, focal clonic, and infantile spasms. Of the 18 individuals with DOORS syndrome from 17 families without TBC1D24 mutations, eight did not have seizures and three did not have deafness. In expression studies, some mutations abrogated TBC1D24 mRNA stability. We also detected Tbc1d24 expression in mouse phalangeal chondrocytes and calvaria, which suggests a role of TBC1D24 in skeletogenesis. INTERPRETATION: Our findings suggest that mutations in TBC1D24 seem to be an important cause of DOORS syndrome and can cause diverse phenotypes. Thus, individuals with DOORS syndrome without deafness and seizures but with the other features should still be screened for TBC1D24 mutations. More information is needed to understand the cellular roles of TBC1D24 and identify the genes responsible for DOORS phenotypes in individuals who do not have a mutation in TBC1D24. FUNDING: US National Institutes of Health, the CIHR (Canada), the NIHR (UK), the Wellcome Trust, the Henry Smith Charity, and Action Medical Research.
Keywords: Adolescent; Carrier Proteins; Child; Child, Preschool; Craniofacial Abnormalities; Exome; Female; Hand Deformities, Congenital; Hearing Loss, Sensorineural; Humans; Infant; Intellectual Disability; Internationality; Male; Nails, Malformed; Phenotype; Sequence Analysis, DNA; Young Adult

Germ-line and somatic DICER1 mutations in pineoblastoma. - de Kock, Leanne; Sabbaghian, Nelly; Druker, Harriet; Weber, Evan; Hamel, Nancy; Miller, Suzanne; Choong, Catherine S; Gottardo, Nicholas G; Kees, Ursula R; Rednam, Surya P; van Hest, Liselotte P; Jongmans, Marjolijn C; et al. (Acta Neuropathol, 2014)
Germ-line RB-1 mutations predispose to pineoblastoma (PinB), but other predisposing genetic factors are not well established. We recently identified a germ-line DICER1 mutation in a child with a PinB. This was accompanied by loss of heterozygosity (LOH) of the wild-type allele within the tumour. We set out to establish the prevalence of DICER1 mutations in an opportunistically ascertained series of PinBs. Twenty-one PinB cases were studied: Eighteen cases had not undergone previous testing for DICER1 mutations; three patients were known carriers of germ-line DICER1 mutations. The eighteen PinBs were sequenced by Sanger and/or Fluidigm-based next-generation sequencing to identify DICER1 mutations in blood gDNA and/or tumour gDNA. Testing for somatic DICER1 mutations was also conducted on one case with a known germ-line DICER1 mutation. From the eighteen PinBs, we identified four deleterious DICER1 mutations, three of which were germ line in origin, and one for which a germ line versus somatic origin could not be determined; in all four, the second allele was also inactivated leading to complete loss of DICER1 protein. No somatic DICER1 RNase IIIb mutations were identified. One PinB arising in a germ-line DICER1 mutation carrier was found to have LOH. This study suggests that germ-line DICER1 mutations make a clinically significant contribution to PinB, establishing DICER1 as an important susceptibility gene for PinB and demonstrates PinB to be a manifestation of a germ-line DICER1 mutation. The means by which the second allele is inactivated may differ from other DICER1-related tumours.
Keywords: Adolescent; Brain Neoplasms; Child; Child, Preschool; DEAD-box RNA Helicases; DNA Mutational Analysis; Family Health; Female; Germ-Line Mutation; Humans; Infant; Male; Pineal Gland; Pinealoma; Ribonuclease III; Young Adult

Gigantism and acromegaly due to Xq26 microduplications and GPR101 mutation. - Trivellin, Giampaolo; Daly, Adrian F; Faucz, Fabio R; Yuan, Bo; Rostomyan, Liliya; Larco, Darwin O; Schernthaner-Reiter, Marie Helene; Szarek, Eva; Leal, Letícia F; Caberg, Jean-Hubert; Castermans, Emilie; Villa, Chiara; et al. (N Engl J Med, 2014)
BACKGROUND: Increased secretion of growth hormone leads to gigantism in children and acromegaly in adults; the genetic causes of gigantism and acromegaly are poorly understood. METHODS: We performed clinical and genetic studies of samples obtained from 43 patients with gigantism and then sequenced an implicated gene in samples from 248 patients with acromegaly. RESULTS: We observed microduplication on chromosome Xq26.3 in samples from 13 patients with gigantism; of these samples, 4 were obtained from members of two unrelated kindreds, and 9 were from patients with sporadic cases. All the patients had disease onset during early childhood. Of the patients with gigantism who did not carry an Xq26.3 microduplication, none presented before the age of 5 years. Genomic characterization of the Xq26.3 region suggests that the microduplications are generated during chromosome replication and that they contain four protein-coding genes. Only one of these genes, GPR101, which encodes a G-protein-coupled receptor, was overexpressed in patients' pituitary lesions. We identified a recurrent GPR101 mutation (p.E308D) in 11 of 248 patients with acromegaly, with the mutation found mostly in tumors. When the mutation was transfected into rat GH3 cells, it led to increased release of growth hormone and proliferation of growth hormone-producing cells. CONCLUSIONS: We describe a pediatric disorder (which we have termed X-linked acrogigantism [X-LAG]) that is caused by an Xq26.3 genomic duplication and is characterized by early-onset gigantism resulting from an excess of growth hormone. Duplication of GPR101 probably causes X-LAG. We also found a recurrent mutation in GPR101 in some adults with acromegaly. (Funded by the Eunice Kennedy Shriver National Institute of Child Health and Human Development and others.).
Keywords: Acromegaly; Adolescent; Adult; Age of Onset; Child; Child, Preschool; Chromosome Duplication; Chromosomes, Human, X; Female; Gigantism; Human Growth Hormone; Humans; Infant; Male; Mutation; Phenotype; Protein Conformation; Receptors, G-Protein-Coupled

Heterozygous de novo and inherited mutations in the smooth muscle actin (ACTG2) gene underlie megacystis-microcolon-intestinal hypoperistalsis syndrome. - Wangler, Michael F; Gonzaga-Jauregui, Claudia; Gambin, Tomasz; Penney, Samantha; Moss, Timothy; Chopra, Atul; Probst, Frank J; Xia, Fan; Yang, Yaping; Werlin, Steven; Eglite, Ieva; Kornejeva, Liene; et al. (PLoS Genet, 2014)
Megacystis-microcolon-intestinal hypoperistalsis syndrome (MMIHS) is a rare disorder of enteric smooth muscle function affecting the intestine and bladder. Patients with this severe phenotype are dependent on total parenteral nutrition and urinary catheterization. The cause of this syndrome has remained a mystery since Berdon's initial description in 1976. No genes have been clearly linked to MMIHS. We used whole-exome sequencing for gene discovery followed by targeted Sanger sequencing in a cohort of patients with MMIHS and intestinal pseudo-obstruction. We identified heterozygous ACTG2 missense variants in 15 unrelated subjects, ten being apparent de novo mutations. Ten unique variants were detected, of which six affected CpG dinucleotides and resulted in missense mutations at arginine residues, perhaps related to biased usage of CpG containing codons within actin genes. We also found some of the same heterozygous mutations that we observed as apparent de novo mutations in MMIHS segregating in families with intestinal pseudo-obstruction, suggesting that ACTG2 is responsible for a spectrum of smooth muscle disease. ACTG2 encodes γ2 enteric actin and is the first gene to be clearly associated with MMIHS, suggesting an important role for contractile proteins in enteric smooth muscle disease.
Keywords: Abnormalities, Multiple; Actins; Adolescent; Adult; Child; Child, Preschool; Colon; Exome; Female; Heterozygote; Humans; Intestinal Pseudo-Obstruction; Male; Muscle, Smooth; Mutation; Urinary Bladder

Human CLP1 mutations alter tRNA biogenesis, affecting both peripheral and central nervous system function. - Karaca, Ender; Weitzer, Stefan; Pehlivan, Davut; Shiraishi, Hiroshi; Gogakos, Tasos; Hanada, Toshikatsu; Jhangiani, Shalini N; Wiszniewski, Wojciech; Withers, Marjorie; Campbell, Ian M; Erdin, Serkan; Isikay, Sedat; et al. (Cell, 2014)
CLP1 is a RNA kinase involved in tRNA splicing. Recently, CLP1 kinase-dead mice were shown to display a neuromuscular disorder with loss of motor neurons and muscle paralysis. Human genome analyses now identified a CLP1 homozygous missense mutation (p.R140H) in five unrelated families, leading to a loss of CLP1 interaction with the tRNA splicing endonuclease (TSEN) complex, largely reduced pre-tRNA cleavage activity, and accumulation of linear tRNA introns. The affected individuals develop severe motor-sensory defects, cortical dysgenesis, and microcephaly. Mice carrying kinase-dead CLP1 also displayed microcephaly and reduced cortical brain volume due to the enhanced cell death of neuronal progenitors that is associated with reduced numbers of cortical neurons. Our data elucidate a neurological syndrome defined by CLP1 mutations that impair tRNA splicing. Reduction of a founder mutation to homozygosity illustrates the importance of rare variations in disease and supports the clan genomics hypothesis.
Keywords: Abnormalities, Multiple; Animals; Central Nervous System Diseases; Cerebrum; Child, Preschool; Endoribonucleases; Female; Fibroblasts; Humans; Infant; Male; Mice; Mice, Inbred CBA; Microcephaly; Mutation, Missense; Nuclear Proteins; Peripheral Nervous System Diseases; Phosphotransferases; RNA, Transfer; Transcription Factors

Individual exome analysis in diagnosis and management of paediatric liver failure of indeterminate aetiology. - Vilarinho, Sílvia; Choi, Murim; Jain, Dhanpat; Malhotra, Ajay; Kulkarni, Sanjay; Pashankar, Dinesh; Phatak, Uma; Patel, Mohini; Bale, Allen; Mane, Shrikant; Lifton, Richard P; Mistry, Pramod K (J Hepatol, 2014)
BACKGROUND & AIMS: In children with liver failure, as many as half remain of indeterminate aetiology. This hinders timely consideration of optimal treatment options. We posit that a significant subset of these children harbour known inherited metabolic liver diseases with atypical presentation or novel inborn errors of metabolism. We investigated the utility of whole-exome sequencing in three children with advanced liver disease of indeterminate aetiology. METHODS: Patient 1 was a 10 year-old female diagnosed with Wilson disease but no detectable ATP7B mutations, and decompensated liver cirrhosis who underwent liver transplant and subsequently developed onset of neurodegenerative disease. Patient 2 was a full-term 2 day-old male with fatal acute liver failure of indeterminate aetiology. Patient 3 was an 8 year-old female with progressive syndromic cholestasis of unknown aetiology since age 3 months. RESULTS: Unbiased whole-exome sequencing of germline DNA revealed homozygous mutations in MPV17 and SERAC1 as the disease causing genes in patient 1 and 2, respectively. This is the first demonstration of SERAC1 loss-of-function associated fatal acute liver failure. Patient 1 expands the phenotypic spectrum of the MPV17-related hepatocerebral mitochondrial DNA depletion syndrome. Patient 3 was found to have syndromic cholestasis due to bi-allelic NOTCH2 mutations. CONCLUSIONS: Our findings validate the application of whole-exome sequencing in the diagnosis and management of children with advanced liver disease of indeterminate aetiology, with the potential to enhance optimal selection of treatment options and adequate counselling of families. Moreover, whole-exome sequencing revealed a hitherto unrecognized phenotypic spectrum of inherited metabolic liver diseases.
Keywords: Amino Acid Sequence; Base Sequence; Carboxylic Ester Hydrolases; Child; Cholestasis; DNA Mutational Analysis; End Stage Liver Disease; Exome; Fatal Outcome; Female; Genes, Recessive; Hepatolenticular Degeneration; Heterozygote; Homozygote; Humans; Infant, Newborn; Liver Failure; Liver Failure, Acute; Male; Membrane Proteins; Mitochondrial Proteins; Molecular Sequence Data; Pedigree; Receptor, Notch2; RNA Splice Sites; Sequence Homology, Amino Acid

Informed consent for exome sequencing research in families with genetic disease: the emerging issue of incidental findings. - Bergner, Amanda L; Bollinger, Juli; Raraigh, Karen S; Tichnell, Crystal; Murray, Brittney; Blout, Carrie Lynn; Telegrafi, Aida Bytyci; James, Cynthia A (Am J Med Genet A, 2014)
Genomic sequencing technology is increasingly used in genetic research. Studies of informed consent for exome and genome sequencing (ES/GS) research have largely involved hypothetical scenarios or healthy individuals enrolling in population-based studies. Studies have yet to explore the consent experiences of adults with inherited disease. We conducted a qualitative interview study of 15 adults recently enrolled in a large-scale ES/GS study (11 affected adults, four parents of affected children). Our study had two goals: (1) to explore three theoretical barriers to consent for ES/GS research (interpretive/technical complexity, possibility of incidental findings, and risks of loss of privacy); and (2) to explore how interviewees experienced the consent process. Interviewees could articulate study goals and processes, describe incidental findings, discuss risks of privacy loss, and reflect on their consent experience. Few expected the study would identify the genetic cause of their condition. All elected to receive incidental findings. Interviewees acknowledged paying little attention to potential implications of incidental findings in light of more pressing goals of supporting research regarding their own medical conditions. Interviewees suggested that experience living with a genetic condition prepared them to adjust to incidental findings. Interviewees also expressed little concern about loss of confidentiality of study data. Some experienced the consent process as very long. None desired reconsent prior to return of study results. Families with inherited disease likely would benefit from a consent process in which study risks and benefits were discussed in the context of prior experiences with genetic research and genetic disease.
Keywords: Adolescent; Adult; Aged; Confidentiality; Ethics, Medical; Exome; Family; Female; Genetic Diseases, Inborn; Genetic Research; High-Throughput Nucleotide Sequencing; Humans; Incidental Findings; Informed Consent; Male; Middle Aged; Young Adult

Laterality defects other than situs inversus totalis in primary ciliary dyskinesia: insights into situs ambiguus and heterotaxy. - Shapiro, Adam J; Davis, Stephanie D; Ferkol, Thomas; Dell, Sharon D; Rosenfeld, Margaret; Olivier, Kenneth N; Sagel, Scott D; Milla, Carlos; Zariwala, Maimoona A; Wolf, Whitney; Carson, Johnny L; Hazucha, Milan J; et al. (Chest, 2014)
BACKGROUND: Motile cilia dysfunction causes primary ciliary dyskinesia (PCD), situs inversus totalis (SI), and a spectrum of laterality defects, yet the prevalence of laterality defects other than SI in PCD has not been prospectively studied. METHODS: In this prospective study, participants with suspected PCD were referred to our multisite consortium. We measured nasal nitric oxide (nNO) level, examined cilia with electron microscopy, and analyzed PCD-causing gene mutations. Situs was classified as (1) situs solitus (SS), (2) SI, or (3) situs ambiguus (SA), including heterotaxy. Participants with hallmark electron microscopic defects, biallelic gene mutations, or both were considered to have classic PCD. RESULTS: Of 767 participants (median age, 8.1 years, range, 0.1-58 years), classic PCD was defined in 305, including 143 (46.9%), 125 (41.0%), and 37 (12.1%) with SS, SI, and SA, respectively. A spectrum of laterality defects was identified with classic PCD, including 2.6% and 2.3% with SA plus complex or simple cardiac defects, respectively; 4.6% with SA but no cardiac defect; and 2.6% with an isolated possible laterality defect. Participants with SA and classic PCD had a higher prevalence of PCD-associated respiratory symptoms vs SA control participants (year-round wet cough, P < .001; year-round nasal congestion, P = .015; neonatal respiratory distress, P = .009; digital clubbing, P = .021) and lower nNO levels (median, 12 nL/min vs 252 nL/min; P < .001). CONCLUSIONS: At least 12.1% of patients with classic PCD have SA and laterality defects ranging from classic heterotaxy to subtle laterality defects. Specific clinical features of PCD and low nNO levels help to identify PCD in patients with laterality defects. TRIAL REGISTRY: ClinicalTrials.gov; No.: NCT00323167; URL: www.clinicaltrials.gov.
Keywords: Adolescent; Adult; Biopsy; Child; Child, Preschool; Cilia; DNA; DNA Mutational Analysis; Female; Humans; Infant; Infant, Newborn; Kartagener Syndrome; Male; Microscopy, Electron, Transmission; Middle Aged; Mutation; Prevalence; Prospective Studies; Tomography, X-Ray Computed; United States; Young Adult

Loss-of-function HDAC8 mutations cause a phenotypic spectrum of Cornelia de Lange syndrome-like features, ocular hypertelorism, large fontanelle and X-linked inheritance. - Kaiser, Frank J; Ansari, Morad; Braunholz, Diana; Concepción Gil-Rodríguez, María; Decroos, Christophe; Wilde, Jonathan J; Fincher, Christopher T; Kaur, Maninder; Bando, Masashige; Amor, David J; Atwal, Paldeep S; Bahlo, Melanie; et al. (Hum Mol Genet, 2014)
Cornelia de Lange syndrome (CdLS) is a multisystem genetic disorder with distinct facies, growth failure, intellectual disability, distal limb anomalies, gastrointestinal and neurological disease. Mutations in NIPBL, encoding a cohesin regulatory protein, account for >80% of cases with typical facies. Mutations in the core cohesin complex proteins, encoded by the SMC1A, SMC3 and RAD21 genes, together account for ∼5% of subjects, often with atypical CdLS features. Recently, we identified mutations in the X-linked gene HDAC8 as the cause of a small number of CdLS cases. Here, we report a cohort of 38 individuals with an emerging spectrum of features caused by HDAC8 mutations. For several individuals, the diagnosis of CdLS was not considered prior to genomic testing. Most mutations identified are missense and de novo. Many cases are heterozygous females, each with marked skewing of X-inactivation in peripheral blood DNA. We also identified eight hemizygous males who are more severely affected. The craniofacial appearance caused by HDAC8 mutations overlaps that of typical CdLS but often displays delayed anterior fontanelle closure, ocular hypertelorism, hooding of the eyelids, a broader nose and dental anomalies, which may be useful discriminating features. HDAC8 encodes the lysine deacetylase for the cohesin subunit SMC3 and analysis of the functional consequences of the missense mutations indicates that all cause a loss of enzymatic function. These data demonstrate that loss-of-function mutations in HDAC8 cause a range of overlapping human developmental phenotypes, including a phenotypically distinct subgroup of CdLS.
Keywords: Amino Acid Sequence; Child; Child, Preschool; Cohort Studies; Cranial Fontanelles; De Lange Syndrome; Eye Abnormalities; Female; Genes, X-Linked; Histone Deacetylases; Humans; Hypertelorism; Infant; Male; Molecular Sequence Data; Mutation, Missense; Phenotype; Repressor Proteins; Sequence Alignment

Microcephaly, epilepsy, and neonatal diabetes due to compound heterozygous mutations in IER3IP1: insights into the natural history of a rare disorder. - Shalev, Stavit A; Tenenbaum-Rakover, Yardena; Horovitz, Yoseph; Paz, Veronica P; Ye, Honggang; Carmody, David; Highland, Heather M; Boerwinkle, Eric; Hanis, Craig L; Muzny, Donna M; Gibbs, Richard A; Bell, Graeme I; et al. (Pediatr Diabetes, 2014)
Neonatal diabetes mellitus is known to have over 20 different monogenic causes. A syndrome of permanent neonatal diabetes along with primary microcephaly with simplified gyral pattern associated with severe infantile epileptic encephalopathy was recently described in two independent reports in which disease-causing homozygous mutations were identified in the immediate early response-3 interacting protein-1 (IER3IP1) gene. We report here an affected male born to a non-consanguineous couple who was noted to have insulin-requiring permanent neonatal diabetes, microcephaly, and generalized seizures. He was also found to have cortical blindness, severe developmental delay and numerous dysmorphic features. He experienced a slow improvement but not abrogation of seizure frequency and severity on numerous anti-epileptic agents. His clinical course was further complicated by recurrent respiratory tract infections and he died at 8 years of age. Whole exome sequencing was performed on DNA from the proband and parents. He was found to be a compound heterozygote with two different mutations in IER3IP1: p.Val21Gly (V21G) and a novel frameshift mutation p.Phe27fsSer*25. IER3IP1 is a highly conserved protein with marked expression in the cerebral cortex and in beta cells. This is the first reported case of compound heterozygous mutations within IER3IP1 resulting in neonatal diabetes. The triad of microcephaly, generalized seizures, and permanent neonatal diabetes should prompt screening for mutations in IER3IP1. As mutations in genes such as NEUROD1 and PTF1A could cause a similar phenotype, next-generation sequencing approaches-such as exome sequencing reported here-may be an efficient means of uncovering a diagnosis in future cases.
Keywords: Amino Acid Substitution; Blindness, Cortical; Carrier Proteins; Developmental Disabilities; Diabetes Mellitus; Epilepsy, Generalized; Fatal Outcome; Frameshift Mutation; Heterozygote; Humans; Infant, Newborn; Infant, Newborn, Diseases; Male; Membrane Proteins; Microcephaly; Neurologic Manifestations; Point Mutation; Severity of Illness Index

Molecular findings among patients referred for clinical whole-exome sequencing. - Yang, Yaping; Muzny, Donna M; Xia, Fan; Niu, Zhiyv; Person, Richard; Ding, Yan; Ward, Patricia; Braxton, Alicia; Wang, Min; Buhay, Christian; Veeraraghavan, Narayanan; Hawes, Alicia; et al. (JAMA, 2014)
IMPORTANCE: Clinical whole-exome sequencing is increasingly used for diagnostic evaluation of patients with suspected genetic disorders. OBJECTIVE: To perform clinical whole-exome sequencing and report (1) the rate of molecular diagnosis among phenotypic groups, (2) the spectrum of genetic alterations contributing to disease, and (3) the prevalence of medically actionable incidental findings such as FBN1 mutations causing Marfan syndrome. DESIGN, SETTING, AND PATIENTS: Observational study of 2000 consecutive patients with clinical whole-exome sequencing analyzed between June 2012 and August 2014. Whole-exome sequencing tests were performed at a clinical genetics laboratory in the United States. Results were reported by clinical molecular geneticists certified by the American Board of Medical Genetics and Genomics. Tests were ordered by the patient's physician. The patients were primarily pediatric (1756 [88%]; mean age, 6 years; 888 females [44%], 1101 males [55%], and 11 fetuses [1% gender unknown]), demonstrating diverse clinical manifestations most often including nervous system dysfunction such as developmental delay. MAIN OUTCOMES AND MEASURES: Whole-exome sequencing diagnosis rate overall and by phenotypic category, mode of inheritance, spectrum of genetic events, and reporting of incidental findings. RESULTS: A molecular diagnosis was reported for 504 patients (25.2%) with 58% of the diagnostic mutations not previously reported. Molecular diagnosis rates for each phenotypic category were 143/526 (27.2%; 95% CI, 23.5%-31.2%) for the neurological group, 282/1147 (24.6%; 95% CI, 22.1%-27.2%) for the neurological plus other organ systems group, 30/83 (36.1%; 95% CI, 26.1%-47.5%) for the specific neurological group, and 49/244 (20.1%; 95% CI, 15.6%-25.8%) for the nonneurological group. The Mendelian disease patterns of the 527 molecular diagnoses included 280 (53.1%) autosomal dominant, 181 (34.3%) autosomal recessive (including 5 with uniparental disomy), 65 (12.3%) X-linked, and 1 (0.2%) mitochondrial. Of 504 patients with a molecular diagnosis, 23 (4.6%) had blended phenotypes resulting from 2 single gene defects. About 30% of the positive cases harbored mutations in disease genes reported since 2011. There were 95 medically actionable incidental findings in genes unrelated to the phenotype but with immediate implications for management in 92 patients (4.6%), including 59 patients (3%) with mutations in genes recommended for reporting by the American College of Medical Genetics and Genomics. CONCLUSIONS AND RELEVANCE: Whole-exome sequencing provided a potential molecular diagnosis for 25% of a large cohort of patients referred for evaluation of suspected genetic conditions, including detection of rare genetic events and new mutations contributing to disease. The yield of whole-exome sequencing may offer advantages over traditional molecular diagnostic approaches in certain patients.
Keywords: Adolescent; Adult; Child; Child, Preschool; Exome; Female; Fetus; Genetic Diseases, Inborn; Genetic Testing; Genomics; Humans; Incidental Findings; Infant; Infant, Newborn; Male; Molecular Diagnostic Techniques; Mutation; Phenotype; Referral and Consultation; Sequence Analysis, DNA

Monoallelic and biallelic mutations in MAB21L2 cause a spectrum of major eye malformations. - Rainger, Joe; Pehlivan, Davut; Johansson, Stefan; Bengani, Hemant; Sanchez-Pulido, Luis; Williamson, Kathleen A; Ture, Mehmet; Barker, Heather; Rosendahl, Karen; Spranger, Jürgen; Horn, Denise; Meynert, Alison; et al. (Am J Hum Genet, 2014)
We identified four different missense mutations in the single-exon gene MAB21L2 in eight individuals with bilateral eye malformations from five unrelated families via three independent exome sequencing projects. Three mutational events altered the same amino acid (Arg51), and two were identical de novo mutations (c.151C>T [p.Arg51Cys]) in unrelated children with bilateral anophthalmia, intellectual disability, and rhizomelic skeletal dysplasia. c.152G>A (p.Arg51His) segregated with autosomal-dominant bilateral colobomatous microphthalmia in a large multiplex family. The fourth heterozygous mutation (c.145G>A [p.Glu49Lys]) affected an amino acid within two residues of Arg51 in an adult male with bilateral colobomata. In a fifth family, a homozygous mutation (c.740G>A [p.Arg247Gln]) altering a different region of the protein was identified in two male siblings with bilateral retinal colobomata. In mouse embryos, Mab21l2 showed strong expression in the developing eye, pharyngeal arches, and limb bud. As predicted by structural homology, wild-type MAB21L2 bound single-stranded RNA, whereas this activity was lost in all altered forms of the protein. MAB21L2 had no detectable nucleotidyltransferase activity in vitro, and its function remains unknown. Induced expression of wild-type MAB21L2 in human embryonic kidney 293 cells increased phospho-ERK (pERK1/2) signaling. Compared to the wild-type and p.Arg247Gln proteins, the proteins with the Glu49 and Arg51 variants had increased stability. Abnormal persistence of pERK1/2 signaling in MAB21L2-expressing cells during development is a plausible pathogenic mechanism for the heterozygous mutations. The phenotype associated with the homozygous mutation might be a consequence of complete loss of MAB21L2 RNA binding, although the cellular function of this interaction remains unknown.
Keywords: Adult; Alleles; Animals; Anophthalmos; Brain Diseases, Metabolic, Inborn; Coloboma; Corneal Opacity; Exome; Eye Proteins; Female; Gene Expression; HEK293 Cells; Heterozygote; Homozygote; Humans; Intellectual Disability; Intracellular Signaling Peptides and Proteins; Male; Mice; Microcephaly; Microphthalmos; Mutation, Missense; Pedigree; Phenotype; Protein Conformation; Signal Transduction

Multilineage somatic activating mutations in HRAS and NRAS cause mosaic cutaneous and skeletal lesions, elevated FGF23 and hypophosphatemia. - Lim, Young H; Ovejero, Diana; Sugarman, Jeffrey S; Deklotz, Cynthia M C; Maruri, Ann; Eichenfield, Lawrence F; Kelley, Patrick K; Jüppner, Harald; Gottschalk, Michael; Tifft, Cynthia J; Gafni, Rachel I; Boyce, Alison M; et al. (Hum Mol Genet, 2014)
Pathologically elevated serum levels of fibroblast growth factor-23 (FGF23), a bone-derived hormone that regulates phosphorus homeostasis, result in renal phosphate wasting and lead to rickets or osteomalacia. Rarely, elevated serum FGF23 levels are found in association with mosaic cutaneous disorders that affect large proportions of the skin and appear in patterns corresponding to the migration of ectodermal progenitors. The cause and source of elevated serum FGF23 is unknown. In those conditions, such as epidermal and large congenital melanocytic nevi, skin lesions are variably associated with other abnormalities in the eye, brain and vasculature. The wide distribution of involved tissues and the appearance of multiple segmental skin and bone lesions suggest that these conditions result from early embryonic somatic mutations. We report five such cases with elevated serum FGF23 and bone lesions, four with large epidermal nevi and one with a giant congenital melanocytic nevus. Exome sequencing of blood and affected skin tissue identified somatic activating mutations of HRAS or NRAS in each case without recurrent secondary mutation, and we further found that the same mutation is present in dysplastic bone. Our finding of somatic activating RAS mutation in bone, the endogenous source of FGF23, provides the first evidence that elevated serum FGF23 levels, hypophosphatemia and osteomalacia are associated with pathologic Ras activation and may provide insight in the heretofore limited understanding of the regulation of FGF23.
Keywords: Adolescent; Child; Exome; Female; Fibroblast Growth Factors; Gene Expression Regulation, Developmental; GTP Phosphohydrolases; Humans; Hypophosphatemia; Male; Membrane Proteins; Mutation; Nevus; Nevus, Pigmented; Osteomalacia; Proto-Oncogene Proteins p21(ras); Sequence Analysis, DNA; Skin; Skin Neoplasms

Mutation of NLRC4 causes a syndrome of enterocolitis and autoinflammation. - Romberg, Neil; Al Moussawi, Khatoun; Nelson-Williams, Carol; Stiegler, Amy L; Loring, Erin; Choi, Murim; Overton, John; Meffre, Eric; Khokha, Mustafa K; Huttner, Anita J; West, Brian; Podoltsev, Nikolai A; et al. (Nat Genet, 2014)
Upon detection of pathogen-associated molecular patterns, innate immune receptors initiate inflammatory responses. These receptors include cytoplasmic NOD-like receptors (NLRs) whose stimulation recruits and proteolytically activates caspase-1 within the inflammasome, a multiprotein complex. Caspase-1 mediates the production of interleukin-1 family cytokines (IL1FCs), leading to fever and inflammatory cell death (pyroptosis). Mutations that constitutively activate these pathways underlie several autoinflammatory diseases with diverse clinical features. We describe a family with a previously unreported syndrome featuring neonatal-onset enterocolitis, periodic fever, and fatal or near-fatal episodes of autoinflammation. We show that the disease is caused by a de novo gain-of-function mutation in NLRC4 encoding a p.Val341Ala substitution in the HD1 domain of the protein that cosegregates with disease. Mutant NLRC4 causes constitutive IL1FC production and macrophage cell death. Infected macrophages from affected individuals are polarized toward pyroptosis and exhibit abnormal staining for inflammasome components. These findings identify and describe the cause of a life-threatening but treatable autoinflammatory disease that underscores the divergent roles of the NLRC4 inflammasome.
Keywords: Calcium-Binding Proteins; CARD Signaling Adaptor Proteins; Enterocolitis; Exome; Family Health; Fatal Outcome; Female; Humans; Inflammation; Male; Mutation, Missense; Pedigree; Sequence Analysis, DNA; Syndrome

Mutations in LAMA1 cause cerebellar dysplasia and cysts with and without retinal dystrophy. - Aldinger, Kimberly A; Mosca, Stephen J; Tétreault, Martine; Dempsey, Jennifer C; Ishak, Gisele E; Hartley, Taila; Phelps, Ian G; Lamont, Ryan E; O'Day, Diana R; Basel, Donald; Gripp, Karen W; Baker, Laura; et al. (Am J Hum Genet, 2014)
Cerebellar dysplasia with cysts (CDC) is an imaging finding typically seen in combination with cobblestone cortex and congenital muscular dystrophy in individuals with dystroglycanopathies. More recently, CDC was reported in seven children without neuromuscular involvement (Poretti-Boltshauser syndrome). Using a combination of homozygosity mapping and whole-exome sequencing, we identified biallelic mutations in LAMA1 as the cause of CDC in seven affected individuals (from five families) independent from those included in the phenotypic description of Poretti-Boltshauser syndrome. Most of these individuals also have high myopia, and some have retinal dystrophy and patchy increased T2-weighted fluid-attenuated inversion recovery (T2/FLAIR) signal in cortical white matter. In one additional family, we identified two siblings who have truncating LAMA1 mutations in combination with retinal dystrophy and mild cerebellar dysplasia without cysts, indicating that cysts are not an obligate feature associated with loss of LAMA1 function. This work expands the phenotypic spectrum associated with the lamininopathy disorders and highlights the tissue-specific roles played by different laminin-encoding genes.
Keywords: Adult; Alleles; Base Sequence; Cerebellar Cortex; Cerebellar Diseases; Child; Child, Preschool; Cysts; Exome; Female; Humans; Laminin; Male; Muscular Dystrophies; Retinal Dystrophies; Sequence Analysis, DNA; Young Adult

Mutations in PCYT1A, encoding a key regulator of phosphatidylcholine metabolism, cause spondylometaphyseal dysplasia with cone-rod dystrophy. - Hoover-Fong, Julie; Sobreira, Nara; Jurgens, Julie; Modaff, Peggy; Blout, Carrie; Moser, Ann; Kim, Ok-Hwa; Cho, Tae-Joon; Cho, Sung Yoon; Kim, Sang Jin; Jin, Dong-Kyu; Kitoh, Hiroshi; et al. (Am J Hum Genet, 2014)
Keywords: Alleles; Child, Preschool; Choline-Phosphate Cytidylyltransferase; Female; Humans; Infant; Male; Middle Aged; Mutation, Missense; Osteochondrodysplasias; Pedigree; Phosphatidylcholines; Retinitis Pigmentosa

Mutations in PIEZO2 cause Gordon syndrome, Marden-Walker syndrome, and distal arthrogryposis type 5. - McMillin, Margaret J; Beck, Anita E; Chong, Jessica X; Shively, Kathryn M; Buckingham, Kati J; Gildersleeve, Heidi I S; Aracena, Mariana I; Aylsworth, Arthur S; Bitoun, Pierre; Carey, John C; Clericuzio, Carol L; Crow, Yanick J; et al. (Am J Hum Genet, 2014)
Gordon syndrome (GS), or distal arthrogryposis type 3, is a rare, autosomal-dominant disorder characterized by cleft palate and congenital contractures of the hands and feet. Exome sequencing of five GS-affected families identified mutations in piezo-type mechanosensitive ion channel component 2 (PIEZO2) in each family. Sanger sequencing revealed PIEZO2 mutations in five of seven additional families studied (for a total of 10/12 [83%] individuals), and nine families had an identical c.8057G>A (p.Arg2686His) mutation. The phenotype of GS overlaps with distal arthrogryposis type 5 (DA5) and Marden-Walker syndrome (MWS). Using molecular inversion probes for targeted sequencing to screen PIEZO2, we found mutations in 24/29 (82%) DA5-affected families and one of two MWS-affected families. The presence of cleft palate was significantly associated with c.8057G>A (Fisher's exact test, adjusted p value < 0.0001). Collectively, although GS, DA5, and MWS have traditionally been considered separate disorders, our findings indicate that they are etiologically related and perhaps represent variable expressivity of the same condition.
Keywords: Abnormalities, Multiple; Arachnodactyly; Arthrogryposis; Blepharophimosis; Child; Child, Preschool; Cleft Palate; Clubfoot; Connective Tissue Diseases; Contracture; Exome; Female; Hand Deformities, Congenital; Humans; Ion Channels; Male; Mutation; Ophthalmoplegia; Pedigree; Retinal Diseases

Mutations in RSPH1 cause primary ciliary dyskinesia with a unique clinical and ciliary phenotype. - Knowles, Michael R; Ostrowski, Lawrence E; Leigh, Margaret W; Sears, Patrick R; Davis, Stephanie D; Wolf, Whitney E; Hazucha, Milan J; Carson, Johnny L; Olivier, Kenneth N; Sagel, Scott D; Rosenfeld, Margaret; Ferkol, Thomas W; et al. (Am J Respir Crit Care Med, 2014)
RATIONALE: Primary ciliary dyskinesia (PCD) is a genetically heterogeneous recessive disorder of motile cilia, but the genetic cause is not defined for all patients with PCD. OBJECTIVES: To identify disease-causing mutations in novel genes, we performed exome sequencing, follow-up characterization, mutation scanning, and genotype-phenotype studies in patients with PCD. METHODS: Whole-exome sequencing was performed using NimbleGen capture and Illumina HiSeq sequencing. Sanger-based sequencing was used for mutation scanning, validation, and segregation analysis. MEASUREMENTS AND MAIN RESULTS: We performed exome sequencing on an affected sib-pair with normal ultrastructure in more than 85% of cilia. A homozygous splice-site mutation was detected in RSPH1 in both siblings; parents were carriers. Screening RSPH1 in 413 unrelated probands, including 325 with PCD and 88 with idiopathic bronchiectasis, revealed biallelic loss-of-function mutations in nine additional probands. Five affected siblings of probands in RSPH1 families harbored the familial mutations. The 16 individuals with RSPH1 mutations had some features of PCD; however, nasal nitric oxide levels were higher than in patients with PCD with other gene mutations (98.3 vs. 20.7 nl/min; P < 0.0003). Additionally, individuals with RSPH1 mutations had a lower prevalence (8 of 16) of neonatal respiratory distress, and later onset of daily wet cough than typical for PCD, and better lung function (FEV1), compared with 75 age- and sex-matched PCD cases (73.0 vs. 61.8, FEV1 % predicted; P = 0.043). Cilia from individuals with RSPH1 mutations had normal beat frequency (6.1 ± Hz at 25°C), but an abnormal, circular beat pattern. CONCLUSIONS: The milder clinical disease and higher nasal nitric oxide in individuals with biallelic mutations in RSPH1 provides evidence of a unique genotype-phenotype relationship in PCD, and suggests that mutations in RSPH1 may be associated with residual ciliary function.
Keywords: Adolescent; Adult; Child; Cilia; DNA Mutational Analysis; DNA-Binding Proteins; Exome; Female; Genetic Association Studies; Genetic Markers; Genetic Testing; Homozygote; Humans; Kartagener Syndrome; Linear Models; Male; Middle Aged; Mutation; Nasal Mucosa; Sequence Analysis, DNA; Young Adult

Mutations in TBC1D24, a gene associated with epilepsy, also cause nonsyndromic deafness DFNB86. - Rehman, Atteeq U; Santos-Cortez, Regie Lyn P; Morell, Robert J; Drummond, Meghan C; Ito, Taku; Lee, Kwanghyuk; Khan, Asma A; Basra, Muhammad Asim R; Wasif, Naveed; Ayub, Muhammad; Ali, Rana A; Raza, Syed I; et al. (Am J Hum Genet, 2014)
Inherited deafness is clinically and genetically heterogeneous. We recently mapped DFNB86, a locus associated with nonsyndromic deafness, to chromosome 16p. In this study, whole-exome sequencing was performed with genomic DNA from affected individuals from three large consanguineous families in which markers linked to DFNB86 segregate with profound deafness. Analyses of these data revealed homozygous mutation c.208G>T (p.Asp70Tyr) or c.878G>C (p.Arg293Pro) in TBC1D24 as the underlying cause of deafness in the three families. Sanger sequence analysis of TBC1D24 in an additional large family in which deafness segregates with DFNB86 identified the c.208G>T (p.Asp70Tyr) substitution. These mutations affect TBC1D24 amino acid residues that are conserved in orthologs ranging from fruit fly to human. Neither variant was observed in databases of single-nucleotide variants or in 634 chromosomes from ethnically matched control subjects. TBC1D24 in the mouse inner ear was immunolocalized predominantly to spiral ganglion neurons, indicating that DFNB86 deafness might be an auditory neuropathy spectrum disorder. Previously, six recessive mutations in TBC1D24 were reported to cause seizures (hearing loss was not reported) ranging in severity from epilepsy with otherwise normal development to epileptic encephalopathy resulting in childhood death. Two of our four families in which deafness segregates with mutant alleles of TBC1D24 were available for neurological examination. Cosegregation of epilepsy and deafness was not observed in these two families. Although the causal relationship between genotype and phenotype is not presently understood, our findings, combined with published data, indicate that recessive alleles of TBC1D24 can cause either epilepsy or nonsyndromic deafness.
Keywords: Alleles; Amino Acid Sequence; Carrier Proteins; Chromosomes, Human, Pair 16; Consanguinity; Deafness; Epilepsy; Exome; Exons; Female; Genes, Recessive; Genetic Loci; Genome-Wide Association Study; Heterozygote; Homozygote; Humans; Male; Molecular Sequence Data; Mutation; Pakistan; Pedigree; Phenotype; Polymorphism, Single Nucleotide; RNA, Messenger; Sequence Analysis, DNA

Neonatal diabetes, gallbladder agenesis, duodenal atresia, and intestinal malrotation caused by a novel homozygous mutation in RFX6. - Concepcion, Jennifer P; Reh, Christina S; Daniels, Mark; Liu, Xiaoming; Paz, Veronica P; Ye, Honggang; Highland, Heather M; Hanis, Craig L; Greeley, Siri Atma W (Pediatr Diabetes, 2014)
Recently, bi-allelic mutations in the transcription factor RFX6 were described as the cause of a rare condition characterized by neonatal diabetes with pancreatic and biliary hypoplasia and duodenal/jejunal atresia. A male infant developed severe hyperglycemia (446 mg/dL) within 24 h of birth. Acute abdominal concerns by day five necessitated exploratory surgery that revealed duodenal atresia, gallbladder agenesis, annular pancreas and intestinal malrotation. He also exhibited chronic diarrhea and feeding intolerance, cholestatic jaundice, and subsequent liver failure. He died of sepsis at four months old while awaiting liver transplantation. The phenotype of neonatal diabetes with intestinal atresia and biliary agenesis clearly pointed to RFX6 as the causative gene; indeed, whole exome sequencing revealed a novel homozygous RFX6 mutation c.779A>C; p.Lys260Thr (K260T). This missense mutation also changes the consensus 5' splice donor site before intron 7 and is thus predicted to cause disruption in splicing. Both parents, who were not known to be related, were heterozygous carriers. Targeted genetic testing based on consideration of phenotypic features may reveal a cause among the many genes now associated with heterogeneous forms of monogenic neonatal diabetes. Our study demonstrates the feasibility of using modern sequencing technology to identify one such rare cause. Continued research is needed to determine the possible cost-effectiveness of this approach, especially when clear phenotypic clues are absent. Further study of patients with RFX6 mutations should clarify its role in pancreatic, intestinal and enteroendocrine cellular development and explain features such as the diarrhea exhibited in our case.
Keywords: Abnormalities, Multiple; Congenital Abnormalities; Diabetes Mellitus, Type 1; Digestive System Abnormalities; DNA-Binding Proteins; Duodenal Obstruction; Fatal Outcome; Gallbladder; Humans; Infant; Infant, Newborn; Infant, Newborn, Diseases; Intestinal Atresia; Intestinal Volvulus; Male; Pancreas; Pancreatic Diseases; Regulatory Factor X Transcription Factors; Transcription Factors

A new congenital disorder of glycosylation caused by a mutation in SSR4, the signal sequence receptor 4 protein of the TRAP complex. - Losfeld, Marie Estelle; Ng, Bobby G; Kircher, Martin; Buckingham, Kati J; Turner, Emily H; Eroshkin, Alexey; Smith, Joshua D; Shendure, Jay; Nickerson, Deborah A; Bamshad, Michael J; Freeze, Hudson H (Hum Mol Genet, 2014)
Nearly 50 congenital disorders of glycosylation (CDG) are known, but many patients biochemically diagnosed with CDG do not have mutations in known genes. Here, we describe a 16-year-old male who was born with microcephaly, developed intellectual disability, gastroesophageal reflux and a seizure disorder. We identified a de novo variant in the X-linked SSR4 gene which encodes a protein of the heterotetrameric translocon-associated protein (TRAP) complex. The c.316delT causes a p.F106Sfs*53 in SSR4 and also reduces expression of other TRAP complex proteins. The glycosylation marker Glyc-ER-GFP was used to confirm the underglycosylation in fibroblasts from the patient. Overexpression of the wild-type SSR4 allele partially restores glycosylation of the marker and of the other members of the TRAP complex. This is the first evidence that the TRAP complex, which binds to the oligosaccharyltransferase complex, is directly involved in N-glycosylation.
Keywords: Adolescent; Calcium-Binding Proteins; Cells, Cultured; Chromosomes, Human, X; Congenital Disorders of Glycosylation; Glycosylation; Humans; Male; Membrane Glycoproteins; Point Mutation; Receptors, Cytoplasmic and Nuclear; Receptors, Peptide

New syndrome with retinitis pigmentosa is caused by nonsense mutations in retinol dehydrogenase RDH11. - Xie, Yajing Angela; Lee, Winston; Cai, Carolyn; Gambin, Tomasz; Nõupuu, Kalev; Sujirakul, Tharikarn; Ayuso, Carmen; Jhangiani, Shalini; Muzny, Donna; Boerwinkle, Eric; Gibbs, Richard; Greenstein, Vivienne C; et al. (Hum Mol Genet, 2014)
Retinitis pigmentosa (RP), a genetically heterogeneous group of retinopathies that occur in both non-syndromic and syndromic forms, is caused by mutations in ∼100 genes. Although recent advances in next-generation sequencing have aided in the discovery of novel RP genes, a number of the underlying contributing genes and loci remain to be identified. We investigated three siblings, born to asymptomatic parents of Italian-American descent, who each presented with atypical RP with systemic features, including facial dysmorphologies, psychomotor developmental delays recognized since early childhood, learning disabilities and short stature. RP-associated ophthalmological findings included salt-and-pepper retinopathy, attenuation of the arterioles and generalized rod-cone dysfunction as determined by almost extinguished electroretinogram in 2 of 3 siblings. Atypical for RP features included mottled macula at an early age and peripapillary sparing of the retinal pigment epithelium. Whole-exome sequencing data, queried under a recessive model of inheritance, identified compound heterozygous stop mutations, c.C199T:p.R67* and c.C322T:p.R108*, in the retinol dehydrogenase 11 (RDH11) gene, resulting in a non-functional protein, in all affected children. In summary, deleterious mutations in RDH11, an important enzyme for vision-related and systemic retinoic acid metabolism, cause a new syndrome with RP.
Keywords: Adolescent; Child; Codon, Nonsense; Female; Humans; Male; Oxidoreductases; Pedigree; Phenotype; Retinitis Pigmentosa; Syndrome; Vision Tests; Visual Acuity; Young Adult

NR2F1 mutations cause optic atrophy with intellectual disability. - Bosch, Daniëlle G M; Boonstra, F Nienke; Gonzaga-Jauregui, Claudia; Xu, Mafei; de Ligt, Joep; Jhangiani, Shalini; Wiszniewski, Wojciech; Muzny, Donna M; Yntema, Helger G; Pfundt, Rolph; Vissers, Lisenka E L M; Spruijt, Liesbeth; et al. (Am J Hum Genet, 2014)
Optic nerve atrophy and hypoplasia can be primary disorders or can result from trans-synaptic degeneration arising from cerebral visual impairment (CVI). Here we report six individuals with CVI and/or optic nerve abnormalities, born after an uneventful pregnancy and delivery, who have either de novo heterozygous missense mutations in NR2F1, also known as COUP-TFI, or deletions encompassing NR2F1. All affected individuals show mild to moderate intellectual impairment. NR2F1 encodes a nuclear receptor protein that regulates transcription. A reporter assay showed that missense mutations in the zinc-finger DNA-binding domain and the putative ligand-binding domain decrease NR2F1 transcriptional activity. These findings indicate that NR2F1 plays an important role in the neurodevelopment of the visual system and that its disruption can lead to optic atrophy with intellectual disability.
Keywords: Adolescent; Adult; Amino Acid Sequence; Child; Child, Preschool; COUP Transcription Factor I; DNA-Binding Proteins; Female; Genotype; Humans; Intellectual Disability; Male; Molecular Sequence Data; Mutation, Missense; Optic Atrophy; Phenotype; Young Adult; Zinc Fingers

Parent of origin, mosaicism, and recurrence risk: probabilistic modeling explains the broken symmetry of transmission genetics. - Campbell, Ian M; Stewart, Jonathan R; James, Regis A; Lupski, James R; Stankiewicz, Paweł; Olofsson, Peter; Shaw, Chad A (Am J Hum Genet, 2014)
Most new mutations are observed to arise in fathers, and increasing paternal age positively correlates with the risk of new variants. Interestingly, new mutations in X-linked recessive disease show elevated familial recurrence rates. In male offspring, these mutations must be inherited from mothers. We previously developed a simulation model to consider parental mosaicism as a source of transmitted mutations. In this paper, we extend and formalize the model to provide analytical results and flexible formulas. The results implicate parent of origin and parental mosaicism as central variables in recurrence risk. Consistent with empirical data, our model predicts that more transmitted mutations arise in fathers and that this tendency increases as fathers age. Notably, the lack of expansion later in the male germline determines relatively lower variance in the proportion of mutants, which decreases with paternal age. Subsequently, observation of a transmitted mutation has less impact on the expected risk for future offspring. Conversely, for the female germline, which arrests after clonal expansion in early development, variance in the mutant proportion is higher, and observation of a transmitted mutation dramatically increases the expected risk of recurrence in another pregnancy. Parental somatic mosaicism considerably elevates risk for both parents. These findings have important implications for genetic counseling and for understanding patterns of recurrence in transmission genetics. We provide a convenient online tool and source code implementing our analytical results. These tools permit varying the underlying parameters that influence recurrence risk and could be useful for analyzing risk in diverse family structures.
Keywords: Adult; Aged; Aged, 80 and over; Chromosome Aberrations; DNA Copy Number Variations; Fathers; Female; Gametogenesis; Genetic Diseases, Inborn; Genomics; Germ Cells; Germ-Line Mutation; Humans; Inheritance Patterns; Male; Middle Aged; Models, Theoretical; Mosaicism; Mothers; Pregnancy; Recurrence; Risk Factors; Young Adult

Parental somatic mosaicism is underrecognized and influences recurrence risk of genomic disorders. - Campbell, Ian M; Yuan, Bo; Robberecht, Caroline; Pfundt, Rolph; Szafranski, Przemyslaw; McEntagart, Meriel E; Nagamani, Sandesh C S; Erez, Ayelet; Bartnik, Magdalena; Wiśniowiecka-Kowalnik, Barbara; Plunkett, Katie S; Pursley, Amber N; et al. (Am J Hum Genet, 2014)
New human mutations are thought to originate in germ cells, thus making a recurrence of the same mutation in a sibling exceedingly rare. However, increasing sensitivity of genomic technologies has anecdotally revealed mosaicism for mutations in somatic tissues of apparently healthy parents. Such somatically mosaic parents might also have germline mosaicism that can potentially cause unexpected intergenerational recurrences. Here, we show that somatic mosaicism for transmitted mutations among parents of children with simplex genetic disease is more common than currently appreciated. Using the sensitivity of individual-specific breakpoint PCR, we prospectively screened 100 families with children affected by genomic disorders due to rare deletion copy-number variants (CNVs) determined to be de novo by clinical analysis of parental DNA. Surprisingly, we identified four cases of low-level somatic mosaicism for the transmitted CNV in DNA isolated from parental blood. Integrated probabilistic modeling of gametogenesis developed in response to our observations predicts that mutations in parental blood increase recurrence risk substantially more than parental mutations confined to the germline. Moreover, despite the fact that maternally transmitted mutations are the minority of alleles, our model suggests that sexual dimorphisms in gametogenesis result in a greater proportion of somatically mosaic transmitting mothers who are thus at increased risk of recurrence. Therefore, somatic mosaicism together with sexual differences in gametogenesis might explain a considerable fraction of unexpected recurrences of X-linked recessive disease. Overall, our results underscore an important role for somatic mosaicism and mitotic replicative mutational mechanisms in transmission genetics.
Keywords: Cell Division; DNA Copy Number Variations; Female; Gametogenesis; Genetic Diseases, Inborn; Genomics; Germ Cells; Germ-Line Mutation; Humans; Male; Models, Genetic; Mosaicism; Mutation; Pedigree; Prospective Studies; Recurrence; Risk; Sex Characteristics; Smith-Magenis Syndrome

PGM3 mutations cause a congenital disorder of glycosylation with severe immunodeficiency and skeletal dysplasia. - Stray-Pedersen, Asbjørg; Backe, Paul H; Sorte, Hanne S; Mørkrid, Lars; Chokshi, Niti Y; Erichsen, Hans Christian; Gambin, Tomasz; Elgstøen, Katja B P; Bjørås, Magnar; Wlodarski, Marcin W; Krüger, Marcus; Jhangiani, Shalini N; et al. (Am J Hum Genet, 2014)
Human phosphoglucomutase 3 (PGM3) catalyzes the conversion of N-acetyl-glucosamine (GlcNAc)-6-phosphate into GlcNAc-1-phosphate during the synthesis of uridine diphosphate (UDP)-GlcNAc, a sugar nucleotide critical to multiple glycosylation pathways. We identified three unrelated children with recurrent infections, congenital leukopenia including neutropenia, B and T cell lymphopenia, and progression to bone marrow failure. Whole-exome sequencing demonstrated deleterious mutations in PGM3 in all three subjects, delineating their disease to be due to an unsuspected congenital disorder of glycosylation (CDG). Functional studies of the disease-associated PGM3 variants in E. coli cells demonstrated reduced PGM3 activity for all mutants tested. Two of the three children had skeletal anomalies resembling Desbuquois dysplasia: short stature, brachydactyly, dysmorphic facial features, and intellectual disability. However, these additional features were absent in the third child, showing the clinical variability of the disease. Two children received hematopoietic stem cell transplantation of cord blood and bone marrow from matched related donors; both had successful engraftment and correction of neutropenia and lymphopenia. We define PGM3-CDG as a treatable immunodeficiency, document the power of whole-exome sequencing in gene discoveries for rare disorders, and illustrate the utility of genomic analyses in studying combined and variable phenotypes.
Keywords: Bone Diseases, Developmental; Congenital Disorders of Glycosylation; Female; Humans; Immunologic Deficiency Syndromes; Male; Mutation; Pedigree; Phosphoglucomutase

Phenotypic expansion of DGKE-associated diseases. - Westland, Rik; Bodria, Monica; Carrea, Alba; Lata, Sneh; Scolari, Francesco; Fremeaux-Bacchi, Veronique; D'Agati, Vivette D; Lifton, Richard P; Gharavi, Ali G; Ghiggeri, Gian Marco; Sanna-Cherchi, Simone (J Am Soc Nephrol, 2014)
Atypical hemolytic uremic syndrome (aHUS) is usually characterized by uncontrolled complement activation. The recent discovery of loss-of-function mutations in DGKE in patients with aHUS and normal complement levels challenged this observation. DGKE, encoding diacylglycerol kinase-ε, has not been implicated in the complement cascade but hypothetically leads to a prothrombotic state. The discovery of this novel mechanism has potential implications for the treatment of infants with aHUS, who are increasingly treated with complement blocking agents. In this study, we used homozygosity mapping and whole-exome sequencing to identify a novel truncating mutation in DGKE (p.K101X) in a consanguineous family with patients affected by thrombotic microangiopathy characterized by significant serum complement activation and consumption of the complement fraction C3. Aggressive plasma infusion therapy controlled systemic symptoms and prevented renal failure, suggesting that this treatment can significantly affect the natural history of this aggressive disease. Our study expands the clinical phenotypes associated with mutations in DGKE and challenges the benefits of complement blockade treatment in such patients. Mechanistic studies of DGKE and aHUS are, therefore, essential to the design of appropriate therapeutic strategies in patients with DGKE mutations.
Keywords: Atypical Hemolytic Uremic Syndrome; Child, Preschool; Diacylglycerol Kinase; Female; Hemolytic-Uremic Syndrome; Humans; Male; Pedigree; Phenotype

Recurrent activating mutation in PRKACA in cortisol-producing adrenal tumors. - Goh, Gerald; Scholl, Ute I; Healy, James M; Choi, Murim; Prasad, Manju L; Nelson-Williams, Carol; Kunstman, John W; Kuntsman, John W; Korah, Reju; Suttorp, Anna-Carinna; Dietrich, Dimo; Haase, Matthias; et al. (Nat Genet, 2014)
Adrenal tumors autonomously producing cortisol cause Cushing's syndrome. We performed exome sequencing of 25 tumor-normal pairs and identified 2 subgroups. Eight tumors (including three carcinomas) had many somatic copy number variants (CNVs) with frequent deletion of CDC42 and CDKN2A, amplification of 5q31.2 and protein-altering mutations in TP53 and RB1. Seventeen tumors (all adenomas) had no somatic CNVs or TP53 or RB1 mutations. Six of these had known gain-of-function mutations in CTNNB1 (β-catenin) or GNAS (Gαs). Six others had somatic mutations in PRKACA (protein kinase A (PKA) catalytic subunit) resulting in a p.Leu206Arg substitution. Further sequencing identified this mutation in 13 of 63 tumors (35% of adenomas with overt Cushing's syndrome). PRKACA, GNAS and CTNNB1 mutations were mutually exclusive. Leu206 directly interacts with the regulatory subunit of PKA, PRKAR1A. Leu206Arg PRKACA loses PRKAR1A binding, increasing the phosphorylation of downstream targets. PKA activity induces cortisol production and cell proliferation, providing a mechanism for tumor development. These findings define distinct mechanisms underlying adrenal cortisol-producing tumors.
Keywords: Adolescent; Adrenal Gland Neoplasms; Adult; Aged; Amino Acid Sequence; Base Sequence; cdc42 GTP-Binding Protein; Cell Proliferation; Cyclic AMP-Dependent Protein Kinase Catalytic Subunits; Cyclin-Dependent Kinase Inhibitor p16; DNA Copy Number Variations; Exome; Female; Gene Deletion; Gene Dosage; HEK293 Cells; Humans; Hydrocortisone; Male; Middle Aged; Molecular Sequence Data; Mutation; Phosphorylation; Sequence Analysis, DNA; Sequence Homology, Amino Acid

RNF213 rare variants in an ethnically diverse population with Moyamoya disease. - Cecchi, Alana C; Guo, Dongchuan; Ren, Zhao; Flynn, Kelly; Santos-Cortez, Regie Lyn P; Leal, Suzanne M; Wang, Gao T; Regalado, Ellen S; Steinberg, Gary K; Shendure, Jay; Bamshad, Michael J; Grotta, James C; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Moyamoya disease (MMD) is a rare, genetically heterogeneous cerebrovascular disease resulting from occlusion of the distal internal carotid arteries. A variant in the Ring Finger 213 gene (RNF213), altering arginine at position 4810 (p.R4810K), is associated with MMD in Asian populations. However, there are a lack of data on the role of RNF213 in patients with MMD of additional ethnicities and diasporic Asian populations. We investigate the contribution of RNF213 alterations to MMD in an ethnically diverse population based in the United States. METHODS: We initially sequenced RNF213 exons 43, 44, and 45 (encoding the eponymous RING finger domain) and exon 60 (encoding p.R4810K) in 86 ethnically diverse patients with MMD. Comprehensive exome sequencing data from 24 additional patients with MMD was then analyzed to identify RNF213 variants globally. Segregation of variants with MMD and other vascular diseases was assessed in families. RESULTS: RNF213 p.R4810K was identified in 56% (9/16) of patients with MMD of Asian descent and not in 94 patients of non-Asian descent. 3.6% (4/110) of patients had variants in the exons encoding the RING finger domain. Seven additional variants were identified in 29% (7/24) of patients with MMD who underwent exome sequencing. Segregation analysis supported an association with MMD for 2 variants and a lack of association with disease for 1 variant. CONCLUSIONS: These results confirm that alterations in RNF213 predispose patients of diverse ethnicities to MMD, and that the p.R4810K variant predisposes individuals of Asian descent in the United States to MMD.
Keywords: Adenosine Triphosphatases; Adolescent; Adult; Child; Cohort Studies; Ethnic Groups; Female; Genetic Variation; Humans; Male; Moyamoya Disease; Population Surveillance; Ubiquitin-Protein Ligases; Young Adult

Sclerocornea in a patient with van den Ende-Gupta syndrome homozygous for a SCARF2 microdeletion. - Migliavacca, Michele P; Sobreira, Nara L M; Antonialli, Graziela P M; Oliveira, Mariana M; Melaragno, Maria Isabel S A; Casteels, Ingele; de Ravel, Thomy; Brunoni, Decio; Valle, David; Perez, Ana Beatriz A (Am J Med Genet A, 2014)
Van den Ende-Gupta Syndrome (VDEGS) is an autosomal recessive disorder characterized by blepharophimosis, distinctive nose, hypoplastic maxilla, and skeletal abnormalities. Using homozygosity mapping in four VDEGS patients from three consanguineous families, Anastacio et al. [Anastacio et al. (2010); Am J Hum Genet 87:553-559] identified homozygous mutations in SCARF2, located at 22q11.2. Bedeschi et al. [2010] described a VDEGS patient with sclerocornea and cataracts with compound heterozygosity for the common 22q11.2 microdeletion and a hemizygous SCARF2 mutation. Because sclerocornea had been described in DiGeorge-velo-cardio-facial syndrome but not in VDEGS, they suggested that the ocular abnormalities were caused by the 22q11.2 microdeletion. We report on a 23-year-old male who presented with bilateral sclerocornea and the VDGEGS phenotype who was subsequently found to be homozygous for a 17 bp deletion in exon 4 of SCARF2. The occurrence of bilateral sclerocornea in our patient together with that of Bedeschi et al., suggests that the full VDEGS phenotype may include sclerocornea resulting from homozygosity or compound heterozygosity for loss of function variants in SCARF2.
Keywords: Abnormalities, Multiple; Adult; Arachnodactyly; Blepharophimosis; Bone and Bones; Chromosomes, Human, Pair 22; Contracture; Cornea; Corneal Diseases; Exons; Facies; Hand Deformities, Congenital; Homozygote; Humans; Male; Phenotype; Radiography; Scavenger Receptors, Class F; Sequence Analysis, DNA; Sequence Deletion; Young Adult

Whole exome sequencing identifies de novo mutations in GATA6 associated with congenital diaphragmatic hernia. - Yu, Lan; Bennett, James T; Wynn, Julia; Carvill, Gemma L; Cheung, Yee Him; Shen, Yufeng; Mychaliska, George B; Azarow, Kenneth S; Crombleholme, Timothy M; Chung, Dai H; Potoka, Douglas; Warner, Brad W; et al. (J Med Genet, 2014)
BACKGROUND: Congenital diaphragmatic hernia (CDH) is a common birth defect affecting 1 in 3000 births. It is characterised by herniation of abdominal viscera through an incompletely formed diaphragm. Although chromosomal anomalies and mutations in several genes have been implicated, the cause for most patients is unknown. METHODS: We used whole exome sequencing in two families with CDH and congenital heart disease, and identified mutations in GATA6 in both. RESULTS: In the first family, we identified a de novo missense mutation (c.1366C>T, p.R456C) in a sporadic CDH patient with tetralogy of Fallot. In the second, a nonsense mutation (c.712G>T, p.G238*) was identified in two siblings with CDH and a large ventricular septal defect. The G238* mutation was inherited from their mother, who was clinically affected with congenital absence of the pericardium, patent ductus arteriosus and intestinal malrotation. Deep sequencing of blood and saliva-derived DNA from the mother suggested somatic mosaicism as an explanation for her milder phenotype, with only approximately 15% mutant alleles. To determine the frequency of GATA6 mutations in CDH, we sequenced the gene in 378 patients with CDH. We identified one additional de novo mutation (c.1071delG, p.V358Cfs34*). CONCLUSIONS: Mutations in GATA6 have been previously associated with pancreatic agenesis and congenital heart disease. We conclude that, in addition to the heart and the pancreas, GATA6 is involved in development of two additional organs, the diaphragm and the pericardium. In addition, we have shown that de novo mutations can contribute to the development of CDH, a common birth defect.
Keywords: Amino Acid Sequence; DNA Mutational Analysis; Exome; Female; GATA6 Transcription Factor; Hernia, Diaphragmatic; Hernias, Diaphragmatic, Congenital; Humans; Male; Molecular Sequence Data; Mutation; Sequence Alignment; Sequence Analysis, DNA

Whole exome sequencing identifies three novel mutations in ANTXR1 in families with GAPO syndrome. - Bayram, Yavuz; Pehlivan, Davut; Karaca, Ender; Gambin, Tomasz; Jhangiani, Shalini N; Erdin, Serkan; Gonzaga-Jauregui, Claudia; Wiszniewski, Wojciech; Muzny, Donna; Elcioglu, Nursel H; Yildirim, M Selman; Bozkurt, Banu; et al. (Am J Med Genet A, 2014)
GAPO syndrome (OMIM#230740) is the acronym for growth retardation, alopecia, pseudoanodontia, and optic atrophy. About 35 cases have been reported, making it among one of the rarest recessive conditions. Distinctive craniofacial features including alopecia, rarefaction of eyebrows and eyelashes, frontal bossing, high forehead, mid-facial hypoplasia, hypertelorism, and thickened eyelids and lips make GAPO syndrome a clinically recognizable phenotype. While this genomic study was in progress mutations in ANTXR1 were reported to cause GAPO syndrome. In our study we performed whole exome sequencing (WES) for five affected individuals from three Turkish kindreds segregating the GAPO trait. Exome sequencing analysis identified three novel homozygous mutations including; one frame-shift (c.1220_1221insT; p.Ala408Cysfs*2), one splice site (c.411A>G; p.Gln137Gln), and one non-synonymous (c.1150G>A; p.Gly384Ser) mutation in the ANTXR1 gene. Our studies expand the allelic spectrum in this rare condition and potentially provide insight into the role of ANTXR1 in the regulation of the extracellular matrix.
Keywords: Adolescent; Adult; Alopecia; Anodontia; Base Sequence; Child; Chromosome Segregation; DNA Mutational Analysis; Exome; Facies; Family; Female; Growth Disorders; Humans; Male; Molecular Sequence Data; Mutation; Neoplasm Proteins; Optic Atrophies, Hereditary; Pedigree; Protein Structure, Tertiary; Receptors, Cell Surface

Whole-exome sequencing links TMCO1 defect syndrome with cerebro-facio-thoracic dysplasia. - Pehlivan, Davut; Karaca, Ender; Aydin, Hatip; Beck, Christine R; Gambin, Tomasz; Muzny, Donna M; Bilge Geckinli, B; Karaman, Ali; Jhangiani, Shalini N; Gibbs, Richard A; Lupski, James R (Eur J Hum Genet, 2014)
Whole-exome sequencing (WES) is a type of disruptive technology that has tremendous influence on human and clinical genetics research. An efficient and cost-effective method, WES is now widely used as a diagnostic tool for identifying the molecular basis of genetic syndromes that are often challenging to diagnose. Here we report a patient with a clinical diagnosis of cerebro-facio-thoracic dysplasia (CFTD; MIM#213980) in whom we identified a homozygous splice-site mutation in the transmembrane and coiled-coil domains 1 (TMCO1) gene using WES. TMCO1 mutations cause craniofacial dysmorphism, skeletal anomalies characterized by multiple malformations of the vertebrae and ribs, and intellectual disability (MIM#614132). A retrospective review revealed that clinical manifestations of both syndromes are very similar and overlap remarkably. We propose that mutations of TMCO1 are not only responsible for craniofacial dysmorphism, skeletal anomalies and mental retardation syndrome but also for CFTD.
Keywords: Abnormalities, Multiple; Exome; Humans; Infant; Intellectual Disability; Male; Membrane Proteins; Mutation; Protein Isoforms

Attitudes of African Americans toward return of results from exome and whole genome sequencing. - Yu, Joon-Ho; Crouch, Julia; Jamal, Seema M; Tabor, Holly K; Bamshad, Michael J (Am J Med Genet A, 2013)
Exome sequencing and whole genome sequencing (ES/WGS) present patients and research participants with the opportunity to benefit from a broad scope of genetic results of clinical and personal utility. Yet, this potential for benefit also risks disenfranchising populations such as African Americans (AAs) that are already underrepresented in genetic research and utilize genetic tests at lower rates than other populations. Understanding a diverse range of perspectives on consenting for ES/WGS and receiving ES/WGS results is necessary to ensure parity in genomic health care and research. We conducted a series of 13 focus groups (n = 76) to investigate if and how attitudes toward participation in ES/WGS research and return of results from ES/WGS differ between self-described AAs and non-AAs. The majority of both AAs and non-AAs were willing to participate in WGS studies and receive individual genetic results, but the fraction not interested in either was higher in AAs. This is due in part to different expectations of health benefits from ES/WGS and how results should be managed. Our results underscore the need to develop and test culturally tailored strategies for returning ES/WGS results to AAs.
Keywords: Adult; African Americans; Aged; Attitude; Exome; Female; Focus Groups; Genetic Research; Genome-Wide Association Study; Humans; Male; Middle Aged; Sequence Analysis, DNA; Surveys and Questionnaires; Washington

De novo mutations in histone-modifying genes in congenital heart disease. - Zaidi, Samir; Choi, Murim; Wakimoto, Hiroko; Ma, Lijiang; Jiang, Jianming; Overton, John D; Romano-Adesman, Angela; Bjornson, Robert D; Breitbart, Roger E; Brown, Kerry K; Carriero, Nicholas J; Cheung, Yee Him; et al. (Nature, 2013)
Congenital heart disease (CHD) is the most frequent birth defect, affecting 0.8% of live births. Many cases occur sporadically and impair reproductive fitness, suggesting a role for de novo mutations. Here we compare the incidence of de novo mutations in 362 severe CHD cases and 264 controls by analysing exome sequencing of parent-offspring trios. CHD cases show a significant excess of protein-altering de novo mutations in genes expressed in the developing heart, with an odds ratio of 7.5 for damaging (premature termination, frameshift, splice site) mutations. Similar odds ratios are seen across the main classes of severe CHD. We find a marked excess of de novo mutations in genes involved in the production, removal or reading of histone 3 lysine 4 (H3K4) methylation, or ubiquitination of H2BK120, which is required for H3K4 methylation. There are also two de novo mutations in SMAD2, which regulates H3K27 methylation in the embryonic left-right organizer. The combination of both activating (H3K4 methylation) and inactivating (H3K27 methylation) chromatin marks characterizes 'poised' promoters and enhancers, which regulate expression of key developmental genes. These findings implicate de novo point mutations in several hundreds of genes that collectively contribute to approximately 10% of severe CHD.
Keywords: Adult; Case-Control Studies; Child; Chromatin; DNA Mutational Analysis; Enhancer Elements, Genetic; Exome; Female; Genes, Developmental; Heart Diseases; Histones; Humans; Lysine; Male; Methylation; Mutation; Odds Ratio; Promoter Regions, Genetic

Incidental copy-number variants identified by routine genome testing in a clinical population. - Boone, Philip M; Soens, Zachry T; Campbell, Ian M; Stankiewicz, Pawel; Cheung, Sau Wai; Patel, Ankita; Beaudet, Arthur L; Plon, Sharon E; Shaw, Chad A; McGuire, Amy L; Lupski, James R (Genet Med, 2013)
PURPOSE: Mutational load of susceptibility variants has not been studied on a genomic scale in a clinical population, nor has the potential to identify these mutations as incidental findings during clinical testing been systematically ascertained. METHODS: Array comparative genomic hybridization, a method for genome-wide detection of DNA copy-number variants, was performed clinically on DNA from 9,005 individuals. Copy-number variants encompassing or disrupting single genes were identified and analyzed for their potential to confer predisposition to dominant, adult-onset disease. Multigene copy-number variants affecting dominant, adult-onset cancer syndrome genes were also assessed. RESULTS: In our cohort, 83 single-gene copy-number variants affected 40 unique genes associated with dominant, adult-onset disorders and unrelated to the patients' referring diagnoses (i.e., incidental) were found. Fourteen of these copy-number variants are likely disease-predisposing, 25 are likely benign, and 44 are of unknown clinical consequence. When incidental copy-number variants spanning up to 20 genes were considered, 27 copy-number variants affected 17 unique genes associated with dominant, adult-onset cancer predisposition. CONCLUSION: Copy-number variants potentially conferring susceptibility to adult-onset disease can be identified as incidental findings during routine genome-wide testing. Some of these mutations may be medically actionable, enabling disease surveillance or prevention; however, most incidentally observed single-gene copy-number variants are currently of unclear significance to the patient.
Keywords: Age of Onset; Base Sequence; Chromosome Mapping; Comparative Genomic Hybridization; DNA Copy Number Variations; Female; Gene Order; Genetic Predisposition to Disease; Humans; Inheritance Patterns; Male; Reproducibility of Results

Mosaicism of the UDP-galactose transporter SLC35A2 causes a congenital disorder of glycosylation. - Ng, Bobby G; Buckingham, Kati J; Raymond, Kimiyo; Kircher, Martin; Turner, Emily H; He, Miao; Smith, Joshua D; Eroshkin, Alexey; Szybowska, Marta; Losfeld, Marie E; Chong, Jessica X; Kozenko, Mariya; et al. (Am J Hum Genet, 2013)
Biochemical analysis and whole-exome sequencing identified mutations in the Golgi-localized UDP-galactose transporter SLC35A2 that define an undiagnosed X-linked congenital disorder of glycosylation (CDG) in three unrelated families. Each mutation reduced UDP-galactose transport, leading to galactose-deficient glycoproteins. Two affected males were somatic mosaics, suggesting that a wild-type SLC35A2 allele may be required for survival. In infancy, the commonly used biomarker transferrin showed abnormal glycosylation, but its appearance became normal later in childhood, without any corresponding clinical improvement. This may indicate selection against cells carrying the mutant allele. To detect other individuals with such mutations, we suggest transferrin testing in infancy. Here, we report somatic mosaicism in CDG, and our work stresses the importance of combining both genetic and biochemical diagnoses.
Keywords: Biological Transport; Case-Control Studies; Child; Child, Preschool; Congenital Disorders of Glycosylation; Exome; Female; Glycosylation; Humans; Male; Monosaccharide Transport Proteins; Mosaicism; Mutation; Spectrometry, Mass, Electrospray Ionization; Transferrin; Uridine Diphosphate Galactose

Mutations in DSTYK and dominant urinary tract malformations. - Sanna-Cherchi, Simone; Sampogna, Rosemary V; Papeta, Natalia; Burgess, Katelyn E; Nees, Shannon N; Perry, Brittany J; Choi, Murim; Bodria, Monica; Liu, Yan; Weng, Patricia L; Lozanovski, Vladimir J; Verbitsky, Miguel; et al. (N Engl J Med, 2013)
BACKGROUND: Congenital abnormalities of the kidney and the urinary tract are the most common cause of pediatric kidney failure. These disorders are highly heterogeneous, and the etiologic factors are poorly understood. METHODS: We performed genomewide linkage analysis and whole-exome sequencing in a family with an autosomal dominant form of congenital abnormalities of the kidney or urinary tract (seven affected family members). We also performed a sequence analysis in 311 unrelated patients, as well as histologic and functional studies. RESULTS: Linkage analysis identified five regions of the genome that were shared among all affected family members. Exome sequencing identified a single, rare, deleterious variant within these linkage intervals, a heterozygous splice-site mutation in the dual serine-threonine and tyrosine protein kinase gene (DSTYK). This variant, which resulted in aberrant splicing of messenger RNA, was present in all affected family members. Additional, independent DSTYK mutations, including nonsense and splice-site mutations, were detected in 7 of 311 unrelated patients. DSTYK is highly expressed in the maturing epithelia of all major organs, localizing to cell membranes. Knockdown in zebrafish resulted in developmental defects in multiple organs, which suggested loss of fibroblast growth factor (FGF) signaling. Consistent with this finding is the observation that DSTYK colocalizes with FGF receptors in the ureteric bud and metanephric mesenchyme. DSTYK knockdown in human embryonic kidney cells inhibited FGF-stimulated phosphorylation of extracellular-signal-regulated kinase (ERK), the principal signal downstream of receptor tyrosine kinases. CONCLUSIONS: We detected independent DSTYK mutations in 2.3% of patients with congenital abnormalities of the kidney or urinary tract, a finding that suggests that DSTYK is a major determinant of human urinary tract development, downstream of FGF signaling. (Funded by the National Institutes of Health and others.).
Keywords: Adult; Animals; Base Sequence; Child; Exome; Female; Gene Knockdown Techniques; Genetic Linkage; Genome-Wide Association Study; Heterozygote; Humans; Infant; Kidney; Male; Mice; Molecular Sequence Data; Mutation; Pedigree; Receptor-Interacting Protein Serine-Threonine Kinases; RNA, Small Interfering; Urinary Tract; Urogenital Abnormalities; Young Adult

Mutations in ECEL1 cause distal arthrogryposis type 5D. - McMillin, Margaret J; Below, Jennifer E; Shively, Kathryn M; Beck, Anita E; Gildersleeve, Heidi I; Pinner, Jason; Gogola, Gloria R; Hecht, Jacqueline T; Grange, Dorothy K; Harris, David J; Earl, Dawn L; Jagadeesh, Sujatha; et al. (Am J Hum Genet, 2013)
Distal arthrogryposis (DA) syndromes are the most common of the heritable congenital-contracture disorders, and ~50% of cases are caused by mutations in genes that encode contractile proteins of skeletal myofibers. DA type 5D (DA5D) is a rare, autosomal-recessive DA previously defined by us and is characterized by congenital contractures of the hands and feet, along with distinctive facial features, including ptosis. We used linkage analysis and whole-genome sequencing of a multiplex consanguineous family to identify in endothelin-converting enzyme-like 1 (ECEL1) mutations that result in DA5D. Evaluation of a total of seven families affected by DA5D revealed in five families ECEL1 mutations that explain ~70% of cases overall. ECEL1 encodes a neuronal endopeptidase and is expressed in the brain and peripheral nerves. Mice deficient in Ecel1 exhibit perturbed terminal branching of motor neurons to the endplate of skeletal muscles, resulting in poor formation of the neuromuscular junction. Our results distinguish a second developmental pathway that causes congenital-contracture syndromes.
Keywords: Arthrogryposis; Consanguinity; Female; Genetic Linkage; Humans; Male; Metalloendopeptidases; Mutation; Sequence Analysis, DNA

Mutations in KARS, encoding lysyl-tRNA synthetase, cause autosomal-recessive nonsyndromic hearing impairment DFNB89. - Santos-Cortez, Regie Lyn P; Lee, Kwanghyuk; Azeem, Zahid; Antonellis, Patrick J; Pollock, Lana M; Khan, Saadullah; Andrade-Elizondo, Paula B; Chiu, Ilene; Adams, Mark D; Basit, Sulman; Smith, Joshua D; Nickerson, Deborah A; et al. (Am J Hum Genet, 2013)
Previously, DFNB89, a locus associated with autosomal-recessive nonsyndromic hearing impairment (ARNSHI), was mapped to chromosomal region 16q21-q23.2 in three unrelated, consanguineous Pakistani families. Through whole-exome sequencing of a hearing-impaired individual from each family, missense mutations were identified at highly conserved residues of lysyl-tRNA synthetase (KARS): the c.1129G>A (p.Asp377Asn) variant was found in one family, and the c.517T>C (p.Tyr173His) variant was found in the other two families. Both variants were predicted to be damaging by multiple bioinformatics tools. The two variants both segregated with the nonsyndromic-hearing-impairment phenotype within the three families, and neither mutation was identified in ethnically matched controls or within variant databases. Individuals homozygous for KARS mutations had symmetric, severe hearing impairment across all frequencies but did not show evidence of auditory or limb neuropathy. It has been demonstrated that KARS is expressed in hair cells of zebrafish, chickens, and mice. Moreover, KARS has strong localization to the spiral ligament region of the cochlea, as well as to Deiters' cells, the sulcus epithelium, the basilar membrane, and the surface of the spiral limbus. It is hypothesized that KARS variants affect aminoacylation in inner-ear cells by interfering with binding activity to tRNA or p38 and with tetramer formation. The identification of rare KARS variants in ARNSHI-affected families defines a gene that is associated with ARNSHI.
Keywords: Animals; Case-Control Studies; Chickens; Cochlea; Computational Biology; Consanguinity; Female; Genetic Linkage; Hair Cells, Auditory, Inner; Haplotypes; Hearing Loss; Homozygote; Humans; Lysine-tRNA Ligase; Male; Mice; Mutation, Missense; Pedigree; Transfer RNA Aminoacylation; Zebrafish

Mutations in KCTD1 cause scalp-ear-nipple syndrome. - Marneros, Alexander G; Beck, Anita E; Turner, Emily H; McMillin, Margaret J; Edwards, Matthew J; Field, Michael; de Macena Sobreira, Nara Lygia; Perez, Ana Beatriz A; Fortes, Jose A R; Lampe, Anne K; Giovannucci Uzielli, Maria Luisa; Gordon, Christopher T; et al. (Am J Hum Genet, 2013)
Scalp-ear-nipple (SEN) syndrome is a rare, autosomal-dominant disorder characterized by cutis aplasia of the scalp; minor anomalies of the external ears, digits, and nails; and malformations of the breast. We used linkage analysis and exome sequencing of a multiplex family affected by SEN syndrome to identify potassium-channel tetramerization-domain-containing 1 (KCTD1) mutations that cause SEN syndrome. Evaluation of a total of ten families affected by SEN syndrome revealed KCTD1 missense mutations in each family tested. All of the mutations occurred in a KCTD1 region encoding a highly conserved bric-a-brac, tram track, and broad complex (BTB) domain that is required for transcriptional repressor activity. KCTD1 inhibits the transactivation of the transcription factor AP-2α (TFAP2A) via its BTB domain, and mutations in TFAP2A cause cutis aplasia in individuals with branchiooculofacial syndrome (BOFS), suggesting a potential overlap in the pathogenesis of SEN syndrome and BOFS. The identification of KCTD1 mutations in SEN syndrome reveals a role for this BTB-domain-containing transcriptional repressor during ectodermal development.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; Branchio-Oto-Renal Syndrome; Ear, External; Ectodermal Dysplasia; Exome; Female; Humans; Hypospadias; Male; Molecular Sequence Data; Muscle Hypotonia; Mutation, Missense; Nipples; Pedigree; Phenotype; Protein Structure, Tertiary; Repressor Proteins; Scalp; Sequence Homology, Amino Acid

Mutations in LAMB1 cause cobblestone brain malformation without muscular or ocular abnormalities. - Radmanesh, Farid; Çağlayan, Ahmet Okay; Silhavy, Jennifer L; Yilmaz, Cahide; Cantagrel, Vincent; Omar, Tarek; Rosti, Basak; Kaymakçalan, Hande; Gabriel, Stacey; Li, Mingfeng; Šestan, Nenad; Bilguvar, Kaya; et al. (Am J Hum Genet, 2013)
Cobblestone brain malformation (COB) is a neuronal migration disorder characterized by protrusions of neurons beyond the first cortical layer at the pial surface of the brain. It is usually seen in association with dystroglycanopathy types of congenital muscular dystrophies (CMDs) and ocular abnormalities termed muscle-eye-brain disease. Here we report homozygous deleterious mutations in LAMB1, encoding laminin subunit beta-1, in two families with autosomal-recessive COB. Affected individuals displayed a constellation of brain malformations including cortical gyral and white-matter signal abnormalities, severe cerebellar dysplasia, brainstem hypoplasia, and occipital encephalocele, but they had less apparent ocular or muscular abnormalities than are typically observed in COB. LAMB1 is localized to the pial basement membrane, suggesting that defective connection between radial glial cells and the pial surface mediated by LAMB1 leads to this malformation.
Keywords: Basement Membrane; Brain; Cerebellum; Cerebral Cortex; Encephalocele; Female; Genetic Predisposition to Disease; Homozygote; Humans; Laminin; Male; Muscular Dystrophies; Nervous System Malformations; Neuroglia; Neurons; Sequence Deletion; Walker-Warburg Syndrome

Mutations in VRK1 associated with complex motor and sensory axonal neuropathy plus microcephaly. - Gonzaga-Jauregui, Claudia; Lotze, Timothy; Jamal, Leila; Penney, Samantha; Campbell, Ian M; Pehlivan, Davut; Hunter, Jill V; Woodbury, Suzanne L; Raymond, Gerald; Adesina, Adekunle M; Jhangiani, Shalini N; Reid, Jeffrey G; et al. (JAMA Neurol, 2013)
IMPORTANCE: Patients with rare diseases and complex clinical presentations represent a challenge for clinical diagnostics. Genomic approaches are allowing the identification of novel variants in genes for very rare disorders, enabling a molecular diagnosis. Genomics is also revealing a phenotypic expansion whereby the full spectrum of clinical expression conveyed by mutant alleles at a locus can be better appreciated. OBJECTIVE: To elucidate the molecular cause of a complex neuropathy phenotype in 3 patients by applying genomic sequencing strategies. DESIGN, SETTING, AND PARTICIPANTS: Three affected individuals from 2 unrelated families presented with a complex neuropathy phenotype characterized by axonal sensorimotor neuropathy and microcephaly. They were recruited into the Centers for Mendelian Genomics research program to identify the molecular cause of their phenotype. Whole-genome, targeted whole-exome sequencing, and high-resolution single-nucleotide polymorphism arrays were performed in genetics clinics of tertiary care pediatric hospitals and biomedical research institutions. MAIN OUTCOMES AND MEASURES: Whole-genome and whole-exome sequencing identified the variants responsible for the patients' clinical phenotype. RESULTS: We identified compound heterozygous alleles in 2 affected siblings from 1 family and a homozygous nonsense variant in the third unrelated patient in the vaccinia-related kinase 1 gene (VRK1). In the latter subject, we found a common haplotype on which the nonsense mutation occurred and that segregates in the Ashkenazi Jewish population. CONCLUSIONS AND RELEVANCE: We report the identification of disease-causing alleles in 3 children from 2 unrelated families with a previously uncharacterized complex axonal motor and sensory neuropathy accompanied by severe nonprogressive microcephaly and cerebral dysgenesis. Our data raise the question of whether VRK1 mutations disturb cell cycle progression and may result in apoptosis of cells in the nervous system. The application of unbiased genomic approaches allows the identification of potentially pathogenic mutations in unsuspected genes in highly genetically heterogeneous and uncharacterized neurological diseases.
Keywords: Child; Child, Preschool; DNA Mutational Analysis; Female; Genotype; Hereditary Sensory and Motor Neuropathy; Humans; Infant; Intracellular Signaling Peptides and Proteins; Magnetic Resonance Imaging; Male; Microcephaly; Mutation; Neural Conduction; Polymorphism, Single Nucleotide; Protein-Serine-Threonine Kinases

Perrault syndrome is caused by recessive mutations in CLPP, encoding a mitochondrial ATP-dependent chambered protease. - Jenkinson, Emma M; Rehman, Atteeq U; Walsh, Tom; Clayton-Smith, Jill; Lee, Kwanghyuk; Morell, Robert J; Drummond, Meghan C; Khan, Shaheen N; Naeem, Muhammad Asif; Rauf, Bushra; Billington, Neil; Schultz, Julie M; et al. (Am J Hum Genet, 2013)
Perrault syndrome is a genetically and clinically heterogeneous autosomal-recessive condition characterized by sensorineural hearing loss and ovarian failure. By a combination of linkage analysis, homozygosity mapping, and exome sequencing in three families, we identified mutations in CLPP as the likely cause of this phenotype. In each family, affected individuals were homozygous for a different pathogenic CLPP allele: c.433A>C (p.Thr145Pro), c.440G>C (p.Cys147Ser), or an experimentally demonstrated splice-donor-site mutation, c.270+4A>G. CLPP, a component of a mitochondrial ATP-dependent proteolytic complex, is a highly conserved endopeptidase encoded by CLPP and forms an element of the evolutionarily ancient mitochondrial unfolded-protein response (UPR(mt)) stress signaling pathway. Crystal-structure modeling suggests that both substitutions would alter the structure of the CLPP barrel chamber that captures unfolded proteins and exposes them to proteolysis. Together with the previous identification of mutations in HARS2, encoding mitochondrial histidyl-tRNA synthetase, mutations in CLPP expose dysfunction of mitochondrial protein homeostasis as a cause of Perrault syndrome.
Keywords: Adenosine Triphosphate; Adolescent; Adult; ATP-Dependent Proteases; Endopeptidase Clp; Exome; Female; Genes, Recessive; Gonadal Dysgenesis, 46,XX; Hearing Loss, Sensorineural; Homozygote; Humans; In Situ Hybridization; Male; Mitochondria; Mutation; Pedigree; Phenotype; Young Adult

Recessive loss of function of the neuronal ubiquitin hydrolase UCHL1 leads to early-onset progressive neurodegeneration. - Bilguvar, Kaya; Tyagi, Navneet K; Ozkara, Cigdem; Tuysuz, Beyhan; Bakircioglu, Mehmet; Choi, Murim; Delil, Sakir; Çağlayan, Ahmet O; Baranoski, Jacob F; Erturk, Ozdem; Yalcinkaya, Cengiz; Karacorlu, Murat; et al. (Proc Natl Acad Sci U S A, 2013)
Ubiquitin C-terminal hydrolase-L1 (UCHL1), a neuron-specific de-ubiquitinating enzyme, is one of the most abundant proteins in the brain. We describe three siblings from a consanguineous union with a previously unreported early-onset progressive neurodegenerative syndrome featuring childhood onset blindness, cerebellar ataxia, nystagmus, dorsal column dysfuction, and spasticity with upper motor neuron dysfunction. Through homozygosity mapping of the affected individuals followed by whole-exome sequencing of the index case, we identified a previously undescribed homozygous missense mutation within the ubiquitin binding domain of UCHL1 (UCHL1(GLU7ALA)), shared by all affected subjects. As demonstrated by isothermal titration calorimetry, purified UCHL1(GLU7ALA), compared with WT, exhibited at least sevenfold reduced affinity for ubiquitin. In vitro, the mutation led to a near complete loss of UCHL1 hydrolase activity. The GLU7ALA variant is predicted to interfere with the substrate binding by restricting the proper positioning of the substrate for tunneling underneath the cross-over loop spanning the catalytic cleft of UCHL1. This interference with substrate binding, combined with near complete loss of hydrolase activity, resulted in a >100-fold reduction in the efficiency of UCHL1(GLU7ALA) relative to WT. These findings demonstrate a broad requirement of UCHL1 in the maintenance of the nervous system.
Keywords: Adult; Age of Onset; Amino Acid Sequence; Base Sequence; Child, Preschool; Exome; Female; Genes, Recessive; Homozygote; Humans; Hydrolysis; Male; Models, Molecular; Molecular Sequence Data; Mutation, Missense; Nerve Degeneration; Neurons; Pedigree; Protein Binding; Sequence Analysis, DNA; Substrate Specificity; Syndrome; Thermodynamics; Ubiquitin; Ubiquitin Thiolesterase

Recessive mutations in DGKE cause atypical hemolytic-uremic syndrome. - Lemaire, Mathieu; Fremeaux-Bacchi, Veronique; Schaefer, Franz; Choi, Murim; Tang, Wai Ho; Le Quintrec, Moglie; Fakhouri, Fadi; Taque, Sophie; Nobili, François; Martinez, Frank; Ji, Weizhen; Overton, John D; et al. (Nat Genet, 2013)
Pathologic thrombosis is a major cause of mortality. Hemolytic-uremic syndrome (HUS) features episodes of small-vessel thrombosis resulting in microangiopathic hemolytic anemia, thrombocytopenia and renal failure. Atypical HUS (aHUS) can result from genetic or autoimmune factors that lead to pathologic complement cascade activation. Using exome sequencing, we identified recessive mutations in DGKE (encoding diacylglycerol kinase ɛ) that co-segregated with aHUS in nine unrelated kindreds, defining a distinctive Mendelian disease. Affected individuals present with aHUS before age 1 year, have persistent hypertension, hematuria and proteinuria (sometimes in the nephrotic range), and develop chronic kidney disease with age. DGKE is found in endothelium, platelets and podocytes. Arachidonic acid-containing diacylglycerols (DAG) activate protein kinase C (PKC), which promotes thrombosis, and DGKE normally inactivates DAG signaling. We infer that loss of DGKE function results in a prothrombotic state. These findings identify a new mechanism of pathologic thrombosis and kidney failure and have immediate implications for treating individuals with aHUS.
Keywords: Acute Kidney Injury; Atypical Hemolytic Uremic Syndrome; Child; Child, Preschool; Diacylglycerol Kinase; Exome; Female; Genes, Recessive; Hemolytic-Uremic Syndrome; Humans; Immunoenzyme Techniques; Infant; Male; Molecular Sequence Data; Mutation; Renal Insufficiency, Chronic; Thrombocytopenia; Thrombotic Microangiopathies

Recurrent gain-of-function mutation in PRKG1 causes thoracic aortic aneurysms and acute aortic dissections. - Guo, Dong-Chuan; Regalado, Ellen; Casteel, Darren E; Santos-Cortez, Regie L; Gong, Limin; Kim, Jeong Joo; Dyack, Sarah; Horne, S Gabrielle; Chang, Guijuan; Jondeau, Guillaume; Boileau, Catherine; Coselli, Joseph S; et al. (Am J Hum Genet, 2013)
Gene mutations that lead to decreased contraction of vascular smooth-muscle cells (SMCs) can cause inherited thoracic aortic aneurysms and dissections. Exome sequencing of distant relatives affected by thoracic aortic disease and subsequent Sanger sequencing of additional probands with familial thoracic aortic disease identified the same rare variant, PRKG1 c.530G>A (p.Arg177Gln), in four families. This mutation segregated with aortic disease in these families with a combined two-point LOD score of 7.88. The majority of affected individuals presented with acute aortic dissections (63%) at relatively young ages (mean 31 years, range 17-51 years). PRKG1 encodes type I cGMP-dependent protein kinase (PKG-1), which is activated upon binding of cGMP and controls SMC relaxation. Although the p.Arg177Gln alteration disrupts binding to the high-affinity cGMP binding site within the regulatory domain, the altered PKG-1 is constitutively active even in the absence of cGMP. The increased PKG-1 activity leads to decreased phosphorylation of the myosin regulatory light chain in fibroblasts and is predicted to cause decreased contraction of vascular SMCs. Thus, identification of a gain-of-function mutation in PRKG1 as a cause of thoracic aortic disease provides further evidence that proper SMC contractile function is critical for maintaining the integrity of the thoracic aorta throughout a lifetime.
Keywords: Acute Disease; Adolescent; Adult; Amino Acid Sequence; Aneurysm, Dissecting; Aorta, Thoracic; Aortic Aneurysm, Thoracic; Cyclic GMP; Cyclic GMP-Dependent Protein Kinase Type I; Exome; Female; Fibroblasts; High-Throughput Nucleotide Sequencing; Humans; Male; Middle Aged; Molecular Sequence Data; Muscle Contraction; Muscle, Smooth, Vascular; Mutation; Myosin Light Chains; Pedigree

A recurrent PDGFRB mutation causes familial infantile myofibromatosis. - Cheung, Yee Him; Gayden, Tenzin; Campeau, Philippe M; LeDuc, Charles A; Russo, Donna; Nguyen, Van-Hung; Guo, Jiancheng; Qi, Ming; Guan, Yanfang; Albrecht, Steffen; Moroz, Brenda; Eldin, Karen W; et al. (Am J Hum Genet, 2013)
Infantile myofibromatosis (IM) is the most common benign fibrous tumor of soft tissues affecting young children. By using whole-exome sequencing, RNA sequencing, and targeted sequencing, we investigated germline and tumor DNA in individuals from four distinct families with the familial form of IM and in five simplex IM cases with no previous family history of this disease. We identified a germline mutation c.1681C>T (p.Arg561Cys) in platelet-derived growth factor receptor β (PDGFRB) in all 11 affected individuals with familial IM, although none of the five individuals with nonfamilial IM had mutations in this gene. We further identified a second heterozygous mutation in PDGFRB in two myofibromas from one of the affected familial cases, indicative of a potential second hit in this gene in the tumor. PDGFR-β promotes growth of mesenchymal cells, including blood vessels and smooth muscles, which are affected in IM. Our findings indicate p.Arg561Cys substitution in PDGFR-β as a cause of the dominant form of this disease. They provide a rationale for further investigations of this specific mutation and gene to assess the benefits of targeted therapies against PDGFR-β in aggressive life-threatening familial forms of the disease.
Keywords: Amino Acid Sequence; Female; Genes, Dominant; Genetic Association Studies; Germ-Line Mutation; Heterozygote; Humans; Male; Models, Molecular; Mutation, Missense; Myofibromatosis; Pedigree; Protein Structure, Tertiary; Receptor, Notch3; Receptor, Platelet-Derived Growth Factor beta; Receptors, Notch; Sequence Analysis, DNA

Somatic and germline CACNA1D calcium channel mutations in aldosterone-producing adenomas and primary aldosteronism. - Scholl, Ute I; Goh, Gerald; Stölting, Gabriel; de Oliveira, Regina Campos; Choi, Murim; Overton, John D; Fonseca, Annabelle L; Korah, Reju; Starker, Lee F; Kunstman, John W; Prasad, Manju L; Hartung, Erum A; et al. (Nat Genet, 2013)
Adrenal aldosterone-producing adenomas (APAs) constitutively produce the salt-retaining hormone aldosterone and are a common cause of severe hypertension. Recurrent mutations in the potassium channel gene KCNJ5 that result in cell depolarization and Ca(2+) influx cause ∼40% of these tumors. We identified 5 somatic mutations (4 altering Gly403 and 1 altering Ile770) in CACNA1D, encoding a voltage-gated calcium channel, among 43 APAs without mutated KCNJ5. The altered residues lie in the S6 segments that line the channel pore. Both alterations result in channel activation at less depolarized potentials; Gly403 alterations also impair channel inactivation. These effects are inferred to cause increased Ca(2+) influx, which is a sufficient stimulus for aldosterone production and cell proliferation in adrenal glomerulosa. We also identified de novo germline mutations at identical positions in two children with a previously undescribed syndrome featuring primary aldosteronism and neuromuscular abnormalities. These findings implicate gain-of-function Ca(2+) channel mutations in APAs and primary aldosteronism.
Keywords: Adrenal Cortex Neoplasms; Adrenocortical Adenoma; Aldosterone; Amino Acid Sequence; Calcium Channels, L-Type; Cell Line; Child; Child, Preschool; Female; Germ-Line Mutation; Humans; Hyperaldosteronism; Male; Molecular Sequence Data; Mutation; Pedigree; Protein Conformation; Sequence Alignment

TM4SF20 ancestral deletion and susceptibility to a pediatric disorder of early language delay and cerebral white matter hyperintensities. - Wiszniewski, Wojciech; Hunter, Jill V; Hanchard, Neil A; Willer, Jason R; Shaw, Chad; Tian, Qi; Illner, Anna; Wang, Xueqing; Cheung, Sau W; Patel, Ankita; Campbell, Ian M; Gelowani, Violet; et al. (Am J Hum Genet, 2013)
White matter hyperintensities (WMHs) of the brain are important markers of aging and small-vessel disease. WMHs are rare in healthy children and, when observed, often occur with comorbid neuroinflammatory or vasculitic processes. Here, we describe a complex 4 kb deletion in 2q36.3 that segregates with early childhood communication disorders and WMH in 15 unrelated families predominantly from Southeast Asia. The premature brain aging phenotype with punctate and multifocal WMHs was observed in ~70% of young carrier parents who underwent brain MRI. The complex deletion removes the penultimate exon 3 of TM4SF20, a gene encoding a transmembrane protein of unknown function. Minigene analysis showed that the resultant net loss of an exon introduces a premature stop codon, which, in turn, leads to the generation of a stable protein that fails to target to the plasma membrane and accumulates in the cytoplasm. Finally, we report this deletion to be enriched in individuals of Vietnamese Kinh descent, with an allele frequency of about 1%, embedded in an ancestral haplotype. Our data point to a constellation of early language delay and WMH phenotypes, driven by a likely toxic mechanism of TM4SF20 truncation, and highlight the importance of understanding and managing population-specific low-frequency pathogenic alleles.
Keywords: Age of Onset; Aging, Premature; Asian Continental Ancestry Group; Base Sequence; Brain; Child; Child, Preschool; Chromosomes, Human, Pair 2; Exons; Female; Genetic Predisposition to Disease; Humans; Language Development Disorders; Leukoencephalopathies; Magnetic Resonance Imaging; Male; Molecular Sequence Data; Pedigree; Sequence Analysis, DNA; Sequence Deletion; Tetraspanins

Whole-exome sequencing identified a patient with TMCO1 defect syndrome and expands the phenotic spectrum. - Caglayan, A O; Per, H; Akgumus, G; Gumus, H; Baranoski, J; Canpolat, M; Calik, M; Yikilmaz, A; Bilguvar, K; Kumandas, S; Gunel, M (Clin Genet, 2013)
Keywords: Abnormalities, Multiple; Base Sequence; Child; Consanguinity; Exome; Humans; Male; Membrane Proteins; Pedigree; Phenotype; Sequence Analysis, DNA; Syndrome

Whole-genome analysis reveals that mutations in inositol polyphosphate phosphatase-like 1 cause opsismodysplasia. - Below, Jennifer E; Earl, Dawn L; Shively, Kathryn M; McMillin, Margaret J; Smith, Joshua D; Turner, Emily H; Stephan, Mark J; Al-Gazali, Lihadh I; Hertecant, Jozef L; Chitayat, David; Unger, Sheila; Cohn, Daniel H; et al. (Am J Hum Genet, 2013)
Opsismodysplasia is a rare, autosomal-recessive skeletal dysplasia characterized by short stature, characteristic facial features, and in some cases severe renal phosphate wasting. We used linkage analysis and whole-genome sequencing of a consanguineous trio to discover that mutations in inositol polyphosphate phosphatase-like 1 (INPPL1) cause opsismodysplasia with or without renal phosphate wasting. Evaluation of 12 families with opsismodysplasia revealed that INPPL1 mutations explain ~60% of cases overall, including both of the families in our cohort with more than one affected child and 50% of the simplex cases.
Keywords: Child; Child, Preschool; Female; Genome, Human; Humans; Infant; Infant, Newborn; Male; Mutation; Osteochondrodysplasias; Phosphatidylinositol-3,4,5-Trisphosphate 5-Phosphatases; Phosphoric Monoester Hydrolases

Digenic inheritance of an SMCHD1 mutation and an FSHD-permissive D4Z4 allele causes facioscapulohumeral muscular dystrophy type 2. - Lemmers, Richard J L F; Tawil, Rabi; Petek, Lisa M; Balog, Judit; Block, Gregory J; Santen, Gijs W E; Amell, Amanda M; van der Vliet, Patrick J; Almomani, Rowida; Straasheijm, Kirsten R; Krom, Yvonne D; Klooster, Rinse; et al. (Nat Genet, 2012)
Facioscapulohumeral dystrophy (FSHD) is characterized by chromatin relaxation of the D4Z4 macrosatellite array on chromosome 4 and expression of the D4Z4-encoded DUX4 gene in skeletal muscle. The more common form, autosomal dominant FSHD1, is caused by contraction of the D4Z4 array, whereas the genetic determinants and inheritance of D4Z4 array contraction-independent FSHD2 are unclear. Here, we show that mutations in SMCHD1 (encoding structural maintenance of chromosomes flexible hinge domain containing 1) on chromosome 18 reduce SMCHD1 protein levels and segregate with genome-wide D4Z4 CpG hypomethylation in human kindreds. FSHD2 occurs in individuals who inherited both the SMCHD1 mutation and a normal-sized D4Z4 array on a chromosome 4 haplotype permissive for DUX4 expression. Reducing SMCHD1 levels in skeletal muscle results in D4Z4 contraction-independent DUX4 expression. Our study identifies SMCHD1 as an epigenetic modifier of the D4Z4 metastable epiallele and as a causal genetic determinant of FSHD2 and possibly other human diseases subject to epigenetic regulation.
Keywords: Adult; Aged; Chromosomal Proteins, Non-Histone; Chromosomes, Human, Pair 18; CpG Islands; DNA Methylation; Epigenesis, Genetic; Female; Haplotypes; Heredity; Homeodomain Proteins; Humans; Male; Middle Aged; Muscular Dystrophy, Facioscapulohumeral; Mutation

Haploinsufficiency of SF3B4, a component of the pre-mRNA spliceosomal complex, causes Nager syndrome. - Bernier, Francois P; Caluseriu, Oana; Ng, Sarah; Schwartzentruber, Jeremy; Buckingham, Kati J; Innes, A Micheil; Jabs, Ethylin Wang; Innis, Jeffrey W; Schuette, Jane L; Gorski, Jerome L; Byers, Peter H; Andelfinger, Gregor; et al. (Am J Hum Genet, 2012)
Nager syndrome, first described more than 60 years ago, is the archetype of a class of disorders called the acrofacial dysostoses, which are characterized by craniofacial and limb malformations. Despite intensive efforts, no gene for Nager syndrome has yet been identified. In an international collaboration, FORGE Canada and the National Institutes of Health Centers for Mendelian Genomics used exome sequencing as a discovery tool and found that mutations in SF3B4, a component of the U2 pre-mRNA spliceosomal complex, cause Nager syndrome. After Sanger sequencing of SF3B4 in a validation cohort, 20 of 35 (57%) families affected by Nager syndrome had 1 of 18 different mutations, nearly all of which were frameshifts. These results suggest that most cases of Nager syndrome are caused by haploinsufficiency of SF3B4. Our findings add Nager syndrome to a growing list of disorders caused by mutations in genes that encode major components of the spliceosome and also highlight the synergistic potential of international collaboration when exome sequencing is applied in the search for genes responsible for rare Mendelian phenotypes.
Keywords: Adult; Child; Child, Preschool; Cohort Studies; Exome; Female; Haploinsufficiency; Humans; Limb Deformities, Congenital; Male; Mandibulofacial Dysostosis; Mutation; Reproducibility of Results; RNA Precursors; RNA Splicing Factors; RNA-Binding Proteins; Spliceosomes; Young Adult

Loss-of-function mutations in TGFB2 cause a syndromic presentation of thoracic aortic aneurysm. - Lindsay, Mark E; Schepers, Dorien; Bolar, Nikhita Ajit; Doyle, Jefferson J; Gallo, Elena; Fert-Bober, Justyna; Kempers, Marlies J E; Fishman, Elliot K; Chen, Yichun; Myers, Loretha; Bjeda, Djahita; Oswald, Gretchen; et al. (Nat Genet, 2012)
Loeys-Dietz syndrome (LDS) associates with a tissue signature for high transforming growth factor (TGF)-β signaling but is often caused by heterozygous mutations in genes encoding positive effectors of TGF-β signaling, including either subunit of the TGF-β receptor or SMAD3, thereby engendering controversy regarding the mechanism of disease. Here, we report heterozygous mutations or deletions in the gene encoding the TGF-β2 ligand for a phenotype within the LDS spectrum and show upregulation of TGF-β signaling in aortic tissue from affected individuals. Furthermore, haploinsufficient Tgfb2(+/-) mice have aortic root aneurysm and biochemical evidence of increased canonical and noncanonical TGF-β signaling. Mice that harbor both a mutant Marfan syndrome (MFS) allele (Fbn1(C1039G/+)) and Tgfb2 haploinsufficiency show increased TGF-β signaling and phenotypic worsening in association with normalization of TGF-β2 expression and high expression of TGF-β1. Taken together, these data support the hypothesis that compensatory autocrine and/or paracrine events contribute to the pathogenesis of TGF-β-mediated vasculopathies.
Keywords: Animals; Aortic Aneurysm, Thoracic; Disease Models, Animal; Female; Fibrillin-1; Fibrillins; Haploinsufficiency; Humans; Loeys-Dietz Syndrome; Male; Marfan Syndrome; Mice; Mice, Knockout; Mice, Mutant Strains; Microfilament Proteins; Mutation; Pedigree; Phenotype; Signal Transduction; Syndrome; Transforming Growth Factor beta2

Phenotype diversity in type 1 Gaucher disease: discovering the genetic basis of Gaucher disease/hematologic malignancy phenotype by individual genome analysis. - Lo, Sarah M; Choi, Murim; Liu, Jun; Jain, Dhanpat; Boot, Rolf G; Kallemeijn, Wouter W; Aerts, Johannes M F G; Pashankar, Farzana; Kupfer, Gary M; Mane, Shrikant; Lifton, Richard P; Mistry, Pramod K (Blood, 2012)
Gaucher disease (GD), an inherited macrophage glycosphingolipidosis, manifests with an extraordinary variety of phenotypes that show imperfect correlation with mutations in the GBA gene. In addition to the classic manifestations, patients suffer from increased susceptibility to hematologic and nonhematologic malignancies. The mechanism(s) underlying malignancy in GD is not known, but is postulated to be secondary to macrophage dysfunction and immune dysregulation arising from lysosomal accumulation of glucocerebroside. However, there is weak correlation between GD/cancer phenotype and the systemic burden of glucocerebroside-laden macrophages. Therefore, we hypothesized that genetic modifier(s) may underlie the GD/cancer phenotype. In the present study, the genetic basis of GD/T-cell acute lymphoblastic lymphoma in 2 affected siblings was deciphered through genomic analysis. GBA gene sequencing revealed homozygosity for a novel mutation, D137N. Whole-exome capture and massively parallel sequencing combined with homozygosity mapping identified a homozygous novel mutation in the MSH6 gene that leads to constitutional mismatch repair deficiency syndrome and increased cancer risk. Enzyme studies demonstrated that the D137N mutation in GBA is a pathogenic mutation, and immunohistochemistry confirmed the absence of the MSH6 protein. Therefore, precise phenotype annotation followed by individual genome analysis has the potential to identify genetic modifiers of GD, facilitate personalized management, and provide novel insights into disease pathophysiology.
Keywords: Adult; beta-Glucosidase; Child; Child, Preschool; Female; Gaucher Disease; Genome, Human; Hematologic Neoplasms; Humans; Individuality; Male; Pedigree; Phenotype; Sequence Analysis, DNA; Siblings